Are coffee silverskin extracts safe for topical use? An in vitro and in vivo approach - Rodrigues, F.; Pereira, C.; Pimentel, F. B.; Alves, R. C.; Ferreira, M.; Sarmento, B.; Helena Amaral, M.; Oliveira, M. Beatriz P. P. (Industrial Crops and Products, 2015)

Modulation of the inflammatory response to chitosan through M2 macrophage polarization using pro-resolution mediators - Vasconcelos, Daniela P.; Costa, Madalena; Amaral, Isabel F.; Barbosa, Mario A.; Aguas, Artur P.; Barbosa, Judite N. (Biomaterials, 2015)

The role of the surface on microglia function: implications for central nervous system tissue engineering - Pires, Liliana R.; Rocha, Daniela N.; Ambrosio, Luigi; Pego, Ana Paula (Journal of the Royal Society, Interface / the Royal Society, 2015)

Safety and toxicity concerns of orally delivered nanoparticles as drug carriers - Araujo, Francisca; Shrestha, Neha; Granja, Pedro L.; Hirvonen, Jouni; Santos, Helder A.; Sarmento, Bruno (Expert opinion on drug metabolism & toxicology, 2015)

Adsorbed fibrinogen enhances production of bone- and angiogenic-related factors by monocytes/macrophages - Maciel, J.; Oliveira, M.I.; Colton, E.; McNally, A.K.; Oliveira, C.; Anderson, J.M.; Barbosa, M.A. (Tissue Engineering - Part A, 2014)
Macrophages are phagocytic cells with great importance in guiding multiple stages of inflammation and tissue repair. By producing a large number of biologically active molecules, they can affect the behavior of other cells and events, such as the foreign body response and angiogenesis. Since protein adsorption to biomaterials is crucial for the inflammatory process, we addressed the ability of the pro-inflammatory molecule fibrinogen (Fg) to modulate macrophage behavior toward tissue repair/regeneration. For this purpose, we used chitosan (Ch) as a substrate for Fg adsorption. Freshly isolated human monocytes were seeded on Ch substrates alone or previously adsorbed with Fg, and allowed to differentiate into macrophages for 10 days. Cell adhesion and morphology, formation of foreign body giant cells (FBGC), and secretion of a total of 80 cytokines and growth factors were evaluated. Both substrates showed similar numbers of adherent macrophages along differentiation as compared with RGD-coated surfaces, which were used as positive controls. Fg did not potentiate FBGC formation. In addition, actin cytoskeleton staining revealed the presence of punctuate F-actin with more elongated and interconnecting cells on Ch substrates. Antibody array screening and quantification of inflammation- and wound-healing-related factors indicated an overall reduction in Ch-based substrates versus RGD-coated surfaces. At late times, most inflammatory agents were down-regulated in the presence of Fg, in contrast to growth factor production, which was stimulated by Fg. Importantly, on Ch+Fg substrates, fully differentiated macrophages produced significant amounts of macrophage inflammatory protein-1delta (MIP-1δ), platelet-derived growth factor-BB, bone morphogenetic protein (BMP)-5, and BMP-7 compared with Ch alone. In addition, other important factors involved in bone homeostasis and wound healing, such as growth hormone, transforming growth factor-β3, and insulin-like growth factor-binding proteins, as well as several angiogenic mediators, including endocrine gland-derived vascular endothelial factor, fibroblast growth factor-7, and placental growth factor, were significantly promoted by Fg. This work provides a new perspective on the inflammatory response in the context of bone repair/regeneration mediated by a pro-inflammatory protein (Fg) adsorbed onto a biomaterial (Ch) that does not otherwise exhibit osteogenic properties. © Copyright 2014, Mary Ann Liebert, Inc.
Cited By (since 1996):1Export Date: 21 November 2014

Age-period-cohort effects in the incidence of hip fractures: Political and economic events are coincident with changes in risk - Alves, S.M.; Castiglione, D.; Oliveira, C.M.; de Sousa, B.; Pina, M.F. (Osteoporosis International, 2014)
Summary: An age-period cohort model was fitted to analyse time effects on hip fracture incidence rates by sex (Portugal, 2000-2008). Rates increased exponentially with age (age effect). Incidence rates decreased after 2004 for women and were random for men (period effect). New but comprehensive fluctuations in risk were coincident with major political/economic changes (cohort effect). Introduction: Healthcare improvements have allowed prevention but have also increased life expectancy, resulting in more people being at risk. Our aim was to analyse the separate effects of age, period and cohort on incidence rates by sex in Portugal, 2000-2008. Methods: From the National Hospital Discharge Register, we selected admissions (aged ≥49 years) with hip fractures (ICD9-CM, codes 820.x) caused by low/moderate trauma (falls from standing height or less), readmissions and bone cancer cases. We calculated person-years at risk using population data from Statistics Portugal. To identify period and cohort effects for all ages, we used an age-period-cohort model (1-year intervals) followed by generalised additive models with a negative binomial distribution of the observed incidence rates of hip fractures. Results: There were 77,083 hospital admissions (77.4% women). Incidence rates increased exponentially with age for both sexes (age effect). Incidence rates fell after 2004 for women and were random for men (period effect). There was a general cohort effect similar in both sexes; risk of hip fracture altered from an increasing trend for those born before 1930 to a decreasing trend following that year. Risk alterations (not statistically significant) coincident with major political and economic change in the history of Portugal were observed around birth cohorts 1920 (stable-increasing), 1940 (decreasing-increasing) and 1950 (increasing-decreasing only among women). Conclusions: Hip fracture risk was higher for those born during major economically/politically unstable periods. Although bone quality reflects lifetime exposure, conditions at birthmay determine future risk for hip fractures. © International Osteoporosis Foundation and National Osteoporosis Foundation 2013.
Cited By (since 1996):1Export Date: 21 November 2014
Keywords: Age-period-cohort; Hip fractures; Osteoporosis; Population-based study; Time trend

Antihyperglycemic Potential of Incretins Orally Delivered via Nano and Microsystems and Subsequent Glucoregulatory Effects - Araujo, Francisca; Shrestha, Neha; Granja, Pedro L.; Hirvonen, Jouni; Santos, Helder A.; Sarmento, Bruno (Current Pharmaceutical Biotechnology, 2014)

Biodistribution and pharmacokinetics of Dapivirine-loaded nanoparticles after vaginal delivery in mice - Das Neves, J.; Araújo, F.; Andrade, F.; Amiji, M.; Bahia, M.F.; Sarmento, B. (Pharmaceutical Research, 2014)
Purpose: To assess the potential of polymeric nanoparticles (NPs) to affect the genital distribution and local and systemic pharmacokinetics (PK) of the anti-HIV microbicide drug candidate dapivirine after vaginal delivery. Methods: Dapivirine-loaded, poly(ethylene oxide)-coated poly(epsilon-caprolactone) (PEO-PCL) NPs were prepared by a nanoprecipitation method. Genital distribution of NPs and their ability to modify the PK of dapivirine up to 24 h was assessed after vaginal instillation in a female mouse model. Also, the safety of NPs upon daily administration for 14 days was assessed by histological analysis and chemokine/cytokine content in vaginal lavages. Results: PEO-PCL NPs (180-200 nm) were rapidly eliminated after administration but able to distribute throughout the vagina and lower uterus, and capable of tackling mucus and penetrate the epithelial lining. Nanocarriers modified the PK of dapivirine, with higher drug levels being recovered from vaginal lavages and vaginal/lower uterine tissues as compared to a drug suspension. Systemic drug exposure was reduced when NPs were used. Also, NPs were shown safe upon administration for 14 days. Conclusions: Dapivirine-loaded PEO-PCL NPs were able to provide likely favorable genital drug levels, thus attesting the potential value of using this vaginal drug delivery nanosystem in the context of HIV prophylaxis. © 2014 Springer Science+Business Media New York.
Cited By (since 1996):2Export Date: 21 November 2014
Keywords: HIV/AIDS; microbicides; poly(ε-caprolactone); pre-exposure prophylaxis; vaginal drug delivery

Chitosan-modified porous silicon microparticles for enhanced permeability of insulin across intestinal cell monolayers - Shrestha, N.; Shahbazi, M.-A.; Araújo, F.; Zhang, H.; Mäkilä, E.M.; Kauppila, J.; Sarmento, B.; Salonen, J.J.; Hirvonen, J.T.; Santos, H.A. (Biomaterials, 2014)
Porous silicon (PSi) based particulate systems are emerging as an important drug delivery system due to its advantageous properties such as biocompatibility, biodegradability and ability to tailor the particles' physicochemical properties. Here, annealed thermally hydrocarbonized PSi (AnnTHCPSi) and undecylenic acid modified AnnTHCPSi (AnnUnTHCPSi) microparticles were developed as a PSi-based platform for oral delivery of insulin. Chitosan (CS) was used to modify the AnnUnTHCPSi microparticles to enhance the intestinal permeation of insulin. Surface modification with CS led to significant increase in the interaction of PSi microparticles with Caco-2/HT-29 cell co-culture monolayers. Compared to pure insulin, the CS-conjugated microparticles significantly improved the permeation of insulin across the Caco-2/HT-29 cell monolayers, with ca. 20-fold increase in the amount of insulin permeated and ca. 7-fold increase in the apparent permeability (Papp) value. Moreover, among all the investigated particles, the CS-conjugated microparticles also showed the highest amount of insulin associated with the mucus layer and the intestinal Caco-2 cells and mucus secreting HT-29 cells. Our results demonstrate that CS-conjugated AnnUnTHCPSi microparticles can efficiently enhance the insulin absorption across intestinal cells, and thus, they are promising microsystems for the oral delivery of proteins and peptides across the intestinal cell membrane. © 2014 Elsevier Ltd.
Cited By (since 1996):1Export Date: 21 November 2014
Keywords: Cell monolayers; chitosan; Diabetes; Insulin; Microparticles; Porous silicon

Complexity-loss in fetal heart rate dynamics during labor as a potential biomarker of acidemia - Costa, Madalena D.; Schnettler, William T.; Amorim-Costa, Celia; Bernardes, Joao; Costa, Antonia; Goldberger, Ary L.; Ayres-de-Campos, Diogo (Early Human Development, 2014)

A critical appraisal of the evidence for using cardiotocography plus ECG ST interval analysis for fetal surveillance in labor. Part I: the randomized controlled trials - Olofsson, Per; Ayres-de-Campos, Diogo; Kessler, Joerg; Tendal, Britta; Yli, Branka M.; Devoe, Lawrence (Acta Obstetricia Et Gynecologica Scandinavica, 2014)
Si

Development and evaluation of an algorithm for computer analysis of maternal heart rate during labor - Pinto, P.; Bernardes, J.; Costa-Santos, C.; Amorim-Costa, C.; Silva, M.; Ayres-de-Campos, D. (Computers in Biology and Medicine, 2014)
Background: Maternal heart rate (MHR) recordings are morphologically similar and sometimes coincident with fetal heart rate (FHR) recordings and may be useful for maternal-fetal monitoring if appropriately interpreted. However, similarly to FHR, visual interpretation of MHR features may be poorly reproducible. Methods: A computer algorithm for on-line MHR analysis was developed based on a previously existing version for FHR analysis. Inter-observer and computer-observer agreement and reliability were assessed in 40 one-hour recordings obtained from 20 women during the last 2. h of labor. Agreement and reliability were evaluated for the detection of basal MHR, long-term variability (LTV), accelerations and decelerations, using proportions of agreement (PA) and Kappa statistic (K), with 95% confidence intervals (95% CI). Changes in MHR characteristics between the first and the second hour of the tracings were also evaluated. Results: There was a statistically significant inter-observer and computer-observer agreement and reliability in estimation of basal MHR, accelerations, decelerations and LTV, with PA values ranging from 0.72 (95% CI: 0.62-0.79) to 1.00 (95% CI: 0.99-1.00), and K values ranging from 0.44 (95% CI: 0.28-0.60) to 0.89 (95% CI: 0.82-0.96). Moreover, basal MHR, number of accelerations and LTV were significantly higher in the last hour of labor, when compared to the initial hour. Discussion: The developed algorithm for on-line computer analysis of MHR recordings provided good to excellent computer-observer agreement and reliability. Moreover, it allowed an objective detection of MHR changes associated with labor progression, providing more information about the interpretation of maternal-fetal monitoring during labor. © 2014 Elsevier Ltd.
Keywords: Agreement; Cardiotocography; computer analysis; Fetal heart rate; Maternal heart rate; reliability

Differences between external and internal fetal heart rate monitoring during the second stage of labor: a prospective observational study - Nunes, Ines; Ayres-de-Campos, Diogo; Costa-Santos, Cristina; Bernardes, Joao (Journal of Perinatal Medicine, 2014)

Dysregulation of T cell receptor N-glycosylation: A molecular mechanism involved in ulcerative colitis - Dias, A.M.; Dourado, J.; Lago, P.; Cabral, J.; Marcos-Pinto, R.; Salgueiro, P.; Almeida, C.R.; Carvalho, S.; Fonseca, S.; Lima, M.; Vilanova, M.; Dinis-Ribeiro, M.; et al. (Human Molecular Genetics, 2014)
The incidence of inflammatory bowel disease is increasing worldwide and the underlying molecular mechanisms are far from being fully elucidated. Herein, we evaluated the role of N-glycosylation dysregulation in T cells as a key mechanism in the ulcerative colitis (UC) pathogenesis. The evaluation of the branched N-glycosylation levelsandprofile of intestinalTcell receptor (TCR)wereassessedin colonic biopsies fromUCpatientsand healthy controls. Expression alterations of the glycosyltransferase gene MGAT5 were also evaluated. We demonstrated thatUCpatients exhibit a dysregulation ofTCRbranchedN-glycosylationonlamina propriaTlymphocytes. Patients with severe UC showed the most pronounced defect on N-glycan branching in T cells. Moreover, UC patients showed a significant reduction of MGAT5 gene transcription in T lymphocytes. In this study, we disclose for the first time that a deficiency in branched N-glycosylation on TCR due to a reduced MGAT5 gene expression is a new molecular mechanism underlying UC pathogenesis, being a potential novel biomarker with promising clinical and therapeutic applications. © The Author 2013. Published by Oxford University Press. All rights reserved.

The effect of hyaluronan-based delivery of stromal cell-derived factor-1 on the recruitment of MSCs in degenerating intervertebral discs - Pereira, C.L.; Gonçalves, R.M.; Peroglio, M.; Pattappa, G.; D'Este, M.; Eglin, D.; Barbosa, M.A.; Alini, M.; Grad, S. (Biomaterials, 2014)
Intervertebral disc (IVD) degeneration is the leading cause of low back pain and disability in the active population. Transplantation of mesenchymal stem cells (MSCs) in a hydrogel carrier can induce regenerative effects in degenerated IVDs. Moreover, it was found that degenerative discs release chemoattractants effective in MSC recruitment. Based on these findings, we hypothesized that an injectable hydrogel that can enhance the number of migrated MSCs in the IVD and provide a suitable matrix for their survival and differentiation would be ideal. The purpose of this study was to evaluate the potential of a thermoreversible hyaluronan-poly(N-isopropylacrylamide) (HAP) hydrogel as chemoattractant delivery system to recruit human MSCs in degenerative IVDs. The results demonstrate that HAP hydrogels containing stromal cell derived factor-1 (SDF-1) significantly increased the number of MSCs migrating into nucleotomized discs compared with discs treated with only HAP or SDF-1 in solution. HAP hydrogels releasing SDF-1 enhanced both the number of recruited cells and their migration distance in the IVD tissue. Furthermore, this phenomenon was dependent on MSC donor age. In conclusion, HAP SDF-1 is effective for the recruitment of stem cells in the IVD, thus opening new possibilities for the development of regenerative therapies based on endogenous cell migration. © 2014 Elsevier Ltd.
Keywords: Intervertebral disc; Mesenchymal Stem Cells; Recruitment; Stromal cell derived factor-1; Thermoreversible hyaluronan hydrogel

Endoplasmic Reticulum Degradation-Enhancing alpha-Mannosidase-like Protein 1 Targets Misfolded HLA-B27 Dimers for Endoplasmic Reticulum-Associated Degradation - Guiliano, David B.; Fussell, Helen; Lenart, Izabela; Tsao, Edward; Nesbeth, Darren; Fletcher, Adam J.; Campbell, Elaine C.; Yousaf, Nasim; Williams, Sarah; Santos, Susana; Cameron, Amy; Towers, Greg J.; et al. (Arthritis & Rheumatology, 2014)

External uterine contractions signal analysis in relation to labor progression and dystocia - Gonçalves, H.; Pinto, P.; Ayres-de-Campos, D.; Bernardes, J. (IFMBE Proceedings, 2014)
Labor dystocia is a major cause of operative delivery, which is associated with increased risks for both mother and fetus. We assessed linear and non-linear dynamics of external uterine contraction signals, in relation to labor progression and dystocia. Linear time domain, spectral and entropy methods were used to analyze external uterine contraction recordings obtained during the last two hours of labor, in 28 cases with normal and 27 cases with operative deliveries (forceps, vacuum or caesarean). Progression of labor was associated with a statistically significant increase in most linear time domain and spectral indices, both in normal and operative deliveries, whereas most entropy indices increased in normal deliveries, but did not change in operative deliveries. On the other hand, when compared with normal births, operative deliveries were associated with significantly increased entropy indices before the last hour of labor and significantly decreased (a probably associated) sympatho-vagal balance in the last hour of labor. Linear and non-linear analysis of external uterine contraction recordings may provide useful physiopathological and clinical information on the progression of labor and the diagnosis of dystocia. © Springer International Publishing Switzerland 2014.
Keywords: Cardiotocography; Dystocia; entropy; External uterine contractions; Spectral analysis

Extracellular matrix stiffness and composition jointly regulate the induction of malignant phenotypes in mammary epithelium - Chaudhuri, Ovijit; Koshy, Sandeep T.; Branco da Cunha, Cristiana; Shin, Jae-Won; Verbeke, Catia S.; Allison, Kimberly H.; Mooney, David J. (Nature Materials, 2014)

Fetal behavioral dynamics in cephalic versus breech presentations - Gonçalves, H.; Ayres-de-Campos, D.; Bernardes, J. (Developmental Psychobiology, 2014)
Differences in fetal neurodevelopment can have important implications on future perceptual and learning capabilities. The aim of this study was to assess autonomic nervous system and complexity dynamics in fetal heart rate (FHR) tracings from 27 singleton fetuses in cephalic or breech presentations, matched for gestational age (37+3-40+4 weeks), weight, gender and outcome. Breeches exhibited significantly higher mean FHR and LF/(MF+HF) ratio, as well as lower entropy, denoting increased sympatho-vagal balance and decreased complexity, consistent with the occurrence of more active fetal behavioral states. These findings suggest that there are neurodevelopment differences between fetuses in cephalic and breech presentation.
Keywords: Breech presentation; Development; entropy; Fetal behavior; Heart rate; Spectral analysis

Fetal Behavioral Dynamics in Cephalic Versus Breech Presentations - Goncalves, Hernani; Ayres-de-Campos, Diogo; Bernardes, Joao (Developmental Psychobiology, 2014)

Fetal QRS detection and heart rate estimation: a wavelet-based approach - Almeida, Rute; Goncalves, Hernani; Bernardes, Joao; Rocha, Ana Paula (Physiological Measurement, 2014)

Field dimension and skill level constrain team tactical behaviours in small-sided and conditioned games in football - Silva, Pedro; Duarte, Ricardo; Sampaio, Jaime; Aguiar, Paulo; Davids, Keith; Araujo, Duarte; Garganta, Julio (Journal of Sports Sciences, 2014)
Si

Hippo pathway effectors control cardiac progenitor cell fate by acting as dynamic sensors of substrate mechanics and nanostructure - Mosqueira, D.; Pagliari, S.; Uto, K; Ebara, M; Romanazzo, S.; Escobedo-Lucea, C; Nakanishi, J; Taniguchi, A; Franzese, O; Di Nardo, P.; Goumans, MJ; Traversa, E; et al. (ACS Nano, 2014)
Stem cell responsiveness to extracellular matrix (ECM) composition and mechanical cues has been the subject of a number of investigations so far, yet the molecular mechanisms underlying stem cell mechano-biology still need full clarification. Here we demonstrate that the paralog proteins YAP and TAZ exert a crucial role in adult cardiac progenitor cell mechano-sensing and fate decision. Cardiac progenitors respond to dynamic modifications in substrate rigidity and nanopattern by promptly changing YAP/TAZ intracellular localization. We identify a novel activity of YAP and TAZ in the regulation of tubulogenesis in 3D environments and highlight a role for YAP/TAZ in cardiac progenitor proliferation and differentiation. Furthermore, we show that YAP/TAZ expression is triggered in the heart cells located at the infarct border zone. Our results suggest a fundamental role for the YAP/TAZ axis in the response of resident progenitor cells to the modifications in microenvironment nanostructure and mechanics, thereby contributing to the maintenance of myocardial homeostasis in the adult heart. These proteins are indicated as potential targets to control cardiac progenitor cell fate by materials design. © 2014 American Chemical Society.
Cited By (since 1996):4Export Date: 21 November 2014
Keywords: adult cardiac progenitor cell; cardiac differentiation; mechano- transduction; substrate nanotopography; YAP/TAZ

Human umbilical cord tissue-derived mesenchymal stromal cells attenuate remodeling after myocardial infarction by proangiogenic, antiapoptotic, and endogenous cell-activation mechanisms - Nascimento, D.S.; Mosqueira, D.; Sousa, L.M.; Teixeira, M.; Filipe, M.; Resende, TP; Araújo, A.F.; Valente, M.; Almeida, J.; Martins, J.P.; Santos, J.M.; Bárcia, R.N.; et al. (Stem Cell Research and Therapy, 2014)
Introduction. Among the plethora of cells under investigation to restore a functional myocardium, mesenchymal stromal cells (MSCs) have been granted considerable interest. However, whereas the beneficial effects of bone marrow MSCs (BM-MSCs) in the context of the diseased heart are widely reported, data are still scarce on MSCs from the umbilical cord matrix (UCM-MSCs). Herein we report on the effect of UCM-MSC transplantation to the infarcted murine heart, seconded by the dissection of the molecular mechanisms at play. Methods. Human umbilical cord tissue-derived MSCs (UCX®), obtained by using a proprietary technology developed by ECBio, were delivered via intramyocardial injection to C57BL/6 females subjected to permanent ligation of the left descending coronary artery. Moreover, medium produced by cultured UCX® preconditioned under normoxia (CM) or hypoxia (CMH) was collected for subsequent in vitro assays. Results: Evaluation of the effects upon intramyocardial transplantation shows that UCX® preserved cardiac function and attenuated cardiac remodeling subsequent to myocardial infarction (MI). UCX® further led to increased capillary density and decreased apoptosis in the injured tissue. In vitro, UCX®-conditioned medium displayed (a) proangiogenic activity by promoting the formation of capillary-like structures by human umbilical vein endothelial cells (HUVECs), and (b) antiapoptotic activity in HL-1 cardiomyocytes subjected to hypoxia. Moreover, in adult murine cardiac Sca- 1§ssup§+§esup§ progenitor cells (CPCs), conditioned medium enhanced mitogenic activity while activating a gene program characteristic of cardiomyogenic differentiation. Conclusions: UCX® preserve cardiac function after intramyocardial transplantation in a MI murine model. The cardioprotective effects of UCX® were attributed to paracrine mechanisms that appear to enhance angiogenesis, limit the extent of the apoptosis, augment proliferation, and activate a pool of resident CPCs. Overall, these results suggest that UCX® should be considered an alternative cell source when designing new therapeutic approaches to treat MI. © 2014 Nascimento et al.; licensee BioMed Central Ltd.
Cited By (since 1996):2Export Date: 21 November 2014

Impact of 3-D printed PLA- and chitosan-based scaffolds on human monocyte/macrophage responses: Unraveling the effect of 3-D structures on inflammation - Almeida, C.R.; Serra, T.; Oliveira, M.I.; Planell, J.A.; Barbosa, M.A.; Navarro, M. (Acta Biomaterialia, 2014)
Recent studies have pointed towards a decisive role of inflammation in triggering tissue repair and regeneration, while at the same time it is accepted that an exacerbated inflammatory response may lead to rejection of an implant. Within this context, understanding and having the capacity to regulate the inflammatory response elicited by 3-D scaffolds aimed for tissue regeneration is crucial. This work reports on the analysis of the cytokine profile of human monocytes/macrophages in contact with biodegradable 3-D scaffolds with different surface properties, architecture and controlled pore geometry, fabricated by 3-D printing technology. Fabrication processes were optimized to create four different 3-D platforms based on polylactic acid (PLA), PLA/calcium phosphate glass or chitosan. Cytokine secretion and cell morphology of human peripheral blood monocytes allowed to differentiate on the different matrices were analyzed. While all scaffolds supported monocyte/macrophage adhesion and stimulated cytokine production, striking differences between PLA-based and chitosan scaffolds were found, with chitosan eliciting increased secretion of tumor necrosis factor (TNF)-α, while PLA-based scaffolds induced higher production of interleukin (IL)-6, IL-12/23 and IL-10. Even though the material itself induced the biggest differences, the scaffold geometry also impacted on TNF-α and IL-12/23 production, with chitosan scaffolds having larger pores and wider angles leading to a higher secretion of these pro-inflammatory cytokines. These findings strengthen the appropriateness of these 3-D platforms to study modulation of macrophage responses by specific parameters (chemistry, topography, scaffold architecture). © 2013 Acta Materialia Inc.
Cited By (since 1996):2Export Date: 21 November 2014
Keywords: 3-D scaffolds; Human macrophages; Inflammation; Rapid prototyping; Tissue engineering

The impact of nanoparticles on the mucosal translocation and transport of GLP-1 across the intestinal epithelium - Araújo, F.; Shrestha, N.; Shahbazi, M.-A.; Fonte, P.; Mäkilä, E.M.; Salonen, J.J.; Hirvonen, J.T.; Granja, P.L.; Santos, H.A.; Sarmento, B. (Biomaterials, 2014)
Glucagon like peptide-1 (GLP-1) is an incretin hormone that is in the pipeline for type 2 diabetes mellitus (T2DM) therapy. However, oral administration of GLP-1 is hindered by the harsh conditions of the gastrointestinal tract and poor bioavailability. In this study, three nanosystems composed by three different biomaterials (poly(lactide-co-glycolide) polymer (PLGA), Witepsol E85 lipid (solid lipid nanoparticles, SLN) and porous silicon (PSi) were developed and loaded with GLP-1 to study their permeability invitro. All the nanoparticles presented a size of approximately 200nm. The nanoparticles' interaction with the mucus and the intestinal cells were enhanced after coating with chitosan (CS). PSi nanosystems presented the best association efficiency (AE) and loading degree (LD), even though a high AE was also observed for PLGA nanoparticles and SLN. Among all the nanosystems, PLGA and PSi were the only nanoparticles able to sustain the release of GLP-1 in biological fluids when coated with CS. This characteristic was also maintained when the nanosystems were in contact with the intestinal Caco-2 and HT29-MTX cell monolayers. The CS-coated PSi nanoparticles showed the highest GLP-1 permeation across the intestinal invitro models. In conclusion, PLGA+CS and PSi+CS are promising nanocarriers for the oral delivery of GLP-1. © 2014 Elsevier Ltd.
Keywords: chitosan; Diabetes; Glucagon like peptide-1; nanoparticles; Oral delivery systems; Triple co-culture

Impact of the introduction of fetal central monitoring on hospital expenses with cardiotocographic paper - Amorim-Costa, C.; Ayres-de-Campos, D.; Costa-Santos, C.; Bernardes, J. (Journal of Obstetrics and Gynaecology, 2014)

In vitro intestinal absorption of amino acid mixtures extracted from codfish (Gadus morhua L.) salting wastewater - Ferraro, V.; Ferreira Jorge, R.; Cruz, I.B.; Antunes, F.; Sarmento, B.; Castro, P.M.L.; Pintado, M.E. (International Journal of Food Science and Technology, 2014)
Summary: This study reports on the intestinal permeability of salt-containing mixtures of amino acids extracted from codfish salting wastewater. Permeability was evaluated in vitro using the Caco-2 cell line model; cell integrity during exposure to mixtures of amino acids was estimated by measuring the transepithelial electrical resistance (TEER). The effect of salt (NaCl) on the permeability and on the intestinal cell's integrity was also examined. Permeation rate (i.e. transport) was ≥95% for all amino acids except for creatine, for which it was 6%. Values for apparent permeability coefficients, Papp > 10-5 cm s-1, for mixture with isotonic concentration of NaCl suggest that amino acids are very likely to be absorbed in humans. Mixture with a hypertonic level of NaCl exerts a cytotoxic effect in intestinal cells resulting in a loss of epithelium integrity. Results show that isotonic mixture of amino acids extracted from codfish salting wastewater could be used in food, feed, cosmetic and pharmaceutical formulations. These applications could contribute to the fish industry sustainability. © 2013 Institute of Food Science and Technology.
Keywords: Absorption; Amino acids; Caco-2 cell; Codfish; Small intestine

Kinetochore motors drive congression of peripheral polar chromosomes by overcoming random arm-ejection forces - Barisic, Marin; Aguiar, Paulo; Geley, Stephan; Maiato, Helder (Nature Cell Biology, 2014)

Long-term effects of chronic cocaine exposure throughout adolescence on anxiety and stress responsivity in a Wistar rat model - Alves, C.J.; Magalhães, A.; Melo, P.; De Sousa, L.; Tavares, M.A.; Monteiro, P.R.R.; Summavielle, T. (Neuroscience, 2014)
Adolescents display increased vulnerability to engage in drug experimentation. This is often considered a risk factor for later drug abuse. In this scenario, the permanent effects of cocaine exposure during adolescence on anxiety levels and stress responsivity, which may result in behavioral phenotypes prone to addiction, are now starting to be unveiled. Thus, the purpose of the present study was to evaluate the long-lasting effects of chronic cocaine administration during adolescence, on anxiety-like behavior and on stress response. Adolescent male Wistar rats were daily administered 45-mg cocaine/kg of body weight in three equal intraperitoneal doses with 1-h interval, from postnatal day (PND) 35 to 50. The effects of cocaine administration on anxiety levels, assessed in the Elevated Plus Maze (EPM), and on social stress response, assessed in the resident-intruder paradigm (R/I), were evaluated 10. days after withdrawal, when rats were reaching the adulthood. The underlying dopaminergic activity, and the corticosterone and testosterone levels were determined. Our results showed that cocaine induced long-lasting alterations in the hypothalamus-pituitary-adrenals (HPA) axis function and in testosterone levels. Such alterations resulted in significant and enduring changes in behavioral responses to environmental challenges, such as the EPM and R/I, including the evaluation of potential threats that may lead to high-risk behavior and low-benefit choices. This was further supported by an altered dopaminergic function in the amygdala and hippocampus. The present findings provide new insights into how the use of cocaine during adolescent development may modulate emotional behavior later in life. Compromised ability to recognize and deal with potential threats is an important risk factor to perpetuate compulsive drug seeking and relapse susceptibility. © 2014 IBRO.
Keywords: Adolescence; anxiety; Cocaine; corticosterone; Dopaminergic system; Social stress

Mad2 checkpoint gene silencing using epidermal growth factor receptor-targeted chitosan nanoparticles in non-small cell lung cancer model - Nascimento, A.V.; Singh, A.; Bousbaa, H.; Ferreira, D.; Sarmento, B.; Amiji, M.M. (Molecular Pharmaceutics, 2014)
RNA interference has emerged as a powerful strategy in cancer therapy because it allows silencing of specific genes associated with tumor progression and resistance. Mad2 is an essential mitotic checkpoint component required for accurate chromosome segregation during mitosis, and its complete abolition leads to cell death. We have developed an epidermal growth factor receptor (EGFR)-targeted chitosan system for silencing the Mad2 gene as a strategy to efficiently induce cell death in EGFR overexpressing human A549 non-small cell lung cancer cells. Control and EGFR-targeted chitosan nanoparticles loaded with small interfering RNAs (siRNAs) against Mad2 were formulated and characterized for size, charge, morphology, and encapsulation efficiency. Qualitative and quantitative intracellular uptake studies by confocal imaging and flow cytometry, respectively, showed time-dependent enhanced and selective intracellular internalization of EGFR-targeted nanoparticles compared to nontargeted system. Targeted nanoparticles showed nearly complete depletion of Mad2 expression in A549 cells contrasting with the partial depletion in the nontargeted system. Accordingly, Mad2-silencing-induced apoptotic cell death was confirmed by cytotoxicity assay and flow cytometry. Our results demonstrate that EGFR-targeted chitosan loaded with Mad2 siRNAs is a potent delivery system for selective killing of cancer cells.
Keywords: chitosan nanoparticles; Epidermal growth factor receptor; Mad2 gene; non-small cell lung cancer; RNA interference; tumor targeting

Modified-chitosan/siRNA nanoparticles downregulate cellular CDX2 expression and cross the gastric mucus barrier - Sadio, A.; Gustafsson, J.K.; Pereira, B.; Gomes, C.P.; Hansson, G.C.; David, L.; Pêgo, A.P.; Almeida, R. (PLoS ONE, 2014)
Development of effective non-viral vectors is of crucial importance in the implementation of RNA interference in clinical routine. The localized delivery of siRNAs to the gastrointestinal mucosa is highly desired but faces specific problems such as the stability in gastric acidity conditions and the presence of the mucus barrier. CDX2 is a transcription factor critical for intestinal differentiation being involved in the initiation and maintenance of gastrointestinal diseases. Specifically, it is the trigger of gastric intestinal metaplasia which is a precursor lesion of gastric cancer. Its expression is also altered in colorectal cancer, where it may constitute a lineage-survival oncogene. Our main objective was to develop a nanoparticle-delivery system of siRNA targeting CDX2 using modified chitosan as a vector. CDX2 expression was assessed in gastric carcinoma cell lines and nanoparticles behaviour in gastrointestinal mucus was tested in mouse explants. We show that imidazolemodified chitosan and trimethylchitosan/siRNA nanoparticles are able to downregulate CDX2 expression and overpass the gastric mucus layer but not colonic mucus. This system might constitute a potential therapeutic approach to treat CDX2-dependent gastric lesions. © 2014 Sadio et al.

A PEX7-Centered Perspective on the Peroxisomal Targeting Signal Type 2-Mediated Protein Import Pathway - Rodrigues, Tony A.; Alencastre, Ines S.; Francisco, Tania; Brites, Pedro; Fransen, Marc; Grou, Claudia P.; Azevedo, Jorge E. (Molecular and Cellular Biology, 2014)

The predominance of M2-polarized macrophages in the stroma of low-hypoxic bladder tumors is associated with BCG immunotherapy failure - Lima, L.; Oliveira, D.; Tavares, A.; Amaro, T.; Cruz, R.; Oliveira, M.J.; Ferreira, J.A.; Santos, L. (Urologic Oncology: Seminars and Original Investigations, 2014)
Objective: Bacillus Calmette-Guérin (BCG) immunotherapy is the gold standard treatment for superficial bladder tumors with intermediate/high risk of recurrence or progression. However, approximately 30% of patients fail to respond to the treatment. Effective BCG therapy needs precise activation of the type 1 helper cells immune pathway. Tumor-associated macrophages (TAMs) often assume an immunoregulatory M2 phenotype and may directly interfere with the BCG-induced antitumor immune response. Thus, we aim to clarify the influence of TAMs, in particular of the M2 phenotype in stroma and tumor areas, in BCG treatment outcome. Patients and methods: The study included 99 patients with bladder cancer treated with BCG. Tumors resected before treatment were evaluated using immunohistochemistry for CD68 and CD163 antigens, which identify a lineage macrophage marker and a M2-polarized specific cell surface receptor, respectively. CD68+ and CD163+ macrophages were evaluated within the stroma and tumor areas, and high density of infiltrating cells spots were selected for counting. Hypoxia, an event known to modulate macrophage phenotype, was also assessed through hypoxia induced factor (HIF)-1α expression. Results: Patients in whom BCG failed had high stroma-predominant CD163+ macrophage counts (high stroma but low tumor CD163+ macrophages counts) when compared with the ones with a successful treatment (71% vs. 47%, P = 0.017). Furthermore, patients presenting this phenotype showed decreased recurrence-free survival (log rank, P = 0.008) and a clear 2-fold increased risk of BCG treatment failure was observed in univariate analysis (hazard ratio = 2.343; 95% CI: 1.197-4.587; P = 0.013). Even when adjusted for potential confounders, such as age and therapeutic scheme, multivariate analysis revealed 2.6-fold increased risk of recurrence (hazard ratio = 2.627; 95% CI: 1.340-5.150; P = 0.005). High stroma-predominant CD163+ macrophage counts were also associated with low expression of HIF-1α in tumor areas, whereas high counts of CD163+ in the tumor presented high expression of HIF-1α in tumor nests. Conclusions: TAMs evaluation using CD163 is a good indicator of BCG treatment failure. Moreover, elevated infiltration of CD163+ macrophages, predominantly in stroma areas but not in the tumor, may be a useful indicator of BCG treatment outcome, possibly owing to its immunosuppressive phenotype. © 2014 Elsevier Inc.
Keywords: BCG immunotherapy; Bladder cancer; CD163; CD68; Tumor-associated macrophages

Production, characterization and biocompatibility of marine collagen matrices from an alternative and sustainable source: The sea urchin Paracentrotus lividus - Di Benedetto, C.; Barbaglio, A.; Martinello, T.; Alongi, V.; Fassini, D.; Cullorà, E.; Patruno, M.; Bonasoro, F.; Barbosa, M.A.; Carnevali, M.D.C.; Sugni, M. (Marine Drugs, 2014)
Collagen has become a key-molecule in cell culture studies and in the tissue engineering field. Industrially, the principal sources of collagen are calf skin and bones which, however, could be associated to risks of serious disease transmission. In fact, collagen derived from alternative and riskless sources is required, and marine organisms are among the safest and recently exploited ones. Sea urchins possess a circular area of soft tissue surrounding the mouth, the peristomial membrane (PM), mainly composed by mammalian-like collagen. The PM of the edible sea urchin Paracentrotus lividus therefore represents a potential unexploited collagen source, easily obtainable as a food industry waste product. Our results demonstrate that it is possible to extract native collagen fibrils from the PM and produce suitable substrates for in vitro system. The obtained matrices appear as a homogeneous fibrillar network (mean fibril diameter 30-400 nm and < 2 μm) and display remarkable mechanical properties in term of stiffness (146 ± 48 MPa) and viscosity (60.98 ± 52.07 GPa·s). In vitro tests with horse pbMSC show a good biocompatibility in terms of overall cell growth. The obtained results indicate that the sea urchin P. lividus can be a valuable low-cost collagen source for mechanically resistant biomedical devices.
Keywords: Biocompatibility; Collagen matrix; Mesenchimal stromal cells; Native fibril; Sea urchin collagen; Tissue regeneration

Prolonged saltatory fetal heart rate pattern leading to newborn metabolic acidosis - Nunes, I.; Ayres-de-Campos, D.; Kwee, A.; Rosen, K. G. (Clinical and Experimental Obstetrics & Gynecology, 2014)

Resveratrol as a Natural Anti-Tumor Necrosis Factor-alpha Molecule: Implications to Dendritic Cells and Their Crosstalk with Mesenchymal Stromal Cells - Silva, Andreia M.; Oliveira, Marta I.; Sette, Laura; Almeida, Catarina R.; Oliveira, Maria J.; Barbosa, Mario A.; Santos, Susana G. (Plos One, 2014)

Sensory neurons and osteoblasts: Close partners in a microfluidic platform - Neto, E.; Alves, C.J.; Sousa, D.M.; Alencastre, I.S.; Lourenço, A.H.; Leitão, L.; Ryu, H.R.; Jeon, N.L.; Fernandes, R.; Aguiar, P.; Almeida, R.D.; Lamghari, M. (Integrative Biology (United Kingdom), 2014)
Innervation has proven to be critical in bone homeostasis/regeneration due to the effect of soluble factors, produced by nerve fibers, associated with changes in the activity of bone cells. Thus, in this study, we have established and characterized a coculture system comprising sensory neurons and osteoblasts to mimic the in vivo scenario where nerve fibers can be found in a bone microenvironment. Embryonic or adult primary dorsal root ganglion (DRG) and MC3T3-E1 osteoblastic cells were cocultured in compartmentalized microfluidic platforms and morphological and functional tests were performed. The time of adhesion and readout of axonal outgrowth were improved by the alignment of DRG with the axis of microgrooves, which showed to be a crucial step for the designed experiments. Cocultures of entire DRG from adult origin with osteoblasts were performed, showing extended DRG projections towards the axonal compartment, reaching osteoblastic cells. Immunocytochemistry showed that the neurites present within the osteoblastic compartment were immunoreactive to synapsin and calcitonin gene-related peptide suggesting the presence of specialized structures involved in this crosstalk. This evidence was further confirmed by electron microscopy where varicosities were detected as well as electron dense structures in neurite membranes. Aiming to mimic the properties of tissue extracellular matrices, MC3T3-E1 cells were seeded in the axonal side upon laminin, collagen or within 3D functionalized alginate matrices and axonal outgrowth was clearly observed. In order to analyze and quantify data with reproducible image analysis, a semi-automated algorithm was also developed. The collagen and laminin substrates displayed a higher amount of axons reaching the axonal side. Overall, the established method revealed to be a suitable tool to study the interaction between the peripheral nervous system and bone cells in different contexts mimicking the in vivo scenario. © 2014 the Partner Organisations 2014.
Cited By (since 1996):2Export Date: 21 November 2014

Stable phenotype and function of immortalized Lin-Sca-1 + cardiac progenitor cells in long-term culture: A step closer to standardization - Freire, AG; Nascimento, D.S.; Forte, G.; Valente, M.; Resende, TP; Pagliari, S.; Abreu, C; Carvalho, I; Nardo, P.D.; Pinto-Do-Ó, P. (Stem Cells and Development, 2014)
Putative cardiac progenitor cells (CPCs) have been identified in the myocardium and are regarded as promising candidates for cardiac cell-based therapies. Although two distinct populations of CPCs reached the clinical setting, more detailed studies are required to portray the optimal cell type and therapeutic setting to drive robust cell engraftment and cardiomyogenesis after injury. Owing to the scarcity of the CPCs and the need for reproducibility, the generation of faithful cellular models would facilitate this scrutiny. Here, we evaluate whether immortalized Lin-Sca-1+ CPCs (iCPC Sca-1) represent their native-cell counterpart, thereby constituting a robust in vitro model system for standardized investigation in the cardiac field. iCPCSca-1 were established in vitro as plastic adherent cells endowed with robust self-renewal capacity while preserving a stable phenotype in long-term culture. iCPCSca-1 differentiated into cardiomyocytic-, endothelial-, and smooth muscle-like cells when subjected to appropriate stimuli. The cell line consistently displayed features of Lin -Sca-1+ CPCs in vitro, as well as in vivo after intramyocardial delivery in the onset of myocardial infarction (MI). Transplanted iCPCSca-1 significantly attenuated the functional and anatomical alterations caused by MI while promoting neovascularization. iCPCSca-1 are further shown to engraft, establish functional connections, and differentiate in loco into cardiomyocyte- and vasculature-like cells. These data validate iCPCSca-1 as an in vitro model system for Lin-Sca-1+ progenitors and for systematic dissection of mechanisms underlying CPC subsets engraftment/differentiation in vivo. Moreover, iCPCSca-1 can be regarded as a ready-to-use CPCs source for pre-clinical bioengineering studies toward the development of novel strategies for restoration of the damaged myocardium. © Copyright 2014, Mary Ann Liebert, Inc. 2014.
Cited By (since 1996):2Export Date: 21 November 2014

Study of the isoflavone content of different extracts of Medicago spp. as potential active ingredient - Rodrigues, F.; Almeida, I.; Sarmento, B.; Amaral, M.H.; Oliveira, M.B.P.P. (Industrial Crops and Products, 2014)
This study focuses on the isoflavones composition of different extracts of Medicago species (M. minima, M. tornata, M. truncatula, M. rigidula, M. scutelata, M. segitalis and M. sativa), a leguminous crop used as animal feeding. There are some research studies on the isoflavones composition of Medicago sativa, but no comprehensive profile of isoflavones has been reported for these other six species. In this work, two glycosides (daidzin and genistin) and six aglycones (daidzein, glycitein, genistein, formononetin, prunetin and biochanin A) were determined by high performance liquid chromatography (HPLC/DAD) in three different extracts of these species: aqueous, hydroalcoholic and alcoholic. In all samples genistin, daidzein and genistein were the most abundant isoflavone compounds. The highest concentration of genistin was observed in the extracts of M. scutelata (5.2 and 9.6. mg/kg. db, respectively, for hydroalcoholic and alcoholic extract), in amounts 2-4.5-fold higher than the other samples evaluated. Daidzein is also present in high amounts in M. scutelata (19.2. mg/kg. db, alcoholic extract). Genistein is detected in several species at concentrations ranging from 0.7 (aqueous extract of M. tornata) to 16.1. mg/kg. db (alcoholic extract of M. scutelata). In terms of total isoflavones content per species, results showed significant differences between M. rigidula and M. sativa, considering all type of solvents, being the highest and the lowest one, respectively. In a general way, the extractability of compounds significantly increased from aqueous to alcoholic extracts. The study demonstrates that some Medicago species possess an excellent potential as a source of these health promoting bioactive compounds. © 2014 Elsevier B.V.
Keywords: By-product; Daidzein; Genistein; Genistin; Isoflavones; Medicago

Timing embryo segmentation: Dynamics and regulatory mechanisms of the vertebrate segmentation clock - Resende, TP; Andrade, R.P.; Palmeirim, I. (BioMed Research International, 2014)
All vertebrate species present a segmented body, easily observed in the vertebrate column and its associated components, which provides a high degree of motility to the adult body and efficient protection of the internal organs. The sequential formation of the segmented precursors of the vertebral column during embryonic development, the somites, is governed by an oscillating genetic network, the somitogenesis molecular clock. Herein, we provide an overview of the molecular clock operating during somite formation and its underlying molecular regulatory mechanisms. Human congenital vertebral malformations have been associated with perturbations in these oscillatory mechanisms. Thus, a better comprehension of the molecular mechanisms regulating somite formation is required in order to fully understand the origin of human skeletal malformations. © 2014 Tatiana P. Resende et al.

Translating chitosan to clinical delivery of nucleic acid-based drugs - Gomes, C.P.; Lopes, C.D.F.; Moreno, P.M.D.; Varela-Moreira, A.; Alonso, M.J.; Pego, A. P. (Mrs Bulletin, 2014)
Gomes, Carla Pereira Ferreira Lopes, Catia Daniela Duarte Moreno, Pedro Miguel Varela-Moreira, Aida Jose Alonso, Maria Pego, Ana PaulaPego, Ana Paula/C-6942-2012; Moreno, Pedro/J-9382-2013; Lopes, Catia/O-1090-2013 Pego, Ana Paula/0000-0001-5169-328X; Moreno, Pedro/0000-0002-3773-3262; Lopes, Catia/0000-0002-7467-6498

What do Portuguese women prefer regarding vaginal products? Results from a cross-sectional web-based survey - Palmeira-de-Oliveira, R.; Duarte, P.; Palmeira-de-Oliveira, A.; Das Neves, J.; Amaral, M.H.; Breitenfeld, L.; Martinez-de-Oliveira, J. (Pharmaceutics, 2014)
Therapeutic outcomes of vaginal products depend not only on their ability to deliver drugs to or through the vagina but also on acceptability and correct use. Women’s preferences, in turn, may vary according to age and cultural backgrounds. In this work, an anonymous online survey was completed by 2529 Portuguese women to assess their preferences for physical characteristics and mode of application of vaginal products, according to age. Additionally, intention to use and misconceptions about these issues were assessed. The majority of women of all age groups would use vaginal products to treat or prevent diseases, upon medical prescription. Women preferred vaginal products to be odorless and colorless gels, creams and ointments composed by natural origin drugs/excipients and applied by means of an applicator. Although the majority of women would prefer not to insert any product in the vagina, intention to use for self and recommendation to use for others was associated with previous experiences with vaginal products. General concerns and misconceptions related to use of vaginal products were rare. These data may contribute to the development of products that women are more prone to use.
Keywords: Acceptability; Vaginal dosage forms; Vaginal products; Women’s preferences

What do portuguese women prefer regarding vaginal products? Results from a cross-sectional web-based survey - Palmeira-de-Oliveira, Rita; Duarte, Paulo; Palmeira-de-Oliveira, Ana; das Neves, Jose; Amaral, Maria Helena; Breitenfeld, Luiza; Martinez-de-Oliveira, Jose (Pharmaceutics, 2014)
25337676

Adsorbed fibrinogen leads to improved bone regeneration and correlates with differences in the systemic immune response - Santos, S.G.; Lamghari, M.; Almeida, C.R.; Oliveira, M.I.; Neves, N.; Ribeiro, A.C.; Barbosa, J.N.; Barros, R.; Maciel, J.; Martins, M.C.L.; Gonçalves, R.M.; Barbosa, M.A. (Acta Biomaterialia, 2013)

Adult stem cells and biocompatible scaffolds as smart drug delivery tools for cardiac tissue repair - Pagliari, S.; Romanazzo, S.; Mosqueira, D.; Pinto-Do-Ó, P.; Aoyagi, T.; Forte, G. (Current Medicinal Chemistry, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

An overview of central fetal monitoring systems in labour - Nunes, Inês; Ayres-de-Campos, Diogo; Figueiredo, Catarina; Bernardes, João %@ 1619-3997 (2013)

Assessing the physical-chemical properties and stability of dapivirine-loaded polymeric nanoparticles - Das Neves, J.; Amiji, M.; Bahia, M.F.; Sarmento, B. (International Journal of Pharmaceutics, 2013)

Characterization of human NLZ1/ZNF703 identifies conserved domains essential for proper subcellular localization and transcriptional repression - Pereira-Castro, I.; Costa, Â.M.S.; Oliveira, M.J.; Barbosa, I.; Rocha, A.S.; Azevedo, L.; Da Costa, L.T. (Journal of Cellular Biochemistry, 2013)

Comparison of real beat-to-beat signals with commercially available 4 Hz sampling on the evaluation of foetal heart rate variability - Gonçalves, H.; Costa, A.; Ayres-de-Campos, D.; Costa-Santos, C.; Rocha, A.P.; Bernardes, J. (Medical and Biological Engineering and Computing, 2013)

Development of bis-locked nucleic acid (bisLNA) oligonucleotides for efficient invasion of supercoiled duplex DNA - Moreno, P.M.D.; Geny, S.; Pabon, Y.V.; Bergquist, H.; Zaghloul, E.M.; Rocha, C.S.J.; Oprea, I.I.; Bestas, B.; Andaloussi, S.E.; Jørgensen, P.T.; Pedersen, E.B.; Lundin, K.E.; et al. (Nucleic Acids Research, 2013)
Cited By (since 1996):2Export Date: 12 December 2013Source: Scopus

Development of PLGA-mannosamine nanoparticles as oral protein carriers - Alonso-Sande, M.; Des Rieux, A.; Fievez, V.; Sarmento, B.; Delgado, A.; Evora, C.; Remuñán-López, C.; Préat, V.; Alonso, M.J. (Biomacromolecules, 2013)

Effect of freeze-drying, cryoprotectants and storage conditions on the stability of secondary structure of insulin-loaded solid lipid nanoparticles - Soares, S.; Fonte, P.; Costa, A.; Andrade, J.; Seabra, V.; Ferreira, D.; Reis, S.; Sarmento, B. (International Journal of Pharmaceutics, 2013)

Endothelialization of chitosan porous conduits via immobilization of a recombinant fibronectin fragment (rhFNIII7-10) - Amaral, I.F.; Neiva, I.; Ferreira da Silva, F.; Sousa, S.R.; Piloto, A.M.; Lopes, C.D.F.; Barbosa, M.A.; Kirkpatrick, C.J.; Pêgo, A.P. (Acta Biomaterialia, 2013)

Enzymatic, physicochemical and biological properties of MMP-sensitive alginate hydrogels - Fonseca, K.B.; Maia, F.R.; Cruz, F.A.; Andrade, D.; Juliano, M.A.; Granja, P.L.; Barrias, C.C. (Soft Matter, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

Establishment of a triple co-culture in vitro cell models to study intestinal absorption of peptide drugs - Antunes, F.; Andrade, F.; Araújo, F.; Ferreira, D.; Sarmento, B. (European Journal of Pharmaceutics and Biopharmaceutics, 2013)
Cited By (since 1996):4Export Date: 12 December 2013Source: Scopus

Gender-specific heart rate dynamics in severe intrauterine growth-restricted fetuses - Gonçalves, H.; Bernardes, J.; Ayres-de-Campos, D. (Early Human Development, 2013)

Highly focalised thermotherapy using a ferrimagnetic cement in the treatment of a melanoma mouse model by low temperature hyperthermia - Portela, A.; Vasconcelos, M.; Fernandes, M.H.; Garcia, M.; Silva, A.; Gabriel, J.; Gartner, F.; Amorim, I.; Cavalheiro, J. (International Journal of Hyperthermia, 2013)
Cited By (since 1996):2Export Date: 12 December 2013Source: Scopus

Hydrolyzed galactomannan-modified nanoparticles and flower-like polymeric micelles for the active targeting of rifampicin to macrophages - Moretton, M.A.; Chiappetta, D.A.; Andrade, F.; Das Neves, J.; Ferreira, D.; Sarmento, B.; Sosnik, A. (Journal of Biomedical Nanotechnology, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

In vitro and Ex Vivo evaluation of polymeric nanoparticles for vaginal and rectal delivery of the anti-HIV drug dapivirine - Das Neves, J.; Araújo, F.; Andrade, F.; Michiels, J.; Ariën, K.K.; Vanham, G.; Amiji, M.; Bahia, M.F.; Sarmento, B. (Molecular Pharmaceutics, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

Information-based measure of disagreement for more than two observers: A useful tool to compare the degree of observer disagreement - Henriques, T.; Antunes, L.; Bernardes, J.; Matias, M.; Sato, D.; Costa-Santos, C. (BMC Medical Research Methodology, 2013)

Keratins and lipids in ethnic hair - Cruz, C.F.; Fernandes, M.M.; Gomes, A.C.; Coderch, L.; Martí, M.; Méndez, S.; Gales, L.; Azoia, N.G.; Shimanovich, U.; Cavaco-Paulo, A. (International Journal of Cosmetic Science, 2013)
Cited By (since 1996):3Export Date: 12 December 2013Source: Scopus

Macrophage polarization following chitosan implantation - Vasconcelos, D.P.; Fonseca, A.C.; Costa, M.; Amaral, I.F.; Barbosa, M.A.; Águas, A.P.; Barbosa, J.N. (Biomaterials, 2013)

Medicago spp. extracts as promising ingredients for skin care products - Rodrigues, F.; Palmeira-de-Oliveira, A.; Das Neves, J.; Sarmento, B.; Amaral, M.H.; Oliveira, M.B. (Industrial Crops and Products, 2013)

Minimum error entropy classification - Marques De Sá, J.P.; Silva, L.M.A.; Santos, J.M.F.; Alexandre, L.A. (Studies in Computational Intelligence, 2013)

A model for educational simulation of the effect of oxytocin on uterine contractions - Lobo, M.F.; Bastos, L.F.; van Meurs, W.L.; Ayres-de-Campos, D. (Medical Engineering and Physics, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

Modulation of stability and mucoadhesive properties of chitosan microspheres for therapeutic gastric application - Fernandes, M.; Gonçalves, I.C.; Nardecchia, S.; Amaral, I.F.; Barbosa, M.A.; Martins, M.C.L. (International Journal of Pharmaceutics, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

Nanotechnology and pulmonary delivery to overcome resistance in infectious diseases - Andrade, F.; Rafael, D.; Videira, M.; Ferreira, D.; Sosnik, A.; Sarmento, B. (Advanced Drug Delivery Reviews, 2013)

Osteoporotic hip fractures: Bisphosphonates sales and observed turning point in trend. A population-based retrospective study - Alves, S.M.; Economou, T.; Oliveira, C.; Ribeiro, A.I.; Neves, N.; Goméz-Barrena, E.; Pina, M.F. (Bone, 2013)

Overexpression of tumour-associated carbohydrate antigen sialyl-Tn in advanced bladder tumours - Ferreira, J.A.; Videira, P.A.; Lima, L.; Pereira, S.; Silva, M.; Carrascal, M.; Severino, P.F.; Fernandes, E.; Almeida, A.; Costa, C.; Vitorino, R.; Amaro, T.; et al. (Molecular Oncology, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

An overview of central fetal monitoring systems in labour - Nunes, I.; Ayres-de-Campos, D.; Figueiredo, C.; Bernardes, J. (Journal of Perinatal Medicine, 2013)
Cited By (since 1996):1Export Date: 12 December 2013Source: Scopus

Sociodemographic determinants of prevalence and incidence of helicobacter pylori infection in portuguese adults - Bastos, J.; Peleteiro, B.; Barros, R.; Alves, L.; Severo, M.; de Fátima Pina, M.; Pinto, H.; Carvalho, S.; Marinho, A.; Guimarães, J.T.; Azevedo, A.; La Vecchia, C.; et al. (Helicobacter, 2013)

Stable phenotype and function of immortalized Lin-Sca-1+ cardiac progenitor cells in long-term culture: a step closer to standardization. - Freire, AG; Nascimento, D.S.; Forte, G.; Valente, M.; Resende, TP; Pagliari, S.; Abreu, C; Carvalho, I; Di Nardo, P.; Pinto-Do-Ó, P. (Stem Cells Dev, 2013)

Towards the characterization of an in vitro triple co-culture intestine cell model for permeability studies - Araújo, F.; Sarmento, B. (International Journal of Pharmaceutics, 2013)

Biosynthesis of highly pure poly-γ-glutamic acid for biomedical applications - Pereira, C.L.; Antunes, J.C.; Gonçalves, R.M.; Ferreira-da-Silva, F.; Barbosa, M.A. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2012)
The remarkable properties of poly-aminoacids, mainly their biocompatibility and biodegradability, have prompted an increasing interest in these polymers for biomedical applications. Poly-γ-glutamic acid (γ-PGA) is one of the most interesting poly-aminoacids with potential applications as a biomaterial. Here we describe the production and characterization of γ-PGA by Bacillus subtilis natto. The γ-PGA was produced with low molecular weight (10-50 kDa), high purity grade (>99 %) and a D-/L-glutamate ratio of 50-60/50-40 %. To evaluate the feasibility of using this γ-PGA as a biomaterial, chitosan (Ch)/γ-PGA nanoparticles were prepared by the coacervation method at pH ranging from 3.0 to 5.0, with dimensions in the interval 214-221 nm with a poly-dispersion index of ca. 0.2. The high purity of γ-PGA produced by this method, which is firstly described here, renders this biopolymer suitable for biomedical applications. Moreover, the Ch/γ-PGA nanocomplexes developed in this investigation can be combined with biologically active substances for their delivery in the organism. The fact that the assembly between Ch and γ-PGA relies on electrostatic interactions enables addition of other molecules that can be released into the medium through changes from acidic to physiological pH, without loss in biological activity. © Springer Science+Business Media, LLC 2012.
Keywords: Amino acids; animal cell; article; Bacillus subtilis; Bacillus subtilis natto; Bioactivity; Biocompatibility; Biocompatible Materials; biodegradability; Biodegradable polymers; Biodegradation; Biologically active substances; biomaterial; Biomedical applications; biomedicine; biosynthesis; chitosan; circular dichroism; complex formation; controlled study; dispersion; Electrophoresis, Polyacrylamide Gel; feasibility study; Functional polymers; gamma polyglutamic acid; Glutamic acid; High purity; Low molecular weight; Medical applications; molecular interaction; molecular weight; Nanocomplexes; nanoparticle; nonhuman; pH; Physiological pH; polyglutamic acid; Potential applications; priority journal; purification; Spectroscopy, Fourier Transform Infrared; static electricity; Stereoisomerism; unclassified drug

Cell-based in vitro models for predicting drug permeability - Sarmento, B.; Andrade, F.; Da Silva, S.B.; Rodrigues, F.; Das Neves, J.; Ferreira, D. (Expert Opinion on Drug Metabolism and ToxicologyExpert Opin. Drug Metab. Toxicol., 2012)
In vitro cell models have been used to predict drug permeation in early stages of drug development, since they represent an easy and reproducible method, allowing the tracking of drug absorption rate and mechanism, with an advantageous costbenefit ratio. Such cell-based models are mainly composed of immortalized cells with an intrinsic ability to grow in a monolayer when seeded in permeable supports, maintaining their physiologic characteristics regarding epithelium cell physiology and functionality. Areas covered: This review summarizes the most important intestinal, pulmonary, nasal, vaginal, rectal, ocular and skin cell-based in vitro models for predicting the permeability of drugs. Moreover, the similitude between in vitro cell models and in vivo conditions are discussed, providing evidence that each model may provisionally resemble different drug absorption route. Expert opinion: Despite the widespread use of in vitro cell models for drug permeability and absorption evaluation purposes, a detailed study on the properties of these models and their in vitroin vivo correlation compared with human data are required to further use in order to consider a future drug discovery optimization and clinical development. © 2012 Informa UK, Ltd.
Keywords: Animals; Caco-2 Cells; carcinoma cell; cell differentiation; cell growth; Cell Line; Cell Membrane Permeability; cell models; cell proliferation; cell strain CACO 2; cell type; Cells; conjunctiva; drug absorption; drug bioavailability; drug delivery system; drug penetration; drug screening; drug transport; epithelium cell; Eye; human; Humans; in vitro models; in vitro study; in vitroin vivo correlation; Intestinal Absorption; intestinal mucosa; intestine cell; Intestines; Lung; lung alveolus cell; Models, Biological; molecular weight; nasal cell; nonhuman; ocular cell; permeability; Pharmaceutical Preparations; rectal cell; review; Skin; skin cell; vaginal cell

Dissection and reconstruction of the extracellular matrix - a cardiac regenerative niche - Nascimento D.; Silva A.; Oliveira MJ.; Barbosa MA.; Pinto-do-Ó P. (Journal of Tissue Engineering and Regenerative Medicine, 2012)
Cited By (since 1996):1Export Date: 2 October 2013Source: Scopus

Endothelialization of chitosan porous conduits via immobilization of a recombinant fibronectin fragment (rhFNIII 7-10) - Amaral, I.F.; Neiva, I.; Ferreira da Silva, F.; Sousa, S.R.; Piloto, A.M.; Lopes, C.D.F.; Barbosa, M.A.; Kirkpatrick, C.J.; Pêgo, A.P. (Acta BiomaterialiaActa Biomater., 2012)
The present study aimed to develop a pre-endothelialized chitosan (CH) porous hollowed scaffold for application in spinal cord regenerative therapies. CH conduits with different degrees of acetylation (DA; 4% and 15%) were prepared, characterized (microstructure, porosity and water uptake) and functionalized with a recombinant fragment of human fibronectin (rhFNIII 7-10). Immobilized rhFNIII 7-10 was characterized in terms of amount ( 125I-radiolabelling), exposure of cell-binding domains (immunofluorescence) and ability to mediate endothelial cell (EC) adhesion and cytoskeletal rearrangement. Functionalized conduits revealed a linear increase in immobilized rhFNIII 7-10 with rhFNIII 7-10 concentration, and, for the same concentration, higher amounts of rhFNIII 7-10 on DA 4% compared with DA 15%. Moreover, rhFNIII 7-10 concentrations as low as 5 and 20 μg ml
Keywords: Protein conformation; Protein radiolabelling; Spinal cord injury; Surface grafting; Three-dimensional scaffolds

Enhanced mesenchymal stromal cell recruitment via natural killer cells by incorporation of inflammatory signals in biomaterials - Almeida, C.R.; Vasconcelos, D.P.; Gonçalves, R.M.; Barbosa, M.A. (Journal of the Royal Society InterfaceJ. R. Soc. Interface, 2012)
An exacerbated inflammatory response questions biomaterial biocompatibility, but on the other hand, inflammation has a central role in the regulation of tissue regeneration. Therefore, it may be argued that an 'ideal' inflammatory response is crucial to achieve efficient tissue repair/regeneration. Natural killer (NK) cells, being one of the first populations arriving at an injury site, can have an important role in regulating bone repair/regeneration, particularly through interactions with mesenchymal stem/stromal cells (MSCs). Here, we studied how biomaterials designed to incorporate inflammatory signals affected NK cell behaviour and NK cell-MSC interactions. Adsorption of the pro-inflammatory molecule fibrinogen (Fg) to chitosan films led to a 1.5-fold increase in adhesion of peripheral blood human NK cells, without an increase in cytokine secretion. Most importantly, it was found that NK cells are capable of stimulating a threefold increase in human bone marrow MSC invasion, a key event taking place in tissue repair, but did not affect the expression of the differentiation marker alkaline phosphatase (ALP). Of significant importance, this NK cell-mediated MSC recruitment was modulated by Fg adsorption. Designing novel biomaterials leading to rational modulation of the inflammatory response is proposed as an alternative to current bone regeneration strategies. © 2011 The Royal Society.
Cited By (since 1996): 1Export Date: 21 November 2012Source: Scopusdoi: 10.1098/rsif.2011.0357Language of Original Document: EnglishCorrespondence Address: Almeida, C.R.; INEB-Instituto de Engenharia Biomédica, Biomaterials Division, NEWTherapies Group, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: cralmeid@ineb.up.ptChemicals/CAS: alkaline phosphatase, 9001-78-9; chitosan, 9012-76-4; fibrinogen, 9001-32-5; gamma interferon, 82115-62-6References: Mountziaris, P.M., Mikos, A.G., Modulation of the inflammatory response for enhanced bone tissue regeneration (2008) Tissue Eng. Part B Rev., 14, pp. 179-186. , doi:10. 1089/ten.teb.2008.0038;Anderson, J.M., Rodriguez, A., Chang, D.T., Foreign body reaction to biomaterials (2008) Semin. Immunol., 20, pp. 86-100. , doi:10.1016/j.smim.2007.11.004; Agaiby, A.D., Dyson, M., Immuno-inflammatory cell dynamics during cutaneous wound healing (1999) J. Anat., 195, pp. 531-542. , doi:10.1046/j.1469-7580.1999.19540531.x; Vivier, E., Tomasello, E., Baratin, M., Walzer, T., Ugolini, S., Functions of natural killer cells (2008) Nat. Immunol., 9, pp. 503-510. , doi:10.1038/ni1582; Aggarwal, S., Pittenger, M.F., Human mesenchymal stem cells modulate allogeneic immune cell responses (2005) Blood, 105, pp. 1815-1822. , doi:10.1182/blood- 2004-04-1559; Caplan, A.I., Adult mesenchymal stem cells for tissue engineering versus regenerative medicine (2007) J. Cell. Physiol., 213, pp. 341-347. , doi:10.1002/jcp.21200; Pittenger, M.F., Multilineage potential of adult human mesenchymal stem cells (1999) Science, 284, pp. 143-147. , doi:10.1126/science.284.5411.143; Poggi, A., Prevosto, C., Massaro, A.M., Negrini, S., Urbani, S., Pierri, I., Saccardi, R., Zocchi, M.R., Interaction between human NK cells and bone marrow stromal cells induces NK cell triggering: Role of NKp30 and NKG2D receptors (2005) J. Immunol., 175, pp. 6352-6360. , doi:10.175/10/6352[pii]; Rasmusson, I., Ringden, O., Sundberg, B., Le Blanc, K., Mesenchymal stem cells inhibit the formation of cytotoxic T lymphocytes, but not activated cytotoxic T lymphocytes or natural killer cells (2003) Transplantation, 76, pp. 1208-1213. , doi:10.1097/01.TP.0000082540.43730.80; Götherström, C., Lundqvist, A., Duprez, I.R., Childs, R., Berg, L., Le Blanc, K., Fetal and adult multipotent mesenchymal stromal cells are killed by different pathways (2010) Cytotherapy, 13, pp. 269-278. , doi:10.3109/14653249.2010.523077; Jewett, A., Arasteh, A., Tseng, H.C., Behel, A., Arasteh, H., Yang, W., Cacalano, N.A., Paranjpe, A., Strategies to rescue mesenchymal stem cells (MSCs) and dental pulp stem cells (DPSCs) from NK cell mediated cytotoxicity (2010) PLoS ONE, 5, pp. e9874. , doi:10.1371/journal.pone. 0009874; Sotiropoulou, P.A., Perez, S.A., Gritzapis, A.D., Baxevanis, C.N., Papamichail, M., Interactions between human mesenchymal stem cells and natural killer cells (2006) Stem Cells, 24, pp. 74-85. , doi:10.1634/stemcells.2004-0359; Spaggiari, G.M., Capobianco, A., Becchetti, S., Mingari, M.C., Moretta, L., Mesenchymal stem cell-natural killer cell interactions: Evidence that activated NK cells are capable of killing MSCs, whereas MSCs can inhibit IL-2- Induced NK-cell proliferation (2006) Blood, 107, pp. 1484-1490. , doi:10.1182/blood-2005-07-2775; Tseng, H.C., Increased lysis of stem cells but not their differentiated cells by natural killer cells; dedifferentiation or reprogramming activates NK cells (2010) PLoS ONE, 5, pp. e11590. , doi:10.1371/journal.pone.0011590; Krampera, M., Role for interferon-gamma in the immunomodulatory activity of human bone marrow mesenchymal stem cells (2006) Stem Cells, 24, pp. 386-398. , doi:10.1634/stemcells.2005-0008; Pradier, A., Passweg, J., Villard, J., Kindler, V., Human bone marrow stromal cells and skin fibroblasts inhibit natural killer cell proliferation and cytotoxic activity (2010) Cell Transplant., , doi:10.3727/096368910X 536545; Selmani, Z., Human leukocyte antigen-G5 secretion by human mesenchymal stem cells is required to suppress T lymphocyte and natural killer function and to induce CD4+CD25highFOXP3+ regulatory T cells (2008) Stem Cells, 26, pp. 212-222. , doi:10.1634/stemcells. 2007-0554; Spaggiari, G.M., Capobianco, A., Abdelrazik, H., Becchetti, F., Mingari, M.C., Moretta, L., Mesenchymal stem cells inhibit natural killer-cell proliferation, cytotoxicity, and cytokine production: Role of indoleamine 2,3-dioxygenase and prostaglandin E2 (2008) Blood, 111, pp. 1327-1333. , doi:10.1182/blood-2007-02- 074997; Salem, H.K., Thiemermann, C., Mesenchymal stromal cells: Current understanding and clinical status (2010) Stem Cells, 28, pp. 585-596. , doi:10.1002/stem.269; Dimitriou, R., Tsiridis, E., Giannoudis, P.V., Current concepts of molecular aspects of bone healing (2005) Injury, 36, pp. 1392-1404. , doi:10.1016/j.injury.2005.07.019; Rifas, L., T-cell cytokine induction of BMP-2 regulates human mesenchymal stromal cell differentiation and mineralization (2006) J. Cell. Biochem., 98, pp. 706-714. , doi:10.1002/jcb.20933; Rifas, L., Arackal, S., Weitzmann, M.N., Inflammatory T cells rapidly induce differentiation of human bone marrow stromal cells into mature osteoblasts (2003) J. Cell. Biochem., 88, pp. 650-659. , doi:10.1002/jcb.10436; Champagne, C.M., Takebe, J., Offenbacher, S., Cooper, L.F., Macrophage cell lines produce osteoinductive signals that include bone morphogenetic protein-2 (2002) Bone, 30, pp. 26-31. , doi:10.1016/S8756-3282(01)00638-X; Gerstenfeld, L.C., Cho, T.J., Kon, T., Aizawa, T., Cruceta, J., Graves, B.D., Einhorn, T.A., Impaired intramembranous bone formation during bone repair in the absence of tumor necrosis factor-alpha signaling (2001) Cells Tissues Organs, 169, pp. 285-294. , doi:10.1159/ 000047893; Gerstenfeld, L.C., Cho, T.J., Kon, T., Aizawa, T., Tsay, A., Fitch, J., Barnes, G.L., Einhorn, T.A., Impaired fracture healing in the absence of TNF-alpha signaling: The role of TNF-α in endochondral cartilage resorption (2003) J. Bone Miner. Res., 18, pp. 1584-1592. , doi:10.1359/jbmr.2003.18.9.1584; Duque, G., Huang, D.C., Macoritto, M., Rivas, D., Yang, X.F., Ste-Marie, L.G., Kremer, R., Autocrine regulation of interferon gamma in mesenchymal stem cells plays a role in early osteoblastogenesis (2009) Stem Cells, 27, pp. 550-558. , doi:10.1634/stemcells.2008-0886; Honczarenko, M., Le, Y., Swierkowski, M., Ghiran, I., Glodek, A.M., Silberstein, L.E., Human bone marrow stromal cells express a distinct set of biologically functional chemokine receptors (2006) Stem Cells, 24, pp. 1030-1041. , doi:10.1634/stemcells.2005-0319; Robertson, M.J., Role of chemokines in the biology of natural killer cells (2002) J. Leukoc Biol., 71, pp. 173-183; Rodrigues, S.N., Gonçalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Fibrinogen adsorption, platelet adhesion and activation on mixed hydroxyl-/methyl-terminated self-assembled monolayers (2006) Biomaterials, 27, pp. 5357-5367. , doi:10.1016/j.biomaterials.2006.06.010; Peled, E., Boss, J., Bejar, J., Zinman, C., Seliktar, D., A novel poly(ethylene glycol)-fibrinogen hydrogel for tibial segmental defect repair in a rat model (2007) J. Biomed. Mater. Res., 80, pp. 874-884. , doi:10.1002/jbm. a.30928; Bryceson, Y.T., March, M.E., Ljunggren, H.G., Long, E.O., Activation, coactivation, and costimulation of resting human natural killer cells (2006) Immunol. Rev., 214, pp. 73-91. , doi:10.1111/j.1600-065X.2006.00457.x; Muto, S., Vetvicka, V., Ross, G.D., CR3 (CD11b/ CD18) expressed by cytotoxic T cells and natural killer cells is upregulated in a manner similar to neutrophil CR3 following stimulation with various activating agents (1993) J. Clin. Immunol., 13, pp. 175-184. , doi:10.1007/ BF00919970; Ross, G.D., Vetvicka, V., CR3 (CD11b, CD18): A phagocyte and NK cell membrane receptor with multiple ligand specificities and functions (1993) Clin. Exp. Immunol., 92, pp. 181-184. , doi:10.1111/j.1365-2249.1993.tb03377.x; Lishko, V.K., Kudryk, B., Yakubenko, V.P., Yee, V.C., Ugarova, T.P., Regulated unmasking of the cryptic binding site for integrin alpha M beta 2 in the gamma C-domain of fibrinogen (2002) Biochemistry, 41, pp. 12942-12951. , doi:10.1021/bi026324c; Mwale, F., Iordanova, M., Demers, C.N., Steffen, T., Roughley, P., Antoniou, J., Biological evaluation of chitosan salts cross-linked to genipin as a cell scaffold for disk tissue engineering (2005) Tissue Eng., 11, pp. 130-140. , doi:10.1089/ten.2005.11.130; Prabaharan, M., Jayakumar, R., Chitosan-graft-beta-cyclodextrin scaffolds with controlled drug release capability for tissue engineering applications (2009) Int. J. Biol. Macromol., 44, pp. 320-325. , doi:10.1016/j.ijbiomac.2009.01.005; Agnihotri, S.A., Mallikarjuna, N.N., Aminabhavi, T.M., Recent advances on chitosan-based micro-and nanoparticles in drug delivery (2004) J. Control Release, 100, pp. 5-28. , doi:10.1016/j.jconrel.2004.08.010; Barbosa, M.A., Granja, P.L., Barrias, C.C., Amaral, I.F., Polysaccharides as scaffolds for bone regeneration (2005) ITBM-RBM, 26, pp. 212-217. , doi:10.1016/j.rbmret.2005.04.006; Berger, J., Reist, M., Mayer, J.M., Felt, O., Gurny, R., Structure and interactions in chitosan hydrogels formed by complexation or aggregation for biomedical applications (2004) Eur. J. Pharm. Biopharm., 57, pp. 35-52. , doi:10.1016/S0939-6411(03)00160-7; Amaral, I.F., Cordeiro, A.L., Sampaio, P., Barbosa, M.A., Attachment, spreading and short-term proliferation of human osteoblastic cells cultured on chitosan films with different degrees of acetylation (2007) J. Biomater. Sci. Polym. Ed., 18, pp. 469-485. , doi:10.1163/ 156856207780425068; Barbosa, J.N., Amaral, I.F., Aguas, A.P., Barbosa, M.A., Evaluation of the effect of the degree of acetylation on the inflammatory response to 3D porous chitosan scaffolds (2010) J. Biomed. Mater. Res., 93 A, pp. 20-28. , doi:10.1002/jbm.a.32499; Oliveira, S.M., Mijares, D.Q., Turner, G., Amaral, I.F., Barbosa, M.A., Teixeira, C.C., Engineering endochondral bone: In vivo studies (2009) Tissue Eng. Part A, 15, pp. 635-643. , doi:10.1089/ten.tea.2008.0052; Amaral, I.F., Sampaio, P., Barbosa, M.A., Three-dimensional culture of human osteoblastic cells in chitosan sponges: The effect of the degree of acetylation (2006) J. Biomed. Mater. Res., 76, pp. 335-346. , doi:10.1002/jbm.a.30522; Goncalves, R.M., Martins, M.C., Almeida-Porada, G., Barbosa, M.A., Induction of notch signaling by immobilization of jagged-1 on self-assembled monolayers (2009) Biomaterials, 30, pp. 6879-6887. , doi:10.1016/j.biomaterials.2009.09.010; Dominici, M., Minimal criteria for defining multipotent mesenchymal stromal cells. The International Society for Cellular Therapy position statement (2006) Cytotherapy, 8, pp. 315-317. , doi:10.1080/14653240600855905; Siddappa, R., Licht, R., Van Blitterswijk, C., De Boer, J., Donor variation and loss of multipotency during in vitro expansion of human mesenchymal stem cells for bone tissue engineering (2007) J. Orthop. Res., 25, pp. 1029-1041. , doi:10.1002/jor.20402; Maeda, Y., Kimura, Y., Antitumor Effects of Various Low-Molecular-Weight Chitosans Are Due to Increased Natural Killer Activity of Intestinal Intraepithelial Lymphocytes in Sarcoma 180-Bearing Mice (2004) Journal of Nutrition, 134 (4), pp. 945-950; Zaharoff, D.A., Rogers, C.J., Hance, K.W., Schlom, J., Greiner, J.W., Chitosan solution enhances both humoral and cell-mediated immune responses to subcutaneous vaccination (2007) Vaccine, 25, pp. 2085-2094. , doi:10. 1016/j.vaccine.2006.11.034; Tang, L., Eaton, J.W., Fibrin(ogen) mediates acute inflammatory responses to biomaterials (1993) J. Exp. Med., 178, pp. 2147-2156. , doi:10.1084/jem.178.6.2147; Drew, A.F., Liu, H., Davidson, J.M., Daugherty, C.C., Degen, J.L., Wound-healing defects in mice lacking fibrinogen (2001) Blood, 97, pp. 3691-3698. , doi:10.1182/blood. V97.12.3691; Flick, M.J., Du, X., Degen, J.L., Fibrin(ogen)- alpha M beta 2 interactions regulate leukocyte function and innate immunity in vivo (2004) Exp. Biol. Med. (Maywood), 229, pp. 1105-1110. , doi:10.229/11/1105[pii]; Culley, F.J., Natural killer cell signal integration balances synapse symmetry and migration (2009) PLoS Biol., 7, pp. e1000159. , doi:10.1371/journal.pbio.1000159; Dustin, M.L., Cell adhesion molecules and actin cytoskeleton at immune synapses and kinapses (2007) Curr. Opin. Cell Biol., 19, pp. 529-533. , doi:10.1016/j.ceb.2007.08.003; Jacobs, R., Hintzen, G., Kemper, A., Beul, K., Kempf, S., Behrens, G., Sykora, K.W., Schmidt, R.E., CD56bright cells differ in their KIR repertoire and cytotoxic features from CD56dim NK cells (2001) Eur. J. Immunol., 31, pp. 3121-3127. , doi:10.1002/1521-4141(2001010)31: 10〈3121::AID-IMMU3121〉3.0. CO;2-4; Anfossi, N., Human NK cell education by inhibitory receptors for MHC class I (2006) Immunity, 25, pp. 331-342. , doi:10.1016/j.immuni.2006.06.013; Nolte-'t Hoen, E.N.M., Almeida, C.R., Cohen, N.R., Nedvetzki, S., Yarwood, H., Davis, D.M., Increased surveillance of cells in mitosis by human NK cells suggests a novel strategy for limiting tumor growth and viral replication (2006) Blood, 109, pp. 670-673. , doi:10.1182/blood-2006-07- 036509; Hemeda, H., Jakob, M., Ludwig, A.K., Giebel, B., Lang, S., Brandau, S., Interferon-gamma and tumor necrosis factor-alpha differentially affect cytokine expression and migration properties of mesenchymal stem cells (2010) Stem Cells Dev., 19, pp. 693-706; Liippo, J., Toriseva, M., Kähäri, V.-M., Natural killer cell in wound healing (2009) Natural Killer Cells - Basic Science and Clinical Application, pp. 519-525. , eds M. Lotze & A. Thomson, New York, NY: Academic Press; Soderstrom, K., Stein, E., Colmenero, P., Purath, U., Muller-Ladner, U., De Matos, C.T., Tarner, I.H., Engleman, E.G., Natural killer cells trigger osteoclastogenesis and bone destruction in arthritis (2010) Proc. Natl Acad. Sci. USA, 107, pp. 13028-13033. , doi:10.1073/pnas.1000546107
Keywords: Adhesion; Adsorption; alkaline phosphatase; article; Biocompatibility; biomaterial; Biomaterials; blood cell; Bone; bone marrow cell; Bone Regeneration; Bone repair; cell adhesion; Cell culture; cell differentiation; cell function; cell interaction; cell invasion; Cells; chitosan; Chitosan film; cytokine; Cytokine secretions; Differentiation markers; fibrinogen; gamma interferon; human; Human bone marrow; human cell; Inflammation; Inflammatory response; Mesenchymal Stem Cells; mesenchymal stroma cell; Mesenchymal stromal cells; natural killer cell; Natural killer cells; NK cells; ossification; Pathology; Peripheral blood; Phosphatases; protein expression; Tissue; Tissue regeneration; tissue repair

Epithelial E- and P-cadherins: Role and clinical significance in cancer - Paredes, J.; Figueiredo, J.; Albergaria, A.; Oliveira, P.; Carvalho, J.; Ribeiro, A.S.; Caldeira, J.; Costa, A.M.; Simões-Correia, J.; Oliveira, M.J.; Pinheiro, H.; Pinho, S.S.; et al. (Biochimica et Biophysica Acta - Reviews on CancerBiochim. Biophys. Acta Rev. Cancer, 2012)
E-cadherin and P-cadherin are major contributors to cell-cell adhesion in epithelial tissues, playing pivotal roles in important morphogenetic and differentiation processes during development, and in maintaining integrity and homeostasis in adult tissues. It is now generally accepted that alterations in these two molecules are observed during tumour progression of most carcinomas. Genetic or epigenetic alterations in E- and P-cadherin-encoding genes (CDH1 and CDH3, respectively), or alterations in their proteins expression, often result in tissue disorder, cellular de-differentiation, increased invasiveness of tumour cells and ultimately in metastasis. In this review, we will discuss the major properties of E- and P-cadherin molecules, its regulation in normal tissue, and their alterations and role in cancer, with a specific focus on gastric and breast cancer models. © 2012 Elsevier B.V.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: BBACEdoi: 10.1016/j.bbcan.2012.05.002Language of Original Document: EnglishCorrespondence Address: Seruca, R.; IPATIMUP, Institute of Molecular Pathology and Immunology, University of Porto, Rua Dr. Roberto Frias s/n, 4200-465 Porto, Portugal; email: rseruca@ipatimup.ptChemicals/CAS: uvomorulin, 112956-45-3Tradenames: pf 03732010References: Cavallaro, U., Christofori, G., Cell adhesion and signalling by cadherins and Ig-CAMs in cancer (2004) Nat. Rev. Cancer, 4, pp. 118-132;Gerrow, K., El-Husseini, A., Cell adhesion molecules at the synapse (2006) Front. Biosci., 11, pp. 2400-2419; Nollet, F., Kools, P., van Roy, F., Phylogenetic analysis of the cadherin superfamily allows identification of six major subfamilies besides several solitary members (2000) J. Mol. Biol., 299, pp. 551-572; Takeichi, M., Cadherins in cancer: implications for invasion and metastasis (1993) Curr. Opin. Cell Biol., 5, pp. 806-811; Pignatelli, M., Bodmer, W.F., Genetics and biochemistry of collagen binding-triggered glandular differentiation in a human colon carcinoma cell line (1988) Proc. Natl. Acad. Sci. U. S. A., 85, pp. 5561-5565; Takeichi, M., Morphogenetic roles of classic cadherins (1995) Curr. Opin. Cell Biol., 7, pp. 619-627; Shapiro, L., Fannon, A.M., Kwong, P.D., Thompson, A., Lehmann, M.S., Grubel, G., Legrand, J.F., Hendrickson, W.A., Structural basis of cell-cell adhesion by cadherins (1995) Nature, 374, pp. 327-337; Ozawa, M., Ringwald, M., Kemler, R., Uvomorulin-catenin complex formation is regulated by a specific domain in the cytoplasmic region of the cell adhesion molecule (1990) Proc. Natl. Acad. Sci. U. S. A., 87, pp. 4246-4250; Blaschuk, O.W., Sullivan, R., David, S., Pouliot, Y., Identification of a cadherin cell adhesion recognition sequence (1990) Dev. Biol., 139, pp. 227-229; Ozawa, M., Baribault, H., Kemler, R., The cytoplasmic domain of the cell adhesion molecule uvomorulin associates with three independent proteins structurally related in different species (1989) EMBO J., 8, pp. 1711-1717; Gumbiner, B.M., McCrea, P.D., Catenins as mediators of the cytoplasmic functions of cadherins (1993) J. Cell Sci. Suppl., 17, pp. 155-158; Yap, A.S., Niessen, C.M., Gumbiner, B.M., The juxtamembrane region of the cadherin cytoplasmic tail supports lateral clustering, adhesive strengthening, and interaction with p120ctn (1998) J. Cell Biol., 141, pp. 779-789; Van Aken, E., De Wever, O., Correia da Rocha, A.S., Mareel, M., Defective E-cadherin/catenin complexes in human cancer (2001) Virchows Arch., 439, pp. 725-751; Mareel, M., Oliveira, M.J., Madani, I., Cancer invasion and metastasis: interacting ecosystems (2009) Virchows Arch., 454, pp. 599-622; Makrilia, N., Kollias, A., Manolopoulos, L., Syrigos, K., Cell adhesion molecules: role and clinical significance in cancer (2009) Cancer Invest., 27, pp. 1023-1037; Bussemakers, M.J., van Bokhoven, A., Voller, M., Smit, F.P., Schalken, J.A., The genes for the calcium-dependent cell adhesion molecules P- and E-cadherin are tandemly arranged in the human genome (1994) Biochem. Biophys. Res. Commun., 203, pp. 1291-1294; Berx, G., Staes, K., van Hengel, J., Molemans, F., Bussemakers, M.J., van Bokhoven, A., van Roy, F., Cloning and characterization of the human invasion suppressor gene E-cadherin (CDH1) (1995) Genomics, 26, pp. 281-289; Jarrard, D.F., Paul, R., van Bokhoven, A., Nguyen, S.H., Bova, G.S., Wheelock, M.J., Johnson, K.R., Isaacs, W.B., P-cadherin is a basal cell-specific epithelial marker that is not expressed in prostate cancer (1997) Clin. Cancer Res., 3, pp. 2121-2128; Hubbard, T.J., Aken, B.L., Ayling, S., Ballester, B., Beal, K., Bragin, E., Brent, S., Flicek, P., Ensembl 2009 (2009) Nucleic Acids Res., 37, pp. D690-D697; Faraldo, M.L., Cano, A., The 5' flanking sequences of the mouse P-cadherin gene. Homologies to 5' sequences of the E-cadherin gene and identification of a first 215 base-pair intron (1993) J. Mol. Biol., 231, pp. 935-941; van Roy, F., Berx, G., The cell-cell adhesion molecule E-cadherin (2008) Cell. Mol. Life Sci., 65, pp. 3756-3788; Stemmler, M.P., Cadherins in development and cancer (2008) Mol. Biosyst., 4, pp. 835-850; Paredes, J., Albergaria, A., Oliveira, J.T., Jeronimo, C., Milanezi, F., Schmitt, F.C., P-cadherin overexpression is an indicator of clinical outcome in invasive breast carcinomas and is associated with CDH3 promoter hypomethylation (2005) Clin. Cancer Res., 11, pp. 5869-5877; Sakharkar, K.R., Chow, V.T., PPD-proteome profile database (2004) In Silico Biol., 4, pp. 219-223; Thomas, D.J., Rosenbloom, K.R., Clawson, H., Hinrichs, A.S., Trumbower, H., Raney, B.J., Karolchik, D., Kent, W.J., The ENCODE Project at UC Santa Cruz (2007) Nucleic Acids Res., 35, pp. D663-D667; Oliveira, P., Sanges, R., Huntsman, D., Stupka, E., Oliveira, C., Characterization of the intronic portion of cadherin superfamily members, common cancer orchestrators (2012) Eur. J. Hum. Genet.; Hosono, S., Gross, I., English, M.A., Hajra, K.M., Fearon, E.R., Licht, J.D., E-cadherin is a WT1 target gene (2000) J. Biol. Chem., 275, pp. 10943-10953; Liu, Y.N., Lee, W.W., Wang, C.Y., Chao, T.H., Chen, Y., Chen, J.H., Regulatory mechanisms controlling human E-cadherin gene expression (2005) Oncogene, 24, pp. 8277-8290; Behrens, J., Lowrick, O., Klein-Hitpass, L., Birchmeier, W., The E-cadherin promoter: functional analysis of a G.C-rich region and an epithelial cell-specific palindromic regulatory element (1991) Proc. Natl. Acad. Sci. U. S. A., 88, pp. 11495-11499; Cano, A., Perez-Moreno, M.A., Rodrigo, I., Locascio, A., Blanco, M.J., del Barrio, M.G., Portillo, F., Nieto, M.A., The transcription factor snail controls epithelial-mesenchymal transitions by repressing E-cadherin expression (2000) Nat. Cell Biol., 2, pp. 76-83; Hajra, K.M., Chen, D.Y., Fearon, E.R., The SLUG zinc-finger protein represses E-cadherin in breast cancer (2002) Cancer Res., 62, pp. 1613-1618; Perez-Moreno, M.A., Locascio, A., Rodrigo, I., Dhondt, G., Portillo, F., Nieto, M.A., Cano, A., A new role for E12/E47 in the repression of E-cadherin expression and epithelial-mesenchymal transitions (2001) J. Biol. Chem., 276, pp. 27424-27431; Comijn, J., Berx, G., Vermassen, P., Verschueren, K., van Grunsven, L., Bruyneel, E., Mareel, M., van Roy, F., The two-handed E box binding zinc finger protein SIP1 downregulates E-cadherin and induces invasion (2001) Mol. Cell, 7, pp. 1267-1278; Eger, A., Aigner, K., Sonderegger, S., Dampier, B., Oehler, S., Schreiber, M., Berx, G., Foisner, R., DeltaEF1 is a transcriptional repressor of E-cadherin and regulates epithelial plasticity in breast cancer cells (2005) Oncogene, 24, pp. 2375-2385; Peinado, H., Olmeda, D., Cano, A., Snail, Zeb and bHLH factors in tumour progression: an alliance against the epithelial phenotype? (2007) Nat. Rev. Cancer, 7, pp. 415-428; Shi, Y., Sawada, J., Sui, G., Affar el, B., Whetstine, J.R., Lan, F., Ogawa, H., Nakatani, Y., Coordinated histone modifications mediated by a CtBP co-repressor complex (2003) Nature, 422, pp. 735-738; Jamora, C., DasGupta, R., Kocieniewski, P., Fuchs, E., Links between signal transduction, transcription and adhesion in epithelial bud development (2003) Nature, 422, pp. 317-322; Vandewalle, C., Comijn, J., De Craene, B., Vermassen, P., Bruyneel, E., Andersen, H., Tulchinsky, E., Berx, G., SIP1/ZEB2 induces EMT by repressing genes of different epithelial cell-cell junctions (2005) Nucleic Acids Res., 33, pp. 6566-6578; Aigner, K., Dampier, B., Descovich, L., Mikula, M., Sultan, A., Schreiber, M., Mikulits, W., Eger, A., The transcription factor ZEB1 (deltaEF1) promotes tumour cell dedifferentiation by repressing master regulators of epithelial polarity (2007) Oncogene, 26, pp. 6979-6988; Spaderna, S., Schmalhofer, O., Wahlbuhl, M., Dimmler, A., Bauer, K., Sultan, A., Hlubek, F., Brabletz, T., The transcriptional repressor ZEB1 promotes metastasis and loss of cell polarity in cancer (2008) Cancer Res., 68, pp. 537-544; Graff, J.R., Herman, J.G., Lapidus, R.G., Chopra, H., Xu, R., Jarrard, D.F., Isaacs, W.B., Baylin, S.B., E-cadherin expression is silenced by DNA hypermethylation in human breast and prostate carcinomas (1995) Cancer Res., 55, pp. 5195-5199; Shimomura, Y., Wajid, M., Shapiro, L., Christiano, A.M., P-cadherin is a p63 target gene with a crucial role in the developing human limb bud and hair follicle (2008) Development, 135, pp. 743-753; Carroll, D.K., Carroll, J.S., Leong, C.O., Cheng, F., Brown, M., Mills, A.A., Brugge, J.S., Ellisen, L.W., P63 regulates an adhesion programme and cell survival in epithelial cells (2006) Nat. Cell Biol., 8, pp. 551-561; Faraldo, M.M., Teuliere, J., Deugnier, M.A., Birchmeier, W., Huelsken, J., Thiery, J.P., Cano, A., Glukhova, M.A., Beta-catenin regulates P-cadherin expression in mammary basal epithelial cells (2007) FEBS Lett., 581, pp. 831-836; Le, T.L., Yap, A.S., Stow, J.L., Recycling of E-cadherin: a potential mechanism for regulating cadherin dynamics (1999) J. Cell Biol., 146, pp. 219-232; Bryant, D.M., Stow, J.L., The ins and outs of E-cadherin trafficking (2004) Trends Cell Biol., 14, pp. 427-434; Hinck, L., Nathke, I.S., Papkoff, J., Nelson, W.J., Dynamics of cadherin/catenin complex formation: novel protein interactions and pathways of complex assembly (1994) J. Cell Biol., 125, pp. 1327-1340; Chen, Y.T., Stewart, D.B., Nelson, W.J., Coupling assembly of the E-cadherin/beta-catenin complex to efficient endoplasmic reticulum exit and basal-lateral membrane targeting of E-cadherin in polarized MDCK cells (1999) J. Cell Biol., 144, pp. 687-699; Lock, J.G., Stow, J.L., Rab11 in recycling endosomes regulates the sorting and basolateral transport of E-cadherin (2005) Mol. Biol. Cell, 16, pp. 1744-1755; Bryant, D.M., Kerr, M.C., Hammond, L.A., Joseph, S.R., Mostov, K.E., Teasdale, R.D., Stow, J.L., EGF induces macropinocytosis and SNX1-modulated recycling of E-cadherin (2007) J. Cell Sci., 120, pp. 1818-1828; Ling, K., Bairstow, S.F., Carbonara, C., Turbin, D.A., Huntsman, D.G., Anderson, R.A., Type I gamma phosphatidylinositol phosphate kinase modulates adherens junction and E-cadherin trafficking via a direct interaction with mu 1B adaptin (2007) J. Cell Biol., 176, pp. 343-353; Mosesson, Y., Mills, G.B., Yarden, Y., Derailed endocytosis: an emerging feature of cancer (2008) Nat. Rev. Cancer, 8, pp. 835-850; Ireton, R.C., Davis, M.A., van Hengel, J., Mariner, D.J., Barnes, K., Thoreson, M.A., Anastasiadis, P.Z., Reynolds, A.B., A novel role for p120 catenin in E-cadherin function (2002) J. Cell Biol., 159, pp. 465-476; Davis, M.A., Ireton, R.C., Reynolds, A.B., A core function for p120-catenin in cadherin turnover (2003) J. Cell Biol., 163, pp. 525-534; Xiao, K., Garner, J., Buckley, K.M., Vincent, P.A., Chiasson, C.M., Dejana, E., Faundez, V., Kowalczyk, A.P., P120-Catenin regulates clathrin-dependent endocytosis of VE-cadherin (2005) Mol. Biol. Cell, 16, pp. 5141-5151; Taniuchi, K., Nakagawa, H., Hosokawa, M., Nakamura, T., Eguchi, H., Ohigashi, H., Ishikawa, O., Nakamura, Y., Overexpressed P-cadherin/CDH3 promotes motility of pancreatic cancer cells by interacting with p120ctn and activating rho-family GTPases (2005) Cancer Res., 65, pp. 3092-3099; Paredes, J., Stove, C., Stove, V., Milanezi, F., Van Marck, V., Derycke, L., Mareel, M., Schmitt, F., P-cadherin is up-regulated by the antiestrogen ICI 182,780 and promotes invasion of human breast cancer cells (2004) Cancer Res., 64, pp. 8309-8317; Palacios, F., Price, L., Schweitzer, J., Collard, J.G., D'Souza-Schorey, C., An essential role for ARF6-regulated membrane traffic in adherens junction turnover and epithelial cell migration (2001) EMBO J., 20, pp. 4973-4986; Figueiredo, J., Simoes-Correia, J., Soderberg, O., Suriano, G., Seruca, R., ADP-ribosylation factor 6 mediates E-cadherin recovery by chemical chaperones (2011) PLoS One, 6, pp. e23188; Palacios, F., Schweitzer, J.K., Boshans, R.L., D'Souza-Schorey, C., ARF6-GTP recruits Nm23-H1 to facilitate dynamin-mediated endocytosis during adherens junctions disassembly (2002) Nat. Cell Biol., 4, pp. 929-936; Otsuki, Y., Tanaka, M., Yoshii, S., Kawazoe, N., Nakaya, K., Sugimura, H., Tumor metastasis suppressor nm23H1 regulates Rac1 GTPase by interaction with Tiam1 (2001) Proc. Natl. Acad. Sci. U. S. A., 98, pp. 4385-4390; Morishige, M., Hashimoto, S., Ogawa, E., Toda, Y., Kotani, H., Hirose, M., Wei, S., Sabe, H., GEP100 links epidermal growth factor receptor signalling to Arf6 activation to induce breast cancer invasion (2008) Nat. Cell Biol., 10, pp. 85-92; Daniel, J.M., Reynolds, A.B., Tyrosine phosphorylation and cadherin/catenin function (1997) Bioessays, 19, pp. 883-891; Palacios, F., Tushir, J.S., Fujita, Y., D'Souza-Schorey, C., Lysosomal targeting of E-cadherin: a unique mechanism for the down-regulation of cell-cell adhesion during epithelial to mesenchymal transitions (2005) Mol. Cell. Biol., 25, pp. 389-402; Fujita, Y., Krause, G., Scheffner, M., Zechner, D., Leddy, H.E., Behrens, J., Sommer, T., Birchmeier, W., Hakai, a c-Cbl-like protein, ubiquitinates and induces endocytosis of the E-cadherin complex (2002) Nat. Cell Biol., 4, pp. 222-231; Pinho, S.S., Seruca, R., Gartner, F., Yamaguchi, Y., Gu, J., Taniguchi, N., Reis, C.A., Modulation of E-cadherin function and dysfunction by N-glycosylation (2011) Cell. Mol. Life Sci., 68, pp. 1011-1020; Zhu, W., Leber, B., Andrews, D.W., Cytoplasmic O-glycosylation prevents cell surface transport of E-cadherin during apoptosis (2001) EMBO J., 20, pp. 5999-6007; Zhou, F., Su, J., Fu, L., Yang, Y., Zhang, L., Wang, L., Zhao, H., Zha, X., Unglycosylation at Asn-633 made extracellular domain of E-cadherin folded incorrectly and arrested in endoplasmic reticulum, then sequentially degraded by ERAD (2008) Glycoconj. J., 25, pp. 727-740; Liwosz, A., Lei, T., Kukuruzinska, M.A., N-glycosylation affects the molecular organization and stability of E-cadherin junctions (2006) J. Biol. Chem., 281, pp. 23138-23149; Pinho, S.S., Reis, C.A., Paredes, J., Magalhaes, A.M., Ferreira, A.C., Figueiredo, J., Xiaogang, W., Seruca, R., The role of N-acetylglucosaminyltransferase III and V in the post-transcriptional modifications of E-cadherin (2009) Hum. Mol. Genet., 18, pp. 2599-2608; Pinho, S.S., Oliveira, P., Cabral, J., Carvalho, S., Huntsman, D., Gartner, F., Seruca, R., Oliveira, C., Loss and recovery of Mgat3 and GnT-III mediated E-cadherin N-glycosylation is a mechanism involved in epithelial-mesenchymal-epithelial transitions (2012) PLoS One, 7, pp. e33191; Osumi, D., Takahashi, M., Miyoshi, E., Yokoe, S., Lee, S.H., Noda, K., Nakamori, S., Taniguchi, N., Core fucosylation of E-cadherin enhances cell-cell adhesion in human colon carcinoma WiDr cells (2009) Cancer Sci., 100, pp. 888-895; Takeichi, M., Functional correlation between cell adhesive properties and some cell surface proteins (1977) J. Cell Biol., 75, pp. 464-474; Hyafil, F., Morello, D., Babinet, C., Jacob, F., A cell surface glycoprotein involved in the compaction of embryonal carcinoma cells and cleavage stage embryos (1980) Cell, 21, pp. 927-934; Ogou, S., Okada, T.S., Takeichi, M., Cleavage stage mouse embryos share a common cell adhesion system with teratocarcinoma cells (1982) Dev. Biol., 92, pp. 521-528; Takeichi, M., The cadherins: cell-cell adhesion molecules controlling animal morphogenesis (1988) Development, 102, pp. 639-655; Fleming, T.P., Javed, Q., Hay, M., Epithelial differentiation and intercellular junction formation in the mouse early embryo (1992) Dev. Suppl., pp. 105-112; Aplin, J.D., Jones, C.J., Harris, L.K., Adhesion molecules in human trophoblast-a review. I. Villous trophoblast (2009) Placenta, 30, pp. 293-298; Nose, A., Takeichi, M., A novel cadherin cell adhesion molecule: its expression patterns associated with implantation and organogenesis of mouse embryos (1986) J. Cell Biol., 103, pp. 2649-2658; Larue, L., Ohsugi, M., Hirchenhain, J., Kemler, R., E-cadherin null mutant embryos fail to form a trophectoderm epithelium (1994) Proc. Natl. Acad. Sci. U. S. A., 91, pp. 8263-8267; Riethmacher, D., Brinkmann, V., Birchmeier, C., A targeted mutation in the mouse E-cadherin gene results in defective preimplantation development (1995) Proc. Natl. Acad. Sci. U. S. A., 92, pp. 855-859; Radice, G.L., Ferreira-Cornwell, M.C., Robinson, S.D., Rayburn, H., Chodosh, L.A., Takeichi, M., Hynes, R.O., Precocious mammary gland development in P-cadherin-deficient mice (1997) J. Cell Biol., 139, pp. 1025-1032; Frebourg, T., Oliveira, C., Hochain, P., Karam, R., Manouvrier, S., Graziadio, C., Vekemans, M., Seruca, R., Cleft lip/palate and CDH1/E-cadherin mutations in families with hereditary diffuse gastric cancer (2006) J. Med. Genet., 43, pp. 138-142; Kjaer, K.W., Hansen, L., Schwabe, G.C., Marques-de-Faria, A.P., Eiberg, H., Mundlos, S., Tommerup, N., Rosenberg, T., Distinct CDH3 mutations cause ectodermal dysplasia, ectrodactyly, macular dystrophy (EEM syndrome) (2005) J. Med. Genet., 42, pp. 292-298; Sprecher, E., Bergman, R., Richard, G., Lurie, R., Shalev, S., Petronius, D., Shalata, A., Szargel, R., Hypotrichosis with juvenile macular dystrophy is caused by a mutation in CDH3, encoding P-cadherin (2001) Nat. Genet., 29, pp. 134-136; Nelson, W.J., Epithelial cell polarity from the outside looking in (2003) News Physiol. Sci., 18, pp. 143-146; Hirai, Y., Nose, A., Kobayashi, S., Takeichi, M., Expression and role of E- and P-cadherin adhesion molecules in embryonic histogenesis. II. Skin morphogenesis (1989) Development, 105, pp. 271-277; Berx, G., Van Roy, F., The E-cadherin/catenin complex: an important gatekeeper in breast cancer tumorigenesis and malignant progression (2001) Breast Cancer Res., 3, pp. 289-293; Shimoyama, Y., Hirohashi, S., Expression of E- and P-cadherin in gastric carcinomas (1991) Cancer Res., 51, pp. 2185-2192; Hines, M.D., Jin, H.C., Wheelock, M.J., Jensen, P.J., Inhibition of cadherin function differentially affects markers of terminal differentiation in cultured human keratinocytes (1999) J. Cell Sci., 112 (PART 24), pp. 4569-4579; Ribeiro, A.S., Albergaria, A., Sousa, B., Correia, A.L., Bracke, M., Seruca, R., Schmitt, F.C., Paredes, J., Extracellular cleavage and shedding of P-cadherin: a mechanism underlying the invasive behaviour of breast cancer cells (2010) Oncogene, 29, pp. 392-402; Moll, R., Mitze, M., Frixen, U.H., Birchmeier, W., Differential loss of E-cadherin expression in infiltrating ductal and lobular breast carcinomas (1993) Am. J. Pathol., 143, pp. 1731-1742; Gamallo, C., Palacios, J., Suarez, A., Pizarro, A., Navarro, P., Quintanilla, M., Cano, A., Correlation of E-cadherin expression with differentiation grade and histological type in breast carcinoma (1993) Am. J. Pathol., 142, pp. 987-993; Reis-Filho, J.S., Cancela Paredes, J., Milanezi, F., Schmitt, F.C., Clinicopathologic implications of E-cadherin reactivity in patients with lobular carcinoma in situ of the breast (2002) Cancer, 94, pp. 2114-2115; author reply 2115-2116Weigelt, B., Geyer, F.C., Natrajan, R., Lopez-Garcia, M.A., Ahmad, A.S., Savage, K., Kreike, B., Reis-Filho, J.S., The molecular underpinning of lobular histological growth pattern: a genome-wide transcriptomic analysis of invasive lobular carcinomas and grade- and molecular subtype-matched invasive ductal carcinomas of no special type (2010) J. Pathol., 220, pp. 45-57; Simpson, P.T., Reis-Filho, J.S., Lambros, M.B., Jones, C., Steele, D., Mackay, A., Iravani, M., Lakhani, S.R., Molecular profiling pleomorphic lobular carcinomas of the breast: evidence for a common molecular genetic pathway with classic lobular carcinomas (2008) J. Pathol., 215, pp. 231-244; Mahler-Araujo, B., Savage, K., Parry, S., Reis-Filho, J.S., Reduction of E-cadherin expression is associated with non-lobular breast carcinomas of basal-like and triple negative phenotype (2008) J. Clin. Pathol., 61, pp. 615-620; Lopes, N., Carvalho, J., Duraes, C., Sousa, B., Gomes, M., Costa, J.L., Oliveira, C., Schmitt, F., 1Alpha,25-dihydroxyvitamin D3 induces de novo E-cadherin expression in triple-negative breast cancer cells by CDH1-promoter demethylation (2012) Anticancer. Res., 32, pp. 249-257; Berx, G., Cleton-Jansen, A.M., Strumane, K., de Leeuw, W.J., Nollet, F., van Roy, F., Cornelisse, C., E-cadherin is inactivated in a majority of invasive human lobular breast cancers by truncation mutations throughout its extracellular domain (1996) Oncogene, 13, pp. 1919-1925; Keller, G., Vogelsang, H., Becker, I., Hutter, J., Ott, K., Candidus, S., Grundei, T., Hofler, H., Diffuse type gastric and lobular breast carcinoma in a familial gastric cancer patient with an E-cadherin germline mutation (1999) Am. J. Pathol., 155, pp. 337-342; Schrader, K.A., Masciari, S., Boyd, N., Wiyrick, S., Kaurah, P., Senz, J., Burke, W., Huntsman, D.G., Hereditary diffuse gastric cancer: association with lobular breast cancer (2008) Fam. Cancer, 7, pp. 73-82; Becker, K.F., Atkinson, M.J., Reich, U., Becker, I., Nekarda, H., Siewert, J.R., Hofler, H., E-cadherin gene mutations provide clues to diffuse type gastric carcinomas (1994) Cancer Res., 54, pp. 3845-3852; Becker, K.F., Kremmer, E., Eulitz, M., Becker, I., Handschuh, G., Schuhmacher, C., Muller, W., Hofler, H., Analysis of E-cadherin in diffuse-type gastric cancer using a mutation-specific monoclonal antibody (1999) Am. J. Pathol., 155, pp. 1803-1809; Machado, J.C., Carneiro, F., Beck, S., Rossi, S., Lopes, J., Taveira-Gomes, A., Cardoso-Oliveira, M., E-cadherin expression is correlated with the isolated cell/diffuse histotype and with features of biological aggressiveness of gastric carcinoma (1998) Int. J. Surg. Pathol., 6, pp. 135-144; Carneiro, F., Machado, J.C., Seruca, R., Sobrinho-Simoes, M., E-cadherin changes in gastric carcimona (1999) Histopathology, 35, pp. 477-478; Carvalho, J., van Grieken, N.C., Pereira, P.M., Sousa, S., Tijssen, M., Buffart, T.E., Diosdado, B., Oliveira, C., Lack of microRNA-101 causes E-cadherin functional deregulation through EZH2 upregulation in intestinal gastric cancer (2012) J. Pathol.; Machado, J.C., Oliveira, C., Carvalho, R., Soares, P., Berx, G., Caldas, C., Seruca, R., Sobrinho-Simoes, M., E-cadherin gene (CDH1) promoter methylation as the second hit in sporadic diffuse gastric carcinoma (2001) Oncogene, 20, pp. 1525-1528; Guilford, P., Hopkins, J., Harraway, J., McLeod, M., McLeod, N., Harawira, P., Taite, H., Reeve, A.E., E-cadherin germline mutations in familial gastric cancer (1998) Nature, 392, pp. 402-405; Oliveira, C., Senz, J., Kaurah, P., Pinheiro, H., Sanges, R., Haegert, A., Corso, G., Huntsman, D., Germline CDH1 deletions in hereditary diffuse gastric cancer families (2009) Hum. Mol. Genet., 18, pp. 1545-1555; Pinheiro, H., Bordeira-Carrico, R., Seixas, S., Carvalho, J., Senz, J., Oliveira, P., Inacio, P., Oliveira, C., Allele-specific CDH1 downregulation and hereditary diffuse gastric cancer (2010) Hum. Mol. Genet., 19, pp. 943-952; Guilford, P., Humar, B., Blair, V., Hereditary diffuse gastric cancer: translation of CDH1 germline mutations into clinical practice (2010) Gastric Cancer, 13, pp. 1-10; Suriano, G., Seixas, S., Rocha, J., Seruca, R., A model to infer the pathogenic significance of CDH1 germline missense variants (2006) J. Mol. Med., 84, pp. 1023-1031; Suriano, G., Oliveira, C., Ferreira, P., Machado, J.C., Bordin, M.C., De Wever, O., Bruyneel, E.A., Seruca, R., Identification of CDH1 germline missense mutations associated with functional inactivation of the E-cadherin protein in young gastric cancer probands (2003) Hum. Mol. Genet., 12, pp. 575-582; Suriano, G., Oliveira, M.J., Huntsman, D., Mateus, A.R., Ferreira, P., Casares, F., Oliveira, C., Seruca, R., E-cadherin germline missense mutations and cell phenotype: evidence for the independence of cell invasion on the motile capabilities of the cells (2003) Hum. Mol. Genet., 12, pp. 3007-3016; Brooks-Wilson, A.R., Kaurah, P., Suriano, G., Leach, S., Senz, J., Grehan, N., Butterfield, Y.S., Huntsman, D., Germline E-cadherin mutations in hereditary diffuse gastric cancer: assessment of 42 new families and review of genetic screening criteria (2004) J. Med. Genet., 41, pp. 508-517; Kaurah, P., MacMillan, A., Boyd, N., Senz, J., De Luca, A., Chun, N., Suriano, G., Huntsman, D., Founder and recurrent CDH1 mutations in families with hereditary diffuse gastric cancer (2007) JAMA, 297, pp. 2360-2372; Corso, G., Roviello, F., Paredes, J., Pedrazzani, C., Novais, M., Correia, J., Marrelli, D., Suriano, G., Characterization of the P373L E-cadherin germline missense mutation and implication for clinical management (2007) Eur. J. Surg. Oncol., 33, pp. 1061-1067; More, H., Humar, B., Weber, W., Ward, R., Christian, A., Lintott, C., Graziano, F., Guilford, P., Identification of seven novel germline mutations in the human E-cadherin (CDH1) gene (2007) Hum. Mutat., 28, p. 203; Oliveira, C., de Bruin, J., Nabais, S., Ligtenberg, M., Moutinho, C., Nagengast, F.M., Seruca, R., Carneiro, F., Intragenic deletion of CDH1 as the inactivating mechanism of the wild-type allele in an HDGC tumour (2004) Oncogene, 23, pp. 2236-2240; Barber, M., Murrell, A., Ito, Y., Maia, A.T., Hyland, S., Oliveira, C., Save, V., Fitzgerald, R.C., Mechanisms and sequelae of E-cadherin silencing in hereditary diffuse gastric cancer (2008) J. Pathol., 216, pp. 295-306; Oliveira, C., Sousa, S., Pinheiro, H., Karam, R., Bordeira-Carrico, R., Senz, J., Kaurah, P., Seruca, R., Quantification of epigenetic and genetic 2nd hits in CDH1 during hereditary diffuse gastric cancer syndrome progression (2009) Gastroenterology, 136, pp. 2137-2148; Grady, W.M., Willis, J., Guilford, P.J., Dunbier, A.K., Toro, T.T., Lynch, H., Wiesner, G., Markowitz, S., Methylation of the CDH1 promoter as the second genetic hit in hereditary diffuse gastric cancer (2000) Nat. Genet., 26, pp. 16-17; Peinado, H., Ballestar, E., Esteller, M., Cano, A., Snail mediates E-cadherin repression by the recruitment of the Sin3A/histone deacetylase 1 (HDAC1)/HDAC2 complex (2004) Mol. Cell. Biol., 24, pp. 306-319; Fujii, S., Ochiai, A., Enhancer of zeste homolog 2 downregulates E-cadherin by mediating histone H3 methylation in gastric cancer cells (2008) Cancer Sci., 99, pp. 738-746; Cao, Q., Yu, J., Dhanasekaran, S.M., Kim, J.H., Mani, R.S., Tomlins, S.A., Mehra, R., Chinnaiyan, A.M., Repression of E-cadherin by the polycomb group protein EZH2 in cancer (2008) Oncogene, 27, pp. 7274-7284; Pena, C., Garcia, J.M., Silva, J., Garcia, V., Rodriguez, R., Alonso, I., Millan, I., Bonilla, F., E-cadherin and vitamin D receptor regulation by SNAIL and ZEB1 in colon cancer: clinicopathological correlations (2005) Hum. Mol. Genet., 14, pp. 3361-3370; Liu, Y., Hong, Y., Zhao, Y., Ismail, T.M., Wong, Y., Eu, K.W., Histone H3 (lys-9) deacetylation is associated with transcriptional silencing of E-cadherin in colorectal cancer cell lines (2008) Cancer Invest., 26, pp. 575-582; von Burstin, J., Eser, S., Paul, M.C., Seidler, B., Brandl, M., Messer, M., von Werder, A., Saur, D., E-cadherin regulates metastasis of pancreatic cancer in vivo and is suppressed by a SNAIL/HDAC1/HDAC2 repressor complex (2009) Gastroenterology, 137, pp. 361-371. , (371 e361-365); Herranz, N., Pasini, D., Diaz, V.M., Franci, C., Gutierrez, A., Dave, N., Escriva, M., Peiro, S., Polycomb complex 2 is required for E-cadherin repression by the Snail1 transcription factor (2008) Mol. Cell. Biol., 28, pp. 4772-4781; Ambros, V., The functions of animal microRNAs (2004) Nature, 431, pp. 350-355; He, L., Hannon, G.J., MicroRNAs: small RNAs with a big role in gene regulation (2004) Nat. Rev. Genet., 5, pp. 522-531; Hurteau, G.J., Carlson, J.A., Spivack, S.D., Brock, G.J., Overexpression of the microRNA hsa-miR-200c leads to reduced expression of transcription factor 8 and increased expression of E-cadherin (2007) Cancer Res., 67, pp. 7972-7976; Korpal, M., Lee, E.S., Hu, G., Kang, Y., The miR-200 family inhibits epithelial-mesenchymal transition and cancer cell migration by direct targeting of E-cadherin transcriptional repressors ZEB1 and ZEB2 (2008) J. Biol. Chem., 283, pp. 14910-14914; Gregory, P.A., Bert, A.G., Paterson, E.L., Barry, S.C., Tsykin, A., Farshid, G., Vadas, M.A., Goodall, G.J., The miR-200 family and miR-205 regulate epithelial to mesenchymal transition by targeting ZEB1 and SIP1 (2008) Nat. Cell Biol., 10, pp. 593-601; Park, S.M., Gaur, A.B., Lengyel, E., Peter, M.E., The miR-200 family determines the epithelial phenotype of cancer cells by targeting the E-cadherin repressors ZEB1 and ZEB2 (2008) Genes Dev., 22, pp. 894-907; Tan, H.X., Wang, Q., Chen, L.Z., Huang, X.H., Chen, J.S., Fu, X.H., Cao, L.Q., Zhang, L.J., MicroRNA-9 reduces cell invasion and E-cadherin secretion in SK-Hep-1 cell (2010) Med. Oncol., 27, pp. 654-660; Ma, L., Young, J., Prabhala, H., Pan, E., Mestdagh, P., Muth, D., Teruya-Feldstein, J., Weinberg, R.A., MiR-9, a MYC/MYCN-activated microRNA, regulates E-cadherin and cancer metastasis (2010) Nat. Cell Biol., 12, pp. 247-256; Oki, Y., Issa, J.P., Epigenetic mechanisms in AML-a target for therapy (2010) Cancer Treat. Res., 145, pp. 19-40; Simoes-Correia, J., Figueiredo, J., Oliveira, C., van Hengel, J., Seruca, R., van Roy, F., Suriano, G., Endoplasmic reticulum quality control: a new mechanism of E-cadherin regulation and its implication in cancer (2008) Hum. Mol. Genet., 17, pp. 3566-3576; Sitia, R., Braakman, I., Quality control in the endoplasmic reticulum protein factory (2003) Nature, 426, pp. 891-894; Meusser, B., Hirsch, C., Jarosch, E., Sommer, T., ERAD: the long road to destruction (2005) Nat. Cell Biol., 7, pp. 766-772; van Hengel, J., van Roy, F., Diverse functions of p120ctn in tumors (2007) Biochim. Biophys. Acta, 1773, pp. 78-88; Jawhari, A.U., Noda, M., Pignatelli, M., Farthing, M., Up-regulated cytoplasmic expression, with reduced membranous distribution, of the src substrate p120(ctn) in gastric carcinoma (1999) J. Pathol., 189, pp. 180-185; Karayiannakis, A.J., Syrigos, K.N., Alexiou, D., Kalahanis, N., Rosenberg, T., Bastounis, E., Pignatelli, M., Expression patterns of the novel catenin p120cas in gastrointestinal cancers (1999) Anticancer. Res., 19, pp. 4401-4405; Karatzas, G., Karayiannakis, A.J., Syrigos, K.N., Chatzigianni, E., Papanikolaou, S., Simatos, G., Papanikolaou, D., Bogris, S., Expression patterns of the E-cadherin-catenin cell-cell adhesion complex in gastric cancer (2000) Hepatogastroenterology, 47, pp. 1465-1469; Apweiler, R., Hermjakob, H., Sharon, N., On the frequency of protein glycosylation, as deduced from analysis of the SWISS-PROT database (1999) Biochim. Biophys. Acta, 1473, pp. 4-8; Dube, D.H., Bertozzi, C.R., Glycans in cancer and inflammation-potential for therapeutics and diagnostics (2005) Nat. Rev. Drug Discov., 4, pp. 477-488; Pinho, S.S., Osorio, H., Nita-Lazar, M., Gomes, J., Lopes, C., Gartner, F., Reis, C.A., Role of E-cadherin N-glycosylation profile in a mammary tumor model (2009) Biochem. Biophys. Res. Commun., 379, pp. 1091-1096; Iijima, J., Zhao, Y., Isaji, T., Kameyama, A., Nakaya, S., Wang, X., Ihara, H., Gu, J., Cell-cell interaction-dependent regulation of N-acetylglucosaminyltransferase III and the bisected N-glycans in GE11 epithelial cells. Involvement of E-cadherin-mediated cell adhesion (2006) J. Biol. Chem., 281, pp. 13038-13046; Yoshimura, M., Ihara, Y., Matsuzawa, Y., Taniguchi, N., Aberrant glycosylation of E-cadherin enhances cell-cell binding to suppress metastasis (1996) J. Biol. Chem., 271, pp. 13811-13815; Giles, R.H., van Es, J.H., Clevers, H., Caught up in a Wnt storm: Wnt signaling in cancer (2003) Biochim. Biophys. Acta, 1653, pp. 1-24; Reynolds, A.B., Roczniak-Ferguson, A., Emerging roles for p120-catenin in cell adhesion and cancer (2004) Oncogene, 23, pp. 7947-7956; Christofori, G., Changing neighbours, changing behaviour: cell adhesion molecule-mediated signalling during tumour progression (2003) EMBO J., 22, pp. 2318-2323; Gottardi, C.J., Wong, E., Gumbiner, B.M., E-cadherin suppresses cellular transformation by inhibiting beta-catenin signaling in an adhesion-independent manner (2001) J. Cell Biol., 153, pp. 1049-1060; Stockinger, A., Eger, A., Wolf, J., Beug, H., Foisner, R., E-cadherin regulates cell growth by modulating proliferation-dependent beta-catenin transcriptional activity (2001) J. Cell Biol., 154, pp. 1185-1196; Suriano, G., Mulholland, D., de Wever, O., Ferreira, P., Mateus, A.R., Bruyneel, E., Nelson, C.C., Seruca, R., The intracellular E-cadherin germline mutation V832 M lacks the ability to mediate cell-cell adhesion and to suppress invasion (2003) Oncogene, 22, pp. 5716-5719; Sahai, E., Marshall, C.J., RHO-GTPases and cancer (2002) Nat. Rev. Cancer, 2, pp. 133-142; Deplazes, J., Fuchs, M., Rauser, S., Genth, H., Lengyel, E., Busch, R., Luber, B., Rac1 and Rho contribute to the migratory and invasive phenotype associated with somatic E-cadherin mutation (2009) Hum. Mol. Genet., 18, pp. 3632-3644; Mateus, A.R., Seruca, R., Machado, J.C., Keller, G., Oliveira, M.J., Suriano, G., Luber, B., EGFR regulates RhoA-GTP dependent cell motility in E-cadherin mutant cells (2007) Hum. Mol. Genet., 16, pp. 1639-1647; Mateus, A.R., Simoes-Correia, J., Figueiredo, J., Heindl, S., Alves, C.C., Suriano, G., Luber, B., Seruca, R., E-cadherin mutations and cell motility: a genotype-phenotype correlation (2009) Exp. Cell Res., 315, pp. 1393-1402; Crepaldi, T., Pollack, A.L., Prat, M., Zborek, A., Mostov, K., Comoglio, P.M., Targeting of the SF/HGF receptor to the basolateral domain of polarized epithelial cells (1994) J. Cell Biol., 125, pp. 313-320; Pece, S., Gutkind, J.S., Signaling from E-cadherins to the MAPK pathway by the recruitment and activation of epidermal growth factor receptors upon cell-cell contact formation (2000) J. Biol. Chem., 275, pp. 41227-41233; Thiery, J.P., Epithelial-mesenchymal transitions in tumour progression (2002) Nat. Rev. Cancer, 2, pp. 442-454; Qian, X., Karpova, T., Sheppard, A.M., McNally, J., Lowy, D.R., E-cadherin-mediated adhesion inhibits ligand-dependent activation of diverse receptor tyrosine kinases (2004) EMBO J., 23, pp. 1739-1748; Takahashi, K., Suzuki, K., Density-dependent inhibition of growth involves prevention of EGF receptor activation by E-cadherin-mediated cell-cell adhesion (1996) Exp. Cell Res., 226, pp. 214-222; Mook, O.R., Frederiks, W.M., Van Noorden, C.J., The role of gelatinases in colorectal cancer progression and metastasis (2004) Biochim. Biophys. Acta, 1705, pp. 69-89; Munshi, H.G., Ghosh, S., Mukhopadhyay, S., Wu, Y.I., Sen, R., Green, K.J., Stack, M.S., Proteinase suppression by E-cadherin-mediated cell-cell attachment in premalignant oral keratinocytes (2002) J. Biol. Chem., 277, pp. 38159-38167; Lochter, A., Galosy, S., Muschler, J., Freedman, N., Werb, Z., Bissell, M.J., Matrix metalloproteinase stromelysin-1 triggers a cascade of molecular alterations that leads to stable epithelial-to-mesenchymal conversion and a premalignant phenotype in mammary epithelial cells (1997) J. Cell Biol., 139, pp. 1861-1872; Davies, G., Jiang, W.G., Mason, M.D., Matrilysin mediates extracellular cleavage of E-cadherin from prostate cancer cells: a key mechanism in hepatocyte growth factor/scatter factor-induced cell-cell dissociation and in vitro invasion (2001) Clin. Cancer Res., 7, pp. 3289-3297; Noe, V., Fingleton, B., Jacobs, K., Crawford, H.C., Vermeulen, S., Steelant, W., Bruyneel, E., Mareel, M., Release of an invasion promoter E-cadherin fragment by matrilysin and stromelysin-1 (2001) J. Cell Sci., 114, pp. 111-118; Ryniers, F., Stove, C., Goethals, M., Brackenier, L., Noe, V., Bracke, M., Vandekerckhove, J., Bruyneel, E., Plasmin produces an E-cadherin fragment that stimulates cancer cell invasion (2002) Biol. Chem., 383, pp. 159-165; Comoglio, P.M., Boccaccio, C., Trusolino, L., Interactions between growth factor receptors and adhesion molecules: breaking the rules (2003) Curr. Opin. Cell Biol., 15, pp. 565-571; Ferreira, P., Oliveira, M.J., Beraldi, E., Mateus, A.R., Nakajima, T., Gleave, M., Yokota, J., Suriano, G., Loss of functional E-cadherin renders cells more resistant to the apoptotic agent taxol in vitro (2005) Exp. Cell Res., 310, pp. 99-104; Ferreira, A.C., Suriano, G., Mendes, N., Gomes, B., Wen, X., Carneiro, F., Seruca, R., Machado, J.C., E-cadherin impairment increases cell survival through Notch-dependent upregulation of Bcl-2 (2012) Hum. Mol. Genet., 21, pp. 334-343; Huang, F.Y., Chan, A.O., Rashid, A., Wong, D.K., Cho, C.H., Yuen, M.F., Helicobacter pylori induces promoter methylation of E-cadherin via interleukin-1beta activation of nitric oxide production in gastric cancer cells (2012) Cancer; Chan, A.O., Lam, S.K., Wong, B.C., Wong, W.M., Yuen, M.F., Yeung, Y.H., Hui, W.M., Kwong, Y.L., Promoter methylation of E-cadherin gene in gastric mucosa associated with Helicobacter pylori infection and in gastric cancer (2003) Gut, 52, pp. 502-506; Leung, W.K., Man, E.P., Yu, J., Go, M.Y., To, K.F., Yamaoka, Y., Cheng, V.Y., Sung, J.J., Effects of Helicobacter pylori eradication on methylation status of E-cadherin gene in noncancerous stomach (2006) Clin. Cancer Res., 12, pp. 3216-3221; Perri, F., Cotugno, R., Piepoli, A., Merla, A., Quitadamo, M., Gentile, A., Pilotto, A., Andriulli, A., Aberrant DNA methylation in non-neoplastic gastric mucosa of H. pylori infected patients and effect of eradication (2007) Am. J. Gastroenterol., 102, pp. 1361-1371; Chan, A.O., Peng, J.Z., Lam, S.K., Lai, K.C., Yuen, M.F., Cheung, H.K., Kwong, Y.L., Wong, B.C., Eradication of Helicobacter pylori infection reverses E-cadherin promoter hypermethylation (2006) Gut, 55, pp. 463-468; Schirrmeister, W., Gnad, T., Wex, T., Higashiyama, S., Wolke, C., Naumann, M., Lendeckel, U., Ectodomain shedding of E-cadherin and c-Met is induced by Helicobacter pylori infection (2009) Exp. Cell Res., 315, pp. 3500-3508; Hoy, B., Lower, M., Weydig, C., Carra, G., Tegtmeyer, N., Geppert, T., Schroder, P., Wessler, S., Helicobacter pylori HtrA is a new secreted virulence factor that cleaves E-cadherin to disrupt intercellular adhesion (2010) EMBO Rep., 11, pp. 798-804; O'Connor, P.M., Lapointe, T.K., Jackson, S., Beck, P.L., Jones, N.L., Buret, A.G., Helicobacter pylori activates calpain via toll-like receptor 2 to disrupt adherens junctions in human gastric epithelial cells (2011) Infect. Immun., 79, pp. 3887-3894; Conlin, V.S., Curtis, S.B., Zhao, Y., Moore, E.D., Smith, V.C., Meloche, R.M., Finlay, B.B., Buchan, A.M., Helicobacter pylori infection targets adherens junction regulatory proteins and results in increased rates of migration in human gastric epithelial cells (2004) Infect. Immun., 72, pp. 5181-5192; Suzuki, M., Mimuro, H., Suzuki, T., Park, M., Yamamoto, T., Sasakawa, C., Interaction of CagA with Crk plays an important role in Helicobacter pylori-induced loss of gastric epithelial cell adhesion (2005) J. Exp. Med., 202, pp. 1235-1247; Franco, A.T., Israel, D.A., Washington, M.K., Krishna, U., Fox, J.G., Rogers, A.B., Neish, A.S., Peek, R.M., Activation of beta-catenin by carcinogenic Helicobacter pylori (2005) Proc. Natl. Acad. Sci. U. S. A., 102, pp. 10646-10651; Murata-Kamiya, N., Kurashima, Y., Teishikata, Y., Yamahashi, Y., Saito, Y., Higashi, H., Aburatani, H., Hatakeyama, M., Helicobacter pylori CagA interacts with E-cadherin and deregulates the beta-catenin signal that promotes intestinal transdifferentiation in gastric epithelial cells (2007) Oncogene, 26, pp. 4617-4626; Sokolova, O., Bozko, P.M., Naumann, M., Helicobacter pylori suppresses glycogen synthase kinase 3beta to promote beta-catenin activity (2008) J. Biol. Chem., 283, pp. 29367-29374; Ogden, S.R., Wroblewski, L.E., Weydig, C., Romero-Gallo, J., O'Brien, D.P., Israel, D.A., Krishna, U.S., Peek, R.M., P120 and Kaiso regulate Helicobacter pylori-induced expression of matrix metalloproteinase-7 (2008) Mol. Biol. Cell, 19, pp. 4110-4121; Bebb, J.R., Leach, L., Zaitoun, A., Hand, N., Letley, D.P., Thomas, R., Atherton, J.C., Effects of Helicobacter pylori on the cadherin-catenin complex (2006) J. Clin. Pathol., 59, pp. 1261-1266; Oliveira, M.J., Costa, A.M., Costa, A.C., Ferreira, R.M., Sampaio, P., Machado, J.C., Seruca, R., Figueiredo, C., CagA associates with c-Met, E-cadherin, and p120-catenin in a multiproteic complex that suppresses Helicobacter pylori-induced cell-invasive phenotype (2009) J. Infect. Dis., 200, pp. 745-755; Oliveira, M.J., Costa, A.C., Costa, A.M., Henriques, L., Suriano, G., Atherton, J.C., Machado, J.C., Figueiredo, C., Helicobacter pylori induces gastric epithelial cell invasion in a c-Met and type IV secretion system-dependent manner (2006) J. Biol. Chem., 281, pp. 34888-34896; Jang, A.C., Starz-Gaiano, M., Montell, D.J., Modeling migration and metastasis in Drosophila (2007) J. Mammary Gland Biol. Neoplasia, 12, pp. 103-114; Pereira, P.S., Teixeira, A., Pinho, S., Ferreira, P., Fernandes, J., Oliveira, C., Seruca, R., Casares, F., E-cadherin missense mutations, associated with hereditary diffuse gastric cancer (HDGC) syndrome, display distinct invasive behaviors and genetic interactions with the Wnt and Notch pathways in Drosophila epithelia (2006) Hum. Mol. Genet., 15, pp. 1704-1712; Caldeira, J., Pereira, P.S., Suriano, G., Casares, F., Using fruitflies to help understand the molecular mechanisms of human hereditary diffuse gastric cancer (2009) Int. J. Dev. Biol., 53, pp. 1557-1561; Humar, B., Blair, V., Charlton, A., More, H., Martin, I., Guilford, P., E-cadherin deficiency initiates gastric signet-ring cell carcinoma in mice and man (2009) Cancer Res., 69, pp. 2050-2056; Mbalaviele, G., Dunstan, C.R., Sasaki, A., Williams, P.J., Mundy, G.R., Yoneda, T., E-cadherin expression in human breast cancer cells suppresses the development of osteolytic bone metastases in an experimental metastasis model (1996) Cancer Res., 56, pp. 4063-4070; Perl, A.K., Wilgenbus, P., Dahl, U., Semb, H., Christofori, G., A causal role for E-cadherin in the transition from adenoma to carcinoma (1998) Nature, 392, pp. 190-193; Kuwabara, Y., Yamada, T., Yamazaki, K., Du, W.L., Banno, K., Aoki, D., Sakamoto, M., Establishment of an ovarian metastasis model and possible involvement of E-cadherin down-regulation in the metastasis (2008) Cancer Sci., 99, pp. 1933-1939; Shimoyama, Y., Hirohashi, S., Hirano, S., Noguchi, M., Shimosato, Y., Takeichi, M., Abe, O., Cadherin cell-adhesion molecules in human epithelial tissues and carcinomas (1989) Cancer Res., 49, pp. 2128-2133; Sanders, D.S., Bruton, R., Darnton, S.J., Casson, A.G., Hanson, I., Williams, H.K., Jankowski, J., Sequential changes in cadherin-catenin expression associated with the progression and heterogeneity of primary oesophageal squamous carcinoma (1998) Int. J. Cancer, 79, pp. 573-579; Rocha, A.S., Soares, P., Machado, J.C., Maximo, V., Fonseca, E., Franssila, K., Sobrinho-Simoes, M., Mucoepidermoid carcinoma of the thyroid: a tumour histotype characterised by P-cadherin neoexpression and marked abnormalities of E-cadherin/catenins complex (2002) Virchows Arch., 440, pp. 498-504; Kim, M.A., Jung, E.J., Lee, H.S., Lee, H.E., Yang, H.K., Oh, D.Y., Bang, Y.J., Kim, W.H., P-cadherin expression in gastric carcinoma: its regulation mechanism and prognostic significance (2010) Hum. Pathol., 41, pp. 877-885; Imai, K., Hirata, S., Irie, A., Senju, S., Ikuta, Y., Yokomine, K., Harao, M., Nishimura, Y., Identification of a novel tumor-associated antigen, cadherin 3/P-cadherin, as a possible target for immunotherapy of pancreatic, gastric, and colorectal cancers (2008) Clin. Cancer Res., 14, pp. 6487-6495; Lo Muzio, L., Campisi, G., Farina, A., Rubini, C., Pannone, G., Serpico, R., Laino, G., Carinci, F., P-cadherin expression and survival rate in oral squamous cell carcinoma: an immunohistochemical study (2005) BMC Cancer, 5, p. 63; Han, A.C., Edelson, M.I., Peralta Soler, A., Knudsen, K.A., Lifschitz-Mercer, B., Czernobilsky, B., Rosenblum, N.G., Salazar, H., Cadherin expression in glandular tumors of the cervix (2000) Cancer, 89, pp. 2053-2058; Longatto Filho, A., Albergaria, A., Paredes, J., Moreira, M.A., Milanezi, F., Schmitt, F.C., P-cadherin expression in glandular lesions of the uterine cervix detected by liquid-based cytology (2005) Cytopathology, 16, pp. 88-93; Stefansson, I.M., Salvesen, H.B., Akslen, L.A., Prognostic impact of alterations in P-cadherin expression and related cell adhesion markers in endometrial cancer (2004) J. Clin. Oncol., 22, pp. 1242-1252; Moreno-Bueno, G., Hardisson, D., Sarrio, D., Sanchez, C., Cassia, R., Prat, J., Herman, J.G., Palacios, J., Abnormalities of E- and P-cadherin and catenin (beta-, gamma-catenin, and p120ctn) expression in endometrial cancer and endometrial atypical hyperplasia (2003) J. Pathol., 199, pp. 471-478; Quattrocchi, L., Green, A.R., Martin, S., Durrant, L., Deen, S., The cadherin switch in ovarian high-grade serous carcinoma is associated with disease progression (2011) Virchows Arch., 459, pp. 21-29; Sarrio, D., Moreno-Bueno, G., Sanchez-Estevez, C., Banon-Rodriguez, I., Hernandez-Cortes, G., Hardisson, D., Palacios, J., Expression of cadherins and catenins correlates with distinct histologic types of ovarian carcinomas (2006) Hum. Pathol., 37, pp. 1042-1049; Soler, A.P., Harner, G.D., Knudsen, K.A., McBrearty, F.X., Grujic, E., Salazar, H., Han, A.C., Keshgegian, A.A., Expression of P-cadherin identifies prostate-specific-antigen-negative cells in epithelial tissues of male sexual accessory organs and in prostatic carcinomas. Implications for prostate cancer biology (1997) Am. J. Pathol., 151, pp. 471-478; Bryan, R.T., Atherfold, P.A., Yeo, Y., Jones, L.J., Harrison, R.F., Wallace, D.M., Jankowski, J.A., Cadherin switching dictates the biology of transitional cell carcinoma of the bladder: ex vivo and in vitro studies (2008) J. Pathol., 215, pp. 184-194; Matos, I., Dufloth, R., Alvarenga, M., Zeferino, L.C., Schmitt, F., P63, cytokeratin 5, and P-cadherin: three molecular markers to distinguish basal phenotype in breast carcinomas (2005) Virchows Arch., 447, pp. 688-694; Arnes, J.B., Brunet, J.S., Stefansson, I., Begin, L.R., Wong, N., Chappuis, P.O., Akslen, L.A., Foulkes, W.D., Placental cadherin and the basal epithelial phenotype of BRCA1-related breast cancer (2005) Clin. Cancer Res., 11, pp. 4003-4011; Palacios, J., Benito, N., Pizarro, A., Suarez, A., Espada, J., Cano, A., Gamallo, C., Anomalous expression of P-cadherin in breast carcinoma. Correlation with E-cadherin expression and pathological features (1995) Am. J. Pathol., 146, pp. 605-612; Peralta Soler, A., Knudsen, K.A., Salazar, H., Han, A.C., Keshgegian, A.A., P-cadherin expression in breast carcinoma indicates poor survival (1999) Cancer, 86, pp. 1263-1272; Paredes, J., Milanezi, F., Reis-Filho, J.S., Leitao, D., Athanazio, D., Schmitt, F., Aberrant P-cadherin expression: is it associated with estrogen-independent growth in breast cancer? (2002) Pathol. Res. Pract., 198, pp. 795-801; Kovacs, A., Dhillon, J., Walker, R.A., Expression of P-cadherin, but not E-cadherin or N-cadherin, relates to pathological and functional differentiation of breast carcinomas (2003) Mol. Pathol., 56, pp. 318-322; Gamallo, C., Moreno-Bueno, G., Sarrio, D., Calero, F., Hardisson, D., Palacios, J., The prognostic significance of P-cadherin in infiltrating ductal breast carcinoma (2001) Mod. Pathol., 14, pp. 650-654; Paredes, J., Correia, A.L., Ribeiro, A.S., Milanezi, F., Cameselle-Teijeiro, J., Schmitt, F.C., Breast carcinomas that co-express E- and P-cadherin are associated with p120-catenin cytoplasmic localisation and poor patient survival (2008) J. Clin. Pathol., 61, pp. 856-862; Foulkes, W.D., Stefansson, I.M., Chappuis, P.O., Begin, L.R., Goffin, J.R., Wong, N., Trudel, M., Akslen, L.A., Germline BRCA1 mutations and a basal epithelial phenotype in breast cancer (2003) J. Natl. Cancer Inst., 95, pp. 1482-1485; Lakhani, S.R., Reis-Filho, J.S., Fulford, L., Penault-Llorca, F., van der Vijver, M., Parry, S., Bishop, T., Easton, D.F., Prediction of BRCA1 status in patients with breast cancer using estrogen receptor and basal phenotype (2005) Clin. Cancer Res., 11, pp. 5175-5180; Palacios, J., Honrado, E., Osorio, A., Cazorla, A., Sarrio, D., Barroso, A., Rodriguez, S., Benitez, J., Immunohistochemical characteristics defined by tissue microarray of hereditary breast cancer not attributable to BRCA1 or BRCA2 mutations: differences from breast carcinomas arising in BRCA1 and BRCA2 mutation carriers (2003) Clin. Cancer Res., 9, pp. 3606-3614; Palacios, J., Honrado, E., Osorio, A., Cazorla, A., Sarrio, D., Barroso, A., Rodriguez, S., Benitez, J., Phenotypic characterization of BRCA1 and BRCA2 tumors based in a tissue microarray study with 37 immunohistochemical markers (2005) Breast Cancer Res. Treat., 90, pp. 5-14; Gorski, J.J., James, C.R., Quinn, J.E., Stewart, G.E., Staunton, K.C., Buckley, N.E., McDyer, F.A., Harkin, D.P., BRCA1 transcriptionally regulates genes associated with the basal-like phenotype in breast cancer (2010) Breast Cancer Res. Treat., 122, pp. 721-731; Albergaria, A., Ribeiro, A.S., Pinho, S., Milanezi, F., Carneiro, V., Sousa, B., Sousa, S., Schmitt, F., ICI 182,780 induces P-cadherin overexpression in breast cancer cells through chromatin remodelling at the promoter level: a role for C/EBPbeta in CDH3 gene activation (2010) Hum. Mol. Genet., 19, pp. 2554-2566; Sato, N., Fukushima, N., Maitra, A., Matsubayashi, H., Yeo, C.J., Cameron, J.L., Hruban, R.H., Goggins, M., Discovery of novel targets for aberrant methylation in pancreatic carcinoma using high-throughput microarrays (2003) Cancer Res., 63, pp. 3735-3742; Milicic, A., Harrison, L.A., Goodlad, R.A., Hardy, R.G., Nicholson, A.M., Presz, M., Sieber, O., Jankowski, J.A., Ectopic expression of P-cadherin correlates with promoter hypomethylation early in colorectal carcinogenesis and enhanced intestinal crypt fission in vivo (2008) Cancer Res., 68, pp. 7760-7768; Van Marck, V., Stove, C., Van Den Bossche, K., Stove, V., Paredes, J., Vander Haeghen, Y., Bracke, M., P-cadherin promotes cell-cell adhesion and counteracts invasion in human melanoma (2005) Cancer Res., 65, pp. 8774-8783; Sarrio, D., Palacios, J., Hergueta-Redondo, M., Gomez-Lopez, G., Cano, A., Moreno-Bueno, G., Functional characterization of E- and P-cadherin in invasive breast cancer cells (2009) BMC Cancer, 9, p. 74; Bauer, K., Dowejko, A., Bosserhoff, A.K., Reichert, T.E., Bauer, R.J., P-cadherin induces an epithelial-like phenotype in oral squamous cell carcinoma by GSK-3beta-mediated Snail phosphorylation (2009) Carcinogenesis, 30, pp. 1781-1788; Bauer, K., Dowejko, A., Bosserhoff, A.K., Reichert, T.E., Bauer, R., Slit-2 facilitates interaction of P-cadherin with Robo-3 and inhibits cell migration in an oral squamous cell carcinoma cell line (2011) Carcinogenesis, 32, pp. 935-943; Mandeville, J.A., Silva Neto, B., Vanni, A.J., Smith, G.L., Rieger-Christ, K.M., Zeheb, R., Loda, M., Summerhayes, I.C., P-cadherin as a prognostic indicator and a modulator of migratory behaviour in bladder carcinoma cells (2008) BJU Int., 102, pp. 1707-1714; Cheung, L.W., Leung, P.C., Wong, A.S., Cadherin switching and activation of p120 catenin signaling are mediators of gonadotropin-releasing hormone to promote tumor cell migration and invasion in ovarian cancer (2010) Oncogene, 29, pp. 2427-2440; Reynolds, A.B., Daniel, J.M., Mo, Y.Y., Wu, J., Zhang, Z., The novel catenin p120cas binds classical cadherins and induces an unusual morphological phenotype in NIH3T3 fibroblasts (1996) Exp. Cell Res., 225, pp. 328-337; Baki, L., Marambaud, P., Efthimiopoulos, S., Georgakopoulos, A., Wen, P., Cui, W., Shioi, J., Robakis, N.K., Presenilin-1 binds cytoplasmic epithelial cadherin, inhibits cadherin/p120 association, and regulates stability and function of the cadherin/catenin adhesion complex (2001) Proc. Natl. Acad. Sci. U. S. A., 98, pp. 2381-2386; Jacobs, K., Van Gele, M., Forsyth, R., Brochez, L., Vanhoecke, B., De Wever, O., Bracke, M., P-cadherin counteracts myosin II-B function: implications in melanoma progression (2010) Mol. Cancer, 9, p. 255; Radice, G.L., Sauer, C.L., Kostetskii, I., Peralta Soler, A., Knudsen, K.A., Inappropriate P-cadherin expression in the mouse mammary epithelium is compatible with normal mammary gland function (2003) Differentiation, 71, pp. 361-373; Gregory, D.J., Mikhaylova, L., Fedulov, A.V., Selective DNA demethylation by fusion of TDG with a sequence-specific DNA-binding domain (2012) Epigenetics, 7; Zhang, C.C., Yan, Z., Zhang, Q., Kuszpit, K., Zasadny, K., Qiu, M., Painter, C.L., VanArsdale, T., PF-03732010: a fully human monoclonal antibody against P-cadherin with antitumor and antimetastatic activity (2010) Clin. Cancer Res., 16, pp. 5177-5188
Keywords: antineoplastic activity; antineoplastic agent; Breast; breast cancer; Cancer; cancer chemotherapy; cancer model; cancer survival; drug effect; E-cadherin; Gastric; gene expression regulation; gene function; gene location; gene overexpression; gene structure; genetic association; genetic code; Helicobacter infection; Hereditary diffuse gastric cancer; human; in vivo study; loss of function mutation; lymph node metastasis; malignant neoplastic disease; molecular dynamics; molecular pathology; molecularly targeted therapy; nonhuman; P cadherin; P cadherin gene; P-cadherin; pf 03732010; priority journal; protein expression; protein function; protein inhibitor; protein processing; review; signal transduction; stomach cancer; transcription regulation; tumor gene; unclassified drug; uvomorulin; uvomorulin gene; vasculotropin inhibitor

(Gd,Yb,Tb)PO 4 up-conversion nanocrystals for bimodal luminescence-MR imaging - Debasu, M.L.; Ananias, D.; Pinho, S.L.C.; Geraldes, C.F.G.C.; Carlos, L.D.; Rocha, J. (NanoscaleNanoscale, 2012)
Up-conversion (Gd,Yb,Tb)PO 4 materials and their potential for bimodal imaging have received little attention in the literature. Herein, we report the first study on the up-conversion emission of (Gd,Yb,Tb)PO 4 nanocrystals synthesized via a hydrothermal method at 150°C. These materials exhibit ultraviolet, blue and green up-conversion emissions upon excitation with a 980 nm continuous wave laser diode. The intensity of the blue-emission band at 479 nm, ascribed to the cooperative up-conversion emission of a pair of excited Yb 3+ ions, depends on the Yb 3+/Tb 3+ concentration ratio, calcination temperature and particle size. Strong green up-conversion emission of Tb 3+ is observed at 543 nm for the 5D 4 → 7F 5 transition. Relaxometry measurements reveal that the nanocrystals are efficient T 2-weighted (negative) contrast agents which, combined with visible-light emission generated by infrared excitation, affords them considerable potential for being used in bimodal, photoluminescence-magnetic resonance, imaging. © 2012 The Royal Society of Chemistry.
Keywords: Blue-emission; Calcination; Calcination temperature; Concentration ratio; Continuous wave lasers; Contrast agent; Gadolinium; Hydrothermal methods; Infrared excitation; Magnetic resonance; Magnetic resonance imaging; Nanocrystals; Relaxometry; Up-conversion; Up-conversion emission; Visible light; Ytterbium

Interactions of microbicide nanoparticles with a simulated vaginal fluid - Das Neves, J.; Rocha, C.M.R.; Gonçalves, M.P.; Carrier, R.L.; Amiji, M.; Bahia, M.F.; Sarmento, B. (Molecular PharmaceuticsMol. Pharm., 2012)
The interaction with cervicovaginal mucus presents the potential to impact the performance of drug nanocarriers. These systems must migrate through this biological fluid in order to deliver their drug payload to the underlying mucosal surface. We studied the ability of dapivirine-loaded polycaprolactone (PCL)-based nanoparticles (NPs) to interact with a simulated vaginal fluid (SVF) incorporating mucin. Different surface modifiers were used to produce NPs with either negative (poloxamer 338 NF and sodium lauryl sulfate) or positive (cetyltrimethylammonium bromide) surface charge. Studies were performed using the mucin particle method, rheological measurements, and real-time multiple particle tracking. Results showed that SVF presented rheological properties similar to those of human cervicovaginal mucus. Analysis of NP transport indicated mild interactions with mucin and low adhesive potential. In general, negatively charged NPs underwent subdiffusive transport in SVF, i.e., hindered as compared to their diffusion in water, but faster than for positively charged NPs. These differences were increased when the pH of SVF was changed from 4.2 to 7.0. Diffusivity was 50- and 172-fold lower in SVF at pH 4.2 than in water for negatively charged and positively charged NPs, respectively. At pH 7.0, this decrease was around 20- and 385-fold, respectively. The estimated times required to cross a layer of SVF were equal to or lower than 1.7 h for negatively charged NPs, while for positively charged NPs these values were equal to or higher than 7 h. Overall, our results suggest that negatively charged PCL NPs may be suitable to be used as carriers in order to deliver dapivirine and potentially other antiretroviral drugs to the cervicovaginal mucosal lining. Also, they further reinforce the importance in characterizing the interactions of nanosystems with mucus fluids or surrogates when considering mucosal drug delivery. © 2012 American Chemical Society.
Keywords: microbicides; mucin; mucoadhesion; mucosal drug delivery; particle tracking; rheology

Mesenchymal stem cell recruitment by stromal derived factor-1-delivery systems based on chitosan/poly(γ-glutamic acid) polyelectrolyte complexes - Gonçalves, R.M.; Antunes, J.C.; Barbosa, M.A. (European Cells and MaterialsEur. Cells and Mater., 2012)
Human mesenchymal stem cells (hMSCs) have an enormous potential for tissue engineering and cell-based therapies. With a potential of differentiation into multiple lineages and immune-suppression, these cells play a key role in tissue remodelling and regeneration. Here a method of hMSC recruitment is described, based on the incorporation of a chemokine in Chitosan (Ch)/ Poly(γ-glutamic acid) (γ-PGA) complexes. Ch is a nontoxic, cationic polysaccharide widely investigated. γ-PGA is a hydrophilic, non-toxic, biodegradable and negatively charged poly-amino acid. Ch and γ-PGA, being oppositely charged, can be combined through electrostatic interactions. These biocompatible structures can be used as carriers for active substances and can be easily modulated in order to control the delivery of drugs, proteins, DNA, etc. Using the layer-by-layer method, Ch and γ-PGA were assembled into polyelectrolyte multilayers films (PEMs) with thickness of 120 nm. The chemokine stromal-derived factor-1 (SDF-1) was incorporated in these complexes and was continuously released during 120 h. The method of SDF-1 incorporation is of crucial importance for polymers assembly into PEMs and for the release kinetics of this chemokine. The Ch/γ-PGA PEMs with SDF-1 were able to recruit hMSCs, increasing the cell migration up to 6 fold to a maximum of 16.2 ± 4.9 cells/mm 2. The controlled release of SDF-1 would be of great therapeutic value in the process of hMSC homing to injured tissues. This is the first study suggesting Ch/γ-PGA PEMs as SDF-1 reservoirs to recruit hMSCs, describing an efficient method of chemokine incorporation that allows a sustained released up to 5 days and that can be easily scaled-up.
Keywords: adsorption kinetics; article; artificial membrane; Biocompatible Materials; biomaterial; cell differentiation; cell migration; cell motion; Cell Movement; Cell recruitment; chemistry; Chemokine CXCL12; chitosan; controlled study; CXCL12 protein, human; cytology; drug adsorption; drug delivery system; Drug Delivery Systems; drug derivative; drug effect; ellipsometry; enzyme linked immunosorbent assay; human; human cell; human tissue; Humans; in vitro study; isotope labeling; Layer-by-layer; Membranes, Artificial; Mesenchymal stem cell; Mesenchymal Stem Cells; metabolism; methodology; poly(gamma glutamic acid); poly(gamma-glutamic acid); Poly(γ-glutamic acid); polyglutamic acid; Protein delivery; static electricity; stromal cell derived factor 1; sustained drug release

Methamphetamine mimics the neurochemical profile of aging in rats and impairs recognition memory - Melo, P.; Magalhães, A.; Alves, C.J.; Tavares, M.A.; De Sousa, L.; Summavielle, T.; Moradas-Ferreira, P. (NeuroToxicologyNeuroToxicology, 2012)
Brain neurochemistry and cognition performance are thought to decline with age. Accumulating data indicate that similar events occur after prolonged methamphetamine (MA) exposure. Using the rat as a model, the present study was designed to uncover common alteration patterns in brain neurochemistry and memory performance between aging and prolonged MA exposure. To this end, animals were treated with a chronic binge MA administration paradigm (20. mg/kg/day from postnatal day 91 to 100). Three-age control groups received isovolumetric saline treatment and were tested at the MA age-matched period, and at 12 and 20 months. We observed that both MA and aged animals presented a long, but not short, time impairment in novelty preference and an increased anxiety-like behavior. Neurochemical analysis indicated similar MA- and age-related impairments in dopamine, serotonin and metabolites in the striatum, prefrontal cortex and hippocampus. Thus, the present data illustrate that MA may be used to mimic age-related effects on neurotransmitter systems and advocate MA treatment as a feasible animal model to study neuronal processes associated with aging. © 2012 Elsevier Inc.
Keywords: Accelerated aging; Age Factors; aging; animal behavior; animal experiment; animal model; animal tissue; Animalia; Animals; anxiety; article; behavior change; Behavior, Animal; Brain; Brain Chemistry; controlled study; corpus striatum; dopamine; Exploratory Behavior; hippocampus; Hydroxyindoleacetic Acid; long term exposure; male; Memory Disorders; mental performance; Methamphetamine; Neurochemistry; neurotransmission; nonhuman; perinatal drug exposure; prefrontal cortex; priority journal; rat; Rats; Rats, Wistar; Rattus; recognition; Recognition (Psychology); Recognition memory; serotonin; sodium chloride; Time Factors

A model for educational simulation of the evolution of uterine contractions during labor - Bastos, L.F.; van Meurs, W.; Ayres-de-Campos, D. (Computer Methods and Programs in BiomedicineComput. Methods Programs Biomed., 2012)
Electronic fetal monitoring remains an important tool in labor ward settings, providing continuous information on fetal heart rate and maternal uterine contractions. A prompt detection of abnormalities in these signals is essential for the timely resolution of situations that may put both mother and fetus at risk. Uterine contraction signals provide information that is important to evaluate the onset and progress of labor, as well as the significance of certain fetal heart rate abnormalities. We present a model for educational simulation of the spontaneous evolution of uterine contractions during labor, which combines a previously published signal generator with literature-based pre-programmed scripts for educationally relevant scenarios. This model is an essential component of a high-fidelity simulator of intrapartum emergencies, aimed to improve the competency of healthcare providers. Real and simulated tracings were presented to three independent clinical experts who judged simulated signals to be indistinguishable or negligibly different from real tracings. © 2011 Elsevier Ireland Ltd.
Keywords: article; clinical competence; computer memory; computer program; Computer simulation; Computer-Assisted Instruction; controlled study; Educational simulations; Essential component; Female; Fetal heart rate; Fetal monitoring; Health care; Health care providers; High-fidelity simulators; Humans; labor; Labor and delivery; medical education; Medical educational simulation; Models, Biological; Neonatal monitoring; Obstetric Labor Complications; Obstetrics; Pregnancy; Script-controlled simulation; signal detection; Signal generators; Simulated signals; User-Computer Interface; Uterine activities; Uterine activity; Uterine Contraction; Uterine Monitoring; uterus contraction

Osteoporotic hip fractures: Bisphosphonates sales and observed turning point in trend. A population-based retrospective study - Alves, Sandra Maria; Economou, Theodoros; Oliveira, Carla; Ribeiro, Ana Isabel; Neves, Nuno; Goméz-Barrena, Enrique; de Pina, Maria de Fátima (Bone %@ 8756-3282, 2012)

Poor reliability of visual analysis of fetal heart rate tracings: What should be done about it? - Bernardes, J.; Ayres-de-Campos, D. (American Journal of Obstetrics and GynecologyAm. J. Obstet. Gynecol., 2012)
Keywords: accuracy; Cardiotocography; clinical decision making; clinical practice; computer analysis; fetus blood sampling; fetus electrocardiography; fetus heart rate; Heart Rate, Fetal; human; Humans; letter; medical education; metabolic acidosis; newborn disease; priority journal; reliability; visual acuity

Tumor cell-educated periprostatic adipose tissue acquires an aggressive cancer-promoting secretory profile - Ribeiro, R.J.T.; Monteiro, C.P.D.; Cunha, V.F.P.M.; Azevedo, A.S.M.; Oliveira, M.J.; Monteiro, R.; Fraga, A.M.; Príncipe, P.; Lobato, C.; Lobo, F.; Morais, A.; Silva, V.; et al. (Cellular Physiology and BiochemistryCell. Physiol. Biochem., 2012)
Background/Aims: The microenvironment produces important factors that are crucial to prostate cancer (PCa) progression. However, the extent to which the cancer cells stimulate periprostatic adipose tissue (PPAT) to produce these proteins is largely unknown. Our purpose was to determine whether PCa cell-derived factors influence PPAT metabolic activity. Methods: Primary cultures of human PPAT samples from PCa patients (adipose tissue organotypic explants and primary stromal vascular fraction, SVF) were stimulated with conditioned medium (CM) collected from prostate carcinoma (PC3) cells. Cultures without CM were used as control. We used multiplex analysis and ELISA for protein quantification, qPCR to determine mitochondrial DNA (mtDNA) copy number and zymography for matrix metalloproteinase activity, in order to evaluate the response of adipose tissue explants and SVFs to PC3 CM. Results: Stimulation of PPAT explants with PCa PC3 CM induced adipokines associated with cancer progression (osteopontin, tumoral necrosis factor alpha and interleukin-6) and reduced the expression of the protective adipokine adiponectin. Notably, osteopontin protein expression was 13-fold upregulated. Matrix metalloproteinase 9 activity and mitochondrial DNA copy number were higher after stimulation with cancer CM. Stromovascular cells from PPAT in culture were not influenced by tumor-derived factors. Conclusion: The modulation of adipokine expression by tumor CM indicates the pervasive extent to which tumor cells command PPAT to produce factors favorable to their aggressiveness. © 2012 S. Karger AG, Basel.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: CEPBEdoi: 10.1159/000337604PubMed ID: 22415092Language of Original Document: EnglishCorrespondence Address: Ribeiro, R.J.T.; Portuguese Institute of Oncology, Porto Centre Molecular Oncology Group -CI, Edifício Laboratórios -Piso 4, Rua Dr. António Bernardino Almeida, 4200-072 Porto, Portugal; email: oriebir.r@gmail.comChemicals/CAS: adiponectin, 283182-39-8; gelatinase B, 146480-36-6; osteopontin, 106441-73-0; Adiponectin; Culture Media, Conditioned; Cytokines; DNA, Mitochondrial; Interleukin-6; Matrix Metalloproteinase 2, 3.4.24.24; Matrix Metalloproteinase 9, 3.4.24.35; Osteopontin, 106441-73-0; Tumor Necrosis Factor-alphaReferences: Hsing, A.W., Sakoda, L.C., Chua Jr., S., Obesity, metabolic syndrome, and prostate cancer (2007) Am J Clin Nutr, 86, pp. s843-857;Cao, Y., Ma, J., Body mass index, prostate cancer-specific mortality, and biochemical recurrence: A systematic review and meta-analysis (2011) Cancer Prev Res (Phila), 4, pp. 486-501; Baillargeon, J., Rose, D.P., Obesity, adipokines, and prostate cancer (review) (2006) Int J Oncol, 28, pp. 737-745; Mistry, T., Digby, J.E., Desai, K.M., Randeva, H.S., Obesity and Prostate Cancer: A Role for Adipokines (2007) European Urology, 52 (1), pp. 46-53. , DOI 10.1016/j.eururo.2007.03.054, PII S0302283807004307; Hirano, T., Morii, H., Nakazawa, K., Murakami, D., Yamashita, A., Asahi, J., Orimo, H., Tokura, Y., Enhancement of adipogenesis induction by conditioned media obtained from cancer cells (2008) Cancer Lett, 268, pp. 286-294; Andarawewa, K.L., Motrescu, E.R., Chenard, M.-P., Gansmuller, A., Stoll, I., Tomasetto, C., Rio, M.-C., Stromelysin-3 is a potent negative regulator of adipogenesis participating to cancer cell-adipocyte interaction/crosstalk at the tumor invasive front (2005) Cancer Research, 65 (23), pp. 10862-10871. , DOI 10.1158/0008-5472.CAN-05-1231; Jotzu, C., Alt, E., Welte, G., Li, J., Hennessy, B.T., Devarajan, E., Krishnappa, S., Song, Y.H., Adipose tissue derived stem cells differentiate into carcinoma-associated fibroblast-like cells under the influence of tumor derived factors (2011) Cell Oncol (Dordr), 34, pp. 55-67; Dolinkova, M., Dostalova, I., Lacinova, Z., Michalsky, D., Haluzikova, D., Mraz, M., The endocrine profile of subcutaneous and visceral adipose tissue of obese patients (2008) Mol Cell Endocrinol, 291, pp. 63-70; Van Roermund, J.G., Hinnen, K.A., Tolman, C.J., Bol, G.H., Witjes, J.A., Bosch, J.L., Kiemeney, L.A., Van Vulpen, M., Periprostatic fat correlates with tumour aggressiveness in prostate cancer patients (2011) BJU Int, 107, pp. 1775-1779; Sumitomo, M., Asakuma, J., Yoshii, H., Sato, A., Horiguchi, A., Ito, K., Nagakura, K., Asano, T., Anterior perirectal fat tissue thickness is a strong predictor of recurrence after high-intensity focused ultrasound for prostate cancer (2010) Int J Urol, 17, pp. 776-782; Finley, D.S., Calvert, V.S., Inokuchi, J., Lau, A., Narula, N., Petricoin, E.F., Zaldivar, F., Ornstein, D.K., Periprostatic adipose tissue as a modulator of prostate cancer aggressiveness (2009) J Urol, 182, pp. 1621-1627; Thalmann, S., Juge-Aubry, C.E., Meier, C.A., Explant cultures of white adipose tissue (2008) Methods Mol Biol, 456, pp. 195-199; Song, G.J., Lewis, V., Mitochondrial DNA integrity and copy number in sperm from infertile men (2008) Fertil Steril, 90, pp. 2238-2244; Park, J., Euhus, D.M., Scherer, P.E., Paracrine and Endocrine Effects of Adipose Tissue on Cancer Development and Progression (2011) Endocr Rev, 32, pp. 550-570; George, D.J., Halabi, S., Shepard, T.F., Sanford, B., Vogelzang, N.J., Small, E.J., Kantoff, P.W., The prognostic significance of plasma interleukin-6 levels in patients with metastatic hormone-refractory prostate cancer: Results from cancer and leukemia group B 9480 (2005) Clinical Cancer Research, 11 (5), pp. 1815-1820. , DOI 10.1158/1078-0432.CCR-04-1560; Michalaki, V., Syrigos, K., Charles, P., Waxman, J., Serum levels of IL-6 and TNF-α correlate with clinicopathological features and patient survival in patients with prostate cancer (2004) British Journal of Cancer, 90 (12), pp. 2312-2316; Dirat, B., Bochet, L., Dabek, M., Daviaud, D., Dauvillier, S., Majed, B., Wang, Y.Y., Muller, C., Cancerassociated adipocytes exhibit an activated phenotype and contribute to breast cancer invasion (2011) Cancer Res, 71, pp. 2455-2465; Culig, Z., New insights into the role of interleukin-6 in human prostate cancer (2009) J Urol, 182, pp. 1255-1256; Chun, J.Y., Nadiminty, N., Dutt, S., Lou, W., Yang, J.C., Kung, H.J., Evans, C.P., Gao, A.C., Interleukin-6 regulates androgen synthesis in prostate cancer cells (2009) Clin Cancer Res, 15, pp. 4815-4822; Weber, G.F., Lett, G.S., Haubein, N.C., Osteopontin is a marker for cancer aggressiveness and patient survival (2010) Br J Cancer, 103, pp. 861-869; Thalmann, G.N., Sikes, R.A., Devoll, R.E., Kiefer, J.A., Markwalder, R., Klima, I., Farach-Carson, C.M., Chung, L.W.K., Osteopontin: Possible role in prostate cancer progression (1999) Clinical Cancer Research, 5 (8), pp. 2271-2277; McAllister, S.S., Gifford, A.M., Greiner, A.L., Kelleher, S.P., Saelzler, M.P., Ince, T.A., Reinhardt, F., Weinberg, R.A., Systemic Endocrine Instigation of Indolent Tumor Growth Requires Osteopontin (2008) Cell, 133 (6), pp. 994-1005. , DOI 10.1016/j.cell.2008.04.045, PII S0092867408006211; Balkwill, F., TNF-alpha in promotion and progression of cancer (2006) Cancer Metastasis Rev, 25, pp. 409-416; Yan, B., Wang, H., Rabbani, Z.N., Zhao, Y., Li, W., Yuan, Y., Li, F., Li, C.-Y., Tumor necrosis factor-α is a potent endogenous mutagen that promotes cellular transformation (2006) Cancer Research, 66 (24), pp. 11565-11570. , DOI 10.1158/0008-5472.CAN-06-2540; Bates, R.C., Mercurio, A.M., Tumor necrosis factor-α stimulates the epithelial-tomesenchymal transition of human colonic organoids (2003) Molecular Biology of the Cell, 14 (5), pp. 1790-1800. , DOI 10.1091/mbc.E02-09-0583; Yamauchi, T., Kamon, J., Waki, H., Terauchi, Y., Kubota, N., Hara, K., Mori, Y., Kadowaki, T., The fat-derived hormone adiponectin reverses insulin resistance associated with both lipoatrophy and obesity (2001) Nature Medicine, 7 (8), pp. 941-946. , DOI 10.1038/90984; Li, H., Stampfer, M.J., Mucci, L., Rifai, N., Qiu, W., Kurth, T., Ma, J., A 25-year prospective study of plasma adiponectin and leptin concentrations and prostate cancer risk and survival (2010) Clin Chem, 56, pp. 34-43; Ribeiro, R., Lopes, C., Medeiros, R., The link between obesity and prostate cancer: The leptin pathway and therapeutic perspectives (2006) Prostate Cancer and Prostatic Diseases, 9 (1), pp. 19-24. , DOI 10.1038/sj.pcan.4500844, PII 4500844; Vaday, G.G., Peehl, D.M., Kadam, P.A., Lawrence, D.M., Expression of CCL5 (RANTES) and CCR5 in prostate cancer (2006) Prostate, 66 (2), pp. 124-134. , DOI 10.1002/pros.20306; Kessenbrock, K., Plaks, V., Werb, Z., Matrix metalloproteinases: Regulators of the tumor microenvironment (2010) Cell, 141, pp. 52-67; Bouloumie, A., Sengenes, C., Portolan, G., Galitzky, J., Lafontan, M., Adipocyte Produces Matrix Metalloproteinases 2 and 9 Involvement in Adipose Differentiation (2001) Diabetes, 50 (9), pp. 2080-2086; Bergers, G., Brekken, R., McMahon, G., Vu, T.H., Itoh, T., Tamaki, K., Tanzawa, K., Hanahan, D., Matrix metalloproteinase-9 triggers the angiogenic switch during carcinogenesis (2000) Nat Cell Biol, 2, pp. 737-744; Lin, C.Y., Tsai, P.H., Kandaswami, C.C., Lee, P.P., Huang, C.J., Hwang, J.J., Lee, M.T., Matrix metalloproteinase-9 cooperates with transcription factor Snail to induce epithelial-mesenchymal transition (2011) Cancer Sci, 102, pp. 815-827; Chakrabarti, S., Patel, K.D., Matrix metalloproteinase-2 (MMP-2) and MMP-9 in pulmonary pathology (2005) Experimental Lung Research, 31 (6), pp. 599-621. , DOI 10.1080/019021490944232; Sehgal, G., Hua, J., Bernhard, E.J., Sehgal, I., Thompson, T.C., Muschel, R.J., Requirement for matrix metalloproteinase-9 (Gelatinase B) expression in metastasis by murine prostate carcinoma (1998) American Journal of Pathology, 152 (2), pp. 591-596; Johnson, T.R., Koul, S., Kumar, B., Khandrika, L., Venezia, S., Maroni, P.D., Meacham, R.B., Koul, H.K., Loss of PDEF, a prostatederived Ets factor is associated with aggressive phenotype of prostate cancer: Regulation of MMP 9 by PDEF (2010) Mol Cancer, 9, p. 148; Trudel, D., Fradet, Y., Meyer, F., Tetu, B., Matrix metalloproteinase 9 is associated with Gleason score in prostate cancer but not with prognosis (2010) Hum Pathol, 41, pp. 1694-1701; Zhang, L., Shi, J., Feng, J., Klocker, H., Lee, C., Zhang, J., Type IV collagenase (matrix metalloproteinase-2 and -9) in prostate cancer (2004) Prostate Cancer and Prostatic Diseases, 7 (4), pp. 327-332. , DOI 10.1038/sj.pcan.4500750, PII 4500750; Zhong, W.D., Han, Z.D., He, H.C., Bi, X.C., Dai, Q.S., Zhu, G., Ye, Y.K., Chen, Z.N., CD147, MMP-1, MMP-2 and MMP-9 protein expression as significant prognostic factors in human prostate cancer (2008) Oncology, 75, pp. 230-236; Sauer, C.G., Kappeler, A., Spath, M., Kaden, J.J., Michel, M.S., Mayer, D., Bleyl, U., Grobholz, R., Expression and activity of matrix metalloproteinases-2 and -9 in serum, core needle biopsies and tissue specimens of prostate cancer patients (2004) Virchows Archiv, 444 (6), pp. 518-526; Opdenakker, G., Masure, S., Grillet, B., Van Damme, J., Cytokine-mediated regulation of human leukocyte gelatinases and role in arthritis (1991) Lymphokine Cytokine Res, 10, pp. 317-324; Unal, R., Yao-Borengasser, A., Varma, V., Rasouli, N., Labbate, C., Kern, P.A., Ranganathan, G., Matrix metalloproteinase-9 is increased in obese subjects and decreases in response to pioglitazone (2010) J Clin Endocrinol Metab, 95, pp. 2993-3001; Catalan, V., Gomez-Ambrosi, J., Rodriguez, A., Ramirez, B., Silva, C., Rotellar, F., Gil, M.J., Frühbeck, G., Increased adipose tissue expression of lipocalin-2 in obesity is related to inflammation and matrix metalloproteinase-2 and metalloproteinase-9 activities in humans (2009) J Mol Med (Berl), 87, pp. 803-813; Villarroya, J., Giralt, M., Villarroya, F., Mitochondrial DNA: An up-and-coming actor in white adipose tissue pathophysiology (2009) Obesity (Silver Spring), 17, pp. 1814-1820; Robin, E.D., Wong, R., Mitochondrial DNA molecules and virtual number of mitochondria per cell in mammalian cells (1988) J Cell Physiol, 136, pp. 507-513; Kaaman, M., Sparks, L.M., Van Harmelen, V., Smith, S.R., Sjolin, E., Dahlman, I., Arner, P., Strong association between mitochondrial DNA copy number and lipogenesis in human white adipose tissue (2007) Diabetologia, 50 (12), pp. 2526-2533. , DOI 10.1007/s00125-007-0818-6; Yamauchi, T., Kamon, J., Waki, H., Murakami, K., Motojima, K., Komeda, K., Ide, T., Kadowaki, T., The mechanisms by which both heterozygous peroxisome proliferator- activated receptor gamma (PPARgamma) deficiency and PPARgamma agonist improve insulin resistance (2001) J Biol Chem, 276, pp. 41245-41254; Wilson-Fritch, L., Burkart, A., Bell, G., Mendelson, K., Leszyk, J., Nicoloro, S., Czech, M., Corvera, S., Mitochondrial biogenesis and remodeling during adipogenesis and in response to the insulin sensitizer rosiglitazone (2003) Molecular and Cellular Biology, 23 (3), pp. 1085-1094. , DOI 10.1128/MCB.23.3.1085-1094.2003; Ducluzeau, P.H., Priou, M., Weitheimer, M., Flamment, M., Duluc, L., Iacobazi, F., Soleti, R., Malthièry, Y., Dynamic regulation of mitochondrial network and oxidative functions during 3T3-L1 fat cell differentiation (2011) J Physiol Biochem, 67, pp. 285-296; Bogacka, I., Ukropcova, B., McNeil, M., Gimble, J.M., Smith, S.R., Structural and functional consequences of mitochondrial biogenesis in human adipocytes in vitro (2005) Journal of Clinical Endocrinology and Metabolism, 90 (12), pp. 6650-6656. , http://jcem.endojournals.org/cgi/reprint/90/12/6650, DOI 10.1210/jc.2005-1024; Toda, S., Uchihashi, K., Aoki, S., Sonoda, E., Yamasaki, F., Piao, M., Ootani, A., Sugihara, H., Adipose tissueorganotypic culture system as a promising model for studying adipose tissue biology and regeneration (2009) Organogenesis, 5, pp. 50-56; Tuxhorn, J.A., Ayala, G.E., Rowley, D.R., Reactive stroma in prostate cancer progression (2001) Journal of Urology, 166 (6), pp. 2472-2483
Keywords: Adipokines; adiponectin; adipose tissue; adult; article; cancer cell; cancer growth; Cells, Cultured; clinical article; controlled study; Culture Media, Conditioned; culture medium; Cytokines; DNA, Mitochondrial; enzyme activity; enzyme linked immunosorbent assay; explant; gelatinase B; human; human cell; human tissue; Humans; interleukin 6; Interleukin-6; male; Matrix Metalloproteinase 2; Matrix Metalloproteinase 9; Middle Aged; mitochondrial DNA; Osteopontin; Periprostatic adipose tissue; priority journal; Prostate cancer; Prostatic Neoplasms; protein expression; protein induction; protein secretion; quantitative analysis; stroma cell; tissue metabolism; tumor necrosis factor alpha; Tumor Necrosis Factor-alpha

Complexity and categorical analysis may improve the interpretation of agreement studies using continuous variables - Costa-Santos, C.; Bernardes, J.; Antunes, L.; Ayres-de-Campos, D. (Journal of Evaluation in Clinical PracticeJ. Eval. Clin. Pract., 2011)
Rationale Complex clinical scenarios involving a high degree of uncertainty frequently lead to a poor agreement over diagnosis and management. However, inconsistent results can be found with the most widely used measures of agreement for continuous variables - the limits of agreement and the intraclass correlation coefficient. Aims and objectives We aim to improve the interpretation of agreement studies using continues variables. Methods and results Evaluation of agreement may be improved by complexity analysis and by categorization of variables, followed by the use of the proportions of agreement. Conclusions The average never characterizes a complex phenomenon and the methods used to access agreement in continuous variables are based on the mean. For future agreement studies, involving complex continuous variables, we recommend a complexity and categorical analysis. © 2011 Blackwell Publishing Ltd.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: JECPFdoi: 10.1111/j.1365-2753.2011.01668.xPubMed ID: 21489051Language of Original Document: EnglishCorrespondence Address: Costa-Santos, C.; Department of Biostatistics and Medical Informatics, Faculty of Medicine, University of Porto, Al. Prof. Hernâni Monteiro, 4200-319 Porto, Portugal; email: csantos@med.up.ptReferences: Costa Santos, C., Costa Pereira, A., Bernardes, J., Agreement studies in obstetrics and gynaecology: Inappropriateness, controversies and consequences (2005) BJOG: An International Journal of Obstetrics and Gynaecology, 112 (5), pp. 667-669. , DOI 10.1111/j.1471-0528.2004.00505.x;Khan, K.S., Chien, P.F., Evaluation of a clinical test. I: Assessment of reliability (2001) BJOG, 108, pp. 562-567; Luiz, R.R., Szklo, M., More than one statistical strategy to assess agreement of quantitative measurements may usefully be reported (2005) Journal of Clinical Epidemiology, 58 (3), pp. 215-216. , DOI 10.1016/j.jclinepi.2004.07.007; Costa-Santos, C., Bernardes, J., Ayres-De-Campos, D., Costa, A., Costa, C., The limits of agreement and the intraclass correlation coefficient may be inconsistent in the interpretation of agreement (2011) Journal of Clinical Epidemiology, 64 (3), pp. 264-269; Costa-Santos, C., Antunes, L., Souto, A., Bernardes, J., Assessment of disagreement: A new information-based approach (2010) Annals of Epidemiology, 20, pp. 555-561; Luiz, R.R., Costa, A.J.L., Kale, P.L., Werneck, G.L., Assessment of agreement of a quantitative variable: A new graphical approach (2003) Journal of Clinical Epidemiology, 56 (10), pp. 963-967. , DOI 10.1016/S0895-4356(03)00164-1; Plsek, P.E., Greenhalgh, T., The challenge of complexity in health care (2001) British Medical Journal, 323 (7313), pp. 625-628; Shiell, A., Hawe, P., Gold, L., Complex interventions or complex systems? Implications for health economic evaluation (2008) BMJ, 336 (7656), pp. 1281-1283; Wilson, T., Holt, T., Complexity science: Complexity and clinical care (2001) British Medical Journal, 323 (7314), pp. 685-688; Miles, A., Complexity in medicine and healthcare: People and systems, theory and practice (2009) Journal of Evaluation in Clinical Practice, 15 (3), pp. 409-410; Shannon, Î., A mathematical theory of communication (1948) Bell System Technical Journal, 27, pp. 379-423. , 623- 656; Bernardes, J., Costa-Pereira, A., Ayres-De-Campos, D., Van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) International Journal of Gynecology and Obstetrics, 57 (1), pp. 33-37. , DOI 10.1016/S0020-7292(97)02846-4, PII S0020729297028464; Ayres-De-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in classification by experts of cardiotocograms and subsequent clinical decision (1999) British Journal of Obstetrics and Gynaecology, 106, pp. 1307-1310; Rooth, G., Guidelines for the use of fetal monitoring (1987) International Journal of Gynaecology and Obstetrics, 25, pp. 159-167; Grant, J.M., The fetal heart rate is normal, isn't it? Observer agreement of categorical assessments (1991) Lancet, 337, pp. 215-218; Müller, R., Büttner, P., A critical discussion of intraclass correlation coefficients (1994) Statistics in Medicine, 13, pp. 2465-2476; Byrt, T., Bishop, J., Carlin, J.B., Bias, prevalence and kappa (1993) Journal of Clinical Epidemiology, 46 (5), pp. 423-429. , DOI 10.1016/0895-4356(93)90018-V; West, B.J., Homeostasis and Gauss statistics: Barriers to understanding natural variability (2010) Journal of Evaluation in Clinical Practice, 16, pp. 403-408; Goncalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Linear and nonlinear fetal heart rate analysis of normal and acidemic fetuses in the minutes preceding delivery (2006) Medical and Biological Engineering and Computing, 44 (10), pp. 847-855. , DOI 10.1007/s11517-006-0105-6; Costa Santos, C., Vitanyi, P.M.B., Bernardes, J., Antunes, L., Clustering fetal heart rate tracings by compression (2006) Proceedings - IEEE Symposium on Computer-Based Medical Systems, 2006, pp. 685-690. , DOI 10.1109/CBMS.2006.68, 1647650, Proceedings - 19th IEEE International Symposium on Computer-Based Medical Systems, CBMS 2006
Keywords: article; Biomedical research; Cardiotocography; clinical decision making; clinical practice; complexity; Data Interpretation, Statistical; Decision Making; entropy; Female; fetus heart rate; Heart Rate, Fetal; human; Humans; observer variation; Pregnancy; Pregnancy Outcome; priority journal; Reproducibility of Results; statistical data interpretation; Uncertainty

Knowledge of adverse neonatal outcome alters clinicians' interpretation of the intrapartum cardiotocograph - Ayres-de-Campos, D.; Arteiro, D.; Costa-Santos, C.; Bernardes, J. (BJOG: An International Journal of Obstetrics and GynaecologyBJOG Int. J. Obstet. Gynaecol., 2011)
Objective: To evaluate the impact of knowledge of neonatal outcome on clinicians' interpretation of the intrapartum cardiotocograph (CTG). Design: Prospective evaluation of pre-recorded cases. Setting: Five maternity hospitals. Population: From a database of intrapartum CTGs acquired with a scalp electrode in singleton near-term fetuses, 20 tracings were sequentially selected from cases with newborn umbilical artery pH < 7.05 and 20 from cases with pH > 7.20. Methods: Five experienced obstetricians practising in different maternity hospitals were asked to analyse the 40 tracings individually, according to the International Federation of Gynaecology and Obstetrics guidelines. In a first round, clinicians were given no information on neonatal outcome. In a second round, carried out 2 months later, clinicians were asked to analyse the same tracings, but the order was randomly altered and information on the newborn's arterial pH was provided. Clinicians were not informed of the purpose of the study or whether the tracings were the same. Main outcome measures: The incidence of individual fetal heart rate feature identification and tracing classification, before and after neonatal outcome was made available. Results: In the group with pH < 7.05, repetitive decelerations and reduced variability were more common in the second round (P < 0.001 and P = 0.001, respectively), as was a pathological classification (P = 0.002); variable decelerations were less common (P = 0.008). In the group with normal pH, less tracings in the second round had prolonged decelerations (P = 0.013) and no accelerations (P = 0.013), but more had pronounced decelerations (P = 0.031) and reduced variability (P = 0.007); there was a reduction in pathological classifications, but this difference failed to reach statistical significance (P = 0.051). Conclusions: A knowledge of adverse neonatal outcome leads to a more severe classification of the intrapartum CTG, which derives mainly from the evaluation of decelerations and variability. © 2011 The Authors BJOG An International Journal of Obstetrics and Gynaecology © 2011 RCOG.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: BIOGFdoi: 10.1111/j.1471-0528.2011.03003.xPubMed ID: 21609381Language of Original Document: EnglishCorrespondence Address: Ayres-de-Campos, D.; Departmento de Ginecologia e Obstetrícia, Faculdade de Medicina do Porto, 4200-309 Porto, Portugal; email: dcampos@med.up.ptReferences: (2006) Perinatal Mortality Surveillance 2004: England, Wales and Northern Ireland, , CEMACH - Centre for Maternal and Child Enquiries (previously Confidential Enquiries into Maternal and Child Health). London: CEMACH;(1997) CESDI - Confidential Enquiry into Stillbirths and Deaths in Infancy, , 4th Annual Report. London: CESDI; Wood, C., Renou, P., Oats, J., A controlled trial of fetal heart rate monitoring in a low-risk obstetric population (1981) American Journal of Obstetrics and Gynecology, 141 (5), pp. 527-534; MacDonald, D., Grant, A., Sheridan-Pereira, M., The Dublin randomized controlled trial of intrapartum fetal heart rate monitoring (1985) American Journal of Obstetrics and Gynecology, 152 (5), pp. 524-539; Shy, K.K., Luthy, D.A., Bennett, F.C., Whitfield, M., Larson, E.B., Van Belle, G., Hughes, J.P., Stenchever, M.A., Effects of electronic fetal-heart-rate monitoring, as compared with periodic auscultation, on the neurologic development of premature infants (1990) New England Journal of Medicine, 322 (9), pp. 588-593; Dillner, L., Babies' deaths linked to suboptimal care (1995) Br Med J, 310, p. 757; Ayres-de-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in classification by experts of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynaecol, 106, pp. 1307-1310; Palomaki, O., Luukkaala, T., Luoto, R., Tuimala, R., Intrapartum cardiotocography - The dilemma of interpretational variation (2006) Journal of Perinatal Medicine, 34 (4), pp. 298-302. , DOI 10.1515/JPM.2006.057, PII JPME344298; Westerhuis, M., Van Horen, E., Kwee, A., Van Der Tweel, I., Visser, G., Moons, K., Inter- and intra-observer agreement of intrapartum ST analysis of the fetal electrocardiogram in women monitored by STAN (2009) BJOG, 116, pp. 545-551; Caplan, R.A., Posner, K.L., Cheney, F.W., Effect of outcome on physician judgment of appropriateness of care (1991) J Am Med Assoc, 265, pp. 1957-1960; Rooth, G., Huch, A., Huch, R., Guidelines for the use of fetal monitoring (1987) Int J Gynecol Obstet, 25, pp. 159-167. , FIGO News; Amer-Wahlin, I., Hellsten, C., Noren, H., Hagberg, H., Herbst, A., Kjellmer, I., Lilja, H., Marsal, K., Cardiotocography only versus cardiotocography plus ST analysis of fetal electrocardiogram for intrapartum fetal monitoring: A Swedish randomised controlled trial (2001) Lancet, 358 (9281), pp. 534-538. , DOI 10.1016/S0140-6736(01)05703-8; Westgate, J., Garibaldi, J.M., Greene, K.R., Umbilical cord blood gas analysis at delivery: A time for quality data (1994) British Journal of Obstetrics and Gynaecology, 101 (12), pp. 1054-1063; Figueras, F., Albela, S., Bonino, S., Palacio, M., Barrau, E., Hernandez, S., Casellas, C., Cararach, V., Visual analysis of antepartum fetal heart rate tracings: Inter- and intra-observer agreement and impact of knowledge of neonatal outcome (2005) Journal of Perinatal Medicine, 33 (3), pp. 241-245. , http://www.extenza-eps.com/extenza/loadPDF?objectIDValue=64432, DOI 10.1515/JPM.2005.044; Zain, H.A., Wright, J.W., Parrish, G.E., Diehl, S.J., Interpreting the fetal heart rate tracing: Effect of knowledge of neonatal outcome (1998) Journal of Reproductive Medicine for the Obstetrician and Gynecologist, 43 (4), pp. 367-370; Almström, H., Axelsson, O., Ekman, G., Ingemarsson, I., Maesel, A., Arström, K., Umbilical artery velocimetry may influence clinical interpretation of intrapartum cardiotocograms (1995) Acta Obstet Gynecol Scand, 74, pp. 526-529; Spencer, J.A.D., Clinical overview of cardiotocography (1993) British Journal of Obstetrics and Gynaecology, Supplement, 100 (9), pp. 4-7; Ayres-de-Campos, D., Bernardes, J., Early, variable and late decelerations: Can a consensus be reached in their identification? (1999) Int J Gynecol Obstet, 65, pp. 305-306; Capstick, J.B., Edwards, P.J., Trends in obstetric malpractice claims (1990) Lancet, 336 (8720), pp. 931-932. , DOI 10.1016/0140-6736(90)92291-O; Symonds, E.M., Litigation and the cardiotocogram (1993) British Journal of Obstetrics and Gynaecology, Supplement, 100 (9), pp. 8-9; Williams, B., Arulkumaran, S., Cardiotocography and medicolegal issues (2004) Best Practice and Research: Clinical Obstetrics and Gynaecology, 18 (3), pp. 457-466. , DOI 10.1016/j.bpobgyn.2004.02.005, PII S1521693404000318
Keywords: adverse outcome; Agreement; article; bradycardia; Cardiotocography; clinical competence; Female; Fetal; Fetal hypoxia; Fetal monitoring; fetus heart rate; fetus outcome; health practitioner; Heart rate; Heart Rate, Fetal; human; Humans; Hydrogen-Ion Concentration; incidence; Infant, Newborn; intrapartum care; Labor, Obstetric; medical practice; pH; practice guideline; Practice Guidelines as Topic; Pregnancy; Pregnancy Outcome; priority journal; Prospective Studies; Questionnaires; Reference Standards; Reproducibility of Results; Research Design; Risk Factors; Sweden; tachycardia; umbilical artery

Layer-by-layer self-assembly of chitosan and poly(γ-glutamic acid) into polyelectrolyte complexes - Antunes, J.C.; Pereira, C.L.; Molinos, M.; Ferreira-da-Silva, F.; Dessi, M.; Gloria, A.; Ambrosio, L.; Gonca̧lves, R.M.; Barbosa, M.A. (BiomacromoleculesBiomacromolecules, 2011)
Chitosan (Ch) is a nontoxic and biocompatible polysaccharide extensively used in biomedical applications. Ch, as a polycation, can be combined with anionic polymers by layer-bylayer (LbL) self-assembly, giving rise to multilayered complexed architectures. These structures can be used in tissue engineering strategies, as drug delivery systems, or artificial matrices mimicking the extracellular microenvironment. In this work, Ch was combined with poly(γ-glutamic acid) (γ-PGA). γ-PGA is a polyanion, which was microbially produced, and is known for its low immunogenic reaction and low cytotoxicity. Multilayered ultrathin films were assembled by LbL, with a maximum of six layers. The interaction between both polymers was analyzed by: ellipsometry, quartz crystal microbalance with dissipation, Fourier transform infrared spectroscopy, atomic force microscopy, and zeta potential measurements. Ch/γ-PGA polyelectrolyte multilayers (PEMs) revealed no cytotoxicity according to ISO 10993-5. Overall, this study demonstrates that Ch can interact electrostatically with γ-PGA forming multilayered films. Furthermore, this study provides a comprehensive characterization of Ch/γ-PGA PEM structures, elucidating the contribution of each layer for the nanostructured films. These model surfaces can be useful substrates to study cell-biomaterial interactions in tissue regeneration. © 2011 American Chemical Society.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: BOMAFdoi: 10.1021/bm2008235PubMed ID: 22032302Language of Original Document: EnglishCorrespondence Address: Antunes, J.C.; INEB - Instituto de Engenharia Biomédica, Porto, Portugal; email: joana.antunes@ineb.up.ptChemicals/CAS: chitosan, 9012-76-4; glutamic acid, 11070-68-1, 138-15-8, 56-86-0, 6899-05-4; Biocompatible Materials; Chitosan, 9012-76-4; Electrolytes; Polyglutamic Acid, 25513-46-6; Viscoelastic Substances; poly(gamma-glutamic acid)References: Bertrand, P., Jonas, A., Laschewsky, A., Legras, R., Ultrathin polymer coatings by complexation of polyelectrolytes at interfaces: Suitable materials, structure and properties (2000) Macromol. Rapid Commun., 21, pp. 319-348;Schonhoff, M., Layered polyelectrolyte complexes: Physics of formation and molecular properties (2003) J. Phys.: Condens. Matter, 15, pp. R1781-R1808; Von Klitzing, R., Internal structure of polyelectrolyte multilayer assemblies (2006) Phys. Chem. Chem. Phys., 8, pp. 5012-5033; Iler, R.K., Multilayers of colloidal particles (1966) J. Colloid Interface Sci., 21, pp. 569-594; Zhang, X., Chen, H., Zhang, H., Layer-by-layer assembly: From conventional to unconventional methods (2007) Chemical Communications, (14), pp. 1395-1405. , DOI 10.1039/b615590a; Decher, G., Hong, J.D., Schmitt, J., Buildup of ultrathin multilayer films by a self-assembly process. 3. Consecutively alternating adsorption of anionic and cationic polyelectrolytes on charged surfaces (1992) Thin Solid Films, 210, pp. 831-835; Boudou, T., Crouzier, T., Ren, K.F., Blin, G., Picart, C., Multiple functionalities of polyelectrolyte multilayer films: New biomedical applications (2010) Adv. Mater., 22, pp. 441-467; Schlenoff, J.B., Retrospective on the future of polyelectrolyte multilayers (2009) Langmuir, 25, pp. 14007-14010; Ariga, K., Hill, J.P., Ji, Q.M., Layer-by-layer assembly as a versatile bottom-up nanofabrication technique for exploratory research and realistic application (2007) Phys. Chem. Chem. Phys., 9, pp. 2319-2340; Meng, S., Liu, Z., Shen, L., Guo, Z., Chou, L.L., Zhong, W., Du, Q., Ge, J., The effect of a layer-by-layer chitosan-heparin coating on the endothelialization and coagulation properties of a coronary stent system (2009) Biomaterials, 30, pp. 2276-2283; De Geest, B.G., Jonas, A.M., Demeester, J., De Smedt, S.C., Glucose-responsive polyelectrolyte capsules (2006) Langmuir, 22 (11), pp. 5070-5074. , DOI 10.1021/la053368o; Dimitrova, M., Affolter, C., Meyer, F., Nguyen, I., Richard, D.G., Schuster, C., Bartenschlager, R., Baumert, T.F., Sustained delivery of siRNAs targeting viral infection by celldegradable multilayered polyelectrolyte films (2008) Proc. Natl. Acad. Sci. U.S.A., 105, pp. 16320-16325; Crouzier, T., Ren, K., Nicolas, C., Roy, C., Picart, C., Layer-bylayer films as a biomimetic reservoir for rhBMP-2 delivery: Controlled differentiation of myoblasts to osteoblasts (2009) Small, 5, pp. 598-608; He, L., Dexter, A.F., Middelberg, A.P.J., Biomolecular engineering at interfaces (2006) Chemical Engineering Science, 61 (3), pp. 989-1003. , DOI 10.1016/j.ces.2005.05.064, PII S000925090500518X, Biomolecular Engineering; Chua, P.H., Neoh, K.G., Shi, Z., Kang, E.T., Structural stability and bioapplicability assessment of hyaluronic acid-chitosan polyelectrolyte multilayers on titanium substrates (2008) J. Biomed. Mater. Res., Part A, 87 A, pp. 1061-1074; Decher, G., Fuzzy nanoassemblies: Toward layered polymeric multicomposites (1997) Science, 277 (5330), pp. 1232-1237. , DOI 10.1126/science.277.5330.1232; Ozin, G.A., Hou, K., Lotsch, B.V., Cademartiri, L., Puzzo, D.P., Scotognella, F., Ghadimi, A., Thomson, J., Nanofabrication by selfassembly (2009) Mater. Today, 12, pp. 12-23; Dubas, S.T., Schlenoff, J.B., Factors controlling the growth of polyelectrolyte multilayers (1999) Macromolecules, 32 (24), pp. 8153-8160. , DOI 10.1021/ma981927a; Kumar, M.N.V.R., Muzzarelli, R.A.A., Muzzarelli, C., Sashiwa, H., Domb, A.J., Chitosan chemistry and pharmaceutical perspectives (2004) Chemical Reviews, 104 (12), pp. 6017-6084. , DOI 10.1021/cr030441b; Yi, H., Wu, L.-Q., Bentley, W.E., Ghodssi, R., Rubloff, G.W., Culver, J.N., Payne, G.F., Biofabrication with chitosan (2005) Biomacromolecules, 6 (6), pp. 2881-2894. , DOI 10.1021/bm050410l; Berger, J., Reist, M., Mayer, J.M., Felt, O., Gurny, R., Structure and interactions in chitosan hydrogels formed by complexation or aggregation for biomedical applications (2004) European Journal of Pharmaceutics and Biopharmaceutics, 57 (1), pp. 35-52. , DOI 10.1016/S0939-6411(03)00160-7; Rinaudo, M., Chitin and chitosan: Properties and applications (2006) Progress in Polymer Science (Oxford), 31 (7), pp. 603-632. , DOI 10.1016/j.progpolymsci.2006.06.001, PII S0079670006000530; Sogias, I.A., Khutoryanskiy, V.V., Williams, A.C., Exploring the factors affecting the solubility of chitosan in water (2010) Macromol. Chem. Phys., 211, pp. 426-433; Sorlier, P., Denuziere, A., Viton, C., Domard, A., Relation between the degree of acetylation and the electrostatic properties of chitin and chitosan (2001) Biomacromolecules, 2 (3), pp. 765-772. , DOI 10.1021/bm015531+; Krayukhina, M.A., Samoilova, N.A., Yamskov, I.A., Polyelectrolyte complexes of chitosan: Formation, properties, and applications (2008) Usp. Khim., 77, pp. 854-869; Buescher, J.M., Margaritis, A., Microbial biosynthesis of polyglutamic acid biopolymer and applications in the biopharmaceutical, biomedical and food industries (2007) Critical Reviews in Biotechnology, 27 (1), pp. 1-19. , DOI 10.1080/07388550601166458, PII 773236840; Shih, I.L., Van, Y.T., Shen, M.H., Biomedical applications of chemically and microbiologically synthesized poly(glutamic acid) and poly(lysine) (2004) Mini-Rev. Med. Chem., 4, pp. 179-188; Nelson, D.L., Cox, M.M., Amino acids peptides and proteins (2005) Lehninger Principles of Biochemistry, pp. 78-79. , 4th ed.; W. H. Freeman and Company: New York; Edde, B., Rossier, J., Lecaer, J.P., Desbruyeres, E., Gros, F., Denoulet, P., Posttranslational glutamylation of alpha-tubulin (1990) Science, 247, pp. 83-85; Candela, T., Fouet, A., Poly-γ-glutamate in bacteria (2006) Mol. Microbiol., 60, pp. 1091-1098; Rhie, G.-E., Roehrl, M.H., Mourez, M., Collier, R.J., Mekalanos, J.J., Wang, J.Y., A dually active anthrax vaccine that confers protection against both bacilli and toxins (2003) Proceedings of the National Academy of Sciences of the United States of America, 100 (19), pp. 10925-10930. , DOI 10.1073/pnas.1834478100; Schneerson, R., Kubler-Kielb, J., Liu, T.-Y., Dai, Z.-D., Leppla, S.H., Yergey, A., Backlund, P., Robbins, J.B., Poly(γ-D-glutamic acid) protein conjugates induce IgG antibodies in mice to the capsule of Bacillus anthracis: A potential addition to the anthrax vaccine (2003) Proceedings of the National Academy of Sciences of the United States of America, 100 (15), pp. 8945-8950. , DOI 10.1073/pnas.1633512100; Prescott, A.G., Stock II, L.R., (2005) Method for Producing Medical and Commercial Grade Poly-γ-glutamic Acid of High Molecular Weight, , U. S. Patent 20050095679; Prodhomme, E.J.F., Tutt, A.L., Glennie, M.J., Bugg, T.D.H., Multivalent Conjugates of Poly-γ-D-glutamic Acid from Bacillus licheniformis with Antibody F(abβ) and Glycopeptide Ligands (2003) Bioconjugate Chemistry, 14 (6), pp. 1148-1155. , DOI 10.1021/bc020019m; Sutherland, M.D., Thorkildson, P., Parks, S.D., Kozel, T.R., In vivo fate and distribution of poly-γ-D-glutamic acid, the capsular antigen from Bacillus anthracis (2008) Infection and Immunity, 76 (3), pp. 899-906. , DOI 10.1128/IAI.01176-07; Serizawa, T., Goto, H., Kishida, A., Endo, T., Akashi, M., Improved alternate deposition of biodegradable naturally occurring polymers onto a quartz crystal microbalance (1999) J. Polym. Sci., Part A: Polym. Chem., 37, pp. 801-804; Tachaboonyakiat, W., Serizawa, T., Endo, T., Akashi, M., The influence of molecular weight over the ultrathin films of biodegradable polyion complexes between chitosan and poly(γ-glutamic acid) (2000) Polym. J., 32, pp. 481-485; Hsieh, C.Y., Tsai, S.P., Wang, D.M., Chang, Y.N., Hsieh, H.J., Preparation of γ-PGA/chitosan composite tissue engineering matrices (2005) Biomaterials, 26, pp. 5617-5623; Kang, H.S., Park, S.H., Lee, Y.G., Son, T.I., Polyelectrolyte complex hydrogel composed of chitosan and poly(γ-glutamic acid) for biological application: Preparation, physical properties, and cytocompatibility (2007) J. Appl. Polym. Sci., 103, pp. 386-394; Tsao, C.T., Chang, C.H., Lin, Y.Y., Wu, M.F., Wang, J.L., Han, J.L., Hsieh, K.H., Antibacterial activity and biocompatibility of a chitosan-γ- poly(glutamic acid) polyelectrolyte complex hydrogel (2010) Carbohydr. Res., 345, pp. 1774-1780; Hajdu, I., Bodnar, M., Filipcsei, G., Hartmann, J.F., Daroczi, L., Zrinyi, M., Borbely, J., Nanoparticles prepared by self-assembly of chitosan and poly-γ-glutamic acid (2008) Colloid Polym. Sci., 286, pp. 343-350; Lin, Y.H., Chung, C.K., Chen, C.T., Liang, H.F., Chen, S.C., Sung, H.W., Preparation of nanoparticles composed of chitosan/poly-γ-glutamic acid and evaluation of their permeability through Caco-2 cells (2005) Biomacromolecules, 6, pp. 1104-1112; Imoto, T., Kida, T., Matsusaki, M., Akashi, M., Preparation and unique pH-responsive properties of novel biodegradable nanocapsules composed of poly(γ-glutamic acid) and chitosan as weak polyelectrolytes (2010) Macromol. Biosci., 10, pp. 271-277; Crompton, K.E., Goud, J.D., Bellamkonda, R.V., Gengenbach, T.R., Finkelstein, D.I., Horne, M.K., Forsythe, J.S., Polylysine-functionalised thermoresponsive chitosan hydrogel for neural tissue engineering (2007) Biomaterials, 28 (3), pp. 441-449. , DOI 10.1016/j.biomaterials.2006.08.044, PII S0142961206007642; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42, pp. 3569-3580; Terbojevich, M., Cosani, A., Muzzarelli, R.A.A., Molecular parameters of chitosans depolymerized with the aid of papain (1996) Carbohydrate Polymers, 29 (1), pp. 63-68. , DOI 10.1016/0144-8617(95)00147-6; Kunioka, M., Goto, A., Biosynthesis of poly(γ-glutamic acid) from L-glutamic acid, citric acid, and ammonium sulfate in Bacillus subtilis IFO3335 (1994) Applied Microbiology and Biotechnology, 40 (6), pp. 867-872. , DOI 10.1007/s002530050082; Kubota, H., Matsunobu, T., Uotani, K., Takebe, H., Satoh, A., Tanaka, T., Taniguchi, M., Production of poly(γ-glutamic acid) by Bacillus subtilis F-2-01 (1993) Biosci., Biotechnol., Biochem., 57, pp. 1212-1213; Ashiuchi, M., Soda, K., Misono, H., A poly-γ-glutamate synthetic system of Bacillus subtilis IFO 3336: Gene cloning and biochemical analysis of poly-γ-glutamate produced by Escherichia coli clone cells (1999) Biochemical and Biophysical Research Communications, 263 (1), pp. 6-12. , DOI 10.1006/bbrc.1999.1298; Yamaguchi, F., Ogawa, Y., Kikuchi, M., Yuasa, K., Motai, H., Detection of γ-polyglutamic acid (γ-PGA) by SDS-PAGE (1996) Biosci., Biotechnol., Biochem., 60, pp. 255-258; Scolnik, Y., Portnaya, I., Cogan, U., Tal, S., Haimovitz, R., Fridkin, M., Elitzur, A.C., Shinitzky, M., Subtle differences in structural transitions between poly-L-and poly-D-amino acids of equal length in water (2006) Phys. Chem. Chem. Phys., 8, pp. 333-339; Martins, M.C.L., Ratner, B.D., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methyl-terminated alkanethiols self-assembled monolayers (2003) Journal of Biomedical Materials Research - Part A, 67 (1), pp. 158-171; Gehanno, V., Freitas, P.P., Veloso, A., Ferreira, J., Almeida, B., Sousa, J.B., Kling, A., Da Silva, M.F., Ion beam deposition of Mn-Ir spin valves (1999) IEEE Transactions on Magnetics, 35 (5 PART 3), pp. 4361-4367. , DOI 10.1109/20.799086; Ambrosio, L., Borzacchiello, A., Netti, P.A., Nicolais, L., Properties of new materials: Rheological study on hyaluronic acid and its derivative solutions (1999) Journal of Macromolecular Science - Pure and Applied Chemistry, 36 A (7-8), pp. 991-1000; Horcas, I., Fernandez, R., Gomez-Rodriguez, J.M., Colchero, J., Gomez-Herrero, J., Baro, A.M., WSXM: A software for scanning probe microscopy and a tool for nanotechnology (2007) Rev. Sci. Instrum., 78, p. 1; Martins, M.C.L., Ochoa-Mendes, V., Ferreira, G., Barbosa, J.N., Curtin, S.A., Ratner, B.D., Barbosa, M.A., Interactions of leukocytes and platelets with poly(lysine/leucine) immobilized on tetraethylene glycol-terminated self-assembled monolayers (2011) Acta Biomater., 7, pp. 1949-1955; Werner, C., Konig, U., Augsburg, A., Arnhold, C., Korber, H., Zimmermann, R., Jacobasch, H.-J., Electrokinetic surface characterization of biomedical polymers - A survey (1999) Colloids and Surfaces A: Physicochemical and Engineering Aspects, 159 (2-3), pp. 519-529. , DOI 10.1016/S0927-7757(99)00290-3, PII S0927775799002903; Fairbrother, F., Mastin, H., Studies in electro-endosmosis part I (1924) J. Chem. Soc., 125, pp. 2319-2330; Voinova, M.V., Rodahl, M., Jonson, M., Kasemo, B., Viscoelastic acoustic response of layered polymer films at fluid-solid interfaces: Continuum mechanics approach (1999) Phy. Scr., 59, pp. 391-396; Hook, F., Kasemo, B., Variations in coupled water, viscoelastic properties, and film thickness of a Mefp-1 protein film during adsorption and cross-linking: A quartz crystal microbalance with dissipation monitoring, ellipsometry, and surface plasmon resonance study (2001) Analytical Chemistry, 73 (24), pp. 5796-5804. , DOI 10.1021/ac0106501; Hook, F., Rodahl, M., Brzezinski, P., Kasemo, B., Measurements using the quartz crystal microbalance technique of ferritin monolayers on methyl-thiolated gold: Dependence of energy dissipation and saturation coverage on salt concentration (1998) Journal of Colloid and Interface Science, 208 (1), pp. 63-67. , DOI 10.1006/jcis.1998.5774; Larsson, C., Rodahl, M., Hook, F., Characterization of DNA immobilization and subsequent hybridization on a 2D arrangement of streptavidin on a biotin-modified lipid bilayer supported on SiO 2 (2003) Analytical Chemistry, 75 (19), pp. 5080-5087. , DOI 10.1021/ac034269n; Sauerbrey, G., Verwendung von schwingquarzen zur wagung dunner schichten und zur mikrowagung (1959) Z. Phys., 155, pp. 206-222; Schlenoff, J.B., Dubas, S.T., Mechanism of polyelectrolyte multilayer growth: Charge overcompensation and distribution (2001) Macromolecules, 34 (3), pp. 592-598. , DOI 10.1021/ma0003093; Kim, D.K., Han, S.W., Kim, C.H., Hong, J.D., Kim, K., Morphology of multilayers assembled by electrostatic attraction of oppositely charged model polyelectrolytes (1999) Thin Solid Films, 350, pp. 153-160; Picart, C., Lavalle, Ph., Hubert, P., Cuisinier, F.J.G., Decher, G., Schaaf, P., Voegel, J.-C., Buildup mechanism for poly(L-lysine)/hyaluronic acid films onto a solid surface (2001) Langmuir, 17 (23), pp. 7414-7424. , DOI 10.1021/la010848g; Richert, L., Lavalle, P., Payan, E., Shu, X.Z., Prestwich, G.D., Stoltz, J.F., Schaaf, P., Picart, C., Layer by layer buildup of polysaccharide films: Physical chemistry and cellular adhesion aspects (2004) Langmuir, 20, pp. 448-458; Tsao, C.T., Hang, C.H., Lin, Y.Y., Wu, M.F., Wang, J.L., Young, T.H., Han, J.L., Hsieh, K.H., Evaluation of chitosan/γ-poly(glutamic acid) polyelectrolyte complex for wound dressing materials (2011) Carbohydr. Polym., 84, pp. 812-819; Bonazzola, C., Calvo, E.J., A Fourier transform infrared reflection-absorption spectroscopy study of redox polyelectrolyte films (2003) Langmuir, 19, pp. 5279-5286; Boulmedais, F., Ball, V., Schwinte, P., Frisch, B., Schaaf, P., Voegel, J.C., Buildup of exponentially growing multilayer polypeptide films with internal secondary structure (2003) Langmuir, 19, pp. 440-445; Boulmedais, F., Bozonnet, M., Schwinte, P., Voegel, J.C., Schaaf, P., Multilayered polypeptide films: Secondary structures and effect of various stresses (2003) Langmuir, 19, pp. 9873-9882; He, L.M., Neu, M.P., Vanderberg, L.A., Bacillus lichenformis γ-glutamyl exopolymer: Physicochemical characterization and U(VI) interaction (2000) Environmental Science and Technology, 34 (9), pp. 1694-1701. , DOI 10.1021/es991119e; Chan, Y.H.M., Schweiss, R., Werner, C., Grunze, M., Electrokinetic characterization of oligo-and poly(ethylene glycol)-terminated self-assembled monolayers on gold and glass surfaces (2003) Langmuir, 19, pp. 7380-7385; Giesbers, M., Kleijn, J.M., Cohen Stuart, M.A., The electrical double layer on gold probed by electrokinetic and surface force measurements (2002) Journal of Colloid and Interface Science, 248 (1), pp. 88-95. , DOI 10.1006/jcis.2001.8144; Schlenoff, J.B., Ly, H., Li, M., Charge and mass balance in polyelectrolyte multilayers (1998) Journal of the American Chemical Society, 120 (30), pp. 7626-7634. , DOI 10.1021/ja980350+; Rodahl, M., Hook, F., Fredriksson, C., Keller, C.A., Krozer, A., Brzezinski, P., Voinova, M., Kasemo, B., Simultaneous frequency and dissipation factor QCM measurements of biomolecular adsorption and cell adhesion (1997) Faraday Discussions, 107, pp. 229-246; Guzman, E., San Miguel, V., Peinado, C., Ortega, F., Rubio, R.C., Polyelectrolyte multilayers containing triblock copolymers of different charge ratio (2010) Langmuir, 26, pp. 11494-11502; Salomaki, M., Laiho, T., Kankare, J., Counteranion-controlled properties of polyelectrolyte multilayers (2004) Macromolecules, 37 (25), pp. 9585-9590. , DOI 10.1021/ma048701u; Dutta, A.K., Nayak, A., Belfort, G., Viscoelastic properties of adsorbed and cross-linked polypeptide and protein layers at a solidliquid interface (2008) J. Colloid Interface Sci., 324, pp. 55-60
Keywords: Amino acids; Anionic polymers; article; Atomic force microscopy; Atomic spectroscopy; Biocompatible Materials; Biocompatible polysaccharides; Biomaterials; Biomedical applications; Cell-biomaterial interactions; chemical interaction; chitosan; controlled study; Cytotoxicity; Drug delivery; drug delivery system; Drug Delivery Systems; Electrolytes; ellipsometry; enzyme activity; Extracellular; Fourier transform infrared spectroscopy; Glutamic acid; immunogenicity; infrared spectroscopy; Layer by layer self assembly; Medical applications; microenvironment; Microenvironments; Microscopy, Atomic Force; Model surface; Models, Molecular; Multi-layered; Multi-layered films; Multilayers; nanofilm; Nanostructured Films; polyanion; Polyanions; Polycations; polyelectrolyte; Polyelectrolyte complexes; Polyelectrolyte multilayer; Polyelectrolytes; Polyethylenes; polyglutamic acid; Polymers; priority journal; Programmed control systems; Quartz; quartz crystal microbalance; Quartz crystal microbalance with dissipation; Self assembly; Tissue; Tissue engineering; Tissue regeneration; Ultrathin films; Viscoelastic Substances; Zeta potential; Zeta potential measurements

The limits of agreement and the intraclass correlation coefficient may be inconsistent in the interpretation of agreement - Costa-Santos, C.; Bernardes, J.; Ayres-de-Campos, D.; Costa, A.; Costa, C. (Journal of Clinical EpidemiologyJ. Clin. Epidemiol., 2011)
Objective: To compare the interpretation of agreement in the prediction of neonatal outcome variables, using the limits of agreement (LA) and the intraclass correlation coefficient (ICC). Study Design and Setting: Three obstetricians were asked to predict neonatal outcomes independently based on the evaluation of intrapartum cardiotocographic tracings. Interobserver agreement was assessed with the LA and the ICC, and the results obtained were interpreted by six clinicians and six statisticians on a scale that established agreement as very poor, poor, fair, good, or very good. Results: Interpretation of the LA results was less consensual than the ICC results, with proportions of agreement of 0.36 (95% confidence interval [CI]: 0.28-0.44) vs. 0.63 (95% CI: 0.54-0.73), respectively. LA results suggested a fair to good agreement among obstetricians, whereas interpretation of ICC results suggested a poor to fair agreement. LA results were more plausible with reality, suggesting that obstetricians predicted neonatal outcomes better than randomly generated values, whereas it was not always the case with the ICC. Conclusions: LA and ICC can provide inconsistent results in agreement studies. Accordingly, in the absence of better strategies to assess agreement, both should be used for this purpose, but their results need to be interpreted with caution keeping their respective limitations in mind. © 2011 Elsevier Inc. All rights reserved.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: JCEPEdoi: 10.1016/j.jclinepi.2009.11.010PubMed ID: 20189765Language of Original Document: EnglishCorrespondence Address: Costa-Santos, C.; Biostatistics and Medical Informatics Department, Faculty of Medicine, University of Porto, Al. Prof. Hernâni Monteiro, 4200-319 Porto, Portugal; email: csantos@med.up.ptReferences: De Vet, H., Observer reliability and agreement (1999) Encyclopedia of Biostatistics, pp. 3123-3127;Ayres-De-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in expert's classification of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynaecol, 106, pp. 1307-1310; Santos, C.C., Pereira, C.A., Bernardes, J., Agreement studies in obstetrics and gynaecology: Inappropriateness, controversies and consequences (2005) Br J Obstet Gynaecol, 112, pp. 667-669; Luiz, R.R., Szklo, M., More than one statistical strategy to assess agreement of quantitative measurements may usefully be reported (2003) J Clin Epidemiol, 56, pp. 963-967; Bland, J.M., Altman, D.G., Statistical methods for assessing two methods of clinical measurement (1986) Lancet, 1, pp. 307-310; Bartko, J.J., The intraclass correlation coefficient as a measure of reliability (1966) Psychol Rep, 19, pp. 3-11; Muller, R., Buttner, P., A critical discussion of intraclass correlation coefficients (1994) Stat Med, 13, pp. 2465-2476; Burdock, E., Fleiss, J.L., Hardesty, A.S., A new view of interobserver agreement (1963) Person Psychol, 16, pp. 373-384; Casey, B.M., McLntire, D.D., Leveno, K.J., The continuing value of the Apgar score for the assessment of newborn infants (2001) N Engl J Med, 344, pp. 467-471; Van De Riet, J.E., Vandenbussche, F.P., Le Cessie, S., Keirse, M.J., Newborn assessment and long-term adverse outcome: A systematic review (1999) Am J Obstet Gynecol, 180, pp. 1024-1029; Shrout, P.E., Fleiss, J.L., Intraclass correlations: Uses in assessing rater reliability (1979) Psychol Bull, 86, pp. 420-427; Fleiss, J.U., Davies, M., Measuring nominal scale agreement among many raters (1971) Psychol Bull, 76, pp. 378-382; Carpenter, J., Bithell, J., Bootstrap confidence intervals: When, which, what? A practical guide for medical statisticians (2000) Stat Med, 19, pp. 1141-1164; Landis, J.R., Koch, G.G., The measurement of observer agreement for categorical data (1977) Biometrics, 33, pp. 159-174
Keywords: Agreement; Apgar score; Cardiotocography; correlation coefficient; Female; Fetal Blood; human; Humans; Hydrogen-Ion Concentration; Infant, Newborn; intrapartum care; limit of agreement; newborn assessment; normal human; observer variation; Obstetrics; outcome variable; Pregnancy; Pregnancy Outcome; priority journal; reproducibility; Reproducibility of Results; review; statistical data interpretation; statistical parameters; Umbilical Arteries; Umbilical artery blood pH; umbilical cord blood

Observer reliability and agreement: Differences, difficulties, and controversies - Costa Santos, C.; Bernardes, J.; Ayres-de-Campos, D. (Journal of Clinical EpidemiologyJ. Clin. Epidemiol., 2011)
Keywords: consensus; correlation coefficient; letter; methodology; organization; priority journal; reliability; research; scientific literature; validity

Segmentation of ultrasound images of the carotid using RANSAC and cubic splines - Rocha, R.; Campilho, A.; Silva, J.; Azevedo, E.; Santos, R. (Computer Methods and Programs in BiomedicineComput. Methods Programs Biomed., 2011)
A new algorithm is proposed for the semi-automatic segmentation of the near-end and the far-end adventitia boundary of the common carotid artery in ultrasound images. It uses the random sample consensus method to estimate the most significant cubic splines fitting the edge map of a longitudinal section. The consensus of the geometric model (a spline) is evaluated through a new gain function, which integrates the responses to different discriminating features of the carotid boundary: the proximity of the geometric model to any edge or to valley shaped edges; the consistency between the orientation of the normal to the geometric model and the intensity gradient; and the distance to a rough estimate of the lumen boundary.A set of 50 longitudinal B-mode images of the common carotid and their manual segmentations performed by two medical experts were used to assess the performance of the method. The image set was taken from 25 different subjects, most of them having plaques of different classes (class II to class IV), sizes and shapes.The quantitative evaluation showed promising results, having detection errors similar to the ones observed in manual segmentations for 95% of the far-end boundaries and 73% of the near-end boundaries. © 2011 Elsevier Ireland Ltd.
Cited By (since 1996): 10Export Date: 21 November 2012Source: ScopusCODEN: CMPBEdoi: 10.1016/j.cmpb.2010.04.015PubMed ID: 20554343Language of Original Document: EnglishCorrespondence Address: Rocha, R.; INEB, Divisão de Sinal e Imagem, Campus FEUP, 4200-465 Porto, Portugal; email: rhr@isep.ipp.ptReferences: Baldassarre, D., Amato, M., Bondioli, A., Sirtori, C.R., Tremoli, E., Carotid artery intima-media thickness measured by ultrasonography in normal clinical practice correlates well with atherosclerosis risk factors (2000) Stroke, 31, pp. 2426-2430;O'Leary, D., Polak, J., Kronmal, R., Manolio, T., Burke, G.W.S., Carotid-artery intima and media thickness as a risk factor for myocardial infarction and stroke in older adults (1999) N. Engl. J. Med., 340, pp. 14-22; Hodis, H., Mack, W., LaBree, L., Selzer, R., Liu, C., Liu, C., Azen, S., The role of carotid arterial intima-media thickness in predicting clinical coronary events (1998) Ann. Intern. Med., 128 (4), pp. 262-269; Reneman, R.S., Meinders, J.M., Hoeks, A.P.G., Non-invasive ultrasound in arterial wall dynamics in humans: what have we learned and what remains to be solved (2005) Eur. Heart J., 26, pp. 960-966; Gee, A., Prager, R., Treece, G., Berman, L., Engineering a freehand 3D ultrasound system (2003) Pattern Recogn. Lett., 24 (4-5), pp. 757-777; Sonka, M., Liang, W., Stefancik, R., Stolpen, A., (2000), 2. , Handbook of Medical Imaging: Medical Image Processing and Analysis,SPIEGiannoglou, G.D., Chatzizisis, Y.S., Koutkias, V., Kompatsiaris, I., Papadogiorgaki, M., Mezaris, V., Parissi, E., Louridas, G.E., A novel active contour model for fully automated segmentation of intravascular ultrasound images: in vivo validation in human coronary arteries (2008) Comput. Biol. Med., 37 (9), pp. 1292-1302; Tsai, A., Yezzi, A.J., Tempany, C., Tucker, D., Fan, A., Grimson, W.E.L., Willsky, A.S., A shape-based approach to the segmentation of medical imagery using level sets (2003) IEEE Trans. Med. Imaging, 22 (2), pp. 137-154; Cremers, D., Kohlberger, T., Schnorr, C., Nonlinear shape statistics in Mumford-Shah based segmentation (2002) Proc. European Conf. on Computer Vision (ECCV'2002), vol. 2351, pp. 93-108; Cremers, D., Sochen, N., Schnorr, C., Towards recognition-based variational segmentation using shape priors and dynamic labeling (2003) Proc. European Conf. on Computer Vision (ECCV'2003), vol. 2695, pp. 388-400; Cremers, D., Osher, S., Soatto, S., Kernel density estimation and intrinsic alignment for knowledge-driven segmentation: teaching level sets to walk (2004) Pattern Recognit., 3175, pp. 36-44; Halenka, M., Noninvasive measurement of early atherosclerosis by high-resolution B-mode ultrasonography (1999) Acta-Universitatis Palackianae Olomucensis Facultatis Medicae, 142, pp. 7-12; Touboul, P.J., Prati, P., Scarabin, P.-Y., Adrai, V., Thibout, E., Ducimetiere, P., Use of monitoring software to improve the measurement of carotid wall thickness by B-mode imaging (1992) J. Hypertension, 10 (5), pp. 37-41; Gariepy, J., Massonneau, M., Levenson, J., Heudes, D., Simon, A., Evidence for in vivo carotid and femoral wall thickness in human hypertension (1993) J. Hypertension, 22 (1), pp. 111-118. , the Groupe de Prevention Cardio-vasculaire en Medecine du Travail; Selzer, R.H., Hodis, H.N., Kwong-Fu, H., Mack, W.J., Lee, P.L., Liu, C.R., Liu, C.H., Evaluation of computerized edge tracking for quantifying intima-media thickness of the common carotid artery from B-mode ultrasound images (1994) Atherosclerosis, 111, pp. 1-11; Gustavsson, T., Liang, Q., Wendelhag, I., Wikstrand, J., A dynamic programming procedure for automated ultrasonic measurement of the carotid artery (1994) Comput. Cardiol., pp. 297-300; Kozick, R.J., Detecting interfaces on ultrasound images of the carotid artery by dynamic programming (1996) SPIE, 2666, pp. 233-241; Gustavsson, T., Abu-Gharbieh, R., Hamarneh, G., Liang, Q., Implementation and comparison of four different boundary detection algorithms for quantitative ultrasonic measurements of the human carotid artery (1997) Comput. Cardiol., pp. 69-72; Detmer, P., Bashein, G., Martin, R., Matched filter identification of left-ventricle endocardial borders in transesophageal echocardiograms (1990) IEEE Trans. Med. Imaging, 9 (4), pp. 396-404; Liang, Q., Wendelhag, I., Wikstrand, J., Gustavsson, T., A multiscale dynamic programming procedure for boundary detection in ultrasound artery images (2000) IEEE Trans. Med. Imaging, 19 (2), pp. 127-142; Schmidt-Trucksass, A., Cheng, D., Sandrock, M., Schulte-Monting, J., Rauramaa, R., Huonker, M., Burkhardt, H., Computerized analysing system using the active contour in ultrasound measurement of carotid artery intima-media thickness (2001) Clin. Physiol., 5, pp. 561-569; Cheng, D., Schmidt-Trucksass, A., Cheng, K., Sandrock, M., Pu, Q., Burkhardt, H., (1999), pp. 452-457. , Automatic detection of the intimal and the adventitial layers of the common carotid artery wall in ultrasound B-mode images using snakes, in: Int. Conf. on Image Analysis and Processing, B. WernerCheng, D., Schmidt-Trucksass, A., Cheng, K., Burkhardt, H., Using snakes to detect the intimal and adventitial layers of the common carotid artery wall in sonographic images (2002) Comput. Methods Programs Biomed., 67, pp. 27-37; Kass, M., Witkin, A., Terzopoulos, D., Snakes: active contour models (1988) Int. J. Comput. Vis., pp. 321-331; Christodoulou, C.I., Pattichis, C.S., Pantziaris, M., Nicolaides, A., Texture based classification of atherosclerotic carotid plaques (2003) IEEE Trans. Med. Imaging, 22 (7), pp. 902-912; Barratt, D., Ariff, B., Humphries, K., Thom, S., Hughes, A., Reconstruction and quantification of the carotid artery bifurcation from 3-D ultrasound images (2004) IEEE Trans. Med. Imaging, 23 (5), pp. 567-583; Fischler, M.A., Bolles, R.C., Random sample consensus: a paradigm for model fitting with applications to image analysis and automated cartography (1981) Commun. ACM, 24 (6), pp. 381-395; Rossi, A.C., Brands, P.J., Hoeks, A.P.G., Automatic recognition of the common carotid artery in longitudinal ultrasound B-mode scans (2008) Med. Image Anal., 12, pp. 653-665; Zack, G.W., Rogers, W.E., Latt, S.A., Automatic measurement of sister chromatid exchange frequency (1977) J. Histochem. Cytochem., 25 (7), pp. 741-753; Tauber, C., (2005), Filtrage anisotrope robuste et segmentation par b-spline snake: application aux images échographiques, Ph.D. thesis, Institut National Polytechnique de Toulouse, ToulouseYu, Y., Acton, S., Speckle reducing anisotropic diffusion (2002) IEEE Trans. Image Process., 11 (11), pp. 1260-1270; Yu, Y., Acton, S., Edge detection in ultrasound imagery using the instantaneous coefficient of variation (2004) IEEE Trans. Image Process., 13 (12), pp. 1640-1655; Black, M.J., Sapiro, G., Marimont, D.H., Heeger, D., Robust anisotropic diffusion (1998) IEEE Trans. Image Process., 7 (3), pp. 421-432; Rudin, L., Osher, S., Fatemi, E., Nonlinear total variation based noise removal algorithms (1992) Proceedings of the 11th Annual Int. Conf. of the Center for Nonlinear Studies on Experimental Mathematics: Computational Issues in Nonlinear Science, pp. 259-268; Rudin, L., Osher, S., Total variation based image restoration with free local constraints (1994) Proceedings of IEEE Int. Conf. on Image Processing (ICIP'94), vol. 1, pp. 31-35; Canny, J., A computational approach to edge detection (1986) IEEE Trans. Pattern Anal. Mach. Intell., 8 (6), pp. 679-698; Guo, Z., Hall, R.W., Parallel thinning with two-subiteration algorithms (1989) Commun. ACM, 32 (3), pp. 359-373; Burden, R., Faires, J.D., (2000) Numerical Analysis, , Brooks Cole; Forsyth, D.A., Ponce, J., (2003) Computer Vision: A Modern Approach, , Prentice Hall; Marquina, A., Osher, S., Explicit algorithms for a new time dependent model based on level set motion for nonlinear deblurring and noise removal (2000) SIAM J. Sci. Comput., 22 (2), pp. 387-405; Chum, O., Matas, J., Kittler, J., (2003), 81, pp. 236-243. , Locally optimized RANSAC, in: Lecture Notes in Computer Science - Pattern Recognition, Springer Berlin/Heidelberg, Springer LNCSBland, J.M., Altman, D.G., Statistical methods for assessing agreement between two methods of clinical measurement (1986) Lancet, 1 (8476), pp. 307-310
Keywords: Algorithms; article; B scan; B-mode images; Carotid; carotid artery; Carotid Artery Diseases; Carotid Artery, Common; Class II; clinical article; Common carotid artery; Cubic spline; Detection error; echography; Edge map; Female; Gain function; Geometric models; Geometry; human; Humans; Image Interpretation, Computer-Assisted; image processing; Image segmentation; Image sets; Intensity gradients; Longitudinal section; male; Manual segmentation; mathematical model; Medical experts; Medical imaging; Non-linear smoothing; Pattern Recognition, Automated; quantitative analysis; Quantitative evaluation; random sample; Random sample consensus; RANSAC; Semi-automatic segmentation; Splines; Ultrasonic applications; Ultrasonics; Ultrasonography; Ultrasound image; Ultrasound images

Simulations of the NK cell immune synapse reveal that activation thresholds can be established by inhibitory receptors acting locally - Kaplan, A.; Kotzer, S.; Almeida, C.R.; Kohen, R.; Halpert, G.; Salmon-Divon, M.; Köhler, K.; Höglund, P.; Davis, D.M.; Mehr, R. (Journal of ImmunologyJ. Immunol., 2011)
NK cell activation is regulated by a balance between activating and inhibitory signals. To address the question of how these signals are spatially integrated, we created a computer simulation of activating and inhibitory NK cell immunological synapse (NKIS) assembly, implementing either a "quantity-based" inhibition model or a "distance-based" inhibition model. The simulations mimicked the observed molecule distributions in inhibitory and activating NKIS and yielded several new insights. First, the total signal is highly influenced by activating complex dissociation rates but not by adhesion and inhibitory complex dissociation rates. Second, concerted motion of receptors in clusters significantly accelerates NKIS maturation. Third, when the potential of a cis interaction between Ly49 receptors and MHC class I on murine NK cells was added to the model, the integrated signal as a function of receptor and ligand numbers was only slightly increased, at least up to the level of 50% cis-bound Ly49 receptors reached in the model. Fourth, and perhaps most importantly, the integrated signal behavior obtained when using the distance-based inhibition signal model was closer to the experimentally observed behavior, with an inhibition radius of the order 3-10 molecules. Microscopy to visualize Vav activation in NK cells on micropatterned surfaces of activating and inhibitory strips revealed that Vav is only locally activated where activating receptors are ligated within a single NK cell contact. Taken together, these data are consistent with a model in which inhibitory receptors act locally; that is, that every bound inhibitory receptor acts on activating receptors within a certain radius around it. Copyright © 2011 by The American Association of Immunologists, Inc.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: JOIMAdoi: 10.4049/jimmunol.1002208PubMed ID: 21690326Language of Original Document: EnglishCorrespondence Address: Mehr, R.; Mina and Everard Goodman Faculty of Life Sciences, Bar-Ilan University, Ramat-Gan 52900, Israel; email: ramit.mehr@biu.ac.ilChemicals/CAS: Vav protein, 282122-55-8; intercellular adhesion molecule 1, 126547-89-5; H-2 Antigens; Histocompatibility Antigens Class I; Intercellular Adhesion Molecule-1, 126547-89-5; KLRK1 protein, human; Lymphocyte Function-Associated Antigen-1; MHC class I-related chain A; NK Cell Lectin-Like Receptor Subfamily A; NK Cell Lectin-Like Receptor Subfamily K; Receptors, KIRReferences: Burgess, S.J., Maasho, K., Masilamani, M., Narayanan, S., Borrego, F., Coligan, J.E., The NKG2D receptor: Immunobiology and clinical implications (2008) Immunol. Res., 40, pp. 18-34;González, S., López-Soto, A., Suarez-Alvarez, B., López-Vázquez, A., López-Larrea, C., NKG2D ligands: Key targets of the immune response (2008) Trends Immunol., 29, pp. 397-403; Vyas, Y.M., Maniar, H., Dupont, B., Cutting edge: Differential segregation of the Src homology 2-containing protein tyrosine phosphatase-1 within the early NK cell immune synapse distinguishes noncytolytic from cytolytic interactions (2002) Journal of Immunology, 168 (7), pp. 3150-3154; Long, E.O., Negative signaling by inhibitory receptors: The NK cell paradigm (2008) Immunol. Rev., 224, pp. 70-84; Ljunggren, H.G., Kärre, K., In search of the 'missing self': MHC molecules and NK cell recognition (1990) Immunol. Today, 11, pp. 237-244; Kane, K.P., Silver, E.T., Hazes, B., Specificity and function of activating Ly-49 receptors (2001) Immunol. Rev., 181, pp. 104-114; Lanier, L.L., Up on the tightrope: Natural killer cell activation and inhibition (2008) Nat. Immunol., 9, pp. 495-502; Radaev, S., Sun, P.D., Structure and function of natural killer cell surface receptors (2003) Annu. Rev. Biophys. Biomol. Struct., 32, pp. 93-114; Vivier, E., Nunes, J.A., Vely, F., Natural killer cell signaling pathways (2004) Science, 306 (5701), pp. 1517-1519. , DOI 10.1126/science.1103478; Yokoyama, W.M., Plougastel, B.F., Immune functions encoded by the natural killer gene complex (2003) Nat. Rev. Immunol., 3, pp. 304-316; Stebbins, C.C., Watzl, C., Billadeau, D.D., Leibson, P.J., Burshtyn, D.N., Long, E.O., Vav1 dephosphorylation by the tyrosine phosphatase SHP-1 as amechanism for inhibition of cellular cytotoxicity (2003) Mol. Cell. Biol., 23, pp. 6291-6299; Bryceson, Y.T., Long, E.O., Line of attack: NK cell specificity and integration of signals (2008) Curr. Opin. Immunol., 20, pp. 344-352; McCann, F.E., Suhling, K., Carlin, L.M., Eleme, K., Taner, S.B., Yanagi, K., Vanherberghen, B., Davis, D.M., Imaging immune surveillance by T cells and NK cells (2002) Immunol. Rev., 189, pp. 179-192; Davis, D.M., Assembly of the immunological synapse for T cells and NK cells (2002) Trends in Immunology, 23 (7), pp. 356-363. , DOI 10.1016/S1471-4906(02)02243-3, PII S1471490602022433; Vyas, Y.M., Mehta, K.M., Morgan, M., Maniar, H., Butros, L., Jung, S., Burkhardt, J.K., Dupont, B., Spatial organization of signal transduction molecules in the NK cell immune synapses during MHC class I-regulated noncytolytic and cytolytic interactions (2001) Journal of Immunology, 167 (8), pp. 4358-4367; Vyas, Y.M., Maniar, H., Lyddane, C.E., Sadelain, M., Dupont, B., Ligand binding to inhibitory killer cell Ig-like receptors induce colocalization with Src homology domain 2-containing protein tyrosine phosphatase 1 and interruption of ongoing activation signals (2004) Journal of Immunology, 173 (3), pp. 1571-1578; Orange, J.S., Formation and function of the lytic NK-cell immunological synapse (2008) Nat. Rev. Immunol., 8, pp. 713-725; Eleme, K., Taner, S.B., Onfelt, B., Collinson, L.M., McCann, F.E., Chalupny, N.J., Cosman, D., Davis, D.M., Cell surface organization of stress-inducible proteins ULBP and MICA that stimulate human NK cells and T cells via NKG2D (2004) J. Exp. Med., 199, pp. 1005-1010; Cebo, C., Da, R.S., Wittnebel, S., Turhan, A.G., Abdelali, J., Caillat-Zucman, S., Bourhis, J.H., Caignard, A., The decreased susceptibility of Bcr/Abl targets to NK cell-mediated lysis in response to imatinib mesylate involves modulation of NKG2D ligands, GM1 expression, and synapse formation (2006) Journal of Immunology, 176 (2), pp. 864-872; Burack, W.R., Lee, K.H., Holdorf, A.D., Dustin, M.L., Shaw, A.S., Cutting edge: Quantitative imaging of raft accumulation in the immunological synapse (2002) J. Immunol., 169, pp. 2837-2841; Harder, T., Engelhardt, K.R., Membrane domains in lymphocytes - From lipid rafts to protein scaffolds (2004) Traffic, 5, pp. 265-275; Laude, A.J., Prior, I.A., Plasma membrane microdomains: Organization, function and trafficking (2004) Mol. Membr. Biol., 21, pp. 193-205; Lou, Z., Jevremovic, D., Billadeau, D.D., Leibson, P.J., A balance between positive and negative signals in cytotoxic lymphocytes regulates the polarization of lipid rafts during the development of cell-mediated killing (2000) J. Exp. Med., 191, pp. 347-354; Pike, L.J., Lipid rafts: Bringing order to chaos (2003) Journal of Lipid Research, 44 (4), pp. 655-667. , DOI 10.1194/jlr.R200021-JLR200; Pizzo, P., Viola, A., Lymphocyte lipid rafts: Structure and function (2003) Curr. Opin. Immunol., 15, pp. 255-260; Rodgers, W., Farris, D., Mishra, S., Merging complexes: Properties of membrane raft assembly during lymphocyte signaling (2005) Trends Immunol., 26, pp. 97-103; Schmitz, G., Grandl, M., Update on lipid membrane microdomains (2008) Curr. Opin. Clin. Nutr. Metab. Care, 11, pp. 106-112; Wright, M.D., Moseley, G.W., Van Spriel, A.B., Tetraspanin microdomains in immune cell signalling and malignant disease (2004) Tissue Antigens, 64 (5), pp. 533-542. , DOI 10.1111/j.1399-0039.2004.00321.x; Vogt, A.B., Spindeldreher, S., Kropshofer, H., Clustering of MHCpeptide complexes prior to their engagement in the immunological synapse: Lipid raft and tetraspan microdomains (2002) Immunol. Rev., 189, pp. 136-151; Lee, S.J.E., Hori, Y., Groves, J.T., Dustin, M.L., Chakraborty, A.K., Correlation of a dynamic model for immunological synapse formation with effector functions: Two pathways to synapse formation (2002) Trends Immunol., 23, pp. 492-499; Giagulli, C., Scarpini, E., Ottoboni, L., Narumiya, S., Butcher, E.C., Constantin, G., Laudanna, C., RhoA and zeta PKC Control Distinct Modalities of LFA-1 Activation by Chemokines: Critical Role of LFA-1 Affinity Triggering in Lymphocyte In Vivo Homing (2004) Immunity, 20 (1), pp. 25-35. , DOI 10.1016/S1074-7613(03)00350-9; Masilamani, M., Nguyen, C., Kabat, J., Borrego, F., Coligan, J.E., CD94/NKG2A inhibits NK cell activation by disrupting the actin network at the immunological synapse (2006) J. Immunol., 177, pp. 3590-3596; Weikl, T.R., Lipowsky, R., Pattern formation during T-cell adhesion (2004) Biophysical Journal, 87 (6), pp. 3665-3678. , DOI 10.1529/biophysj.104.045609; Kotzer, S., Salmon-Divon, M., Kaplan, A., Almeida, C.R., Hoglund, P., Davis, D.M., Mehr, R., Modeling the influence of molecule and cell surface micro-domain distribution on the formation of T cell immunological synapses (2007) Life Science Systems and Applications Workshop, 2007. LISA 2007. IEEE/NIH. 8-9 November, , http://ieeexplore.ieee.org/xpl/freeabs_all.jsp?arnumber=4400878, Available at; Culley, F.J., Johnson, M., Evans, J.H., Kumar, S., Crilly, R., Casasbuenas, J., Schnyder, T., Ushakov, D.S., Natural killer cell signal integration balances synapse symmetry and migration (2009) PLoS Biol., 7, pp. e1000159; Treanor, B., Lanigan, P.M.P., Kumar, S., Dunsby, C., Munro, I., Auksorius, E., Culley, F.J., Neil, M.A.A., Microclusters of inhibitory killer immunoglobulin-like receptor signaling at natural killer cell immunological synapses (2006) J. Cell Biol., 174, pp. 153-161; Back, J., Chalifour, A., Scarpellino, L., Held, W., Stable masking by H-2Dd cis ligand limits Ly49A relocalization to the site of NK cell/target cell contact (2007) Proc. Natl. Acad. Sci. USA, 104, pp. 3978-3983; Back, J., Scarpellino, L., Held, W., Probing the interactions of NK cell receptors with ligand expressed in trans and cis (2010) MethodsMol. Biol., 612, pp. 313-323; Chalifour, A., Scarpellino, L., Back, J., Brodin, P., Devèvre, E., Gros, F., Lévy, F., Held, W., A role for cis interaction between the inhibitory Ly49A receptor and MHC class I for natural killer cell education (2009) Immunity, 30, pp. 337-347; Doucey, M.A., Scarpellino, L., Zimmer, J., Guillaume, P., Luescher, I.F., Bron, C., Held, W., Cis association of Ly49A with MHC class I restricts natural killer cell inhibition (2004) Nat. Immunol., 5, pp. 328-336; Held, W., Mariuzza, R.A., Cis interactions of immunoreceptors with MHC and non-MHC ligands (2008) Nat. Rev. Immunol., 8, pp. 269-278; Scarpellino, L., Oeschger, F., Guillaume, P., Coedert, J.D., Levy, F., Leclercq, G., Held, W., Interactions of Ly49 family receptors with MHC class I ligands in trans and cis (2007) Journal of Immunology, 178 (3), pp. 1277-1284; Saffman, P.G., Delbrück, M., Brownian motion in biological membranes (1975) Proc. Natl. Acad. Sci. USA, 72, pp. 3111-3113; Raychaudhuri, S., Chakraborty, A.K., Kardar, M., Effective membrane model of the immunological synapse (2003) Phys. Rev. Lett., 91, p. 208101; Burroughs, N.J., Wülfing, C., Differential segregation in a cell-cell contact interface: The dynamics of the immunological synapse (2002) Biophys. J., 83, pp. 1784-1796; Coombs, D., Goldstein, B., Effects of the geometry of the immunological synapse on the delivery of effector molecules (2004) Biophysical Journal, 87 (4), pp. 2215-2220. , DOI 10.1529/biophysj.104.045674; Köhler, K., Xiong, S., Brzostek, J., Mehrabi, M., Eissmann, P., Harrison, A., Cordoba, S.P., Gould, K., Matched sizes of activating and inhibitory receptor/ligand pairs are required for optimal signal integration by human natural killer cells (2010) PLoS ONE, 5, pp. e15374; Dykstra, M., Cherukuri, A., Sohn, H.W., Tzeng, S.J., Pierce, S.K., Location is everything: Lipid rafts and immune cell signaling (2003) Annu. Rev. Immunol., 21, pp. 457-481; Horejsí, V., The roles of membrane microdomains (rafts) in T cell activation (2003) Immunol. Rev., 191, pp. 148-164; Fujiwara, T., Ritchie, K., Murakoshi, H., Jacobson, K., Kusumi, A., Phospholipids undergo hop diffusion in compartmentalized cell membrane (2002) Journal of Cell Biology, 157 (6), pp. 1071-1081. , DOI 10.1083/jcb.200202050; Giurisato, E., McIntosh, D.P., Tassi, M., Gamberucci, A., Benedetti, A., T cell receptor can be recruited to a subset of plasma membrane rafts, independently of cell signaling and attendantly to raft clustering (2003) J. Biol. Chem., 278, pp. 6771-6778; Kusumi, A., Koyama-Honda, I., Suzuki, K., Molecular dynamics and interactions for creation of stimulation-induced stabilized rafts from small unstable steady-state rafts (2004) Traffic, 5 (4), pp. 213-230. , DOI 10.1111/j.1600-0854.2004.0178.x; Marwali, M.R., MacLeod, M.A., Muzia, D.N., Takei, F., Lipid rafts mediate association of LFA-1 and CD3 and formation of the immunological synapse of CTL (2004) Journal of Immunology, 173 (5), pp. 2960-2967; Montixi, C., Langlet, C., Bernard, A.M., Thimonier, J., Dubois, C., Wurbel, M.A., Chauvin, J.P., He, H.T., Engagement of T cell receptor triggers its recruitment to low-density detergent-insoluble membrane domains (1998) EMBO J., 17, pp. 5334-5348; Munro, S., Lipid rafts: Elusive or illusive? (2003) Cell, 115, pp. 377-388; Pizzo, P., Giurisato, E., Bigsten, A., Tassi, M., Tavano, R., Shaw, A., Viola, A., Physiological T cell activation starts and propagates in lipid rafts (2004) Immunol. Lett., 91, pp. 3-9; Xavier, R., Brennan, T., Li, Q., McCormack, C., Seed, B., Membrane compartmentation is required for efficient T cell activation (1998) Immunity, 8, pp. 723-732; Filipp, D., Julius, M., Lipid rafts: Resolution of the "fyn problem"? (2004) Mol. Immunol., 41, pp. 645-656; Schade, A.E., Levine, A.D., Lipid raft heterogeneity in human peripheral blood T lymphoblasts: A mechanism for regulating the initiation of TCR signal transduction (2002) J. Immunol., 168, pp. 2233-2239; Janes, P.W., Ley, S.C., Magee, A.I., Aggregation of lipid rafts accompanies signaling via the T cell antigen receptor (1999) J. Cell Biol., 147, pp. 447-461; Hiltbold, E.M., Poloso, N.J., Roche, P.A., MHC class II-peptide complexes and APC lipid rafts accumulate at the immunological synapse (2003) J. Immunol., 170, pp. 1329-1338; Wülfing, C., Tskvitaria-Fuller, I., Burroughs, N., Sjaastad, M.D., Klem, J., Schatzle, J.D., Interface accumulation of receptor/ligand couples in lymphocyte activation: Methods, mechanisms, and significance (2002) Immunol. Rev., 189, pp. 64-83; Poloso, N.J., Roche, P.A., Association of MHC class II-peptide complexes with plasma membrane lipid microdomains (2004) Curr. Opin. Immunol., 16, pp. 103-107; Anderson, H.A., Hiltbold, E.M., Roche, P.A., Concentration of MHC class II molecules in lipid rafts facilitates antigen presentation (2000) Nat. Immunol., 1, pp. 156-162; Meyer Zum Bueschenfelde, C.O., Unternaehrer, J., Mellman, I., Bottomly, K., Regulated recruitment of MHC class II and costimulatory molecules to lipid rafts in dendritic cells (2004) J. Immunol., 173, pp. 6119-6124; Szollosi, J., Horejsi, V., Bene, L., Angelisova, P., Damjanovich, S., Supramolecular Complexes of MHC Class I, MHC Class II, CD20, and Tetraspan Molecules (CD53, CD81, and CD82) at the Surface of a B Cell Line JY (1996) Journal of Immunology, 157 (7), pp. 2939-2946; Leitinger, B., Hogg, N., The involvement of lipid rafts in the regulation of integrin function (2002) Journal of Cell Science, 115 (5), pp. 963-972; Cherukuri, A., Cheng, P.C., Pierce, S.K., The role of the CD19/CD21 complex in B cell processing and presentation of complement-tagged antigens (2001) J. Immunol., 167, pp. 163-172; Sheets, E.D., Holowka, D., Baird, B., Critical role for cholesterol in Lyn-mediated tyrosine phosphorylation of FcepsilonRI and their association with detergent-resistant membranes (1999) Journal of Cell Biology, 145 (4), pp. 877-887. , DOI 10.1083/jcb.145.4.877; Jordan, S., Rodgers, W., T cell glycolipid-enriched membrane domains are constitutively assembled as membrane patches that translocate to immune synapses (2003) Journal of Immunology, 171 (1), pp. 78-87; Kaizuka, Y., Douglass, A.D., Vardhana, S., Dustin, M.L., Vale, R.D., The coreceptor CD2 uses plasma membrane microdomains to transduce signals in T cells (2009) J. Cell Biol., 185, pp. 521-534; Dustin, M.L., Membrane domains and the immunological synapse: Keeping T cells resting and ready (2002) J. Clin. Invest., 109, pp. 155-160; Almeida, C.R., Davis, D.M., Segregation of HLA-C from ICAM-1 at NK cell immune synapses is controlled by its cell surface density (2006) J. Immunol., 177, pp. 6904-6910; Delon, J., The immunological synapse (2000) Curr. Biol., 10, pp. R214; Anton Van Der Merwe, P., Davis, S.J., Shaw, A.S., Dustin, M.L., Cytoskeletal polarization and redistribution of cell-surface molecules during T cell antigen recognition (2000) Semin. Immunol., 12, pp. 5-21; Bossi, G., Trambas, C., Booth, S., Clark, R., Stinchcombe, J., Griffiths, G.M., The secretory synapse: The secrets of a serial killer (2002) Immunol. Rev., 189, pp. 152-160; Endt, J., McCann, F.E., Almeida, C.R., Urlaub, D., Leung, R., Pende, D., Davis, D.M., Watzl, C., Inhibitory receptor signals suppress ligation-induced recruitment of NKG2D to GM1-rich membrane domains at the human NK cell immune synapse (2007) Journal of Immunology, 178 (9), pp. 5606-5611; Gasser, S., Raulet, D.H., Activation and self-tolerance of natural killer cells (2006) Immunol. Rev., 214, pp. 130-142; Rubio, G., Férez, X., Sánchez-Campillo, M., Gálvez, J., Martí, S., Verdú, R., Hernández-Caselles, T., García-Peñarrubia, P., Cross-linking of MHC class I molecules on human NK cells inhibits NK cell function, segregates MHC I from the NK cell synapse, and induces intracellular phosphotyrosines (2004) J. Leukoc. Biol., 76, pp. 116-124; Kaizuka, Y., Douglass, A.D., Varma, R., Dustin, M.L., Vale, R.D., Mechanisms for segregating T cell receptor and adhesion molecules during immunological synapse formation in Jurkat T cells (2007) Proc. Natl. Acad. Sci. USA, 104, pp. 20296-20301; Brodin, P., Lakshmikanth, T., Mehr, R., Johansson, M.H., Duru, A.D., Achour, A., Salmon-Divon, M., Johansson, S., Natural killer cell tolerance persists despite significant reduction of self MHC class I on normal target cells in mice (2010) PLoS ONE, 5, pp. e1317; Carlin, L.M., Eleme, K., McCann, F.E., Davis, D.M., Intercellular transfer and supramolecular organization of human leukocyte antigen C at inhibitory natural killer cell immune synapses (2001) J. Exp. Med., 194, pp. 1507-1517; Fassett, M.S., Davis, D.M., Valter, M.M., Cohen, G.B., Strominger, J.L., Signaling at the inhibitory natural killer cell immune synapse regulates lipid raft polarization but not class I MHC clustering (2001) Proc. Natl. Acad. Sci. USA, 98, pp. 14547-14552; Faure, M., Barber, D.F., Takahashi, S.M., Jin, T., Long, E.O., Spontaneous clustering and tyrosine phosphorylation of NK cell inhibitory receptor induced by ligand binding (2003) J. Immunol., 170, pp. 6107-6114; Standeven, L.J., Carlin, L.M., Borszcz, P., Davis, D.M., Burshtyn, D.N., The actin cytoskeleton controls the efficiency of killer Ig-like receptor accumulation at inhibitory NK cell immune synapses (2004) J. Immunol., 173, pp. 5617-5625; Abeyweera, T.P., Merino, E., Huse, M., Inhibitory signaling blocks activating receptor clustering and induces cytoskeletal retraction in natural killer cells (2011) J. Cell Biol., 192, pp. 675-690; Labadia, M.E., Jeanfavre, D.D., Caviness, G.O., Morelock, M.M., Molecular regulation of the interaction between leukocyte function-associated antigen-1 and soluble ICAM-1 by divalent metal cations (1998) J. Immunol., 161, pp. 836-842; Tominaga, Y., Kita, Y., Satoh, A., Asai, S., Kato, K., Ishikawa, K., Horiuchi, T., Takashi, T., Affinity and kinetic analysis of the molecular interaction of ICAM-1 and leukocyte function-associated antigen-1 (1998) Journal of Immunology, 161 (8), pp. 4016-4022; Maenaka, K., Van Der Merwe, P.A., Stuart, D.I., Jones, E.Y., Sondermann, P., The human low affinity Fcgamma receptors IIa, IIb, and III bind IgG with fast kinetics and distinct thermodynamic properties (2001) J. Biol. Chem., 276, pp. 44898-44904; Dustin, M.L., Ferguson, L.M., Chan, P.Y., Springer, T.A., Golan, D.E., Visualization of CD2 interaction with LFA-3 and determination of the twodimensional dissociation constant for adhesion receptors in a contact area (1996) J. Cell Biol., 132, pp. 465-474; Sloan-Lancaster, J., Presley, J., Ellenberg, J., Yamazaki, T., Lippincott-Schwartz, J., Samelson, L.E., ZAP-70 association with T cell receptor zeta (TCRzeta): Fluorescence imaging of dynamic changes upon cellular stimulation (1998) J. Cell Biol., 143, pp. 613-624; Von Essen, M., Bonefeld, C.M., Siersma, V., Rasmussen, A.B., Lauritsen, J.P.H., Nielsen, B.L., Geisler, C., Constitutive and ligand-induced TCR degradation (2004) Journal of Immunology, 173 (1), pp. 384-393; Groves, J.T., Wulfing, C., Boxer, S.G., Electrical manipulation of glycan-phosphatidyl inositol-tethered proteins in planar supported bilayers (1996) Biophys. J., 71, pp. 2716-2723; Krogsgaard, M., Li, Q.J., Sumen, C., Huppa, J.B., Huse, M., Davis, M.M., Agonist/endogenous peptide-MHC heterodimers drive T cell activation and sensitivity (2005) Nature, 434, pp. 238-243; Dimasi, N., Sawicki, M.W., Reineck, L.A., Li, Y., Natarajan, K., Margulies, D.H., Mariuzza, R.A., Crystal structure of the Ly49I natural killer cell receptor reveals variability in dimerization mode within the Ly49 family (2002) J. Mol. Biol., 320, pp. 573-585; Natarajan, K., Boyd, L.F., Schuck, P., Yokoyama, W.M., Eliat, D., Margulies, D.H., Interaction of the NK cell inhibitory receptor Ly49A with H-2Dd: Identification of a site distinct from the TCR site (1999) Immunity, 11, pp. 591-601; O'Callaghan, C.A., Cerwenka, A., Willcox, B.E., Lanier, L.L., Bjorkman, P.J., Molecular competition for NKG2D: H60 and RAE1 compete unequally for NKG2D with dominance of H60 (2001) Immunity, 15, pp. 201-211; Borrego, F., Masilamani, M., Marusina, A.I., Tang, X., Coligan, J.E., The CD94/NKG2 family of receptors: From molecules and cells to clinical relevance (2006) Immunol. Res., 35, pp. 263-278
Keywords: animal cell; animal experiment; Animals; antigen recognition; article; cell maturation; cell membrane; Computer simulation; controlled study; dissociation; H-2 Antigens; Histocompatibility Antigens Class I; HLA antigen; HLA C antigen; Humans; immunological synapse; Immunological Synapses; intercellular adhesion molecule 1; Intercellular Adhesion Molecule-1; killer cell immunoglobulin like receptor 2DL1; Killer Cells, Natural; lymphocyte activation; lymphocyte function associated antigen 1; Lymphocyte Function-Associated Antigen-1; major histocompatibility antigen class 1; Membrane Microdomains; Mice; Models, Immunological; mouse; natural killer cell; natural killer cell receptor NKG2D; NK Cell Lectin-Like Receptor Subfamily A; NK Cell Lectin-Like Receptor Subfamily K; nonhuman; priority journal; protein assembly; Receptors, KIR; signal transduction; steady state; Vav protein

Access to computerised analysis of intrapartum cardiotocographs improves clinicians' prediction of newborn umbilical artery blood pH - Costa, A.; Santos, C.; Ayres-de-Campos, D.; Costa, C.; Bernardes, J. (BJOG: An International Journal of Obstetrics and GynaecologyBJOG Int. J. Obstet. Gynaecol., 2010)
Objective To evaluate the impact of access to computerised cardiotocograph (CTG) analysis on reproducibility and accuracy of clinicians' predictions of umbilical artery blood pH (UAB pH) and 5-minute Apgar score. Design Prospective evaluation of pre-recorded cases. Setting A tertiary-care university hospital. Population From databases of intrapartum CTGs acquired in singleton term pregnancies, 204 tracings with low signal loss and short time interval to delivery were consecutively selected. Methods Tracings were randomly assigned to computer analysis by the Omniview-SisPorto 3.5 ® system (study group n = 104) or to no analysis (control group n = 100). Three experienced clinicians evaluated all tracing printouts independently and were asked to predict the newborns' UAB pH and 5-minute Apgar scores from them. Main outcome measures Interobserver agreement (measured by the intraclass correlation coefficient [ICC]) and accuracy in prediction of neonatal outcomes with 95% CI. Results Agreement on prediction of UAB pH was significantly higher in the study group (ICC = 0.70; 95% CI 0.61-0.77) than in the control group (ICC = 0.43; 95% CI 0.21-0.60), and a trend towards better agreement was also seen in estimation of 5-minute Apgar scores (ICC = 0.55; 95% CI 0.38-0.68 versus ICC = 0.43; 95% CI 0.25-0.57). Observers predicted UAB pH values correctly within a 0.10 margin in 70% of cases in the study group (95% CI 0.61-0.79) versus 46% in the control group (95% CI 0.35-0.56). They predicted 5-minute Apgar scores within a margin of one in 81% of cases in the study group (95% CI 0.73-0.88) and in 70% of cases in the control group (95% CI 0.61-0.79). Conclusions Prediction of UAB pH is more reproducible and accurate when clinicians have access to computerised analysis of CTGs. © RCOG 2010 BJOG An International Journal of Obstetrics and Gynaecology.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: BIOGFdoi: 10.1111/j.1471-0528.2010.02645.xPubMed ID: 20618316Language of Original Document: EnglishCorrespondence Address: Costa, A.; Departamento de Ginecologia e Obstetrícia, Faculdade de Medicina da Universidade Do Porto, Alameda Hernani Monteiro, 4200-319 Porto, Portugal; email: cosantonia@gmail.comReferences: Ayres-De-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in classification by experts of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynaecol, 106, pp. 1307-10;Donker, D.K., Van Geijn, H.P., Hasman, A., Interobserver variation in the assessment of fetal heart rate recordings (1993) Eur J Obstet Gynecol Reprod Biol, 52, pp. 21-8; Paneth, N., Bommarito, M., Stricker, J., Electronic fetal monitoring and later outcome (1993) Clin Invest Med, 16, pp. 159-65; Bernardes, J., Moura, C., Marques-De-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-5; Ayres-De-Campos, D., Sousa, P., Costa, A., Bernardes, J., Omniview-SisPorto ® 3.5 - A central fetal monitoring station with online alerts based on computerized cardiotocogram+ST event analysis (2008) J Perinat Med, 36, pp. 260-4; Costa, A., Ayres-De-Campos, D., Costa, F., Santos, C., Bernardes, J., Prediction of neonatal acidemia by computer analysis of fetal heart rate and ST event signals (2009) Am J Obstet Gynecol, 201, pp. 464e1-6. , Jun 17. [Epub ahead of print]; Westerhuis, M., Van Horen, E., Kwee, A., Van Dertweel, I., Visser, G., Moons, K., Inter- and intra-observer agreement of intrapartum ST analysis of the fetal electrocardiogram in women monitored by STAN (2009) BJOG, 116, pp. 545-51; Ayres-De-Campos, D., Bernardes, J., Marsalb, K., Nickelsen, C., Makarainend, L., Banfield, P., Can the reproducibility of fetal heart rate baseline estimation be improved? (2004) Eur J Obstet Gynecol Reprod Biol, 112, pp. 49-54; Huch, A., Huch, C., Rooth, G., Guidelines for blood sampling and measurement of pH and blood gas values in Obstetrics (1994) Eur J Obstet Gynecol Reprod Biol, 54, pp. 165-75; Umbilical artery blood acid-base analysis (1996) Int J Gynecol Obstet, 52, pp. 305-10. , ACOG technical bulletin; Westgate, J., Garibaldi, J.M., Greene, K.R., Umbilical cord blood gas analysis at delivery: A time for quality data (1994) Br J Obstet Gynaecol, 101, pp. 1054-63; Costa-Santos, C., Costa Pereira, A., Bernardes, J., Agreement studies in obstetrics and gynaecology: Inappropriateness, controversies and consequences (2005) BJOG, 112, pp. 667-9; Bland, J.M., Altman, D.G., Agreement between methods of measurement with multiple observations per individual (2007) J Biopharm Stat, 17, pp. 571-82; Chauhan, S.P., Klauser, C.K., Woodring, T.C., Sanderson, M., Magann, E.F., Morrison, J.C., Intrapartum nonreassuring fetal heart rate tracing and prediction of adverse outcomes: Interobserver variability (2008) Am J Obstet Gynecol, 199, pp. 623e1-e5; Nielsen, P.V., Stigsby, B., Nickelsen, C., Nim, J., The value of computer assessment compared with visual assessment (1988) Acta Obstet Gynecol Scand, 67, pp. 461-464
Keywords: access to information; Apgar score; arterial pH; article; Cardiotocography; clinical competence; computer analysis; computerised analysis; controlled study; delivery; Diagnosis, Computer-Assisted; diagnostic accuracy; Female; Fetal Blood; Fetal heart rate; Fetal monitoring; Gestational Age; human; Humans; Hydrogen-Ion Concentration; Infant, Newborn; male; neonatal acidaemia; Neonatology; newborn; observer variation; outcome assessment; prediction; Pregnancy; priority journal; Prospective Studies; prospective study; reproducibility; Umbilical Arteries; umbilical artery; university hospital

Adhesion of human leukocytes on mixtures of hydroxyl- and methyl-terminated self-assembled monolayers: Effect of blood protein adsorption - Barbosa, J.N.; Martins, M.C.L.; Freitas, S.C.; Gonçalves, I.C.; Águas, A.P.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
The adhesion of human leukocytes to nanostructured surfaces with different chemical properties and the effect of protein adsorption were investigated. Selfassembled monolayers (SAMs) prepared with mixtures of methyl- and hydroxyl-terminated alkanethiols in different percentages on gold were used. The surfaces were preimmersed in distinct protein solutions (human serum albumin, human fibrinogen, and autologous plasma). Adherent leukocytes were analyzed both by light and SEM. SAMs submitted to pre-immersion in plasma presented higher numbers of adherent leukocytes in the pure OH-terminated SAM, whereas methyl-terminated surfaces accounted for the lowest number of adherent cells. We observed a general increase in the number of adherent human leukocytes as the percentage of OH groups on the surface of the SAMs increased for all the pre-immersion conditions investigated. The number of adherent human leukocytes is highly influenced by the pre-immersion conditions used, and this observation is particularly relevant in the case of the methyl-terminated SAMs. The results obtained demonstrate that surface chemistry has a major influence in leukocyte adhesion to biomaterials, and that pre-immersion in protein solutions has a determinant effect in leukocyte adhesion. © 2009 Wiley Periodicals, Inc.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.32480PubMed ID: 19484768Language of Original Document: EnglishCorrespondence Address: Barbosa, J. N.; Divisão de Biomateriais, INEB-Instituto de Engenharia Biomédica, Universidade do Porto, Porto 4150-180, Portugal; email: judite@ineb.up.ptChemicals/CAS: Blood Proteins; Gold, 7440-57-5; Hydroxyl Radical, 3352-57-6References: Brodbeck, W.G., Nakayama, Y., Matsuda, T., Colton, E., Ziats, N.P., Anderson, J.M., Biomaterial surface chemistry dictates adherent monocyte/macrophage cytokine expression in vitro (2002) Cytokine, 18, pp. 311-319;Kao, W.Y.J., Evaluation of leukocyte adhesion on polyurethanes: The effects of shear stress and blood proteins (2000) Biomaterials, 21, pp. 2295-2303; Tegoulia, V.A., Cooper, S.L., Leukocyte adhesion on model surfaces under flow: Effects of surface chemistry, protein adsorption, and shear rate (2000) J Biomed Mater Res, 50, pp. 291-301; Nimeri, G., Ohman, L., Elwing, H., Wettero, J., Bengtsson, T., The influence of plasma proteins and platelets on oxygen radical production and F-actin distribution in neutrophils adhering to polymer surfaces (2002) Biomaterials, 23, pp. 1785-1795; Wettero, J., Bengtsson, T., Tengvall, P., C1q-independent activation of neutrophils by immunoglobulin M-coated surfaces (2001) J Biomed Mater Res, 57, pp. 550-558; Yung, L.Y.L., Colman, R.W., Cooper, S.L., Neutrophil adhesion on polyurethanes preadsorbed with high molecular weight kininogen (1999) Blood, 94, pp. 2716-2724; Eriksson, C., Nygren, H., Polymorphonuclear leukocytes in coagulating whole blood recognize hydrophilic and hydrophobic titanium surfaces by different adhesion receptors and show different patterns of receptor expression (2001) J Lab Clin Med, 137, pp. 296-302; Tang, L.P., Eaton, J.W., Mechanism of acute inflammatory response to biomaterials (1994) Cell Mater, 4, pp. 429-436; Tang, L.P., Eaton, J.W., Inflammatory responses to biomaterials (1995) Am J Clin Pathol, 103, pp. 466-471; Jenney, C.R., Anderson, J.M., Adsorbed serum proteins responsible for surface dependent human macrophage behavior (1999) J Biomed Mater Res, 49, pp. 435-447; Collier, T.O., Anderson, J.M., Protein and surface effects on monocyte and macrophage adhesion, maturation, and survival (2002) J Biomed Mater Res, 60, pp. 487-496; Yun, J.K., Defife, K., Colton, E., Stack, S., Azeez, A., Cahalan, L., Verhoeven, M., Anderson, J.M., Human monocytemacrophage adhesion and cytokine production on surface-modified poly(tetrafluoroethylene hexafluoropropylene) polymers with and without protein preadsorption (1995) J Biomed Mater Res, 29, pp. 257-268; Ulman, A., Formation and structure of self-assembled monolayers (1996) Chem Rev, 96, pp. 1533-1554; Mrksich, M., Tailored substrates for studies of attached cell culture (1998) Cell Mol Life Sci, 54, pp. 653-662; Mrksich, M., Model substrates for studying and controlling cell adhesion (2000) Abstr Pap Am Chem Soc, 219, pp. U572-U572; Rodrigues, S.N., Goncalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Fibrinogen adsorption, platelet adhesion and activation on mixed hydroxyl-/methyl-terminated self-assembled monolayers (2006) Biomaterials, 27, pp. 5357-5367; Martins, M.C.L., Ratner, B.D., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methylterminated alkanethiols self-assembled monolavers (2003) J Biomed Mater Res, 67 A, pp. 158-171. , Part A; Anderson, J.M., Biological responses to materials (2001) Annu Rev Mater Res, 31, pp. 81-110; Tang, L.P., Liu, L., Elwing, H.B., Complement activation and inflammation triggered by model biomaterial surfaces (1998) J Biomed Mater Res, 41, pp. 333-340; Bergman, A.J., Zygourakis, K., Migration of lymphocytes on fibronectin-coated surfaces: Temporal evolution of migratory parameters (1999) Biomaterials, 20, pp. 2235-2244; Taborelli, M., Eng, L., Descouts, P., Ranieri, J.P., Bellamkonda, R., Aebischer, P., Bovine serum-albumin conformation on methyl and amine functionalized surfaces compared by scanning force microscopy (1995) J Biomed Mater Res, 29, pp. 707-714; Liu, L., Elwing, H., Complement activation on thiol-modi.ed gold surfaces (1996) J Biomed Mater Res, 30, pp. 535-541; Sperling, C., Schweiss, R.B., Streller, U., Werner, C., In vitro hemocompatibility of self-assembled monolayers displaying various functional groups (2005) Biomaterials, 26, pp. 6547-6557; Hirata, I., Hioko, Y., Toda, M., Kitazawa, T., Murakami, Y., Kitano, E., Kitamura, H., Iwata, H., Deposition of complement protein C3b on mixed self-assembled monolayers carrying surface hydroxyl and methyl groups studied by surface plasmon resonance (2003) J Biomed Mater Res, 66 A, pp. 669-676. , Part A; Kalltorp, M., Oblogina, S., Jacobsson, S., Karlsson, A., Tengvall, P., Thomsen, P., In vivo cell recruitment, cytokine release and chemiluminescence response at gold, and thiol functionalized surfaces (1999) Biomaterials, 20, pp. 2123-2137; Brash, J.L., Tenhove, P., Protein adsorption studies on standard polymeric materials (1993) J Biomater Sci Polym Ed, 4, pp. 591-599; Brash, J.L., Tenhove, P., Effect of plasma dilution on adsorption of fibrinogen to solid-surfaces (1984) Thromb Haemost, 51, pp. 326-330; Tang, L.P., Ugarova, T.P., Plow, E.F., Eaton, J.W., Molecular determinants of acute inflammatory responses to biomaterials (1996) J Clin Invest, 97, pp. 1329-1334; Thomsen, P., Gretzer, C., Macrophage interactions with modified material surfaces (2001) Curr Opin Solid State Mater Sci, 5, pp. 163-176; Werthen, M., Sellborn, A., Kalltorp, M., Elwing, H., Thomsen, P., In vitro study of monocyte viability during the initial adhesion to albumin- and fibrinogen-coated surfaces (2001) Biomaterials, 22, pp. 827-832; Wettero, J., Bengtsson, T., Tengvall, P., Complement activation on immunoglobulin G-coated hydrophobic surfaces enhances the release of oxygen radicals from neutrophils through an actin-dependent mechanism (2000) J Biomed Mater Res, 51, pp. 742-751; Jenney, C.R., Anderson, J.M., Adsorbed IgG: A potent adhesive substrate for human macrophages (2000) J Biomed Mater Res, 50, pp. 281-290; Lindblad, M., Lestelius, M., Johansson, A., Tengvall, P., Thomsen, P., Cell and soft tissue interactions with methyl- and hydroxyl-terminated alkane thiols on gold surfaces (1997) Biomaterials, 18, pp. 1059-1068; Roach, P., Farrar, D., Perry, C.C., Interpretation of protein adsorption: Surface-induced conformational changes (2005) J Am Chem Soc, 127, pp. 8168-8173; Barbosa, J.N., Barbosa, M.A., Aguas, A.P., Adhesion of human leukocytes to biomaterials: An in vitro study using alkanethiolate monolayers with different chemically functionalized surfaces (2003) J Biomed Mater Res, 65 A, pp. 429-434. , Part A; Barbosa, J.N., Barbosa, M.A., Aguas, A.P., Inflammatory responses and cell adhesion to self-assembled monolayers of alkanethiolates on gold (2004) Biomaterials, 25, pp. 2557-2563; Barbosa, J.N., Barbosa, M.A., Aguas, A.P., Inflammatory cell recruitment and adhesion to methyl-terminated selfassembled monolayers: Effect of implantation time (2005) Microsc Res Tech, 66, pp. 37-42; Barbosa, J.N., Madureira, P., Barbosa, M.A., Aguas, A.P., The attraction of Mac-1(+) phagocytes during acute inflammation by methyl-coated self-assembled monolayers (2005) Biomaterials, 26, pp. 3021-3027
Keywords: Adherent cells; Adhesion; Adsorption; Alkanethiols; article; Biological materials; biomaterial; Blood protein adsorption; Blood Proteins; cell adhesion; Cell Count; Chemical properties; gold; human; human cell; Human leukocytes; Human serum albumins; Humans; hydroxyl group; Hydroxyl Radical; Hydroxyl-terminated; immersion; Inflammatory response; leukocyte adherence; Leukocyte adhesion; Leukocytes; Nanostructured materials; Nanostructured surface; Nanostructured surfaces; OH group; Protein adsorption; protein blood level; Protein solution; Proteins; Sams; Scanning electron microscopy; Self assembled monolayers; Self-assembled monolayers; SEM; Surface chemistry; Surface Properties

Assessment of Disagreement: A New Information-Based Approach - Costa-Santos, C.; Antunes, L.; Souto, A.; Bernardes, J. (Annals of EpidemiologyAnn. Epidemiol., 2010)
Purpose: Disagreement on the interpretation of diagnostic tests and clinical decisions remains an important problem in medicine. As no strategy to assess agreement seems to be fail-safe to compare the degree of agreement, or disagreement, we propose a new information-based approach to assess disagreement. Methods: The sum over all logarithms of possible outcomes of a variable is a valid measure of the amount of information contained in the variable. The proposed measure is based on the amount of information contained in the differences between two observations. This measure is normalized and satisfies the flowing properties: it is a metric, scaled invariant and it has differential weighting. Results: Two real examples and a simulation were used to illustrate the usefulness of the proposed measure to compare the degree of disagreement. Conclusions: Used as complement to the existing methods, we believe our approach can be useful to compare the degree of disagreement among different populations. © 2010 Elsevier Inc.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: ANNPEdoi: 10.1016/j.annepidem.2010.02.011Language of Original Document: EnglishCorrespondence Address: Costa-Santos, C.; Biostatistics and Medical Informatics Department, Faculty of Medicine, University of Porto, Al. Prof. Hernâni Monteiro, 4200-319 Porto, Portugal; email: csantos@med.up.ptReferences: Bland, M., (2000) An introduction to medical statistics, , Oxford University Press, Oxford;Costa Santos, C., Costa Pereira, A., Bernardes, J., Agreement studies in obstetrics and gynecology: inappropriateness, controversies and consequences (2005) Br J Obstet Gynaecol, 112, pp. 667-669; Gow, R.M., Barrowman, N.J., Lai, L., Moher, D., A review of five cardiology journals found that observer variability of measured variables was infrequently reported (2008) J Clin Epidemiol, 61, pp. 394-401; Luiz, R.R., Szklo, M., More than one statistical strategy to assess agreement of quantitative measurements may usefully be reported (2005) J Clin Epidemiol, 58, pp. 215-216; de Vet, H., Observer reliability and agreement (1999) Encyclopedia of Biostatistics, pp. 3123-3127. , Wiley, Chichester, P. Armitage, T. Colton (Eds.); Shrout, P.E., Fleiss, J.L., Intraclass correlation: uses in assessing rater reliability (1979) Psychol Bull, 88, pp. 420-428; Burdock, E.I., Fleiss, J.L., Hardesty, A.S., A new view of interobserver agreement (1963) Psychol Bull, 16, pp. 373-384; McGraw, K.O., Wong, S.P., Forming inferences about some intraclass correlation coefficients (1996) Psychol Methods, 1, pp. 30-46; Muller, R., Buttner, P., A critical discussion of intraclass correlation coefficients (1994) Stat Med, 13, pp. 2465-2476; Steiner, D.L., Norman, G.R., (2003) Health measurements scales. A practical guide to their development and use, , Oxford University Press, Oxford; Lee, D., Koh, D., Ong, C.N., Statistical evaluation of the agreement between two methods for measuring a quantitative variable (1989) Comput Biol Med, 19, pp. 61-70; Lin, L.K., A concordance correlation coefficient to evaluate reproducibility (1989) Biometrics, 45, pp. 255-268; Nickerson, C.A.E., A note on " A Concordance Correlation Coefficient to Evaluate Reproducibility" (1997) Biometrics, 53, pp. 1503-1507; Atkinson, G., Nevill, A., Comment on the " Use of Concordance Correlation to Assess the Agreement between Two Variables" (1997) Biometrics, 53, pp. 775-777; Bland, J.M., Altman, D.G., Statistical methods for assessing two methods of clinical measurement (1986) Lancet, 1, pp. 307-310; Luiz, R.R., Costa, A.J., Kale, P.L., Werneck, G.L., Assessment of agreement of a quantitative variable: a new graphical approach (2003) J Clin Epidemiol, 56, pp. 963-967; Monti, K.L., Folded empirical distribution function curves-mountain plots (1995) Am Stat, 33, pp. 525-527; Shannon, I., A mathematical theory of communication (1948) Bell System Tech J, 27, pp. 379-423. , 623-656; Bland, J.M., Altaman, D.G., Measuring agreement in method comparison studies (1999) Stat Methods Med Res, 8, pp. 135-160
Keywords: analysis of variance; Apgar score; article; Blood Pressure Determination; blood pressure measurement; correlation coefficient; human; Humans; information science; Information Theory; intermethod comparison; mathematical computing; measurement error; medical research; metric system; Models, Statistical; observer variation; priority journal; probability; process model; reliability; Reproducibility of Results; scale up; standard; Statistical analysis; statistical model; statistics; Statistics as Topic; systolic blood pressure; validity; variance

Bioactivity of immobilized EGF on self-assembled monolayers: Optimization of the immobilization process - Gonçalves, R.; Martins, M.C.L.; Oliveira, M.J.; Almeida-Porada, G.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
Last trends in Biomaterials focus the mimic of cellular environments capable to control cellular responses. Epidermal growth factor (EGF) is a pleiotropic cytokine known to regulate cell proliferation, differentiation, and death. This study aims to optimize the immobilization of EGF on 11-mercapto-1-undecyl-tetra(ethylene)glycol (EG4) - self-assembled monolayers (SAMs) and to establish a new model surface to study EGF-mediated signaling. Gold substrates were modified with a monolayer of EG4 and N,N′- carbonyldiimidazole (CDI) was used to activate hydroxyl terminated groups of EG4-SAMs. EGF was then immobilized on activated EG4-SAMs at pH 7.4, 4°C, and 100 rpm. Different immobilization reaction times were tested as well as different CDI concentrations to optimize the reaction conditions and obtain a range of immobilized EGF concentrations on the surfaces. Surface characterization of EGF-SAMs was performed using radiolabeling, water contact angle measurements, X-ray photoelectron spectroscopy, and ELISA. Phosphorylation of EGFR on BT-20 breast cancer cell line by EGF-SAMs was tested by immunostaining. EGF was successfully immobilized on EG4-SAMs, at 4°C and pH 7.4 in a range of concentrations from 3.6 ± 0.8 to 17.6 ± 1.5 ng/cm 2. The concentration of EGF increases with immobilization time and with the CDI concentration reaching the maximum for surfaces activated with 30 mg/mL of CDI after 48 h. The bioactivity of EGF-SAMs was confirmed by immunostaining of phospho-EGFR of BT-20 cells. This study described EGF immobilization on EG4-SAMs at different concentrations, which could be important surface models to study specific protein interactions at the molecular level evolving EGF-family of proteins. © 2010 Wiley Periodicals, Inc. J.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.32723PubMed ID: 20198690Language of Original Document: EnglishCorrespondence Address: Gonçalves, R.; INEB, Biomaterials Division, NEWTherapies Group, R. Campo Alegre, 823, Porto 4150-180, Portugal; email: raquelg@ineb.up.ptChemicals/CAS: epidermal growth factor, 62229-50-9; gold, 7440-57-5; Biocompatible Materials; Epidermal Growth Factor, 62229-50-9; Gold, 7440-57-5; Imidazoles; N,N-carbonyldiimidazole, 530-62-1; Polyethylene Glycols; Receptor, Epidermal Growth Factor, 2.7.10.1; Sulfhydryl CompoundsReferences: Singh, A., Harris, R.C., Autocrine, paracrine and juxtacrine signaling by EGFR ligands (2005) Cell Signal, 17, pp. 1183-1193;Luca, A., Carotenuto, A., Rachiglio, A., Gallo, M., Maiello, M.R., Aldinucci, D.L., Pinto, A., Normanno, N., The role of the EGFR signaling in tumor microenvironment (2008) J Cell Physiol, 214, pp. 559-567; Stenflo, J., Stenberg, Y., Muranyi, A., Calcium-binding EGF-like modules in coagulation proteinases: Function of the calcium ion in module interactions (2000) Biochim Biophys Acta, 1477, pp. 51-63; Leong, K., Karsan, A., Recent insights in the role of notch signaling in tumorigenesis (2006) Blood, 107, pp. 2223-2233; Sakamoto, K., Chao, W.S., Katsube, K.-I., Yamaguchi, A., Distinct roles of EGF repeats for the Notch signaling system (2005) Experimental Cell Research, 302 (2), pp. 281-291. , DOI 10.1016/j.yexcr.2004.09.016, PII S0014482704005658; Savage, C., Hash, J.H., Cohen, S., Epidermal growth factor (1973) J Biol Chem, 248, pp. 7669-7672; Bell, G., Fong, N.M., Stempien, M.M., Wormsted, M.A., Caput, D., Ku, L., Urdea, M.S., Sanchez-Pescador, R., Human epidermal growth factor precursor: cDNA sequence, expression in vitro and gene organization (1986) Nucleic Acids Res, 14, pp. 8427-8446; Carpenter, G., Cohen, S., Epidermal growth factor (1990) J Biol Chem, 265, pp. 7709-7712; Schlessinger, J., Allosteric regulation of epidermal growth factor receptor kinase (1986) J Cell Biol, 103, pp. 2067-2072; Mitamura, T., Higashiyama, S., Taniguchi, N., Klagsbrun, M., Mekada, E., Diphtheria toxin binds to the epidermal growth factor (EGF)-like domain of human heparin-binding EGF-like growth factor/diphtheria toxin receptor and inhibits specifically its mitogenic activity (1995) J Biol Chem, 270, pp. 1015-1019; Wong, R.W.C., Guillaud, L., The role of epidermal growth factor and its receptors in mammalian CNS (2004) Cytokine Growth Factor Rev, 15, pp. 147-156; Mrksich, M., What can surface chemistry do for cell biology? (2002) Curr Opion Chem Biol, 6, pp. 794-797; Tohda, S.K.H., Murakami, N., Sakano, S., Nara, N., Diverse effects of the notch ligands Jagged1 and Delta1 on the growth and differentiation of primary acute myeloblastic leukemia cells (2005) Exp Hematol, 33, pp. 558-563; France, R.M., Short, R.D., Dawson, R.A., MacNeil, S., Attachment of human keratinocytes to plasma co-polymers of acrylic acid/octa-1,7-diene and allyl amine/octa-1,7-diene (1998) Journal of Materials Chemistry, 8 (1), pp. 37-42; Love, J., Estroff, L.A., Kriebel, J.K., Nuzzo, R.G., Whitesides, G.M., Selfassembled monolayers of thiolates on metals as a form of nanotechnology (2005) Chem Rev, 105, pp. 1103-1169; Saha, K.P.J., Schaffer, D.V., Healy, K.E., Designing synthetic materials to control stem cell phenotype (2007) Curr Opin Chem Biol, 11, pp. 381-387; Barbosa, J.B.M., Águas, A.P., Adhesion of human leukocytes to biomaterials: An in vitro study using alkanethiolate monolayers with different chemically functionalized surfaces (2003) J Biomed Mater Res A, 65, pp. 429-434; Rodrigues, S.N.G.I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Fibrinogen adsorption, platelet adhesion and activation on mixed hydroxyl/methyl-terminated self-assembled monolayers (2006) Biomaterials, 27, pp. 5357-5367; Barrias, C., Martins, M.C., Almeida-Porada, G., Barbosa, M.A., Granja, P.L., The correlation between the adsorption of adhesive proteins and cell behaviour on hydroxyl-methyl mixed self-assembled monolayers (2009) Biomaterials, 30, pp. 307-316; Curran, J.M.C.R., Hunt, J.A., The guidance of human mesenchymal stem cell differentiation in vitro by controlled modifications to the cell substrate (2006) Biomaterials, 27, pp. 4783-4793; Lee, M., Brass, D.A., Morris, R., Composto, R.J., Ducheyne, P., The effect of non-specific interactions on cellular adhesion using model surfaces (2005) Biomaterials, 26, pp. 1721-1730; Martins, M.C.L.C.S., Freitas, S.C., Salgueiro, P., Ratner, B.D., Barbosa, M.A., Molecularly designed surfaces for blood deheparinization using an immobilized heparin-binding peptide (2009) J Biomed Mater Res A, 88, pp. 162-173; Gehanno, V., Freitas, P.P., Veloso, A., Ferreira, J., Almeida, B., Sousa, J.B., Kling, A., Silva, M.F., Ion beam deposition of Mn-Ir spin valves (1999) IEEE Trans Magn, 35, pp. 4361-4367; Martins, M.C.L.R.B., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methyl- Terminated self-assebled monolyers (2003) J Biomed Mater Res, 67, pp. 158-171; Barrias, C.C.M.M., Bidarra, S., Sámiranda, M.C., Barbosa, M.A., Adsorption of a therapeutic enzyme to self-assembled monolayers: Effect of the surface chemistry and solution pH on the amount and activity of adsorbed enzyme (2005) Biomaterials, 26, pp. 2695-2704; (1993) Iodine-125. A Guide to Radioiodination Techniques, , Amersham Life Science. Amersham Place, Little Chalfont, Bucks: Amersham International plc; Zhang, J., Matthews, J.M., Ward, L.D., Simpson, R.J., Disruption of the disulfide bonds of recombinant murine interleukin-6 induces formation of a partially unfolded state (1997) Biochemistry, 36, pp. 2380-2389; Solomons, T., (1996) Organic Chemistry, , New York: Wiley; Lukkari, J., Meretoja, M., Kartio, I., Laajalehto, K., Rajamaki, M., Lindstrom, M., Kankare, J., Organic thiosulfates (bunte salts): Novel surface-active sulfur compounds for the preparation of selfassembled monolayers on gold (1999) Langmuir, 15, pp. 3529-3537; Castner, D.G., Hinds, K., Grainger, D.W., X-ray photoelectron spectroscopy sulfur 2p study of organic thiol and bisulfide binding interactions with gold surfaces (1996) Langmuir, 12 (21), pp. 5083-5086; Molina, R., Espinós, J.P., Yubero, F., Erra, P., González-Elipe, A.R., XPS analysis of down stream plasma treated wool: Influence of the nature of the gas on the surface modification of wool (2005) Appl Surf Sci, 252, pp. 1417-1429; Flynn, N., Tran, T.N.T., Cima, M.J., Langer, R., Long-term stability of self-assembled monolayers in biological media (2003) Langmuir, 19, pp. 10909-10915; Willey, T., Vance, A.L., Van Buuren, T., Bostedt, C., Terminello, L.J., Fadley, C.S., Rapid degradation of alkanethiol-based self-assembled monolayers on gold in ambient laboratory conditions (2005) Surf Sci, 576, pp. 188-196; Lage, A., Crombet, T., González, G., Targeting epidermal growth factor receptor signaling: Early results and future trends in oncology (2003) Trends Mol Med, 35, pp. 327-336; Lee, H., Hu, M., Reilly, R.M., Allen, C., Apoptotic epidermal growth factor (EGF)- Conjugated block copolymer micelles as a nanotechnology platform for targeted combination therapy (2007) Mol Pharm, 4, pp. 769-781; Nakaji-Hirabayashi, T., Kato, K., Arima, Y., Iwata, H., Oriented immobilization of epidermal growth factor onto culture substrates for the selective expansion of neural stem cells (2007) Biomaterials, 28, pp. 3517-3529; Stefonek, T., Masters, K.S., Immobilized gradients of epidermal growth factor promote accelerated and directed keratinocyte migration (2007) Wound Repair Regen, 15, pp. 847-855; Ito, Y., Li, J.S., Takahashi, T., Imanishi, Y., Okabayashi, Y., Kido, Y., Kasuga, M., Enhancement of the mitogenic effect by artificial juxtacrine stimulation using immobilized EGF (1997) J Biochem, 121, pp. 514-520; Wang, Q., Bohn, P.W., Surface composition gradients of immobilized cell signaling molecules: Epidermal growth factor on gold (2006) Thin Solid Films, 513, pp. 338-346; Karakecili, A., Satriano, C., Gumusderelioglu, M., Marletta, G., Enhancement of fibroblastic proliferation on chitosan surfaces by immobilized epidermal growth factor (2008) Acta Biomater, 4, pp. 989-996; Hodneland, C., Lee, Y.S., Min, D.H., Mrksich, M., Selective immobilization of proteins to self-assembled monolayers presenting active site-directed capture ligands (2002) PNAS, 99, pp. 5048-5052; Liu, L., Chen, S., Giachelli, C.M., Ratner, B.D., Jiang, S., Controlling osteopontin orientation on surfaces to modulate endothelial cell adhesion (2005) J Biomed Mater Res A, 74, pp. 23-31; Kim, H., Noh, J., Hara, M., Lee, H., Characterization of mixed selfassembled monolayers for immobilization of streptavidin using chemical force microscopy (2008) Ultramicroscopy, 108, pp. 1140-1143; Delamarche, E., Sundarababu, G., Biebuyck, H., Michel, B., Gerber, Ch., Sigrist, H., Wolf, H., Mathieu, H.J., Immobilization of antibodies on a photoactive self-assembled monolayer on gold (1996) Langmuir, 12 (8), pp. 1997-2006; Gonçalves, R., Martins, M.C.L., Almeida-Porada, G., Barbosa, M.A., Induction of notch signaling by immobilization of jagged-1 on self-assembled monolayers (2009) Biomaterials, 30, pp. 6879-6887; Mrksich, M., Whitesides, G.M., Using Self-Assembled Monolayers That Present Oligo(ethylene glycol) Groups to Control the Interactions of Proteins with Surfaces (1997) ACS Symposium Series, 680, pp. 361-373; Chen, G., Ito, Y., Gradient micropattern immobilization of EGF to investigate the effect of artificil juxtacrine stimulation (2001) Biomaterials, 22, pp. 2453-2457; Allewood, D., Nielsen, K., Alewwod, P.F., Craik, D.J., Andrews, P., Nerrie, M., White, S., Nice, E.C., The role of disulfide bonds in the structure and function of murine epidermal growth factor (mEGF) (2005) Growth Factors, 23, pp. 97-110; Morton, R., Mangroo, D., Gerber, G.E., A novel method of complete activation by carbonyldiimidazole: Application to esther synthesis (1988) Can J Chem, 66, pp. 1701-1705; Stollner, D., Scheller, F.W., Warsinke, A., Activation of cellulose membranes with 1,1-carbonyldiimidazole or 1-cyano-4-dimethylaminopyridinium tetrafluoroborate as a basis for the development of immunosensors (2002) Anal Biochem, 304, pp. 157-165; Crowley, S.C., Chan, K.C., Walters, R.R., Optimization of protein immobilization on 1,1′-carbonyldiimidazole- activated diol-bonded silica (1986) J Chromatogr A, 359, pp. 359-368; Mateus, A., Seruca, R., Machado, J.C., Keller, G., Oliveira, M.J., Suriano, G., Luber, B., EGFR regulates RhoA-GTP dependent cell motility in E-cadherin mutant cells (2007) Hum Mol Genet, 16, pp. 1639-1647; Garcia, R., Franklin, R.A., Mccubrey, J.A., EGF induces cell motility and multi-drug resistance gene expression in breast cancer cells (2006) Cell Cycle, 5, pp. 2820-2826
Keywords: Adsorption; Angle measurement; article; Biocompatible Materials; Biological materials; Breast cancer cells; cancer cell culture; Carbonyldiimidazole; Cell culture; Cell immobilization; Cell Line, Tumor; cell proliferation; Cellular environment; Cellular response; Concentration (process); Concentration of; Contact angle; controlled study; Cytokines; EGF; Electron energy levels; enzyme linked immunosorbent assay; Enzyme-Linked Immunosorbent Assay; epidermal growth factor; Epidermal growth factors; Ethylene; Glycols; gold; Gold substrates; human; human cell; Humans; Hydroxyl-terminated; Imidazoles; Immobilization process; Immobilization reaction; immunofluorescence; immunohistochemistry; Immunostaining; Molecular levels; Nanostructured materials; Nanostructured surface; Nanostructured surfaces; New model; Optimization; Phosphorylation; Photoelectron spectroscopy; Polyethylene Glycols; Protein adsorption; protein immobilization; protein interaction; protein phosphorylation; Proteins; Radiolabeling; Radioligand Assay; Reaction conditions; reaction optimization; Receptor, Epidermal Growth Factor; Sams; self assembled monolayer; Self assembled monolayers; Self-assembled monolayers; Sulfhydryl Compounds; Surface characterization; Surface functionalization; Surface models; Surface Properties; Water contact angle measurement; X ray photoelectron spectroscopy

Characterization of polymeric solutions as injectable vehicles for hydroxyapatite microspheres - Oliveira, S.M.; Almeida, I.F.; Costa, P.C.; Barrias, C.C.; Ferreira, M.R.P.; Bahia, M.F.; Barbosa, M.A. (AAPS PharmSciTechAAPS PharmSciTech, 2010)
A polymeric solution and a reinforcement phase can work as an injectable material to fill up bone defects. However, the properties of the solution should be suitable to enable the transport of that extra phase. Additionally, the use of biocompatible materials is a requirement for tissue regeneration. Thus, we intended to optimize a biocompatible polymeric solution able to carry hydroxyapatite microspheres into bone defects using an orthopedic injectable device. To achieve that goal, polymers usually regarded as biocompatible were selected, namely sodium carboxymethylcellulose, hydroxypropylmethylcellulose, and Na-alginate (ALG). The rheological properties of the polymeric solutions at different concentrations were assessed by viscosimetry before and after moist heat sterilization. In order to correlate rheological properties with injectability, solutions were tested using an orthopedic device applied for minimal invasive surgeries. Among the three polymers, ALG solutions presented the most suitable properties for our goal and a non-sterile ALG 6% solution was successfully used to perform preliminary injection tests of hydroxyapatite microspheres. Sterile ALG 7.25% solution was found to closely match non-sterile ALG 6% properties and it was selected as the optimal vehicle. Finally, sterile ALG 7.25% physical stability was studied at different temperatures over a 3-month period. It was observed that its rheological properties presented minor changes when stored at 25°C or at 4°C. © 2010 American Association of Pharmaceutical Scientists.
Cited By (since 1996): 1Export Date: 21 November 2012Source: Scopusdoi: 10.1208/s12249-010-9447-3PubMed ID: 20490958Language of Original Document: EnglishCorrespondence Address: Oliveira, S. M.; Dep. de Eng. Mecânica e Gestão Industrial, Escola Superior de Tecnologia e Gestão de Viseu, Campus Politécnico de Repeses, 3504-510, Viseu, Portugal; email: soliveira@estv.ipv.ptChemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; carboxymethylcellulose, 8050-38-2, 9000-11-7, 9004-32-4, 9050-04-8; hydroxyapatite, 1306-06-5, 51198-94-8; hydroxypropylmethylcellulose, 9004-65-3; Biocompatible Materials; Capsules; Durapatite, 1306-06-5; Excipients; Polymers; Solutions; VehiclesReferences: Verlaan, J.J., Oner, F.C., Dhert, W.J., Anterior spinal column augmentation with injectable bone cements (2006) Biomat, 27 (3), pp. 290-301;Chenite, A., Chaput, C., Wang, D., Combes, C., Buschmann, M.D., Hoemann, C.D., Novel injectable neutral solutions of chitosan form biodegradable gels in situ (2000) Biomat, 21 (21), pp. 2155-2161; Hoemann, C.D., Sun, J., Legare, A., McKee, M.D., Buschmann, M.D., Tissue engineering of cartilage using an injectable and adhesive chitosan-based cell-delivery vehicle (2005) Osteoarthritis Cart., 13 (4), pp. 318-329; Balakrishnan, B., Jayakrishnan, A., Self-cross-linking biopolymers as injectable in situ forming biodegradable scaffolds (2005) Biomat, 26 (18), pp. 3941-3951; Shu, X.Z., Ghosh, K., Liu, Y., Palumbo, F.S., Luo, Y., Clark, R.A., Attachment and spreading of fibroblasts on an RGD peptidemodified injectable hyaluronan hydrogel (2004) J. Biomed. Mater. Res., 68 A (2), pp. 365-375; Shu, X.Z., Ahmad, S., Liu, Y., Prestwich, G.D., Synthesis and evaluation of injectable, in situ crosslinkable synthetic extracellular matrices for tissue engineering (2006) J. Biomed. Mater. Res. A, 79 (4), pp. 902-912; Weiss, P., Gauthier, O., Bouler, J.-M., Grimandi, G., Daculsi, G., Injectable bone substitute using a hydrophilic polymer (1999) Bone, 25 (SUPPL. 1), pp. 67S-70S. , DOI 10.1016/S8756-3282(99)00146-5, PII S8756328299001465; Trojani, C., Weiss, P., Michiels, J.F., Vinatier, C., Guicheux, J., Daculsi, G., Three-dimensional culture and differentiation of human osteogenic cells in an injectable hydroxypropylmethylcellulose hydrogel (2005) Biomat, 26 (27), pp. 5509-5517; Virto, M.R., Frutos, P., Torrado, S., Frutos, G., Gentamicin release from modified acrylic bone cements with lactose and hydroxypropylmethylcellulose (2003) Biomat, 24 (1), pp. 79-87; Bodic, F., Amouriq, Y., Gayet-Delacroix, M., Gauthier, O., Bouler, J.-M., Daculsi, G., Méthode nom invasive d'evaluation d'un substitut osseux injectable/Non-invasive evaluation of an injectable bone substitute (2002) C R Biologies, 325, pp. 345-353; Andrews, G.P., Gorman, S.P., Jones, D.S., Rheological characterisation of primary and binary interactive bioadhesive gels composed of cellulose derivatives designed as ophthalmic viscosurgical devices (2005) Biomat, 26 (5), pp. 571-580; He, S., Yaszemski, M.J., Yasko, A.W., Engel, P.S., Mikos, A.G., Injectable biodegradable polymer composites based on poly (propylene fumarate) crosslinked with poly (ethylene glycol) dimethacrylate (2000) Biomat, 21 (23), pp. 2389-2394; Temenoff, J.S., Mikos, A.G., Injectable biodegradable materials for orthopedic tissue engineering (2000) Biomat, 21 (23), pp. 2405-2412; Iooss, P., Le Ray, A.M., Grimandi, G., Daculsi, G., Merle, C., A new injectable bone substitute combining poly (epsilon-caprolactone) microparticles with biphasic calcium phosphate granules (2001) Biomat, 22 (20), pp. 2785-2794; Uda, H., Sugawara, Y., Nakasu, M., Experimental studies on hydroxyapatite powder-carboxymethyl chitin composite: Injectable material for bone augmentation (2006) J. Plast. Reconstr. Aesthet. Surg., 59 (2), pp. 188-196; Carrodeguas, R.G., Lasa, B.V., Barrio, J.S.D., Injectable acrylic bone cements for vertebroplasty with improved properties (2004) J. Biomed. Mater. Res. B-Appl. Biomat., 68 (1), pp. 94-104; Oliveira, S.M., Barrias, C.C., Ribeiro, C.C., Almeida, I.F., Bahia, M.F., Barbosa, M.A., Morphology and mechanical properties of injectable ceramic microspheres (2009) Key Engineering Mat., 396-398, pp. 691-694; Barrias, C.C., Ribeiro, C.C., Barbosa, M.A., Adhesion and proliferation of human osteoblastic cells seeded on injectable hydroxyapatite microspheres (2004) Key Engineering Mat., 254-256, pp. 877-880; Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., Preparation and characterisation of calcium-phosphate porous microspheres with a uniform size for biomedical applications (2006) J. Mater. Sci. Mater. Med., 17 (5), pp. 455-463; Oliveira, S.M., Barrias, C.C., Almeida, I.F., Costa, P.C., Ferreira, M.P., Bahia, M.F., Injectability of a bone filler system based on hydroxyapatite microspheres and a vehicle with in situ gelforming ability (2008) J. Biomed. Mater. Res. B-Appl. Biomat., 87 B, pp. 49-58; Barnes, H.A., Hutton, J.F., Walters, K., (1998) An Introduction to Rheology, , Amsterdam: Elsevier Science; Leo, W.J., McLoughlin, A.J., Malone, D.M., Effects of sterilization treatments on some properties of alginate solutions and gels (1990) Biotech. Progress, 6 (1), pp. 51-53; Holme, H.K., Lindmo, K., Kristiansen, A., Smidsrød, O., Thermal depolymerization of alginate in the solid state (2003) Carbohydrate Polym., 54 (4), pp. 431-438; Bohner, M., Baroud, G., Injectability of calcium phosphate pastes (2005) Biomat, 26 (13), pp. 1553-1563; Hide, I.G., Gangi, A., Percutaneous vertebroplasty: History, technique and current perspectives (2004) Clin. Radiol., 59 (6), pp. 461-467; Lewis, G., Injectable bone cements for use in vertebroplasty and kyphoplasty: State-of-the-art review (2006) J. Biomed. Mat. Res. B-Appl. Biomat., 76 B (2), pp. 456-468; Baumann, A., Tauss, J., Baumann, G., Tomka, M., Hessinger, M., Tiesenhausen, K., Cement embolization into the vena cava and pulmonal arteries after vertebroplasty: Interdisciplinary management (2006) Europ J. Vasc. and End Surg., 31 (5), pp. 558-561; Mathis, J.M., Wong, W., Percutaneous vertebroplasty: Technical considerations (2003) J. Vasc. and Intervent Rad., 14 (8), pp. 953-960; Xu, H.H., Weir, M.D., Burguera, E.F., Fraser, A.M., Injectable and macroporous calcium phosphate cement scaffold (2006) Biomat, 27 (24), pp. 4279-4287; Gisep, A., Curtis, R., Hanni, M., Suhm, N., Augmentation of implant purchase with bone cements: An in vitro study of injectability and dough distribution (2006) J. Biomed. Mater. Res. B-Appl. Biomat., 77 (1), pp. 114-119; Krebs, J., Ferguson, S.J., Bohner, M., Baroud, G., Steffen, T., Heini, P.F., Clinical measurements of cement injection pressure during vertebroplasty (2005) Spine, 30 (5), pp. E118-E122; Draget, K.I., Skjak-Braek, G., Smidsrod, O., Alginate-based new materials (1997) Int. J. Biol. Macromol., 21 (1-2), pp. 47-55
Keywords: Alginate; alginic acid; article; Biocompatibility; Biocompatible Materials; Capsules; Carboxymethylcellulose; Drug Compounding; Durapatite; Excipients; hydroxyapatite; Hydroxypropylmethylcellulose; Injectability; injection; Injections; instrument sterilization; microsphere; Microspheres; minimally invasive surgery; molecular weight; orthopedic equipment; Polymers; priority journal; Solutions; Vehicles; viscometry

Characterization of two DLC coatings for joint prosthesis: The role of albumin on the tribological behavior - Carapeto, A.P.; Serro, A.P.; Nunes, B.M.F.; Martins, M.C.L.; Todorovic, S.; Duarte, M.T.; André, V.; Colaço, R.; Saramago, B. (Surface and Coatings TechnologySurf. Coat. Technol., 2010)
A commonly used strategy for reduction of wear and friction of the sliding surfaces in prosthetic pairs is the use of hard coatings. DLCs (diamond like carbons) offer a promising solution, because these coatings, already used in other biomedical applications, exhibit a unique combination of chemical inertness, mechanical and tribological properties. In the present work we investigated the role of albumin, the most abundant protein in the periprosthetic fluid, on the tribological behavior of two DLCs with different compositions, against ultra-high molecular weight polyethylene (UHMWPE). The results are compared with those obtained with uncoated stainless steel surfaces. We have characterized the coatings by atomic force microscopy, X-ray diffraction, Raman spectroscopy, ultramicrohardness and wettability measurements. The adsorption of albumin onto the surfaces was investigated by ellipsometry and using a quartz crystal microbalance. Both DLCs adsorb a larger amount of protein than stainless steel. The tribological tests were performed in microtribometer aiming for a deeper understanding of the tribological mechanisms which occur at the submicrometric contact scale. Results showed no significant differences between the tribological behavior of the two coatings. Under the tested conditions, the tribological performance does not improve significantly with the application of the DLCs. Moreover, the presence of albumin on the lubricant leads to higher friction of the polymer against all counterfaces. This effect was attributed to the formation of bridges between the two sliding surfaces by the denaturated protein. The significant differences in the adsorbed amounts of protein onto the stainless steel and the two types of DLCs did not affect considerably the tribological behavior of these materials. © 2010 Elsevier B.V.
Cited By (since 1996): 6Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.surfcoat.2010.04.022Language of Original Document: EnglishCorrespondence Address: Serro, A.P.; Centro de Química Estrutural, Complexo I, Instituto Superior Técnico, Av. Rovisco Pais, TU Lisbon, 1049-001 Lisboa, Portugal; email: anapaula.serro@ist.utl.ptReferences: Donnet, C., Erdemir, A., (2009), Springer Science & Business Media, New YorkGutensohn, K., Beythien, C., Bau, J., Fenner, T., Grewe, P., Koester, R., Padmanaban, K., Kuehnl, P., (2000) Thromb. Res., 99, p. 577;Cadosch, D., Chan, E., Gautschi, O.P., Simmen, H.-P., Filgueira, L., (2009) J. Orthop. Res., 27, p. 841; Gillespie, W.L., Frampton, C.M.A., Henderson, R.J., Ryan, P.M., (1988) J. Bone Joint Surg. Br., 70 (4), p. 539; Roy, R.K., Lee, K.-R., (2007) J. Biomed. Mater. Res. B Appl. Biomater., 83 B (1), p. 72; Alakoski, E., Tiainen, V.-M., Soininen, A., Konttinen, Y.T., (2008) Open Orthop. J., 2, p. 43; Fisher, J., Firkins, P., Reeves, E.A., Hailey, J.L., Isaac, G.H., (1995) Proc. Inst. Mech. Eng., 209, p. 263; Sheeja, D., Tay, B.K., Lau, S.P., Nung, L.N., (2001) Surf. Coat. Technol., p. 410; Tiainen, V.-M., (2001) Diamond Relat. Mater., 10 (2), p. 153; Oñate, J.I., Comin, M., Braceras, I., Garcia, A., Viviente, J.L., Brizuela, M., Garagorri, N., Alava, J.I., (2001) Surf. Coat. Technol., p. 1056; Shi, B., Ajayi, O.O., Fenske, G., Erdemir, A., Liang, H., (2003) Wear, 255, p. 1015; Lappalainen, R., Selenius, M., Anttila, A., Konttinen, Y.T., Santavirta, S.S., (2003) J. Appl. Biomater., 66 B, p. 410; Sheeja, D., Tay, B.K., Nung, L.N., (2004) Diamond Relat. Mater., 13, p. 184; Xu, T., Pruitt, L., (1999) J. Mater. Sci. Mater. Med., 10, p. 83; Lappalainen, R., Anttila, A., Heinonen, H., (1998) Clin. Orthop., 352, p. 118; Saikko, V., Ahlroos, T., Calonius, O., Keränen, J., (2001) Biomaterials, 22, p. 1507; Sheeja, D., Tay, B.K., Lau, S.P., Nung, L.N., (2001) Surf. Coat. Technol., 146, p. 410; Affatato, S., Frigo, M., Toni, A., (2000) J. Biomed. Mater. Res., 53 (3), p. 221; Scholes, S.C., Unsworth, A., Goldsmit, A.A.J., (2000) Phys. Med. Biol., 45, p. 3721; Ahlroos, T., Saikko, V., (1997) Wear, 211, p. 113; Fedel, M., Motta, A., Maniglio, D., (2009) J. Biomed. Mater. Res., 90 B (1), p. 338; Lousiniana, S., Logothetidis, S., Laskarakisa, A., Gioti, M., (2007) Biomolec. Eng., 24 (1), p. 107; Li, B.G., Kang, Y.Q., Yin, G.F., Zheng, C.Q., (2007) Key Eng. Mater. High-Performance Ceram. IV, p. 1814; Fenske, G.R., (2009) Presented to Chicago Section STLE meeting, , M; Eryilmaz, O.L., Erdemir, A., (2008) Surf. Coat. Technol., 203, p. 750; Gerwin, N., Hops, C., Lucke, A., (2006) Adv. Drug Deliv. Rev., 58 (2), p. 226; Visco, A.M., Torrisi, L., Campo, N., Emanuele, U., Trifiro, A., Trimarchi, M., (2009) J. Biomed. Mater. Res. B Appl. Biomater., 89 B, p. 55; Ferrari, A.C., Robertson, J., (2001) Phys. Rev. B, 64, p. 75414; Ferrari, A.C., Robertson, J., (2000) Phys. Rev. B, 61, p. 14095; Zhou, B., Prorok, B.C., Erdemir, A., Eryilmaz, O., (2007) Diamond Relat. Mater., 16, p. 342; Zhou, B., Prorok, B.C., Erdemir, A., Eryilmaz, O., (2006) Diamond Relat. Mater., 15, p. 2051; Beeman, D., Silverman, J., Lynds, R., Anderson, M.R., (1984) Phys. Rev. B., 30 (2), p. 870; Colaço, R., Serro, A.P., Eryilmaz, O.L., Erdemir, E., (2009) J. Phys. D Appl. Phys., 42, p. 85307; Paul, R., Das, S.N., Dalui, S., Gayen, R.N., Roy, R.K., Bhar, R., Pal, A.K., (2008) J. Phys. D Appl. Phys., 41 (5), p. 55309; Serro, A.P., Fernandes, A.C., Saramago, B., (1997) Colloids Surf. A Physicochem. Eng. Aspects, 125, p. 209; Serro, A.P., Degiampietro, K., Colaço, R., Saramago, B., (2010) Saramago, Adsorption of albumin and sodium hyaluronate on UHMWPE: A QCM-D and AFM study, Colloids and Surfaces B: Biointerfaces, 78, p. 1; de Feijter, J.A., Benjamins, J., Veer, F.A., (1978) Biopolymers, 17, p. 1759; Gispert, M.P., Serro, A.P., Colaço, R., Saramago, B., (2008) Surf. Int. Anal., 40 (12), p. 1529; Hook, F., Kasemo, B., Nylander, T., Fant, C., Sott, K., Elwing, H., (2001) Anal. Chem., 73 (24), p. 5796; Hook, F., Voros, J., Rodahl, M., Kurrat, R., Boni, P., Ramsden, J.J., Textor, M., Kasemo, B., (2002) Colloids Surf. B Biointerfaces, 24, p. 155; Colaço, R., Gispert, M.P., Serro, A.P., Saramago, B., (2007) Tribol. Lett., 26 (2), p. 119; Gispert, M.P., Serro, A.P., Colaço, R., Saramago, B., (2006) Wear, 260, p. 149; Serro, A.P., Completo, C., Colaço, R., Dos Santos, F., Lobato da Silva, C., Cabral, J.M.S., Araújo, H., Saramago, B., (2009) Surf. Coat. Technol., 203, p. 3701; Widmer, M.R., Heuberger, M., Vörös, J., Spencer, N.D., (2001) Tribol. Lett., 10, p. 111; Chen, X.M., Jin, Z.M., Fisher, J., (2008) Proc. Inst. Mech. Eng. Part J. Eng. Tribol., 222 (3), p. 513; Kumar, P., Oka, M., Ikeuchi, K., Shimizu, K., Yamamuro, T., Okumura, H., Kotoura, Y., (1991) J. Biomater. Mater. Res., 25, p. 813; Roba, M., Naka, M., Gautier, E., Spencer, N.D., Crockett, R., (2009) Biomaterials, 30, p. 2072; Karuppiah, K.S.K., Sundararajan, S., Xu, Z.-H., Li, X., (2006) Tribol. Lett., 22 (2), p. 181; Yang, C.-B., Fang, H.-W., Liu, H.-L., Chang, C.-H., Hsieh, M.-C., Lee, W.-M., Huang, H.-T., (2006) Chem. Phys. Lett., 431, p. 380; Fang, H.-W., Wang, H.-C., Tsai, T.-H., Tsai, W.-B., Hou, S.-Y., Liu, H.-L., Lee, W.-H., Huang, C.-H., (2008) J. Appl. Polym. Sci., 108, p. 2428; Zappone, B., Rosenberg, K.J., Israelachvili, J., (2007) Tribol. Lett., 26 (3), p. 191; Grill, A., (1997) Surf. Coat. Technol., (1-3), p. 507; Fontaine, J., Belin, M., Le Mogne, T., Grill, A., (2004) Tribol. Int., 37, p. 869; Sanchez-Lopez, J.C., Erdemir, A., Donnet, C., Rojas, T.C., (2003) Surf. Coat. Technol., 163, p. 444; Robertson, J., (2002) Mater. Sci. Eng., 37, p. 129
Keywords: Adsorbed amount; Adsorption; Albumin adsorption; Atomic force microscopy; Atomic spectroscopy; Biomedical applications; Chemical inertness; Corrosion resistant alloys; Diamond like carbon; DLC coatings; Friction; Hard coatings; Joint prostheses; Mechanical and tribological properties; Mechanical properties; Microtribology; Microtribometer; Nonmetallic matrix composites; Oxide minerals; Polyethylenes; Proteins; Quartz; Raman spectroscopy; Scanning electron microscopy; Sliding surface; Stainless steel; Stainless steel surface; Steel corrosion; Surfaces; Tribological behaviors; Tribological mechanism; Tribological performance; Tribological tests; Tribology; UHMW-PE; UHMWPE; Ultramicrohardness; Wear and friction; Wettability measurements; X ray diffraction

Comparison of a computer system evaluation of intrapartum cardiotocographic events and a consensus of clinicians. - Costa, M.A.; Ayres-de-Campos, D.; Machado, A.P.; Santos, C.C.; Bernardes, J. (Journal of perinatal medicineJ Perinat Med, 2010)
AIMS: To compare between computer analysis of intrapartum cardiotocography (CTG) features by the Omniview-SisPorto 3.5 and a consensus of clinicians. METHODS: Agreement study using 50 consecutively acquired tracings (206 h of signals) with >60 min duration, <10% signal loss and recorded in labor at term by internal fetal heart rate (FHR) monitoring. Tracings were divided into 10-min segments and independently analyzed by three experienced clinicians, in order to estimate the FHR baseline and identify periodic events. A consensus was reached using a three round Delphi procedure. Results were compared with the analysis provided by the Omniview-SisPorto 3.5 system. RESULTS: For baseline estimation, agreement between the computer and the consensus was high [intraclass correlation coefficient (ICC)=0.85; 95% confidence interval (CI) 0.46-0.93], with a mean difference of 3.7 bpm (limits of agreement -4.4-11.9 bpm), and 99% of differences under 15 bpm. A concordant identification was observed in 71% of accelerations (95% CI: 69%-73%), 68% of decelerations (95% CI: 66%-70%), and 87% of uterine contractions (95% CI: 85%-89%). CONCLUSIONS: A high agreement was observed between the Omniview-SisPorto 3.5 and a consensus of clinicians in evaluation of intrapartum CTG baseline, accelerations, decelerations and uterine contractions.
Cited By (since 1996): 2Export Date: 21 November 2012Source: Scopusdoi: 10.1515/JPM.2010.030PubMed ID: 20121542Language of Original Document: EnglishCorrespondence Address: Costa, M.A.email: cosantonia@gmail.com
Keywords: algorithm; Algorithms; article; Cardiotocography; comparative study; computer assisted diagnosis; Diagnosis, Computer-Assisted; Female; Fetal Heart; Fetal monitoring; fetus heart; fetus monitoring; human; Humans; instrumentation; methodology; physician; Physicians; physiology; Pregnancy

Dynamic cell-cell interactions between cord blood haematopoietic progenitors and the cellular niche are essential for the expansion of CD34 +, CD34 +CD38 - Da Silva, C.L.; Gonçalves, R.; Dos Santos, F.; Andrade, P.Z.; Almeida-Porada, G.; Cabral, J.M.S. (Journal of Tissue Engineering and Regenerative MedicineJ. Tissue Eng. Regenerative Med., 2010)
Most clinical applications of haematopoietic stem/progenitor cells (HSCs) would benefit from their ex vivo expansion to obtain a therapeutically significant amount of cells from the available donor samples. We studied the impact of cellular interactions between umbilical cord blood (UCB) haematopoietic cells and bone marrow (BM)-derived mesenchymal stem cells (MSCs) on the ex vivo expansion and differentiative potential of UCB CD34 +-enriched cells. UCB cells were cultured: (a) directly in contact with BM MSC-derived stromal layers (contact); (b) separated by a microporous membrane (non-contact); or (c) without stroma (no stroma). Highly dynamic culture events occurred in HSC-MSC co-cultures, involving cell-cell interactions, which preceded HSC expansion. Throughout the time in culture [18 days], total cell expansion was significantly higher in contact (fold increase of 280 ± 37 at day 18) compared to non-contact (85 ± 25). No significant cell expansion was observed in stroma-free cultures. CD34 + cell expansion was also clearly favoured by direct contact with BM MSCs (35 ± 5- and 7 ± 3-fold increases at day 18 for contact and non-contact, respectively). Moreover, a higher percentage of CD34 +CD38
Cited By (since 1996): 8Export Date: 21 November 2012Source: Scopusdoi: 10.1002/term.226PubMed ID: 19937912Language of Original Document: EnglishCorrespondence Address: Da Silva, C. L.; IBB-Institute for Biotechnology and Bioengineering, Centre for Biological and Chemical Engineering, Instituto Superior Técnico, Avenida Rovisco Pais, 1049-001 Lisbon, Portugal; email: claudialobato@ist.utl.ptChemicals/CAS: Antigens, CD34; Antigens, CD38, 3.2.2.5; Antigens, CD7; SuspensionsReferences: Alakel, N., Jing, D., Muller, K., Direct contact with mesenchymal stromal cells affects migratory behavior and gene expression profile of CD133 + hematopoietic stem cells during ex vivo expansion (2009) Exp Hematol, 37 (4), pp. 504-513;Almeida-Porada, G., Brown, R.L., MacKintosh, F.R., Evaluation of serum-free culture conditions able to support the ex vivo expansion and engraftment of human hematopoietic stem cells in the human-to-sheep xenograft model (2000) J Hematother Stem Cell Res, 9 (5), pp. 683-693; Ando, K., Nakamura, Y., Chargui, J., Extensive generation of human cord blood CD34 + stem cells from Lin -CD34 - cells in a long-term in vitro system (2000) Exp Hematol, 28 (6), pp. 690-699; Bernstein, I.D., Boyd, R.L., van den Brink, M.R., Clinical strategies to enhance posttransplant immune reconstitution (2008) Biol Blood Marrow Transpl, 14 (1 and SUPPL. 1), pp. 94-99; Bilko, N.M., Votyakova, I.A., Vasylovska, S.V., Characterization of the interactions between stromal and haematopoietic progenitor cells in expansion cell culture models (2005) Cell Biol Int, 29 (1), pp. 83-86; Breems, D.A., Blokland, E.A., Siebel, K.E., Stroma contact prevents loss of hematopoietic stem cell quality during ex vivo expansion of CD34 + mobilized peripheral blood stem cells (1998) Blood, 91 (1), pp. 111-117; Cheng, X., Macvittie, T., Meisenberg, B., Human brain endothelial cells (HUBEC) promote SCID repopulating cell expansion through direct contact (2007) Growth Factors, 25 (3), pp. 141-150; Corre, J., Planat-Benard, V., Corberand, J., Human bone marrow adipocytes support complete myeloid and lymphoid differentiation from human CD34 + cells (2004) Br J Haematol, 127 (3), pp. 344-347; da Silva, C.L., Goncalves, R., Crapnell, K.B., A human stromal-based serum-free culture system supports the ex vivo expansion/maintenance of bone marrow and cord blood hematopoietic stem/progenitor cells (2005) Exp Hematol, 33 (7), pp. 828-835; da Silva, C.L., Goncalves, R., Porada, C.D., Differences amid bone marrow and cord blood hematopoietic stem/progenitor cell division kinetics (2009) J Cell Physiol, , DOI: 10.1002/jcp.21736; de Lima, M., Shpall, E., Strategies for widening the use of cord blood in hematopoietic stem cell transplantation (2006) Haematologica, 91 (5), pp. 584-587; Foguenne, J., Di Stefano, I., Giet, O., Ex vivo expansion of hematopoietic progenitor cells is associated with downregulation of α4 integrin- and CXCR4-mediated engraftment in NOD/SCID β2-microglobulin-null mice (2009) Haematologica, 94 (2), pp. 185-194; Freund, D., Bauer, N., Boxberger, S., Polarization of human hematopoietic progenitors during contact with multipotent mesenchymal stromal cells: Effects on proliferation and clonogenicity (2006) Stem Cells Dev, 15 (6), pp. 815-829; Frias, A.M., Porada, C.D., Crapnell, K.B., Generation of functional natural killer and dendritic cells in a human stromal-based serum-free culture system designed for cord blood expansion (2008) Exp Hematol, 36 (1), pp. 61-68; Goncalves, R., Lobato da Silva, C., Cabral, J.M.S., A Stro-1 + human universal stromal feeder layer to expand/maintain human bone marrow hematopoietic stem/progenitor cells in a serum-free culture system (2006) Exp Hematol, 34 (10), pp. 1353-1359; Gordon, M.Y.M.S., Davidson, R.J., Grand, F.H., Contact-mediated inhibition of human hematopoietic progenitor cell proliferationmay be conferred by stem cell antigen, CD34 (2000) Hematol J, 1, pp. 77-86; Hao, Q.L., Zhu, J., Price, M.A., Identification of a novel, human multilymphoid progenitor in cord blood (2001) Blood, 97 (12), pp. 3683-3690; Haylock, D.N., Nilsson, S.K., Osteopontin: A bridge between bone and blood (2006) Br J Haematol, 134 (5), pp. 467-474; Hidalgo, A., Robledo, M.M., Teixido, J., CD44-mediated hematopoietic progenitor cell adhesion and its complex role in myelopoiesis (2002) J Hematother Stem Cell Res, 11 (3), pp. 539-547; Hofmeister, C.C., Zhang, J., Knight, K.L., Ex vivo expansion of umbilical cord blood stem cells for transplantation: Growing knowledge from the hematopoietic niche (2007) Bone Marrow Transpl, 39 (1), pp. 11-23; Jones, P., May, G., Healy, L., Stromal expression of Jagged 1 promotes colony formation by fetal hematopoietic progenitor cells (1998) Blood, 92 (5), pp. 1505-1511; Katayama, Y., Frenette, P.S., Galactocerebrosides are required postnatally for stromal-dependent bone marrow lymphopoiesis (2003) Immunity, 18 (6), pp. 789-800; Kawada, H., Ando, K., Tsuji, T., Rapid ex vivo expansion of human umbilical cord hematopoietic progenitors using a novel culture system (1999) Exp Hematol, 27 (5), pp. 904-915; Kilroy, G.E., Foster, S.J., Wu, X., Cytokine profile of human adipose-derived stem cells: Expression of angiogenic, hematopoietic, and pro-inflammatory factors (2007) J Cell Physiol, 212 (3), pp. 702-709; Kim, J.A., Kang, Y.J., Park, G., Identification of a stromamediated Wnt/β-catenin signal promoting self-renewal of hematopoietic stem cells in the stem cell niche (2009) Stem Cells, 27 (6), pp. 1318-1329; Koller, M.R., Oxender, M., Jensen, T.C., Direct contact between CD34 +lin - cells and stroma induces a soluble activity that specifically increases primitive hematopoietic cell production (1999) Exp Hematol, 27 (4), pp. 734-741; Lewis, I.D., Almeida-Porada, G., Du, J., Umbilical cord blood cells capable of engrafting in primary, secondary, and tertiary xenogeneic hosts are preserved after ex vivo culture in a noncontact system (2001) Blood, 97 (11), pp. 3441-3449; Li, N., Feugier, P., Serrurrier, B., Human mesenchymal stem cells improve ex vivo expansion of adult human CD34 + peripheral blood progenitor cells and decrease their allostimulatory capacity (2007) Exp Hematol, 35 (3), pp. 507-515; Li, Y.P., Paczesny, S., Lauret, E., Human mesenchymal stem cells license adult CD34 + hemopoietic progenitor cells to differentiate into regulatory dendritic cells through activation of the Notch pathway (2008) J Immunol, 180 (3), pp. 1598-1608; Loeuillet, C., Bernard, G., Remy-Martin, J., Distinct hematopoietic support by two human stromal cell lines (2001) Exp Hematol, 29 (6), pp. 736-745; Mayani, H., Lansdorp, P.M., Biology of human umbilical cord blood-derived hematopoietic stem/progenitor cells (1998) Stem Cells, 16 (3), pp. 153-165; McKenzie, J.L., Gan, O.I., Doedens, M., Reversible cell surface expression of CD38 on CD34-positive human hematopoietic repopulating cells (2007) Exp Hematol, 35 (9), pp. 1429-1436; Moore, K.A., Lemischka, I.R., Stem cells and their niches (2006) Science, 311 (5769), pp. 1880-1885; Nolta, J.A., Smogorzewska, E.M., Kohn, D.B., Analysis of optimal conditions for retroviral-mediated transduction of primitive human hematopoietic cells (1995) Blood, 86 (1), pp. 101-110; Oostendorp, R.A., Robin, C., Steinhoff, C., Long-term maintenance of hematopoietic stem cells does not require contact with embryo-derived stromal cells in cocultures (2005) Stem Cells, 23 (6), pp. 842-851; Oritani, K., Wu, X., Medina, K., Antibody ligation of CD9 modifies production of myeloid cells in long-term cultures (1996) Blood, 87 (6), pp. 2252-2261; Sadlon, T.J., Lewis, I.D., D'Andrea, R.J., BMP4: Its role in development of the hematopoietic system and potential as a hematopoietic growth factor (2004) Stem Cells, 22 (4), pp. 457-474; Shih, C.C., Hu, M.C.T., Hu, J., Long-term ex vivo maintenance and expansion of transplantable human hematopoietic stem cells (1999) Blood, 94 (5), pp. 1623-1636; Shpall, E.J., Quinones, R., Giller, R., Transplantation of ex vivo expanded cord blood (2002) Biol Blood Marrow Transpl, 8 (7), pp. 368-376; Suzuki, T., Yokoyama, Y., Kumano, K., Highly efficient ex vivo expansion of human hematopoietic stem cells using Δ1-Fc chimeric protein (2006) Stem Cells, 24 (11), pp. 2456-2465; Verfaillie, C.M., Direct contact between human primitive hematopoietic progenitors and bone marrow stroma is not required for long-term in vitro hematopoiesis (1992) Blood, 79 (11), pp. 2821-2826; Wagner, W., Wein, F., Roderburg, C., Adhesion of hematopoietic progenitor cells to human mesenchymal stem cells as a model for cell-cell interaction (2007) Exp Hematol, 35 (2), pp. 314-325; Yin, T., Li, L., The stem cell niches in bone (2006) J Clin Invest, 116 (5), pp. 1195-1201; Zhang, C.C., Kaba, M., Iizuka, S., Angiopoietin-like 5 and IGFBP2 stimulate ex vivo expansion of human cord blood hematopoietic stem cells as assayed by NOD/SCID transplantation (2008) Blood, 111 (7), pp. 3415-3423; Zhang, Y., Chai, C., Jiang, X.S., Co-culture of umbilical cord blood CD34 + cells with human mesenchymal stem cells (2006) Tissue Eng, 12 (8), pp. 2161-2170
Keywords: Antigens, CD34; Antigens, CD38; Antigens, CD7; article; Bone marrow microenvironment; CD34 antigen; CD38 antigen; CD7 antigen; cell adhesion; Cell Communication; cell contact; Cell culture; cell differentiation; cell interaction; cell proliferation; Cells, Cultured; cellular distribution; clonogenic assay; coculture; Coculture Techniques; Colony-Forming Units Assay; controlled study; Ex vivo expansion; ex vivo study; Fetal Blood; flow cytometry; Haematopoietic stem/progenitor cells; hematopoietic stem cell; Hematopoietic Stem Cells; human; human cell; Humans; Lymphocytes; lymphoid cell; Mesenchymal stem cell; Mesenchymal Stem Cells; Microscopy, Electron, Scanning; phenotype; priority journal; Scanning electron microscopy; somatic gene therapy; stem cell expansion; Stem Cell Niche; stroma cell; Suspensions; umbilical cord blood

Evaluation of the effect of the degree of acetylation on the inflammatory response to 3D porous chitosan scaffolds - Barbosa, J.N.; Amaral, I.F.; Águas, A.P.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2010)
The effect of the degree of acetylation (DA) of 3D chitosan (Ch) scaffolds on the inflammatory reaction was investigated. Chitosan porous scaffolds with DAs of 4 and 15% were implanted using a subcutaneous air-pouch model of inflammation. The initial acute inflammatory response was evaluated 24 and 48 h after implantation. To characterize the initial response, the recruitment and adhesion of inflammatory cells to the implant site was studied. The fibrous capsule formation and the infiltration of inflammatory cells within the scaffolds were evaluated for longer implantation times (2 and 4 weeks). Chitosan with DA 15% attracted the highest number of leukocytes to the implant site. High numbers of adherent inflammatory cells were also observed in this material. For longer implantation periods Ch scaffolds with a DA of 15% induced the formation of a thick fibrous capsule and a high infiltration of inflammatory cells within the scaffold. Our results indicate that the biological response to implanted Ch scaffolds was influenced by the DA. Chitosan with a DA of 15% induce a more intense inflammatory response when compared with DA 4% Ch. Because inflammation and healing are interrelated, this result may provide clues for the relative importance of acetyl and amine functional groups in tissue repair and regeneration. © 2009 Wiley Periodicals, Inc.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.32499PubMed ID: 19484769Language of Original Document: EnglishCorrespondence Address: Barbosa, J. N.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: judite@ineb.up.ptChemicals/CAS: chitosan, 9012-76-4; Chitosan, 9012-76-4References: Sefton, M.V., Babensee, J.E., Woodhouse, K.A., Innate and adaptative immune responses in tissue engineering (2008) Semin Immunol, 20, pp. 83-85;VandeVord, P.J., Matthew, H.W.T., DeSilva, S.P., Mayton, L., Wu, B., Wooley, P.H., Evaluation of the biocompatibility of a chitosan scaffold in mice (2002) J Biomed Mater Res, 59, pp. 585-590; Anderson, J.M., Biological responses to materials (2001) Annu Rev Mater Res, 31, pp. 81-110; Babensee, J.E., Anderson, J.M., McIntire, L.V., Mikos, A.G., Host response to tissue engineered devices (1998) Adv Drug Deliv Rev, 33, pp. 111-139; Ueno, H., Mori, T., Fujinaga, T., Topical formulations and wound healing applications of chitosan (2001) Adv Drug Deliv Rev, 52, pp. 105-115; Kim, I.Y., Seo, S.J., Moon, H.S., Yoo, M.K., Park, I.Y., Kim, B.C., Cho, C.S., Chitosan and its derivatives for tissue engineering applications (2008) Biotechnol Adv, 26, pp. 1-21; Tomihata, K., Ikada, Y., In vitro and in vivo degradation of films of chitin and its deacetylated derivatives (1997) Biomaterials, 18, pp. 567-575; Peluso, G., Petillo, O., Ranieri, M., Santin, M., Ambrosio, L., Calabro, D., Avallone, B., Balsamo, G., Chitosan-mediated stimulation of macrophage function (1994) Biomaterials, 15, pp. 1215-1220; Porporatto, C., Bianco, I.D., Riera, C.M., Correa, S.G., Chitosan induces different L-arginine metabolic pathways in resting and in.ammatory macrophages (2003) Biochem Biophys Res Commun, 304, pp. 266-272; Mori, T., Okumura, M., Matsuura, M., Ueno, K., Tokura, S., Okamoto, Y., Minami, S., Fujinaga, T., Effects of chitin and its derivatives on the proliferation and cytokine production of fibroblasts in vitro (1997) Biomaterials, 18, pp. 947-951; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42, pp. 3569-3580; Vachoud, L., Zydowicz, N., Domard, A., Formation and characterisation of a physical chitin gel (1997) Carbohydr Res, 302, pp. 169-177; Suh, J.K.F., Matthew, H.W.T., Application of chitosan-based polysaccharide biomaterials in cartilage tissue engineering: A review (2000) Biomaterials, 21, pp. 2589-2598; Nakagawa, Y., Murai, T., Hasegawa, C., Hirata, M., Tsuchiya, T., Yagami, T., Haishima, Y., Endotoxin contamination in wound dressings made of natural biomaterials (2003) J Biomed Mater Res Part B: Appl Biomater, 66 B, pp. 347-355; Sedwick, A.D., Sin, Y.M., Edwards, J.C., Willoughby, D.A., Increased inflammatory reactivity in newly formed lining tissue (1983) J Pathol, 141, pp. 483-495; Castro, A.G., Esaguy, N., Macedo, P.M., Aguas, A.P., Silva, M.T., Live but not heat-killed mycobacteria cause rapid chemotaxis of large numbers of eosinophils in vivo and are ingested by the attracted granulocytes (1991) Infect Immun, 59, pp. 3009-3014; Tang, L.P., Liu, L., Elwing, H.B., Complement activation and inflammation triggered by model biomaterial surfaces (1998) J Biomed Mater Res, 41, pp. 333-340; Tang, L.P., Jennings, T.A., Eaton, J.W., Mast cells mediate acute inflammatory responses to implanted biomaterials (1998) Proc Natl Acad Sci USA, 95, pp. 8841-8846; Food and Drug Administration (1987) Guideline on Validation of the Limulus Amebocyte Lysate Test as an End-product Endotoxin Test for Human and Animal Parental Drugs, Biological Products, and Medical Devices, , US Department of Health and Human Services PHS, Washington, DC: US Department of Health and Human Services;; Hooper, K.A., Nickolas, T.L., Yurkow, E.J., Kohn, J., Laskin, D.L., Characterization of the inflammatory response to biomaterials using a rodent air pouch model (2000) J Biomed Mater Res, 50, pp. 365-374; Wooley, P.H., Morren, R., Andary, J., Sud, S.A., Yang, S.Y., Mayton, L., Markel, D., Nasser, S., Inflammatory responses to orthopaedic biomaterials in the murine air pouch (2002) Biomaterials, 23, pp. 517-526; Amaral, I.F., Sampaio, P., Barbosa, M.A., Three-dimensional culture of human osteoblastic cells in chitosan sponges: The effect of the degree of acetylation (2006) J Biomed Mater Res, 76 A, pp. 335-346. , Part A; Thomsen, P., Gretzer, C., Macrophage interactions with modified material surfaces (2001) Curr Opin Solid State Mater Sci, 5, pp. 163-176; Hu, W.J., Eaton, J.W., Tang, L.P., Molecular basis of biomaterial - mediated foreign body reactions (2001) Blood, 98, pp. 1231-1238; Benesch, J., Tengvall, P., Blood protein adsorption onto chitosan (2002) Biomaterials, 23, pp. 2561-2568; Hidaka, Y., Ito, M., Mori, K., Yagasaki, H., Kafrawy, A.H., Histopathological and immunohistochemical studies of membranes of deacetylated chitin derivatives implanted over rat calvaria (1999) J Biomed Mater Res, 46, pp. 418-423; Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., Rat bone marrow stromal cell osteogenic differentiation and fibronectin adsorption on chitosan membranes: The effect of the degree of acetylation (2005) J Biomed Mater Res, 75 A, pp. 387-397. , Part A; Ueno, H., Murakami, M., Okumura, M., Kadosawa, T., Uede, T., Fujinaga, T., Chitosan accelerates the production of osteopontin from polymorphonuclear leukocytes (2001) Biomaterials, 22, pp. 1667-1673
Keywords: acetic acid derivative; Acetylation; Acute inflammatory response; amine; Amine functional groups; animal cell; animal experiment; animal tissue; Animals; article; Biological materials; Biological response; Biomaterials; cell adhesion; cell infiltration; Chitin; chitosan; Chitosan scaffold; Degree of acetylation; Fibrous capsule; Fibrous capsule formation; freeze drying; Functional groups; Hydrogels; implant; implantation; Implantation periods; Implants, Experimental; Inflammation; Inflammatory cells; Inflammatory reaction; Inflammatory response; leukocyte count; Leukocytes; male; Mice; Mice, Inbred BALB C; Microscopy, Electron, Scanning; mouse; nonhuman; Pathology; porosity; Porous scaffold; Prosthesis Implantation; Relative importance; Scaffolds; Subcutaneous Tissue; Surface Properties; Three dimensional; Tissue regeneration; tissue repair; Tissue response; Tissue responses; Tissue Scaffolds

An intrauterine pressure generator for educational simulation of labour and delivery - Bastos, L.F.; Lobo, M.F.; van Meurs, W.L.; Ayres-de-Campos, D. (Medical Engineering and PhysicsMed. Eng. Phys., 2010)
Simulation provides a risk free and controllable environment for training of healthcare providers. The limited realism of available simulators and training programs impedes immersive training in obstetric emergencies. In developed countries, intrapartum monitoring in high-risk cases involves continuous evaluation of foetal heart rate and uterine contractions signals. We present an essential component of a high-fidelity simulator for normal and critical situations in labour and delivery, namely an intrauterine pressure generator. The signal model behind the generator consists of a truncated Gaussian curve with the programmable features: amplitude, frequency, duration, and resting tone. Through analysis of 44. h of physiological data, we demonstrate that the natural variability of these features and of the baseline pressure can be approximated by deterministic trends and stationary stochastic processes. Signal parameters can be controlled by simulation instructors, scripts, or other models to reflect different patients, pathologies, and evolving clinical situations. Twelve 40-min tracings reflecting three different patients in labour were presented to three clinical experts, who attributed similar realism scores to simulated and to real tracings. © 2010 IPEM.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: MEPHEdoi: 10.1016/j.medengphy.2010.04.015PubMed ID: 20494606Language of Original Document: EnglishCorrespondence Address: Bastos, L.F.; Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Rua Dr. Roberto Frias, s/n, I302, 4200-465 Porto, Portugal; email: lbastos@fe.up.ptReferences: Carlin, A., Alfirevic, Z., Intrapartum foetal emergencies (2006) Semin Foetal Neonatal Med, 11, pp. 150-157;Draycott, T., Sibanda, T., Owen, L., Akande, V., Winter, C., Reading, S., Does training in obstetric emergencies improve neonatal outcome? (2006) BJOG, 113, pp. 177-182; Daniels, K., Lipman, S., Harney, K., Arafeh, J., Druzin, M., Use of simulation based team training for obstetric crises in resident education (2008) Simul Healthc, 3, pp. 154-160; Gardner, R., Walzer, T.B., Simon, R., Raemer, D.B., Obstetric simulation as a risk control strategy: course design and evaluation (2008) Simul Healthc, 3, pp. 119-127; Pliego, J.F., Wehbe-Janek, H., Rajab, M.H., Browning, J.L., Fothergill, R.E., Ob/Gyn boot camp using high-fidelity human simulators: enhancing residents' perceived competency, confidence in taking a leadership role, and stress hardiness (2008) Simul Healthc, 3, pp. 82-89; Crofts, J.F., Bartlett, C., Ellis, D., Hunt, L.P., Fox, R., Draycott, T.J., Training for shoulder dystocia: a trial of simulation using low-fidelity and high-fidelity mannequins (2006) Obstet Gynecol (New York, 1953), 108, pp. 1477-1485; Gardner, R., Raemer, D.B., Simulation in obstetrics and gynecology (2008) Obstet Gynecol Clin North Am, 35, pp. 97-127; (2001) The use of electronic foetal monitoring: the use and interpretation of cardiotocography in intrapartum foetal surveillance, , Royal-College-of-Obstetricians-and-Gynaecologists, RCOG, London; (2006) Intrapartum foetal surveillance: clinical guidelines, , Royal-Australian-and-New-Zealand-College-of-Obstetricians-and-Gynaecologists, RANZCOG, Melbourne; Bracero, L.A., Roshanfekr, D., Byrne, D.W., Analysis of antepartum foetal heart rate tracing by physician and computer (2000) J Matern Foetal Med, 9, pp. 181-185; Doyle, C., Angelotti, T., Diagnosis of an unsuspected maternal hemorrhage via foetal heart rate tracing (2004) J Clin Anesth, 16, pp. 465-468; Donn, S.M., Sinha, S.K., Chiswick, M.L., (2002) Birth asphyxia and the brain: basic science and clinical implications, , Blackwell Publishing; Laros, J.R.K., Presidential address: medical-legal issues in obstetrics and gynecology (2005) Am J Obstet Gynecol, 192, pp. 1883-1889; Cusick, W., Smulian, J.C., Vintzileos, A.M., Intrapartum use of foetal heart rate monitoring, contraction monitoring, and amnioinfusion (1995) Clin Perinatol, 22, pp. 875-906; Vanner, T., Gardosi, J., Intrapartum assessment of uterine activity (1996) Baillieres Clin Obstet Gynaecol, 10, pp. 243-257; Bakker, P.C.A.M., Van Rijswijk, S., Van Rijsiwijk, S., van Geijn, H.P., Uterine activity monitoring during labor (2007) J Perinat Med, 35, pp. 468-477; Bakker, P.C.A.M., van Geijn, H.P., Uterine activity: implications for the condition of the foetus (2008) J Perinat Med, 36, pp. 30-37; Andersen, H.F., Barclay, M.L., A computer-model of uterine contractions based on discrete contractile elements (1995) Obstet Gynecol, 86, pp. 108-111. , J; Young, R.C., A computer model of uterine contractions based on action potential propagation and intercellular calcium waves (1997) Obstet Gynecol, 89, pp. 604-608. , A; Wray, S., Uterine contraction and physiological mechanisms of modulation (1993) Am J Physiol, 264, pp. C1-C18. , J; Wray, S., Kupittayanant, S., Shmygol, A., Smith, R.D., Burdyga, T., The physiological basis of uterine contractility: a short review (2001) Exp Physiol, 86, pp. 239-246; Vauge, C., Carbonne, B., Papiernik, E., Ferre, F., A mathematical model of uterine dynamics and its application to human parturition (2000) Acta Biotheor, 48, pp. 95-105. , J; Moreau, R., Pham, M.T., Redarce, T., Dupuis, O., Simulation of forceps extraction on a childbirth simulator (2008) Proceedings of the IEEE International Conference on Robotics and Automation (ICRA), pp. 1100-1105; Klavan, M., Laver, A.T., Boscola, M.A., (1977) Clinical concepts of foetal heart rate monitoring, , Hewlett-Packard Waltham, Mass; Parer, J.T., (1997) Handbook of foetal heart rate monitoring, , W.B. Saunders Company, Philadelphia; Maul, H., Maner, W.L., Olson, G., Saade, G.R., Garfield, R.E., Non-invasive transabdominal uterine electromyography correlates with the strength of intrauterine pressure and is predictive of labor and delivery (2004) J Matern Foetal Neonatal Med, 15, pp. 297-301; Cobo, E., Quintero, C.A., Strada, G., Zambrana, M.A., Uterine behavior in abruptio placentae. I. Contraction patterns and their reactivity to oxytocin (1965) Am J Obstet Gynecol, 93, pp. 1151-1156; Seitchik, J., Quantitating uterine contractility in clinical context (1981) Obstet Gynecol, 57, pp. 453-457; Burchell, H.J., Odendaal, H.J., de Wet, J.I., Badenhorst, P.N., Uterine contraction patterns in abruptio placentae (1985) S Afr Med J, 67, pp. 48-50; Harbert, G.M., Assessment of uterine contractility and activity (1992) Clin Obstet Gynecol, 35, pp. 546-558; Bruce, E.N., (2001) Biomedical signal processing and signal modeling, , Wiley-Interscience; Levinson, N., The Wiener RMS (root mean square) error criterion in filter design and prediction (1947) J Math Phys, 25, pp. 261-278; Paul, M.J., Smeltzer, J.S., Relationship of measured external tocodynamometry with measured internal uterine activity (1991) Am J Perinatol, 8, pp. 417-420; Miles, A.M., Monga, M., Richeson, K.S., Correlation of external and internal monitoring of uterine activity in a cohort of term patients (2001) Am J Perinatol, 18, pp. 137-140; van Meurs, W.L., Good, M.L., Lampotang, S., Functional anatomy of full-scale patient simulators (1997) J Clin Monit Comput, 13, pp. 317-324; van Meurs, W.L., Nikkelen, E., Good, M.L., Pharmacokinetic-pharmacodynamic model for educational simulations (1998) IEEE Trans Biomed Eng, 45, pp. 582-590
Keywords: article; Clinical situations; Computer simulation; delivery; Delivery, Obstetric; Developed countries; Educational simulations; Essential component; Female; Fetal monitoring; Gaussian curves; generator; Health care providers; Heart Rate, Fetal; Heart rates; High-fidelity simulators; Humans; Immersive; intrauterine pressure; labor; Labor, Obstetric; Labour and delivery; medical education; Medical educational simulation; muscle tone; Natural variability; normal distribution; Obstetrics; Physiological data; Pregnancy; Prenatal Diagnosis; Pressure; Pressure generators; priority journal; Random processes; Risk free; Signal generator; Signal generators; Signal models; Signal parameters; Signal Processing, Computer-Assisted; simulation; Stationary stochastic process; statistical model; statistical parameters; statistics; Stochastic Processes; Time Factors; Training program; Uterine activities; Uterine activity; Uterine Contraction; Uterine Monitoring; uterus contraction

The MEE principle in data classification: A perceptron-based analysis - Silva, L.M.; Marques de Sá, J.; Alexandre, L.A. (Neural ComputationNeural Comp., 2010)
This letter focuses on the issue of whether risk functionals derived from information-theoretic principles, such as Shannon or Rényi's entropies, are able to cope with the data classification problem in both the sense of attaining the risk functional minimum and implying the minimum probability of error allowed by the family of functions implemented by the classifier, here denoted by min Pe. The analysis of this so-called minimization of error entropy (MEE) principle is carried out in a single perceptron with continuous activation functions, yielding continuous error distributions. In spite of the fact that the analysis is restricted to single perceptrons, it reveals a large spectrum of behaviors that MEE can be expected to exhibit in both theory and practice. In what concerns the theoretical MEE, our study clarifies the role of the parameters controlling the perceptron activation function (of the squashing type) in often reaching the minimum probability of error. Our study also clarifies the role of the kernel density estimator of the error density in achieving the minimum probability of error in practice. © 2010 Massachusetts Institute of Technology.
Cited By (since 1996): 3Export Date: 21 November 2012Source: Scopusdoi: 10.1162/NECO_a_00013PubMed ID: 20569178Language of Original Document: EnglishCorrespondence Address: Silva, L.M.; Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Porto 4200-465, Portugal; email: lmsilva@fe.up.ptReferences: Alexandre, L.A., Marques de Sá, J., Error entropy minimization for LSTM training (2006) Proceedings of the 16th International Conference on Artificial Neural Networks, pp. 244-253. , Berlin: Springer;Asuncion, A., Newman, D., (2007) UCI machine learning repository. Irvine University of California, Irvine, , http://www.ics.uci.edu/~mlearn/MLRepository.html, School of Information and Computer Sciences. Available online at; Bishop, C., (1995) Neural networks for pattern recognition, , New York: OxfordUniversity Press; Erdogmus, D., Hild K., II., Príncipe, J.C., Blind source separation using Rényi's α-marginal entropies (2002) Neurocomputing, 49, pp. 25-38; Erdogmus, D., Príncipe, J.C., Comparison of entropy and mean square error criteria in adaptive system training using higher order statistics (2000) Proceedings of the Intl. Conf. on ICA and Signal Separation, pp. 75-80. , Berlin: Springer-Verlag; Erdogmus, D., Príncipe, J.C., An error-entropy minimization algorithm for supervised training of nonlinear adaptive systems (2002) IEEE Transactions on Signal Processing, 50 (7), pp. 1780-1786; Erdogmus, D., Príncipe, J.C., Convergence properties and data efficiency of the minimum error entropy criterion in adaline training (2003) IEEE Transactions on Signal Processing, 51 (7), pp. 1966-1978; Gokcay, E., Príncipe, J.C., Information theoretic clustering (2002) IEEE Trans. on Pattern Analysis and Machine Learning, 24 (2), pp. 158-171; Han, L., Kernel partial least squares (K-PLS) for scientific data mining. Unpublished doctoral dissertation (2007) Rensselaer Polytechnic Institute; Hild, I.I., Erdogmus, K., Príncipe D., J.C., Blind source separation using Rényi's mutual information (2001) IEEE Signal Processing Letters, 8, pp. 174-176; Jacobs, R., Jordan, M., Nowlan, S., Hinton, G., Adaptive mixtures of local experts (1991) Neural Computation, 3, pp. 79-87; Jenssen, R., Hild, K., Erdogmus, D., Príncipe, J.-C., Eltoft, T., Clustering using Rényis entropy (2003) Proceedings of the Int. Joint Conference on Neural Networks, pp. 523-528. , Piscataway, NJ: IEEE Press; Johnson, N., Kotz, S., (1970) Continuous univariate distributions, , Hoboken, NJ:Wiley; Kapur, J., Maximum-entropy models in science and engineering (1993), (rev. ed.). Hoboken, NJ: WileyLagarias, J., Reeds, J.A., Wright, M.H., Wright, P.E., Convergence properties of the nelder-mead simplex method in low dimensions (1998) SIAM Journal of Optimization, 9 (1), pp. 112-147; Linsker, R., Self-organization in a perceptual network (1988) IEEE Computer, 21, pp. 105-117; Liu, W., Pokharel, P., Príncipe, J., Correntropy: Properties and applications in non-gaussian signal processing (2007) IEEE Transactions on Signal Processing, 55 (11), pp. 5286-5298; Parzen, E., On the estimation of a probability density function and the mode (1962) Annals of Mathematical Statistics, 33, pp. 1065-1076; Príncipe, J.C., Xu, D., Fisher, J., Information theoretic learning (2000) Unsupervised adaptive filtering, 1, pp. 265-319. , S. Haykin (Ed.), Blind source separation, Hoboken, NJ: Wiley; Rényi, A., (1970) Probability theory, , Dordrecht: North-Holland; Richard, M., Lippmann, R., Neural network classifiers estimate Bayesian a posteriori probabilities (1991) Neural Computation, 3, pp. 461-483; Santos, J., (2007) Data classification with neural networks and entropic criteria, , Unpublished doctoral dissertation, University of Porto; Santos, J.M., Marques de Sá, J., Alexandre, L.A., Batch-sequential algorithm for neural networks trained with entropic criteria (2005) Proceedings of the International Conference on Artificial Neural Networks, pp. 91-96. , Berlin: Springer-Verlag; Santos, J.M., Marques de Sá, J., Alexandre, L.A., Legclust-a clustering algorithm based on layered entropic subgraphs (2007) IEEE Transactions on Pattern Analysis and Machine Intelligence, 30 (1), pp. 62-75; Santos, J.M., Marques de Sá, J., Alexandre, L.A., Sereno, F., Optimization of the error entropy minimization algorithm for neural network classification (2004) Intelligent engineering systems through artificial neural networks, pp. 81-86. , C. Dagli, A. Buczak, D. Enke, M. Embrechts, & O. Ersoy (Eds.), Washington, DC: ASME; Silva, L.M., (2008) Neural networks with error-density risk functionals for data classification, , Unpublished doctoral dissertation, University of Porto; Silva, L.M., Embrechts, M., Santos, J.M., Marques de Sá, J., The influence of the risk functional in data classification with MLPs (2008) Proceedings of the International Conference on Artificial Neural Networks, pp. 185-194. , Berlin: Springer-Verlag; Silva, L.M., Felgueiras, C., Alexandre, L.A., Marques de Sá, J., Error entropy in classification problems: A univariate data analysis (2006) Neural Computation, 18 (9), pp. 2036-2061; Silva, L.M., Marques de Sá, J., Alexandre, L.A., Neural network classification using Shannon's entropy (2005) Proceedings of the European Symposium on Artificial Neural Networks, pp. 217-222. , Bruges: d-side; Stoller, D., Univariate two-population distribution free discrimination (1954) Journal of the American Statistical Association, 49, pp. 770-777; Thompson, J., Tapia, R., (1978) Nonparametric probability density estimation, , Baltimore, MD: Johns Hopkins University Press; Watanabe, S., Pattern recognition as a quest for minimum entropy (1981) Pattern Recognition, 13 (5), pp. 381-387
Keywords: algorithm; Algorithms; artificial intelligence; artificial neural network; automated pattern recognition; Computer simulation; entropy; letter; Mathematical Concepts; mathematical phenomena; Models, Statistical; Neural Networks (Computer); Pattern Recognition, Automated; standard; statistical model

A model for educational simulation of hemodynamic transitions at birth - Sá-Couto, C.D.; Andriessen, P.; van Meurs, W.L.; Ayres-de-Campos, D.; Sá-Couto, P.M. (Pediatric ResearchPediatr. Res., 2010)
Birth is characterized by swift and complex transitions in hemodynamic and respiratory variables. Unrecognized pathologies or incidents may quickly become fatal or cause permanent damage. This article introduces an essential component of an acute perinatal care simulator, namely a model for educational simulation of normal hemodynamic transitions seen during and shortly after birth. We explicitly formulate educational objectives and adapt a preexisting model for the simulation of neonatal cardiovascular physiology to include essential aspects of fetal hemodynamics. From the scientific literature, we obtain model parameters that characterize these aspects quantitatively. The fetal model is controlled by a time-and event-based script of changes occurring at birth, such as onset of breathing and cord clamping, and the transitory phase up to 24 h after birth. Comparison of simulation results with published target data confirms that realistic simulated hemodynamic vital signs are achieved. Copyright © 2010 International Pediatric Research Foundation, Inc.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: PEREBdoi: 10.1203/PDR.0b013e3181c2def3Language of Original Document: EnglishCorrespondence Address: Van Meurs, W. L.; INEB-Instituto de Engenharia Biomédica, Divisão de Sinal e Imagem, Campus FEUP, Rua Roberto Frias, s/n, 4200-465 Porto, Portugal; email: wvanmeurs@ineb.up.ptReferences: Van Meurs, W.L., Good, M.L., Lampotang, S., Functional anatomy of full-scale patient simulators (1997) J Clin Monit, 13, pp. 317-324;Sá Couto, C.D., Van Meurs, W.L., Goodwin, J.A., Andriessen, P., A model for educational simulation of neonatal cardiovascular pathophysiology (2006) Simul Healthc, 1, pp. 4-9; Zijlmans, M., Sá-Couto, C.D., Van Meurs, W.L., Goodwin, J.A., Andriessen, P., Corrected and improved model for educational simulation of neonatal cardiovascular pathophysiology (2009) Simul Healthc, 4, pp. 49-53; Goodwin, J.A., Van Meurs, W.L., Sá Couto, C.D., Beneken, J.E., Graves, S.A., A model for educational simulation of infant cardiovascular physiology (2004) Anesth Analg, 99, pp. 1655-1664; Ménigault, E., Vieyres, P., Lepoivre, B., Durand, A., Pourcelot, L., Berson, M., Fetal heart modelling based on a pressure-volume relationship (1997) Med Biol Eng Comput, 35, pp. 715-721; Pennati, G., Bellotti, M., Fumero, R., Mathematical modeling of the human foetal cardiovascular system based on Doppler ultrasound data (1997) Med Eng Phys, 19, pp. 327-335; Huikeshoven, F., Coleman, T.G., Jongsma, H.W., Mathematical model of the fetal cardiovascular system: The uncontrolled case (1980) Am J Physiol, 239, pp. R317-R325; Mielke, G., Benda, N., Cardiac output and central distribution of blood flow in the human fetus (2001) Circulation, 103, pp. 1662-1668; Cunningham, G., Leveno, K., MacDonald, P., Gilstrap III, L., Gant, N., Hankins, G., Clark, S., The morphological and functional development of the fetus (1996) Williams Obstetrics, pp. 151-190. , Cunningham G, Leveno K, MacDonald P, Gilstrap III L, Gant N, Hankins G, Clark S (eds) 20th Ed. Appleton & Lange, CT; Huikeshoven, F.J., Hope, I.D., Power, G.G., Gilbert, R.D., Longo, L.D., Mathematical model of fetal circulation and oxygen delivery (1985) Am J Physiol, 249, pp. R192-R202; Rasanen, J., Wood, D.C., Weiner, S., Ludomirski, A., Huhta, J.C., Role of the pulmonary circulation in the distribution of human fetal cardiac output during the second half of pregnancy (1996) Circulation, 94, pp. 1068-1073; Assali, N.S., Morris, J.A., Beck, R., Cardiovascular hemodynamics in the fetal lamb before and after lung expansion (1965) Am J Physiol, 208, pp. 122-129; Vilos, G.A., Liggins, G.C., Intrathoracic pressures in fetal sheep (1982) J Dev Physiol, 4, pp. 247-256; Hooper, S.B., Wallace, M.J., Role of the physicochemical environment in lung development (2006) Clin Exp Pharmacol Physiol, 33, pp. 273-279; Greenspan, J.S., Shaffer, T.H., Fox, W.W., Spitzer, A.R., Assisted ventilation: Physiologic implications and complications (1998) Fetal and Neonatal Physiology, 2. , Polin RA, Fox WW (eds) W.B. Saunders Company, Philadelphia, PA; Friedman, A.H., Fahey, J.T., The transitions from fetal to neonatal circulation: Normal responses and implications for infants with heart disease (1993) Semin Perinatol, 17, pp. 106-121; Ghanayem, N.S., Gordon, J.B., Modulation of pulmonary vasomotor tone in the fetus and neonate (2001) Respir Res, 2, pp. 139-144; Dawes, G.S., Mott, J.C., Widdicombe, J.G., Wyatt, D.G., Changes in the lungs of the new-born lamb (1953) J Physiol, 121, pp. 141-162; Brook, M.M., Heymann, M.A., Teitel, D.F., The heart (2001) Care of the High-Risk, , Klaus MH, Fanaroff AA (eds) 5th ed. W.B. Saunders Company, Philadelphia, PA; Gutyon, A.C., Fetal and neonatal physiology (1991) Textbook of Medical Physiology, , Guyton AC (ed) 8th ed. W.B. Saunders Company Philadelphia, PA; Lagercrantz, H., Bistoletti, P., Catecholamine release in the newborn infant at birth (1977) Pediatr Res, 11, pp. 889-893; Padbury, J.F., Diakomanolis, E.S., Hobel, C.J., Perelman, A., Fisher, D.A., Neonatal adaptation: Sympatho-adrenal response to umbilical cord cutting (1981) Pediatr Res, 15, pp. 1483-1487; Minoura, S., Gilbert, R.D., Postnatal change of cardiac function in lambs: Effects of ganglionic block and afterload (1987) J Dev Physiol, 9, pp. 123-135; Coskun, S., Yüksel, H., Bilgi, Y., Lacin, S., Tansug, N., Onag, A., Non-invasive evaluation of the adaptations of cardiac function in the neonatal period: A comparison of healthy infants delivered by vaginal route and caesarean section (2001) Acta Med Okayama, 55, pp. 213-218; Kishkurno, S., Takahashi, Y., Harada, K., Ishida, A., Tamura, M., Takada, G., Postnatal changes in left ventricular volume and contractility in healthy term infants (1997) Pediatric Cardiology, 18 (2), pp. 91-95. , DOI 10.1007/s002469900123; Shiota, T., Harada, K., Takada, G., Left ventricular systolic and diastolic function during early neonatal period using transthoracic echocardiography (2002) Tohoku J Exp Med, 197, pp. 151-158; Walther, F.J., Benders, M.J., Leighton, J.O., Early changes in the neonatal circulatory transition (1993) J Pediatr, 123, pp. 625-632; Hiraishi, S., Misawa, H., Oguchi, K., Kadoi, N., Saito, K., Fujino, N., Hojo, M., Yashiro, K., Two-dimensional Doppler echocardiographic assessment of closure of the ductus arteriosus in normal newborn infants (1987) J Pediatr, 111, pp. 755-760; Migliavacca, F., Dubini, G., Pennati, G., Pietrabissa, R., Fumero, R., Hsia, T.Y., De Leval, M.R., Computational model of the fluid dynamics in systemic-to-pulmonary shunts (2000) J Biomech, 33, pp. 549-557; Teitel, D.F., Iwamoto, H.S., Rudolph, A.M., Effects of birth-related events on central blood flow patterns (1987) Pediatr Res, 22, pp. 557-566; Anderson, D.F., Bissonnette, J.M., Faber, J.J., Thornburg, K.L., Central shunt flows and pressures in the mature fetal lamb (1981) Am J Physiol, 241, pp. H60-H66; Agata, Y., Hiraishi, S., Oguchi, K., Misawa, H., Horiguchi, Y., Fujino, N., Yashiro, K., Shimada, N., Changes in left ventricular output from fetal to early neonatal life (1991) J Pediatr, 119, pp. 441-445; Harada, K., Shiota, T., Takahashi, Y., Tamura, M., Takada, G., Changes in the volume and performance of the left ventricle in the early neonatal period (1994) Early Hum Dev, 39, pp. 201-209; Moss, A.J., Emmanouilides, G.C., Adams, F.H., Chuang, K., Response of ductus arteriosus and pulmonary and systemic arterial pressure to changes in oxygen environment in newborn infants (1964) Pediatrics, 33, pp. 937-944; Emmanouilides, G.C., Moss, A.J., Monset-Couchard, M., Marcano, B.A., Rzeznic, B., Cardiac output in newborn infants (1970) Biol Neonate, 15, pp. 186-197; Emmanouilides, G.C., Moss, A.J., Duffie Jr., E.R., Adams, F.H., Pulmonary arterial pressure changes in human newborn infants from birth to 3 days of age (1964) J Pediatr, 65, pp. 327-333; Soni, N., Williams, P., Positive pressure ventilation: What is the real cost? (2008) Br J Anaesth, 101, pp. 446-457; Moss, A.J., Emmanouilides, G.C., Duffie Jr., E.R., Closure of the ductus arteriosus in the newborn infant (1963) Pediatrics, 32, pp. 25-30
Keywords: article; artificial ventilation; biological model; birth; Blood flow; blood flow velocity; blood pressure; breathing; breathing mechanics; cardiovascular function; clamp; comparative study; Computer simulation; Constriction; education; evaluation; fetus; hemodynamics; human; Humans; Infant, Newborn; ligation; Models, Cardiovascular; newborn; Parturition; perinatal care; priority journal; Regional Blood Flow; reproducibility; Reproducibility of Results; Respiration, Artificial; Respiratory Mechanics; scientific literature; simulator; stimulation; time; Time Factors; umbilical cord; vascularization; vital sign

Segmentation of the carotid intima-media region in B-mode ultrasound images - Rocha, R.; Campilho, A.; Silva, J.; Azevedo, E.; Santos, R. (Image and Vision ComputingImage Vision Comput, 2010)
This paper proposes a new approach for the segmentation of both near-end and far-end intima-media regions of the common carotid artery in ultrasound images. The method requires minimal user interaction and is able to segment the near-end wall in arteries with large, hypoechogenic and irregular plaques, issues usually not considered previously due to the increased segmentation difficulty. The adventitia is detected by searching for the best fit of a cubic spline to edges having features compatible with the adventitia boundary. The algorithm uses a global smoothness constraint and integrates discriminating features of the adventitia to reduce the attraction by other edges. Afterwards, using the information of the adventitia location, the lumen boundary is detected by combining dynamic programming, smooth intensity thresholding surfaces and geometric snakes. Smooth contours that correctly adapt to the intima are produced, even in the presence of deep concavities. Moreover, unlike balloon-based snakes, the propagation force does not depend on gradients and does not require a predefined direction. An extensive statistical evaluation is computed, using a set of 47 images from 24 different symptomatic patients, including several classes, sizes and shapes of plaques. Bland-Altman plots of the mean intima-media thickness, for manual segmentations of two medical experts, show a high intra-observer and inter-observer agreement, with mean differences close to zero (mean between -0.10 mm and 0.18 mm) and with the large majority of differences within the limits of agreement (standard deviation between 0.10 mm and 0.12 mm). Similar plots reveal a good agreement between the automatic and the manual segmentations (mean between -0.07 mm and 0.11 mm and standard deviation between 0.11 mm and 0.12 mm). © 2009 Elsevier B.V. All rights reserved.
Cited By (since 1996): 18Export Date: 21 November 2012Source: ScopusCODEN: IVCODdoi: 10.1016/j.imavis.2009.09.017Language of Original Document: EnglishCorrespondence Address: Rocha, R.; INEB - Inst. de Eng. Biomédica, Divisão de Sinal e Imagem, Campus FEUP, 4200-465 Porto, Portugal; email: rhr@isep.ipp.ptReferences: O'Leary, D., Polak, J., Kronmal, R., Manolio, T., Burke, G., Wolfson Jr., S., Carotid-artery intima and media thickness as a risk factor for myocardial infarction and stroke in older adults (1999) New Engl. J. Med., 340, pp. 14-22;Hodis, H., Mack, W., LaBree, L., Selzer, R., Liu, C., Liu, C., Azen, S., The role of carotid arterial intima-media thickness in predicting clinical coronary events (1998) Ann. Intern. Med., 128 (4), pp. 262-269; Kern, R., Szabo, K., Hennerici, M., Meairs, S., Characterization of carotid artery plaques using real-time compound B-mode ultrasound (2004) Stroke, 35, pp. 870-875; Ellis, S.M., Naoumova, R.P., Neuwirth, C.K., Eckersley, R., Cosgrove, D.O., Thompson, G.R., Sidhu, P.S., Measurement of the reflectivity of the intima-medial layer of the common carotid artery improves the discriminatory value of intima-medial thickness measurement as a predictor of risk of atherosclerotic disease (2007) Ultrasound Med. Biol., 33 (7), pp. 1029-1038; Graf, I.M., Schreuder, F.H.B.M., Hameleers, J.M., Mess, W.H., Reneman, R.S., Hoeks, A.P.G., Wall irregularity rather than intima-media thickness is associated with nearby atherosclerosis (2009) Ultrasound Biol. Med., 35 (6), pp. 955-961; Baldassarre, D., Amato, M., Bondioli, A., Sirtori, C.R., Tremoli, E., Carotid artery intima-media thickness measured by ultrasonography in normal clinical practice correlates well with atherosclerosis risk factors (2000) Stroke, 31, pp. 2426-2430; Halenka, M., Noninvasive measurement of early atherosclerosis by high-resolution B-mode ultrasonography (1999) Acta Univ. Palacki. Olomu. Fac. Med., 142, pp. 7-12; Rocha, R., (2007) Image Segmentation and Reconstruction of 3D Surfaces from Carotid Ultrasound Images, , http://www.ineb.fe.up.pt/bmivic, Ph.D. thesis, Faculdade de Engenharia da Universidade do Porto, Porto July; Gee, A., Prager, R., Treece, G., Berman, L., Engineering a freehand 3D ultrasound system (2003) Pattern Recogn. Lett., 24 (4-5), pp. 757-777; Sonka, M., Liang, W., Stefancik, R., Stolpen, A., Handbook of Medical Imaging: Medical Image Processing and Analysis (2000) SPIE, 2; Yu, Y., Acton, S., Speckle reducing anisotropic diffusion (2002) IEEE Trans. Image Process., 11 (11), pp. 1260-1270; Yu, Y., Acton, S., Edge detection in ultrasound imagery using the instantaneous coefficient of variation (2004) IEEE Trans. Image Process., 13 (12), pp. 1640-1655; Thijssen, J.M., Ultrasonic speckle formation, analysis and processing applied to tissue characterization (2003) Pattern Recogn. Lett., 24 (4-5), pp. 659-675; Loizou, C.P., Pattichis, C.S., Christodoulou, C.I., Istepanian, R.S.H., Pantziaris, M., Nicolaides, A., Comparative evaluation of despeckle filtering in ultrasound imaging of the carotid artery (2005) IEEE Trans. Ultrason. Fer. Freq. Control, 52 (10), pp. 1653-1669; Chan, K.L., Ultrasonic tissue characterization using fractal feature (1993) IEE Conf. Acoustic Sensing and Imaging, 369, pp. 183-188; Touboul, P.J., Prati, P., Scarabin, P.-Y., Adrai, V., Thibout, E., Ducimetiere, P., Use of monitoring software to improve the measurement of carotid wall thickness by B-mode imaging (1992) J. Hypertens., 10 (5), pp. 37-41; Gariepy, J., Massonneau, M., Levenson, J., Heudes, D., Simon, A., the Groupe de prevention cardio-vasculaire en medecine du travail, evidence for in vivo carotid and femoral wall thickness in human hypertension (1993) J. Hypertens., 22 (1), pp. 111-118; Selzer, R.H., Hodis, H.N., Kwong-Fu, H., Mack, W.J., Lee, P.L., Liu, C.R., Liu, C.H., Evaluation of computerized edge tracking for quantifying intima-media thickness of the common carotid artery from B-mode ultrasound images (1994) Atherosclerosis, 111, pp. 1-11; Gustavsson, T., Liang, Q., Wendelhag, I., Wikstrand, J., A dynamic programming procedure for automated ultrasonic measurement of the carotid artery (1994) Comput. Cardiol.; Wendelhag, I., Liang, Q., Gustavsson, T., Wikstrand, J., A new automated computerized analyzing system simplifies readings and reduces the variability in ultrasound measurement of intima-media thickness (1997) Stroke, 28, pp. 2195-2200; Automatic detection of the intimal and the adventitial layers of the common carotid artery wall in ultrasound Bmode images using snakes, in: International Conference on Image Analysis and Processing, B. Werer, 1999, pp. 452-457Liang, Q., Wendelhag, I., Wikstrand, J., Gustavsson, T., A multiscale dynamic programming procedure for boundary detection in ultrasound artery images (2000) IEEE Trans. Med. Imag., 19 (2), pp. 127-142; Selzer, R.H., Mack, W.J., Lee, P.L., Kwong-Fu, H., Hodis, H.N., Improved common carotid elasticity and intima-media thickness measurements from computer analysis of sequential ultrasound frames (2001) Atherosclerosis, 154 (1), pp. 185-193; Schmidt-Trucksass, A., Cheng, D., Sandrock, M., Schulte-Monting, J., Rauramaa, R., Huonker, M., Burkhardt, H., Computerized analysing system using the active contour in ultrasound measurement of carotid artery intima-media thickness (2001) Clin. Physiol., 5, pp. 561-569; Cheng, D., Schmidt-Trucksass, A., Cheng, K., Burkhardt, H., Using snakes to detect the intimal and adventitial layers of the common carotid artery wall in sonographic images (2002) Comput. Methods Programs Biomed., 67, pp. 27-37; Stein, J.H., Korcarz, C.E., Mays, M.E., Douglas, P.S., Palta, M., Zhang, H., LeCaire, T., Fan, L., A semiautomated ultrasound border detection program that facilitates clinical measurement of ultrasound carotid intima-media thickness (2005) J. Am. Soc. Echocardiogr., 18 (3), pp. 244-251; Loizou, C.P., Pattichis, C.S., Pantziaris, M., Tyllis, T., Nicolaides, A., Snakes based segmentation of the common carotid artery intima media (2007) Med. Bio. Eng. Comput., 45, pp. 35-49; Yanowitz, S.D., Bruckstein, A.M., A new method for image segmentation (1989) Comput. Graph. Image Process., 46, pp. 82-95; Chan, T., Vese, L., Active contours without edges (2001) IEEE Trans. Image Process., 10 (2), pp. 266-277; Vese, L.A., Chan, T.F., A multiphase level set framework for image segmentation using the Mumford and Shah model (2002) Int. J. Comput. Vision, 50 (3), pp. 271-293; Fischler, M.A., Bolles, R.C., Random sample consensus: a paradigm for model fitting with applications to image analysis and automated cartography (1981) Commun. ACM, 24 (6), pp. 381-395; Zack, G.W., Rogers, W.E., Latt, S.A., Automatic measurement of sister chromatid exchange frequency (1977) J. Histochem. Cytochem., 25 (7), pp. 741-753; Canny, J., A computational approach to edge detection (1986) IEEE Trans. Pattern Anal. Mach. Intell., 8 (6), pp. 679-698; Rudin, L., Osher, S., Fatemi, E., Nonlinear total variation based noise removal algorithms (1992) Proceedings of the Eleventh Annual International Conference of the Center for Nonlinear Studies on Experimental Mathematics: Computational Issues in Nonlinear Science, pp. 259-268. , Elsevier North-Holland, Inc; Rudin, L., Osher, S., Total variation based image restoration with free local constraints (1994) Proceedings of IEEE International Conference on Image Processing (ICIP'94), 1, pp. 31-35; Sethian, J.A., (1999) Level Set Methods and Fast Marching Methods, , Cambridge University Press; Osher, S., Fedkiw, R., (2003) Level Set Methods and Dynamic Implicit Surfaces, , Springer-Verlag, New York; Mumford, D., Shah, J., Optimal approximations by piecewise smooth functions and associated variational problems (1989) Commun. Pure Appl. Math., 42 (5), pp. 577-685; Burden, R., Faires, J.D., (2000) Numerical Analysis, , Brooks Cole; Breu, H., Gil, J., Kirkpatrick, D., Werman, M., Linear time Euclidean distance transform algorithms (1995) IEEE Trans. Pattern Anal. Mach. Intell., 17 (5), pp. 529-533; Bland, J.M., Altman, D.G., Statistical methods for assessing agreement between two methods of clinical measurement (1986) Lancet, 1 (8476), pp. 307-310; Loizou, C.P., Pattichis, C.S., Pantziaris, M., Nicolaides, A., An integrated system for the segmentation of atherosclerotic carotid plaque (2007) IEEE Trans. Info. Tech. Biomed., 11 (6), pp. 661-667; de Boor, C., (1978) A Practical Guide to Splines, , Springer-Verlag; Unser, M., Splines: a perfect fit for signal and image processing (1999) IEEE Signal Processing Magazine, 16 (6), pp. 22-38; Yang, Z., Tuthill, T.A., Raunig, D.L., Fox, M.D., Analoui, M., Pixel compounding: resolution-enhanced ultrasound imaging for quantitative analysis (2007) Ultrasound Med. Biol., 33 (8), pp. 1309-1319
Keywords: Acoustic waves; B-mode ultrasound images; Best fit; Carotid; Common carotid artery; Cubic spline; Digital image storage; Dynamic programming; Edge detection; End-wall; Function evaluation; Geometric snake; Geometric snakes; Image segmentation; Intima-media thickness; Manual segmentation; Medical experts; New approaches; Smoothness constraints; Standard deviation; Statistical evaluation; statistics; Thresholding; Ultrasonics; Ultrasound image; Ultrasound images; User interaction

Simulation for teaching normal delivery and shoulder dystocia to midwives in training - Reynolds, A.; Ayres-de-Campos, D.; Pereira-Cavaleiro, A.; Ferreira-Bastos, L. (Education for Health: Change in Learning and PracticeEduc. Health, 2010)
Introduction and objective: The cognitive impact of using simulation sessions in midwifery training has not been the subject of previous research. The aim of this study was to compare the effect on students' knowledge of a simulation session versus an image-based lecture, for teaching routine management of normal delivery and resolution of shoulder dystocia to midwives in training. Methods: Sixty students were enrolled three weeks after a "labour and delivery" class, and randomly assigned to two groups. Ten were subsequently excluded as they were not able to attend the whole session and/or did not complete the tests. In the simulation group (n=26), students were divided into pairs and attended a 30-minute hands-on session in the simulation centre. In the lecture group (n=24), students participated in a 30-minute image-based interactive lecture. A ten-question multiple-choice test was taken before (pre-test) and after (post-test) both sessions, to evaluate students' knowledge of labour and delivery and shoulder dystocia. Learner satisfaction was evaluated by adding a six question Likert scale questionnaire to the post-test. Independent t-test, paired samples t-test, and Mann-Whitney test were used for statistical analysis, setting significance at p<0.05. Results: The simulation group showed a significantly higher mean post-test score (6.38 vs. 5.16; p=0.003) and a significantly greater inter-test score progression (p<0.0001). Overall learner satisfaction was also higher in this group (p=0.0001). Conclusions: A significantly higher short-term reinforcement of knowledge and greater learner satisfaction was obtained using simulation sessions compared to image-based lectures when teaching routine management of normal delivery and resolution of shoulder dystocia to midwives in training. © A Reynolds, D Ayres-de-Campos, A Pereira-Cavaleiro, L Ferreira-Bastos, 2010.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: EDHEFLanguage of Original Document: EnglishCorrespondence Address: Reynolds, A.; Simulation Centre, Department of Obstetrics and Gynaecology, Faculty of Medicine, University of PortoPortugalReferences: Wilford, A., Doyle, T.J., Integrating simulation training into the nursing curriculum (2006) British Journal of Nursing, 15 (17), pp. 926-930;Lichtman, R., Walker, D., Supporting Innovations in Midwifery Education (2003) Journal of Midwifery & Women's Health, 48 (6), pp. 389-390; Johnson, P.G., Fullerton, J.T., Midwifery education models. A Contemporary Review (1998) Journal of Nurse-Midwifery, 43 (5), pp. 351-357; Lathrop, A., Winningham, B., van de Vusse, L., Simulation-Based Learning for Midwives: Background and Pilot Implementation (2007) Journal of Midwifery & Women's Health, 52, pp. 492-498; Murray, C., Grant, M.J., Howarth, M.L., Leigh, J., The use of simulation as a teaching and learning approach to support practice learning (2008) Nurse Education in Practice, 8, pp. 5-8; Council of Deans for Health. Simulation and Practice Learning Project: Outcome of a pilot study to the test principles for auditing simulated practice learning environments in the pre-registration nursing programme (2007) Final Report, , http://www.webcitation.org/5am8HXGA3, Nursing and Midwifery Council (NMC), Retrieved April 6, 2010 from, (Archived by WebCite®); Jeffries, P.R., A Framework for Designing, Implementing and Evaluating Simulations Used as Teaching Strategies in Nursing (2005) Nursing Education Perspectives, 26 (2), pp. 96-103; McCallum, J., The debate in favour of using simulation education in pre-registration adult nursing (2007) Nurse Education Today, 27, pp. 825-831; Morgan, R., Using clinical skills laboratories to promote theory-practice integration during first practice placement: An Irish perspective (2006) Journal of Clinical Nursing, 15, pp. 155-161; Issenberg, S.B., McGaghie, W.C., Hart, I.R., Mayer, J.W., Felner, J.M., Petrusa, E.R., Waugh, R.A., Ewy, G.A., Simulation Technology for Health Care Professional Skills Training and Assessment (1999) Journal of the American Medical Association, 282 (9), pp. 861-866; Gardner, R., Raemer, D.B., Simulation in Obstetrics and Gynecology (2008) Obstetrics and Gynecology Clinics of North America, 35, pp. 97-127; LeFlore, J.L., Anderson, M., Michael, J.L., Engle, W.D., Anderson, J.D., Comparison of Self-Directed Learning Versus Instructor-Modeled Learning During a Simulated Clinical Experience (2007) Simulation in Healthcare, 2, pp. 170-177; Seybert, A.L., Barton, C.M., Simulation-Based Learning to Teach Blood Pressure Assessment to Doctor of Pharmacy Students (2007) American Journal of Pharmaceutical Education, 71 (3), pp. 1-6; Hoffmann, R.L., O'Donnell, J.M., Kim, Y., The Effects of Human Patient Simulators on Basic Knowledge in Critical Care Nursing with Undergraduate Senior Baccalaureate Nursing Students (2007) Simulation in Healthcare, 2, pp. 110-114; Shepherd, I.A., Kelly, C.M., Skene, F.M., White, K.T., Enhancing Graduate Nurses' Health Assessment Knowledge and Skills Using Low-fidelity Adult Human Simulation (2007) Simulation in Healthcare, 2, pp. 16-24; Reynolds, A., Ayres-de-Campos, D., Bastos, L.F., van Meurs, W.L., J. B. Impact of Labor and Delivery Simulation Classes in Undergraduate Medical Learning (2008) Medical Education Online, 13, p. 14; Seropian, M., Dillman, D., Lasater, K., Gavilanes, J., Mannequin-Based Simulation to Reinforce Pharmacology Concepts (2007) Simulation in Healthcare, 2, pp. 218-223; Cioffi, J., Purcal, N., Arundell, F., A Pilot Study to Investigate the Effect of a Simulation Strategy on the Clinical Decision Making of Midwifery Students (2005) The Journal of Nursing Education, 44 (3), pp. 131-134; Robertson, B., An Obstetric Simulation Experience in an Undergraduate Nursing Curriculum (2006) Nurse Educator, 31 (2), pp. 74-78
Keywords: Labour and delivery; Midwifery training; Patient simulators; Shoulder dystocia

Synthesis and characterization of HAp nanorods from a cationic surfactant template method - Coelho, J.M.; Moreira, J.A.; Almeida, A.; Monteiro, F.J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2010)
Hydroxyapatite (HAp) [Ca 10(PO 4) 6(OH) 2] nanorods were synthesized using a surfactant templating method, with cetyltrimethylammonium bromide (CTAB) micelles acting as template for HAp growth. The effects of the sintering temperature on the morphological and crystallographic characteristics and on chemical composition of the "as-prepared" structures are discussed. The experimental results show that low heat-treatment temperatures are preferred in order to obtain high quality nanorods, with diameters ranging between 20 and 50 nm. High heat-treatment temperatures enhance the thermal decomposition of HAp into other calcium phosphate compounds, and the sintering of particles into micrometer ball-like structures. The stability of aqueous suspensions of HAp nanorods is also discussed. © 2010 Springer Science+Business Media, LLC.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-010-4122-5PubMed ID: 20623177Language of Original Document: EnglishCorrespondence Address: Moreira, J. A.; IFIMUP, IN-Institute of Nanoscience and Nanotechnology, Universidade Do Porto, Rua do Campo Alegre 687, Porto 4169-007, Portugal; email: jamoreir@fc.up.ptChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; hydroxyapatite, 1306-06-5, 51198-94-8; Cations; Cetrimonium Compounds; Surface-Active Agents; cetrimonium, 6899-10-1References: Rao, C.N.R., Cheetham, A.K., Materials science at the nanoscale (2006) Nanomaterials Handbook, pp. 1-2. , Y. Gogotsi (eds). CRC Press, Taylor & Francis Group New York;Guo, Y., Shi, D., Lian, J., Zdw, W., Cho, H., Liu, G., Quantum dot conjugated hydroxylapatite nanoparticles for in vivo imaging (2008) Nanotechnology, 19, 6p. , 175102; Queiroz, A.C., Teixeira, S., Santos, J.D., Monteiro, F.J., Production of porous hydroxyapatite with potential for controlled drug delivery (2004) Mater Sci Forum, 455-456, pp. 358-360. , 10.4028/www.scientific.net/MSF.455-456.358; Vallet-Regi, M., Ceramics for medical applications (2001) Journal of the Chemical Society, Dalton Transactions, (2), pp. 97-108. , DOI 10.1039/b007852m; Dorozhkin, S.V., Epple, M., Biological and medical significance of calcium phosphates (2002) Angewandte Chemie - International Edition, 41 (17), pp. 3130-3146. , DOI 10.1002/1521-3773(20020902)41:17<3130::AID-ANIE3130>3.0.CO;2-1; Ferraz, M.P., Monteiro, F.J., Manuel, C.M., Hydroxyapatite nanoparticles: A review of preparation methodologies (2004) J Appl Biomater Biomech, 2, pp. 74-80. , 1:CAS:528:DC%2BD2cXnvFWiurk%3D; Cengiz, B., Gokce, Y., Yildiz, N., Aktas, Z., Calimi, A., Synthesis and characterization of hydroxyapatite nanoparticles (2008) Colloids Surf A Physichochem Eng Aspects, 322, pp. 29-33. , 1:CAS:528:DC%2BD1cXmt1OqtbY%3D 10.1016/j.colsurfa.2008.02.011; Ying, J.Y., Mehnert, P.C., Wong, M.S., Synthesis and application of supramolecular-templated mesoporous materials (1999) Angew Chem Int Ed, 38, pp. 56-77. , 1:CAS:528:DyaK1MXpsValtg%3D%3D 10.1002/(SICI)1521-3773(19990115)38:1/ 2<56::AID-ANIE56>3.0.CO;2-E; Cates, M.E., Fielding, S.M., Rheology of giant micelles (2006) Advances in Physics, 55 (7-8), pp. 799-879. , DOI 10.1080/00018730601082029, PII T6J4U87W3G5RTN2J; Nagarajan, R., Molecular thermodynamics of giant micelles (2007) Giant Micelles-properties and Applications, pp. 2-5. , R. Zana E.W. Kaler (eds). CRC Pess, Taylor & Francis Group New York; Li, Y., Tjandra, W., Tam, K.C., Synthesis of nanoporous hydroxyapatite using cationic surfactants as templates (2008) Mater Res Bull, 43, pp. 2318-2326. , 1:CAS:528:DC%2BD1cXnsVSrtr4%3D 10.1016/j.materresbull.2007.08.008; Yao, J., Tjandra, W., Chen, Y.Z., Tam, K.C., Mab, J., Soh, B., Hydroxyapatite nanostructure material derived using cationic surfactant as a template (2003) J Mater Chem, 13, pp. 3053-3057. , 1:CAS:528:DC%2BD3sXptlemsro%3D 10.1039/b308801d; Berret, J.F., Rheology of wormlike micelles: Equilibrium properties and shear banding transition (2006) Molecular Gels. Materials with Self-assembled Fibrillar Networks, pp. 667-720. , R.G. Weiss P. Terech (eds). Springer Dordrecht; Kresge, C.T., Leonowicz, M.E., Roth, W.J., Vartuli, J.C., Beck, J.S., Ordered mesoporous molecular sieves synthesized by a liquid-crystal template mechanism (1992) Nature, 359 (6397), pp. 710-712. , DOI 10.1038/359710a0; Beck, J.S., Vartuli, J.C., Roth, W.J., Leonowicz, M.E., Kresge, C.T., Schmitt, K.D., A new family of mesoporous molecular sieves prepared with liquid crystal templates (1992) J Am Chem Soc, 114, pp. 10834-10843. , 1:CAS:528:DyaK38Xms1entr8%3D 10.1021/ja00053a020; Li, Y.Y., Li, J., Nakajima, B., Nanostructured porous biomaterials for controlled drug release systems (2008) Biomaterials-fabrication and Processing, pp. 196-206. , K.C. Paul L. Xuanyong (eds). CRC Press, Taylor & Francis Group New York. 10.1201/9780849379741; Herzberg, G., (1945) The Infrared and Raman Spectra of Poliatomic Molecules, , D van Nostrand Company, Inc. New York; Awonusi, A., Morris, M.D., Tecklenburg, M.M.J., Carbonate assignment and calibration in the Raman spectrum of apatite (2007) Calcified Tissue International, 81 (1), pp. 46-52. , DOI 10.1007/s00223-007-9034-0; Fowler, B.O., Infrared studies of apatites. I. Vibrational assignments for calcium, strontium, and barium hydroxyapatites utilizing isotopic substitution (1974) Inorg Chem, 13, pp. 194-207. , 1:CAS:528:DyaE2cXlsVWktw%3D%3D 10.1021/ic50131a039; Aza, P.N., Santos, C., Pazo, A., Aza, S., Cuscó, R., Artus, L., Vibrational properties of calcium phospate coumpounds. 1. Raman spectrum of β-tricalcium phosphate (1997) Chem Mater, 9, pp. 912-915. , 10.1021/cm960425d
Keywords: Ammonium compounds; Aqueous suspensions; article; Bromine compounds; Calcium; calcium phosphate; cationic surfactant; Cationic surfactants; Cations; Cetrimonium Compounds; Cetyltrimethylammonium bromide; chemical composition; Chemical compositions; Chemical structure; Crystallographic characteristics; Dyes; Heat treatment temperature; High quality; hydroxyapatite; Microscopy, Electron, Scanning; Microscopy, Electron, Transmission; nanorod; Nanorods; Nanotubes; Phosphate compounds; priority journal; Pyrolysis; Scanning electron microscopy; Sintering; Sintering temperatures; Surface-Active Agents; Surfactant template method; Surfactant templating; Suspensions (fluids); synthesis; Synthesis and characterizations; Thermal decompositions; X-Ray Diffraction

Corrected and improved model for educational simulation of neonatal cardiovascular pathophysiology - Zijlmans, M.; Sá-Couto, C.D.; van Meurs, W.L.; Goodwin, J.A.; Andriessen, P. (Simulation in HealthcareSimul. Healthc., 2009)
We identified errors in the software implementation of the mathematical model presented in: Sá Couto CD, van Meurs WL, Goodwin JA, Andriessen P. A model for educational simulation of neonatal cardiovascular pathophysiology. Simul Healthcare 2006;1:4-12. Simulation results obtained with corrected code are presented for future reference. All but one of the simulation results do not differ by more than 9% from the previously published results. The heart rate response to acute loss of 30% of blood volume, simulated with corrected code is stronger than published target data. This modeling error was masked by errors in code implementation. We improved this response and the model by adjusting the gains and adding thresholds and saturations in the baroreflex model. General considerations on identification of model and code errors and model validity are presented. Copyright © 2009 Society for Simulation in Healthcare.
Cited By (since 1996): 4Export Date: 21 November 2012Source: Scopusdoi: 10.1097/SIH.0b013e31818b27a8Language of Original Document: EnglishCorrespondence Address: Zijlmans, M.; INEB-Instituto de Engenharia Biomédica, Porto, PortugalReferences: Sá Couto, C.D., Van Meurs, W.L., Goodwin, J.A., Andriessen, P., A model for educational simulation of neonatal cardiovascular pathophysiology (2006) Simul Healthc, 1, pp. 4-12;Goodwin, J.A., Van Meurs, W.L., Sá Couto, C.D., Beneken, J.E.W., Graves, S.A., A model for educational simulation of infant cardiovascular physiology (2004) Anesth Analg, 99, pp. 1655-1664; Beneken, J.E.W., A mathematical approach to cardiovascular function (1965) The Uncontrolled Human System, , Thesis, University of Utrecht, The Netherlands; Andriessen, P., Bambang Oetomo, S., Peters, C., Vermeulen, B., Wijn, P.F.F., Blanco, C.E., Baroreceptor reflex sensitivity in human neonates: The effect of postmenstrual age (2005) J Physiol, 568, pp. 333-341; Segar, J.L., Roghair, R.D., Segar, E.M., Bailey, M.C., Scholz, T.D., Lamb, F.S., Early gestation dexamethasone alters baroreflex and vascular responses in newborn lambs before hypertension (2006) Am J Physiol Regul Integr Comp Physiol, 291, pp. R481-R488; Wallgren, G., Barr, M., Rudhe, U., Hemodynamic studies of induced acute hypo- and hypervolemia in the newborn infant (1964) Acta Paediatr, 53, pp. 1-12
Keywords: aorta coarctation; article; Baroreflex; bleeding; blood pressure; blood volume; Cardiac Output; cardiovascular disease; Cardiovascular Diseases; Cardiovascular physiology; computer program; Computer simulation; Congenital heart defect; congenital heart malformation; diastolic blood pressure; Education, Medical; Erratum; Fallot tetralogy; great vessels transposition; heart output; Heart rate; heart right ventricle pressure; human; Humans; Infant, Newborn; lung pressure; mathematical model; mean arterial pressure; medical education; medical error; methodology; Neonate; Neonatology; newborn; patent ductus arteriosus; pathophysiology; physiology; pressoreceptor reflex; priority journal; simulation; Software Design; systolic blood pressure; Validation; validity; vascular resistance; Verification; vital sign

The correlation between the adsorption of adhesive proteins and cell behaviour on hydroxyl-methyl mixed self-assembled monolayers - Barrias, C.C.; Martins, M.C.L.; Almeida-Porada, G.; Barbosa, M.A.; Granja, P.L. (BiomaterialsBiomaterials, 2009)
The objective of this study was to compare the biological effects of two key cell-adhesive proteins, fibronectin (FN) and vitronectin (VN), upon adsorption onto molecularly-designed model surfaces. Single-component and mixed self-assembled monolayers (SAMs) of alkanethiols on gold with OH and CH 3 terminal groups were prepared at 100%, 65%, 36% and 0% of OH at the surface, to generate a range of surfaces with a simple chemistry and a wettability gradient. FN and VN were adsorbed under non-competitive (single-protein solutions) and competitive (multi-protein solutions) conditions, and compared at different levels: adsorbed amount (radiolabelling), elution, functional presentation of cell-binding domains (ELISA), and role in mediating cell adhesion (antibody-based assay). The observed trends were related to mesenchymal stem cell response in terms of adhesion and overall cell morphology. Under non-competitive conditions, adsorption of both proteins increased with surface hydrophobicity. The presence of competitive proteins significantly decreased the adsorbed amounts, although both proteins were still detected in all SAMs. Adsorption of FN followed a trend similar to that of non-competitive conditions, while adsorption of VN was higher on 100%OH-SAMs. Concerning elution, retention of adsorbed VN was always higher than that of FN. For both proteins, functional presentation of cell-binding domains was more effective on the more hydrophilic 100%OH-SAMs. This fact, coupled to the ability of this type of SAMs to selectively recruit and retain VN in the presence of competitive serum proteins, seems to correlate with the better cell response observed on these surfaces, as compared with hydrophobic 0%OH(100%CH 3)-SAMs. © 2008 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 41Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2008.09.048PubMed ID: 18952279Language of Original Document: EnglishCorrespondence Address: Barrias, C.C.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, R. Campo Alegre 823, 4150-180 Porto, Portugal; email: ccbarrias@ineb.up.ptChemicals/CAS: fibronectin, 86088-83-7; gold, 7440-57-5; thiol derivative, 13940-21-1; Biocompatible Materials; Fibronectins; VitronectinReferences: Wilson, C.J., Clegg, R.E., Leavesley, D.I., Pearcy, M.J., Mediation of biomaterial-cell interactions by adsorbed proteins: a review (2005) Tissue Eng, 11, pp. 1-18;García, A.J., Vega, M.D., Boettiger, D., Modulation of cell proliferation and differentiation through substrate-dependent changes in fibronectin conformation (1999) Mol Biol Cell, 10, pp. 785-798; Keselowsky, B.G., Collard, D.M., García, A.J., Surface chemistry modulates fibronectin conformation and directs integrin binding and specificity to control cell adhesion (2003) J Biomed Mater Res A, 66, pp. 247-259; Underwood, P.A., Bennett, F.A., A comparison of the biological activities of the cell-adhesive proteins vitronectin and fibronectin (1989) J Cell Sci, 93, pp. 641-649; Steele, J.G., Johnson, G., Underwood, P.A., Role of serum vitronectin and fibronectin in adhesion of fibroblasts following seeding onto tissue culture polystyrene (1992) J Biomed Mater Res, 26, pp. 861-884; Steele, J.G., Dalton, B.A., Johnson, G., Underwood, P.A., Polystyrene chemistry affects vitronectin activity: an explanation for cell attachment to tissue culture polystyrene but not to unmodified polystyrene (1993) J Biomed Mater Res, 27, pp. 927-940; Underwood, P.A., Steele, J.G., Dalton, B.A., Effects of polystyrene surface chemistry on the biological activity of solid phase fibronectin and vitronectin, analysed with monoclonal antibodies (1993) J Cell Sci, 104, pp. 793-803; Suzuki, S., Oldberg, A., Hayman, E.G., Pierschbacher, M.D., Ruoslahti, E., Complete amino acid sequence of human vitronectin deduced from cDNA. Similarity of cell attachment sites in vitronectin and fibronectin (1985) EMBO J, 4, pp. 2519-2524; Lee, M.H., Ducheyne, P., Lynch, L., Boettiger, D., Composto, R.J., Effect of biomaterial surface properties on fibronectin-alpha5beta1 integrin interaction and cellular attachment (2006) Biomaterials, 27, pp. 1907-1916; Grinnell, F., Feld, M.K., Fibronectin adsorption on hydrophilic and hydrophobic surfaces detected by antibody binding and analyzed during cell adhesion in serum-containing medium (1982) J Biol Chem, 257, pp. 4888-4893; Sousa, S.R., Lamghari, M., Sampaio, P., Moradas-Ferreira, P., Barbosa, M.A., Osteoblast adhesion and morphology on TiO 2 depends on the competitive preadsorption of albumin and fibronectin (2008) J Biomed Mater Res A, 84, pp. 281-290; Fabrizius-Homan, D.J., Cooper, S.L., Competitive adsorption of vitronectin with albumin, fibrinogen, and fibronectin on polymeric biomaterials (1991) J Biomed Mater Res, 25, pp. 953-971; Bale, M.D., Wohlfahrt, L.A., Mosher, D.F., Tomasini, B., Sutton, R.C., Identification of vitronectin as a major plasma protein adsorbed on polymer surfaces of different copolymer composition (1989) Blood, 74, pp. 2698-2706; Thomas, C.H., McFarland, C.D., Jenkins, M.L., Rezania, A., Steele, J.G., Healy, K.E., The role of vitronectin in the attachment and spatial distribution of bone-derived cells on materials with patterned surface chemistry (1997) J Biomed Mater Res, 37, pp. 81-93; McFarland, C.D., Thomas, C.H., DeFilippis, C., Steele, J.G., Healy, K.E., Protein adsorption and cell attachment to patterned surfaces (2000) J Biomed Mater Res, 49, pp. 200-210; Love, J.C., Estroff, L.A., Kriebel, J.K., Nuzzo, R.G., Whitesides, G.M., Self-assembled monolayers of thiolates on metals as a form of nanotechnology (2005) Chem Rev, 105, pp. 1103-1169; Mrksich, M., Whitesides, G.M., Using self-assembled monolayers to understand the interactions of man-made surfaces with proteins and cells (1996) Annu Rev Biophys Biomol Struct, 25, pp. 55-78; Bain, C.D., Troughton, E.B., Tao, Y.T., Evall, J., Whitesides, G.M., Nuzzo, R.G., Formation of monolayer films by the spontaneous assembly of organic thiols from solution onto gold (1989) J Am Chem Soc, 111, pp. 321-335; Faucheux, N., Schweiss, R., Lützow, K., Werner, C., Groth, T., Self-assembled monolayers with different terminating groups as model substrates for cell adhesion studies (2004) Biomaterials, 25, pp. 2721-2730; Bernards, M.T., Jiang, S., pH-induced conformation changes of adsorbed vitronectin maximize its bovine aortic endothelial cell binding ability (2008) J Biomed Mater Res A; Martins, M.C., Ratner, B.D., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methyl-terminated alkanethiols self-assembled monolayers (2003) J Biomed Mater Res A, 67, pp. 158-171; Rodrigues, S.N., Gonçalves, I.C., Martins, M.C., Barbosa, M.A., Ratner, B.D., Fibrinogen adsorption, platelet adhesion and activation on mixed hydroxyl-/methyl-terminated self-assembled monolayers (2006) Biomaterials, 27, pp. 5357-5367; Chamberlain, J., Yamagami, T., Colletti, E., Theise, N.D., Desai, J., Frias, A., Efficient generation of human hepatocytes by the intrahepatic delivery of clonal human mesenchymal stem cells in fetal sheep (2007) Hepatology, 46, pp. 1935-1945; (1993) Iodine-125. A guide to radioiodination techniques, , Amersham Life Science, Little Chalfort; Horbett, T.A., Techniques for protein adsorption studies (1986) Techniques of biocompatibility tests, pp. 183-214. , Williams D.F. (Ed), CRC Press Inc., Harcover; Arima, Y., Iwata, H., Effect of wettability and surface functional groups on protein adsorption and cell adhesion using well-defined mixed self-assembled monolayers (2007) Biomaterials, 28, pp. 3074-3082; Capadona, J.R., Collard, D.M., Garcia, A.J., Fibronectin adsorption and cell adhesion to mixed monolayers of tri(ethylene glycol)- and methyl-terminated alkanethiols (2003) Langmuir, 19, pp. 1847-1852; Tidwell, C.D., Ertel, S.I., Ratner, B.D., Tarasevich, B.J., Atre, S., Allara, D.L., Endothelial cell growth and protein adsorption on terminally functionalized, self-assembled monolayers of alkanethiolates on gold (1997) Langmuir, 13, pp. 3404-3413; Jenney, C.R., Anderson, J.M., Adsorbed serum proteins responsible for surface dependent human macrophage behavior (2000) J Biomed Mater Res, 49, pp. 435-447; Wertz, C.F., Santore, M.M., Fibrinogen adsorption on hydrophilic and hydrophobic surfaces: geometrical and energetic aspects of interfacial relaxations (2002) Langmuir, 18, pp. 706-715; Pitt, W.G., Fabrizius-Homan, D.J., Mosher, D.F., Cooper, S.L., Vitronectin adsorption on polystyrene and oxidized polystyrene (1989) J Colloid Interface Sci, 129, pp. 231-239; Seiffert, D., Smith, J.W., The cell adhesion domain in plasma vitronectin is cryptic (1997) J Biol Chem, 272, pp. 13705-13710
Keywords: Adhesion; Adhesiveness; Adsorption; alkane; Animals; article; Biocompatible Materials; Biological Assay; bone marrow; Cattle; cell adhesion; Cell culture; Cell Movement; Cells; Cells, Cultured; cytology; cytoskeleton; Electric currents; Electron energy levels; enzyme linked immunosorbent assay; Fibronectin; Fibronectins; Focal adhesions; Functional groups; Functionalization; gold; human; human cell; Humans; hydrophilicity; hydrophobicity; Hydroxylation; isotope labeling; Mesenchymal stem cell; Mesenchymal Stem Cells; Microscopy, Confocal; Missile bases; Molecular interactions; monoclonal antibody; priority journal; Protein adsorption; protein analysis; protein binding; Protein Structure, Tertiary; Proteins; Self assembled monolayers; Self-assembled monolayers; stem cell; Stem cells; Surface Properties; thiol derivative; Vitronectin

Cytotoxicity evaluation of nanocrystalline diamond coatings by fibroblast cell cultures - Amaral, M.; Gomes, P.S.; Lopes, M.A.; Santos, J.D.; Silva, R.F.; Fernandes, M.H. (Acta BiomaterialiaActa Biomater., 2009)
The cytotoxicity profile of nanocrystalline diamond (NCD) coatings on a Si 3N 4 ceramic was investigated. This material is envisaged to have biomedical dental applications such as burrs and surgical instruments. Two fibroblast cell culture systems were used to address the cytotoxicity of NCD-coated samples: L929 cells (a mouse permanent cell line) and human gingival fibroblasts. Cell behavior was evaluated in terms of cell adhesion, cell viability/proliferation (mitochondrial function, MTT assay) and the pattern of cell growth. Fibroblast cell behavior on standard polystyrene culture plates was used as control, as Si 3N 4 substrates have previously been shown to be biocompatible. NCD coatings provided a suitable surface for cell attachment, spreading and proliferation. Human gingival cells showed a homogeneous cytoplasm spreading, a flattened elongated morphology and a typical parallel alignment on confluent cultures. In comparison, L929 cells denoted a lower cytoplasm expansion, a heterogeneous spreading but a higher proliferation rate. For both cells, after few days, the NCD coating was completely covered with continuous cell layers. As compared to standard polystyrene culture plates, no deleterious or cytotoxic responses were observed with L929 and human fibroblast cell cultures, and in both a slight enhancement in cell proliferation was observed. In addition, the seeded NCD film allowed reproduction of the typical features of the two cell culture systems tested, further suggesting the lack of cytotoxicity of this coating. © 2008 Acta Materialia Inc.
Cited By (since 1996): 8Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2008.08.015PubMed ID: 18819854Language of Original Document: EnglishCorrespondence Address: Amaral, M.; CICECO, Department of Ceramics and Glass Engineering, University of Aveiro, 3810-193 Aveiro, Portugal; email: margarida.amaral@ua.ptChemicals/CAS: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide, 298-93-1; diamond, 7782-40-3; polystyrene, 9003-53-6; silicon nitride, 12033-89-5; Culture Media; Diamond, 7782-40-3References: Griffin, J., Ray, P.C., Role of inert gas in the low-temperature nano-diamond chemical vapour deposition process (2006) Nanotechnology, 17, pp. 1225-1229;Mitura, S., Mitura, K., Niedzielski, P., Louda, P., Danilenko, V., Nanocrystalline diamond, its synthesis, properties and applications (2006) J Achievements Mater Manuf Eng, 16, pp. 9-16; Okrój, W., Kamińska, M., Klimek, L., Szymański, W., Walkowiak, B., Blood platelets in contact with nanocrystalline diamond surfaces (2006) Diamond Relat Mater, 15, pp. 1535-1539; Xiao, X., Wang, J., Liu, C., Carlisle, J.A., Mech, B., Greenberg, R., In vitro and in vivo evaluation of ultrananocrystalline diamond for coating of implantable retinal microchips (2006) J Biomed Mater Res B: Appl Biomater, 77 B, pp. 273-281; Tang, L., Tsai, C., Gerberich, W.W., Kruckeberg, L., Kania, D.R., Biocompatibility of chemical-vapour-deposited diamond (1995) Biomaterials, 16, pp. 483-488; Steinmueller-Nethl, D., Kloss, F.R., Haq, M.N.U., Rainer, M., Larsson, K., Linsmeier, C., Strong binding of bioactive BMP-2 to nanocrystalline diamond by physisorption (2006) Biomaterials, 27, pp. 4547-4556; Wenmackers, S., Christiaens, P., Daenen, M., Haenen, K., Nesládek, M., Ven, M., DNA attachment to nanocrystalline diamond films (2005) Phys Status Solidi, 202, pp. 2212-2216; Retama, J.R., Hernando, J., Lopez-Ruiz, B., Härtl, A., Steinmüller, D., Stutzmann, M., Synthetic nanocrystalline diamond as a third-generation biosensor support (2006) Langmuir, 22, pp. 5837-5842; Siew, P.S., Loh, K.P., Poh, W.C., Zhang, H., Biosensing properties of nanocrystalline diamond film grown on polycrystalline diamond electrodes (2005) Diamond Relat Mater, 14, pp. 426-431; Jakubowski, W., Bartosz, G., Niedzielski, P., Szymanski, W., Walkowiak, B., Nanocrystalline diamond surface is resistant to bacterial colonization (2004) Diamond Relat Mater, 13, pp. 1761-1763; Trava-Airoldi, V.J., Corat, E.J., Leite, N.F., Nono, M., Ferreira, N.G., Baranauskas, V., CVD diamond burrs-development and applications (1996) Diamond Relat Mater, 5, pp. 857-860; Amar, M., Ahmed, W., Sein, H., Jones, A.N., Rego, C., Chemical vapour deposition of diamond coatings onto molybdenum dental tools (2003) J Phys Condens Matter, 15, pp. S2977-S2982; Tetsumura, A., Honda, E., Sasaki, T., Kino, K., Metallic residues as a source of artifacts in magnetic resonance imaging of the temporomandibular joint (1999) Dentomaxillofac Radiol, 28, pp. 186-190; Carvalho, C.A., Fagundes, T.C., Barata, T.E., Trava-Airoldi, V.J., Navarro, M.L., The use of CVD diamond burrs for ultraconservative cavity preparations: a report of two cases (2007) J Esthet Restor Dent, 19, pp. 19-29; Mitura, K., Niedzielski, P., Grzegorz, B., Moll, J., Walkowiak, B., Pawlowska, Z., Interactions between carbon coatings and tissue (2006) Surf Coat Technol, 201, pp. 2117-2123; Fries, M.D., Vohra, Y.K., Microcrystalline and nanocrystalline diamond film deposition on cobalt chrome alloy (1999) Thin films-stresses and mechanical properties VIII, , Vinci R., Kraft O., Moody N., Besser P., and Shaffer II E. (Eds), MRS Publications, Boston, MA; Fries, M.D., Vohra, Y.K., Properties of nanocrystalline thin films grown by MPCVD for biomedical implant purposes (2004) Diamond Relat Mater, 13, pp. 1740-1743; Papo, M.J., Catledge, S.A., Vohra, Y.K., Mechanical wear behavior of nanocrystalline and multilayer diamond coatings on temporomandibular joint implants (2004) J Mater Sci: Mater Med, 15, pp. 773-777; Sun, F.H., Zhang, Z.M., Ma, Y.P., Chen, M., Synthesis of nanocrystalline diamond films on smooth WC-Co cemented carbide substrates (2007) Int J Abrasive Technol, 1, pp. 161-172; Belmonte, M., Fernandes, A.J.S., Costa, F.M., Oliveira, F.J., Silva, R.F., Adhesion behaviour assessment on diamond coated silicon nitride by acoustic emission (2003) Diamond Relat Mater, 12, pp. 733-737; Petzow, G., Herrmann, M., Silicon nitride ceramics (2002) Struct Bond, 102, pp. 47-167; Amaral, M., Costa, M.A., Lopes, M.A., Silva, R.F., Santos, J.D., Fernandes, M.H., Si 3N 4-bioglass composites stimulate the proliferation of MG63 osteoblast-like cells and osteogenic differentiation of human bone marrow cells (2002) Biomaterials, 23, pp. 4897-4906; Kue, R., Sahrabi, A., Nagle, D., Frondonza, C., Hungerford, D., Enhanced proliferation and osteocalcin production by human osteoblast-like cells on silicon nitride ceramic discs (1999) Biomaterials, 20, pp. 1195-1201; Popov, C., Kulisch, W., Jelinek, M., Bock, A., Strnad, J., Nanocrystalline diamond/amorphous carbon composite films for applications in tribology, optics and biomedicine (2006) Thin Solid Films, 494, pp. 92-97; Chong, K.F., Loh, K.P., Vedula, S.R., Lim, C.T., Sternschulte, H., Steinmüller, D., Cell adhesion properties on photochemically functionalized diamond (2007) Langmuir, 23, pp. 5615-5621; Bajaj, P., Akin, D., Gupta, A., Sherman, D., Shi, B., Auciello, O., Ultra-nanocrystalline diamond film as an optimal cell interface for biomedical applications (2007) Biomed Microdevices, , [Epub ahead of print]; Arnold, L.F., Baram, B., In vitro culture of periodontal ligament cells (1972) J Dent Res, 51, pp. 953-959; Piche, J.E., Carnes Jr., D.L., Graves, D.T., Initial characterization of cells derived from human periodontia (1989) J Dent Res, 68, pp. 761-767; Trigo Cabral, C., Costa, M.A., Fernandes, M.H., In vitro models of periodontal cells: a comparative study of long-term gingival, periodontal ligament and alveolar bone cell cultures in the presence of β-glycerophosphate and dexamethasone (2007) J Mater Sci: Mater Med, 18, pp. 1079-1088; Bajpai, P.K., Billote, W.G., Ceramic biomaterials (1995) The biomedical engineering handbook, pp. 552-580. , Bronzino J.D. (Ed), CRC Press, Boca Raton, FL; Nishitani-Gamo, M., Ando, T., Watanabe, K., Sekita, M., Dennig, P.A., Yamamoto, K., Interfacial structures of oriented diamond on Si (1 0 0) characterized by confocal Raman spectroscopy (1997) Diamond Relat Mater, 6, pp. 1036-1040; Ferrari, A.C., Robertson, J., Origin of the 1150 cm -1 Raman mode in nanocrystalline diamond (2001) Phys Rev B, 63, pp. 121405-1-121405-4; Pfeiffer, R., Kuzmany, H., Knoll, P., Bokova, S., Salk, N., Günther, B., Evidence for trans-polyacetylene in nano-crystalline diamond films (2003) Diamond Relat Mater, 12, pp. 268-271; Zimmermann, T., Janischowsky, K., Denisenko, A., Guillén, F.J.H., Kubovic, M., Gruen, D.M., Nanocrystalline diamond pn-structure grown by hot-filament CVD (2006) Diamond Relat Mater, 15, pp. 203-206; Krauss, A.R., Auciello, O., Gruen, D.M., Jayatissa, A., Sumant, A., Tucek, J., Ultrananocrystalline diamond thin films for MEMS and moving mechanical assembly devices (2001) Diamond Relat Mater, 10, pp. 1952-1961; Amaral, M., Fernandes, A.J.S., Vila, M., Oliveira, F.J., Silva, R.F., Growth rate improvements in the hot-filament CVD deposition of nanocrystalline diamond (2006) Diamond Relat Mater, 15, pp. 1822-1827; Alberts, B., Johnson, A., Lewis, J., Raff, M., Roberts, K., Walter, P., The cytoskeleton (2002) Molecular biology of the cell. 4th ed., pp. 907-972. , Alberts B., Johnson A., Lewis J., Raff M., Roberts K., and Walter P. (Eds), Garland Publishing, New York; Stamenovic, D., Effects of cytoskeletal prestress on cell rheological behaviour (2005) Acta Biomater, 1, pp. 255-262; Freshney, T.I., Biology of cultured cells (2000) Culture of animal cells. A manual of basic technique, pp. 9-18. , Wiley-Liss, New York; Garguilo, J.M., Davis, B.A., Buddie, M., Köck, F.A.M., Nemanich, R.J., Fibrinogen adsorption onto microwave plasma chemical vapor deposited diamond films (2004) Diamond Relat Mater, 13, pp. 595-599; Ariano, P., Baldellia, P., Carbonea, E., Gilardino, A., Giudicea, A.L., Lovisolo, D., Cellular adhesion and neuronal excitability on functionalised diamond surfaces (2005) Diamond Relat Mater, 14, pp. 669-674; Heinrich, G., Grijgler, T., Rosiwal, S.M., Singer, R.F., CVD diamond coated titanium alloys for biomedical and aerospace applications (1997) Surf Coat Technol, 94-95, pp. 514-520; Müller, R., Adamschik, M., Steidl, D., Kohn, E., Thamasett, S., Stiller, S., Application of CVD-diamond for catheter ablation in the heart (2004) Diamond Relat Mater, 13, pp. 1080-1083; Nordsletten, L., Hogasen, A.K.M., Konttinen, Y.T., Santavirta, S., Aspenberg, P., Aasen, A.O., Human monocytes stimulation by particles of hydroxyapatite, silicon carbide and diamond: in vitro studies of new prosthesis coatings (1996) Biomaterials, 17, pp. 1521-1527; Aspenberg, P., Antilla, A., Konttinen, Y.T., Lappalainen, R., Goodman, S.B., Nordsletten, L., Benign response to particles of diamond and SiC: bone chamber studies of new joint replacement coating materials in rabbits (1996) Biomaterials, 17, pp. 807-812; Specht, C.G., Williams, O.A., Jackman, R.B., Schoepfer, R., Ordered growth of neurons on diamond (2004) Biomaterials, 25, pp. 4073-4078; Schrand, A.M., Huang, H., Carlson, C., Schlager, J.J., Omacr Sawa, E., Hussain, S.M., Are diamond nanoparticles cytotoxic? (2007) J Phys Chem B, 111, pp. 2-7; International Organization for Standardization, ISO 10993-5: biological evaluation of medical devices. Part 5. Tests for cytotoxicity: in vitro methods. Geneva; 1992International Organization for Standardization, ISO 7405: dentistry-preclinical evaluation of biocompatibility of medical devices used in dentistry-test methods for dental materials. Geneva; 1997Kaplan, F.S., Hayes, W.C., Keaveny, T.M., Boskey, A., Einhorn, T.A., Iannotti, J.P., Form and function of bone (1994) Orthopedic basic science, pp. 127-185. , Simon S.P. (Ed), American Academy of Orthopedic Surgeons, Columbus, OH; Webster, T.J., Proteins: structure and interactions patterns to solid surfaces (2004) Encyclopedia of nanoscience and nanotechnology, pp. 3079-3095. , Schwarz J.A., Contescu C., and Putyera K. (Eds), Marcel Dekker, New York; Webster, T.J., Enhanced functions of osteoblasts on nanophase ceramics (2000) Biomaterials, 21, pp. 1803-1810; Webster, T.J., Ergun, C., Doremus, R.H., Siegel, R.W., Bizios, R., Specific proteins mediate enhanced osteoblast adhesion on nanophase ceramics (2000) J Biomed Mater Res, 51, pp. 475-483; Shane, A.C., Marc, D.F., Yogesh, K.V., William, R.L., Jack, E.L., Shanna, W., Nanostructured ceramics for biomedical implants (2002) J Nanosci Nanotechnol, 2, pp. 1-20; Price, R.L., Haberstroh, K.M., Webster, T.J., Enhanced functions of osteoblasts on nanostructured surfaces of carbon and alumina (2003) Med Biol Eng Comput, 41, pp. 372-375; Webster, T.J., Siegel, R.W., Bizios, R., Osteoblast adhesion on nanophase ceramics (1999) Biomaterials, 20, pp. 1221-1227; Perla, V., Webster, T.J., Better osteoblast adhesion on nanoparticulate selenium-A promising orthopedic implant material (2005) J Biomed Mater Res, 75 A, pp. 356-364
Keywords: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide; animal cell; Animals; article; Biocompatibility; Biomedical dental applications; biomedicine; cell adhesion; Cell Division; cell function; cell growth; Cell Line; cell proliferation; cell spreading; cell structure; cell surface; cell survival; cell viability; ceramics; controlled study; Culture Media; cytoplasm; Cytotoxicity; dentistry; diamond; Fibroblast cell cultures; fibroblast culture; Fibroblasts; gingiva; human; human cell; Humans; material coating; Mice; Microscopy, Electron, Scanning; mitochondrial respiration; mouse; nanocrystal; Nanocrystalline diamond coating; Nanostructures; nonhuman; polystyrene; priority journal; Silicon nitride; Surgical instrument

Decision trees using the minimum Entropy-of-error principle - De Sá, J.P.M.; Gama, J.; Sebastião, R.; Alexandre, L.A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2009)
Binary decision trees based on univariate splits have traditionally employed so-called impurity functions as a means of searching for the best node splits. Such functions use estimates of the class distributions. In the present paper we introduce a new concept to binary tree design: instead of working with the class distributions of the data we work directly with the distribution of the errors originated by the node splits. Concretely, we search for the best splits using a minimum entropy-of-error (MEE) strategy. This strategy has recently been applied in other areas (e.g. regression, clustering, blind source separation, neural network training) with success. We show that MEE trees are capable of producing good results with often simpler trees, have interesting generalization properties and in the many experiments we have performed they could be used without pruning. © 2009 Springer Berlin Heidelberg.
Conference code: 77256Export Date: 21 November 2012Source: Scopusdoi: 10.1007/978-3-642-03767-2_97Language of Original Document: EnglishCorrespondence Address: De Sá, J. P. M.; INEB-Instituto de Engenharia Biomédica, Porto, Portugal; email: jmsa@fe.up.ptReferences: Asuncion, A., Newman, D.J., (2007) UCI Machine Learning Repository, , http://www.ics.uci.edu/̃mlearn/MLRepository.html, Univ. of California, SICS, Irvine, CA;Breiman, L., Friedman, J.H., Olshen, R.A., Stone, C.J., (1993) Classification and Regression Trees, , Chapman & Hall/CRC, Boca Raton; Devroye, L., Giörfi, L., Lugosi, G., (1996) A Probabilistic Theory of Pattern Recognition, , Springer, Heidelberg; Forina, M., Armanino, C., Eigenvector Projection and Simplified Nonlinear Mapping of Fatty Acid Content of Italian Olive Oils (1981) Ann. Chim, 72, pp. 127-155; Loh, W.-Y., Shih, Y.-S., Split Selection Methods for Classification Trees (1997) Statistica Sinica, 7, pp. 815-840; Marques de Sá, J.P., (2007) Applied Statistics Using SPSS, STATISTICA, MATLAB and R, , 2nd edn. Springer, Heidelberg; Quinlan, J.R., Induction of Decision Trees (1986) Machine Learning, 1, pp. 81-106; Quinlan, J.R.: C4.5 Programs for Machine Learning. Morgan Kaufmann, San Francisco (1993)Silva, L.M., Felgueiras, C.S., Alexandre, L.A., Marques de Sá, J., Error Entropy in Classification Problems: A Univariate Data Analysis (2006) Neural Comp, 18, pp. 2036-2061; Silva, L.M., Embrechts, M.J., Santos, J.M., de Sá, J.M., The influence of the risk functional in data classification with mLPs (2008) LNCS, 5163, pp. 185-194. , Kůrková, V, Neruda, R, Koutník, J, eds, ICANN 2008, Part I, Springer, Heidelberg Sponsors: University of Munster; International Association for Pattern Recognition; Olympus Soft Imaging Solutions GmbH; Philips
Keywords: Binary decision trees; Binary trees; Blind source separation; Class distributions; decision trees; Electronic medical equipment; entropy; entropy-of-error; Generalization properties; Image analysis; Minimum entropy; Neural network training; Neural networks; New concept; node split criteria; Univariate

The effect of the co-immobilization of human osteoprogenitors and endothelial cells within alginate microspheres on mineralization in a bone defect - Grellier, M.; Granja, P.L.; Fricain, J.-C.; Bidarra, S.J.; Renard, M.; Bareille, R.; Bourget, C.; Amédée, J.; Barbosa, M.A. (BiomaterialsBiomaterials, 2009)
Bone regeneration seems to be dependant on cell communication between osteogenic and endothelial cells arising from surrounding blood vessels. This study aims to determine whether endothelial cells can regulate the osteogenic potential of osteoprogenitor cells in vitro and in vivo, in a long bone defect, when co-immobilized in alginate microspheres. Alginate is a natural polymer widely used as a biomaterial for cell encapsulation. Human osteoprogenitors (HOP) from bone marrow mesenchymal stem cells were immobilized alone or together with human umbilical vein endothelial cells (HUVEC) inside irradiated, oxidized and RGD-grafted alginate microspheres. Immobilized cells were cultured in dynamic conditions and cell metabolic activity increased during three weeks. The gene expression of alkaline phosphatase and osteocalcin, both specific markers of the osteoblastic phenotype, and mineralization deposits were upregulated in co-immobilized HOPs and HUVECs, comparing to the immobilization of monocultures. VEGF secretion was also increased when HOPs were co-immobilized with HUVECs. Microspheres containing co-cultures were further implanted in a bone defect and bone formation was analysed by μCT and histology at 3 and 6 weeks post-implantation. Mineralization was observed inside and around the implanted microspheres containing the immobilized cells. However, when HOPs were co-immobilized with HUVECs, mineralization significantly increased. These findings demonstrate that co-immobilization of osteogenic and endothelial cells within RGD-grafted alginate microspheres provides a promising strategy for bone tissue engineering. © 2009 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 38Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2009.02.033PubMed ID: 19299013Language of Original Document: EnglishCorrespondence Address: Grellier, M.; INSERM, U577, Université Victor Segalen Bordeaux 2, UMR-S577, F-33076 Bordeaux Cedex, France; email: maritie.grellier@inserm.frChemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; alkaline phosphatase, 9001-78-9; arginylglycylaspartic acid, 99896-85-2; osteocalcin, 136461-80-8; Alginates; Glucuronic Acid, 576-37-4; Hexuronic Acids; alginic acid, 9005-32-7References: Oreffo, R.O., Triffitt, J.T., Future potentials for using osteogenic stem cells and biomaterials in orthopedics (1999) Bone, 25 (2 SUPPL), pp. 5S-9S;Lubiatowski, P., Kruczynski, J., Gradys, A., Trzeciak, T., Jaroszewski, J., Articular cartilage repair by means of biodegradable scaffolds (2006) Transplant Proc, 38 (1), pp. 320-322; Evangelista, M.B., Hsiong, S.X., Fernandes, R., Sampaio, P., Kong, H.J., Barrias, C.C., Upregulation of bone cell differentiation through immobilization within a synthetic extracellular matrix (2007) Biomaterials, 28 (25), pp. 3644-3655; Gerber, H.P., Ferrara, N., Angiogenesis and bone growth (2000) Trends Cardiovasc Med, 10 (5), pp. 223-228; Carano, R.A., Filvaroff, E.H., Angiogenesis and bone repair (2003) Drug Discov Today, 8 (21), pp. 980-989; Deckers, M.M., Karperien, M., van der Bent, C., Yamashita, T., Papapoulos, S.E., Lowik, C.W., Expression of vascular endothelial growth factors and their receptors during osteoblast differentiation (2000) Endocrinology, 141 (5), pp. 1667-1674; Guillotin, B., Bourget, C., Remy-Zolgadri, M., Bareille, R., Fernandez, P., Conrad, V., Human primary endothelial cells stimulate human osteoprogenitor cell differentiation (2004) Cell Physiol Biochem, 14 (4-6), pp. 325-332; Villars, F., Bordenave, L., Bareille, R., Amedee, J., Effect of human endothelial cells on human bone marrow stromal cell phenotype: role of VEGF? (2000) J Cell Biochem, 79 (4), pp. 672-685; Kaigler, D., Krebsbach, P.H., Wang, Z., West, E.R., Horger, K., Mooney, D.J., Transplanted endothelial cells enhance orthotopic bone regeneration (2006) J Dent Res, 85 (7), pp. 633-637; Sun, H., Qu, Z., Guo, Y., Zang, G., Yang, B., In vitro and in vivo effects of rat kidney vascular endothelial cells on osteogenesis of rat bone marrow mesenchymal stem cells growing on polylactide-glycoli acid (PLGA) scaffolds (2007) Biomed Eng Online, 6, p. 41; Augst, A.D., Kong, H.J., Mooney, D.J., Alginate hydrogels as biomaterials (2006) Macromol Biosci, 6 (8), pp. 623-633; Leal, D., Matsuhiro, B., Rossi, M., Caruso, F., FT-IR spectra of alginic acid block fractions in three species of brown seaweeds (2008) Carbohydr Res, 343 (2), pp. 308-316; Keshaw, H., Forbes, A., Day, R.M., Release of angiogenic growth factors from cells encapsulated in alginate beads with bioactive glass (2005) Biomaterials, 26 (19), pp. 4171-4179; Alsberg, E., Anderson, K.W., Albeiruti, A., Franceschi, R.T., Mooney, D.J., Cell-interactive alginate hydrogels for bone tissue engineering (2001) J Dent Res, 80 (11), pp. 2025-2029; Abbah, S.A., Lu, W.W., Chan, D., Cheung, K.M., Liu, W.G., Zhao, F., In vitro evaluation of alginate encapsulated adipose-tissue stromal cells for use as injectable bone graft substitute (2006) Biochem Biophys Res Commun, 347 (1), pp. 185-191; Barrias, C.C., Lamghari, M., Granja, P.L., Sa Miranda, M.C., Barbosa, M.A., Biological evaluation of calcium alginate microspheres as a vehicle for the localized delivery of a therapeutic enzyme (2005) J Biomed Mater Res A, 74 (4), pp. 545-552; Durrieu, M.C., Pallu, S., Guillemot, F., Bareille, R., Amedee, J., Baquey, C.H., Grafting RGD containing peptides onto hydroxyapatite to promote osteoblastic cells adhesion (2004) J Mater Sci Mater Med, 15 (7), pp. 779-786; Kong, H.J., Smith, M.K., Mooney, D.J., Designing alginate hydrogels to maintain viability of immobilized cells (2003) Biomaterials, 24 (22), pp. 4023-4029; Bordenave, L., Baquey, C., Bareille, R., Lefebvre, F., Lauroua, C., Guerin, V., Endothelial cell compatibility testing of three different Pellethanes (1993) J Biomed Mater Res, 27 (11), pp. 1367-1381; Rowley, J.A., Mooney, D.J., Alginate type and RGD density control myoblast phenotype (2002) J Biomed Mater Res, 60 (2), pp. 217-223; Villars, F., Guillotin, B., Amedee, T., Dutoya, S., Bordenave, L., Bareille, R., Effect of HUVEC on human osteoprogenitor cell differentiation needs heterotypic gap junction communication (2002) Am J Physiol Cell Physiol, 282 (4), pp. C775-C785; Clarkin, C.E., Emery, R.J., Pitsillides, A.A., Wheeler-Jones, C.P., Evaluation of VEGF-mediated signaling in primary human cells reveals a paracrine action for VEGF in osteoblast-mediated crosstalk to endothelial cells (2007) J Cell Physiol; Cheng, C., Liu, H., Ge, H., Qian, J., Qin, J., Sun, L., Essential role of Src suppressed C kinase substrates in endothelial cell adhesion and spreading (2007) Biochem Biophys Res Commun, 358 (1), pp. 342-348; Gerber, H.P., McMurtrey, A., Kowalski, J., Yan, M., Keyt, B.A., Dixit, V., Vascular endothelial growth factor regulates endothelial cell survival through the phosphatidylinositol 3′-kinase/Akt signal transduction pathway. Requirement for Flk-1/KDR activation (1998) J Biol Chem, 273 (46), pp. 30336-30343; Cross, M.J., Claesson-Welsh, L., FGF and VEGF function in angiogenesis: signalling pathways, biological responses and therapeutic inhibition (2001) Trends Pharmacol Sci, 22 (4), pp. 201-207; Volkmer, E., Drosse, I., Otto, S., Stangelmayer, A., Stengele, M., Kallukalam, B.C., Hypoxia in static and dynamic 3D culture systems for tissue engineering of bone (2008) Tissue Eng Part A, 14 (8), pp. 1331-1340; Stiehler, M., Bunger, C., Baatrup, A., Lind, M., Kassem, M., Mygind, T., Effect of dynamic 3-D culture on proliferation, distribution, and osteogenic differentiation of human mesenchymal stem cells (2008) J Biomed Mater Res A; Mann, V., Huber, C., Kogianni, G., Jones, D., Noble, B., The influence of mechanical stimulation on osteocyte apoptosis and bone viability in human trabecular bone (2006) J Musculoskelet Neuronal Interact, 6 (4), pp. 408-417; Bjerre, L., Bunger, C.E., Kassem, M., Mygind, T., Flow perfusion culture of human mesenchymal stem cells on silicate-substituted tricalcium phosphate scaffolds (2008) Biomaterials, 29 (17), pp. 2616-2627; Bouletreau, P.J., Warren, S.M., Spector, J.A., Peled, Z.M., Gerrets, R.P., Greenwald, J.A., Hypoxia and VEGF up-regulate BMP-2 mRNA and protein expression in microvascular endothelial cells: implications for fracture healing (2002) Plast Reconstr Surg, 109 (7), pp. 2384-2397; Simmons, C.A., Alsberg, E., Hsiong, S., Kim, W.J., Mooney, D.J., Dual growth factor delivery and controlled scaffold degradation enhance in vivo bone formation by transplanted bone marrow stromal cells (2004) Bone, 35 (2), pp. 562-569; Lu, H.H., Vo, J.M., Chin, H.S., Lin, J., Cozin, M., Tsay, R., Controlled delivery of platelet-rich plasma-derived growth factors for bone formation (2008) J Biomed Mater Res A; Yu, H., Vandevord, P.J., Gong, W., Wu, B., Song, Z., Matthew, H.W., Promotion of osteogenesis in tissue-engineered bone by pre-seeding endothelial progenitor cells-derived endothelial cells (2008) J Orthop Res, 26 (8), pp. 1147-1152; Bouhadir, K.H., Lee, K.Y., Alsberg, E., Damm, K.L., Anderson, K.W., Mooney, D.J., Degradation of partially oxidized alginate and its potential application for tissue engineering (2001) Biotechnol Prog, 17 (5), pp. 945-950
Keywords: adult; aged; Alginate; Alginates; alginic acid; alkaline phosphatase; animal tissue; Animals; arginylglycylaspartic acid; article; Bioactivity; Biopolymers; Blood vessel prostheses; Blood Vessels; Bone; Bone and Bones; bone defect; Bone defects; Bone formations; Bone marrow mesenchymal stem cells; bone mineralization; Bone Regeneration; Bone regenerations; bone tissue; Bone tissue engineerings; Calcification, Physiologic; Cell communications; Cell culture; Cell encapsulations; cell function; cell growth; Cell immobilization; Cell membranes; cell metabolism; Cells, Cultured; Co immobilizations; Co-culture; coculture; computer assisted tomography; controlled study; Defects; Dynamic conditions; Endothelial Cells; endothelium cell; gene expression; gene expression regulation; Glucuronic Acid; Grafting (chemical); Hexuronic Acids; histology; human; human cell; Human umbilical vein endothelial cells; Humans; Humulus; immobilized cell; Immobilized cells; in vitro study; in vivo study; In-vitro; In-vivo; irradiation; long bone; Long bones; Mesenchymal stem cell; Metabolic activities; Mice; Mice, Nude; microsphere; Microspheres; Middle Aged; Mineralogy; monoculture; mouse; nonhuman; osteoblast; osteocalcin; Osteogenic; Osteogenic potentials; Osteoprogenitor cells; Osteoprogenitors; Oxidation; Peptides; phenotype; Post implantations; priority journal; Self assembly; Sodium compounds; stem cell transplantation; Stem cells; Tissue engineering; umbilical vein; upregulation; Vascular endothelial growth factor (VEGF); X ray analysis; Young Adult

Engineering endochondral bone: In vitro studies - Oliveira, S.M.; Amaral, I.F.; Barbosa, M.A.; Teixeira, C.C. (Tissue Engineering - Part ATissue Eng. Part A, 2009)
Chitosan scaffolds have been shown to possess biological and mechanical properties suitable for tissue engineering and clinical applications. In the present work, chitosan sponges were evaluated regarding their ability to support cartilage cell proliferation and maturation, which are the first steps in endochondral bone formation. Chitosan sponges were seeded with chondrocytes isolated from chicken embryo sterna. Chondrocyte/chitosan constructs were cultured for 20 days, and treated with retinoic acid (RA) to induce chondrocyte maturation and matrix synthesis. At different time points, samples were collected for microscopic, histological, biochemical, and mechanical analyses. Results show chondrocyte attachment, proliferation, and abundant matrix synthesis, completely obliterating the pores of the sponges. RA treatment caused chondrocyte hypertrophy, characterized by the presence of type X collagen in the extracellular matrix and increased alkaline phosphatase activity. In addition, hypertrophy markedly changed the mechanical properties of the chondrocyte/chitosan constructs. In conclusion, we have developed chitosan sponges with adequate pore structure and mechanical properties to serve as a support for hypertrophic chondrocytes. In parallel studies, we have evaluated the ability of this mature cartilage scaffold to induce endochondral ossification. © Copyright 2009, Mary Ann Liebert, Inc. 2009.
Cited By (since 1996): 19Export Date: 21 November 2012Source: Scopusdoi: 10.1089/ten.tea.2008.0051Language of Original Document: EnglishCorrespondence Address: Teixeira, C. C.; Departments of Basic Science and Craniofacial Biology and of Orthodontics, New York University, College of Dentistry, 345 East 24th St., New York, NY 10010; email: ct40@nyu.eduChemicals/CAS: DNA, 9007-49-2; alkaline phosphatase, 9001-78-9; chitosan, 9012-76-4; retinoic acid, 302-79-4; Alkaline Phosphatase, 3.1.3.1; Chitosan, 9012-76-4; Collagen Type X; DNA, 9007-49-2; Tretinoin, 302-79-4References: Steinemann, S.G., Metal implants and surface reactions (1996) Injury, 27, p. 16;Disegi, J.A., Eschbach, L., Stainless steel in bone surgery (2000) Injury, 31, p. 2; Reitman, R.D., Emerson, R., Higgins, L., Head, W., Thirteen year results of total hip arthroplasty using a tapered titanium femoral component inserted without cement in patients with type C bone (2003) J Arthroplasty, 18, p. 116; Epinette, J.A., Manley, M.T., D'Antonio, J.A., Edidin, A.A., Capello, W.N., A 10-year minimum follow-up of hydroxyapatite-coated threaded cups: Clinical, radiographic and survivorship analyses with comparison to the literature (2003) J Arthroplasty, 18, p. 140; Xynos, I.D., Hukkanen, M.V., Batten, J.J., Buttery, L.D., Hench, L.L., Polak, J.M., Bioglass 45S5 stimulates osteoblast turnover and enhances bone formation in vitro: Implications and applications for bone tissue engineering (2000) Calcif Tissue Int, 67, p. 321; Barrias, C.C., Ribeiro, C.C., Barbosa, M.A., Adhesion and proliferation of human osteoblastic cells seeded on injectable hydroxyapatite microspheres (2004) Bioceramics, 254, p. 877; Saito, N., Takaoka, K., New synthetic biodegradable polymers as BMP carriers for bone tissue engineering (2003) Biomaterials, 24, p. 2287; Suzuki, T., Kawamura, H., Kasahara, T., Nagasaka, H., Resorbable poly-L-lactide plates and screws for the treatment of mandibular condylar process fractures: A clinical and radiologic follow-up study (2004) J Oral Maxillofac Surg, 62, p. 919; Sittinger, M., Reitzel, D., Dauner, M., Hierlemann, H., Hammer, C., Kastenbauer, E., Planck, H., Bujia, J., Resorbable polyesters in cartilage engineering: Affinity and biocompatibility of polymer fiber structures to chondrocytes (1996) J Biomed Mater Res, 33, p. 57; Vaccaro, A.R., Singh, K., Haid, R., Kitchel, S., Wuisman, P., Taylor, W., Branch, C., Garfin, S., The use of bioabsorbable implants in the spine (2003) Spine J, 3, p. 227; Jianqi, H., Hong, H., Lieping, S., Genghua, G., Comparison of calcium alginate film with collagen membrane for guided bone regeneration in mandibular defects in rabbits (2002) J Oral Maxillofac Surg, 60, p. 1449; Chan, C., Thompson, I., Robinson, P., Wilson, J., Hench, L., Evaluation of bioglass/dextran composite as a bone graft substitute (2002) Int J Oral Maxillofac Surg, 31, p. 73; Mukherjee, D.P., Tunkle, A.S., Roberts, R.A., Clavenna, A., Rogers, S., Smith, D., An animal evaluation of a paste of chitosan glutamate and hydroxyapatite as a synthetic bone graft material (2003) J Biomed Mater Res B Appl Biomater, 67 B, p. 603; Sashiwa, H., Aiba, S., Chemically modified chitin and chitosan as biomaterials (2004) Prog Polym Sci, 89, p. 887; Hoekstra, A., Struszczyk, H., Kivekas, O., Percutaneous microcrystalline chitosan application for sealing arterial puncture sites (1998) Biomaterials, 19, p. 1467; Lee, K.Y., Ha, W.S., Park, W.H., Blood compatibility and biodegradability of partially N-acylated chitosan derivatives (1995) Biomaterials, 16, p. 1211; Suh, J.K., Matthew, H.W., Application of chitosan-based polysaccharide biomaterials in cartilage tissue engineering: A review (2000) Biomaterials, 21, p. 2589; Hirano, S., Tsuchida, H., Nagao, N., N-acetylation in chitosan and the rate of its enzymic hydrolysis (1989) Biomaterials, 10, p. 574; Prashanth, K.V.H., Tharanathan, R.N., Chitin/chitosan: Modifications and their unlimited application potential-an overview (2007) Trends Food Sci Technol, 18, p. 117; Chellat, F., Tabrizian, M., Dumitriu, S., Chornet, E., Hilaire, C., Yahia, R., Study of biodegradation behavior of chitosan-xanthan microspheres in simulated physiological media (2000) J Biomed Mater Res, 53, p. 592; Lahiji, A., Sohrabi, A., Hungerford, D.S., Frondoza, C.G., Chitosan supports the expression of extracellular matrix proteins in human osteoblasts and chondrocytes (2000) J Biomed Mater Res, 51, p. 586; Nettles, D.L., Elder, S.H., Gilbert, J.A., Potential use of chitosan as a cell scaffold material for cartilage tissue engineering (2002) Tissue Eng, 8, p. 1009; Lu, J.X., Prudhommeaux, F., Meunier, A., Sedel, L., Guillemin, G., Effects of chitosan on rat knee cartilages (1999) Biomaterials, 20, p. 1937; Abe, M., Takahashi, M., Tokura, S., Tamura, H., Nagano, A., Cartilage-scaffold composites produced by bioresorbable beta-chitin sponge with cultured rabbit chondrocytes (2004) Tissue Eng, 10, p. 585; Sechriest, V.F., Miao, Y.J., Niyibizi, C., Westerhausen-Larson, A., Matthew, H.W., Evans, C.H., Fu, F.H., Suh, J.K., GAGaugmented polysaccharide hydrogel: A novel biocompatible and biodegradable material to support chondrogenesis (2000) J Biomed Mater Res, 49, p. 534; Rajpurohit, R., Koch, C.J., Tao, Z., Teixeira, C.M., Shapiro, I.M., Adaptation of chondrocytes to low oxygen tension: Relationship between hypoxia and cellular metabolism (1996) J Cell Physiol, 168, p. 424; Maes, C., Carmeliet, P., Moermans, K., Stockmans, I., Smets, N., Collen, D., Bouillon, R., Carmeliet, G., Impaired angiogenesis and endochondral bone formation in mice lacking the vascular endothelial growth factor isoforms VEGF164 and VEGF188 (2002) Mech Dev, 111, p. 61; Petersen, W., Tsokos, M., Pufe, T., Expression of VEGF121 and VEGF165 in hypertrophic chondrocytes of the human growth plate and epiphyseal cartilage (2002) J Anat, 201, p. 153; Pullig, O., Weseloh, G., Ronneberger, D., Kakonen, S., Swoboda, B., Chondrocyte differentiation in human osteoarthritis: Expression of osteocalcin in normal and osteoarthritic cartilage and bone (2000) Calcif Tissue Int, 67, p. 230; Hashimoto, S., Ochs, R.L., Rosen, F., Quach, J., McCabe, G., Solan, J., Seegmiller, J.E., Lotz, M., Chondrocyte-derived apoptotic bodies and calcification of articular cartilage (1998) Proc Natl Acad Sci USA, 95, p. 3094; Pullig, O., Weseloh, G., Gauer, S., Swoboda, B., Osteopontin is expressed by adult human osteoarthritic chondrocytes: Protein andmRNAanalysis of normal and osteoarthritic cartilage (2000) Matrix Biol, 19, p. 245; Eerola, I., Salminen, H., Lammi, P., Lammi, M., von der Mark, K., Vuorio, E., Saamanen, A.M., Type X collagen, a natural component of mouse articular cartilage: Association with growth, aging, and osteoarthritis (1998) Arthritis Rheum, 41, p. 1287; Amaral, I.F., Sampaio, P., Barbosa, M.A., Threedimensional culture of human osteoblastic cells in chitosan sponges: The effect of the degree of acetylation (2006) J Biomed Mater Res A, 76, p. 335; Mow, V.C., Kuei, S.C., Lai, W.M., Armstrong, C.G., Biphasic creep and stress relaxation of articular cartilage in compression? Theory and experiments (1980) J Biomech Eng, 102, p. 73; Iwamoto, M., Shapiro, I.M., Yagami, K., Boskey, A.L., Leboy, P.S., Adams, S.L., Pacifici, M., Retinoic acid induces rapid mineralization and expression of mineralizationrelated genes in chondrocytes (1993) Exp Cell Res, 207, p. 413; Teixeira, C.C., Hatori, M., Leboy, P.S., Pacifici, M., Shapiro, I.M., A rapid and ultrasensitive method for measurement of DNA, calcium and protein content, and alkaline phosphatase activity of chondrocyte cultures (1995) Calcif Tissue Int, 56, p. 252; Nehrer, S., Breinan, H.A., Ramappa, A., Young, G., Shortkroff, S., Louie, L.K., Sledge, C.B., Spector, M., Matrix collagen type and pore size influence behaviour of seeded canine chondrocytes (1997) Biomaterials, 18, p. 769; Karande, T.S., Ong, J.L., Agrawal, C.M., Diffusion in musculoskeletal tissue engineering scaffolds: Design issues related to porosity, permeability, architecture, and nutrient mixing (2004) Ann Biomed Eng, 32, p. 1728; VandeVord, P.J., Matthew, H.W., DeSilva, S.P., Mayton, L., Wu, B., Wooley, P.H., Evaluation of the biocompatibility of a chitosan scaffold in mice (2002) J Biomed Mater Res, 59, p. 585; Hong, Y., Song, H., Gong, Y., Mao, Z., Gao, C., Shen, J., Covalently crosslinked chitosan hydrogel: Properties of in vitro degradation and chondrocyte encapsulation (2007) Acta Biomater, 3, p. 23; Ho, M., Wang, D., Hsieh, H., Liu, H.C., Hsien, T.Y., Lai, J.Y., Hou, L.T., Preparation and characterization of RGDimmobilized chitosan scaffolds (2005) Biomaterials, 26, p. 3197; Amaral, I.F., Cordeiro, A.L., Sampaio, P., Barbosa, M.A., Attachment, spreading and short-term proliferation of human osteoblastic cells cultured on chitosan films with different degrees of acetylation (2007) J Biomater Sci Polym Ed, 18, p. 469; Hoemann, C.D., Sun, J., Legare, A., McKee, M.D., Buschmann, M.D., Tissue engineering of cartilage using an injectable and adhesive chitosan-based cell-delivery vehicle (2005) Osteoarthritis Cartilage, 13, p. 318; Griffon, D.J., Sedighi, M.R., Schaeffer, D.V., Eurell, J.A., Johnson, A.L., Chitosan scaffolds: Interconnective pore size and cartilage engineering (2006) Acta Biomater, 2, p. 313; Underhill, T.M., Weston, A.D., Retinoids and their receptors in skeletal development (1998) Microsc Res Tech, 43, p. 137; Cohen, A.J., Lassova, L., Golden, E.B., Niu, Z., Adams, S.L., Retinoids directly activate the collagen X promoter in prehypertrophic chondrocytes through a distal retinoic acid response element (2006) J Cell Biochem, 99, p. 269; Pacifici, M., Golden, E.B., Iwamoto, M., Adams, S.L., Retinoic acid treatment induces type X collagen gene expression in cultured chick chondrocytes (1991) Exp Cell Res, 195, p. 38; Gentili, C., Bianco, P., Neri, M., Malpeli, M., Campanile, G., Castagnola, P., Cancedda, R., Cancedda, F.D., Cellproliferation, extracellular-matrix mineralization, and ovotransferrin transient expression during in-vitro differentiation of chick hypertrophic chondrocytes into osteoblast-like cells (1993) J Cell Biol, 122, p. 703; Naumann, A., Dennis, J.E., Awadallah, A., Carrino, D.A., Mansour, J.M., Kastenbauer, E., Caplan, A.I., Immunochemical and mechanical characterization of cartilage subtypes in rabbit (2002) J Histochem Cytochem, 50, p. 1049; Wang, W., Kirsch, T., Retinoic acid stimulates annexinmediated growth plate chondrocyte mineralization (2002) J Cell Biol, 157, p. 1061; Whyte, M.P., Hypophosphatasia and the role of alkaline phosphatase in skeletal mineralization (1994) Endocr Rev, 15, p. 439; Lewinson, D., Toister, Z., Silbermann, M., Quantitative and distributional changes in the activity of alkaline phosphatase during the maturation of cartilage (1982) J Histochem Cytochem, 30, p. 261; Amaral, I.F., Sampaio, P., Barbosa, M.A., Threedimensional culture of human osteoblastic cells in chitosan sponges: The effect of the degree of acetylation (2005) J Biomed Mater Res A, 76, p. 335; Park, J.H., Park, B.H., Kim, H.K., Park, T.S., Baek, H.S., Hypoxia decreases Runx2/Cbfa1 expression in human osteoblast-like cells (2002) Mol Cell Endocrinol, 192, p. 197; Utting, J.C., Robins, S.P., Brandao-Burch, A., Orriss, I.R., Behar, J., Arnett, T.R., Hypoxia inhibits the growth, differentiation and bone-forming capacity of rat osteoblasts (2006) Exp Cell Res, 312, p. 1693; Warren, S.M., Steinbrech, D.S., Mehrara, B.J., Saadeh, P.B., Greenwald, J.A., Spector, J.A., Bouletreau, P.J., Longaker, M.T., Hypoxia regulates osteoblast gene expression (2001) J Surg Res, 99, p. 147; Salim, A., Nacamuli, R.P., Morgan, E.F., Giaccia, A.J., Longaker, M.T., Transient changes in oxygen tension inhibit osteogenic differentiation and Runx2 expression in osteoblasts (2004) J Biol Chem, 279, p. 40007; Vu, T.H., Shipley, J.M., Bergers, G., Berger, J.E., Helms, J.A., Hanahan, D., Shapiro, S.D., Werb, Z., MMP-9/gelatinase B is a key regulator of growth plate angiogenesis and apoptosis of hypertrophic chondrocytes (1998) Cell, 93, p. 411; Skawina, A., Litwin, J.A., Gorczyca, J., Miodonski, A.J., The vascular system of human fetal long bones: A scanning electron microscope study of corrosion casts (1994) J Anat, 185, p. 369; Pfander, D., Cramer, T., Schipani, E., Johnson, R.S., HIF-1alpha controls extracellular matrix synthesis by epiphyseal chondrocytes (2003) J Cell Sci, 116, p. 1819; Deckers, M.M., Karperien, M., van der Bent, C., Yamashita, T., Papapoulos, S.E., Lowik, C.W., Expression of vascular endothelial growth factors and their receptors during osteoblast differentiation (2000) Endocrinology, 141, p. 1667; Gerber, H.P., Vu, T.H., Ryan, A.M., Kowalski, J., Werb, Z., Ferrara, N., VEGF couples hypertrophic cartilage remodeling, ossification and angiogenesis during endochondral bone formation (1999) Nat Med, 5, p. 623; Nakagawa, M., Kaneda, T., Arakawa, T., Morita, S., Sato, T., Yomada, T., Hanada, K., Hakeda, Y., Vascular endothelial growth factor (VEGF) directly enhances osteoclastic bone resorption and survival of mature osteoclasts (2000) FEBS Lett, 473, p. 161; Pfander, D., Kortje, D., Zimmermann, R., Weseloh, G., Kirsch, T., Gesslein, M., Cramer, T., Swoboda, B., Vascular endothelial growth factor in articular cartilage of healthy and osteoarthritic human knee joints (2001) Ann RheumDis, 60, p. 1070; Oliveira, S.M., Turner, G., Mijares, D., Amaral, I.F., Barbosa, M.A., Teixeira, C.C., (2007) Engineering endochondral bone: In vivo studies
Keywords: alkaline phosphatase; Alkaline phosphatase activity; animal; animal cell; animal tissue; Animals; article; biomechanics; Body fluids; Bone; Bone and Bones; Bone formation; Cartilage; cartilage cell; Cell culture; cell damage; cell hypertrophy; cell isolation; cell maturation; Cell membranes; cell proliferation; Cells, Cultured; chick embryo; Chicken embryo; Chitin; chitosan; Chitosan scaffold; Chondrocyte; Chondrocyte maturation; Chondrocytes; Clinical application; collagen type 10; Collagen Type X; controlled study; cytology; DNA; drug effect; embryo; enchondral ossification; Endochondral ossification; enzyme activity; enzymology; Extracellular matrices; extracellular matrix; gene expression profiling; Hypertrophic chondrocytes; in vitro study; In-vitro; Ligaments; Matrix synthesis; Mechanical analysis; Mechanical properties; metabolism; methodology; nonhuman; Pathology; physiology; Porifera; porosity; priority journal; retinoic acid; Retinoic acids; Scaffolds; sponge (Porifera); Sterna; sternum; synthesis; Time points; Tissue engineering; tissue scaffold; Tissue Scaffolds; Tretinoin; Type X collagen

Engineering endochondral bone: In vivo studies - Oliveira, S.M.; Mijares, D.Q.; Turner, G.; Amaral, I.F.; Barbosa, M.A.; Teixeira, C.C. (Tissue Engineering - Part ATissue Eng. Part A, 2009)
The use of biomaterials to replace lost bone has been a common practice for decades. More recently, the demands for bone repair and regeneration have pushed research into the use of cultured cells and growth factors in association with these materials. Here we report a novel approach to engineer new bone using a transient cartilage scaffold to induce endochondral ossification. Chondrocyte/chitosan scaffolds (both a transient cartilage scaffold- experimental-and a permanent cartilage scaffold-control) were prepared and implanted subcutaneously in nude mice. Bone formation was evaluated over a period of 5 months. Mineralization was assessed by Faxitron, micro computed tomography, backscatter electrons, and Fourier transform infrared spectroscopy analyses. Histological analysis provided further information on tissue changes in and around the implanted scaffolds. The deposition of ectopic bone was detected in the surface of the experimental implants as early as 1 month after implantation. After 3 months, bone trabeculae and bone marrow cavities were formed inside the scaffolds. The bone deposited was similar to the bone of the mice vertebra. Interestingly, no bone formation was observed in control implants. In conclusion, an engineered transient cartilage template carries all the signals necessary to induce endochondral bone formation in vivo. © Copyright 2009, Mary Ann Liebert, Inc. 2009.
Cited By (since 1996): 14Export Date: 21 November 2012Source: Scopusdoi: 10.1089/ten.tea.2008.0052Language of Original Document: EnglishCorrespondence Address: Teixeira, C. C.; Department of Basic Science and Craniofacial Biology, College of Dentistry, New York University, 345 East. 24th St., New York, NY 10010; email: ct40@nyu.eduChemicals/CAS: chitosan, 9012-76-4; Chitosan, 9012-76-4; MineralsReferences: Yelin, E., Callahan, L.F., The economic cost and social and psychological impact of musculoskeletal conditions. National Arthritis Data Work Groups (1995) Arthritis Rheum, 38, p. 1351;Service, R.F. Tissue engineers build new bone. Science 289,1498, 2000Dupraz, A., Delecrin, J., Moreau, A., Pilet, P., Passuti, N., Long-term bone response to particulate injectable ceramic (1998) J Biomed Mater Res, 42, p. 368; Gauthier, O., Khairoun, I., Bosco, J., Obadia, L., Bourges, X., Rau, C., Magne, D., Daculsi, G., Noninvasive bone replacement with a new injectable calcium phosphate biomaterial (2003) J Biomed Mater Res, 66 A, p. 47; Maroudas, A., Bayliss, M.T., Uchitel-Kaushansky, N., Schneiderman, R., Gilav, E., Aggrecan turnover in human articular cartilage: Use of aspartic acid racemization as a marker of molecular age (1998) Arch Biochem Biophys, 350, p. 61; Ferguson, C., Alpern, E., Miclau, T., Helms, J.A., Does adult fracture repair recapitulate embryonic skeletal formation? (1999) Mech Dev, 87, p. 57; Iwamoto, M., Higuchi, Y., Enomoto-Iwamoto, M., Kurisu, K., Koyama, E., Yeh, H., Rosenbloom, J., Pacifici, M., The role of ERG (ets related gene) in cartilage development (2001) Osteoarthr Cartil, 9 (SUPPL. A), pp. S41; Montufar-Solis, D., Nguyen, H.C., Nguyen, H.D., Horn, W.N., Cody, D.D., Duke, P.J., Using cartilage to repair bone: An alternative approach in tissue engineering (2004) Ann Biomed Eng, 32, p. 504; Pountos, I., Jones, E., Tzioupis, C., McGonagle, D., Giannoudis, P.V., Growing bone and cartilage: The role of mesenchymal stem cells (2006) J Bone Joint Surg Br, 88, p. 421; Valimaki, V.V., Yrjans, J.J., Vuorio, E.I., Aro, H.T., Molecular biological evaluation of bioactive glass microspheres and adjunct bone morphogenetic protein 2 gene transfer in the enhancement of new bone formation (2005) Tissue Eng, 11, p. 387; Huang, Y.C., Simmons, C., Kaigler, D., Rice, K.G., Mooney, D.J., Bone regeneration in a rat cranial defect with delivery of PEI-condensed plasmid DNA encoding for bone morphogenetic protein-4 (BMP-4) (2005) Gene Ther, 12, p. 418; Bikram, M., Fouletier-Dilling, C., Hipp, J.A., Gannon, F., Davis, A.R., Olmsted-Davis, E.A., West, J.L., Endochondral bone formation from hydrogel carriers loaded with BMP2-transduced cells (2007) Ann Biomed Eng, 35, p. 796; Alsberg, E., Anderson, K.W., Albeiruti, A., Rowley, J.A., Mooney, D.J., Engineering growing tissues (2002) Proc Natl Acad Sci USA, 99, p. 12025; Deckers, M.M., Karperien, M., van der Bent, C., Yamashita, T., Papapoulos, S.E., Lowik, C.W., Expression of vascular endothelial growth factors and their receptors during osteoblast differentiation (2000) Endocrinology, 141, p. 1667; Petersen, W., Tsokos, M., Pufe, T., Expression of VEGF121 and VEGF165 in hypertrophic chondrocytes of the human growth plate and epiphyseal cartilage (2002) J Anat, 201, p. 153; Nakagawa, M., Kaneda, T., Arakawa, T., Morita, S., Sato, T., Yomada, T., Hanada, K., Hakeda, Y., Vascular endothelial growth factor (VEGF) directly enhances osteoclastic bone resorption and survival of mature osteoclasts (2000) FEBS Lett, 473, p. 161; Gerber, H.P., Vu, T.H., Ryan, A.M., Kowalski, J., Werb, Z., Ferrara, N., VEGF couples hypertrophic cartilage remodeling, ossification and angiogenesis during endochondral bone formation (1999) Nat Med, 5, p. 623; Oliveira, S.M., Amaral, I.F., Barbosa, M.A., Teixeira, C.C., (2007) Engineering endochondral bone: In vitro studies; Hasegawa, S., Ishii, S., Tamura, J., Furukawa, T., Neo, M., Matsusue, Y., Shikinami, Y., Nakamura, T., A 5-7 year in vivo study of high-strength hydroxyapatite/ poly(L-lactide) composite rods for the internal fixation of bone fractures (2006) Biomaterials, 27, p. 1327; Gauthier, O., Muller, R., von Stechow, D., Lamy, B., Weiss, P., Bouler, J.M., Aguado, E., Daculsi, G., In vivo bone regeneration with injectable calcium phosphate biomaterial: A three-dimensional micro-computed tomographic, biomechanical and SEM study (2005) Biomaterials, 26, p. 5444; Chan, C., Thompson, I., Robinson, P., Wilson, J., Hench, L., Evaluation of Bioglass/dextran composite as a bone graft substitute (2002) Int J Oral Maxillofac Surg, 31, p. 73; Trojani, C., Boukhechba, F., Scimeca, J.C., Vandenbos, F., Michiels, J.F., Daculsi, G., Boileau, P., Rochet, N., Ectopic bone formation using an injectable biphasic calcium phosphate/Si-HPMC hydrogel composite loaded with undifferentiated bone marrow stromal cells (2006) Biomaterials, 27, p. 3256; van Gaalen, S.M., Dhert, W.J.A., van den Muysenberg, A., Oner, F.C., van Blitterswijk, C., Verbout, A.J., de Bruijn, J.D., Bone tissue engineering for spine fusion: An experimental study on ectopic and orthotopic implants in rats (2004) Tissue Eng, 10, p. 231; Kim, H., Suh, H., Jo, S.A., Kim, H.W., Lee, J.M., Kim, E.H., Reinwald, Y., Jo, I., In vivo bone formation by human marrow stromal cells in biodegradable scaffolds that release dexamethasone and ascorbate-2-phosphate (2005) Biochem Biophys Res Commun, 332, p. 1053; Krebsbach, P.H., Kuznetsov, S.A., Satomura, K., Emmons, R.V.B., Rowe, D.W., Robey, P.G., Bone formation in vivo: Comparison of osteogenesis by transplanted mouse and human marrow stromal fibroblasts (1997) Transplantation, 63, p. 1059; Musgrave, D.S., Bosch, P., Lee, J.Y., Pelinkovic, D., Ghivizzani, S.C., Whalen, J., Niyibizi, C., Huard, J., Ex vivogene therapy to produce bone using different cell types (2000) Clin Orthop Relat Res, 378, p. 290; Kojima, K., Bonassar, L.J., Ignotz, R.A., Syed, K., Cortiella, J., Vacanti, C.A., Comparison of tracheal and nasal chondrocytes for tissue engineering of the trachea (2003) Ann Thorac Surg, 76, p. 1884; van Susante, J.L., Buma, P., Homminga, G.N., van den Berg, W.B., Veth, R.P., Chondrocyte-seeded hydroxyapatite for repair of large articular cartilage defects: A pilot study in the goat (1998) Biomaterials, 19, p. 2367; Lu, J.X., Prudhommeaux, F., Meunier, A., Sedel, L., Guillemin, G., Effects of chitosan on rat knee cartilages (1999) Biomaterials, 20, p. 1937; Dorotka, R., Windberger, U., Macfelda, K., Bindreiter, U., Toma, C., Nehrer, S., Repair of articular cartilage defects treated by microfracture and a three-dimensional collagen matrix (2005) Biomaterials, 26, p. 3617; Marijnissen, W.J.C.M., van Osch, G.J.V.M., Aigner, J., Verwoerd-Verhoef, H.L., Verhaar, J.A.N., Tissueengineered cartilage using serially passaged articular chondrocytes. Chondrocytes in alginate, combined in vivo with a synthetic (E210) or biologic biodegradable carrier (DBM) (2000) Biomaterials, 21, p. 571; Case, N.D., Duty, A.O., Ratcliffe, A., Muller, R., Guldberg, R.E., Bone formation on tissue-engineered cartilage constructs in vivo: Effects of chondrocyte viability and mechanical loading (2003) Tissue Eng, 9, p. 587; Cancedda, R., Cancedda, F.D., Castagnola, P., Chondrocyte differentiation (1995) Int Rev Cytol, 159, p. 265; Hunziker, E.B., Mechanism of longitudinal bone-growth and its regulation by growth-plate chondrocytes (1994) Microsc Res Tech, 28, p. 505; Kirsch, T., Nah, H.D., Shapiro, I.M., Pacifici, M., Regulated production of mineralization-competent matrix vesicles in hypertrophic chondrocytes (1997) J Cell Biol, 137, p. 1149; Anderson, H.C., Molecular-biology of matrix vesicles (1995) Clin Orthop Relat Res, 314, p. 266; Yaylaoglu, M.B., Yildiz, C., Korkusuz, F., Hasirci, V., A novel osteochondral implant (1999) Biomaterials, 20, p. 1513; Garimella, R., Bi, X.H., Camacho, N., Sipe, J.B., Anderson, H.C., Primary culture of rat growth plate chondrocytes: An in vitro model of growth plate histotype, matrix vesicle biogenesis and mineralization (2004) Bone, 34, p. 961; Boskey, A., Camacho, N.P., FT-IR imaging of native and tissue-engineered bone and cartilage (2007) Biomaterials, 28, p. 2465; Jikko, A., Aoba, T., Murakami, H., Takano, Y., Iwamoto, M., Kato, Y., Characterization of the mineralization process in cultures of rabbit growth plate chondrocytes (1993) Dev Biol, 156, p. 372; Cadet, E.R., Gafni, R.I., McCarthy, E.F., McCray, D.R., Bacher, J.D., Barnes, K.M., Baron, J., Mechanisms responsible for longitudinal growth of the cortex: Coalescence of trabecular bone into cortical bone (2003) J Bone Joint Surg Am, 85 A, p. 1739; Lee, C., Grad, S., Wimmer, M., Alini, M., The influence of mechanical stimuli on articular cartilage tissue engineering (2006) Cartilage Tissue Eng, 2, p. 1; Trepczik, B., Lienau, J., Schell, H., Epari, D.R., Thompson, M.S., Hoffmann, J.E., Kadow-Romacker, A., Duda, G.N., Endochondral ossification in vitro is influenced by mechanical bending (2007) Bone, 40, p. 597; Tanck, E., Hannink, G., Ruimerman, R., Buma, P., Burger, E.H., Huiskes, R., Cortical bone development under the growth plate is regulated by mechanical load transfer (2006) J Anat, 208, p. 73; Dong, J., Uemura, T., Kojima, H., Kikuchi, M., Tanaka, J., Tateishi, T., Application of low-pressure system to sustain in vivo bone formation in osteoblast/porous hydroxyapatite composite (2001) DNLM, 17, p. 37; Stevens, M., Marini, R., Schaefer, D., Aronson, J., Langer, R., Shastri, V., In vivo engineering of organs: The bone bioreactor (2005) Proc Natl Acad Sci USA, 102, p. 11450; Rinaudo, M., Chitin and chitosan: Properties and applications (2006) Prog Polym Sci, 31, p. 603
Keywords: animal; animal experiment; animal tissue; Animals; article; Biological materials; Biomaterials; Bone; Bone and Bones; Bone formation; bone marrow; bone mineralization; Bone repair; bone transplantation; Calcification, Physiologic; Cartilage; cartilage cell; chick embryo; chitosan; Chondrocytes; Computerized tomography; controlled study; Cultured cell; cytology; drug effect; Ectopic bones; ectopic tissue; electron; enchondral ossification; Endochondral ossification; Fourier transform infrared spectroscopy; Growth (materials); Growth factor; Histological analysis; histology; implantation; in vivo study; In-control; In-vivo; infrared spectroscopy; Ligaments; male; metabolism; methodology; Mice; Mice, Nude; micro-computed tomography; Microcomputed tomography; Microscopy, Electron, Scanning; mineral; Minerals; mouse; Mus; Mus musculus; nonhuman; Nude mice; nude mouse; ossification; physiology; priority journal; Prosthesis Implantation; Scaffolds; Scanning electron microscopy; Spectroscopic analysis; Spectroscopy; Spectroscopy, Fourier Transform Infrared; Tissue changes; Tissue engineering; tissue scaffold; Tissue Scaffolds; Tomography; trabecular bone; vertebra

Fibronectin-mediated endothelialisation of chitosan porous matrices - Amaral, I.F.; Unger, R.E.; Fuchs, S.; Mendonça, A.M.; Sousa, S.R.; Barbosa, M.A.; Pêgo, A.P.; Kirkpatrick, C.J. (BiomaterialsBiomaterials, 2009)
Chitosan (Ch) porous matrices were investigated regarding their ability to be colonized by human microvascular endothelial cells (HPMEC-ST1.6R cell line) and macrovascular endothelial cells namely HUVECs. Specifically we assessed if previous incubation of Ch in a fibronectin (FN) solution was effective in promoting endothelial cell (EC) adhesion to Ch matrices with different degrees of acetylation (DAs). Upon FN physiadsorption, marked differences were found between the two DAs investigated, namely DA 4% and 15%. While cell adhesion was impaired on Ch with DA 15%, ECs were able to not only adhere to Ch with DA 4%, but also to spread and colonize the scaffolds, with retention of the EC phenotype and angiogenic potential. To explain the observed differences between the two DAs, protein adsorption studies using 125I-FN and immunofluorescent labelling of FN cell-binding domains were carried out. In agreement with the higher cell numbers found, scaffolds with DA 4% revealed a higher number of exposed FN cell-binding domains as well as greater ability to adsorb FN and to retain and exchange adsorbed FN in the presence of competitive proteins. These findings suggest that the DA is a key parameter modulating EC adhesion to FN-coated Ch by influencing the adsorbed protein layer. © 2009 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2009.06.056PubMed ID: 19615736Language of Original Document: EnglishCorrespondence Address: Amaral, I.F.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: iamaral@ineb.up.ptChemicals/CAS: chitosan, 9012-76-4; fibronectin, 86088-83-7; Biocompatible Materials; Chitosan, 9012-76-4; FibronectinsReferences: Moon, J.J., West, J.L., Vascularization of engineered tissues: approaches to promote angiogenesis in biomaterials (2008) Current Topics in Medicinal Chemistry, 8 (4), pp. 300-310;Blitterswijk, C.A., Moroni, L., Rouwkema, J., Siddappa, R., Sohier, J., Tissue engineering - an introduction (2008) Tissue engineering, , Blitterswijk C.A. (Ed), Elsevier; Ehrbar, M., Zeisberger, S.M., Raeber, G.P., Hubbell, J.A., Schnell, C., Zisch, A.H., The role of actively released fibrin-conjugated VEGF for VEGF receptor 2 gene activation and the enhancement of angiogenesis (2008) Biomaterials, 29 (11), pp. 1720-1729; Elbjeirami, W.M., West, J.L., Angiogenesis-like activity of endothelial cells co-cultured with VEGF-producing smooth muscle cells (2006) Tissue Engineering, 12 (2), pp. 381-390; Unger, R.E., Peters, K., Wolf, M., Motta, A., Migliaresi, C., Kirkpatrick, C.J., Endothelialization of a non-woven silk fibroin net for use in tissue engineering: growth and gene regulation of hunian endothelial cells (2004) Biomaterials, 25 (21), pp. 5137-5146; Fuchs, S., Motta, A., Migliaresi, C., Kirkpatrick, C.J., Outgrowth endothelial cells isolated and expanded from human peripheral blood progenitor cells as a potential source of autologous cells for endothelialization of silk fibroin biomaterials (2006) Biomaterials, 27 (31), pp. 5399-5408; Kirkpatrick, C.J., Unger, R.E., Krump-Konvalinkova, V., Peters, K., Schmidt, H., Kamp, G., Experimental approaches to study vascularization in tissue engineering and biomaterial applications (2003) Journal of Materials Science, 14 (8), pp. 677-681; Calonder, C., Matthew, H.W.T., Van Tassel, P.R., Adsorbed layers of oriented fibronectin: a strategy to control cell-surface interactions (2005) Journal of Biomedical Materials Research Part A, 75 A (2), pp. 316-323; Kouvroukoglou, S., Dee, K.C., Bizios, R., McIntire, L.V., Zygourakis, K., Endothelial cell migration on surfaces modified with immobilized adhesive peptides (2000) Biomaterials, 21 (17), pp. 1725-1733; Burdick, J.A., Khademhosseini, A., Langer, R., Fabrication of gradient hydrogels using a microfluidics/photopolymerization process (2004) Langmuir, 20 (13), pp. 5153-5156; Garcia, A.J., Get a grip: integrins in cell-biomaterial interactions (2005) Biomaterials, 26, pp. 7525-7529; Tomihata, K., Ikada, Y., In vitro and in vivo degradation of films of chitin and its deacetylated derivatives (1997) Biomaterials, 18 (7), pp. 567-575; Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., Rat bone marrow stromal cells osteogenic differentiation and fibronectin adsorption on chitosan membranes: the effect of the degree of acetylation (2005) Journal of Biomedical Materials Research Part A, 75 A (2), pp. 387-397; Nettles, D.L., Elder, S.H., Gilbert, J.A., Potential use of chitosan as a cell scaffold material for cartilage tissue engineering (2002) Tissue Engineering, 8 (6), pp. 1009-1016; Oliveira, S.M., Amaral, I.F., Barbosa, M.A., Teixeira, C.C., Engineering endochondral bone: in vitro studies (2009) Tissue Engineering, 15 (3), pp. 625-634; Freier, T., Koh, H.S., Kazazian, K., Shoichet, M.S., Controlling cell adhesion and degradation of chitosan films by N-acetylation (2005) Biomaterials, 26 (29), pp. 5872-5878; Wang, X.H., Cui, F.Z., Feng, Q.L., Li, J.C., Zhang, Y.H., Preparation and characterization of collagen/chitosan matrices as potential biomaterials (2003) Journal of Bioactive and Compatible Polymers, 18 (6), pp. 453-467; Chupa, J.M., Foster, A.M., Sumner, S.R., Madihally, S.V., Matthew, H.W.T., Vascular cell responses to polysaccharide materials: in vitro and in vivo evaluations (2000) Biomaterials, 21 (22), pp. 2315-2322; Chung, T.W., Lu, Y.F., Wang, S.S., Lin, Y.S., Chu, S.H., Growth of human endothelial cells on photochemically grafted Gly-Arg-Gly-Asp (GRGD) chitosans (2002) Biomaterials, 23 (24), pp. 4803-4809; Cuy, J.L., Beckstead, B.L., Brown, C.D., Hoffman, A.S., Giachelli, C.M., Adhesive protein interactions with chitosan: consequences for valve endothelial cell growth on tissue-engineering materials (2003) Journal of Biomedical Materials Research Part A, 67 A (2), pp. 538-547; Huang, Y., Onyeri, S., Siewe, M., Moshfeghian, A., Madihally, S.V., In vitro characterization of chitosan-gelatin scaffolds for tissue engineering (2005) Biomaterials, 26 (36), pp. 7616-7627; Huang, Y., Siewe, M., Madilhally, S.V., Effect of spatial architecture on cellular colonization (2006) Biotechnology and Bioengineering, 93 (1), pp. 64-75; Kirsebom, H., Aguilar, M.R., Roman, J.S., Fernandez, M., Prieto, M.A., Bondar, B., Macroporous scaffolds based on chitosan and bioactive molecules (2007) Journal of Bioactive and Compatible Polymers, 22 (6), pp. 621-636; Cao, W.L., Jing, D.H., Li, J.M., Gong, Y.D., Zhao, N.M., Zhang, X.F., Effects of the degree of deacetylation on the physicochemical properties and Schwann cell affinity of chitosan films (2005) Journal of Biomaterials Applications, 20 (2), pp. 157-177; Amaral, I.F., Sampaio, P., Barbosa, M.A., Three-dimensional culture of human osteoblastic cells in chitosan sponges: the effect of the degree of acetylation (2006) Journal of Biomedical Materials Research Part A, 76 A (2), pp. 335-346; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42 (8), pp. 3569-3580; Vachoud, L., Zydowicz, N., Domard, A., Formation and characterisation of a physical chitin gel (1997) Carbohydrate Research, 302 (3-4), pp. 169-177; Montembault, A., Viton, C., Domard, A., Physico-chemical studies of the gelation of chitosan in a hydroalcoholic medium (2005) Biomaterials, 26 (8), pp. 933-943; Amaral, I.F., Cordeiro, A.L., Sampaio, P., Barbosa, M.A., Attachment, spreading and short-term proliferation of human osteoblastic cells cultured on chitosan films with different degrees of acetylation (2007) Journal of Biomaterials Science Polymer Edition, 18 (4), pp. 469-485; Krump-Konvalinkova, V., Bittinger, F., Unger, R.E., Peters, K., Lehr, H.A., Kirkpatrick, C.J., Generation of human pulmonary microvascular endothelial cell lines (2001) Laboratory Investigation, 81 (12), pp. 1717-1727; Unger, R.E., Krump-Konvalinkova, V., Peters, K., Kirkpatrick, C.J., In vitro expression of the endothelial phenotype: comparative study of primary isolated cells and cell lines, including the novel cell line HPMEC-ST1.6R (2002) Microvascular Research, 64 (3), pp. 384-397; Jaffe, E.A., Nachman, R.L., Becker, C.G., Minick, C.R., Culture of human endothelial cells derived from umbilical veins. Identification by morphologic and immunologic criteria (1973) J Clin Invest, 52 (11), pp. 2745-2756; O'Brien, J., Wilson, I., Orton, T., Pognan, F., Investigation of the Alamar blue (resazurin) fluorescent dye for the assessment of mammalian cell cytotoxicity (2000) European Journal of Biochemistry, 267 (17), pp. 5421-5426; Teixeira, C.C., Hatori, M., Leboy, P.S., Pacifici, M., Shapiro, I.M., A rapid and ultrasensitive method for measurement of DNA, calcium and protein-content, and alkaline-phosphatase activity of chondrocyte cultures (1995) Calcified Tissue International, 56 (3), pp. 252-256; Barbosa, J.N., Amaral, I.F., Águas, A.P., Barbosa, M.A., Evaluation of the effect of the degree of acetylation on the inflammatory response to 3D porous chitosan scaffolds Journal of Biomedical Materials Research Part A, , in press, doi:10.1002/jbm.a.32499; Marshall, A.J., Barker, T., Sage, E.H., Hauch, K.D., Ratner, B.D., (2004) Pore size controls angiogenesis in subcutaneously implanted porous matrices. 7th World Biomaterials Congress; 2004, , Australian Society for Biomaterials Inc., Sydney, Australia p. 710; Unger, R.E., Sartoris, A., Peters, K., Motta, A., Migliaresi, C., Kunkel, M., Tissue-like self-assembly in cocultures of endothelial cells and osteoblasts and the formation of microcapillary-like structures on three-dimensional porous biomaterials (2007) Biomaterials, 28 (27), pp. 3965-3976; Tidwell, C.D., Ertel, S.I., Ratner, B.D., Tarasevich, B.J., Atre, S., Allara, D.L., Endothelial cell growth and protein adsorption on terminally functionalized, self-assembled monolayers of alkanethiolates on gold (1997) Langmuir, 13 (13), pp. 3404-3413; Wendt, D., Marsano, A., Jakob, M., Heberer, M., Martin, I., Oscillating perfusion of cell suspensions through three-dimensional scaffolds enhances cell seeding efficiency and uniformity (2003) Biotechnology and Bioengineering, 84 (2), pp. 205-214; Santos, M.I., Fuchs, S., Gomes, M.E., Unger, R.E., Reis, R.L., Kirkpatrick, C.J., Response of micro- and macrovascular endothelial cells to starch-based fiber meshes for bone tissue engineering (2007) Biomaterials, 28 (2), pp. 240-248; Vestweber, D., Molecular mechanisms that control endothelial cell contacts (2000) Journal of Pathology, 190 (3), pp. 281-291; Mori, T., Irie, Y., Nishimura, S., Tokura, S., Matsuura, M., Okumura, M., Endothelial cell responses to chitin and its derivatives (1998) Journal of Biomedical Materials Research, 43 (4), pp. 469-472; Panetti, T.S., Hannah, D.F., Avraamides, C., Gaughan, J.P., Marcinkiewicz, Z., Huttenlocher, A., Extracellular matrix molecules regulate endothelial cell migration stimulated by lysophosphatidic acid (2004) Journal of Thrombosis and Haemostasis, 2 (9), pp. 1645-1656; Garcia, A.J., Boettiger, D., Integrin-fibronectin interactions at the cell-material interface: initial integrin binding and signaling (1999) Biomaterials, 20 (23-24), pp. 2427-2433; Danen, E.H.J., Sonnenberg, A., Integrins in regulation of tissue development and function (2003) Journal of Pathology, 200 (4), pp. 471-480; Keselowsky, B.G., Collard, D.M., Garcia, A.J., Surface chemistry modulates fibronectin conformation and directs integrin binding and specificity to control cell adhesion (2003) Journal of Biomedical Materials Research Part A, 66 A (2), pp. 247-259; Renner, L., Jorgensen, B., Markowski, M., Salchert, K., Werner, C., Pompe, T., Control of fibronectin displacement on polymer substrates to influence endothelial cell behaviour (2004) Journal of Materials Science-Materials in Medicine, 15 (4), pp. 387-390; Garcia, A.J., Vega, M.D., Boettiger, D., Modulation of cell proliferation and differentiation through substrate-dependent changes in fibronectin conformation (1999) Molecular Biology of the Cell, 10 (3), pp. 785-798; Koenig, A.L., Gambillara, V., Grainger, D.W., Correlating fibronectin adsorption with endothelial cell adhesion and signaling on polymer substrates (2003) Journal of Biomedical Materials Research Part A, 64 A (1), pp. 20-37; Keselowsky, B.G., Collard, D.M., Garcia, A.J., Surface chemistry modulates focal adhesion composition and signaling through changes in integrin binding (2004) Biomaterials, 25, pp. 5947-5954; Pompe, T., Kobe, F., Salchert, K., Jorgensen, B., Oswald, J., Werner, C., Fibronectin anchorage to polymer substrates controls the initial phase of endothelial cell adhesion (2003) Journal of Biomedical Materials Research Part A, 67 A (2), pp. 647-657
Keywords: Acetylation; Adhesion; Adsorption; angiogenesis; article; Biocompatible Materials; Blood vessel prostheses; cell adhesion; Cell culture; cell invasion; Cell Line; Cell lines; Cell membranes; Cell number; cell proliferation; Cell size; cell spreading; cell survival; Cell-binding domain; Chitin; Chitin/chitosan; chitosan; colony formation; controlled study; Degrees of acetylation; Electric conductivity measurement; Electric currents; Endothelial cell; Endothelial Cells; Endothelialisation; endothelium; endothelium cell; epithelization; Fibronectin; Fibronectins; human; human cell; Human microvascular endothelial cells; Humans; immunofluorescence test; Key parameters; Labels; materials testing; Matrix algebra; Neovascularization, Physiologic; phenotype; porosity; Porous matrixs; priority journal; Protein adsorption; Protein layers; Scaffold; Scaffolds; Self assembly; Tissue engineering; tissue scaffold; umbilical vein

Induction of notch signaling by immobilization of jagged-1 on self-assembled monolayers - Gonçalves, R.M.; Martins, M.C.L.; Almeida-Porada, G.; Barbosa, M.A. (BiomaterialsBiomaterials, 2009)
Notch signaling is a key mechanism during mammal development and stem cell regulation. This study aims to target and control Notch signaling by ligands immobilization using self-assembled monolayers (SAMs) as model surfaces. Non-fouling substrates were prepared by immersion of gold substrates in (1-Mercapto-11-undecyl)tetra(ethylene glycol) thiol solutions. These surfaces were activated with N,N′-carbonyldiimidazole (CDI) at different concentrations (0, 0.03, 0.3, 3 and 30 mg/ml) and an anti-human IgG, Fc specific fragment antibody (Ab) was covalently bound to EG4-SAMs to guarantee the correct exposure of the Notch ligand Jagged-1/Fc chimera (Jag-1). The presence of Ab and Jag-1 was confirmed by radiolabeling, X-ray photoelectron spectroscopy (XPS), ellipsometry and ELISA. The biological activity of Jag-1-Ab-SAMs was assessed by real-time PCR for Hes-1 family gene expression, a Notch pathway target gene, in HL-60 cell line. Results have shown an increase of the amount of immobilized Ab with increasing surface activator concentrations. Jag-1 concentration also increases with Ab concentration. Interestingly, a higher Jagged-1 exposure and fold increase in Hes-1 expression were obtained for surfaces activated with the lowest concentration of CDI (0.03 mg/ml). These results illustrate the great importance of ligands orientation and exposure, when compared with density. This investigation brings new insights into Notch signaling mechanisms. In particular, Jag-1-Ab-SAMs have shown to be adequate model surfaces to study Notch pathway activation and may provide a basis to develop new interfaces in biomaterials to control Notch mechanism in different cell systems. © 2009 Elsevier Ltd.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2009.09.010PubMed ID: 19783294Language of Original Document: EnglishCorrespondence Address: Gonçalves, R.M.; INEB, Biomaterials Division, NEWTherapies Group, R. Campo Alegre, 823, 4150-180 Porto, Portugal; email: raquelg@ineb.up.ptChemicals/CAS: Calcium-Binding Proteins; Gold, 7440-57-5; Immunoglobulin G; Intercellular Signaling Peptides and Proteins; Membrane Proteins; Receptors, Fc; Receptors, Notch; Recombinant Fusion Proteins; Serrate proteins, 134324-36-0References: Artavanis-Tsakonas, S., Rand, M.D., Lake, R.J., Notch signaling: cell fate control and signal integration in development (1999) Science, 284, pp. 770-776;Leong, K., Karsan, A., Recent insights in the role of notch signaling in tumorigenesis (2006) Blood, 107 (6), pp. 2223-2233; Chiba, S., Concise review: notch signaling in stem cell systems (2006) Stem Cells, 24, pp. 2437-2447; Lowell, S., Benchoua, A., Heavey, B., Smith, A.G., Notch promotes neural lineage entry by pluripotent embryonic stem cells (2006) PLoS Biol, 4 (5); Hellström, M.P.L., Hofmann, J.J., Wallgard, E., Coultas, L., Lindblom, P., Alva, J., Dll4 signalling through notch1 regulates formation of tip cells during angiogenesis (2007) Nature, 15 (445), pp. 776-780; Hofmeister, C., Zhang, J., Knight, K.L., Le, P., Stiff, P.J., Ex vivo expansion of umbilical cord blood stem cells for transplantation: growing knowledge from the hematopoietic niche (2007) Bone Marrow Transplant, 39 (1), pp. 11-23; Hilton, M., Tu, X., Wu, X., Bai, S., Zhao, H., Kobayashi, T., F. Notch signaling maintains bone marrow mesenchymal progenitors by suppressing osteoblast differentiation (2008) Nat Med, 14 (3), pp. 306-314; Stylianou, S., Clarke, R.B., Brennan, K., Aberrant activation of notch signaling in human breast cancer (2006) Cancer Res, 66 (3), pp. 1517-1525; Demarest, R., Ratti, F., Capobianco, A.J., It's T-ALL about notch (2008) Oncogene, 27 (38), pp. 5082-5091; Fre, S., Huyghe, M., Mourikis, P., Robine, S., Louvard, D., Artavanis-Tsakonas, S., Notch signals control the fate of immature progenitor cells in the intestine (2005) Nature, 16 (435), pp. 964-968; Fischer, A., Gessler, M., Delta-notch-and then? Protein interactions and proposed modes of repression by Hes and Hey bHLH factors (2007) Nucleic Acids Res, 35 (14), pp. 4583-4596; Zweidler-McKay, P.A., He, Y., Xu, L., Rodriguez, C.G., Karnell, F.G., Carpenter, A.C., Notch signaling is a potent inducer of growth arrest and apoptosis in a wide range of B-cell malignancies (2005) Blood, 106 (12), pp. 3898-3906; Beckstead, B., Santosa, D.M., Giachelli, C.M., Mimicking cell-cell interactions at the biomaterial-cell interface for control of stem cell differentiation (2006) J Biomed Mater Res, 79 A, pp. 94-103; Varnum-Finney, B., Wu, L., Yu, M., Brashem-Stein, C., Staats, S., Flowers, D., Immobilization of Notch ligand, Delta-1, is required for induction of notch signaling (2000) J Cell Sci, 113 (23), pp. 4313-4318; Delaney, C., Varnum-Finney, B., Aoyama, K., Brashem-Stein, C., Bernstein, I.D., Dose-dependent effects of the notch ligand delta1 on ex vivo differentiation and in vivo marrow repopulating ability of cord blood cells (2005) Blood, 106, pp. 2693-2699; Lefort, N., Bennea, C., Lelièvrea, J.D., Dorivala, C., Balboa, M., Sakanoc, S., Short exposure to notch ligand delta-4 is sufficient to induce T-cell differentiation program and to increase the T cell potential of primary human CD34+ cells (2006) Exp Hematol, 34, pp. 1720-1729; Taqvi, S., Dixit, L., Krishnendu, R., Biomaterial-based notch signaling for the differentiation of hematopoietic stem cells into T cells (2006) J Biomed Mater Res, 79 A, pp. 689-697; Bernstein, I., Delaney, C., Dallas, M., Heimfeld, S., Varnum-Finney, B., Notch signaling in hematopoiesis: implication for improving stem cell transplantation (2008) Biol Blood Marrow Transplant, 14, pp. 94-99; De Smedt, M., Hoebeke, I., Reyvoet, K., Leclercq, G., Plum, J., Different thresholds of Notch signaling bias human precursor cells toward B-, NK-, monocytic/dendritic-, or T-cell lineage in thymus microenvironment (2005) Blood, 106, pp. 3498-3506; Mrksich, M., What can surface chemistry do for cell biology? (2002) Curr Opin Chem Biol, 6, pp. 794-797; France, R., Short, R.D., Dawsonb, R.A., MacNeilb, S., Attachment of human keratinocytes to plasma copolymers of acrylic acid/octa-1,7-diene and allyl amine/octa-1,7-diene (1998) J Mater Chem, 81 (1), pp. 37-42; Neves, H., Weerkamp, F., Gomes, A.C., Naber, B., Gameiro, P., Becker, J.L., Effects of delta1 and jagged1 on early human hematopoiesis: correlation with expression of notch signaling-related genes in CD34+ Cells (2006) Stem Cells, 24, pp. 1328-1337; Sokolova, V., Epple, M., Inorganic nanoparticles as carriers of nucleic acids into cells (2008) Angewandte Chemie, 47, pp. 1382-1395; Yao, J., Duan, L., Fan, M., Yuan, J., Wu, X., Notch1 induces cell cycle arrest and apoptosis in human cervical cancer cells: involvement of nuclear factor kappa B inhibition (2007) Int J Gynecol Cancer, 17, pp. 502-510; Chadwick, N., Nostro, M.C., Baron, M., Mottram, R., Brady, G., Buckle, A., Notch signaling induces apoptosis in primary human CD34+ hematopoietic progenitor cells (2007) Stem Cells, 25, pp. 203-210; Love, J., Estroff, L.A., Kriebel, J.K., Nuzzo, R.G., Whitesides, G.M., Self-assembled monolayers of thiolates on metals as a form of nanotechnology (2005) Chem Rev, 105, pp. 1103-1169; Gehanno, V., Freitas, P.P., Veloso, A., Ferreira, J., Almeida, B., Sousa, J.B., Ion beam deposition of Mn-Ir spin valves (1999) IEEE Trans Magn, 35, pp. 4361-4367; Martins, M.C.L., Ratner, B., Barbosa, M.A., Protein adsorption on mixtures of hydroxyl- and methyl- terminated self-assembled monolyers (2003) J Biomed Mater Res, 67 (A), pp. 158-171; Martins, M.C.L., Curtins, S.A., Freitas, S.C., Salgueiro, P., Ratner, B.D., Barbosa, M.A., Molecularly designed surfaces for blood deheparinization using an immobilized heparin-binding peptide (2009) J Biomed Mater Res A, 88 (1), pp. 162-173; Barrias, C.C., Martins, M.C.L., Bidarra, S., Sá Miranda, M.C., Barbosa, M.A., Adsorption of a therapeutic enzyme to self-assembled monolayers: effect of the surface chemistry and solution pH on the amount and activity of adsorbed enzyme (2005) Biomaterials, 26, pp. 2695-2704; Iodine-125. A guide to radioiodination techniques. In: techniques I-Agtr, ed.: Little Chalfort: Amersham Life Science 1993Horbett, T., Techniques for protein adsorption studies (1986) Techniques of biocompatibility tests, pp. 183-214. , DF W. (Ed), CRC Press Inc, Harcover; Ohishi, K., Varnum-Finney, B., Bernstein, I.D., Delta-1 enhances marrow and thymus repopulating ability of human CD34+ CD38- cord blood cells (2002) J Clin Invest, 110, pp. 1165-1174; Li, L., Chen, S., Zheng, J., Ratner, B.D., Jiang, S., Protein adsorption on oligo(ethylene glycol)-terminated alkanethiolate self-assembled monolayers: the molecular basis for nonfouling behavior (2005) J Phys Chem B, 109 (7), pp. 2934-2941; Tohda, S., Murata-Ohsawa, M., Sakano, S., Nara, N., Notch ligands, Delta-1 and Delta-4 supress the self-renewal capacity and long-term growth of two myeloblastic leukemia cell lines (2003) Int J Oncol, 22 (5), pp. 1073-1079; Tohda, S.K.H., Murakami, N., Sakano, S., Nara, N., Diverse effects of the Notch ligands Jagged1 and Delta1 on the growth and differentiation of primary acute myeloblastic leukemia cells (2005) Exp Hematol, 33, pp. 558-563; Aoyama, K., Delaney, C., Varnun-Finney, B., Kohn, A.D., Moon, R.T., Bernstein, I.D., The interaction of the Wnt and notch pathways modulates natural killer versus T cell differentiation (2007) Stem Cells, 25, pp. 2488-2497; Beckstead B, Tung JC, Liang KJ, Tavakkol Z, Usui ML, Olerud JE, et al. Methods to promote notch signaling at the biomaterial interface and evaluation in a rafted organ culture model. J Biomed Mater Res A, in press. [Epub ahead of print]Semler, E., Dasgupta, A., Moghe, P.V., Cytomimetic engineering of hepatocyte morphogenesis and function by substrate-based presentation of acellular E-cadherin (2005) Tissue Eng, 11 (5-6), pp. 734-750; Zhao, Z., Matsui, H., Accurate immobilization of antibody-functionalized peptide nanotubes on protein-patterned arrays by optimizing their ligand-receptor interactions (2007) Small, 3 (8), pp. 1390-1393; Longo, G., Szleifer, Ligand-receptor interactions in tethered polymer layers (2005) Langmuir, 21, pp. 11342-11351; Gonçalves, I.C., Martins, M.C.L., Barbosa, M.A., Ratner, B.D., Protein adsorption and clotting time of pHEMA hydrogels modified with C18 ligands to adsorb albumin selectively and reversibly (2009) Biomaterials, 30 (29), pp. 5541-5551
Keywords: Activator concentration; Adequate models; Adsorption; Animals; article; Bioactivity; Biological activities; Biological materials; biomaterial; Calcium-Binding Proteins; Carbonyldiimidazole; Cell culture; Cell Line; Cell membranes; cell strain HL 60; Cell system; Chemical activation; Concentration (process); Concentration of; controlled study; Covalently bound; Ethylene; Ethylene Glycol; gene expression; gold; Gold substrates; HL-60 cell line; human; human cell; Human IgG; Humans; Immunoassay; immunoglobulin Fc fragment; Immunoglobulin G; immunoglobulin G antibody; Intercellular Signaling Peptides and Proteins; Jagged1; Ligands; Mammalia; Membrane Proteins; Model surface; Molecular Structure; Nanostructured materials; Nanostructured surfaces; Nonfouling; Notch receptor; Notch signaling; Photoelectron spectroscopy; priority journal; Protein adsorption; protein immobilization; Radiolabeling; Real-time PCR; Receptors, Fc; Receptors, Notch; Recombinant Fusion Proteins; Sams; self assembled monolayer; Self assembled monolayers; Self-assembled monolayers; signal transduction; Signaling; stem cell; Surface Properties; Target genes; Tetra; transcription factor HES 1; X ray photoelectron spectroscopy

Morphology and mechanical properties of injectable ceramic microspheres - Oliveira, S.M.; Barrias, C.C.; Ribeiro, C.C.; Almeida, I.F.; Bahia, M.F.; Barbosa, M.A. (Key Engineering MaterialsKey Eng Mat, 2009)
The aim of this study was to analyze the effect of starting powder granulometry and sintering conditions on the morphological structure and mechanical properties of injectable hydroxyapaptite (HAp) microspheres. The mechanical properties of the microspheres were evaluated, to investigate if their integrity could be maintained during the injection process. To obtain microspheres, HAp powders were dispersed in a sodium alginate solution and spherical particles were prepared by droplet extrusion under a co-axial air stream, coupled with ionotropic gelation in the presence of Ca 2+. This was followed by a sintering process at various temperatures and times. The morphology of microspheres was observed under SEM, diameter measurements were performed in an optical microscope and the compression strength was evaluated using a texture analyzer. Finally, microspheres prepared using lower granulometry HAp powders and sintered at 1200°C for 1 hour presented the best properties and were selected as the most suitable for the envisaged application.
Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAEdoi: 10.4028/0-87849-353-0.691Language of Original Document: EnglishCorrespondence Address: Oliveira, S. M.; ESTV, Departamento de Engenharia Mecânica, Instituto Politécnico de Viseu, Viseu, PortugalReferences: Barrias, C.C., Ribeiro, C.C., Lamghari, M., Miranda, C.S., Barbosa, M.A., Proliferation, activity, and osteogenic differentiation of bone marrow stromal cells cultured on calcium titanium phosphate microspheres (2005) Journal of Biomedical Materials Research, 72 A (1), pp. 57-66;Barrias, C.C., Ribeiro, C.C., Barbosa, M.A., Adhesion and proliferation of human osteoblastic cells seeded on injectable hydroxyapatite microspheres (2004) Bioceramics, 16, pp. 254-262,877-880; Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., Calcium phosphate-alginate microspheres as enzyme delivery matrices (2004) Biomaterials, 25 (18), pp. 4363-4373; Silva, R.V., Camilli, J.A., Bertran, C.A., Moreira, N.H., The use of hydroxyapatite and autogenous cancellous bone grafts to repair bone defects in rats (2005) International Journal of Oral and Maxillofacial Surgery, 34 (2), pp. 178-184; Boyan, B.D., Lossdörfer, S., Wang, L., Zhao, G., Lohmann, C.H., Cochran, D.L., Schwartz, Z., Osteoblasts generate an osteogenic microenvironment when grown on surfaces with rough microtopographies (2003) Eur Cell Mater, 6, pp. 22-27; Cardoso, O.N., Sotto Mayor, T., Pinto, A.M.F.R., Campos, J.B.L.M., Axial dispersion of particles in a slugging column - the role of the laminar wake of the bubbles (2003) Chemical Engineering Science, 58 (18), pp. 4159-4172; Gauthier, O., Bouler, J.M., Weiss, P., Bosco, J., Aguado, E., Daculsi, G., Short-term effects of mineral particle sizes on cellular degradation activity after implantation of injectable calcium phosphate biomateriais and the consequences for bone substitution (1999) Bone, 25 (2), pp. 71S-74S; Xu, H.H., Weir, M.D., Burguera, E.F., Fraser, A.M., Injectable and macroporous calcium phosphate cement scaffold (2006) Biomaterials, 27 (24), pp. 4279-4287; Ginebra, M.P., Rilliard, A., Fernandez, E., Elvira, C., San Roman, J., Planell, J.A., Mechanical and rheological improvement of a calcium phosphate cement by the addition of a polymeric drug (2001) J Biomed Mater Res, 57 (1), pp. 113-118
Keywords: Air streams; Apatite; Calcium; Ceramic microspheres; Co-axial; Coagulation; Compression strengths; Diameter measurements; Gelation; Granulometry; hydroxyapatite; Injectable; Injection process; Ionotropic gelations; Mechanical properties; Microspheres; Morphological structures; Morphology and mechanical properties; Optical microscopes; Powders; SEM; Sintering; Sintering conditions; Sintering process; Sodium; Sodium alginates; Spherical particles; Starting powders; Texture analyzers

Neural cell growth on TiO 2 anatase nanostructured surfaces - Collazos-Castro, J.E.; Cruz, A.M.; Carballo-Vila, M.; Lira-Cantú, M.; Abad, L.; del Pino, Á.P.; Fraxedas, J.; San Juan, A.; Fonseca, C.; Pêgo, A.P.; Casañ-Pastor, N. (Thin Solid FilmsThin Solid Films, 2009)
Titanium oxides have anti-inflammatory activity and tunable electrochemical properties that make them attractive materials for biomedical applications. This work investigated the compatibility of nanometric coatings of low-temperature phases of TiO 2 with neurons in 4-day and 10-day cultures, using different cell densities to quantify cell survival and neurite extension. TiO 2 films were prepared by sol-gel and thermal treatment (250-450 °C) of hydrolyzed titanium tetra-isopropoxide on electrically conducting or insulating slides. The conducting substrates were not passivated by the nanometric oxide layer and could be used as electrodes. Characterization of the films showed nano-structured TiO 2 containing exclusively Ti +4 valence in anatase and amorphous phases. When coated with polylysine, all films permitted good neuron attachment and survival for at least ten days in culture. However, they generally reduced neurite growth compared to cell culture borosilicate glass, with dendrites more affected than axons. The analyses of surface topography, hydrophilicity, charge and chemical composition revealed that TiO 2 chemistry was the main factor responsible for neurite inhibition. © 2009 Elsevier B.V. All rights reserved.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: THSFAdoi: 10.1016/j.tsf.2009.06.048Language of Original Document: EnglishCorrespondence Address: Casañ-Pastor, N.; Instituto de Ciencias de Materiales de Barcelona, CSIC, Campus la Universidad Autonoma Barcelona, E-08193 Barcelona, Spain; email: nieves@icmab.esReferences: Suzuki, R., Frangos, J.Á., (2000) Clin. Orthop. Relat. Res., 372, p. 280;Suzuki, R., Muyco, J., McKittrick, J., Frangos, J.A., (2003) J. Biomed. Mater. Res. A, 66, p. 396; Ulbrich, M.H., Fromherz, P., (2005) Appl. Phys. A., 81, p. 887; Topoglidis, E., Lutz, T., Willis, R.L., Barnett, C.J., Cass, A.E., Durrant, J.R., (2000) Faraday Discuss., 116, p. 35; Smith, J.R., Walsh, F.C., Clarke, R.L., (1998) J. Appl. Electrochem., 28, p. 1021; Dinh, N.N., Oan, N.T., Long, P.D., Bernard, M.N., Hugot-Le Goffb, A., (2003) Thin Solid Films, 423, p. 70; (2001) Titanium in Medicine, , Brunette D.M., Tengvall P., Textor M., and Thomsen P. (Eds), Springer-Verlag, Berlin; Textor, M., Sittig, C., Frauchiger, V., Tosatti, S., Brunette, D.M., (2001) Titanium in Medicine, 171. , Brunette D.M., Tengvall P., Textor M., and Thomsen P. (Eds), Springer-Verlag, Berlin; Contreras, R., Sahlin, H., Frangos, J.Á., (2007) J. Biomed. Mater. Res. A, 80, p. 480; Kolbrecka, K., Przyluski, J., (1994) Electrochim. Acta, 39, p. 1591; Diebold, U., (2003) Surf. Sci. Rep., 48, p. 53; Jeong, B.S., Norton, D.P., Budai, J.D., (2003) Solid-State Electron., 47, p. 2275; Moulton, S.E., Barisci, J.N., Bath, A., Stella, R., Wallace, G.C., (2005) Langmuir, 21, p. 316; Jackson, D.R., Omanovic, S., Roscoe, S.G., (2005) Langmuir, 16, p. 5449; Subramanian, V., Karki, A., Gnanasekar, K.I., Eddy, FP., Rambabu, B., (2006) J. Power Sources, 159, p. 186; Carballo-Vila, M., Moreno-Burriel, B., Jurado, J.R., Chinarro, E., Casañ-Pastor, N., Collazos-Castro, J.E., (2009) J. Biomed. Mater. Res. A, 90, p. 94; Brewer, G.J., Torricelli, J.R., Evege, E.K., Price, P.J., (1993) J. Neurosci. Res., 35, p. 567; Rajnicek, A.M., Britland, S., McCaig, C.D., (1997) J. Cell Sci., 110, p. 2905; Bao, W., Thullberg, M., Zhang, H., Onischenko, A., Strömblad, S., (2002) Mol. Cell. Biol., 22, p. 4587; Sanjana, N.E., Fuller, S.B., (2004) J. Neurosci. Methods, 136, p. 151; Parak, W.J., George, M., Kudera, M., Gaub, H.E., Behrends, J.C., (2001) Eur. Biophys. J., 29, p. 607; Dotti, C.G., Sullivan, C.A., Banker, G.A., (1988) J. Neurosci., 8, p. 1454; Davenport, R.W., McCaig, C.D., (1993) J. Neurobiology, 24, p. 89; Chuckowree, J.A., Vickers, J.C., (2003) J. Neurosci., 23, p. 3715; Long, T.C., Saleh, N., Tilton, R.D., Lowry, G.V., Veronesi, B., (2006) Environ. Sci. Technol., 40, p. 4346; Zhao, L., Chang, J., Zhai, W., (2005) J. Biomater. Appl., 19, p. 237; Swamy, V., Kusnetzov, A., Dubrovinsky, L.S., Caruso, R.A., Shchukin, D.G., Muddle, B.C., (2005) Phys. Rev., B, 71, p. 1; Lozano, M.P., Fraxedas, J., (2000) Surf. Interface Anal., 30, p. 623; Martínez-Ferrero, E., Sakatani, Y., Boissière, C., David Grosso, D., Fuertes, A., Fraxedas, J., Sánchez, C., (2007) Adv. Funct. Mater., 17, p. 3348; Roddick-Lanzilotta, A.D., McQuillan, A.J., (1999) J. Colloid Interface Sci., 217, p. 194; Kosmulski, M., (2002) Adv. Colloid Interface Sci., 99, p. 255; Ikegaya, Y., Itsukaichi-Nishida, Y., Ishihara, M., Tanaka, D., Matsuki, N., (2000) Neuroscience, 97, p. 215; Cyster, L.A., Parker, K.G., Parker, T.L., Grant, D.M., (2004) Biomaterials, 25, p. 97; Blau, A., Weinl, C., Mack, J., Kienle, S., Jung, G., Ziegler, C., (2001) J. Neurosci. Methods, 112, p. 65; Kommireddy, D.S., Sriram, S.M., Lvov, Y.M., Mills, D.K., (2006) Biomaterials, 27, p. 4296; Cai, K., Bossert, J., Jandt, K.D., (2006) Colloids Surf., B, 49, p. 136; Wang, Y.-X., Robertson, J.L., Spillman Jr., W.B., Claus, R.O., (2004) Pharm. Res., 21, p. 1362; Greve, F., Frerker, S., Bittermann, A.G., Burkhardt, C., Hierlemann, A., Hall, H., (2007) Biomaterials, 28, p. 5246; Yang, H., Fung, S.-Y., Pritzker, M., Chen, P., (2007) PLoS ONE, 2, pp. e1325; Giovambattista, N., Debenedetti, P.G., Rosky, P.J., (2007) J. Phys. Chem. B, 111, p. 9581; Onur, M.A., Taş, Z., Gürpnar, A., Şahin, A., Çehreli, M.C., (2004) Clin. Oral Implants Res., 15, p. 513; Lopez, T., Ortiz-Islas, E., Manjarrez, J., Rodríguez-Reinoso, F., Sepúlveda, A., Gonzalez, R.D., (2006) Opt. Mater., 29, p. 70
Keywords: Amorphous phasis; Anatase; Anti-inflammatory activity; Biomedical applications; Borosilicate glass; Cell culture; cell density; Cell membranes; cell survival; Chemical compositions; Coatings; Conducting substrates; Conductive films; Electrochemical properties; Gelation; Growth kinetics; Heat treatment; Iso-propoxide; Low temperature phasis; Nano-structured; Nanometrics; Nanostructured surface; Nanostructures; Neural cell; Neural cells; Neurite extension; Neurite growth; Neurites; Neurons; Oxide layer; polylysine; Surface topography; Thermal treatment; TiO; Titanium; Titanium dioxide; Titanium oxide; Titanium oxides

Prediction of neonatal acidemia by computer analysis of fetal heart rate and ST event signals - Costa, A.; Ayres-de-Campos, D.; Costa, F.; Santos, C.; Bernardes, J. (American Journal of Obstetrics and GynecologyAm. J. Obstet. Gynecol., 2009)
Objective: The objective of the study was to evaluate the accuracy of computer analysis of fetal heart rate (FHR) and ST event signals in prediction of neonatal acidemia. Study Design: One hundred forty-eight FHR tracings were evaluated to identify red alerts provided by the system, based on automated analysis of FHR and ST event signals, and compared with the occurrence of umbilical artery acidemia (pH ≤7.05). Results: The presence of red alerts obtained sensitivity of 1.00 (95% confidence interval [CI], 0.56-1.00), specificity of 0.94 (95% CI, 0.89-0.97), positive predictive value (PPV) of 0.47 (95% CI, 0.22-0.72), negative predictive value (NPV) of 1 (95% CI, 0.96-1.00), positive likelihood ratio (PLR) of 17.6 (95% CI, 9.0-34.5), and negative likelihood ratio (NLR) of 0. When limiting analysis to red alerts that did not include ST data, sensitivity was 0.57 (95% CI, 0.20-0.88), specificity was 0.97 (95% CI, 0.92-0.99), PPV was 0.50 (95% CI, 0.17-0.82), NPV was 0.98 (95% CI, 0.93-0.99), PLR was 20.14 (95% CI, 6.3-64.2), and NLR was 0.44 (95% CI, 0.19-1.04). Conclusion: Computer analysis of FHR and ST event signals provide higher accuracy in predicting neonatal academia. © 2009 Mosby, Inc. All rights reserved.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: AJOGAdoi: 10.1016/j.ajog.2009.04.033PubMed ID: 19539895Language of Original Document: EnglishCorrespondence Address: Costa, A.; Departamento de Ginecologia e Obstetrícia, Faculdade de Medicina, Hospital S. JoãoPortugal; email: cosantonia@gmail.comReferences: (2006) Perinatal Mortality Surveillance 2004: England, Wales, and Northern Ireland, , CEMACH (Confidential Enquiry into Maternal and Child Health), Confidential Enquiry into Maternal and Child Health, London, UK;(1997) 4th annual report, , CESDI (Confidential Enquiry into Stillbirths and Deaths in Infancy), Maternal and Child Health Research Consortium, London, UK; Ayres-de-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in classification by experts of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynaecol, 106, pp. 1307-1310; Paneth, N., Bommarito, M., Stricker, J., Electronic fetal monitoring and later outcome (1993) Clin Invest Med, 16, pp. 159-165; Bernardes, J., Costa-Pereira, A., Ayres-de-Campos, D., van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynecol Obstet, 57, pp. 33-37; Donker, D.K., van Geijn, H.P., Hasman, A., Interobserver variation in the assessment of fetal heart rate recordings (1993) Eur J Obstet Gynecol Reprod Biol, 52, pp. 21-28; Neilson, J.P., Fetal electrocardiogram (ECG) for fetal monitoring during labour (2006) Cochrane Database Syst Rev, 3; Doria, V., Papageorghiou, A., Gustafsson, A., Ugwumadu, A., Farrer, K., Arulkumaran, S., Review of the first 1502 cases of ECG-ST waveform analysis during labour in a teaching hospital (2007) BJOG, 114, pp. 1202-1207; Westerhuis, M., Kwee, A., van Ginkel, A., Drogtrop, A., Gyselaers, W., Visser, G., Limitations of ST analysis in clinical practice: three cases of intrapartum metabolic acidosis (2007) BJOG, 114, pp. 1194-1201; Amer-Wahlin, I., Arulkumaran, S., Hagberg, H., Marsal, K., Visser, G., Fetal electrocardiogram: ST waveform analysis in intrapartum surveillance (2007) BJOG, 114, pp. 1191-1193; Dawes, G.S., Redman, C.W., Smith, J.H., Improvements in the registration and analysis of fetal heart rate records at the bedside (1985) Br J Obstet Gynaecol, 92, pp. 317-325; Ayres-de-Campos, D., Costa-Santos, C., Bernardes, J., Prediction of neonatal state by computer analysis of fetal heart rate tracings: the antepartum arm of the SisPorto multicentre validation study (2005) Eur J Obstet Gynecol Reprod Biol, 118, pp. 52-60. , SisPorto Multicentre Validation Study Group; Dawes, G.S., Moulden, M., Redman, C.W.G., System 8000: computerized antenatal FHR analysis (1991) J Perinat Med, 19, pp. 47-51; Bernardes, J., Moura, C., Marques-de-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-65; Ayres-de-Campos, D., Bernardes, J., Garrido, A., Marques-de-Sá, J.P., Pereira-Leite, L., SisPorto 2.0-a program for automated analysis of cardiotocograms (2000) J Matern Fetal Med, 9, pp. 311-318; Ayres-de-Campos, D., Sousa, P., Costa, A., Bernardes, J., Omniview-SisPorto® 3.5-a central fetal monitoring station with online alerts based on computerized cardiotocogram+S.T.event analysis (2008) J Perinat Med, 36, pp. 260-264; Ayres-de-Campos, D., Bernardes, J., Kwee, A., Westehuis, M., Visser, G.H.A., Computer quantification of short-term variability as an adjunct to fetal electrocardiographic monitoring (2007) BJOG, 114, pp. 1446-1447; Downing, J.W., Houlton, P.C., Barclay, A., Extradural analgesia for cesarean section: a comparison with general anesthesia (1979) Br J Anaesth, 51, pp. 367-374; Crawford, J.S., James, F.M., Davies, P., Crawley, M., A further study of general anaesthesia for cesarean section (1976) Br J Anaesth, 48, pp. 661-667; Huch, A., Huch, C., Rooth, G., Guidelines for blood sampling and measurement of pH and blood gas values in obstetrics (1994) Eur J Obstet Gynecol Reprod Biol, 54, pp. 165-175; ACOG technical bulletin. Umbilical artery blood acid-base analysis (1996) Int J Gynecol Obstet, 52, pp. 305-310; Westgate, J., Garibaldi, J.M., Greene, K.R., Umbilical cord blood gas analysis at delivery: a time for quality data (1994) Br J Obstet Gynaecol, 101, pp. 1054-1063; Low, J.A., Intrapartum fetal asphyxia: definition, diagnosis and classification (1997) Am J Obstet Gynecol, 176, pp. 957-959; Fleiss, J.L., (1981) Statistical methods for rates and proportions. 2nd ed., , John Wiley & Sons, New York, NY Section 5.6; Keith, R.D., Beckley, S., Garibaldi, J.M., Westgate, J.A., Ifeachor, E.C., Greene, K.R., A multicentre comparative study of 17 experts and an intelligent computer system for managing labour using cardiotocogram (1995) Br J Obstet Gynecol, 102, pp. 668-700; Chung, T.K., Mohajer, M.P., Yang, Z.j., Chang, A.M., Sahota, D.S., The prediction of fetal acidosis at birth by computerised analysis of intrapartum cardiotocography (1995) Br J Obstet Gynaecol, 102, pp. 454-460; Nielsen, P.V., Stigsby, B., Nickelsen, C., Nim, J., Computer assessment of the intrapartum cardiotocogram. II. The value of computer assessment compared with visual assessment (1988) Acta Obstet Gynecol Scand, 67, pp. 461-464; Policy statement. The Apgar score-American Academy of Pediatrics and American College of Obstetricians and Gynecologists (2006) Pediatrics, 117, pp. 1444-1447; Casey, B.M., McIntire, D.D., Leveno, K.J., The continuing value of the Apgar score for the assessment of the newborn infants (2001) N Engl J Med, 334, pp. 467-471; Moster, D., Lie, R.T., Irgens, L.M., Bjerkedal, T., Markestad, The association of Apgar score with subsequent death and cerebral palsy: a population-based study in term infants (2001) J Pediatr, 138, pp. 798-803
Keywords: acidemia; Acidosis; article; autoanalysis; Cardiotocography; computer analysis; computer assisted; computer prediction; Diagnosis, Computer-Assisted; diagnostic value; Electrocardiography; Female; Fetal heart rate; Fetal hypoxia; Fetal monitoring; fetus electrocardiography; fetus heart rate; Heart Rate, Fetal; human; Humans; Infant, Newborn; major clinical study; male; newborn; newborn acidosis; observational study; pH; Predictive Value of Tests; priority journal; Prospective Studies; prospective study; Reproducibility of Results; sensitivity and specificity; signal transduction; ST segment; umbilical artery

The role of composition, morphology and crystalline structure in the electrochemical behaviour of TiN x thin films for dry electrode sensor materials - Cunha, L.T.; Pedrosa, P.; Tavares, C.J.; Alves, E.; Vaz, F.; Fonseca, C. (Electrochimica ActaElectrochim Acta, 2009)
A morphological, structural and electrochemical study of titanium nitride (TiN x) thin films, obtained by DC reactive sputtering on titanium substrates, was carried out for a wide range of compositions (0 < x < 1.34) aiming a selection of the best coatings for dry biomedical electrodes. The films displayed a columnar-type structure, with morphologies strongly dependent on the composition: a compact and smooth surface was found for the Ti-rich films, (x < 1), whereas the N-rich films, (x ≥ 1) displayed a rough and porous structure. The electrochemical study of the TiN x films was performed in synthetic sweat, aiming at simulating the contact with the skin. The voltammetric analysis showed anodic currents higher for TiN x films than for titanium for low and medium polarization potentials, whereas for potentials beyond 2 V the blocking behaviour of the TiN x films allowed them to display lower current values. The passive dissolution currents in the sub-μA/cm 2 range and the charge transfer resistances of the order of the MΩ proved the excellent stability of all films in sweat conditions. Finally, the electrochemical noise analysis showed that the near-stoichiometric and N-rich films display the lowest noise, being therefore the most suitable for electrode applications, where signals in the microvolt range, such as the electroencephalographic (EEG) signals, are to be monitored. © 2009 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 10Export Date: 21 November 2012Source: ScopusCODEN: ELCAAdoi: 10.1016/j.electacta.2009.08.004Language of Original Document: EnglishCorrespondence Address: Fonseca, C.; INEB - Instituto de Engenharia Biomédica, Divisão de Biomateriais, Universidade do Porto, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: cfonseca@ineb.up.ptReferences: McAdams, E., Bioelectrodes (1988) Encyclopedia of Medical Devices and Instrumentation, p. 120. , Webster J.G. (Ed), Wiley, New York;Teplan, M., (2002) Meas. Sci. Rev., 2 (2); Searle, A., Kirkup, L., (2000) Physiolog. Meas., 22, p. 71; Ko, W.K., Hynecek, J., Dry electrodes and electrode amplifiers (1974) Biomedical Electrode Technology, , Miller H.A., and Harrison D.C. (Eds), Academic Press, N.Y; Fonseca, C., Vaz, F., Barbosa, M.A., (2004) Corros. Sci., 46 (12), p. 3005; Tallgren, P., Vanhatalo, S., Kaila, K., Voipio, J., (2005) Clin. Neurophysiol., 116, p. 799; Abd El Aal, (2008) Corros. Sci., 50, p. 41; Malik, H., Mgaloblishvili, R., Mills, B., (2004) J. Mat. Sci. Lett., 19 (19), p. 1779; Piscanec, S., Ciacchi, L., Vesselli, E., Comelli, G., Sbaizero, O., Meriani, S., De Vita, A., (2004) Acta Mater., 52, p. 1237; Gao, L., Gstöttner, J., Emling, R., Linsmeier, Ch., Wiltner, A., Hansch, W., Schmitt-Landsiedel, D., (2004) Microelectronic Eng., 76 (1-4), p. 76; Vaz, F., Ferreira, J., Ribeiro, E., Rebouta, L., Lanceros-Méndez, S., Mendes, J.A., Alves, E., de Rijk, J., (2005) Surf. Coat. Technol., 191, p. 317; Barradas, N.P., Jeynes, C., Webb, R.P., (1997) Appl. Phys. Lett., 71, p. 291; Ramos, A.R., Paúl, A., Rijniers, L., da Silva, M.F., Soares, J.C., (2002) Nucl. Instr. Meth., B190, p. 95; Randin, J.-O., (1988) J. Biomed. Mat. Res., 22, p. 649; Subramaniam, T.K., Srinivasulu Naidu, B., Uthanna, S., (1999) Cryst. Res. Technol., 34, p. 8; Rizzo, A., Signore, M.A., De Riccardis, M.F., Capodieci, L., Dimaio, D., Nocco, T., (2007) Thin Solid Films, 515, p. 6665; Sundgren, J.-E., Johansson, B.-O., Karlsson, S.-E., (1983) Thin Solid Films, 105, p. 353; Elstner, F., Ehrlich, A., Giegengack, H., Kupfer, H., Richter, F., (1994) J. Vac. Sci. Technol. A, 12, p. 476; Han, Z., Tian, J., Lai, Q., Yu, X., Li, G., (2003) Surf. Coat. Technol., 162, p. 189; Wriedt, H.A., Murray, J.L., Bull. Alloy Phase Diagrams (1987) 8/4, p. 378; Lu, K., Sui, M.L., Lück, R., (1994) Nanostruct. Mat., 4 (4), p. 465; Vaz, F., Machado, P., Rebouta, L., Cerqueira, P., Goudeau, Ph., Rivière, J.P., Alves, E., de Rijk, J., (2003) Surf. Coat. Technol., 174-175, p. 375; Norlin, A., Pan, J., Leygraf, C., (2005) J. Electrochem. Soc., 152 (2), pp. J7; Milosev, I., Strehblow, H., Navinsek, B., (1997) Thin Solid Films, 303, p. 246; Orazem, M., Tribollet, B., (2008) Electrochemical Impedance Spectroscopy, , John Wiley &Sons 233; Chappé, J.-M., Matin, N., Pearson, J., GTerwagne, J., Lintymer, J., Gavoille, J., Takadoum, (2004) Applied Suf. Sci., 222, p. 229; Logothetidis, S., Meletis, E., Stergioudis, G., Adjaottor, A., (1999) Thin Solid Films, p. 304; Huigen, E., Peper, A., Grimbergen, C., (2002) Med. Biol. Eng. Comput., 40, p. 332; Hladky, K., Dawson, J., (1982) Corrosion Sci., 22, p. 231
Keywords: Anodic currents; Bioelectric phenomena; Biomedical devices; biomedical electrodes; Blocking behaviour; Charge transfer; Charge transfer resistance; Chemical analysis; Crystalline structure; DC reactive sputtering; Dissolution; Dry electrode; EIS; Electrochemical behaviour; Electrochemical corrosion; Electrochemical electrodes; Electrochemical Noise Analysis; Electrochemical studies; Electroencephalographic signals; Ion exchange; morphology; Polarization potential; Porous structures; Selection of the best; Sensor materials; Smooth surface; Sputtering; Thin films; Titanium; Titanium nitride; Titanium substrates; Type structures; Voltammetric analysis

Role of vascular endothelial growth factor in the communication between human osteoprogenitors and endothelial cells - Grellier, M.; Ferreira-Tojais, N.; Bourget, C.; Bareillke, R.; Guillemot, F.; Amédée, J. (Journal of Cellular BiochemistryJ. Cell. Biochem., 2009)
Proper bone remodeling requires an active process of angiogenesis which in turn supplies the necessary growth factors and stem cells. This tissue cooperation suggests a cross-talk between osteoblasts and endothelial cells. This work aims to identify the role of paracrine communication through vascular endothelial growth factor (VEGF) in co-culture between osteoblastic and endothelial cells. Through a well defined direct contact co-culture model between human osteoprogenitors (HOPs) and human umbilical vein endothelial cells (HUVECs), we observed that HUVECs were able to migrate along HOPs, inducing the formation of specific tubular-like structures. VEGF 165 gene expression was detected in the HOPs, was up-regulated in the co-cultured HOPs and both Fit-1 and KDR gene expression increased in co- cultured HUVECs. However, the cell rearrangement observed in co-culture was promoted by a combination of soluble chemoattractive factors and not by VEGF 165 alone. Despite having no observable effect on endothelial cell tubular-like formation, VEGF appeared to have a crucial role in osteoblastic differentiation since the inhibition of its receptors reduced the co-culture-stimulated osteoblastic phenotype. This co-culture system appears to enhance both primary angiogenesis events and osteoblastic differentiation, thus allowing for the development of new strategies in vascularized bone tissue engineering. © 2009 Wiley-Liss, Inc.
Cited By (since 1996): 32Export Date: 21 November 2012Source: ScopusCODEN: JCEBDdoi: 10.1002/jcb.22018Language of Original Document: EnglishCorrespondence Address: Grellier, M.; 146 Rue Leo Saignat, Zone Nord, Bat 4A, Case 45, F-33076 Bordeaux Cedex, France; email: maritie.grellier@inserm.frMolecular Sequence Numbers: GENBANK: AB021221, AF063657, AF063658, BC015690, BC021289, NM_000089;Chemicals/CAS: vasculotropin A, 489395-96-2; vasculotropin receptor, 301253-48-5; Receptors, Vascular Endothelial Growth Factor, EC 2.7.1.112; RNA, Messenger; Vascular Endothelial Growth Factor AReferences: Bordenave, L., Baquey, C., Bareille, R., Lefebvre, F., Lauroua, C., Guerin, V., Rouais, F., Anderson, J.M., Endothelial cell compatibility testing of three different Pellethanes (1993) J Biomed Mater Res, 27, pp. 1367-1381;Bouletreau, P.J., Warren, S.M., Spector, J.A., Peled, Z.M., Gerrets, R.P., Greenwald, J.A., Longaker, M.T., Hypoxia and VEGF up-regulate BMP-2 mRNA and protein expression in microvascular endothelial cells: Implications for fracture healing (2002) Plast Reconstr Surg, 109, pp. 2384-2397; Carano, R.A., Filvaroff, E.H., Angiogenesis and bone repair (2003) Drug Discov Today, 8, pp. 980-989; Carmeliet, P., Collen, D., Molecular basis of angiogenesis. Role of VEGF and VE-cadherin (2000) Ann NY Acad Sci, 902, pp. 249-262. , discussion 262-264; Clarkin, C.E., Emery, R.J., Pitsillides, A.A., Wheeler-Jones, C.P., Evaluation of VEGF-mediated signaling in primary human cells reveals a paracrine action for VEGF in osteoblast-mediated crosstalk to endothelial cells (2007) J Cell Physiol, 214, pp. 437-444; Cross, M.J., Claesson-Welsh, L., FGF and VEGF function in angiogenesis: Signalling pathways, biological responses and therapeutic inhibition (2001) Trends Pharmacol Sci, 22, pp. 201-207; Cross, M.J., Dixelius, J., Matsumoto, T., Claesson-Welsh, L., VEGF-receptor signal transduction (2003) Trends Biochem Sci, 28, pp. 488-494; Dallas, S.L., Rosser, J.L., Mundy, G.R., Bonewald, L.F., Proteolysis of latent transforming growth factor-beta (TGF-beta)-binding protein-1 by osteoclasts. A cellular mechanism for release of TGF-beta from bone matrix (2002) J Biol Chem, 277, pp. 21352-21360; Ferrara, N., Gerber, H.P., LeCouter, J., The biology of VEGF and its receptors (2003) Nat Med, 9, pp. 669-676; Fiedler, J., Leucht, F., Waltenberger, J., Dehio, C., Brenner, R.E., VEGF-A and P1GF-1 stimulate chemotactic migration of human mesenchymal progenitor cells (2005) Biochem Biophys Res Commun, 334, pp. 561-568; Gerber, H.P., Ferrara, N., Angiogenesis and bone growth (2000) Trends Cardiovasc Med, 10, pp. 223-228; Gerhardt, H., Golding, M., Fruttiger, M., Ruhrberg, C., Lundkvist, A., Abramsson, A., Jeltsch, M., Betsholtz, C., VEGF guides angiogenic sprouting utilizing endothelial tip cell filopodia (2003) J Cell Biol, 161, pp. 1163-1177; Guillotin, B., Bourget, C., Remy-Zolgadri, M., Bareille, R., Fernandez, P., Conrad, V., Amedee-Vilamitjana, J., Human primary endothelial cells stimulate human osteoprogenitor cell differentiation (2004) Cell Physiol Biochem, 14, pp. 325-332; Guillotin, B., Bareille, R., Bourget, C., Bordenave, L., Amedee, J., Interaction between human umbilical vein endothelial cells and human osteoprogenitors triggers pleiotropic effect that may support osteoblastic function (2008) Bone, 42, pp. 1080-1091; Jaffe, E.A., Culture of human endothelial cells (1980) Transplant Proc, 12, pp. 49-53; Lamalice, L., Le Boeuf, F., Huot, J., Endothelial cell migration during angiogenesis (2007) Circ Res, 100, pp. 782-794; Lampugnani, M.G., Orsenigo, F., Gagliani, M.C., Tacchetti, C., Dejana, E., Vascular endothelial cadherin controls VEGFR-2 internalization and signaling from intracellular compartments (2006) J Cell Biol, 174, pp. 593-604; Lebrin, F., Deckers, M., Bertolino, P., Ten Dijke, P., TGF-beta receptor function in the endothelium (2005) Cardiovasc Res, 65, pp. 599-608; Mayr-Wohlfart, U., Waltenberger, J., Hausser, H., Kessler, S., Gunther, K.P., Dehio, C., Puhl, W., Brenner, R.E., Vascular endothelial growth factor stimulates chemotactic migration of primary human osteoblasts (2002) Bone, 30, pp. 472-477; Miralem, T., Steinberg, R., Price, D., Avraham, H., VEGF(165) requires extracellular matrix components to induce mitogenic effects and migratory response in breast cancer cells (2001) Oncogene, 20, pp. 5511-5524; Neufeld, G., Cohen, T., Gengrinovitch, S., Poltorak, Z., Vascular endothelial growth factor (VEGF) and its receptors (1999) FASEB J, 13, pp. 9-22; Ortega, N., Behonick, D., Stickens, D., Werb, Z., How proteases regulate bone morphogenesis (2003) Ann NY Acad Sci, 995, pp. 109-116; Rousseau, S., Houle, F., Huot, J., Integrating the VEGF signals leading to actin-based motility in vascular endothelial cells (2000) Trends Cardiovasc Med, 10, pp. 321-327; Sorrell, J.M., Baber, M.A., Caplan, A., Human dermal fibroblast subpo- pulations; differential interactions with vascular endothelial cells in coculture: Nonsoluble factors in the extracellular matrix influence interactions (2008) Wound Repair Regen, 16, pp. 300-309; Street, J., Bao, M., deGuzman, L., Bunting, S., Peale Jr., F.V., Ferrara, N., Steinmetz, H., Filvaroff, E.H., Vascular endothelial growth factor stimulates bone repair by promoting angiogenesis and bone turnover (2002) Proc Natl Acad Sci USA, 99, pp. 9656-9661; Suarez, S., Ballmer-Hofer, K., VEGF transiently disrupts gap junctional communication in endothelial cells (2001) J Cell Sci, 114, pp. 1229-1235; Sun, L., Vitolo, M., Passaniti, A., Runt-related gene 2 in endothelial cells: Inducible expression and specific regulation of cell migration and invasion (2001) Cancer Res, 61, pp. 4994-5001; Unger, R.E., Sartoris, A., Peters, K., Motta, A., Migliaresi, C., Kunkel, M., Bulnheim, U., Kirkpatrick, C.J., Tissue-like self-assembly in cocultures of endothelial cells and osteoblasts and the formation of microcapillary-like structures on three-dimensional porous biomaterials (2007) Biomaterials, 28, pp. 3965-3976; Villars, F., Bordenave, L., Bareille, R., Amedee, J., Effect of human endothelial cells on human bone marrow stromal cell phenotype: Role of VEGF? (2000) J Cell Biochem, 79, pp. 672-685; Villars, F., Guillotin, B., Amedee, T., Dutoya, S., Bordenave, L., Bareille, R., Amedee, J., Effect of HUVEC on human osteoprogenitor cell differentiation needs heterotypic gap junction communication (2002) Am J Physiol Cell Physiol, 282, pp. C775-C785; Walker, D.L., Vacha, S.J., Kirby, M.L., Lo, C.W., Connexin43 deficiency causes dysregulation of coronary vasculogenesis (2005) Dev Biol, 284, pp. 479-498; Wang, H., Keiser, J.A., Vascular endothelial growth factor upregulates the expression of matrix metalloproteinases in vascular smooth muscle cells: Role of flt-1 (1998) Circ Res, 83, pp. 832-840; Wang, D.S., Miura, M., Demura, H., Sato, K., Anabolic effects of 1,25- dihydroxyvitamin D3 on osteoblasts are enhanced by vascular endothelial growth factor produced by osteoblasts and by growth factors produced by endothelial cells (1997) Endocrinology, 138, pp. 2953-2962; Xin, X., Yang, S., Ingle, G., Zlot, C., Rangell, L., Kowalski, J., Schwall, R., Gerritsen, M.E., Hepatocyte growth factor enhances vascular endothelial growth factor-induced angiogenesis in vitro and in vivo (2001) Am J Pathol, 158, pp. 1111-1120
Keywords: angiogenesis; article; Cell Communication; cell contact; Cell culture; cell differentiation; cell migration; cell motion; Cell Movement; Cells, Cultured; Co-culture; coculture; Coculture Techniques; controlled study; cytology; Endothelial Cells; endothelium cell; Enzyme Activation; gene expression; gene expression regulation; genetics; human; human cell; Human stem cells; human tissue; Humans; Humulus; messenger RNA; metabolism; Microscopy, Electron, Scanning; Migration; nucleotide sequence; osteoblast; Osteoblasts; Osteogenesis; paracrine signaling; phenotype; priority journal; Receptors, Vascular Endothelial Growth Factor; RNA, Messenger; Scanning electron microscopy; secretion; stem cell; umbilical cord; umbilical vein; upregulation; Vascular Endothelial Growth Factor A; vasculotropin 165; vasculotropin A; vasculotropin receptor; vasculotropin receptor 1; vasculotropin receptor 2; Vegf

Sex differences in linear and complex fetal heart rate dynamics of normal and acidemic fetuses in the minutes preceding delivery - Bernardes, J.; Gonçalves, H.; Ayres-de-Campos, D.; Rocha, A.P. (Journal of Perinatal MedicineJ. Perinat. Med., 2009)
Aim: To assess linear and complex heart rate dynamics in relation to fetal gender in normal and acidemic fetuses during the minutes preceding delivery. Methods: Linear and non-linear fetal heart rate indices, namely mean FHR, long-term irregularity index, short-term variability, low and high frequency spectral indices, approximate and sample entropy, were assessed in 36 female and 30 male fetuses, adjusted for gestational age and weight, during the minutes preceding delivery. Analysis was performed in the initial and final minutes of each tracing in fetuses with umbilical artery blood pH at delivery ≥7.20, 7.11-7.19 and ≤7.10. Results: Progression of labor was associated with a significant decrease in non-linear indices and an increase in almost all linear indices, both in female and male fetuses, but changes were more marked in female fetuses. Non-acidemic females showed higher mean FHR in the final minutes of labor, compared with males. Acidemic females had higher linear indices when compared to similar male fetuses. Conclusions: During the minutes preceding delivery, female fetuses express higher linear indices than male fetuses, suggesting greater activation of the autonomic nervous system, while maintaining similar complexity indices, which suggests different reaction and adaptation capabilities to stress and distress. © 2009 by Walter de Gruyter.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: JPEMAdoi: 10.1515/JPM.2009.024PubMed ID: 19021459Language of Original Document: EnglishCorrespondence Address: Bernardes, J.; Faculdade de Medicina, Universidade Do Porto, Ginecologia e Obstetrícia, Al. Hernani Monteiro, Porto, 4200, Portugal; email: jbernardes59@gmail.comReferences: Ayres-de-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in classification by experts of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynaecol, 106, pp. 1307-1310;Ayres-de-Campos, D., Bernardes, J., Garrido, A., Marques-de-Sà, J.P., Pereira-Leite, L., SisPorto 2.0 - a program for automated analysis of cardiotocograms (2000) J Matern Fetal Med, 9, pp. 311-318; Ayres-de-Campos, D., Costa-Santos, C., Bernardes, J., SisPorto Multicentre Validation Study Group. Prediction of neonatal state by computer analysis of fetal heart rate tracings: The antepartum arm of the SisPorto multicentre validation study (2005) Eur J Obstet Gynecol Reprod Biol, 118, pp. 52-60; Ayres-de-Campos, D., Sousa, P., Costa, A., Bernardes, J., Omniview-SisPorto 3.5 - a central fetal monitoring station with online alerts based on computerized cardio-tocogram+ST event analysis (2008) J Perinat Med, 36, pp. 260-264; Beckers, F., Verheyden, B., Aubert, A.E., Aging and non-linear heart rate control in a healthy population (2006) Am J Physiol Heart Circ Physiol, 290, pp. H2560-H2570; Bekedam, D.J., Engelsbel, S., Mol, B.W., Buitendijk, S.E., van der Pal-de Bruin, K.M., Male predominance in fetal distress during labor (2002) Am J Obstet Gynecol, 187, pp. 1605-1607; Bennet, L., Booth, L.C., Ahmed-Nasef, N., Dean, J.M., Davidson, J., Quaedackers, J.S., Male disadvantage? Fetal sex and cardiovascular responses to asphyxia in preterm fetal sheep (2007) Am J Physiol Regul Integr Comp Physiol, 293, pp. R1280-R1286; Bernardes, J., Moura, C., Marques-de-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-65; Bernardes, J., Costa-Pereira, A., Ayres-de-Campos, D., van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynecol Obstet, 57, pp. 33-37; Bernardes, J., Ayres-de-Campos, D., Costa-Pereira, A., Pereira-Leite, L., Garrido, A., Objective computerized fetal heart rate analysis (1998) Int J Gynaecol Obstet, 62, pp. 141-147; Bernardes, J., Gonçalves, H., Ayres-de-Campos, D., Rocha, A.P., Linear and complex heart rate dynamics vary with sex in relation to fetal behavioural states (2008) Early Hum Dev, 84, pp. 433-439; Boog, G., Analyse informatisée du rythme cardiaque foetal au cours de la grosssesse et de l'accouchement. (2004) Encyclopédie Médico- Chirurgicale, 148, pp. 1-10; Browner, W.S., Newman, T.B., Cummings, S.R., Hulley, S.B., (2001) Estimating sample size and power: The nitty-gritty, pp. 65-84. , Hulley SB, Cummings SR, Browner WS, Grady D, Hearst N, Newman TB, editors. Philadelphia: Lippincot Williams & Wilkins; Chaffin, D.G., Barnard, J.M., Phernetton, T., Reed, K.L., Decreased approximate entropy of heart rate variability in the hypoxic ovine fetus (1998) J Matern Fetal Invest, 8, pp. 23-26; Dawes, G.S., Moulden, M., Redman, C.W., Improvements in computerized fetal heart rate analysis antepartum (1996) J Perinat Med, 24, pp. 25-36; Dawes, N.W., Dawes, G.S., Moulden, M., Redman, C.W., Fetal heart rate patterns in term labor vary with sex, gestational age, epidural analgesia, and fetal weight (1999) Am J Obstet Gynecol, 180, pp. 181-187; DiPietro, J.A., Costigan, K.A., Shupe, A.K., Pressman, E.K., Johnson, T.R., Fetal neurobehavioral development: Associations with socioeconomic class and fetal sex (1998) Dev Psychobiol, 33, pp. 79-91; Dudewicz, E., Mishra, S., (1998) Modern mathematical statistics, , John Wiley and Sons, Inc; Fleisher, L.A., Dipietro, J.A., Johnson, T.R., Pincus, S., Complementary and non-coincident increases in heart rate variability and irregularity during fetal development (1997) Clin Sci (Lond), 92, pp. 345-349; Fusheng, Y., Bo, H., Qingyu, T., (1998) Approximate entropy and its application in biosignal analysis, 2, pp. 72-91. , editor. Nonlinear biomedical signal processing, Dynamical analysis and modelling. IEEE Press;; Gonçalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Internal versus external intrapartum foetal heart rate monitoring: The effect on linear and nonlinear parameters (2006) Physiol Meas, 27, pp. 307-319; Goncalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Linear and nonlinear fetal heart rate analysis of normal and acidemic fetuses in the minutes preceding delivery (2006) Med Biol Eng Comput, 44, pp. 847-855; Goncalves, H., Bernardes, J., Rocha, A.P., Ayres-de-Campos, D., Linear and nonlinear analysis of heart rate patterns associated with fetal behavioral states in the antepartum period (2007) Early Hum Dev, 83, pp. 585-591; Groome, L.J., Mooney, D.M., Holland, S.B., Smith, L.A., Atterbury, J.L., Dykman, R.A., Behavioral state affects heart rate response to low-intensity sound in human fetuses (1999) Early Hum Dev, 54, pp. 39-54; Ingemarsson, I., Herbst, A., Thorngren-Jerneck, K., Long-term outcome after umbilical artery acidemia at term birth: Influence of gender and duration of fetal heart rate abnormalities (1997) Br J Obstet Gynaecol, 104, pp. 1123-1127; Jensen-Urstad, K., Storck, N., Bouvier, F., Ericson, M., Lindblad, L.E., Jensen-Urstad, M., Heart rate variability in healthy subjects is related to age and gender (1997) Acta Physiol Scand, 160, pp. 235-241; King, T., Parer, J., The physiology of fetal heart rate patterns and perinatal asphyxia (2000) J Perinat Neonat Nurs, 14, pp. 19-39; Kuo, T.B., Yang, C.C., Sexual dimorphism in the complexity of cardiac pacemaker activity (2002) Am J Physiol Heart Circ Physiol, 283, pp. H1695-H1702; Li, X., Tang, D., Zhou, S., Zhou, G., Wang, C., Zhuang, Y., Redistribution of power spectrum of heart rate variability during acute umbilical artery embolism and hypoxemia in late-gestation fetal sheep (2004) J Obstet Gynecol Reprod Biol, 114, pp. 137-143; Magenes, G., Signorini, M.G., Arduini, D., Classification of cardiotocographic records by neural networks (2000) IJCNN 2000, Proceedings of the IEEE-INNS-ENNS International Joint Conference on Neural Networks, 3, pp. 637-641; Martinez, W.L., Martinez, A.R., (2002) Computational statistics handbook with MATLAB, , CRC Press;; Pincus, S., Approximate entropy as a measure of system complexity (1991) Proc Natl Acad Sci USA, 88, pp. 2297-2301; Pincus, S., Viscarello, R., Approximate Entropy: A regularity measure for fetal heart rate analysis (1992) Obstet Gynecol, 79, pp. 249-255; Richman, J.S., Moorman, J.R., Physiological time-series analysis using approximate entropy and sample entropy (2000) Am J Physiol Heart Circ Physiol, 278, pp. H2039-H2049; Ryan, S.M., Goldberger, A.L., Pincus, S.M., Mietus, J., Lipsitz, L.A., Gender- and age-related differences in heart rate dynamics: Are women more complex than men? (1994) J Am Coll Cardiol, 24, pp. 1700-1707; Sheiner, E., Hadar, A., Hallak, M., Katz, M., Mazor, M., Shoham-Vardi, I., Clinical significance of fetal heart rate tracings during the second stage of labor (2001) Obstet Gynecol, 97, pp. 747-752; Signorini, M.G., Magenes, G., Cerrutti, S., Arduini, D., Linear and nonlinear parameters for the analysis of fetal heart rate signal from cardiotacographic recordings (2003) IEEE Transactions on Biomedical Engineering, 50, pp. 365-373; Siira, S.M., Ojala, T.H., Vahlberg, T.J., Jalonen, J.O., Välimäki, I.A., Rosén, K.G., Marked fetal acidosis and specific changes in power spectrum analysis of fetal heart rate variability recorded during the last hour of labor (2005) Br J Obstet Gynaecol, 112, pp. 418-423; Suzuki, T., Okamura, K., Kimura, Y., Watanabe, T., Yaegashi, N., Murotsuki, J., Power spectral analysis of R-R interval variability before and during the sinusoidal heart rate pattern in fetal lambs (2000) Am J Obstet Gynecol, 182, pp. 1227-1232;
Keywords: acidemia; Acidemic fetuses; article; autonomic nervous system; Birth Weight; blood pH; Cross-Sectional Studies; delivery; Delivery, Obstetric; entropy; Entropy and spectral analysis; Female; Fetal Heart; fetus; fetus heart rate; Gestational Age; Heart Rate, Fetal; human; Humans; Hydrogen-Ion Concentration; Intrapartum; labor; Labor, Obstetric; male; Pregnancy; priority journal; Retrospective Studies; Sex Characteristics; sex difference; Umbilical Arteries; umbilical artery

Skin adhesive versus subcuticular suture for perineal skin repair after episiotomy - A randomized controlled trial - Mota, R.; Costa, F.; Amaral, A.; Oliveira, F.; Santos, C.C.; Ayres-de-Campos, D. (Acta Obstetricia et Gynecologica ScandinavicaActa Obstet. Gynecol. Scand., 2009)
Objective. Surgical repair of perineal lesions after delivery is frequently associated with pain and discomfort, interfering with the normal activities of the puerperium. The aim of this study was to compare perineal skin repair after episiotomy with adhesive glue versus a subcuticular suture, regarding the incidence of pain and wound complications. Study design. Randomized clinical trial. Setting. Tertiary care university hospital. Material and methods. One hundred women having mediolateral episiotomy at vaginal delivery were enrolled. They were randomized to receive skin adhesive (n = 53) or subcuticular suture (n = 47) for closure of perineal skin. The main outcome measure was self-evaluated pain in the 30 days following delivery. Secondary outcome measures were technical difficulties reported with the procedure, duration of surgical repair, wound complications observed at 42-68 hours post-partum and re-initiation of sexual activity by 30 days post-partum. Results. No significant differences were observed between the two groups in incidence of technical difficulties and failed procedures, pain during the procedure, wound complications at hospital discharge, self-evaluated measures of pain at 7 and 30 days or re-initiation of sexual activity by 30 days post-partum. The skin adhesive group had a significantly shorter mean duration of the procedure (four minutes less). Conclusion. Perineal skin closure using adhesive glue is faster than subcuticular suture, and associated with a similar incidence of complications and pain in the first 30 days.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: AOGSAdoi: 10.1080/00016340902883133Language of Original Document: EnglishCorrespondence Address: Mota, R.; Serviço de Ginecologia e Obstetrícia, Hospital de S. João, 4200-319 Porto, Portugal; email: sisporto@med.up.ptChemicals/CAS: Tissue Adhesives; cyanoacrylic acid octyl ester, 6701-17-3; polyglactin, 26780-50-7, 34346-01-5Tradenames: Dermabond, EthiconManufacturers: EthiconReferences: Kettle, C., Hills, R.K., Jones, P., Darby, L., Gray, R., Johanson, R., Continuous versus interrupted perineal repair with standard or rapidly absorbed sutures after spontaneous vaginal birth: A randomized controlled trial (2002) Lancet, 359, pp. 2217-2223;Gordon, B., Mackrodt, C., Fern, E., Truesdale, A., Ayers, S., Grant, A., The Ipswich Childbirth Study: 1. A randomized evaluation of two stage postpartum perineal repair leaving the skin unsutured (1998) Br J Obstet Gynaecol, 105, pp. 435-440; Mackrodt, C., Gordon, B., Fern, E., Ayers, S., Truesdale, A., Grant, A., The Ipswich Childbirth Study: 2. A randomized comparison of polyglactin 910 with chromic catgut for postpartum perineal repair (1998) Br J Obstet Gynaecol, 105, pp. 441-445; Kettle, C., Johanson, R.B., Continuous versus interrupted sutures for perineal repair (2000) Cochrane DataBase Syst Rev, (2). , CD000947; Kettle, C., Hills, R.K., Ismail, K.M.K., Continuous versus interrupted sutures for repair of episiotomy or second degree tears (2007) Cochrane DataBase Syst Rev, (4). , CD000947; Gemynthe, A., Langhoff-Roos, J., Sahl, S., Knudsen, J., New VICRYL formulation: An improved method of perineal repair? (1996) Br J Midwifery, 4, pp. 230-234; Oboro, V.O., Tabowei, T.O., Loto, O.M., Bosah, J.O., A multicentre evaluation of the two-layered repair of postpartum perineal trauma (2003) J Obstet Gynaecol, 23, pp. 5-8; Kindberg, S., Stehouwer, M., Hvidman, L., Henriksen, T.B., Postpartum perineal repair performed by midwives: A randomised trial comparing two suture techniques leaving the skin unsutured (2008) Br J Obstet Gynaecol, 115, pp. 472-479; Gennari, R., Rotmensz, N., Ballardini, B., Scevola, S., Perego, E., Zanini, V., A prospective, randomized, controlled clinical trial of tissue adhesive (2-octylcyanoacrylate) versus standard wound closure in breast surgery (2004) Surgery, 136, pp. 593-599; Bernard, L., Doyle, J., Friedlander, S.F., Eichenfield, L.F., Gibbs, N.F., Cunningham, B.B., A prospective comparison of octylcya-noacrylate tissue adhesive (dermabond) and suture for the closure of excisional wounds in children and adolescents (2001) Arch Dermatol, 137, pp. 1177-1180; Matin, S.F., Prospective randomized trial of skin adhesive versus sutures for closure of 217 laparoscopic port-site incisions (2003) J Am Coll Surg, 196, pp. 845-853; Bhende, S., Rothenburger, S., Spangler, D.J., Dito, M., In vitro assessment of microbial barrier properties of Dermabond( topical skin adhesive (2002) Surg Infect, 3, pp. 251-257; Rogerson, L., Mason, G.C., Roberts, A.C., Preliminary experience with twenty perineal repairs using Indermil tissue adhesive (2000) Eur J Obstet Gynecol Reprod Biol, 88, pp. 139-142; Bowen, M.L., Selinger, M., Episiotomy closure comparing enbucrilate tissue adhesive with conventional sutures (2002) Int J Gynecol Obstet, 78, pp. 201-205; Adoni, A., Anteby, E., The use of Histoacryl for the episiotomy repair (1991) Br J Obstet Gynaecol, 98, pp. 476-478; Man, J., Quinn, J., Cyanoacrylate tissue adhesives (1997) Am J Cosm Surg, 14, pp. 413-416; Maw, J.L., Quinn, J.V., Wells, G.A., Ducic, Y., Odell, P.F., Lamothe, A., A prospective comparison of octylcyanoacrylate tissue adhesive and suture for the closure of head and neck incisions (1997) J Otolaryngol, 26, pp. 26-30
Keywords: adult; article; clinical trial; comparative study; controlled clinical trial; controlled study; cyanoacrylic acid octyl ester; edema; episiotomy; Episiotomy closure; Female; granuloma; human; Humans; injury; major clinical study; obstetric care; pain; pain assessment; Perineal repair; perineum; perineum injury; polyglactin; priority journal; questionnaire; randomized controlled trial; sexual intercourse; Skin; Skin adhesive; suture; Suture Techniques; suturing method; Tissue adhesive; Tissue Adhesives; treatment outcome; vaginal delivery; wound closure; wound dehiscence; Wounds and Injuries

3-D biomodelling technology for maxillofacial reconstruction - Oliveira, M.; Sooraj Hussain, N.; Dias, A.G.; Lopes, M.A.; Azevedo, L.; Zenha, H.; Costa, H.; Santos, J.D. (Materials Science and Engineering CMater. Sci. Eng. C, 2008)
Biomodel is a product of rapid prototyping process that represents a new approach for surgical planning and simulation. Biomodels were found to be particularly effective to locate an exact defect with good measurement accuracy and without any risk to the patients' health. These models could provide surgeons a realistic impression of complex structures before surgical intervention, allowing a define diagnosis and a precise preoperative simulation of skeleton modifying interventions. This work reports on the application of innovative 3-D biomodelling technology in the maxillofacial reconstruction. This technology allows for the calculation of the exact contours, angulations, length and general morphology of iliac crest and fibula flaps for maxillofacial reconstruction in a total of 28 clinical cases. Clinical results have shown that by using this technique, much better facial symmetry and improved functionality were achieved after surgery, which resulted in enormous benefits for treated patients. © 2008 Elsevier B.V. All rights reserved.
Cited By (since 1996): 3Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.msec.2008.02.007Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Instituto de Engenharia Biomédica (INEB), Laboratório de Biomateriais, Rua Campo Alegre, 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptReferences: Pessa, J.E., (2001) Am. J. Orthod. Dentofac. Orthop., 119, p. 117;Poukens, J., Haex, J., Riediger, D., (2003) Comput. Aided Surg., 8 (3), p. 146; Brown, G.A., Milner, B., Firoozbakhsh, K., (2002) J. Orthop. Trauma, 16 (5), p. 347; Berry, E., Brown, J.M., Connell, M., Craven, C.M., Efford, N.D., Radjenovic, A., Smith, M.A., (1997) Med. Eng. Phys., 19 (1), p. 90; Urso, P.S.D., Barker, T.M., Earwaker, W.J., Bruce, L.J., Atkinson, R.L., Lanigan, M.W., Arvier, J.F., Effeney, D.J., (1999) J. Cranio-Maxillo-Facial Surg., 27, p. 30; Urso, P.S.D., Thompson, R.G., (1998) Aust. N.Z. J. Obstet. Gynaecol., 38, p. 205; Clair, J.J., (1996) J. Mater. Process. Technol., 57, p. 393; Pham, D.T., Gault, R.S., (1998) Int. J. Mach. Tools Manuf., 38, p. 1257; Onuh, S.O., Hon, K.K.B., (1998) Int. J. Mach. Tools Manuf., 38, p. 329; Barker, T.M., Earwaker, W.J., Lisle, D.A., (1994) Australas. Radiol., 38, p. 106; Peckitt, N.S., (1999) Br. J. Oral Maxillofac. Surg., 37, p. 353; Holck, D.E.E., Boyd Jr., E.M., Ng, J., Mauffray, R.O., B, (1999) Ophthalmology, 106, p. 1214; Pessa, J.E., Desvigne, L.D., Lambros, V.S., Nimerick, J., Sugunan, B., Zadoo, V.P., (1999) Aesthet. Plast. Surg., 23, p. 337; Gutierres, M., Dias, A.G., Lopes, M.A., Sooraj Hussain, N., Cabral, A.T., Almeida, L., Santos, J.D., (2007) J. Mater. Sci. Mater. Med., 18, p. 2377; Gauthier, O., Bouler, J.M., Aguado, E., Pilet, P., Daculsi, G., (1998) Biomaterials, 19 (1-3), p. 133; Lu, J.X., Flautre, B., Anselme, K., Hardouin, P., Gallur, A., Descamps, M., Thierry, B., (1999) J. Mater. Sci., Mater. Med., 10 (2), p. 111; Martina, M., Subramanyam, G., Weaver, J.C., Hutmacher, D.W., Morse, D.E., Valiyaveettil, S., (2005) Biomaterials, 26 (28), p. 5609; Moroni, L., de Wijn, J.R., van Blitterswijk, C.A., (2006) Biomaterials, 27 (7), p. 974; Sanghera, B., Naique, S., Papaharilaou, Y., Amis, A., (2001) Rapid Prototyping J., 7 (5), p. 275; Pentecost, J.O., Icardo, J., Thornburg, K.L., (1999) Comput. Med. Imaging Graph., 23, p. 45; Urso, P.S.D., Atkinson, R.L., Lanigan, M.W., Earwaker, W.J., Bruce, L.J., Holmes, A., Barker, T.M., Thompson, RG., (1998) Br. J. Plast. Surg., 51, p. 522
Keywords: 3D Biomodelling; Biomodels; Complex structures; Concurrent engineering; Facial symmetries; Free flap designing; Health risks; Job analysis; Maxillofacial reconstruction; Measurement accuracies; New approaches; Process engineering; Prototyping processes; Rapid prototyping; Repair; Restoration; Surgical interventions; Surgical planning; Three dimensional

Bone ingrowth in macroporous Bonelike ® for orthopaedic applications - Gutierres, M.; Lopes, M.A.; Sooraj Hussain, N.; Lemos, A.F.; Ferreira, J.M.F.; Afonso, A.; Cabral, A.T.; Almeida, L.; Santos, J.D. (Acta BiomaterialiaActa Biomater., 2008)
The aim of this study was to evaluate the biological behaviour of porous scaffold structures of Bonelike ® which is suitable for either direct clinical use or tissue engineering applications. Porous cylindrical specimens 8 × 10 mm were implanted in the lateral aspect of the tibia of 13 patients (mean age 54 years), during osteotomy surgery for the treatment of medial compartment osteoarthritis of the knee. Implanted cylinders were retrieved at the same time as the removal of the blade plates at 3, 6, 9 and 12 months. Scanning electron microscopy and histological evaluations were performed to observe the biological responses of human bone tissue to porous Bonelike ®. The penetration depth was determined for all implantation periods, and after 6 months it was already possible to see new bone in the centre of the implanted cylinders, which gives 100% of penetration depth for all implantations periods except for 3 months when bone could only be seen in the peripherical region. Regarding the percentage of the area covered by new bone calculated from two-dimensional histological sections, values of 53 ± 15, 76 ± 12 and 88 ± 9% were achieved for 6, 9 and 12 months, respectively. Due to its structural features porous Bonelike ® permitted effective vascularization and bone ingrowth, and therefore was fully osteointegrated as shown in the histological surveys. A slow biomaterial degradation with implantation time is envisaged since the material has displayed surface degradation. Bonelike ® scaffolds show potential for complete ingrowth of osseous tissue and restoration of vascularization throughout the defected site. © 2007.
Cited By (since 1996): 13Export Date: 21 November 2012Source: Scopusdoi: 10.1016/j.actbio.2007.06.009PubMed ID: 17716960Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; FEUP - Faculdade de Engenharia, Universidade do Porto, Rua Dr. Roberto Frias, 4200-465 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: Bone SubstitutesTradenames: BonelikeReferences: Akamatsu, Y., Koshino, T., Saito, T., Wada, J., Changes in osteosclerosis of the osteoarthritic knee after high tibial osteotomy (1997) Clin Orthop, 334, pp. 207-214;Coventry, M.B., Ilstrup, D.M., Wallrichs, S.L., Proximal tibial osteotomy. A critical long-term study of eighty-seven cases (1993) J Bone Joint Surg, 75 -A, pp. 196-201; Hernigou, P., Medevielle, D., Debeyre, J., Goutallier, D., Proximal tibial osteotomy for osteoarthritis with varus deformity. A ten to thirteen-year follow-up study (1987) J Bone Joint Surg Am, 69, pp. 332-354; Hernigou, P., Ma, W., Open wedge tibial osteotomy with acrylic bone cement as bone substitute (2001) Knee, 8, pp. 103-110; Koshino, T., Murase, T., Saito, T., Medial opening-wedge high tibial osteotomy with use of porous hydroxyapatite to treat medial compartment osteoarthritis of the knee (2003) J Bone Joint Surg Am, 85, pp. 78-85; Simske SJ, Ayers RA, Bateman TA. Porous Materials for Bone Engineered. In: Materials Science Forum. Zurich: Trans Tech Publications; 1997. Vol. 250, pp. 151-182Hing, K.A., Bone repair in the twenty-first century: biology, chemistry or engineering? (2004) Philos Trans A Math Phys Eng Sci, 362 (1825), pp. 2821-2850; Hui, P.W., Leung, P.C., Sher, A., Fluid conductance of cancellous bone graft as a predictor for graft-host interface healing (1996) J Biomech, 29 (1), pp. 123-132; Ben-Nissan, B., Natural bioceramics: from coral to bone and beyond (2003) Curr Opin Solid State Mater Sci, 7 (4-5), p. 283; Shors, E.C., Holmes, R.E., Porous hydroxyapatite (1993) Introduction to Biomaterials, pp. 181-198. , Hench L.L., and Wilson J. (Eds), World Scientific, Singapore; Prado da Silva, M.H., Lemos, A.F., Gibson, I.R., Ferreira, J.M.F., Santos, J.D., Porous glass reinforced hydroxyapatite materials produced with different organic additives (2002) J Non-Cryst Solids, 304, pp. 286-292; Prado da Silva, M.H., Lemos, A.F., Ferreira, J.M.F., Lopes, M.A., Santos, J.D., Production of porous biomaterials based on glass reinforced hydroxyapatite composites (2002) Key Eng Mater, 230-232, pp. 483-486; Rocha, J., Lemos, A., Agathopoulos, S., Valério, P., Kannan, S., Oktar, F., Scaffolds for bone restoration from cuttlefish (2005) Bone, 37 (6), pp. 850-857; Sepulveda, P., Binner, J.G.P., Processing of cellular ceramics by foaming and in situ polymerization of organic monomers (1999) J Eur Ceram Soc, 19 (12), pp. 2059-2066; Ozgur Engin, N., Cuneyt Tas, A., Manufacture of macroporous calcium hydroxyapatite bioceramics (1999) J Eur Ceram Soc, 19 (13-14), pp. 2569-2572; Peng, H.X., Fan, Z., Evans, J.R.G., Busfield, J.J.C., Microstructure of ceramic foams (2000) J Eur Ceram Soc, 20 (7), pp. 807-813; Komlev Vladimir, S., Barinov Serguei, M., Koplik Elena, V., A method to fabricate porous spherical hydroxyapatite granules intended for time-controlled drug release (2002) Biomaterials, 23 (16), pp. 3449-3454; Milosevski, M., Bossert, J., Milosevski, D., Gruevska, N., Preparation and properties of dense and porous calcium phosphate (1999) Ceram Int, 25, pp. 693-696; Tadic, D., Beckmann, F., Schwarz, K., Epple, M., A novel method to produce hydroxyapatite objects with interconnecting porosity that avoids sintering (2004) Biomaterials, 25, pp. 3335-3340; Lemos, A.F., Santos, J.D., Ferreira, J.M.F., Influence of characteristics of the starting hydroxyapatite powders and of deagglomeration procedure, on rheological behaviour of the suspensions (2004) Mater Sci Forum, 455-456, pp. 361-365; Lemos, A.F., Ferreira, J.M.F., Porous bioactive calcium carbonate implants processed by starch consolidation (2000) J Mat Sci Eng C, C11, pp. 35-40; Lemos, A.F., Ferreira, J.M.F., Combining foaming and starch consolidation methods to develop macroporous HA implants (2004) Key Eng Mater, 254-256, pp. 1041-1044; Lemos, A.F., Santos, J.D., Ferreira, J.M.F., New method for the incorporation of soluble bioactive glasses to reinforce porous HA structures (2004) Key Eng Mater, 254-256, pp. 1033-1036; Gauthiera, O., Boulerb, J.M., Aguadoa, E., Piletb, P., Daculsi, G., Macroporous biphasic calcium phosphate ceramics: influence of macropore diameter and macroporosity percentage on bone ingrowth (1998) Biomaterials, 19, pp. 133-139; Hing, A.K., Best, S.M., Tanner, K.E., Bonfield, W., Revell, P.A., Mediation of bone ingrowth in porous hydroxyapatite bone graft substitutes (2004) J Biomed Mater Res, 68 A, pp. 187-200; Rubin, P.A., Popham, J.K., Bilyk, J.R., Shore, J.W., Comparison of fibrovascular ingrowth into hydroxyapatite and porous polyethylene orbital implants (1994) Ophthal Plast Reconstr Surg, 10 (2), pp. 96-103; Hing, K.A., Annaz, B., Saeed, S., Revell, P.A., Buckland, T., Microporosity enhances bioactivity of synthetic bone graft substitutes (2005) J Mater Sci: Mater Med, 16, pp. 467-475; Klawitter, J.J., Bagwell, J.G., Weinstein, A.M., Sauer, B.W., An evaluation of bone growth into porous high density polyethylene (1976) J Biomed Mater Res, 10 (2), pp. 311-323; Hing, K.A., Best, S.M., Tanner, K.E., Bonfield, W., Revell, P.A., Quantification of bone ingrowth within bone-derived porous hydroxyapatite implants of varying density (1999) J Mater Sci: Mater Med, 10, pp. 663-670; Hing, K.A., Best, S.M., Tanner, K.E., Bonfield, W., Revell, P.A., Biomechanical assessment of bone ingrowth in porous hydroxyapatite (1997) J Mater Sci: Mater Med, 8, pp. 731-736; Ayers, R.A., Wolford, L.M., Bateman, T.A., Ferguson, V.L., Simske, S.J., Quantification of bone ingrowth into porous block hydroxyapatite in humans (1999) J Biomed Mater Res, 47, pp. 54-59; Lu, J.X., Flautre, B., Anselme, K., Hardouin, P., Gallur, A., Descamps, M., Role of interconnections in porous bioceramics on bone recolonization in vitro and in vivo (1999) J Mater Sci: Mater Med, 10 (2), pp. 111-120; Eggli, P.S., Muller, W., Schenk, R.K., Porous hydroxyapatite and tricalcium phosphate cylinders with two different pore size ranges implanted in the cancellous bone of rabbits - A comparative histomorphometric and histologic study of bony ingrowth and implant substitution (1988) Clin Orthop Relat Res, 232, pp. 127-138; Kuhne, J.H., Bartl, R., Frisch, B., Hammer, C., Jansson, V., Zimmer, M., Bone formation in coralline hydroxyapatite. Effects of pore size studied in rabbits (1994) Acta Orthop Scand, 65 (3), pp. 246-252; Holmes, R., Mooney, V., Bucholz, R., Tencer, A., A coralline hydroxyapatite bone graft substitute. Preliminary report (1984) Clin Orthop Relat Res, 188, pp. 252-262; Lopes, M.A., Knowles, J.C., Santos, J.D., Structural insights of glass-reinforced hydroxyapatite composites by Rietveld refinement (2000) Biomaterials, 21 (18), pp. 1905-1910; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., Glass-reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39 (2), pp. 244-251; Santos JD, Hastings G, Knowles JC. Sintered hydroxyapatite compositions and method for the preparation thereof. Worldwide Application (PCT), Patent No. 1 189 851, 1999Lopes, M.A., Monteiro, F.J., Santos, J.D., Glass-reinforced hydroxyapatite composites: fracture toughness and hardness dependence on microstructural characteristics (1999) Biomaterials, 20 (21), pp. 2085-2090; Lopes, M.A., Monteiro, F.J., Santos, J.D., Glass-reinforced hydroxyapatite composites: Secondary phase proportions and densification effects on biaxial bending strength (1999) J Biomed Mater Res, 48 (5), pp. 734-740; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., Hydrophobicity, Surface tension and Zeta potential measurements of glass reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., Direct and Indirect effects of P 2O 5 - glass reinforced - hydroxyapatite composites and growth and function of osteoblast-like cells (2000) Biomaterials, 21, pp. 1165-1172; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibiae of rabbits (2001) J Biomed Mater Res, 54, pp. 463-469; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., HA and Double layer HA-P 2O 5/CaO Glass coatings: influence of chemical composition on human bone marrow cells osteoblastic behaviour (2001) J Mater Sci: Mater Med, 12, pp. 629-638; Gutierres, M., Hussain, N.S., Afonso, A., Almeida, L., Cabral, T., Lopes, M.A., Biological behaviour of Bonelike ® graft implanted in the tibia of humans (2005) Key Eng Mater, 17, pp. 1041-1044; Duarte, F., Santos, J.D., Afonso, A., Medical applications of Bonelike ® in maxillofacial surgery (2004) Adv Mater Forum, pp. 370-373; Lobato, J.V., Hussain, N.S., Botelho, C.M., Titanium dental implants coated with Bonelike ®: clinical case report (2006) Thin Solid Films, 515, p. 279; Coventry, M.B., Osteotomy of the upper portion of the tibia for degenerative arthritis of the knee: a preliminary report (1965) J Bone Joint Surg Am, 47, pp. 984-990; Coventry, M.B., Upper tibia osteotomy for gonarthrosis. The evolution of the operation in the last 18 years and long term results (1979) Orthop Clin North Am, 10, pp. 191-210; Coventry, M.B., Current concepts review. Upper tibia osteotomy for osteoarthritis (1985) J Bone Joint Surg Am, 67 A, pp. 1136-1140
Keywords: adult; aged; article; biomaterial; bone defect; Bone graft; bone growth; Bone Regeneration; Bone Substitutes; bone tissue; Bonelike; clinical article; controlled study; Female; histology; human; human tissue; Humans; implant; knee osteoarthritis; male; materials testing; Microscopy, Electron, Scanning; Middle Aged; molecular scaffold; Orthopaedic; orthopedics; Osseointegration; Osteoarthritis; osteotomy; porosity; Porous materials; priority journal; Prostheses and Implants; Scanning electron microscopy; tibia; Time Factors; Tissue engineering; tissue section; vascularization; ®

Data classification with multilayer perceptrons using a generalized error function - Silva, L.M.; Marques de Sá, J.; Alexandre, L.A. (Neural NetworksNeural Netw., 2008)
The learning process of a multilayer perceptron requires the optimization of an error function E (y, t) comparing the predicted output, y, and the observed target, t. We review some usual error functions, analyze their mathematical properties for data classification purposes, and introduce a new one, E Exp, inspired by the Z-EDM algorithm that we have recently proposed. An important property of E Exp is its ability to emulate the behavior of other error functions by the sole adjustment of a real-valued parameter. In other words, E Exp is a sort of generalized error function embodying complementary features of other functions. The experimental results show that the flexibility of the new, generalized, error function allows one to obtain the best results achievable with the other functions with a performance improvement in some cases. © 2008 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: NNETEdoi: 10.1016/j.neunet.2008.04.004PubMed ID: 18572384Language of Original Document: EnglishCorrespondence Address: Silva, L.M.; INEB-Instituto de Engenharia Biomédica, Porto, Portugal; email: lmsilva@fe.up.ptReferences: Baum, E.B., Wilczek, F., Supervised learning of probability distributions by neural networks (1987) NIPS, pp. 52-61. , Anderson D.Z. (Ed), American Institute of Physics;Bishop, C., (1995) Neural networks for pattern recognition, , Oxford University Press; Blake, C., & Merz, C. (1998). UCI repository of machine learning databases. University of California, Irvine, Dept. of Information and Computer SciencesForina, M., Armanino, C., Eigenvector projection and simplified non-linear mapping of fatty acid content of italian olive oils (1981) Annali di Chimica (Rome), 50, pp. 127-155; Gish, H. (1990). A probabilistic approach to the understanding and training of neural network classifiers. In Proceedings of the 1990 IEEE international conference on acoustics, speech, and signal processingHampshire, J., Waibel, A., A novel objective function for improved phoneme recognition using time-delay neural networks (1990) IEEE Transactions on Neural Networks, 1 (2), pp. 216-228; Hinton, G.E., Connectionist learning procedures (1989) Artificial Intelligence, 40 (1-3), pp. 185-234; Jacobs, R., Jordan, M., Nowlan, S., Hinton, G., Adaptive mixtures of local experts (1991) Neural Computation, 3, pp. 79-87; Møller, M. (1993). Efficient training of feed-forward neural networks. Ph.D. thesis. Computer Science Department - Aarhus UniversityMarques de Sá, J., (2001) Pattern recognition: Concepts, methods and applications, , Springer Verlag; Matsuoka, K., & Yi, J. (1991). Backpropagation based on the logarithmic error function and elimination of local minima. In Proceedings of the 1990 IEEE international joint conference on neural networksRichard, M., Lippmann, R., Neural network classifiers estimate bayesian a posteriori probabilities (1991) Neural Computation, 3, pp. 461-483; Santos, J., Alexandre, L., & Marques de Sá, J. (2004). The error entropy minimization algorithm for neural network classification. In int. conf. on recent advances in soft computingSilva, L., Alexandre, L., Marques de Sá, J., Neural network classification: Maximizing zero-error density (2005) LNCS, 3686, pp. 127-135. , ICAPR 2005; Silva, L., Alexandre, L.A., & Marques de Sá, J. (2006). New developments of the Z-EDM algorithm. In Proceedings of the sixth international conference intelligent systems design and applications: Vol. 1 (pp. 1067-1072)Silva, L., Marques de Sá, J., & Alexandre, L. (2005). Neural network classification using Shannon's entropy. In European symposium on artificial neural networksSilverman, B., (1986) Density estimation for statistics and data analysis, , Chapman & Hall; Solla, S.A., Levin, E., Fleisher, M., Accelerated learning in layered neural networks (1988) Complex Systems, 2 (6), pp. 625-639
Keywords: algorithm; Algorithms; analytical error; article; calculation; Classification; Complementary features; Cybernetics; data analysis; Data classification; Data classifications; Data Interpretation, Statistical; Electric loads; entropy; Error functions; learning; Learning processes; mathematical analysis; Mathematical properties; Models, Statistical; Multilayer neural networks; Multilayer perceptron; Multilayer perceptrons; Multilayers; Neural networks; Neural Networks (Computer); Pattern recognition systems; perceptron; Performance improvements; priority journal; Probability density function

Frequency domain and entropy analysis of fetal heart rate: Appealing tools for fetal surveillance and pharmacodynamic assessment of drugs - Gonçalves, H.; Rocha, A.P.; Ayres-de-Campos, D.; Bemardes, J. (Cardiovascular and Hematological Disorders - Drug TargetsCardiovasc. Hematol. Disord. Drug Targets, 2008)
Recently, frequency domain and entropy analysis of fetal heart rate (FHR) have been assessed in several studies, providing new insights into physiologic regulatory mechanisms, constituting appealing tools for pharmacodynamic assessment, namely during fetal life. There is evidence that entropy and frequency domain analysis convey information on cortical and autonomic nervous system activities, respectively. Use of internal versus external FHR acquisition sensors and the signal sampling frequency may dramatically affect results. Most FHR frequency domain indices are significantly increased with rising fetal activity, namely during active wakefulness and active sleep, whereas the opposite occurs with nonlinear indices. This is in favour of increased activity of the autonomous nervous system and decreased activity of the central nervous system complexity control systems, during periods of fetal activity. Progression of labor is associated with a significant increase in FHR frequency domain indices, whereas entropy indices are significantly decreased. This denotes activation of the autonomic nervous system in the final minutes of labour, associated with decreased central nervous system activity. The emerging knowledge on FHR frequency domain and entropy analysis substantiates a continued interest of these methods in evaluation of the fetal pathophysiologic regulatory mechanisms, and opens new perspectives for clinical and pharmacodynamic assessment. © 2008 Bentham Science Publishers Ltd.
Cited By (since 1996): 1Export Date: 21 November 2012Source: Scopusdoi: 10.2174/187152908784533720Language of Original Document: EnglishCorrespondence Address: Gonçalves, H.; Departamento de Matemática Aplicada, Faculdade de Ciências, Universidade do Porto, Rua do Campo Alegre 687, 4169-007 Porto, Portugal; email: hernani.goncalves@fc.up.ptChemicals/CAS: atropine, 51-55-8, 55-48-1; betamethasone, 378-44-9; lidocaine, 137-58-6, 24847-67-4, 56934-02-2, 73-78-9; magnesium sulfate, 7487-88-9; opiate, 53663-61-9, 8002-76-4, 8008-60-4; propranolol, 13013-17-7, 318-98-9, 3506-09-0, 4199-09-1, 525-66-6; salbutamol, 18559-94-9References: Task-Force. Heart rate variability. Standards of measurement, physiological interpretation, and clinical use. Task Force of the European Society of Cardiology and the North American Society of Pacing and Electrophysiology (1996) Eur. Heart J, 17, pp. 354-381;Beckers, F., Verheyden, B., Aubert, A.E., Aging and nonlinear heart rate control in a healthy population (2006) Am. J. Physiol. Heart Circ. Physiol, 29, pp. H2560-H2570; Pincus, S.M., Minkin, M.J., Assessing sequential irregularity of both endocrine and heart rate rhythms (1998) Curr. Opin. Obstet. Gynecol, 1 (4), pp. 281-291; Rooth, G., Huch, A., Huch, R., Guidelines for the use of fetal monitoring (1987) Int. J. Gynecol. Obstet, 25, pp. 159-167; American College of Obstetricians and Gynecologists. ACOG Practice Bulletin. Clinical Management Guidelines for Obstetrician-Gynecologists, Number 70, December 2005 (2005) Int. J. Gynecol. Obstet, 1, pp. 1453-1460. , ACOG; (2001) Royal College of Obstetricians and Gynaecologists. Evidence-Based Clinical Guideline Number 8. The Use of Electronic Fetal Monitoring, , RCOG, Royal College of Obstetricians and Gynaecologists: London; International Federation of Gynecology and Obstetrics. Intrapartum surveillance: Recommendations on current practice and overview of new developments. FIGO Study Group on the Assessment of New Technology. International Federation of Gynecology and Obstetrics (1995) Int. J. Gynecol. Obstet, 49 (2), pp. 213-221. , FIGO; National Institute of Child Health and Human Development Research Planning Worlshop. Electronic fetal heart rate monitoring: Research guidelines for interpretation (1997) Am. J. Obstet. Gynecol, 177, pp. 1385-1390. , NICH; Dawes, G.S., Moulden, M., Redman, C.W.G., System 8000 - Computerized antenatal FHR analysis (1991) J. Perinat. Med, 19 (1-2), pp. 47-51; Bernardes, J., Moura, C., Marques-de-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J. Perinat. Med, 19, pp. 61-65; Ayres-de-Campos, D., Bernardes, J., Garrido, A., Marques-de-Sá, J., Pereira-Leite, L., SisPorto 2.0: A program for automated analysis of cardiotocograms (2000) J. Mat. Fet. Med, 9, pp. 311-318; Bernardes, J., Ayres-de-Campos, D., Costa-Pereira, A., Pereira-Leite, L., Garrido, A., Objective computerized fetal heart rate analysis (1998) Int. J. Gynecol. Obstet, 2, pp. 141-147; Bernardes, J., Costa-Pereira, A., The effect of different sampling intervals on the measurement of intrapartum fetal heart rate variability. Letter to the Editor (1997) Obstet. Gynecol, 9, pp. 318-319; Ayres-de-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in expert's classification of cardiotocograms and subsequent clinical decision (1999) Br. J. Obstet. Gynecol, 1, pp. 1307-1310; Ayres-de-Campos, D., Bernardes, J., Early, variable and late decelerations: Can a consensus be reached in their identification? (1999) Int. J. Gynecol. Obstet, 5 (3), pp. 305-306; Grant, J.M., The fetal heart rate trace is normal, isn't it? Observer agreement of categorical assessments (1991) Lancet, 337, pp. 215-218; Bernardes, J.; Costa-Pereira, A. Efficacy and safety of intrapartum electronic fetal monitoring: An update. Obstet. Gynecol., 1996}, 87 3, 476-477Bernardes, J., Costa-Pereira, A., Admission cardiotocography (2003) Lancet, 3 (1), p. 1741; Alfirevic, Z., Devane, D., Gyte, G.M.L., Continuous cardiotocography (CTG) as a form of electronic fetal monitoring (EFM) for fetal assessment during labour (2006) Coch. Data. Sys. Rev, 3; Pincus, S., Viscarello, R., Approximate Entropy: A regularity measure for fetal heart rate analysis (1992) Obstet. Gynecol, 79 (2), pp. 249-255; Signorini, M.G., Magenes, G., Cerrutti, S., Arduini, D., Linear and nonlinear parameters for the analysis of fetal heart rate signal from cardiotacographic recordings (2003) IEEE Trans. Biomed. Eng, 5 (3), pp. 365-373; Gonçalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Linear and nonlinear fetal heart rate analysis of normal and acidemic fetuses in the minutes preceding delivery (2006) Med. Biol. Eng. Comput, 44 (1), pp. 847-855; Gonçalves, H., Bernardes, J., Rocha, A.P., Ayres-de-Campos, D., Linear and nonlinear analysis of heart rate patterns associated with fetal behavioral states in the antepartum period (2007) Early Hum. Dev, 83, pp. 585-591; Parer, J.T., (1997) Handbook of Fetal Heart Rate Monitoring, , W. B. Saunders Company: Philadelphia, Pennsylvania; Oppenheimer, L.W., Lewinsky, R.M., Power spectral analysis of fetal heart rate (1994) Baillieres Clin. Obstet. Gynaecol, 8 (3), pp. 643-661; Suzuki, T., Okamura, K., Kimura, Y., Watanabe, T., Yaegashi, N., Murotsuki, J., Uehara, S., Yajima, A., Power spectral analysis of R-R interval variability before and during the sinusoidal heart rate pattern in fetal lambs (2000) Am. J. Obstet. Gynecol, 182, pp. 1227-1232; Li, X., Tang, D., Zhou, S., Zhou, G., Wang, C., Zhuang, Y., Wu, G., Shen, L., Redistribution of power spectrum of heart rate variability during acute umbilical artery embolism and hypoxemia in late-gestation fetal sheep (2004) Eur. J. Obstet. Gynecol. Reprod. Biol, 114, pp. 137-143; Court, D.J., Parer, J.T., In Research in Perinatal Medicine (1984) Experimental studies of fetal asphyxia and fetal heart rate interpretation, pp. 113-169. , Nathanielsz, P.W, Parer, J.T; Eds, Perinatology Press: New York; vanGeijn, H.P., Developments in CTG analysis (1996) Baillieres Clin. Obstet. Gynaecol, 1 (2), pp. 185-209; Bernardes, J., Costa-Pereira, A., A more objective fetal heart rate baseline estimation (1996) Br. J. Obstet. Gynaecol, 1 (3), pp. 714-715; Ayres-de-Campos, D., Bernardes, J., Marsal, K., Nickelsen, C., Makarainen, L., Banfield, P., Xavier, P., Campos, I., Can the reproducibility of fetal heart rate baseline estimation be improved? (2004) Eur. J. Obstet. Gynecol. Reprod. Biol, 112, pp. 49-54; Ayres-de-Campos, D., Santos, C., Bernardes, J., Prediction of neonatal state by computer analysis of fetal heart rate tracings: The antepartum arm of the SisPorto ® multicentre validation study (2005) Eur. J. Obstet. Gynecol. Reprod. Biol, 118 (1), pp. 52-60; Pincus, S., Approximate entropy as a measure of system complexity (1991) Proc. Natl. Acad. Sci. USA, 88, pp. 2297-2301; Richman, J.S., Moorman, J.R., Physiological time-series analysis using approximate entropy and sample entropy (2000) Am. J. Physiol. Heart. Circ. Physiol, 278, pp. H2039-H2049; Fusheng, Y., Bo, H., Qingyu, T., (1998) Nonlinear biomedical signal processing - Volume II: Dynamical analysis and modelling, pp. 72-91. , Ed, Approximate entropy and its application in biosignal analysis; IEEE Press: New York; Pincus, S., Approximate entropy (ApEn) as a complexity measure (1995) Chaos, 5 (1), pp. 110-117; Hayes, M., (1996) Statistical digital signal processing and modelling, , Jonh Wiley and Sons, Inc.:New York; Boog, G., Analyse informatisée du rythme cardiaque foetal au cours de la grossesse et de l'accouchement (2004) Encyclopédie Médico-Chirurgicale, 148, pp. 1-10. , 5.049-D-23; Gonçalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Internal versus external intrapartum foetal heart rate monitoring: The effect on linear and nonlinear parameters (2006) Physiol. Meas, 27, pp. 307-319; Magenes, G., Signorini, M.G., Arduini, D., Cerutti, S., Fetal heart rate variability due to vibroacoustic stimulation: Linear and nonlinear contribution (2004) Methods Inf. Med, 43 (1), pp. 47-51; Hallak, M.; Martinez-Poyer, J.; Kruger, M.L.; Hassan, S.; Blackwell, S.C.; Sorokin, Y. The effect of magnesium sulfate on fetal heart rate parameters: A randomized, placebo-controlled trial. Am. J. Obstet. Gynecol., 1999, 181 5 Part 1, 1122-1127Swartjes, J.M., van Geijn, H.P., Meinardi, H., Mantel, R., Fetal heart-rate patterns and chronic exposure to antiepileptic drugs (1992) Epilepsia, 33 (4), pp. 721-728; Bernardes, J., Costa-Pereira, A., Ayres-de-Campos, D., van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int. J. Gynecol. Obstet, 57 (1), pp. 33-37; Rotmensch, S., Lev, S., Kovo, M., Efrat, Z., Zahavi, Z., Lev, N., Celentano, C., Ben-Rafael, Z., Effect of betamethasone administration on fetal heart rate tracing: A blinded longitudinal study (2005) Fetal. Diagn. Ther, 2 (5), pp. 371-376; Lunshof, M.S., Boer, K., Wolf, H., Koppen, S., Velderman, J.K., Mulder, E.J.H., Short-term (0-48h) effects of maternal betamethasone administration on fetal heart rate and its variability (2005) Pediatr. Res, 57 (4), pp. 545-549; Beckers, F.; Verheyden, B.; Ramaekers, D.; Swinghedauw, B.; Aubert, A.E. Effects of autonomic blockade on non-linear cardiovascular variability indices in rats. Clin. Exp. Pharmacol. Physiol., 2006, 33 5-, 431-439Georgoulas, G., Stylios, C.D., Groumpos, P.P., Predicting the risk of metabolic acidosis for newborns based on fetal heart rate signal classification using support vector machines (2006) IEEE Trans. Biomed. Eng, 53 (5), pp. 875-884; DiRenzo, G.C., Montani, M., Fioriti, V., Clerici, G., Branconi, F., Pardini, A., Indraccolo, R., Cosmi, E.V., Fractal analysis: A new method for evaluating fetal heart rate variability (1996) J. Perinat. Med, 24 (3), pp. 261-269; Felgueiras, C., Marques-de-Sá, J.P., Bernardes, J., Gama, S., Fractal characterisation of fetal heart rate sequences (1998) Biomed. Eng, 3 (2), pp. 197-201;
Keywords: acidemia; adrenergic receptor stimulating agent; alpha adrenergic receptor blocking agent; anticonvulsive agent; article; atropine; autonomic nervous system function; beta adrenergic receptor blocking agent; betamethasone; Cardiotocography; central depressant agent; central nervous system function; cholinergic receptor blocking agent; chronotropism; Computerized analysis; drug effect; drug mechanism; electronic sensor; entropy; External and internal monitoring; Female; Fetal behavioral states; Fetal heart rate (FHR); Fetal monitoring; fetus; fetus heart rate; fetus monitoring; frequency analysis; Frequency domain and entropy analysis; gestation period; Heart rate variability; Heart Rate, Fetal; human; Humans; instrumentation; labor; lidocaine; local anesthetic agent; magnesium sulfate; mathematical computing; methodology; nonhuman; opiate; pharmacodynamics; physiology; Pregnancy; prenatal screening; propranolol; pulse rate; review; salbutamol; signal detection

Hip fractures cluster in space: An epidemiological analysis in Portugal - De Pina, M.F.; Alves, S.M.; Barbosa, M.; Barros, H. (Osteoporosis InternationalOsteoporosis Int., 2008)
Summary: Using Portuguese hospital registers (2000-2002) we calculated age-standardized incidence rates of hip fractures. Spatial clusters of high incidence rates were found, with annual averages (per 100,000 inhabitants) varying from 154.4 to 572.2 and 77.3 to 231.5 for women and men, respectively. Geographic inequalities in the occurrence of hip fractures were also found. Introduction: The aim of this study was to identify spatial patterns in the incidence of hip fracture in Portugal during the period 2000 to 2002. Methods: From the National Hospital Discharge Register, admissions of patients (50 years of age or more) with low-energy hip fracture were selected. Age-standardized incidence rates in relation to the municipality of the patients' place of residence were calculated. Empirical Bayes estimators were used to smooth the local risk and spatial statistics methods were used to identify spatial clusters. Results: Of 25,634 hip fractures in individuals aged 50 years or more caused by low or moderate impact, 19,759 occurred in women (age, mean±SD, 80.6±8.6 years) and 5,875 in men (age 77.7±10.0 years). Incidence rates increased exponentially with age, being higher in women nation-wide (female to male ratio from 1.5 to 5.1). Significant geographic differences were found: the incidence rates (95% CI) varied from 154.4 (153.6-155.3) to 572.2 (569.5-575.0) in women and 77.3 (76.64-78.05) to 231.5 (229.9-233.0) in men per 100,000 inhabitants. Spatial autocorrelation values (Moran index) were 0.56 and 0.45 for women and men, respectively. Conclusion: Spatial clusters (p<0.0001) of high incidences were identified. Geographic differences in incidence rates were about threefold. Some regions had incidence rates as high as some north European countries. The geographic inequalities could be due to environmental or socioeconomic factors, but further investigation needs to be done to confirm this hypothesis. © 2008 International Osteoporosis Foundation and National Osteoporosis Foundation.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: OSINEdoi: 10.1007/s00198-008-0623-1PubMed ID: 18536955Language of Original Document: EnglishCorrespondence Address: De Pina, M. F.; Laboratório de Biomateriais, INEB - Instituto de Engenharia Biomédica, Rua do Campo Alegre, 823, Porto 4150-180, Portugal; email: fpina@ineb.up.ptReferences: Center, J., Eisman, J., The epidemiology and pathogenesis of osteoporosis (1997) Baillieres Clin Endocrinol Metab, 11, pp. 23-62. , 1;Cooper, C., Melton III, L.J., Marcus, R., Feldman, D., Kelsey, J., Magnitude and Impact of osteoporosis and fractures (1996) Osteoporosis, pp. 419-434. , Academic Press San Diego; Walker-Bone, K., Dennison, E., Cooper, C., Epidemiology of osteoporosis (2001) Rheum Dis Clin North Am, 27, pp. 1-18. , 1; Cummings, S.R., Melton III, L.J., Epidemiology and outcomes of osteoporotic fractures (2002) Lancet, 359, pp. 1761-1767; Cooper, C., Campion, G., Melton, L.J., Hip fractures in the elderly: A world-wide projection (1992) Osteoporos Int, 2, pp. 285-289; Karagas, M.R., Lu-Yao, G.L., Barrett, J.A., Heterogeneity of hip fracture: Age, race, sex, and geographic patterns of femoral neck and trochanteric fractures among the US elderly (1996) Am J Epidemiol, 143, pp. 677-682. , 7; Jordan, K.M., Cooper, C., Epidemiology of osteoporosis (2002) Best Pract Res Clin Rheumatol, 16, pp. 795-806. , 5; Orimo, H., Hashimoto, T., Sakata, K., Trends in the incidence of hip fracture in Japan, 1987-1997: The third nationwide survey (2000) J Bone Miner Metab, 18, pp. 126-131; Kennedy, S., Goodchild, M., Gopal, S., The small number problem and the accuracy of spatial databases (1994) Accuracy of Spatial Databases, pp. 187-196. , Taylor and Francis London; (1995) Interactive Spatial Data Analysis, , Bailey TC, Gatrell AC (eds) Longman, London; Anselin, L., Local indicators of spatial association - LISA (1995) Geogr Anal, 27, pp. 93-115. , 2; Chevalley, T., Herrmann, F.R., Delmi, M., Evaluation of the age-adjusted incidence of hip fractures between urban and rural areas: The difference is not related to the prevalence of institutions for the elderly (2002) Osteoporos Int, 13, pp. 113-118; Sanders, K., Nicholson, G.C., Ugoni, A.M., Fracture rates lower in rural than urban communities: The Geelong Osteoporosis Study (2002) J Epidemiol Community Health, 56, pp. 466-470; Vaz, A.L., Epidemiology and costs of osteoporotic hip fractures in Portugal (1993) Bone, 14, p. 9. , Suppl 1; Lofthus, C.M., Osnes, E.K., Falch, J.A., Epidemiology of hip fractures in Oslo, Norway (2001) Bone, 29, pp. 413-418. , 5; Nydegger, V., Rizzoli, R., Rapin, C.H., Epidemiology of fractures of the proximal femur in Geneva: Incidence, clinical and social aspects (1991) Osteoporos Int, 2, pp. 42-47. , 1; Hernandez, J., Olmos, J.M., Alonso, M.A., Trend in hip fracture epidemiology over a 14-year period in a Spanish population (2006) Osteoporos Int, 17, pp. 464-470; Giversen, I.M., Time trends of age-adjusted incidence rates of first hip fractures: A register-based study among older people in Viborg County, Denmark, 1987-1997 (2006) Osteoporos Int, 17, pp. 552-564; Coster, A., Haberkamp, M., Allolio, B., Incidence of femoral neck fractures in the German Federal Republic in comparison to other countries (1994) Soz Praventivmed, 39, pp. 287-292. , 5; Paspati, I., Galanos, A., Lyritis, G.P., Hip fracture epidemiology in Greece during 1977-1992 (1998) Calcif Tissue Int, 62, pp. 542-547. , 6; Kannus, P., Niemi, S., Parkkari, J., Hip fractures in Finland between 1970 and 1997 and predictions for the future (1999) Lancet, 353, pp. 802-805. , 9155
Keywords: adult; Age Distribution; aged; Aged, 80 and over; article; Bayes Theorem; Bone Density; Cluster Analysis; Databases, Factual; falling; Female; fracture; geographic information system; Geographic information systems; hip fracture; Hip fractures; human; Humans; incidence; international classification of diseases; major clinical study; male; Middle Aged; Osteoporosis; Portugal; priority journal; Risk Factors; sex difference; Sex Distribution; Space-Time Clustering; Spatial analysis; Spatial clusters; Spatial dependency

Injectability of a bone filler system based on hydroxyapatite microspheres and a vehicle with in situ gel-forming ability - Oliveira, S.M.; Barrias, C.C.; Almeida, I.F.; Costa, P.C.; Pena Ferreira, M.R.; Bahia, M.F.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part B Applied BiomaterialsJ. Biomed. Mater. Res. Part B Appl. Biomater., 2008)
The aim of this study was to test the injectability of a bone filler system based on the combination of ceramic microspheres with a gel-like vehicle, for noninvasive surgery. Porous hydroxyapatite microspheres with a uniform size and an average diameter of 535 ± 38 μm were prepared, and their compression strength and friability were tested. The sodium-alginate solution with a concentration of 7.25% (w/v) was used as the vehicle. To promote its in situ gelation, calcium carbonate and D-gluconic-δ-lactone were added to the solution. Microspheres were mixed with the vehicle at different percentages (20-40 wt %). Gelation times in the range of 8-20 min, were obtained, depending on the formulation. Mixtures of HAp microspheres with alginate solution at 7.25% originating a gel in 11 min present an adequate handling time to perform an injection. Their injectability was evaluated using an injection device commonly employed in vertebroplasty surgical procedures, coupled to a texturometer in compression mode. Using an extrusion rate of 0.1 mm/s, the force required to extrude any of the mixtures tested was lower than 100 N. For an extrusion rate of 1 mm/s mixtures with 40 wt % of microspheres were very difficult to inject. Mixtures with 35 wt % of microspheres presented the best compromise between injectability and compression strength of the gelled system. MicroCT analysis revealed a homogeneous distribution of the microspheres inside the vehicle, as well as full interconnection of the intra-microspheres spaces. The compression strength for the gelled systems ranged from 80 kPa (gel itself) to 600 kPa (composite with 40 Wt % of microspheres). © 2008 Wiley Periodicals, Inc.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: JBMRGdoi: 10.1002/jbm.b.31066PubMed ID: 18437700Language of Original Document: EnglishCorrespondence Address: Oliveira, S. M.; Escola Superior de Tecnologia de Viseu (ESTV), Dep. de Eng. Mecânica e Gestão Industrial, 3504-510 Viseu, Portugal; email: serafim@ineb.up.ptChemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; calcium carbonate, 13397-26-7, 13701-58-1, 14791-73-2, 471-34-1; gluconolactonase, 9012-44-6, 9012-73-1; hydroxyapatite, 1306-06-5, 51198-94-8; Bone Substitutes; Durapatite, 1306-06-5; GelsTradenames: Captal S, Plasma BiotalManufacturers: Plasma BiotalReferences: Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., Calcium phosphate-alginate microspheres as enzyme delivery matrices (2004) Biomaterials, 25, pp. 4363-4373;Grabowski, G.A., Leslie, N., Wenstrup, R., Enzyme therapy for Gaucher disease: The first 5 years (1998) Blood Rev, 12, pp. 115-133; Melton, L.J., Melton, L.J., Kan, S.H., Frye, M.A., Wahner, H.W., O'Fallon, W.M., Riggs, B.L., Epidemiology of vertebral fractures in women (1989) Am J Epidemiol, 129, pp. 1000-1011; Carrodeguas, R.G., Lasa, B.V., Del Barrio, J.S., injectable acrylic bone cements for vertebroplasty with improved properties (2004) J Biomed Mater Res B Appl Biomater, 68, pp. 94-104; Hee, H.T., Percutaneous vertebroplasty: Current concepts and local experience (2005) Neurol India, 53, pp. 475-482; Hide, I.G., Gangi, A., Percutaneous vertebroplasty: History, technique and current perspectives (2004) Clin Radiol, 59, pp. 461-467; Verlaan, J.J., Oner, F.C., Verbout, A.J., Dhert, W.J., Temperature elevation after vertebroplasty with polymethylmethacrylate in the goat spine (2003) J Biomed Mater Res B Appl Biomater, 67, pp. 581-585; Hardouin, P., Grados, F., Cotten, A., Cortet, B., Should percutaneous vertebroplasty be used to treat osteoporotic fractures? An update (2001) Joint Bone Spine, 68, pp. 216-221; Berlemann, U., Ferguson, S.J., Nolte, L.P., Heini, P.F., Adjacent vertebral failure after vertebroplasty. A biomechanical investigation (2002) J Bone Joint Surg Br, 84, pp. 748-752; Wilcox, R.K., The biomechanical effect of vertebroplasty on the adjacent vertebral body: A finite element study (2006) Proc Inst Mech Eng [H], 220, pp. 565-572; Uppin, A.A., Hirsch, J.A., Centenera, L.V., Pfiefer, B.A., Pazianos, A.G., Choi, I.S., Occurrence of new vertebral body fracture after percutaneous vertebroplasty in patients with osteoporosis (2003) Radiology, 226, pp. 119-124; Barrias, C.C., Ribeiro, C.C., Barbosa, M.A., Adhesion and proliferation of human osteoblastic cells seeded on injectable hydroxyapatite microspheres (2004) Bioceramics, 254, pp. 877-880; Becker, T.A., Kipke, D.R., Brandon, T., Calcium alginate gel: A biocompatible and mechanically stable polymer for endovascular embolization (2001) J Biomed Mater Res, 54, pp. 76-86; Alsberg, E., Anderson, K.W., Albeiruti, A., Franceschi, R.T., Mooney, D.J., Cell-interactive alginate hydrogels for bone tissue engineering (2001) J Dent Res, 80, pp. 2025-2029; Steinert, A., Weber, M., Dimmler, A., Julius, C., Schutze, N., Noth, U., Cramer, H., Hendrich, C., Chondrogenic differentiation of mesenchymal progenitor cells encapsulated in ultrahigh-viscosity alginate (2003) J Orthop Res, 21, pp. 1090-1097; Wang, L., Shelton, R.M., Cooper, P.R., Lawson, M., Triffitt, J.T., Barralet, J.E., Evaluation of sodium alginate for bone marrow cell tissue engineering (2003) Biomaterials, 24, pp. 3475-3481; Shapiro, L., Cohen, S., Novel alginate sponges for cell culture and transplantation (1997) Biomaterials, 18, pp. 583-590; Eiselt, P., Yeh, J., Latvala, R.K., Shea, L.D., Mooney, D.J., Porous carriers for biomedical applications based on alginate hydrogels (2000) Biomaterials, 21, pp. 1921-1927; Wee, S., Gombotz, W.R., Protein release from alginate matrices (1998) Adv Drug Deliv Rev, 31, pp. 267-285; Draget, K.I., Skjak-Braek, G., Smidsrod, O., Alginate based new materials (1997) Int J Biol Macromol, 21, pp. 47-55; Bajpai, S.K., Sharma, S., Investigation of swelling/degradation behaviour of alginate beads crosslinked with Ca2+ and Ba2+ ions (2004) React Funct Polym, 59, pp. 129-140; Ouwerx, C., Velings, N., Mestdagh, M.M., Axelos, M.A.V., Physico-chemical properties and rheology of alginate gel beads formed with various divalent cations (1998) Polym Gels Networks, 6, pp. 393-408; Paul, W., Sharma, C.P., Development of porous spherical hydroxyapatite granules: Application towards protein delivery (1999) J Mater Sci Mater Med, 10, pp. 383-388; Jarcho, M., Calcium-phosphate ceramics as hard tissue prosthetics (1981) Clin Orthop Relat Res, 157, pp. 259-278; Uda, H., Sugawara, Y., Nakasu, M., Experimental studies on hydroxyapatite powder-carboxymethyl chitin composite: Injectable material for bone augmentation (2006) Br J Plast Surg, 59, pp. 188-196; Xu, H.H., Weir, M.D., Burguera, E.F., Fraser, A.M., Injectable and macroporous calcium phosphate cement scaffold (2006) Biomaterials, 27, pp. 4279-4287; Weiss, P., Gauthier, O., Bouler, J.M., Grimandi, G., Daculsi, G., Injectable bone substitute using a hydrophilic polymer (1999) Bone, 25, pp. 67S-70S; Iooss, P., Le Ray, A.M., Grimandi, G., Daculsi, G., Merle, C., A new injectable bone substitute combining poly(epsilon-caprolactone) microparticles with biphasic calcium phosphate granules (2001) Biomaterials, 22, pp. 2785-2794; Gauthier, O., Khairoun, I., Bosco, J., Obadia, L., Bourges, X., Rau, C., Magne, D., Weiss, P., Noninvasive bone replacement with a new injectable calcium phosphate biomaterial (2000) J Biomed Mater Res A, 66, pp. 47-54; Kuo, C.K., Ma, P.X., Ionically crosslinked alginate hydrogels as scaffolds for tissue engineering, Part 1: Structure, gelation rate and mechanical properties (2001) Biomaterials, 22, pp. 511-521; Oakenfull, D., Scott, A., Stabilization of gelatin by sugars and polyols (1986) Food Hydrocolloyds, 1, pp. 163-175; Poon, C.Y., Tonicity, O., Osmolality and Osmolarity (2006) Philadelphia: The Science and Practice of Pharmacy, pp. 250-265. , 21st ed; Gauthier, O., Bouler, J.M., Weiss, P., Bosco, J., Aguado, E., Daculsi, G., Short-term effects of mineral particle sizes on cellular degradation activity after implantation of injectable calcium phosphate biomaterials and the consequences for bone substitution (1999) Bone, 25, pp. 71S-74S; Gisep, A., Curtis, R., Hanni, M., Suhm, N., Augmentation of implant purchase with bone cements: An in vitro study of injectability and dough distribution (2006) J Biomed Mater Res B Appl Biomater, 77, pp. 114-119; Ginebra, M.P., Rilliard, A., Fernandez, E., Elvira, C., San Roman, J., Planell, J.A., Mechanical and rheological improvement of a calcium phosphate cement by the addition of a polymeric drug (2001) J Biomed Mater Res, 57, pp. 113-118; Krebs, J., Ferguson, S.J., Bohner, M., Baroud, G., Steffen, T., Heini, P.F., Clinical measurements of cement injection pressure during vertebroplasty (2005) Spine, 30, pp. E118-E122; Bohner, M., Baroud, G., Injectability of calcium phosphate pastes (2005) Biomaterials, 26, pp. 1553-1563; Hernandez, L., Gurruchaga, M., Goni, I., Influence of powder particle size distribution on complex viscosity and other properties of acrylic bone cement for vertebroplasty and kyphoplasty (2006) J Biomed Mater Res B Appl Biomater, 77, pp. 98-103; Yoshimine, F., Latta, L.L., Milne, E.L., Sliding characteristics of compression hip screws in the intertrochanteric fracture: A clinical study (1993) J Orthop Trauma, 7, pp. 348-353; Jasper, L.E., Deramond, H., Mathis, J.M., Belkoff, S.M., Material properties of various cements for use with vertebroplasty (2002) J Mater Sci Mater Med, 13, pp. 1-5
Keywords: Alginate; alginic acid; Apatite; article; Average diameter; bioengineering; Bone; bone filler system; Bone Substitutes; Calcium; Calcium carbonate; Ceramic; Ceramic microspheres; Coagulation; Colloids; compression; Compression mode; Compression strengths; Compressive Strength; Computerized tomography; Concentration (process); Data compression; Durapatite; Extrusion; Extrusion rates; Fillers; Forming; Gel-forming ability; Gelation; Gels; gluconolactonase; Handling time; Homogeneous distribution; hydrogel; hydroxyapatite; In situ gelation; in situ hybridization; In-situ; Injectability; injection; Injection (oil wells); Micro-CT; microsphere; Microspheres; Mixtures; non invasive procedure; Particle Size; Porous hydroxyapatite; Sodium; Surgery; Surgical procedures; Uniform size; Vehicles; Vertebroplasty

LEGClust - A clustering algorithm based on layered entropic subgraphs - Santos, J.M.; De Sá, J.M.; Alexandre, L.A. (IEEE Transactions on Pattern Analysis and Machine IntelligenceIEEE Trans Pattern Anal Mach Intell, 2008)
Hierarchical clustering is a stepwise clustering method usually based on proximity measures between objects or sets of objects from a given data set. The most common proximity measures are distance measures. The derived proximity matrices can be used to build graphs, which provide the basic structure for some clustering methods. We present here a new proximity matrix based on an entropic measure and also a clustering algorithm (LEGClust) that builds layers of subgraphs based on this matrix, and uses them and a hierarchical agglomerative clustering technique to form the clusters. Our approach capitalizes on both a graph structure and a hierarchical construction. Moreover, by using entropy as a proximity measure we are able, with no assumption about the cluster shapes, to capture the local structure of the data, forcing the clustering method to reflect this structure. We present several experiments on artificial and real data sets that provide evidence on the superior performance of this new algorithm when compared with competing ones. © 2007 IEEE.
Cited By (since 1996): 8Export Date: 21 November 2012Source: ScopusCODEN: ITPIDdoi: 10.1109/TPAMI.2007.1142Language of Original Document: EnglishCorrespondence Address: Santos, J.M.; Department of Mathematics, ISEP - Polytechnic School of Engineering, R. Dr. A. Bernardino de Almeida 431, 4200-072 Porto, Portugal; email: jms@isep.ipp.ptReferences: Jain, A.K., Dubes, R.C., (1988) Algorithms for Clustering Data, , Prentice Hall International;Jain, A.K., Murty, M.N., Flynn, P.J., Data clustering: A review (1999) ACM Computing Surveys, 31 (3), pp. 264-323; Jain, A., Topchy, A., Law, M., Buhmann, J., Landscape of clustering algorithms (2004) 17th International Conference on Pattern Recognition, 1, pp. 260-263; Berkhin, P., (2002) Survey of clustering data mining techniques, , Accrue Software, San Jose, CA, Tech. Rep; Guha, S., Rastogi, R., Shim, K., CURE: An efficient clustering algorithm for large databases (1998) ACM SIGMOD International Conference on Management of Data, pp. 73-84; Guha, S., Rastogi, R., Shim, K., ROCK: A robust clustering algorithm for categorical attributes (2000) Information Systems, 25 (5), pp. 345-366; Kaufman, L., Rousseeuw, P., (1990) Finding Groups in Data: An Introduction to Cluster Analysis, , New York, NY: John Wiley and Sons; Zhang, T., Ramakrishnan, R., Livny, M., BIRCH: An efficient clustering method for very large databases (1996) ACM SIGMOD Workshop on Research Issues on Data Mining and Knowledge Discovery, pp. 103-114. , Montreal, Canada; Zhang, T., Ramakrishnan, R., Livny, M., BIRCH: A new data clustering algorithm and its applications (1997) Data Mining and Knowledge Discovery, 1 (2), pp. 141-182; Karypis, G., Han, E.-H.S., Kumar, V., Chameleon: Hierarchical clustering using dynamic modeling (1999) IEEE Computer, 32 (8), pp. 68-75; Kamvar, S.D., Klein, D., Manning, C.D., Interpreting and extending classical agglomerative clustering algorithms using a model-based approach (2002) Proceedings of the Nineteenth International Conference on Machine Learning, pp. 283-290. , San Francisco, CA, USA: Morgan Kaufmann Publishers Inc; Johnson, E.L., Mehrotra, A., Nemhauser, G.L., Min-cut clustering (1993) Mathematical Programming, 62, pp. 133-151; Matula, D., Cluster analysis via graph theoretic techniques (1970) Proc. Luisiana Conference on Combinatorics, Graph Theory and Computing, pp. 199-212. , R.C.Mullin, K.B.Reid, and D.P.Roselle, Eds. University of Manitoba, Winnipeg; Matula, D., k-components, clusters and slicings in graphs (1972) SIAM J. Appl. Math, 22 (3), pp. 459-480; Hartuv, E., Schmitt, A., Lange, J., Meier-Ewert, S., Lehrachs, H., Shamir, R., An algorithm for clustering cDNAs for gene expression analysis (1999) RECOMB, pp. 188-197; Hartuv, E., Shamir, R., A clustering algorithm based on graph connectivity (2000) Information Processing Letters, 76 (4-6), pp. 175-181; Wu, Z., Leahy, R., An optimal graph theoretic approach to data clustering: Theory and its application to image segmentation (1993) IEEE Transactions on Pattern Analysis and Machine Learning, 15 (11), pp. 1101-1113; G. Karypis and V. Kumar, Multilevel algorithms for multi-constraint graph partitioning, University of Minnesota, Department of Computer Science/Army HPC Research Center, Minneapolis, Tech. Rep. 98-019, May 1998Fiedler, M., A property of eigenvectors of nonnegative symmetric matrices and its application to graph theory (1975) Czechoslovak Mathematical Journal, 25 (100), pp. 619-633; Chung, F.R.K., (1997) Spectral Graph Theory, (92). , Providence, RI: American Mathematical Society; Shi, J., Malik, J., Normalized cuts and image segmentation (2000) IEEE Transactions on Pattern Analysis and Machine Intelligence, 22 (8), pp. 888-905; Kannan, R., Vempala, S., Vetta, A., On clusterings: Good, bad, and spectral (2000) Proceedings of the 41st Annual Symposium on the Foundation of Computer Science, pp. 367-380; Ding, C., He, X., Zha, H., Gu, M., Simon, H., A min-max cut algorithm for graph partitioning and data clustering (2001) International Conference on Data Mining, pp. 107-114; Ng, A.Y., Jordan, M.I., Weiss, Y., On spectral clustering: Analysis and an algorithm (2001) Advances in Neural Information Processing Systems, 14; Meila, M., Shi, J., A random walks view of spectral segmentation (2001) Eighth International Workshop on Artificial Intelligence and Statistics; Verma, D., Meila, M., (2003) A comparison of spectral clustering algorithms, , Washington University, Tech. Rep. UW-CSE-03-05-01; Ester, M., Kriegel, H.-P., Sander, J., Xu, X., A density-based algorithm for discovering clusters in large spatial databases with noise (1996) 2nd International Conference on Knowledge Discovery and Data Mining, pp. 226-231. , A. Press, Ed; Fukunaga, K., Hostetler, L.D., The estimation of the gradient of a density function, with applications in pattern recognition (1975) IEEE Trans. in Information Theory, 21, pp. 32-40; Cheng, Y., Mean shift, mode seeking, and clustering (1995) IEEE Trans. on Pattern Analysis and Machine Intelligence, 17 (8), pp. 790-799; Comaniciu, D., Meer, P., Mean shift analysis and applications (1999) IEEE International Conference on Computer Vision, pp. 1197-1203; Comaniciu, D., Meer, P., Mean shift: A robust approach toward feature space analisys (2002) IEEE Trans. on Pattern Analysis and Machine Intelligence, 24 (5), pp. 603-619; Fischer, B., Zöller, T., Buhmann, J.M., Path based pairwise data clustering with application to texture segmentation (2001) LNCS - Proceed. of International Workshop on Energy Minimization Methods in Computer Vision and Pattern Recognition, 2134, pp. 235-250; Fischer, B., Buhmann, J.M., Path-based clustering for grouping of smooth curves and texture segmentation (2003) IEEE Transactions on Pattern Analysis and Machine Intelligence, 25 (4), pp. 513-518; Shannon, C., A mathematical theory of communication (1948) Bell System Technical Journal, 27, pp. 379-423,623-656; Renyi, A., Some fundamental questions of information theory (1976) Selected Papers of Alfred Renyi, 2, pp. 526-552; Parzen, E., On the estimation of a probability density function and mode (1962) Annals of Mathematical Statistics, 33, pp. 1065-1076; Xu, D., Príncipe, J., Training mlps layer-by-layer with the information potential (1999) Intl. Joint Conf. on Neural Networks, pp. 1716-1720; H. Li, K. Zhang, and T. Jiang, Minimum entropy clustering and applications to gene expression analysis, in IEEE Computational Systems Bioinformatics Conference, IEEE, Ed., 2004, pp. 142-151Hero, A.O., Ma, B., Michel, O.J., Gorman, J., Applications of entropic spanning graphs (2002) IEEE Signal Processing Magazine, 19 (5), pp. 85-95; Cheng, C.H., Fu, A.W., Zhang, Y., Entropy-based subspace clustering for mining numerical data (1999) International Conference on Knowledge Discovery and Data Mining; Jenssen, R., Hild, I., Erdogmus, K.E.D., Príncipe, J., Eltoft, T., Clustering using renyi's entropy (2003) Proceedings of the International Joint Conference on Neural Networks, pp. 523-528; Gokcay, E., Príncipe, J.C., Information theoretic clustering (2002) IEEE Transactions on Pattern Analysis and Machine Learning, 24 (2), pp. 158-171; Lee, Y., Choi, S., Minimum entropy, k-means, spectral clustering (2004) IEEE International Joint Conference on Neural Networks, 1, pp. 117-122; Lee, Y., Maximum within-cluster association (2005) Pattern Recognition Letters, 26 (10), pp. 1412-1422. , July; J. M. Santos and J. Marques de Sá, Human clustering on bi-dimensional data: An assessment, INEB - Instituto de Engenharia Biomédica, Porto, Portugal, Technical Report 1, October 2005. [Online]. Available: http://www.fe.up.pt/~nnig/papers/ JMS_TechReport2005_1.pdfSilverman, B.W., (1986) Density Estimation for Statistics and Data Analisys, 26. , Chapman & Hall; Bowman, A.W., Azzalini, A., (1997) Applied Smooting Techniques for Data Analysis, , London: Oxford University Press; Jenssen, R., Eltoft, T., Príncipe, J., Information theoretic spectral clustering (2004) Proceedings of the International Joint Conference on Neural Networks, pp. 111-116; Santos, J.M., Marques de Sá, J., Alexandre, L.A., Neural Networks Trained with the EEM Algorithm: Tuning the Smoothing Parameter (2005) 6th WSEAS Int. Conf. on Neural Networks; Proença, H., Alexandre, L.A., UBIRIS: A noisy iris image database (2005) Proceed. of ICIAP 2005 - Intern. Confer. on Image Analysis and Processing, 1, pp. 970-977; (2000), http:// genome-www.stanford.edu/nci60, Stanford NCI60 cancer microarray projectBlake, C., Keogh, E., Merz, C., (1998) UCI repository of machine learning Databases, , http://www.ics.uci.edu/~mlearn/MLRepository.html; Forina, M., Armanino, C., Eigenvector projection and simplified nonlinear mapping of fatty acid content of italian olive oils (1981) Ann. Chim. (Rome), 72, pp. 127-155; G. Karypis, Cluto: Software package for clustering high-dimensional datasets, November 2003, version 2.1.1Karypis, G., (2003) Cluto: A Clustering Toolkit, , University of Minnesota, Department of Computer Science, Minneapolis, MN 55455, November; Sanguinetti, G., Laidler, J., Lawrence, N.D., Automatic determination of the number of clusters using spectral algorithms (2005) International Workshop on Machine Learning for Signal Processing, pp. 55-60; Xu, X., Dbscan, , http://ifsc.ualr.edu/xwxu, Online, Available; Duin, R.P., Dutch handwritten numerals, , http://www.ph.tn.tudelft.nl/~duin; Hubert, L., Arabie, P., Comparing partitions (1985) Journal of Classification, 2 (1), pp. 193-218; Porter, M.F., An algorithm for suffix stripping (1980) Program, 14 (3), pp. 130-137; Hastie, T., Tibshirani, R., Friedman, J., (2001) The Elements of Statistical Learning, , Springer
Keywords: algorithm; Algorithms; article; artificial intelligence; automated pattern recognition; Cluster Analysis; Clustering; Clustering algorithms; computer assisted diagnosis; Distance measurement; Entropic subgraphs; entropy; Graph theory; Graphs; Hierarchical clustering; Hierarchical systems; Image enhancement; Image Interpretation, Computer-Assisted; Imaging, Three-Dimensional; methodology; Pattern Recognition, Automated; reproducibility; Reproducibility of Results; sensitivity and specificity; three dimensional imaging

Linear and complex heart rate dynamics vary with sex in relation to fetal behavioural states - Bernardes, J.; Gonçalves, H.; Ayres-de-Campos, D.; Rocha, A.P. (Early Human DevelopmentEarly Hum. Dev., 2008)
Background: A better understanding of gender influences on fetal heart rate can help to improve analysis of the latter and perhaps elucidate the increased risk of perinatal death that occurs in males. Aim: To assess differences in linear and complex heart rate dynamics according to fetal sex, in the antepartum period of normal term pregnancies, for patterns associated with fetal behavioural states. Study design and subjects: One hundred and eighty seven fetal heart rate segments of 10-minute duration, acquired with a system for computerized analysis of cardiotocograms and classified into fetal behavioural patterns A, B, C or D were analysed. They had been acquired from 24 female and 23 male term fetuses, with uneventful perinatal outcomes. Four different comparative studies between female and male fetuses were conducted, considering different adjustments for gestational age, weight and FHR pattern. Outcome measures: Indices of linear and nonlinear fetal heart rate variability, namely, long-term irregularity index, very low, low and high frequency spectral indices, approximate entropy and sample entropy. Results: Pattern B was the most frequent, both in female and male fetuses. Pattern A was more likely to be associated to female than male fetuses, whereas the opposite occurred with patterns C and D. Linear indices were significantly higher in male than in female fetuses, whereas the opposite occurred with nonlinear indices. Conclusions: Male fetuses exhibited significantly more linear and significantly less complex fetal heart rate activity than female fetuses, expressing signs of a more active autonomous nervous system and of less active complexity control systems. These aspects may need to be considered when interpreting FHR tracings. © 2007 Elsevier Ireland Ltd. All rights reserved.
Cited By (since 1996): 16Export Date: 21 November 2012Source: ScopusCODEN: EHDEDdoi: 10.1016/j.earlhumdev.2007.12.001PubMed ID: 18248921Language of Original Document: EnglishCorrespondence Address: Bernardes, J.; Departamento de Ginecologia e Obstetrícia, Faculdade de Medicina, Universidade do Porto and INEB (Instituto Nacional de Engenharia Biomédica), Porto, Portugal; email: jbernardes@mail.telepac.ptReferences: Ingemarsson, I., Herbst, A., Thorngren-Jerneck, K., Long term outcome after umbilical artery acidaemia at term birth: influence of gender and duration of fetal heart rate abnormalities (1997) Br J Obstet Gynaecol, 104 (10), pp. 1123-1127;Ingemarsson, I., Gender aspects of preterm birth (2003) BJOG, 110 (SUPPL. 20), pp. 34-38; DiPietro, J.A., Hodgson, D.M., Costigan, K.A., Hilton, S.C., Johnson, T.R., Development of fetal movement-fetal heart rate coupling from 20 weeks through term (1996) Early Hum Dev, 44 (2), pp. 139-151; DiPietro, J.A., Costigan, K.A., Shupe, A.K., Pressman, E.K., Johnson, T.R., Fetal neurobehavioral development: associations with socioeconomic class and fetal sex (1998) Dev Psychobiol, 33 (1), pp. 79-91; Ogueh, O., Steer, P., Gender does not affect fetal heart rate variation (1998) Br J Obstet Gynaecol, 105 (12), pp. 1312-1314; Dawes, N.W., Dawes, G.S., Moulden, M., Redman, C.W., Fetal heart rate patterns in term labor vary with sex, gestational age, epidural analgesia, and fetal weight (1999) Am J Obstet Gynecol, 180, pp. 181-187; Lange, S., Van Leeuwen, P., Geue, D., Hatzmann, W., Gronemeyer, D., Influence of gestational age, heart rate, gender and time of day on fetal heart rate variability (2005) Med Biol Eng Comput, 43 (4), pp. 481-486; Gonçalves, H., Bernardes, J., Rocha, A.P., Ayres-de-Campos, D., Linear and nonlinear analysis of heart rate patterns associated with fetal behavioral states in the antepartum period (2007) Early Hum Dev, 83 (9), pp. 585-591; Nijhuis, J.G., Prechtl, H.F., Martin Jr., C.B., Bots, R.S., Are there behavioural states in the human fetus? (1982) Early Hum Dev, 6 (2), pp. 177-195; Gonçalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Internal versus external intrapartum foetal heart rate monitoring: the effect on linear and nonlinear parameters (2006) Physiol Meas, 27 (3), pp. 307-319; Goncalves, H., Rocha, A.P., Bernardes, J., Ayres-de-Campos, D., Linear and nonlinear fetal heart rate analysis of normal and acidemic fetuses in the minutes preceding delivery (2006) Med Biol Eng Comput, 44 (10), pp. 847-855; Ayres-de-Campos, D., Bernardes, J., Garrido, A., Marques-de-Sá, Pereira-Leite, L., SisPorto 2.0 - a program for automated analysis of cardiotocograms (2000) J Matern Fetal Med, 9, pp. 311-318.; Magenes, G., Signorini, M.G., Arduini, D., Classification of cardiotocographic records by neural networks (2000) IJCNN 2000, Proceedings of the IEEE-INNS-ENNS International Joint Conference on Neural Networks, 3, pp. 637-641; Signorini, M.G., Magenes, G., Cerrutti, S., Arduini, D., Linear and nonlinear parameters for the analysis of fetal heart rate signal from cardiotacographic recordings (2003) IEEE Trans Biomed Eng, 50, pp. 365-373; Task force of the European Society of Cardiology and the North American Society of Pacing and Electrophysiology, Heart rate variability - standards of measurement, physiological interpretation and clinical use (1996) Circulation, 17, pp. 354-381; Boog, G., Analyse informatisée du rythme cardiaque foetal au cours de la grosssesse et de l'accouchement (2004) Encyclopédie Médico-Chirurgicale, 148 (5-49 -D-23), pp. 1-10; Suzuki, T., Okamura, K., Kimura, Y., Watanabe, T., Yaegashi, N., Murotsuki, J., Power spectral analysis of R-R interval variability before and during the sinusoidal heart rate pattern in fetal lambs (2000) Am J Obstet Gynecol, 182, pp. 1227-1232; Pincus, S., Approximate entropy as a measure of system complexity (1991) Proc Natl Acad Sci U. S. A., 88, pp. 2297-2301; Richman, J.S., Moorman, J.R., Physiological time-series analysis using approximate entropy and sample entropy (2000) Am J Physiol Heart Circ Physiol, 278, pp. H2039-H2049; Fusheng, Y., Bo, H., Qingyu, T., Approximate entropy and its application in biosignal analysis (1998) Nonlinear biomedical signal processing - Volume II: Dynamical analysis and modelling, pp. 72-91. , Akay M. (Ed), IEEE Press; Pincus, S., Viscarello, R., Approximate entropy: a regularity measure for fetal heart rate analysis (1992) Obstet Gynecol, 79, pp. 249-255; Martinez, W.L., Martinez, A.R., (2002) Computational statistics handbook with MATLAB, , CRC Press; Dudewicz, E., Mishra, S., (1998) Modern Mathematical Statistics, , John Wiley and Sons, Inc; Robles de Medina, P.G., Visser, G.H., Huizink, A.C., Buitelaar, J.K., Mulder, E.J., Fetal behaviour does not differ between boys and girls (2003) Early Hum Dev, 73 (1-2), pp. 17-26; Ryan, S.M., Goldberger, A.L., Pincus, S.M., Mietus, J., Lipsitz, L.A., Gender- and age-related differences in heart rate dynamics: are women more complex than men? (1994) J Am Coll Cardiol, 24 (7), pp. 1700-1707; Jensen-Urstad, K., Storck, N., Bouvier, F., Ericson, M., Lindblad, L.E., Jensen-Urstad, M., Heart rate variability in healthy subjects is related to age and gender (1997) Acta Physiol Scand, 160 (3), pp. 235-241; Beckers, F., Verheyden, B., Aubert, A.E., Aging and nonlinear heart rate control in a healthy population (2006) Am J Physiol Heart Circ Physiol, 290 (6), pp. H2560-H2570; Kuo, T.B., Yang, C.C., Sexual dimorphism in the complexity of cardiac pacemaker activity (2002) Am J Physiol Heart Circ Physiol, 283 (4), pp. H1695-H1702; Groome, L.J., Mooney, D.M., Holland, S.B., Smith, L.A., Atterbury, J.L., Dykman, R.A., Behavioral state affects heart rate response to low-intensity sound in human fetuses (1999) Early Hum Dev, 54 (1), pp. 39-54; Fleisher, L.A., Dipietro, J.A., Johnson, T.R., Pincus, S., Complementary and non-coincident increases in heart rate variability and irregularity during fetal development (1997) Clin Sci (Lond), 92 (4), pp. 345-349; Bernardes, J., Costa-Pereira, A., Ayres-de-Campos, D., van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynecol Obstet, Suppl, 57 (1), pp. 33-37; Ayres-de-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in expert's classification of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynecol, 106, pp. 1307-1310; Bernardes, J., Moura, C., Marques-de-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-65; Bernardes, J., Ayres-de-Campos, D., Costa-Pereira, A., Pereira-Leite, L., Garrido, A., Objective computerized fetal heart rate analysis (1998) Int J Gynaecol Obstet, 62 (2), pp. 141-147; Ayres-de-Campos, D., Costa-Santos, C., Bernardes, J., SisPorto Multicentre Validation Study Group. Prediction of neonatal state by computer analysis of fetal heart rate tracings: the antepartum arm of the SisPorto multicentre validation study (2005) Eur J Obstet Gynecol Reprod Biol, 118 (1), pp. 52-60; Dawes, G.S., Moulden, M., Redman, C.W., Improvements in computerized fetal heart rate analysis antepartum (1996) J Perinat Med, 24 (1), pp. 25-36
Keywords: article; Behavior; Cardiotocography; comparative study; Computerized analysis; Entropy and spectral analysis; Female; Fetal behavioural states and sex; Fetal heart rate; Fetal monitoring; Fetal Movement; fetus; fetus heart rate; Gestational Age; heart hemodynamics; Heart Rate, Fetal; human; Humans; male; normal human; Pregnancy; Pregnancy Outcome; Sex Characteristics; sex difference; SisPorto

Nanocrystalline diamond as a coating for joint implants: Cytotoxicity and biocompatibility assessment - Amaral, M.; Gomes, P.S.; Lopes, M.A.; Santos, J.D.; Silva, R.F.; Fernandes, M.H. (Journal of NanomaterialsJ. Nanomater., 2008)
Nanocrystalline diamond (NCD) coatings combine a very low surface roughness with the outstanding diamond properties, such as superlative hardness, low self-friction coefficient, high wear and corrosion resistance, and biotolerance, which are ideal features for applications in medicine (knee and hip replacement) and surgical tools. The present work presents a comprehensive study of the cytotoxicity and biocompatibility of NCD films grown by hot-filament chemical vapour deposition (HFCVD) technique, aiming such future applications. Cytotoxicity was evaluated in vitro by seeding human gingival fibroblasts on the NCD surface for 14 days, while specific biocompatibility was assessed on samples seeded with human bone marrow-derived osteoblasts during 21 days. The NCD coatings proved to be noncytotoxic in the preliminary human gingival fibroblast cell cultures, as denoted by a notable sequence of cell attachment, spreading, and proliferation events. In the specific biocompatibility assay envisaging bone tissue applications, NCD coatings induced human osteoblast proliferation and the stimulation of differentiation markers, compared to standard polystyrene tissue culture plates. Copyright © 2008.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusArt. No.: 894352doi: 10.1155/2008/894352Language of Original Document: EnglishCorrespondence Address: Silva, R. F.; Departamento de Engenharia Cerâmica e Vidro, Centro de Investigação em Materiais Cerâmicos e Compósitos (CICECO), Universidade de Aveiro, 3810-193 Aveiro, Portugal; email: rsilva@ua.ptReferences: Grabarczyk, J., Batory, D., Louda, P., Couvrat, P., Kotela, I., Bakowicz Mitura, K., Carbon coatings for medical implants (2007) Journal of Achievements in Materials and Manufacturing Engineering, 20 (20), pp. 107-110;Jakubowski, W., Bartosz, G., Niedzielski, P., Szymanski, W., Walkowiak, B., Nanocrystalline diamond surface is resistant to bacterial colonization (2004) Diamond and Related Materials, 13 (10), pp. 1761-1763; Amaral, M., Abreu, C.S., Oliveira, F.J., Gomes, J.R., Silva, R.F., Biotribological performance of NCD coated Si3N4 -bioglass composites (2007) Diamond and Related Materials, 16, pp. 790-795; Amaral, M., Abreu, C.S., Oliveira, F.J., Gomes, J.R., Silva, R.F., Tribological characterization of NCD in physiological fluids (2008) Diamond and Related Materials, 17 (4-5), pp. 848-852; Nordsletten, L., Hgsen, A.K.M., Konttinen, Y.T., Santavirta, S., Aspenberg, P., Aasen, A.O., Human monocytes stimulation by particles of hydroxyapatite, silicon carbide and diamond: In vitro studies of new prosthesis coatings (1996) Biomaterials, 17 (15), pp. 1521-1527; Aspenberg, P., Anttila, A., Konttinen, Y.T., Benign response to particles of diamond and SiC: Bone chamber studies of new joint replacement coating materials in rabbits (1996) Biomaterials, 17 (8), pp. 807-812; Tang, L., Tsai, C., Gerberich, W.W., Kruckeberg, L., Kania, D.R., Biocompatibility of chemical-vapour-deposited diamond (1995) Biomaterials, 16 (6), pp. 483-488; Bakowicz-Mitura, K., Bartosz, G., Mitura, S., Influence of diamond powder particles on human gene expression (2007) Surface Coatings Technology, 201 (13), pp. 6131-6135; Kulisch, W., Popov, C., Bliznakov, S., Surface and bioproperties of nanocrystalline diamond/amorphous carbon nanocomposite films (2007) Thin Solid Films, 515 (23), pp. 8407-8411; Popov, C., Kulisch, W., Reithmaier, J.P., Bioproperties of nanocrystalline diamond/amorphous carbon composite films (2007) Diamond and Related Materials, 16, pp. 735-739; Rubio-Retama, J., Hernando, J., Lpez-Ruiz, B., Synthetic nanocrystalline diamond as a third-generation biosensor support (2006) Langmuir, 22 (13), pp. 5837-5842; Siew, P.S., Loh, K.P., Poh, W.C., Zhang, H., Biosensing properties of nanocrystalline diamond film grown on polycrystalline diamond electrodes (2005) Diamond and Related Materials, 14, pp. 426-431; Wenmackers, S., Christiaens, P., Daenen, M., DNA attachment to nanocrystalline diamond films (2005) Physica Status Solidi (A), 202 (11), pp. 2212-2216; Yang, W., Hamers, R.J., Fabrication and characterization of a biologically sensitive field-effect transistor using a nanocrystalline diamond thin film (2004) Applied Physics Letters, 85 (16), pp. 3626-3628; Steinmller-Nethl, D., Kloss, F.R., Najam-Ul-Haq, M., Strong binding of bioactive BMP-2 to nanocrystalline diamond by physisorption (2006) Biomaterials, 27 (26), pp. 4547-4556; Williams, D., Revisiting the definition of biocompatibility (2003) Medical Device Technology, 14 (8), pp. 10-13; Kue, R., Sohrabi, A., Nagle, D., Frondoza, C., Hungerford, D., Enhanced proliferation and osteocalcin production by human osteoblast-like MG63 cells on silicon nitride ceramic discs (1999) Biomaterials, 20 (13), pp. 1195-1201; Howlett, C., McCartney, E., Ching, W., The effects of silicon nitride ceramic on rabbit skeletal cells and tissues (1989) Clinical Orthopaedics and Related Research, (244), pp. 296-301; Amaral, M., Costa, M.A., Lopes, M.A., Silva, R.F., Santos, J.D., Fernandes, M.H., Si 3 N 4 -bioglass composites stimulate the proliferation of MG63 osteoblast-like cells and support the osteogenic differentiation of human bone marrow cells (2002) Biomaterials, 23 (24), pp. 4897-4906; Belmonte, M., Fernandes, A.J.S., Costa, F.M., Oliveira, F.J., Silva, R.F., Adhesion behaviour assessment on diamond coated silicon nitride by acoustic emission (2003) Diamond and Related Materials, 12, pp. 733-737; Amaral, M., Fernandes, A.J.S., Vila, M., Oliveira, F.J., Silva, R.F., Growth rate improvements in the hot-filament CVD deposition of nanocrystalline diamond (2006) Diamond and Related Materials, 15 (11-12), pp. 1822-1827; Almeida, F.A., Amaral, M., Oliveira, F.J., Fernandes, A.J.S., Silva, R.F., Nano to micrometric HFCVD diamond adhesion strength to Si3N4 (2007) Vacuum, 81 (11-12), pp. 1443-1447; Trigo Cabral, M.C., Costa, M.A., Fernandes, M.H., In vitro models of periodontal cells: A comparative study of long-term gingival, periodontal ligament and alveolar bone cell cultures in the presence of -glycerophosphate and dexamethasone (2007) Journal of Materials Science, 18 (6), pp. 1079-1088; Coelho, M.J., Trigo Cabral, A., Fernandes, M.H., Human bone cell cultures in biocompatibility testingpart I: Osteoblastic differentiation of serially passaged human bone marrow cells cultured in -MEM and in DMEM (2000) Biomaterials, 21 (11), pp. 1087-1094; Alberts, B., Johnson, A., Lewis, J., Ratt, M., Roberts, K., Walter, P., The cytoskeleton (2002) Molecular Biology of the Cell, , 4th New York, NY, USA Garland Science; Fawcett, D.W., Connective tissue (1994) A Textbook of Histology, pp. 133-169. , 12th New York, NY, USA Chapman Hall; Freshney, R.I., Biology of cultured cells (2000) Culture of Animal Cells: A Manual of Basic Technique, pp. 9-18. , 4th New York, NY, USA Wiley-Liss; Biological evaluation of medical devicespart 5: Tests for in vitro cytotoxicity, , International Organization for Standardization, Geneva, Switzerland, 1992; Okrj, W., Kamiska, M., Klimek, L., Szymaski, W., Walkowiak, B., Blood platelets in contact with nanocrystalline diamond surfaces (2006) Diamond and Related Materials, 15 (10), pp. 1535-1539; Popov, C., Kulisch, W., Jelinek, M., Bock, A., Strnad, J., Nanocrystalline diamond/amorphous carbon composite films for applications in tribology, optics and biomedicine (2006) Thin Solid Films, 494 (1-2), pp. 92-97; Kalbacova, M., Kalbac, M., Dunsch, L., The effect of SWCNT and nano-diamond films on human osteoblast cells (2007) Physica Status Solidi (B), 244 (11), pp. 4356-4359; Chong, K.F., Loh, K.P., Vedula, S.R.K., Cell adhesion properties on-photochemically functionalized diamond (2007) Langmuir, 23 (10), pp. 5615-5621; Bajaj, P., Akin, D., Gupta, A., Ultrananocrystalline diamond film as an optimal cell interface for biomedical applications (2007) Biomedical Microdevices, 9 (6), pp. 787-794; Stein, G.S., Lian, J.B., Molecular mechanisms mediating proliferation/differentiation interrelationships during progressive development of the osteoblast phenotype (1993) Endocrine Reviews, 14 (4), pp. 424-442; Coelho, M.J., Fernandes, M.H., Human bone cell cultures in biocompatibility testingpart II: Effect of ascorbic acid, -glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21 (11), pp. 1095-1102; Sikavitsas, V.I., Temenoff, J.S., Mikos, A.G., Biomaterials and bone mechanotransduction (2001) Biomaterials, 22 (19), pp. 2581-2593; Webster, T.J., Ergun, C., Doremus, R.H., Siegel, R.W., Bizios, R., Enhanced functions of osteoblasts on nanophase ceramics (2000) Biomaterials, 21 (17), pp. 1803-1810; Webster, T.J., Smith, T.A., Increased osteoblast function on PLGA composites containing nanophase titania (2005) Journal of Biomedical Materials Research Part A, 74 (4), pp. 677-686; Kay, S., Thapa, A., Haberstroh, K.M., Webster, T.J., Nanostructured polymer/nanophase ceramic composites enhance osteoblast and chondrocyte adhesion (2002) Tissue Engineering, 8 (5), pp. 753-761; Balasundaram, G., Sato, M., Webster, T.J., Using hydroxyapatite nanoparticles and decreased crystallinity to promote osteoblast adhesion similar to functionalizing with RGD (2006) Biomaterials, 27 (14), pp. 2798-2805; Kaplan, F.S., Hayes, W.C., Keaveny, T.M., Boskey, A., Einhorn, T.A., Iannotti, J.P., Simon, S.P., Form and function of bone (1994) Orthopedic Basic Science, pp. 127-185. , Columbus, Ohio, USA American Academy of Orthopedic Surgeons; Palin, E., Liu, H., Webster, T.J., Mimicking the nanofeatures of bone increases bone-forming cell adhesion and proliferation (2005) Nanotechnology, 16 (9), pp. 1828-1835; Siegel, R.W., Creating nanophase materials (1996) Scientific American Magazine, 275 (6), pp. 74-79; Webster, T.J., Ergun, C., Doremus, R.H., Siegel, R.W., Bizios, R., Specific proteins mediate enhanced osteoblast adhesion on nanophase ceramics (2000) Journal of Biomedical Materials Research, 51 (3), pp. 475-483; Webster, T.J., Schadler, L.S., Siegel, R.W., Bizios, R., Mechanisms of enhanced osteoblast adhesion on nanophase alumina involve vitronectin (2001) Tissue Engineering, 7 (3), pp. 291-301

Nanocrystalline diamond: In vitro biocompatibility assessment by MG63 and human bone marrow cells cultures - Amaral, M.; Dias, A.G.; Gomes, P.S.; Lopes, M.A.; Silva, R.F.; Santos, J.D.; Fernandes, M.H. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2008)
Nanocrystalline diamond (NCD) has a great potential for prosthetic implants coating. Nevertheless, its biocompatibility still has to be better understood. To do so, we employed several materials characterization techniques (SEM, AFM, micro-Raman spectroscopy) and cell culture assays using MG63 osteoblast-like and human bone marrow cells. Biochemical routines (MTT assays, Lowry's method, ALP activity) supported by SEM and confocal microscopy characterization were carried out. We used silicon nitride (Si 3N 4) substrates for NCD coatings based on a previous demonstration of the superior adhesion and tribological performance of these NCD coated ceramics. Results demonstrate an improved human osteoblast proliferation and the stimulation of differentiated markers, like ALP activity and matrix mineralization, compared with standard polystyrene tissue culture plates. The nanometric featuring of NCD, associated to its chemical affinity are key points for bone regeneration purposes. © 2007 Wiley Periodicals, Inc.
Cited By (since 1996): 25Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.31742PubMed ID: 18085649Language of Original Document: EnglishCorrespondence Address: Silva, R. F.; CICECO, Department of Ceramics and Glass Engineering, University of Aveiro, 3810-193 Aveiro, Portugal; email: rsilva@cv.ua.ptChemicals/CAS: diamond, 7782-40-3; polystyrene, 9003-53-6; silicon nitride, 12033-89-5; Alkaline Phosphatase, EC 3.1.3.1; Ceramics; Coated Materials, Biocompatible; Diamond, 7782-40-3; Silicon Compounds; silicon nitride, 12033-89-5References: Ratner, B.D., Hoffman, A.S., Schoen, A.S., Lemons, J.E., (1996) Biomaterials Science: An Introduction to Materials in Medicine, , New York: Academic Press;;Emery, D.F.G., Clarke, H.J., Grover, M.L., Stanmore total hip replacement in younger patients: Review of a group of patients under 50 years of age at operation (1997) J Bone Joint Surg, 79, pp. 240-246; Shane, A.C., Monique, C., Yogesh, K.V., Erick, M.S., Michelle, D.M., David Moore, K., Surface crystalline phases and nanoindentation hardness of explanted zirconia femoral heads (2003) J Mater Sci: Mater Med, 14, pp. 863-867; Shane, A.C., Marc, D.F., Yogesh, K.V., William, R.L., Jack, E.L., Shanna, W., Ramakrishna, V., Nanostructured ceramics for biomedical implants (2002) J Nanosci Nanotechnol, 2, pp. 293-312; Palin, E., Liu, H., Webster, T.J., Mimicking the nanofeatures of bone increases bone-forming cell adhesion and proliferation (2005) Nanotechnology, 16, pp. 1828-1835; Webster, T.J., Siegel, R.W., Bizios, R., Osteoblast adhesion on nanophase ceramics (1999) Biomaterials, 20, pp. 1221-1227; Price, R.L., Haberstroh, K.M., Webster, T.J., Enhanced functions of osteoblasts on nanostructured surfaces of carbon and alumina (2003) Med Biol Eng Comput, 41, pp. 372-375; Perla, V., Webster, T.J., Better osteoblast adhesion on nanoparticulate selenium - A promising orthopedic implant material (2005) J Biomed Mater Res, 75 A, pp. 356-364; Fries, M.D., Vohra, Y.K., Nanostructure diamond film deposition on curved surfaces of metallic temporomandibular joint implant (2002) J Phys D: Appl Phys, 35, pp. L105-L107; Papo, M.J., Catledge, S.A., Vohra, Y.K., Mechanical wear behaviour of nanocrystalline and multilayer diamond coatings on temporomandibular joint implants (2004) J Mater Sci: Mater Med, 15, pp. 773-777; Aspenberg, P., Antilla, A., Konttinen, Y.T., Lappalainen, R., Goodman, S.B., Nordsletten, L., Santavirta, S., Benign response to particles of diamond and SiC: Bone chamber studies of new joint replacement coating materials in rabbits (1996) Biomaterials, 17, pp. 807-812; Nordsletten, L., Hogasen, A.K.M., Konttinen, Y.T., Santavirta, S., Aspenberg, P., Aasen, A.O., Human monocytes stimulation by particles of hydroxyapatite, silicon carbide and diamond: In vitro studies of new prosthesis coatings (1996) Biomaterials, 17, pp. 1521-1527; Mitura, S., Mitura, A., Niedzielski, P., Couvrat, P., Nanocrystalline diamond coatings (1999) Chaos Solitons Fractals, 10, pp. 2165-2176; Mitura, K., Niedzielski, P., Grzegorz, B., Moll, J., Walkowiak, B., Pawlowska, Z., Louda, P., Mitura, S., Interactions between carbon coatings and tissue (2006) Surf Coat Technol, 201, pp. 2117-2123; Garguilo, J.M., Davis, B.A., Buddie, M., Köck, F.A.M., Nemanich, R.J., Fibrinogen adsorption onto microwave plasma chemical vapour deposited diamond films (2004) Diamond Relat Mater, 13, pp. 595-599; Tang, L., Tsai, C., Gerberich, W.W., Kruckeberg, L., Kania, D.R., Biocompatibility of chemical-vapour deposited diamond (1995) Biomaterials, 16, pp. 483-488; Narayan, R.J., Wei, W., Jin, C., Andara, M., Agarwal, A., Gerhardt, R.A., Shih, C., Singh, R.N., Microstructural and biological properties of nanocrystalline diamond coatings (2006) Diamond Relat Mater, 15, pp. 1935-1940; Popov, C., Kulisch, W., Jelinek, M., Bock, A., Strnad, J., Nanocrystalline diamond/amorphous carbon composite films for applications in tribology, optics and biomedicine (2006) Thin Solid Films, 494, pp. 92-97; Nethl, D.S., Kloss, F.R., Haq, M.N.U., Rainer, M., Larsson, K., Linsmeier, C., Köhler, G., Bonn, G., Strong binding of bioactive BMP-2 to nanocrystalline diamond by physisorption (2006) Biomaterials, 27, pp. 4547-4556; Silva, V.A., Costa, F.M., Fernandes, A.J.S., Nazaré, M.H., Silva, R.F., Influence of SiC particle addition on the nucleation density and adhesion strength of MPCVD diamond coatings on S13N4 substrates (2000) Diamond Relat Mater, 9, pp. 483-488; Kue, R., Sahrabi, A., Nagle, D., Frondonza, C., Hungerford, D., Enhanced proliferation and osteocalcin production by human osteoblast-like cells on silicon nitride ceramic discs (1999) Biomaterials, 20, pp. 1195-1201; Howlett, C., McCartney, E., Ching, W., The effects of silicon nitride ceramic on rabbit skeletal cells and tissues (1989) Clin Orthop, 244, pp. 296-301; Amaral, M., Costa, M.A., Lopes, M.A., Silva, R.F., Santos, J.D., Fernandes, M.H., Si 3N 4-bioglass composites stimulate the proliferation of MG63 osteoblast-like cells and support the osteogenic differentiation of human bone marrow cells (2002) Biomaterials, 23, pp. 4897-4906; Belmonte, M., Fernandes, A.J.S., Costa, F.M., Oliveira, F.J., Silva, R.F., Adhesion behaviour assessment on diamond coated silicon nitride by acoustic emission (2003) Diamond Relat Mater, 12, pp. 733-737; Coelho, M.J., Trigo Cabrai, A., Fernandes, M.H., Human bone cell cultures in biocompatibility testing, Part 1: Osteoblastic differentiation of serially passaged human bone marrow cells cultured in α-MEM and in DMEM (2000) Biomaterials, 21, pp. 1087-1094; Clifford, C.J., Downes, S., A comparative study of the use of colorimetric assays in the assessment of biocompatibility (1996) J Mater Sci: Mater Med, 7, pp. 637-643; Ciapetti, G., Cenni, E., Pratelli, L., Pizzoferrato, A., In vitro evaluation of cell/biomaterial interaction by MTT assay (1993) Biomaterials, 14, pp. 359-364; Ferrari AC, Robertson J. Origin of the 1150 cm -1 Raman mode in nanocrystalline diamond. Phys Rev B 2001;63:121405-1-4Pfeiffer, R., Kuzmany, H., Knoll, P., Bokova, S., Salk, N., Günther, B., Evidence for trans-polyacetylene in nano-crystalline diamond films (2003) Diamond Relat Mater, 12, pp. 268-271; Fernandes, A.J.S., Neto, M.A., Almeida, F.A., Silva, R.F., Costa, F.M., Nano- and micro-crystalline diamond growth by MPCVD in extremely poor hydrogen uniform plasmas (2007) Diamond Relat Mater, 16, pp. 757-761; Almeida, F.A., Amaral, M., Oliveira, F.J., Fernandes, A.J.S., Silva, R.F., Nano to micrometric HFCVD diamond adhesion strength to Si 3N 4 (2007) Vacuum, 81, pp. 1443-1447; Abreu, C.S., Amaral, M., Oliveira, F.J., Fernandes, A.J.S., Gomes, J.R., Silva, R.F., Enhanced performance of HFCVD nanocrystalline diamond self-mated tribosystems by plasma pretreatments on silicon nitride substrates (2006) Diamond Relat Mater, 15, pp. 2024-2028; Abreu, C.S., Amaral, M., Fernandes, A.J.S., Oliveira, F.J., Silva, R.F., Gomes, J.R., Friction and wear performance of HFCVD nano-crystalline diamond coated silicon nitride ceramics (2006) Diamond Relat Mater, 15, pp. 739-744; Stein, G.S., Lian, J.B., Molecular mechanisms mediated proliferation- differentiation interrelationships during progressive development of the osteoblast phenotype (1993) Endocr Rev, 14, pp. 424-442; Coelho, M.J., Fernandes, M.H., Human bone cell cultures in biocompatibility testing, Part 2: Effect of ascorbic acid, β-glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21, pp. 1095-1102; Kaplan, F.S., Hayes, W.C., Keaveny, T.M., Boskey, A., Einhorn, T.A., Iannotti, J.P., Form and function of bone (1994) Orthopedic Basic Science, pp. 127-185. , Simon SP, editor, Columbus, OH: American Academy of Orthopedic Surgeons;; Webster, T.J., Ejiofor, J.U., Increased osteoblast adhesion on nanophase metals: Ti, Ti6A14V, and CoCrMo (2004) Biomaterials, 25, pp. 4731-4739; Kay, S., Thapa, A., Haberstroh, K.M., Webster, T.J., Nanostructured polymer/nanophase ceramic composites enhance osteoblast and chondrocyte adhesion (2002) Tissue Eng, 8, pp. 753-761; Webster, T.J., Smith, T.A., Increased osteoblast function on PLGA composites containing nanophase titania (2005) J Biomed Mater Res A, 74, pp. 677-686; Balasundaram, G., Sato, M., Webster, T.J., Using hydroxyapatite nanoparticles and decreased crystallinity to promote osteoblast adhesion similar to functionaizing with RGD (2006) Biomaterials, 27, pp. 2798-2805; Webster, T.J., (2004) Proteins: Structure and interactions patterns to solid surfaces, pp. 1-16. , editors. Encyclopedia of Nanoscience and Nanotechnology. New York: Marcel Dekker; Siegel RW. Creating nanophase materials. Sci Am (Int Ed) 1996;275:74-79Webster, T.J., Enhanced functions of osteoblasts on nanophase ceramics (2000) Biomaterials, 21, pp. 1803-1810; Webster, T.J., Enhanced osteoclast-like cell functions on nano-phase ceramics (2001) Biomaterials, 22, pp. 1327-1333; Webster, T.J., Ergun, C., Doremus, R.H., Siegel, R.W., Bizios, R., Specific proteins mediate enhanced osteoblast adhesion on nano-phase ceramics (2000) J Biomed Mater Res, pp. 51475-51483; Webster, T.J., Schadler, L.S., Siegel, R.W., Bizios, R., Mechanisms of enhanced osteoblast sdhesion on nanophase alumina involve vitronectin (2001) Tissue Eng, 7, pp. 291-301
Keywords: adult; alkaline phosphatase; ALP activity; Animal cell culture; Architectural acoustics; article; Atomic force microscopy; Biocompatibility; Bone; bone marrow cell; Bone Marrow Cells; Bone Regeneration; Cell culture; cell proliferation; cell survival; Cells; Cells, Cultured; ceramics; Cladding (coating); Coated Materials, Biocompatible; confocal microscopy; controlled study; diamond; Diamonds; enzyme activity; extracellular matrix; human; Human bone marrow cells; human cell; Humans; Imaging techniques; Implants (surgical); In vitro biocompatibility; in vitro selection; Joint replacement; male; Materials characterization; materials testing; Micro-Raman spectroscopy; Microscopic examination; Microscopy, Atomic Force; Microscopy, Confocal; Microscopy, Electron, Scanning; mineralization; MTT assaying; Nano-crystalline diamond; nanocrystal; Nanocrystalline alloys; Nanocrystalline materials; nanoparticles; Nanostructured materials; Nitrides; Nonmetals; osteoblast; Osteoblasts; polystyrene; Prostheses and Implants; Raman spectrometry; Scanning electron microscopy; Secondary emission; Silicon; Silicon compounds; Silicon nitride; Spectrum Analysis, Raman; Surface Properties; Tissue engineering

Omniview-SisPorto® 3.5 - A central fetal monitoring station with online alerts based on computerized cardiotocogram+ST event analysis - Ayres-de-Campos, D.; Sousa, P.; Costa, A.; Bernardes, J. (Journal of Perinatal MedicineJ. Perinat. Med., 2008)
Visual analysis of cardiotocograms is poorly reproducible and is currently recognized as the main weakness of the STAN® methodology. The Omniview-SisPorto® 3.5 program is the most recent version of a central monitoring system that provides visual and sound alerts, based on computer analysis of cardiotocographic and ST event features. This paper describes the program's main characteristics and provides an overview of the system's online alerts. Omniview-SisPorto® 3.5 is the first central monitoring system to incorporate computerized analysis of cardiotocographic and ST event features, providing health professionals with online alerts for minor and major changes in monitored signals. The system is currently undergoing extensive clinical evaluation. © 2008 by Walter de Gruyter.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: JPEMAdoi: 10.1515/JPM.2008.030Language of Original Document: EnglishCorrespondence Address: Ayres-De-Campos, D.; Departmento Ginecologia e Obstetricia, Faculdade de Medicina, Universidade Do Porto, Alameda Hernani Monteiro, 4200-319 Porto, Portugal; email: sisporto@med.up.ptTradenames: Omniview-SisPorto 3.5 system, SpeculumManufacturers: SpeculumReferences: Amer-Wahlin, I., Arulkumaran, S., Hagberg, H., Marsal, K., Visser, G., Fetal electrocardiogram: ST waveform analysis in intrapartum surveillance (2007) Br J Obstet Gynaecol, 114, pp. 1191-1193;Ayres-de-Campos, D., Bernardes, J., Garrido, A., Marquesde-Sá, J., Pereira-Leite, L., SisPorto 2.0: A program for automated analysis of cardiotocograms (2000) J Matern Fetal Med, 9, pp. 311-318; Ayres-de-Campos, D., Bernardes, J., Comparison of fetal heart rate baseline estimation by SisPorto 2.01 and a consensus of clinicians (2004) Eur J Obstet Gynecol Reprod Biol, 117, pp. 174-178; Ayres-de-Campos, D., Costa-Santos, C., Bernardes, J., SisPorto Multicentre Validation Study Group. Prediction of neonatal state by computer analysis of fetal heart rate tracings: The antepartum arm of the SisPorto multicentre validation study (2005) Eur J Obstet Gynecol Reprod Biol, 118, pp. 52-60; Ayres-de-Campos, D., Bernardes, J., Kwee, A., Westehuis, M., Visser, G.H.A., Computer quantification of short-term variability as an adjunct to fetal electrocardiographic monitoring (2007) Br J Obstet Gynaecol, 114, pp. 1446-1447; Bernardes, J., Moura, C., Marques de, S.J., Pereira Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-65; Electronic fetal heart rate monitoring: Research guidelines for interpretation (1997) Am J Obstet Gynecol, 177, pp. 1385-1390. , National Institute of Child Health and Human Development Research Planning Workshop; Neilson, J.P., Fetal electrocardiogram (ECG) for fetal monitoring during labor (2006) Cochrane Database of Systematic Reviews, (3); Paneth, N., Bommarito, M., Stricker, J., Electronic fetal monitoring and later outcome (1993) Clin Invest Med, 16, pp. 159-165; (2001) Evidence-based clinical guideline: The use of electronic fetal monitoring, , RCOG, Royal College of Obstetricians and Gynaecologists, London, RCOG Press; Rooth, G., Huch, A., Huch, R., Guidelines for the use of fetal monitoring (1987) Int J Gynecol Obstet, 25, pp. 159-167
Keywords: article; Cardiotocography; computer program; Computer-assisted; Electrocardiography; Female; Fetal; Fetal hypoxia; Fetal monitoring; fetus hypoxia; fetus monitoring; Heart rate; human; Humans; instrumentation; online system; Pregnancy; priority journal; Signal processing; ST segment

Surface characterization and cell response of a PLA/CaP glass biodegradable composite material - Navarro, M.; Engel, E.; Planell, J.A.; Amaral, I.; Barbosa, M.; Ginebra, M.P. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2008)
Bioabsorbable materials are of great interest for bone regeneration applications, since they are able to degrade gradually as new tissue is formed. In this work, a fully biodegradable composite material containing polylactic acid (PLA) and calcium phosphate (CaP) soluble glass particles has been characterized in terms of surface properties and cell response. Cell cultures were performed in direct contact with the materials and also with their extracts, and were evaluated using the MTT assay, alkaline phosphatase activity, and osteocalcin measurements. The CaP glass and PLA were used as reference materials. No significant differences were observed in cell proliferation with the extracts containing the degradation by-products of the three materials studied. A relation between the materials wettability and the material-cell interactions at the initial stages of contact was observed. The most hydrophilic material (CaP glass) presented the highest cell adhesion values as well as an earlier differentiation, followed by the PLA/glass material. The incorporation of glass particles into the PLA matrix increased surface roughness. SEM images showed that the heterogeneity of the composite material induced morphological changes in the cells cytoskeleton. © 2007 Wiley Periodicals, Inc.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.31546PubMed ID: 17729262Language of Original Document: EnglishCorrespondence Address: Ginebra, M. P.; Department of Materials Science, Institute of Bioengineering of Catalonia (IBEC), Technical University of Catalonia, Avda Diagonal 647, 08028-Barcelona, Spain; email: maria.pau.ginebra@upc.eduChemicals/CAS: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide, 298-93-1; calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; osteocalcin, 136461-80-8; polylactic acid, 26100-51-6; Alkaline Phosphatase, EC 3.1.3.1; Bone Substitutes; calcium phosphate, 10103-46-5; Calcium Phosphates; Lactic Acid, 50-21-5; Osteocalcin, 104982-03-8; poly(lactic acid), 26100-51-6; PolymersReferences: Barrows, T., Degradable implants materials: A review of synthetic absorbable polymers and their applications (1986) Clin Mater, 1, pp. 233-267;Ciccone, W., Motz, C., Bentley, C., Tasto, J., Bioabsorbable implants in orthopaedics: New developments and clinical applications (2001) J Am Acad Orthop Surg, 9, pp. 280-288; Dunn, R.L., Clinical applications and update on the poly (alpha-hydroxy acids) (1995) Biomedical Applications of Synthetic Biodegradable Polymers, pp. 17-31. , Hollinger JO, editor, Boca Raton: CRC Press;; Middleton, J.C., Tipton, A.J., Synthetic biodegradable polymers as orthopedic devices (2000) Biomaterials, 21, pp. 2335-2346; Böstman O Current concepts review. Absorbable implants for fracture fixation. J Bone Joint Surgery 1991;73A:148-153Ashammakhi, N., Suuronen, R., Tiainen, J., Tormala, P., Waris, T., Spotlight on naturally absorbable osteofixation devices (2003) J Craniofac Surg, 14, pp. 247-259; Hou, Q.P., Grijpma, D.W., Feijen, J., Porous polymeric structures for tissue engineering prepared by a coagulation, compression moulding and salt leaching technique (2003) Biomaterials, 24, pp. 1937-1947; Kellomaki, M., Niiranen, H., Puumanen, K., Ashammakhi, N., Waris, T., Tormala, P., Bioabsorbable scaffolds for guided bone regeneration and generation (2000) Biomaterials, 21, pp. 2495-2505; Mooney, D.J., Park, S., Kaufmann, P.M., Sano, K., Mcnamara, K., Vacanti, J.P., Langer, R., Biodegradable sponges for hepatocyte transplantation (1995) J Biomed Mater Res, 29, pp. 959-965; Ragel, C.V., Vallet-Regi, M., In vitro bioactivity and gentamicin release from glass-polymer-antibiotic composites (2000) J Biomed Mater Res, 51, pp. 424-429; Kohn, J., Langer, R., Bioabsorbable and bioerodible materials (1996) Biomaterials Science, pp. 64-72. , Ratner BD, Hoffman A, Schoen F, Lemons J, editors, New York: Academic Press;; Navarro, M., Ginebra, M.P., Clement, J., Martinez, S., Avila, G., Planell, J.A., Physicochemical degradation of titania-stabilized soluble phosphate glasses for medical applications (2003) J Am Ceram Soc, 86, pp. 1345-1352; Navarro, M., Ginebra, M.P., Planell, J.A., Barrias, C.C., Barbosa, M., In vitro degradation behavior of a novel bioabsorbable composite material based on PLA and a soluble CaP glass (2005) Acta Biomaterialia, 1, pp. 411-419; Stephansson, S.N., Byers, B.A., Garcia, A.J., Enhanced expression of the osteoblastic phenotype on substrates that modulate fibronectin conformation and integrin receptor binding (2002) Biomaterials, 23, pp. 2527-2534; Keselowsky, B.G., Collard, D.M., Garcia, A.J., Surface chemistry modulates fibronectin conformation and directs integrin binding and specificity to control cell adhesion (2003) J Biomed Mater Res A, 66, pp. 247-259; Beumer, G., van Blitterswijk, C., Bakker, D., Ponec, M., Cell-seeding and in vitro biocompatibility evaluation of polymeric matrices of PEO/PBT copolymers and PLLA (1993) Biomaterials, 14, pp. 598-604; Ishaug, S., Yaszemski, M., Bizios, R., Mikos, A., Osteoblast function on synthetic biodegradable polymers (1994) J Biomed Mater Res, 28, pp. 1445-1453; Navarro, M., Ginebra, M.P., Planell, J.A., Cellular response to calcium phosphate glasses with controlled solubility (2003) J Biomed Mater Res A, 67, pp. 1009-1015; Huffman, K.R., Casey, D.J., Effect of carboxyl end groups on hydrolysis of polyglycolic acid (1985) J Polym Sci A: Polym Chem, 23, pp. 1939-1954; Ishaug-Riley, S.L., Okun, L.E., Prado, G., Applegate, M.A., Ratcliffe, A., Human articular chondrocyte adhesion and proliferation on synthetic biodegradable polymer films (1999) Biomaterials, 20, pp. 2245-2256; Park, A., Griffith, L., In vitro cell response to differences in poly-1-lactide crystallinity (1996) Biomaterials, 31, pp. 117-130; Cai, K.Y., Yao, K.D., Lin, S.B., Yang, Z.M., Li, X.Q., Xie, H.Q., Poly (D, L-lactic acid) surfaces modified by silk fibroin: Effects on the culture of osteoblast in vitro (2002) Biomaterials, 23, pp. 1153-1160; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., Hydrophobicity, surface tension, and zeta potential measurements of glass-reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Vogler, E.A., Structure and reactivity of water at biomaterial surfaces (1998) Adv Colloid Interface Sci, 74, pp. 69-117; Vogler, E.A., Interfacial chemistry in biomaterials science (1993) Surfactant Science Series, pp. 183-250. , Berg JC, editor. Wettability, Marcel Dekker, New York; Charles-Harris, M., Navarro, M., Engel, E., Aparicio, C., Ginebra, M.P., Planell, J., A Surface characterisation of completely degradable composite scaffolds (2005) J Mater Svi: Mater Med, 16, pp. 1125-1130; Lampin, M., WarocquierClerout, R., Legris, C., Degrange, M., SigotLuizard, M.F., Correlation between substratum roughness and wettability, cell adhesion, and cell migration (1997) J Biomed Mater Res, 36, pp. 99-108; Khang, G., Jeon, J.H., Lee, L.W., Cho, S.C., Lee, H.B., Cell and platlet adhesion on plasma glow discharge-treated poly(lactide-co-glycolide) (1997) Biomed Mater Engl, 7, pp. 357-368; Webb, K., Hlady, V., Tresco, P.A., Relative importance of surface wettability and charged functional groups on NIH 3T3 fibroblast attachment, spreading, and cytoskeletal organization (1998) J Biomed Mater Res, 41, pp. 422-430; Owen, T.A., Aronow, M., Shalhoub, V., Barone, L.M., Wilming, L., Tassinari, M.S., Progressive development of the rat osteoblast phenotype in vitro - Reciprocal relationships in expression of genes associated with osteoblast proliferation and differentiation during formation of the bone extracellular-matrix (1990) J Cell Physiol, 143, pp. 420-430; Lian, J.B., Stein, G.S., Concepts of osteoblast growth and differentiation - Basis for modulation of bone cell-development and tissue formation (1992) Crit Rev Oral Biol Med, 3, pp. 269-305; Quarles, L.D., Yohay, D.A., Lever, L.W., Caton, R., Wenstrup, R.J., Distinct proliferative and differentiated stages of murine Mc3T3-E1 cells in culture - An in vitro model of osteoblast development (1992) J Bone Miner Res, 7, pp. 683-692; Boyan, B.D., Dean, D.D., Lohmann, C.H., Cochran, D.L., Sylvia, V.L., Schwartz, Z., The titanium-bone cell interface in vitro: The role of the surface in promoting osteointegration (2001) Titanium in Medicine, pp. 562-585. , Brunette D, Tengvall P, Textor M, Thomsen P, editors, Berlin: Springer-Verlag;; Gronowicz, G., McCarthy, M.B., Ahmad, M., Direct integrin-mediated attachment of human osteoblasts to implants (1996) J Bone Miner Res, 11, pp. S323; Boyan, B.D., Hummert, T.W., Kieswetter, K., Schraub, D., Dean, D.D., Schwartz, Z., Effect of titanium surface characteristics on chondrocytes and osteoblasts in vitro (1995) Scan Electron Microsc, 5, pp. 323-335; Martin, J.Y., Schwartz, Z., Hummert, T.W., Schraub, D.M., Simpson, J., Lankford, J., Effect of titanium surface-roughness on proliferation. Differentiation, and protein-synthesis of human osteoblast-like cells (MG63) (1995) J Biomed Mater Res, 29, pp. 389-401
Keywords: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide; Absorbable Implants; alkaline phosphatase; article; Biodegradable composite materials; biodegradable implant; Biodegradation; Bone; Bone Regeneration; Bone Substitutes; calcium phosphate; Calcium phosphates; cell adhesion; Cell culture; cell function; cell interaction; Cell Line; cell proliferation; Cell response; Composite materials; cytoskeleton; glass; human; human cell; Humans; hydrophilicity; hydrophobicity; In vitro test; Lactic Acid; materials testing; Osteoblasts; osteocalcin; polylactic acid; Polymers; scanning electron microscope; Surface analysis; Surface Properties; wettability

Attachment, spreading and short-term proliferation of human osteoblastic cells cultured on chitosan films with different degrees of acetylation - Amaral, I.F.; Cordeiro, A.L.; Sampaio, P.; Barbosa, M.A. (Journal of Biomaterials Science, Polymer EditionJ. Biomater. Sci. Polym. Ed., 2007)
Chitosan (Ch) is being actively investigated as a non-protein template for the growth of an increasing number of anchorage-dependent cells, including chondrocytes and bone cells. In the present work, Ch films with degrees of N-acetylation (DAs) in the range of 4 to 49% were evaluated with respect to the attachment, spreading and short-term proliferation of osteoblasts, using human osteoblastic MG-63 cells. The films were characterized in terms of surface morphology and surface charge by atomic force microscopy and streaming potential measurements, respectively. Cell attachment was assessed after 3 and 24 h of cell culture. After 24 h of incubation, cell attachment was found to be dependent on the DA, lower DAs favouring cell adhesion. With time, cell spreading and cytoskeleton organization were only attained for DAs ≤ 13%. Regarding cell proliferation, cells grown on films with the lowest DA (4%) revealed a higher specific growth rate as compared to those grown on films with higher DAs. Films with a DA of 49% failed to sustain cell proliferation. In addition, a longer lag-phase was observed on Ch, as compared to TCPS, in accordance to an observed delay of cell spreading. The present findings revealed that differences in the DA as small as 9% may be critical in terms of the osteoblast response to two-dimensional Ch-based matrices. © 2007 VSP.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: JBSEEdoi: 10.1163/156856207780425068Language of Original Document: EnglishCorrespondence Address: Amaral, I.F.; INEB - Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: iamaral@ineb.up.ptChemicals/CAS: chitosan, 9012-76-4; Biocompatible Materials; Chitosan, 9012-76-4References: Vacanti, C.A., Bonassar, L.J., Vacanti, J.P., (2000) Principles of Tissue Engineering, p. 671. , R. P. Lanza, R. Langer and J. Vacanti Eds, p, Academic Press, San Diego, CA;Bruder, S.P., Caplan, A.I., (2000) Principles of Tissue Engineering, p. 683. , R. P. Lanza, R. Langer and J. Vacanti Eds, p, Academic Press, San Diego, CA; Burg, K.J.L., Porter, S., Kellam, J.F., (2000) Biomaterials, 21, p. 2347; Khor, E., Lim, L.Y., (2003) Biomaterials, 24, p. 2339; Nettles, D.L., Elder, S.H., Gilbert, J.A., (2002) Tissue Eng, 8, p. 1009; Lee, J.Y., Nam, S.H., Im, S.Y., Park, Y.J., Lee, Y.M., Seol, Y.J., Chung, C.P., Lee, S.J., (2002) J. Control. Rel, 78, p. 187; Muzzarelli, R.A.A., (1997) Cell. Mol. Life Sci, 53, p. 131; Madihally, S.V., Matthew, H.W.T., (1999) Biomaterials, 20, p. 1133; Chupa, J.M., Foster, A.M., Sumner, S.R., Madihally, S.V., Matthew, H.W.T., (2000) Biomaterials, 21, p. 2315; Lahiji, A., Sohrabi, A., Hungerford, D.S., Frondoza, C.G., (2000) J. Biomed. Mater. Res, 51, p. 586; Ho, M.H., Wang, D.M., Hsieh, H.J., Liu, H.C., Hsien, T.Y., Lai, J.Y., Hou, L.T., (2005) Biomaterials, 26, p. 3197; A. Domard, in: Advances in Chitin Science, II, A. Domard, G. A. F. Roberts and K. M. Varum (Eds), p. 410. Jacques André, Lyon (1997)Tomihata, K., Ikada, Y., (1997) Biomaterials, 18, p. 567; Baxter, A., Dillon, M., Taylor, K.D.A., Roberts, G.A.F., (1992) Int. J. Biol. Macromol, 14, p. 166; Anselme, K., (2000) Biomaterials, 21, p. 667; Prasitsilp, M., Jenwithisuk, R., Kongsuwan, K., Damrongchai, N., Watts, P., (2000) J. Mater. Sci. Mater. Med, 11, p. 773; Chatelet, C., Damour, O., Domard, A., (2001) Biomaterials, 22, p. 261; Dhiman, H.K., Ray, A.R., Panda, A.K., (2004) Biomaterials, 25, p. 5147; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., (2001) Polymer, 42, p. 3569; Mima, S., Miya, M., Iwamoto, R., Yoshikawa, S., (1983) J. Appl. Polym. Sci, 28, p. 1909; Aiba, S., (1986) Int. J. Biol. Macromol, 8, p. 173; Terbojevich, M., Cosani, A., Muzzarelli, R.A.A., (1996) Carbohydr. Polym, 29, p. 63; (1987) Guideline on Validation of the Limulus Amebocyte Lysate Test as an End-product Endotoxin Test for Human and Animal Parental Drugs, Biological Products, and Medical Devices, , US Department of Health and Human Services, Public Health Service, Food and Drug Administration, US Department of Health and Human Services, Washington, DC; Nakagawa, Y., Murai, T., Hasegawa, C., Hirata, M., Tsuchiya, T., Yagami, T., Haishima, Y., (2003) J. Biomed. Mater. Res, 66 B, p. 347; Walker, S.L., Bhattacharjee, S., Hoek, E.M.V., Elimelech, M., (2002) Langmuir, 18, p. 2193; Clover, J., Gowen, M., (1994) Bone, 15, p. 585; Mosmann, T., (1983) J. Immunol. Methods, 65, p. 55; Domke, J., Dannohl, S., Parak, W.J., Muller, O., Aicher, W.K., Radmacher, M., (2000) Colloid Surfaces B: Biointerfaces, 19, p. 367; Sorlier, P., Denuziere, A., Viton, C., Domard, A., (2001) Biomacromolecules, 2, p. 765; Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., (2005) J. Biomed. Mater. Res, 75 A, p. 387; Andrade, J.D., Smith, L.M., Gregonis, D.E., (1985) Surface and Interfacial Aspects of Biomedical Polymers, 1, p. 249. , J. D. Andrade Ed, p, Plenum Press, New York, NY; Dewez, J.L., Doren, A., Schneider, Y.J., Rouxhet, P.G., (1999) Biomaterials, 20, p. 547; Kikuchi, T., Yoshikai, Y., Miyoshi, J., Katsuki, M., Musikacharoen, T., Mitani, A., Tanaka, S., Matsuguchi, T., (2003) J. Dent. Res, 82, p. 546; Denuziere, A., Ferrier, D., Damour, O., Domard, A., (1998) Biomaterials, 19, p. 1275; Shirosaki, Y., Tsuru, K., Hayakawa, S., Osaka, A., Lopes, M.A., Santos, J.D., Fernandes, M.H., (2005) Biomaterials, 26, p. 485; Wang, J.H., Wei, C.W., Liu, H.C., Young, T.H., (2003) J. Biomed. Mater. Res, 64 A, p. 606; Michael, K.E., Vernekar, V.N., Keselowsky, B.G., Meredith, J.C., Latour, R.A., Garcia, A.J., (2003) Langmuir, 19, p. 8033; Keselowsky, B.G., Collard, D.M., Garcia, A.J., (2003) J. Biomed. Mater. Res, 66 A, p. 247; Cuy, J.L., Beckstead, B.L., Brown, C.D., Hoffman, A.S., Giachelli, C.M., (2003) J. Biomed. Mater. Res, 67 A, p. 538; McFarland, C.D., Mayer, S., Scotchford, C., Dalton, B.A., Steele, J.G., Downes, S., (1999) J. Biomed. Mater. Res, 44, p. 1; Cowles, E.A., Brailey, L.L., Gronowicz, G.A., (2000) J. Biomed. Mater. Res, 52, p. 725; Marco, R.A.W., Diaz-Montero, C.M., Wygant, J.N., Kleinerman, E.S., McIntyre, B.W., (2003) J. Cell. Biochem, 88, p. 1038; Martin, J.Y., Schwartz, Z., Hummert, T.W., Schraub, D.M., Simpson, J., Lankford, J., Dean, D.D., Boyan, B.D., (1995) J. Biomed. Mater. Res, 29, p. 389; Anselme, K., Bigerelle, M., Noel, B., Dufresne, E., Judas, D., Iost, A., Hardouin, P., (2000) J. Biomed. Mater. Res, 49, p. 155; Zinger, O., Anselme, K., Denzer, A., Habersetzer, P., Wieland, M., Jeanfils, J., Hardouin, P., Landolt, D., (2004) Biomaterials, 25, p. 2695
Keywords: Acetylation; AFM; article; Atomic force microscopy; Biocompatible Materials; biofilm; Biofilms; biomaterial; bone cell; cartilage cell; cell adhesion; cell anchorage; Cell culture; cell growth; Cell Line, Tumor; cell proliferation; Cell Shape; cell spreading; cell survival; Chemical structure; chemistry; Chitin; chitosan; comparative study; controlled study; cytoskeleton; Degree of acetylation; drug effect; Growth kinetics; human; human cell; Humans; incubation time; metabolism; Microscopy, Atomic Force; osteoblast; Osteoblast-like cells; Osteoblasts; Pathology; priority journal; Surface charge; Surface Properties; surface property; Surface treatment; tumor cell line; Zeta potential

Epidemiology of femur fractures in Portugal - Alves, S.F.; Pina, M.D.F.; Barbosa, M. (Epidemiologia das fracturas do fémur em Portugal: Fracturas do colo do fémur versus fracturas de outras localizações não especificadas do fémurArquivos de MedicinaArq. Med., 2007)
Fractures related to osteoporosis have been increasing in many countries. Femoral neck fractures have been widely studied, however little is known about other femur fractures and its relationship with osteoporosis. The main objective of this study is the comparison between the incidence of neck fractures attributed to osteoporosis with the ones that occurs in other places of femur other than the neck, in the same conditions. It was used a national database, under the regulation of a governmental institute, with registers from 2000 to 2002. From the total number of femural fractures the authors selected the registers corresponding to individuals with more than fifty years of age and due to low impact, it were analysed separately the femoral neck fractures (International Classification of Diseases codes, 9 th Revision, Clinical Modification, ICD9-CM codes 820 and derivates) from the fractures that occurred in other locations in the femur (ICD9-CM codes 821 and derivates). Case fatality rates and the incidence rates were calculated for that period of time, and an analysis of the variables age, days and costs of hospital admission as well as of the variable destination after discharge. Only 7.6% of the femural fractures were coded as 821.x, all the others were coded as 820.x. In both groups the fractures were more frequent in women (above 75%) and showed an exponential increase with age. The costs were higher in the 820.x fractures which also presented higher case fatality rates. ©ArquiMed, 2007.
Keywords: adult; aged; article; Female; femur; femur fracture; fracture; hip fracture; human; incidence; Low impact; male; Osteoporosis; outcome assessment; Portugal; risk assessment; survival

Linear and nonlinear analysis of heart rate patterns associated with fetal behavioral states in the antepartum period - Gonçalves, H.; Bernardes, J.; Paula Rocha, A.; Ayres-de-Campos, D. (Early Human DevelopmentEarly Hum. Dev., 2007)
Background: Fetal behavioral states are important indicators of fetal physiology and pathology associated to typical fetal heart rate (FHR) patterns. Aim: To provide linear and nonlinear analysis of FHR patterns associated with fetal behavioral states regarding a better understanding of these states and patterns. Study design and subjects: Fifty FHR tracings from normal term pregnancies with a median duration of 40.3 min were acquired with the SisPorto® 2.01 system for computerized analysis of cardiotocograms. Each tracing was divided into consecutive 10-minute segments and each segment was classified by two experts as pattern A, B, C or D. Outcome measures: Linear and nonlinear indices were computed in each segment, namely mean FHR, long-term irregularity index (LTI), very low (VLF), low (LF) and high (HF) frequency spectral indices, approximate entropy (ApEn) and sample entropy (SampEn). Kappa statistic (κ) and proportions of agreement (Pa) were used for assessment of inter-observer agreement. Bootstrap percentile confidence intervals and nonparametric statistical tests were calculated for statistical inference. Results: Overall agreement between experts in pattern classification was good to excellent with values for κ and Pa of 0.74 (95% CI: 0.64-0.94) and 0.94 (95% CI: 0.92-0.96), respectively. Most linear domain indices increased significantly with rising fetal activity whereas the opposite occurred with nonlinear indices, except for SampEn(2, 0.1). LF/(MF + HF) ratio also significantly increased with fetal activity, denoting an increased sympatho-vagal balance. Conclusions: Results support the hypothesis that entropy and linear variability indices measure different FHR features. FHR patterns associated with active sleep (B) and active wakefulness (D) evidenced more signs of autonomous nervous system activity, with sympatho-vagal imbalance, and less signs related to complexity or irregularity control systems than patterns associated with calm sleep (A) and calm wakefulness (C). © 2006 Elsevier Ireland Ltd. All rights reserved.
Cited By (since 1996): 17Export Date: 21 November 2012Source: ScopusCODEN: EHDEDdoi: 10.1016/j.earlhumdev.2006.12.006PubMed ID: 17261357Language of Original Document: EnglishCorrespondence Address: Gonçalves, H.; Universidade do Porto, Faculdade de Ciências, Departamento de Matemática Aplicada, Porto, Portugal; email: hernani.goncalves@fc.up.ptReferences: Nijhuis, J.G., Prechtl, H.F., Martin, C.B.J., Bots, R.S., Are there behavioural states in the human fetus? (1982) Early Hum Dev, 6, pp. 177-195;Nijhuis, I., ten Hof, J., Development of fetal heart rate and behavior: indirect measures to assess the fetal nervous system (1999) Eur J Obstet Gynaecol Reprod Biol, 87, pp. 1-2; Vindla, S., James, D., Fetal behaviour as a test of fetal wellbeing (1995) Br J Obstet Gynaecol, 102, pp. 597-600; Swartjes, J.M., van Geijn, H.P., Mantel, R., van Woerden, E.E., Schoemaker, H.C., Coincidence of behavioural state parameters in the human fetus at three gestational ages (1990) Early Hum Dev, 23, pp. 75-83; Ayres-de-Campos, D., Santos, C., Bernardes, J., Prediction of neonatal state by computer analysis of fetal heart rate tracings: the antepartum arm of the SisPorto® multicentre validation study (2005) Eur J Obstet Gynaecol Reprod Biol, 118, pp. 52-60; Ayres-de-Campos, D., Bernardes, J., Garrido, A., de Sá, J.M., Pereira-Leite, L., SisPorto 2.0: a program for automated analysis of cardiotocograms (2000) J Matern Fetal Med, 9, pp. 311-318; Rooth, G., Huch, A., Huch, R., FIGO news. Guidelines for the use of fetal monitoring (1987) Int J Gynaecol Obstet, 25, p. 159; Bernardes, J., Moura, C., de Sá, J.P.M., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-65; Gonçalves, H., Rocha, A.P., Ayres-de-Campos, D., Bernardes, J., Internal versus external intrapartum foetal heart rate monitoring: the effect on linear and nonlinear parameters (2006) Physiol Meas, 27, pp. 307-319; Signorini, M.G., Magenes, G., Cerrutti, S., Arduini, D., Linear and nonlinear parameters for the analysis of fetal heart rate signal from cardiotacographic recordings (2003) IEEE Trans Biomed Eng, 50 (3), pp. 365-373; Pincus, S., Viscarello, R., Approximate Entropy: a regularity measure for fetal heart rate analysis (1992) Obstet Gynaecol, 79 (2), pp. 249-255; Richman, J.S., Moorman, J.R., Physiological time-series analysis using approximate entropy and sample entropy (2000) Am J Physiol Heart Circ Physiol, 278, pp. H2039-H2049; Pincus, S., Approximate entropy (ApEn) as a complexity measure (1995) Chaos, 5 (1), pp. 110-117; Grant, J.M., The fetal heart rate trace is normal, isn't it? Observer agreement of categorical assessments (1991) Lancet, 337, pp. 215-218; Martinez, W.L., Martinez, A.R., (2002) Computational statistics handbook with MATLAB, , CRC Press; van Woerden, E.E., Geijn, H.P., Caron, F.J., Swartjes, J.M., Mantel, R., Arts, N.F., Automated assignment of behavioural states in the human near term fetus (1989) Early Hum Dev, 19, pp. 137-146; Ten Hof, J., Nijhuis, I.J., Mulder, E.J., Nijhuis, J.G., Narayan, H., Taylor, D.J., Longitudinal study of fetal body movements: nomograms, intrafetal consistency, and relationship with episodes of heart rate patterns A and B (2002) Pediatr Res, 52 (4), pp. 568-575; Bernardes, J., Costa-Pereira, A., de Campos, D.A., van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynaecol Obstet, 57 (1), pp. 33-37; Bernardes, J., Costa-Pereira, A., van Geijn, H.P., Pereira-Leite, L., A more objective fetal heart rate baseline estimation (1996) Br J Obstet Gynaecol, 103, pp. 714-715; Mantel, R., van Geijn, H.P., Ververs, I.A., Copray, F.J., Automated analysis of near-term antepartum fetal heart rate in relation to fetal behavioral states: the Sonicaid System 8000 (1992) Am J Obstet Gynaecol, 167 (6), pp. 1912-1914; Court, D.J., Parer, J.T., Experimental studies of fetal asphyxia and fetal heart rate interpretation (1984) Research in perinatal medicine, pp. 113-169. , Nathanielsz P.W., and Parer J.T. (Eds), Perinatology Press, New York; Oppenheimer, L.W., Lewinsky, R.M., Power spectral analysis of fetal heart rate (1994) Bailliere's Clin Obstet Gynaecol, 8 (3), pp. 643-661; van Woerden, E.E., Geijn, H.P., Caron, F.J., Mantel, R., Spectral analysis of fetal heart rhythm in relation to fetal regular mouthing (1990) Int J Biomed Comput, 25 (4), pp. 253-260; Boog, G., Analyse informatisée du rythme cardiaque foetal au cours de la grossesse et de l'accouchement (2004) Encycl Méd-Chir, 148 (5-49 -D-23), pp. 1-10; Suzuki, T., Okamura, K., Kimura, Y., Watanabe, T., Murotsuki, N.Y.J., Uehara, S., Power spectral analysis of R-R interval variability before and during the sinusoidal heart rate pattern in fetal lambs (2000) Am J Obstet Gynaecol, 182, pp. 1227-1232; Dawes, G.S., Moulden, M., Sheil, O., Redman, C.W.G., Approximate entropy, a statistic of regularity, applied to fetal heart rate data before and during labour (1992) Obstet Gynaecol, 80 (5), pp. 763-768; Magenes, G., Signorini, M.G., Arduini, D., Cerutti, S., Fetal heart rate variability due to vibroacoustic stimulation: linear and nonlinear contribution (2004) Methods Inf Med, 43 (1), pp. 47-51; Felgueiras, C., de Sá, J.P.M., Bernardes, J., Gama, S., Fractal characterisation of fetal heart rate sequences (1998) Biomed Eng, 36 (2), pp. 197-201; Vieira, P., Marques-de-Sá, J.P., Bernardes, J., Fractal analysis of foetal heart rate (2004) Proceedings of biosignal 2004, pp. 53-55. , Jan J., Kozumplík J., and Provazník I. (Eds), Vutium Press, Brno University of Technology; di Renzo, G.C., Montani, M., Fioriti, V., Clerici, G., Branconi, F., Pardini, A., Fractal analysis: a new method for evaluating fetal heart rate variability (1996) J Perinat Med, 24 (3), pp. 261-269
Keywords: adult; article; behavior change; Cardiotocography; Computerized analysis; controlled study; entropy; Female; Fetal behavioral states; Fetal heart rate; Fetal monitoring; fetus; fetus heart rate; fetus monitoring; Heart Rate, Fetal; human; Humans; Image Interpretation, Computer-Assisted; Linear Models; Nonlinear Dynamics; Pregnancy; SisPorto; Spectral analysis; vagus nerve stimulation

Opening wedge high tibial osteotomy using 3D biomodelling Bonelike® macroporous structures: Case report - Gutierres, M.; Dias, A.G.; Lopes, M.A.; Hussain, N.S.; Cabral, A.T.; Almeida, L.; Santos, J.D. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 2007)
Two synthetic calcium phosphates in porous wedge shape, Bonelike® and a commercial HA/β-TCP biphasic material, were used as an alternative to bone autografts and allografts in the treatment of medial compartment osteoarthritis of varus knees. The structure of Bonelike® has a 3D architecture that is computer controlled, and a composition that mimics the mineral composition of natural bone. The HA/β-TCP biphasic material used as a control material in this study was prepared using conventional foaming based methods. No signs of inflammatory reactions were observed post-operatively for both materials. After 4 months signs of fusion at the osteotomy site and good integration of the implanted wedges were observed, showing good mechanical resistance. Concerning the final correction attained, the left knee revealed a satisfactory valgus of 10°, but the right one only had a final value of 6°. The clinical evaluation using International Knee Score (IKS) showed good outcome in all parameters with complete range of motion in both knees and climbing stairs without crutches with only slight pain. © 2007 Springer Science+Business Media, LLC.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/s10856-007-3171-xPubMed ID: 17569003Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Laboratório de Biomateriais, Instituto de Engenharia Biomédica (INEB), Rua do Campo Alegre 823, Porto 4150-180, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; hydroxyapatite, 1306-06-5, 51198-94-8; Bone Substitutes; Calcium Phosphates; Ceratite, 124097-42-3; HydroxyapatitesTradenames: BonelikeReferences: Gaasbeek, R.D.A., Welsing, R.T.C., Verdonschot, N., Rijnberg, W.J., Van Loon, C.J.M., Van Kampen, A., (2005) Knee Surg. Sports Traumatol. Arthrosc., 13, p. 689. , 8;Scott, W.N., Clarke, H.D., (2004) Orthopedics, 27, p. 975. , 9; Virolainen, P., Aro, H.T., (2004) Arch. Orthop. Trauma Surg., 124, p. 258. , 4; Wright, J.M., Crockett, H.C., Slawski, D.P., Madsen, M.W., Windsor, R.E., (2005) J. Am. Acad. Orthop. Surg., 13, p. 279. , 4; Fujisawa, Y., Masura, K., Shiomi, S., (1979) Clin. Orthop. North Am., 10, p. 585; Odenbridge, S., Egund, N., Lindstrand, A., Lohmander, L.S., Willen, H., (1992) Clin Orthop., 277, p. 210; Koshino, T., Wada, S., Ara, Y., Saito, T., (2003) Knee, 10, p. 229; Hernigou, P., (2002) Knee, 9, p. 15. , 1; Hoell, S., Suttmoeller, J., Stoll, V., Fuchs, S., Gosheger, G., (2005) Arch. Orthop. Trauma Surg., 125, p. 638. , 9; Betz, R.R., (2002) Orthopedics, 25, p. 561. , 5; Legeros, R.Z., (2002) Clin. Orthop. Relat. Res., 395, p. 81; Steffen, T., Stoll, T., Arvinte, T., Schenk, R.K., (2001) Eur. Spine J., 10, p. 132; Chu, T.M.G., Orton, D.G., Hollister, S.J., Feinberg, S.E., Halloran, J.W., (2002) Biomaterials, 23, p. 1283. , 5; Hutmacher, D.W., Sittinger, M., Risbud, M.V., (2004) Trends Biotechnol., 22, p. 354. , 7; Jones, J.R., Ehrenfried, L.M., Hench, L.L., (2006) Biomaterials, 27, p. 964. , 7; Gauthier, O., Bouler, J.M., Aguado, E., Pilet, P., Daculsi, G., (1998) Biomaterials, 19, p. 133. , 1-3; LU, J.X., Flautre, B., Anselme, K., Hardouin, P., Gallur, A., Descamps, M., Thierry, B., (1999) J. Mater. Sci. Mater. Med., 10, p. 111. , 2; Martina, M., Subramanyam, G., Weaver, J.C., Hutmacher, D.W., Morse, D.E., Valiyaveettil, S., (2005) Biomaterials, 26, p. 5609. , 28; Moroni, L., De Wijn, J.R., Van Blitterswijk, C.A., (2006) Biomaterials, 27, p. 974. , 7; Duarte, F., Santos, J.D., Afonso, A., (2004) Adv. Mater. Forum, 455-456, p. 370; Lobato, J.V., Hussain, N.S., Botelho, C.M., Mauricio, A.C., Lobato, J.M., Lopes, M.A., Afonso, A., Santos, J.D., (2006) Thin Solid Films, 515, p. 279. , 1; Gutierres, M., Hussain, N.S., Afonso, A., Almeida, L., Cabral, T., Lopes, M.A., Santos, J.D., (2005) Bioceramics, 17, p. 1041; Lobato, J.V., Hussain, N.S., Botelho, C.M., Rodrigues, J.M., Luís, A.L., Maurício, A.C., Lopes, M.A., Santos, J.D., (2005) Key Eng. Mater., 284-286, p. 877; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., (2001) J. Biomed. Mater. Res., 54, p. 463; Leong, K.F., Cheah, C.M., Chua, C.K., (2003) Biomaterials, 24, p. 2363. , 13; Hutmacher, D.W., (2001) J. Biomater. Sci. Polym. Ed., 12, p. 107. , 1; Santos, J., Hastings, G., Knowles, J., Sintered hydroxyapatite compositions and method for the preparation thereof (1999), Worldwide Application (PCT), Patent No. 1 189 851Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., (1998) J. Biomed. Mater. Res., 39, p. 244. , 2; Lopes, M.A., Knowles, J.C., Santos, J.D., (2000) Biomaterials, 21, p. 1905. , 18; Schwartz, C., Liss, P., Jacquemaire, B., Lecestre, P., Frayssinet, P., (1999) J. Mater. Sci. Mater. Med., 10, p. 821. , 12; Van Hemert, W.L.W., Willems, K., Anderson, P.G., Van Heerwaarden, R.J., Wymenga, A.B., (2004) Knee, 11, p. 451. , 6; Gaasbeek, R.D.A., Toonen, H.G., Van Heerwaarden, R.J., Buma, P., (2005) Biomaterials, 26, p. 6713. , 33; Hernigou, P., Ma, W., (2001) Knee, 8, p. 103. , 2; Koshino, T., Murase, T., Saito, T., (2003) J. Bone Joint Surg. Am., 85, p. 78. , 1; Koshino, T., Murase, T., Takagi, T., Saito, T., (2001) Biomaterials, 22, p. 1579. , 12; Zhim, F., Laflamme, G.Y., Viens, H., Saidane, K., Yahia, L., (2005) Clin. Biomech., 20, p. 871. , 8; Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) Biomaterials, 20, p. 2085. , 21; Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mater. Res., 48, p. 734. , 5
Keywords: adult; article; Biological organs; Biomodeling; Bone; bone allograft; Bone graft; bone mineral; Bone Substitutes; calcium phosphate; Calcium phosphates; case report; climbing; clinical evaluation; Computer simulation; Grafts; human; Humans; hydroxyapatite; Hydroxyapatites; Imaging, Three-Dimensional; knee; knee pain; Macroporous structures; male; Mechanical properties; Middle Aged; Osteoarthritis; Osteoarthritis, Knee; Osteoblasts; osteotomy; pain assessment; porosity; Porous wedge shapes; priority journal; Prostheses and Implants; range of motion; structure analysis; tibia; tibia osteotomy; Tibial osteotomy; Valgus; valgus knee

Absorption and emission properties of Ho 3+ doped lead-zinc-borate glasses - Sooraj Hussain, N.; Ali, N.; Dias, A.G.; Lopes, M.A.; Santos, J.D.; Buddhudu, S. (Thin Solid FilmsThin Solid Films, 2006)
This paper reports on the affect of lead content on the absorption and emission spectra of the Ho 3+ ion doped lead-zinc-borate glasses in the composition (mol%) of (20 - x)PbO-20ZnO-(59 + x)B 2O 3-1.0Ho 2O 3 where x = 0, 5,10,15 of PbO content with λ exc = 405 nm. The experimental absorption band energies have satisfactorily been correlated with the theoretical results with an r.m.s deviation of zero with the following correction factors obtained by a least square fit analysis: ΔE 1 = 348.495936 cm
Cited By (since 1996): 18Export Date: 21 November 2012Source: ScopusCODEN: THSFAdoi: 10.1016/j.tsf.2005.12.085Language of Original Document: EnglishCorrespondence Address: Sooraj Hussain, N.; DEMM, Faculty of Eng. University of Porto, Rua Dr. Roberto Frias, 4200-465 Porto, Portugal; email: sooraj@fe.up.ptReferences: Song, J.H., Jong Heo, Park, S.H., (2003) J. Appl. Phys., 93, p. 9441;Chen, Q., Ferraris, M., Menke, Y., Milanese, D., Monchiero, E., (2003) J.Non-Cryst. Solids, 324, p. 1; Kassab, L.R.P., Courrol, L.C., Morais, A.S., Mendes, C.M.S.P., Tatumi, S.H., Wetter, N.U., Gomes, L., Salvador, V.L.R., (2002) J.Non-Cryst. Solids, 304, p. 233; Kityk, I.V., Wasylak, J., Kucharski, J., Dorosz, D., (2002) J .Non-Cryst. Solids, 297, p. 285; Souza Filho, A.G., Mendes Filho, J., Melo, F.E.A., Custodio, M.C.C., Lebullenger, R., Hernandes, A.C., (2000) .J. Phys. Chem. Solids, 61, p. 1535; Choi, Y.G., Jong Heo, (1997) J. Non-Cryst. Solids, 217, p. 199; Koepke, Cz., Wisniewski, K., Sikorski, L., Piatkowski, D., Kowalska, K., Naftaly, M., (2006) Opt. Mater., 28, p. 129; Szachowicz, M., Tascu, S., Joubert, M.-F., Moretti, P., Nikl, M., (2006) Opt. Mater., 28, p. 162; Kassab, L.R.P., de Oliveira Preto, A., Lozano, W., de Sá, F.X., Maciel, G.S., (2005) J. Non-Cryst. Solids, 351, p. 3468; Lavín, V., Lahoz, F., Martín, I.R., Rodríguez-Mendoza, U.R., Cáceres, J.M., (2005) Opt. Mater., 27, p. 1754; Karmakar, B., (2005) J. Solid State Chem., 178, p. 2663; Pisarski, W.A., Goryczka, T., Wodecka-Duś, B., Płońska, M., Pisarska, J., (2005) Mater. Sci. Eng., 122, p. 94; Speghini, A., Peruffo, M., Casarin, M., Ajo, D., Bettinelli, M., (2000) J. Alloys Comp., 300-301, p. 174; Fermi, F., Ingletto, G., Aschieri, C., Bettinelli, M., (1989) Inorg. Chim. Acta, 163, p. 123; Ingletto, Bettinelli, M., Di Sipio, L., Negrisolo, F., Aschieri, C., (1991) Inorg. Chim. Acta, 188, p. 201; Saisudha, M.B., Ramakrishna, J., (1996) Phys. Rev., B, 53, p. 6186; Zahara, A.-M., Zahra, C.Y., (1993) J. Non-Cryst. Solids, 155, p. 45; Motke, S.G., Yawale, S.P., Yawale, S.S., (2002) Bull. Mater. Sci., 25, p. 75; Peres, T., Litton, D.A., Capobianco, J.A., Garofalini, S.H., (1997) J. Non-Cryst. Solids, 221, p. 34; Reddy, M.R., Raju, S.B., Veeraiah, N., (2000) J. Phys. Chem. Solids, 61, p. 1567; Prasad, N.V.V., Annapurna, K., Sooraj Hussain, N., Buddhudu, S., (2003) Mater. Lett., 57, p. 2071; Sooraj Hussain, N., Prabhakara Reddy, Y., Buddhudu, S., (2001) Mater. Lett., 48, p. 303; Sooraj Hussain, N., Prabhakara Reddy, Y., Buddhudu, S., (2002) Spectrosc. Lett., 35 (2), p. 275; Sooraj Hussain, N., Prabhakara Reddy, Y., Rajamohan Reddy, K., Buddhudu, S., (2001) Phys. Chem. Glasses, 42 (6), p. 358; Sooraj Hussain, N., Annapurna, K., Prabhakara Reddy, Y., Buddhudu, S., (2002) J. Mater. Sci. Lett., 21, p. 397; Sooraj Hussain, N., Prabhakara Reddy, Y., Buddhudu, S., (2001) Mater. Res. Bull., 36, p. 1813; Sooraj Hussain, N., Prabhakara Reddy, Y., Buddhudu, S., (2002) Mater. Lett., 52, p. 429; Lakshminarayana, G., Buddhudu, S., (2005) Spectrochim. Acta, A, 62, p. 364; Judd, B.R., (1962) Phys. Rev., 127, p. 750; Ofelt, G.S., (1962) J. Chem. Phys., 37, p. 511; Weber, M.J., Matsinger, B.H., Domlan, V.L., Surratt, G.T., (1972) J. Chem. Phys., 57, p. 562; Rukmini, E., Jayasankar, C.K., (1995) Opt. Mater., 4, p. 529; Auzel, F., (1987) Spectroscopy of Solid State Lase-Type Materials, , Di Bartolo B. (Ed), Plenum, New York; Guery, C., Adam, J.L., Lucas, J., (1987) J. Lumin., 42, p. 266; Shelby, J.E., Ruller, J., (1987) Phys. Chem. Glasses, 28, p. 262; Wong, E.Y., (1961) J. Chem. Phys., 35, p. 544; Wong, E.Y., (1963) J. Chem. Phys., 38, p. 976; Hufner, S., (1978) Optical Spectra of Transparent Rare-Earth Compounds, , Academic Press, New York; Jorgensen, C.K., (1962) Orbitals in Atoms and Molecules, , Academic Press, London; Sinha, S.P., (1966) Complexes of Rare-Earths, , Pergamon Press, Oxford; Rao, T.V.R., Reddy, R.R., Nazeer Ahammed, Y., Parandamaiah, M., Sooraj Hussain, N., Buddhudu, S., Purandar, K., (2000) Infrared Phys. Technol., 41, p. 247; Weber, M.J., Ziegler, D.C., Angell, C.A., (1982) J. Appl. Phys., 53, p. 4344; Rai, S.B., (2002) Spectrochim. Acta, A, 58, p. 1559; Rakov, N., Maciel, G.S., de Araujo, C.B., Messaddeq, Y., (2002) J. Appl. Phys., 91, p. 1272; Villacampa, B., Orera, V.M., Merino, R.I., Cases, R., Alonso, P.J., Alcalá, R., (1991) Mater. Res. Bull., 26, p. 741; Weber, M.J., Matsinger, B.H., Donlan, V.L., Surratt, G.T., (1972) J. Chem. Phys., 57, p. 562; Quagliano, J.R., Richardson, F.S., Reid, M.F., (1992) J. Alloys Compd., 180, p. 131; McDugall, J., Hollis, D.B., Payne, M.J.P., (1994) Phys. Chem. Glasses, 35, p. 258; Cases, R., Chamarro, M.A., (1991) J. Solid State Chem., 90, p. 313
Keywords: Band energies; Doping (additives); Energy gap; glass; Glasses; Holmium; Holmium glasses; Light absorption; Luminescence; Luminescences; Luminescent transitions; Optical properties; Stimulated emission

Assessment of Bonelike® graft with a resorbable matrix using an animal model - Lobato, J.V.; Hussain, N.S.; Botelho, C.M.; Maurício, A.C.; Afonso, A.; Ali, N.; Santos, J.D. (Thin Solid FilmsThin Solid Films, 2006)
Synthetic bone grafts have been developed to provide an alternative to autografts and allografts. Bonelike® is a patented synthetic osteoconductive bone graft that mimics the mineral composition of natural bone. In the present preliminary animal studies a user-friendly version of synthetic bone graft Bonelike® have been developed by using a resorbable matrix, Floseal®, as a vehicle and raloxifene hydrochloride as a therapeutic molecule, that is known to decrease osteoclast activity and therefore enhanced bone formation. From histological and scanning electron microscopy evaluations, the use of Bonelike® associated with Floseal® and raloxifene hydrochloride showed that new bone was rapidly apposed on implanted granules and also that the presence of the matrix and therapeutic molecule does not alter the proven highly osteoconductivity properties of Bonelike®. Therefore, this association may be one step-forward for the clinical applications of Bonelike® scaffolds since it is much more easy-to-handle when compared to granular materials. © 2006 Elsevier B.V. All rights reserved.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: THSFAdoi: 10.1016/j.tsf.2005.12.153Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua Campo Alegre, 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptReferences: Hench, L.L., Wilson, J., (1993) An Introduction to Bioceramics, Singapore, , Scientific W. (Ed);Hench, L.L., (1998) Biomaterials, 19, p. 1419; Giannoudis, P.V., Dinopoulos, H., Tsiridis, E., (2005) Injury, 36 S, pp. S20; Murugan, R., Ramakrishma, S., (2005) Compos. Sci. Technol., 65, p. 2385; Ewers, R., Simons, B., (1992) Biomaterials-Hard tissue repair and replacement, pp. 67-80. , Elsiever, The Netherlands; Ilan, D.I., Ladd, A.L., (2002) Oper. Tech. Plast. Reconstr. Surg., 9, p. 151; Mary, E.A.R., Raymond, A.Y., (1998) Dent. Clin. North Am., 42, p. 491; Keating, J., McQueen, M., (2001) J. Bone Jt. Surg., 83 B, p. 3; Summers, B.M., Eisenstein, S.M., (2001) J. Bone Jt. Surg., 71 B, p. 677; Younger, E.M., Chapman, M.W., (1989) J. Orthop. Trauma, 3, p. 192; LeGeros, R.Z., (2002) Clin. Orthop. Res., 395, p. 81; Daculsi, G., (1998) Biomaterials, 19, p. 1473; Bohner, M., van Lenthe, G.H., Grunenfelder, S., Hirsiger, W., Evison, R., Muller, R., (2005) Biomaterials, 26, p. 6099; LeGeros, R.Z., (1981) Prog. Cryst. Growth Charact., 1-2, p. 1; LeGeros, R.Z., (1993) Dense Hydroxyapatite, An Introduction to Bioceramics, , World Scientific, Singapore; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., (1998) J. Biomed. Mater. Res., 39, p. 244; Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) Biomaterials, 20, p. 2085; Lopes, M.A., Silva, R.F., Monteiro, F.J., Santos, J.D., (1999) Biomaterials, 21, p. 749; Lopes, M.A., Knowles, J.C., Santos, J.D., (2000) Biomaterials, 21, p. 1905; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Oslen, I., (1998) J. Biomed. Mater. Res., 41, p. 649; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., (2000) Biomaterials, 21, p. 1165; Mathiasen, R.A., Cruz, R.M., (2004) Otolaryngol. Head Neck Surg., 131, p. 601; User, H.M., Robert, B.N., (2003) Urology, 62, p. 342; Kheirabadi, B.S., Field-Redley, A., Pearson, R., MacPhee, M., Drohan, W., Tuthill, D., (2002) J. Surg. Res., 106, p. 99; Gill, I.S., Ramani, A.P., Spaliviero, M., Xu, M., Finelli, A., Kaouk, J.H., Desai, M.M., (2005) Urology, 65, p. 463; Weaver, F.A., Hood, D.B., Zatina, M., Messina, L., Badduke, B., (2002) Ann. Vasc. Surg., 16, p. 286; Ettinger, B., Genant, H.K., Cann, C.E., (1985) Ann. Intern. Med., 102, p. 319; Manolagas, S., Kousteni, S., Jilka, R., (2002) Recent Prog. Horm. Res., 57, p. 385; Trontelj, J., Vovk, T., Bogataj, M., Mrhar, A., (2005) Pharmacol. Res., 52, p. 334; Bryant, H., Glasebrook, A.L., Yang, N.N., Sato, M., (1999) J. Steroid Biochem. Mol. Biol., 69, p. 37; Bjarnason, N.H., Haarbo, J., Byrjalsen, I., Alexandersen, P., Kauffman, R.F., Christiansen, C., (2001) Atherosclerosis, 154, p. 97; Somjen, D., Yoles, I., (2003) J. Steroid Biochem. Mol. Biol., 86, p. 93; Buelke-Sam, J., Bryant, H.U., Francis, P.C., (1998) Reprod. Toxicol., 12, p. 217; Black, L.J., Sato, M., Rowley, E.R., Magee, D.E., Bekele, A., Williams, D.C., Cullinan, G.J., Bryant, H.U., (1994) J. Clin. Invest., 93, p. 63; Delmas, P.D., Bjarnason, N.H., Mitlak, B.H., Ravoux, A.C., Shah, A.S., Huster, W.J., Draper, M., Christiansen, C., (1997) N. Engl. J. Med., 337, p. 1641; Lobato, J.V., Sooraj Hussain, N., Botelho, C.M., Rodrigues, J.M., Luis, A.L., Mauricio, A.C., Lopes, M.A., Santos, J.D., (2005) Key Eng. Mater., 284-286, p. 877; Gutierres, M., Sooraj Hussain, N., Afonso, A., Almeida, L., Cabral, T., Lopes, M.A., Santos, J.D., (2005) Key Eng. Mater., 284-286, p. 1041; Costa, M.A., Gutierres, M., Almeida, L., Lopes, M.A., Santos, J.D., Fernandes, M.H., (2004) Key Eng. Mater., 254-256, p. 821; Duarte, F.M., Santos, J.D., Afonso, A., (2004) Mat. Sci. Forum, 455-456, p. 370; Ross, M.H., Romrell, L.J., Kaye, G.I., (1995) Histology a Text and Atlas, New York
Keywords: animal model; Bone; Bonelike®; FloSeal®; Grafting (chemical); Histological analysis; Mathematical models; Raloxifene hydrochloride; Scanning electron microscopy

Characterization of fetal heart rate irregularity using approximate entropy and wavelet filtering - Magalhães, F.; Marques De Sá, J.P.; Bernardes, J.; Ayres-de-Campos, D. (Computers in CardiologyComput Cardiol, 2006)
Approximate Entropy (ApEn) has been used by several researchers as a means to characterize the irregularity of fetal heart rate (FHR), a major contributor to fetal risk assessment. The present work starts by analyzing the influence of accelerative and decelerative (AD) components of the FHR signal in the computation of ApEn. Having shown that the AD components may completely distort the ApEn evaluation we proceed to present two methods of eliminating the influence of the AD components: wavelet filtering; AD detection using specific algorithms based on well-established physiological criteria. We obtained good results with the first method when applied to simulated signals; however it proved unreliable in the practical application of discriminating normal from pathological fetal FHR. With the second method we were able to achieve this discrimination with high statistical significance.
Conference code: 73228Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusArt. No.: 4512006CODEN: COCADLanguage of Original Document: EnglishCorrespondence Address: Marques De Sá, J. P.; Faculdade de Engenharia, DEEC, Rua Dr. Roberto Frias, 4200-465 Porto, Portugal; email: jmsa@fe.up.ptReferences: Pincus, S., Approximate entropy as a measure of system complexity (1991) Proc. Natl. Acad. Sci. U.S.A, 88, pp. 2297-2301;Pincus, S., Randomness and degrees of irregularity (1996) Proc. Natl. Acad. Sci. U.S.A, 93, pp. 2083-2088; Pincus, S.M., Viscarello, R.R., Approximate entropy: A regularity measure for fetal heart rate (1992) Obstet. Gynecol, 2, pp. 249-255; Fleisher, L.A., Dipietro, J.A., Johnson, T.R., Pincus, S., Complementary and non-coincident increases in heart rate variability and irregularity during fetal development (1997) Clin. Sci, 4, pp. 345-349; van Leeuwen, P., Lange, S., Betterman, H., Gronemeyer, D., Hatzmann, W., Fetal heart rate variability and complexity in the course of pregnancy (1999) Early Human Develop, 54, pp. 259-269; Pincus, S., Assessing Serial Irregularity and its Implications for Health (2001) Ann N Y Acad Sci, 954, pp. 245-267; Cysarz, D., Betterman, H., van Leeuwen, P., Entropies of short binary sequences in heart period dynamics (2000) Am J Physiol Heart Circ Physiol, 6, pp. 2163-2172; Signorini, M.G., Magenes, G., Cerutti, S., Arduini, D., Linear and Nonlinear Parameters for the Analysis of Fetal Heart Rate Signal from Cardiotocographic Recordings (2003) IEEE Tr. BME, 50, pp. 365-373; Ayres-de-Campos, D., Bernardes, J., Garrido, A., Marques-de-Sá, J., Pereira-Leite, L., SisPorto 2.0 - A Program for Automated Analysis of Cardiotocograms (2000) J Matern Fetal Med, 9, pp. 311-318; Sá Couto, P.M., van Meurs, W.L., Bernardes, J.F., Marques de, S.J., Goodwin, J.A., Combined Model-Driven and Rule-Based Approach for Educational Simulation of Fetal Heart Rate (2002) Proc. 16th Biennial Int. Conf. Europ. Assoc. for Speech, Signal and Image Processing, pp. 400-402. , EURASIP, Brno, Czech Rep, pp; Marques de Sá, J.P., Characterization of fetal heart rate using approximate entropy (2005) Proc. IEEE Comp. in Cardiology 2005, 32, pp. 671-673
Keywords: Approximate entropy; Cardiology; Fetal heart rate; Neonatal monitoring; Occupational risks; Physiological models; risk assessment; Risk management; Safety engineering; Simulated signals; Statistical significance; Wavelet filtering

Error entropy in classification problems: A univariate data analysis - Silva, L.M.; Felgueiras, C.S.; Alexandre, L.A.; Marques de Sá, J. (Neural ComputationNeural Comp., 2006)
Entropy-based cost functions are enjoying a growing attractiveness in unsupervised and supervised classification tasks. Better performances in terms both of error rate and speed of convergence have been reported. In this letter, we study the principle of error entropy minimization (EEM) from a theoretical point of view. We use Shannon's entropy and study univariate data splitting in two-class problems. In this setting, the error variable is a discrete random variable, leading to a not too complicated mathematical analysis of the error entropy. We start by showing that for uniformly distributed data, there is equivalence between the EEM split and the optimal classifier. In a more general setting, we prove the necessary conditions for this equivalence and show the existence of class configurations where the optimal classifier corresponds to maximum error entropy. The presented theoretical results provide practical guidelines that are illustrated with a set of experiments with both real and simulated data sets, where the effectiveness of EEM is compared with the usual mean square error minimization. © 2006 Massachusetts Institute of Technology.
Cited By (since 1996): 7Export Date: 21 November 2012Source: Scopusdoi: 10.1162/neco.2006.18.9.2036PubMed ID: 16846386Language of Original Document: EnglishCorrespondence Address: Silva, L.M.; Institute de Engenharia Biomédica, Laboratório Sinal e Imagem Biomédica, 4200-465, Porto, Portugal; email: lmsilva@fe.up.ptReferences: Devroye, L., Gyorfi, L., Lugosi, G., (1996) A Probabilistic Theory of Pattern Recognition, , Berlin: Springer-Verlag;Erdogmus, D., Principe, J., Comparison of entropy and mean square error criteria in adaptive system training using higher order statistics (2000) Proceedings of the Intl. Conf., on ICA and Signal Separation, pp. 75-80. , Helsinki, Finland; Erdogmus, D., Principe, J.C., An error-entropy minimization algorithm for supervised training of nonlinear adaptive systems (2002) IEEE Transactions on Signal Processing, 50 (7), pp. 1780-1786; Kapur, J., (1993) Maximum-entropy Models in Science and Engineering (Rev. Ed), , New York: Wiley; Kullback, S., (1959) Statistics and Information Theory, , New York: Wiley; Linsker, R., Self-organization in a perceptual network (1988) IEEE Computer, 21, pp. 105-117; Marques De Sa, J., (2001) Pattern Recognition: Concepts, Methods and Applications, , Berlin: Springer-Verlag; Newman, D., Hettich, S., Blake, C., Merz, C., (1998) UCI Repository of Machine Learning Databases, , http://www.ics.uci.edu/~mlearn/MLRepository.html, Irvine: University of California, Irvine, Department of Information and Computer Sciences; Parzen, E., On the estimation of a probability density function and the mode (1962) Annals of Mathematical Statistics, 33, pp. 1065-1076; Press, W., Teukolsky, S., Vetterling, W., Flannery, B., (1992) Numerical Recipes in C: The Art of Scientific Computing, , Cambridge: Cambridge University Press; Principe, J.C., Xu, D., Fisher, J., Information theoretic learning (2000) Unsupervised Adaptive Filtering, Vol. 1: Blind Source Separation, 1, pp. 265-319. , S. Haykin (Ed.), New York: Wiley; Santos, J., Alexandre, L., Marques De Sá, J., The error entropy minimization algorithm for neural network classification (2004) Int. Conf. on Recent Advances in Soft Computing, , Nottingham, U.K.: Nottingham Trent University; Santos, J., Marques De Sa, J., Alexandre, L., Sereno, F., Optimization of the error entropy minimization algorithm for neural network classification (2004) Intelligent Engineering Systems Through Artificial Neural Networks, 14, pp. 81-86. , C. Dagli, A. Buczak, D. Enke, M. Embrechts, & O. Ersoy (Eds.), New York: American Society of Mechanical Engineers; Shannon, C.E., A mathematical theory of communication (1948) Bell System Technical Journal, 27, pp. 379-423; Silva, L., Marques De Sa, J., Alexandre, L., Neural network classification using Shannon's entropy (2005) European Symposium on Artificial Neural Networks, , Bruges, Belgium: d-side publications; Silverman, B., (1986) Density Estimation for Statistics and Data Analysis, , London: Chapman & Hall; Stoller, D., Univariate two-population distribution free discrimination (1954) Journal of the American Statistical Association, 49, pp. 770-777
Keywords: article; Classification; entropy; methodology; Models, Theoretical; normal distribution; theoretical model

Error entropy minimization for LSTM training - Alexandre, L.A.; Marques De Sá, J.P. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2006)
In this paper we present a new training algorithm for the Long Short-Term Memory (LSTM) recurrent neural network. This algorithm uses entropy instead of the usual mean squared error as the cost function for the weight update. More precisely we use the Error Entropy Minimization approach, were the entropy of the error is minimized after each symbol is present to the network. Our experiments show that this approach enables the convergence of the LSTM more frequently than with the traditional learning algorithm. This in turn relaxes the burden of parameter tuning since learning is achieved for a wider range of parameter values. The use of EEM also reduces, in some cases, the number of epochs needed for convergence. © Springer-Verlag Berlin Heidelberg 2006.
Conference code: 68317Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Alexandre, L.A.; Department of Informatics, IT-Networks and Multimedia Group, University of Beira Interior, Covilhã, Portugal; email: lfbaa@di.ubi.ptReferences: Hochreiter, S., Schmidhuber, J., Long short-term memory (1997) Neural Computation, 9 (8), pp. 1735-1780;Gers, F., Schmidhuber, J., Cummins, F., Learning to forget: Continual prediction with LSTM (2000) Neural Computation, 12 (10), pp. 2451-2471; Gers, F., Schmidhuber, J., Recurrent nets that time and count (2000) Proc. IJCNN'2000, Int. Joint Conf. on Neural Networks, , Como, Italy; Pérez-Ortiz, J., Gers, F., Eck, D., Schmidhuber, J., Kalman filters improve LSTM network performance in problems unsolvable by traditional recurrent nets (2003) Neural Networks, 16 (2), pp. 241-250; Haykin, S., (1999) Neural Networks: A Comprehensive Foundation, 2nd Edition, , Prentice Hall; Erdogmus, D., Principe, J., An error-entropy minimization algorithm for supervised training of nonlinear adaptive systems (2002) IEEE Trans. Signal Processing, 50 (7), pp. 1780-1786; Santos, J., Alexandre, L., Sereno, F., Marques De Sá, J., Optimization of the error entropy minimization algorithm for neural network classification (2004) ANNIE 2004, Intelligent Engineering Systems Through Artificial Neural Networks, 14, pp. 81-86. , St.Louis, USA, ASME Press Series; Santos, J., Alexandre, L., Marques De Sá, J., The error entropy minimization algorithm for neural network classification (2004) Proceedings of the 5th International Conference on Recent Advances in Soft Computing, pp. 92-97. , Lofti, A., ed.: Nottingham, United Kingdom; Silva, L., Marques De Sá, J., Alexandre, L., Neural network classification using Shannon's entropy (2005) 13th European Symposium on Artificial Neural Networks - ESANN 2005, pp. 217-222. , Bruges, Belgium
Keywords: Algorithms; Convergence of numerical methods; Cost function; entropy; Error Entropy Minimization; Errors; Long Short-Term Memory (LSTM); Neural networks; Optimization

Functionalization of chitosan membranes through phosphorylation: Atomic force microscopy, wettability, and cytotoxicity studies - Amaral, I.F.; Granja, P.L.; Melo, L.V.; Saramago, B.; Barbosa, M.A. (Journal of Applied Polymer ScienceJ. Appl. Polym. Sci., 2006)
Grafting negatively charged groups such as phosphates is a well-known strategy for inducing the deposition of apatite-like layers under simulated physiological conditions. In this investigation, chitosan was phosphorylated in an attempt to enhance its osteoconduction. Chitosan membranes were phosphorylated at 30°C with the H 3PO 4/ Et 3PO 4/P 2O 5/butanol reaction system for periods up to 48 h. This method is an alternative to the phosphoric acid/ urea/dimethylformamide phosphorylation method, which involves the use of much higher temperatures. In this study, the effects of the phosphorylation reaction time on the surface morphology and surface free energy of phosphorylated membranes were investigated with atomic force microscopy and static-contact-angle measurements, respectively. In addition, the modified membranes were evaluated with respect to their cytotoxiciry toward bone cells through the incubation of human osteoblastic cells with extracts of the materials for two different periods: 24 and 120 h. The results revealed a reduction of the average surface roughness at the nanometer scale with increasing phosphorylation reaction time. Wettability studies showed an increase in the polar component of the surface free energy with increasing reaction time as a result of the increase in the phosphate surface concentration. Cytotoxicity studies revealed no cytotoxic effect of phosphorylated membranes on osteoblastic cells, regardless of the incubation period. © 2006 Wiley Periodicals, Inc.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusCODEN: JAPNAdoi: 10.1002/app.23737Language of Original Document: EnglishCorrespondence Address: Amaral, I.F.; Laboratório de Biomateriais, Instituto de Engenharia Biomédica, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: iamaral@ineb.up.ptReferences: Tomihata, K., Ikada, Y., (1997) Biomaterials, 18, p. 567;VandeVord, P.J., Matthew, H.W.T., DeSilva, S.P., Mayton, L., Wu, B., Wooley, P.H., (2002) J Biomed Mater Res, 59, p. 585; Khor, E.C., (2001) Fulfilling a Biomaterials Promise, , Elsevier: Oxford; Peluso, G., Petillo, O., Ranieri, M., Santin, M., Ambrosio, L., Calabro, D., Avallone, B., Balsamo, G., (1994) Biomaterials, 15, p. 1215; Muzzarelli, R.A.A., (1997) CeUul Mol Life Sci, 53, p. 131; Ishihara, M., Nakanishi, K., Ono, K., Sato, M., Kikuchi, M., Saito, Y., Yura, H., Kurita, A., (2002) Biomaterials, 23, p. 833; Muzzarelli, R.A.A., Zucchini, C., Ilari, P., Pugnaloni, A., Belmonte, M.M., Biagini, G., Castaldini, C., (1993) Biomaterials, 14, p. 925; Muzzarelli, R.A.A., Mattiolibelmonte, M., Tietz, C., Biagini, R., Ferioli, G., Brunelli, M.A., Fini, M., Biagini, G., (1994) Biomaterials, 15, p. 1075; Madihally, S.V., Matthew, H.W.T., (1999) Biomaterials, 20, p. 1133; Zhao, F., Yin, Y.J., Lu, W.W., Leong, J.C., Zhang, W.J., Zhang, J.Y., Zhang, M.F., Yao, K.D., (2002) Biomaterials, 23, p. 3227; Lahiji, A., Sohrabi, A., Hungerford, D.S., Frondoza, C.G., (2000) J Biomed Mater Res, 51, p. 586; Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., (2005) J Biomed Mater Res Part A, 75, p. 387; Muzzarelli, R.A.A., Muzzarelli, C., (2002) Chitosan in Pharmacy and Chemistry, p. 233. , Muzzarelli, R. A. A.; Muzzarelli, C., Eds.; Atec Edizioni: Grottammare, Italy; Lee, J.Y., Nam, S.H., Im, S.Y., Park, Y.J., Lee, Y.M., Seol, Y.J., Chung, C.P., Lee, S.J., (2002) J Controlled Release, 78, p. 187; Ho, M.H., Wang, D.M., Hsieh, H.J., Liu, H.C., Hsien, T.Y., Lai, J.Y., Hou, L.T., (2005) Biomaterials, 26, p. 3197; Amaral, I.F., Cordeiro, A., Sampaio, P., Barbosa, M.A., J Biomat Sci: Polym, , accepted; Chatelet, C., Damour, O., Domard, A., (2001) Biomaterials, 22, p. 261; Hidaka, Y., Ito, M., Mori, K., Yagasaki, H., Kafrawy, A.H., (1999) J Biomed Mater Res, 46, p. 418; Mucalo, M.R., Yokogawa, Y., Suzuki, T., Kawamoto, Y., Nagata, F., Nishizawa, K., (1995) J Mater Sci: Mater Med, 6, p. 658; Tanahashi, M., Matsuda, T., (1997) J Biomed Mater Res, 34, p. 305; Yokogawa, Y., Rayes, J.P., Mucalo, M.R., Toriyama, M., Kawamoto, Y., Suzuki, T., Nishizawa, K., Kamayama, T., (1997) J Mater Sci: Mater Med, 8, p. 407; Granja, P.L., Barbosa, M.A., Pouysegu, L., De Jeso, B., Rouais, F., Baquey, C., (2001) J Mater Sci, 36, p. 2163; Amaral, I.F., Granja, P.L., Barbosa, M.A., (2005) J Biomater Sci Polym Ed, 16, p. 1575; Amaral, I.F., Granja, P.L., Barbosa, M.A., (2004) Key Eng Mater, 254, p. 577; Granja, P.L., Pouysegu, L., Petraud, M., De Jeso, B., Baquey, C., Barbosa, M.A., (2001) J Appl Polym Sci, 82, p. 3341; Touey, G.P., Kingsport, T., (1956), U.S. Pat. 2,759,924Fricain, J.C., Granja, P.L., Barbosa, M.A., De Jeso, B., Barthe, N., Baquey, C., (2002) Biomaterials, 23, p. 971; Sakaguchi, T., Horikoshi, T., Nakajima, A., (1981) Agric Biol Chem, 45, p. 2191; Sakairi, N., Shirai, A., Miyazaki, S., Tashiro, H., Tsuji, Y., Kawahara, H., Yoshida, T., Tokura, S., (1998) Kobunshi Ronbunshu, 55, p. 212; Lee, Y.M., Shin, E.M., (1991) J Membr Sci, 64, p. 145; Varma, H.K., Yokogawa, Y., Espinosa, F.F., Kawamoto, Y., Nishizawa, K., Nagata, F., Kameyama, T., (1999) Biomaterials, 20, p. 879; Yokogawa, Y., Nishizawa, K., Nagata, F., Kamayama, T., (1999) Bioceramics, p. 129. , Ohgushi, H.; Hastings, G. W.; Yoshikawa, T., Eds.; World Scientific: Singapore; Anselme, K., (2000) Biomaterials, 21, p. 667; Northup, S.J., Cammack, J., (1999) Handbook of Biomaterials Evaluation: Scientific, Technical, and Clinical Testing of Implant Materials, p. 325. , Recum, A. F., Ed.; Taylor & Francis: Philadelphia, PA; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., (2001) Polymer, 42, p. 3569; Terbojevich, M., Cosani, A., Muzzarelli, R.A.A., (1996) Carbohydr Polym, 29, p. 63; Grundke, K., Bogumil, T., Werner, C., Janke, A., Poschel, K., Jacobasch, H.J., (1996) Colloids Surf A, 116, p. 79; Kerkeb, M.L., Gonzalezcaballero, F., Chibowski, E., (1993) J Colloid Interface Sci, 159, p. 439; Andrade, J.D., Smith, L.M., Gregonis, D.E., (1985) Surface and Interfacial Aspects of Biomedical Polymers, p. 249. , Andrade, J. D., Ed.; Plenum: New York; Owens, D.K., Wendt, R.C., (1969) J Appl Polym Sci, 13, p. 1741; Berridge, M.V., Tan, A.S., McCoy, K.D., Wang, R., (1996) Biochemica, 4, p. 14; Mosmann, T., (1983) J Immunol Methods, 65, p. 55; Huang, R.Y.M., Moon, G.Y., Pal, R., (2001) J Membr Sci, 184, p. 1; Domke, J., Dannohl, S., Parak, W.J., Muller, O., Aicher, W.K., Radmacher, M., (2000) Colloids Surf B, 19, p. 367; MacDonald, D.E., Markovic, B., Allen, M., Somasundaran, P., Boskey, A.L., (1998) J Biomed Mater Res, 41, p. 120; Roberts, G.A.F., (1992) Chitin Chemistry, p. 350. , Macmillan: London; Andrade, J.D., (1992) Clin Mater, 11, p. 19; Wu, S., (1982) Polymer Interface and Adhesion, , Marcel Dekker: New York; Granja, P.L., Pouysegu, L., Deffieux, D., Daude, G., De Jeso, B., Labrugere, C., Baquey, C., Barbosa, M.A., (2001) J Appl Polym Sci, 82, p. 3354; Ratner, B.D., Caster, D.G., (1997) Surface Analysis - The Principal Techniques, p. 43. , Vickerman, J. C., Ed.; Wiley: Chichester, England; Barnes, A., Corkhill, P.H., Tighe, B.J., (1988) Polymer, 29, p. 2191; Domard, A., (1997) Advances in Chitin Science, p. 410. , Domard, A.; Roberts, G.; Vårum, K., Eds.; Jacques André: Lyon, France; Denuziere, A., Ferrier, D., Damour, O., Domard, A., (1998) Biomaterials, 19, p. 1275; Wang, X.H., Ma, J.B., Feng, Q.L., Cui, F.Z., (2002) Biomaterials, 23, p. 4591; Wang, X.H., Ma, J.B., Wang, Y.N., He, B.L., (2002) Biomaterials, 23, p. 4167; Hamano, T., Chiba, D., Nakatsuka, K., Nagahata, M., Teramoto, A., Kondo, Y., Hachimori, A., Abe, K., (2002) Polym Adv Technol, 13, p. 46
Keywords: Atomic force microscopy; Atomic force microscopy (AFM); Biocompatibility; Biological applications; Biological applications of polymers; Biomaterials; Chitin; chitosan; Chitosan membranes; grafting; Grafting (chemical); Osteoblastic cells; Phosphorylation; Polymeric membranes; polysaccharide; Polysaccharides; surface property; toxicity; Urea

Histological and scanning electron microscopy analyses of bone/implant interface using the novel Bonelike® synthetic bone graft - Gutierres, M.; Hussain, N.S.; Lopes, M.A.; Alfonso, A.; Cabral, A.T.; Almeida, L.; Santos, J.D. (Journal of Orthopaedic ResearchJ. Orthop. Res., 2006)
Synthetic bone grafts provide an alternative to autografts and allografts. Bonelike® is a patented synthetic bone graft that mimics the mineral composition of bone. The aim of the present work was to assess the biological behavior of Bonelike® graft in humans, before using the material in orthopedic applications of bone regeneration, for example, in opening wedge high tibial osteotomies for medial knee osteoarthritis. Bonelike® granules were implanted in cortical bone of 11 patients undergoing osteotomies, and new bone formation, osteoconductive properties, and resorption characteristics of the granules were analyzed. The granules ranged from 500 to 1000 μm and were implanted in the lateral aspect of the tibia. The patients' mean age was 59 years (range 48 to 70 years); there were eight women and three men, all suffering from medial compartment osteoarthritis of the knee. At surgery, a 1 × 1 × 1-cm cortical defect was created 3 cm distal to the entry point of the screws, in line with the long axis of tibia. The implanted Bonelike® graft sample was extracted for analysis during removal of the metallic prosthesis after implantation times of 6, 9, and 12 months. Radiological follow-up, scanning electron microscopy, histological analysis, and histomorphometric measurements were conducted on the retrieved samples to assess bone regeneration in the defect area. Osteoconductive capacity was demonstrated by extensive mature bone formation around the implanted granules and high levels of percentage bone-to-graft contact (from 67-84%). Bonelike® acted as an excellent bioactive scaffold, allowing the migration, proliferation, and differentiation of bone cells on its surface, and therefore regeneration of the defects was achieved in a rapid, controlled manner. Our results suggest that Bonelike® graft is an excellent candidate for orthopedic applications where rapid new bone formation is a fundamental requirement. © 2006 Orthopaedic Research Society. Published by Wiley Periodicals, Inc.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: JOREDdoi: 10.1002/jor.20117Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; DEMM, Faculty of Engg., University of Porto, Rua Dr. Roberto Frias, 4200-465 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: Bone SubstitutesTradenames: Bonelike; JSM 630IF, JeolManufacturers: JeolReferences: Peter, P., Heinrich, R., Meinrad, P., (2003) Orthopaedic Issues in Osteoporosis, , YH An, editor. Boca Raton, FL: CRC Press;Hench, L.L., Wilson, J., (1999) An Introduction to Bioceramics, , Singapore: World Scientific Publishing Co. Pvt. Ltd; Corpe, R.S., Steflik, D.E., Whitehead, R.Y., Correlative experimental animal and human clinical retrieval evaluations (2000) Crit Rev Biomed Eng, 28, pp. 395-398; Kitsugi, T., Yamamuro, T., Nakamura, T., Four calcium phosphate ceramics as bone substitutes for non-weight bearing (1993) Biomaterials, 14, pp. 216-224; Koshino, T., Murase, T., Takagi, T., New bone formation around porous hydroxyapatite wedge implanted in opening wedge high tibial osteotomy in patients with osteoarthritis (2001) Biomaterials, 22, pp. 1579-1582; LeGeros, R.Z., (1991) Calcium Phosphates in Oral Biology and Medicine, pp. 4-45. , Meyers HM, editor. New York: Karger; Macdonald, D.E., Betts, F., Stranick, M., Physicochemical study of plasma-sprayed hydroxyapatite-coated implants in humans (2001) J Biomed Mater Res, 54, pp. 480-490; Oonishi, H., Yamamoto, M., Ishimaru, H., The effect of hydroxyapatite coating on bone growth into porous titanium alloy implants (1989) J Bone Surg Br, 71, pp. 213-216; Thomas, K.A., Hydroxyapatite coatings (1994) Orthopedics, 17, pp. 267-278; Doron, H., Amy, L.L., Bone graft substitutes (2003) Oper Tech Plastic Reconstruct Surg, 9, pp. 151-160; Write, S., The bone-graft market in Europe. Commentary extracted from a report entitled "Emerging technologies in orthopedics I.: Bone graft substitutes, bone growth stimulators and bone growth factors" (1999), pp. 591-595. , London: Datamonitor plcBotelho, C.M., Brooks, R.A., Best, S.M., Biological and physical-chemical characterization of phase pure HA and si-substituted hydroxyapatite by different microscopy techniques (2004) Key Eng Mater, 254, p. 845; Costa, M.A., Gutierres, M., Almeida, L., In vitro mineralisation of human bone marrow cells cultured on bonelike® (2004) Key Eng Mater, 254-256, pp. 821-824; Gutierres, M., Hussain, N.S., Afonso, A., Biological behaviour of bonelike® graft Implanted in the tibia of humans (2005) Key Eng Mater, 284-286, pp. 1041-1044; Lopes, M.A., Santos, J.D., Monteiro, F.J., Glass reinforced hydroxyapatite: A comprehensive study of the effect of glass composition on the crystallography of the composite (1998) J Biomed Mater Res, 39, pp. 244-251; Lopes, M.A., Monteiro, F.J., Santos, J.D., Glass-reinforced hydroxyapatite composites: Fracture toughness and hardness dependence on microstructural characteristics (1999) Biomaterials, 20, pp. 2085-2090; Lopes, M.A., Silva, R.F., Monteiro, F.J., Microstructural dependence of Young's and shear moduli of P 2O 5 glass reinforced hydroxyapatite for biomedical applications (2000) Biomaterials, 21, pp. 749-754; Lopes, M.A., Knowles, J.C., Santos, J.D., Structural insights of glass-reinforced hydroxyapatite composites by Rietveld refinement (2000) Biomaterials, 21, pp. 1905-1910; Santos, J.D., Knowles, J.C., Reis, R.L., Microstructural characterization of glass-reinforced hydroxyapatite composites (1994) Biomaterials, 15, pp. 5-10; Lopes, M.A., Santos, J.D., Monteiro, F.J., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibia of rabbits (2001) J Biomed Mater Res, 54, pp. 463-469; Felson, D.T., Naimark, A., Anderson, J., The prevalence of knee osteoarthritis in the elderly: The Framingham Study (1987) Arthritis Rheum, 30, pp. 914-918; Guincamp, C., Pap, T., Schedel, J., Gene therapy in osteoarthritis (2000) Joint Bone Spine, 67, pp. 570-571; Marc, F., Serge, P., Mario, M.L.C., Assessment of the test-retest reliability and construct validity of a modified lequesne index in knee osteoarthritis (2003) Joint Bone Spine, 70, pp. 520-525; Pendleton, A., Arden, N., Dougados, M., EULAR recommendations for the management of knee osteoarthritis: Report of a task force of the Standing Committee for International Clinical Studies Including Therapeutic Trials (ESCISIT) (2000) Ann Rheum Dis, 59, pp. 936-944; Santos, J.D., Hastings, G.W., Knowles, J.C., Sintered hydroxyapatite compositions and method for the preparation thereof (1999) Eur. Pat. WO 0068164; Coventry, M.B., Osteotomy of the upper portion of the tibia for degenerative arthritis of the knee: A preliminary report (1965) J Bone Joint Surg Am, 47, p. 984; Hing, K.A., Assessment of porous hydroxyapatite for bone replacement (1996), (Ph D Thesis). London: University of LondonLopes, M.A., Knowles, J.C., Santos, J.D., Direct and indirect effects of P 2O 5-glass reinforced-hydroxyapatite composites and growth and function of osteoblast-like cells (2000) Biomaterials, 21, pp. 1165-1172; Lopes, M.A., Knowles, J.C., Santos, J.D., Flow cytometry for assessing biocompatibility (1998) J Biomed Mater Res, 41, pp. 649-656; Ross, M.H., Romrell, L.J., Kaye, G.I., (1995) Histology - A Text and Atlas, , 3rd ed. Baltimore, MD: Williams & Wilkins; Lobato, J.V., Hussain, N.S., Botelho, C.M., Assessment of the potential of Bonelike® graft for bone regeneration by using an animal model (2005) Key Eng Mater, 284-286, pp. 877-880; Duarte, F., Lopes, M.A., Santos, J.D., Bonelike® composites for the regeneration of bone lesions (2004) Mater Sci Forum, 455-456, pp. 370-373; Laurencin, C.T., (2003) Bone Graft Substitutes, , West Conshohocken, PA: ASTM International
Keywords: adult; aged; article; Bone; Bone and Bones; bone cell; bone conduction; bone development; Bone graft; bone prosthesis; bone radiography; Bone Regeneration; bone screw; Bone Substitutes; bone transplantation; Bonelike®; cell differentiation; cell migration; cell proliferation; Clinical applications; clinical article; controlled study; Female; follow up; Histological analysis; histology; human; Humans; knee osteoarthritis; male; Microscopy, Electron, Scanning; Middle Aged; morphometrics; orthopedics; ossification; Osteoconduction; Osteogenesis; osteolysis; Pathology; priority journal; Prostheses and Implants; prostheses and orthoses; prosthesis material; Scanning electron microscopy; surgical technique; Synthetic bone graft; tibia osteotomy; ultrastructure

In vivo performance of biodegradable calcium phosphate glass ceramics using the rabbit model: Histological and SEM observation - Dias, A.G.; Lopes, M.A.; Santos, J.D.; Afonso, A.; Tsuru, K.; Osaka, A.; Hayakawa, S.; Takashima, S.; Kurabayashi, Y. (Journal of Biomaterials ApplicationsJ. Biomater. Appl., 2006)
Two MK5 (45CaO-45P 2O 5-5MGO-5K 2O, in mol% and MT13 (45CaO-37P 2O 5-5MgO-13TiO 2, in mol%) glasses are prepared in the meta- and pyrophosphate regions and crystallized to obtain MK5B and MT13B, respectively. MK5B was obtained by controlled crystallization, and MT13B by powder sintering. As a result of these heat treatment processes, the crystalline phases precipitated in the glassy matrix are KCa(PO 3) 3, β-Ca(PO 3) 2, β-Ca 2P 2O 7 and Ca 4P 6O 19 phases for MK5B and CaTi 4(PO 4) 6, TiP 2O 7, α- and β-Ca 2P 2O 7 phases for MT13B. To assess the in vivo biological behavior of these glass ceramics, a mixed granulometry in the range 250-355 μm and 355-425 μm with a ratio of 1/1 was implanted for 2, 4, and 12 weeks in the tibiae of Japanese white rabbits. The results showed that the in vivo behavior was strongly affected by their solubility. All implanted materials, MK5B and MT13B, and β-tricalcium phosphate (β-TCP) as control material, showed signs of degradation in vivo. However, the levels of degradation were quite different throughout the implantation periods. The highest degradation was observed for MK5B glass ceramic and the lowest for MT13B with β-TCP in-between. All implanted materials allow for new bone formation in the bone defect area. At the longest implantation period (12 weeks), the MT13B and β-TCP materials were almost completely surrounded by new bone tissue, whereas MK5B showed some unfilled spaces. This behavior is discussed in terms of the high degradation observed in previous studies. © 2006 SAGE Publications.
Cited By (since 1996): 10Export Date: 21 November 2012Source: ScopusCODEN: JBAPEdoi: 10.1177/0885328206052466Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Instituto de Engenharia Biomédica (INEB), Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; Bone Substitutes; calcium phosphate, 10103-46-5; Calcium Phosphates; CeramicsReferences: Parikh, S.N., Bone Graft Substitutes in Modern Orthopedics (2002) Orthopedics, 25 (11), pp. 1301-1309;Tomford, W.W., Bone Allografts: Past, Present and Future (2000) Cell and Tissue Banking, 1, pp. 105-109; Betz, R.R., Limitations of Autograft and Allograft: New Synthetic Solutions (2002) Orthopedics, 25 (5), pp. S561-S570; Lane, J.M., Tomin, E., Bostrom, M.P.G., Biosynthetic Bone Grafting, Clinical Orthopaedics and Related Research (1999) Supplement S, 367, pp. S107-S117; Gazdag, A.R., Lane, J.M., Glaser, D., Forster, R.A., Alternatives to Autogenous Bone Graft: Efficacy and Indications (1995) Journal of the American Academy of Orthopaedic Surgeons, 3 (1); Vaccaro, A.R., The Role of the Osteoconductive Scaffold in Synthetic Bone Grafts (2002) Orthopedics, 25 (5), pp. S571-S578; Damien, C.J., Parsons, J.R., Bone-Graft and Bone-Graft Substitutes - A Review of Current Technology and Applications (1991) Journal of Applied Biomaterials, 2 (3), pp. 187-208; Porter, A.E., Patel, N., Skepper, J.N., Best, S.M., Bonfield, W., Comparison of in vivo Dissolution Processes in Hydroxyapatite and Silicon-substituted Hydroxyapatite Bioceramics (2003) Biomaterials, 24 (25), pp. 4609-4620; Raynaud, S., Champion, E., Lafon, J.P., Bernache-Assollant, D., Calcium Phosphate Apatites with Variable Ca/P Atomic Ratio III Mechanical Properties and Degradation in Solution of Hot Pressed Ceramics (2002) Biomaterials 23, 4, pp. 1081-1089; Klein, C., Wolke, J.G.C., Deblieckhogervorst, J.M.A., Degroot, K., Features of Calcium-Phosphate Plasma-Sprayed Coatings - An in-vitro Study (1994) Journal of Biomedical Materials Research, 28 (8), pp. 961-967; Brow, R.K., Review: The Structure of Simple Phosphate Glasses (2000) Journal of Non-Crystalline Solids, 263 (1-4), pp. 1-28; Shelby, J.E., (1997) Introduction to Glass Science and Technology, , The Royal Society of Chemistry, UK; Fini, M., Giardino, R., In vitro and in vivo Tests for the Biological Evaluation of Candidate Orthopedic Materials: Benefits and Limits (2003) Journal of Applied Biomaterials & Biomechanics, 1, pp. 155-163; Ratner, B.D., Hoffman, A.S., Schoen, F.J., Lemons, F.J., (1996) Biomaterials Science: An Introduction to Materials in Medicine, , Academic Press; Dias, A.G., Lopes, M.A., Gibson, I.R., Santos, J.D., In vitro Degradation Studies of Calcium Phosphate Glass Ceramics Prepared by Controlled Crystallization (2003) Journal of Non-Crystalline Solids, 330 (1-3), pp. 81-89; Dias, A.G., Lopes, M.A., Santos, J.D., Protein Adsorption Effect on in vitro Acellular Biodegradation of CaO-P 2O 5 Glass Ceramics (2004) Advanced Materials Forum, 455-456, pp. 398-401; Dias, A.G., Skakle, J.M.S., Gibson, I.R., Lopes, M.A., Santos, J.D., In situ Thermal and Structural Characterization of Bioactive Calcium Phosphate Glass Ceramics Containing TiO 2 and MgO Oxides: HT-XRD Studies (2005) Journal of Non-Crystalline Solids, 351, pp. 810-817; Dias, A.G., Tsuru, K., Hayakawa, T., Lopes, M.A., Santos, J.D., Osaka, A., Crystallisation Studies of Biodegradable CaO-P 2O 5 Glass with MgO and TiO 2 for Bone Regeneration Applications (2004) Glass Technology, 45 (2), pp. 78-79; Gross, U., Muller-Mai, C., Voigt, C., Mesgarian, M., Berger, G., Ploska, U., Tissue Response in the Femur of Rabbits after Implantation of a New Calcium Titanium Phosphate Composition (2000) Key Engineering Materials, 192, pp. 383-386; Kitsugi, T., Yamamuro, T., Nakamura, T., Masanori, O., Transmission Electron Microscopy Observations at the Interface of Bone and Four Types of Calcium Phosphate Ceramics with Different Calcium/ Phosphorous Molar Ratios (1995) Biomaterials, 16 (14), pp. 1101-1107; Chun, S., Jeong, J.H., Kim, K-H., Kim, S., Biodegradation Study of Amorphous and Crystalline Calcium Metaphosphate in the SBF and Tris-buffer Solution (2000) Key Engineering Materials, 192, pp. 131-134; Chun, S., Na, S.W., Lee, J.H., Chung, J.P., Ryu, I.C., Kim, S.Y., Biodegradation Study of Potassium Calcium Metaphosphate in the SBF and Tris-buffer Solution (2002) Key Engineering Materials, 218, pp. 149-152; Lin, F.H., Liao, C.J., Chen, K.S., Sun, J.S., Liu, H.C., Degradation Behaviour of a New Bioceramic: Ca 2P 2O 7 with Addition of Na 4P 2O 7 · 10H 2O (1997) Biomaterials, 18 (13), pp. 915-921; Koerten, H.K., van der Meulen, J., Degradation of Calcium Phosphate Ceramics (1999) Journal of Biomedical Materials Research, 44 (1), pp. 78-86; Kwon, S.H., Jun, Y.K., Hong, S.H., Kim, H.E., Synthesis and Dissolution Behavior of Beta-TCP and HA/Beta-TCP Composite Powders (2003) Journal of the European Ceramic Society, 23 (7), pp. 1039-1045; Lu, J.X., Gallur, A., Flautre, B., Anselme, K., Descamps, M., Thierry, B., Comparative Study of Tissue Reactions to Calcium Phosphate Ceramics among Cancellous, Cortical, and Medullar Bone Sites in Rabbits (1998) Journal of Biomedical Materials Research, 42 (3), pp. 357-367; Yuan, H.P., De Bruijn, J.D., Li, Y.B., Feng, J.Q., Yang, Z.J., De Groot, K., Zhang, X.D., Bone Formation Induced by Calcium Phosphate Ceramics in Soft Tissue of Dogs: A Comparative Study Between Porous α-TCP and Β-TCP (2001) Journal of Materials Science-Materials in Medicine, 12 (1), pp. 7-13; Jiaxi, L., Michel, D., Jacques, D., Gilles, K., Pierre, H., Jacques, L., The Biodegradation Mechanism of Calcium Phosphate Biomaterials in Bone Journal of Biomedical Materials Research (Applied Biomaterials), 63, pp. 408-412; Legeros, R.Z., Biodegradation and Bioresorption of Calcium Phosphate Ceramics (1993) Clinic Materials, 14, pp. 65-88; Yli-Urpo, H., Vallittu, P.K., Narhi, T.O., Forsback, A.P., Vakiparta, M., Release of Silica, Calcium, Phosphorus, and Fluoride from Glass Ionomer Cement Containing Bioactive Glass (2004) Journal of Biomaterials Applications, 19 (1), pp. 5-20; John, A., Varma, H.K., Kumari, T.V., Surface Reactivity of Calcium Phosphate based Ceramics in a Cell Culture System (2003) Journal of Biomaterials Applications, 18 (1), pp. 63-78; Dias, A.G., Lopes, M.A., Gibson, I.R., Skakle, J.M.S., Tsuru, K., Hayakawa, S., Osaka, A., Santos, J.D., Studies of Calcium Phosphate Glass Ceramic Containing TiO 2 and MgO Ions: Dissolution Behavior, , vitro (submitted)
Keywords: Absorbable Implants; animal; Animals; article; Biodegradable glass ceramics; biodegradable implant; Biodegradation; bone prosthesis; Bone Substitutes; bone tissue; Calcium Compounds; calcium phosphate; Calcium phosphates; ceramics; chemistry; disease model; Disease Models, Animal; glass; Glass ceramics; histology; Imaging techniques; In vivo testing; materials testing; Optical microscopy; Pathology; rabbit; Rabbits; Scanning electron microscopy; tibia fracture; Tibial Fractures; Tissue; treatment outcome; X ray diffraction analysis

The influence of functional groups of self-assembled monolayers on fibrous capsule formation and cell recruitment - Barbosa, J.N.; Madureira, P.; Barbosa, M.A.; Águas, A.P. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2006)
The contribution of the surface chemistry of an implant to the thickness of the fibrous capsule formed after implantation was herein investigated. For that, self-assembled monolayers (SAMs) of alkanethiols on gold with different terminal functional groups (COOH, OH, and CH 3) were used. These surfaces were implanted in subcutaneous air pouches of BALB/c mice and the ensuing fibrous capsules were evaluated and compared with the initial inflammatory response caused by the implant. The thickness of the fibrous capsules that are under organization around the implant was measured 1 week after implantation by histology. Inflammatory exudates were collected from the air pouches 24 h after the implantation of SAMs and were analyzed by flow cytometry. A significant increase in the thickness of fibrous capsules was seen around implanted CH 3-terminated SAMs, and also in gold surfaces, in comparison with the air pouch wall of sham-operated mice and of COOH- and OH-covered SAMs. The CH 3-coated implants also recruited higher numbers of inflammatory cells; this enhancement involved a significant number of Mac-1 + cells. Our data indicate that implant surfaces coated with CH 3 induce thick fibrous capsules and this may be the result of the stronger inflammatory effect of CH 3 in comparison with COOH or OH chemical groups. © 2005 Wiley Periodicals, Inc.
Cited By (since 1996): 13Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30602Language of Original Document: EnglishCorrespondence Address: Barbosa, J.N.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: judite@ibmc.up.ptChemicals/CAS: gold, 7440-57-5; thiol derivative, 13940-21-1; Biocompatible Materials; Gold, 7440-57-5; Sulfhydryl CompoundsReferences: Babensee, J.E., Anderson, J.M., McIntire, L.V., Mikos, A.G., Host response to tissue engineered devices (1998) Adv Drug Deliv Rev, 33, pp. 111-139;Anderson, J.M., In vivo biocompatibility of implantable delivery systems and biomaterials (1994) Eur J Pharm Biopharm, 40, pp. 1-8; Anderson, J.M., Biological responses to materials (2001) Annu Rev Mater Res, 31, pp. 81-110; Tang, L., Eaton, J.W., Inflammatory responses to biomaterials (1995) Am J Clin Pathol, 103, pp. 466-471; Mrksich, M., Whitesides, G.M., Interactions of SAM's with proteins (1996) Annu Rev Biophys Biomol Struct, 25, pp. 55-57; Ulman, A., Formation and structure of self-assembled monolayers (1996) Chem Rev, 96, pp. 1533-1554; Mrkisich, M., Tailored substrates for studies of attached cell culture (1998) Cell Mol Life Sci, 54, pp. 653-662; Pan, S., Castner, D.G., Ratner, B.D., Multitechnique surface characterization of derivatization efficiences for hydroxyl-terminated self-assembled monolayers (1998) Langmuir, 14, pp. 3545-3550; Sedwick, A.D., Sin, Y.M., Edwards, J.C., Willoughby, D.A., Increased inflammatory reactivity in newly formed lining tissue (1983) J Pathol, 141, pp. 483-495; Castro, A.G., Esaguy, N., Macedo, P.M., Águas, A.P., Silva, M.T., Live but not heat-killed mycobacteria cause rapid chemotaxis of large numbers of eosinophils in vivo and are ingested by the attracted granulocytes (1991) Infect Immun, 59, pp. 3009-3014; Isaji, M., Momose, Y., Naito, J., Enhancement of inflammatory reactions in a non-immunological air pouch model in rats (1989) Br J Exp Pathol, 70, pp. 705-716; Martins, M.C.L., Naeemi, E., Ratner, B.D., Barbosa, M.A., Albumin adsorption on cibacron blue F3G-A immobilized onto oligo(ethylene glycol)-terminated self-assembled monolayers (2003) J Mater Sci Mater Med, 14, pp. 945-954; Lin, J., Chuang, W., Synthesis, surface characterization, and platelet reactivity evaluation for the self-assembled monolayer of alkanethiol with sulfonic acid functionality (2000) J Biomed Mater Res, 51, pp. 413-423; Thomsen, P., Gretzer, C., Macrophage interactions with modified materials surfaces (2001) Curr Opin Solid State Mater Sci, 5, pp. 163-176; Tegoulia, V.A., Cooper, S.L., Leukocyte adhesion on model surfaces under flow: Effects of surface chemistry, protein adsorption, and shear rate (2000) J Biomed Mater Res, 50, pp. 291-301; Tsai, M., Lin, J., Surface characterization and platelet adhesion studies of self-assembled monolayers with phosphonate ester and phosphonic acid functionalities (2001) J Biomed Mater Res, 55, pp. 554-565; Ostuni, E., Yan, L., Whitesides, G.M., The interaction of proteins and cells with self-assembled monolayers of alkanethiolates on gold and silver (1999) Colloids Surf B, 15, pp. 3-30; Yang, S., Ren, W., Park, Y., Sieving, A., Hsu, S., Nasser, S., Wooley, P.H., Diverse cellular and apoptotic responses to variant shapes of UHMWPE particles in a murine model of inflammation (2002) Biomaterials, 23, pp. 3535-3543; Sieving, A., Wu, B., Mayton, L., Nasser, S., Wooley, P.H., Morphological characteristics of total joint arthroplasty-derived ultrahigh molecular weight polyethylene (UHMWPE) wear debris that provoke inflammation in a murine model of inflammation (2003) J Biomed Mater Res A, 64, pp. 457-464; Barbosa, J.N., Barbosa, M.A., Águas, A.P., Inflammatory responses and cell adhesion to self-assembled monolayers of alkanethiolates on gold (2004) Biomaterials, 25, pp. 2557-2563; Anderson, D.C., Springer, T.A., Leukocyte adhesion deficiency: An inherited defect in the Mac-1, LFA-1 and p150, 95 glycoproteins (1987) Annu Rev Med, 38, pp. 175-184; Murphy, R.T., Foley, J.B., Crean, P., Walsh, M.J., Reciprocal activation of leukocyte-endothelial adhesion molecules in acute coronary syndromes (2003) Int J Cardiol, 90, pp. 247-252; Tang, L., Wu, Y., Timmons, R.B., Fibrinogen adsorption and host tissue responses to plasma functionalized surfaces (1998) J Biomed Mater Res, 42, pp. 156-163; Barbosa, J.N., Madureira, P., Barbosa, M.A., Águas, A.P., The attraction of Mac-1 + phagocytes during acute inflammation by methyl-coated self-assembled monolayers (2005) Biomaterials, 26, pp. 3021-3027
Keywords: animal; animal cell; animal experiment; animal model; animal tissue; Animals; article; Bagg albino mouse; Biocompatible Materials; biomaterial; chemistry; controlled study; flow cytometry; functional group; gold; histology; implantation; Inflammation; male; Mice; Mice, Inbred BALB C; Monolayers; mouse; nonhuman; Self assembly; Self-assembled monolayers; Sulfhydryl Compounds; Surface chemistry; thiol derivative; tissue reaction; Tissue responses

Internal versus external intrapartum foetal heart rate monitoring: The effect on linear and nonlinear parameters - Gonçalves, H.; Rocha, A.P.; Ayres-de-Campos, D.; Bernardes, J. (Physiological MeasurementPhysiol. Meas., 2006)
The effect of foetal heart rate (FHR) acquisition mode on linear and nonlinear parameters is still largely unknown. In 33 normal labouring women, FHR signals were acquired simultaneously by an external ultrasound sensor applied to the maternal abdomen and an internal scalp electrode, in the minutes preceding delivery. For each case, the initial and final 5, 10 and 20 min segments were analysed, considering FHR signals at a frequency of 4 Hz (the frequency at which they are transmitted by the majority of commercialized foetal monitors). Several time and frequency domain linear and nonlinear FHR indices were computed in these segments, namely mean FHR, very low frequency (VLF), low frequency (LF), high frequency (HF), approximate entropy (ApEn) and sample entropy (SampEn). Parametric confidence intervals, statistical tests and correlation coefficients were calculated in order to evaluate the effect of internal versus external FHR monitoring modes on the considered indices. The whole evaluation was repeated using FHR signals at a frequency of 2 Hz. Most time domain linear indices were similar with external and internal monitoring in the initial and final segments of the tracings. However, linear frequency domain indices were poorly correlated in the final segments and had significantly different mean values in the initial segments. Nonlinear indices were significantly different in both initial and final segments. The correlation between 4 and 2 Hz sampled parameters was high for both linear and nonlinear indices (most correlation coefficient values ranging between 0.95 and 1) but nonlinear index values were significantly higher at 2 Hz. In conclusion, the mode used to acquire FHR signals and the sampling rate employed can significantly affect most FHR indices. © 2006 IOP Publishing Ltd.
Cited By (since 1996): 15Export Date: 21 November 2012Source: ScopusCODEN: PMEAEdoi: 10.1088/0967-3334/27/3/008PubMed ID: 16462016Language of Original Document: EnglishCorrespondence Address: Gonçalves, H.; Departamento de Matemática Aplicada, Faculdade de Ciências, Universidade Do Porto, Porto, Portugal; email: hernani.goncalves@fc.up.ptReferences: Ayres-De-Campos, D., Bernardes, J., Garrido, A., Marques-De-Sá, J., Pereira-Leite, L., SisPorto 2.0: A program for automated analysis of cardiotocograms (2000) J. Matern. Fetal Med., 9 (5), pp. 311-318;Ayres-De-Campos, D., Bernardes, J., Reynolds, A., Saraiva, J.P., Santos, C., Pereira-Leite, L., Computer evaluation of internal versus external FHR monitoring in the minutes preceding delivery (2000) Int. J. Gynecol. Obstet., 70, pp. 60-B61; Ayres-De-Campos, D., Santos, C., Bernardes, J., Prediction of neonatal state by computer analysis of fetal heart rate tracings: The antepartum arm of the SisPorto ®multicentre validation study (2005) Eur. J. Obstet. Gynecol. Reprod. Biol., 118 (1), pp. 52-60; Bakker, P.C., Colenbrander, G.J., Verstraeten, A.A., Geijn, V., The quality of intrapartum fetal heart rate monitoring (2004) Eur. J. Obstet. Gynecol. Reprod. Biol., 116 (1), pp. 22-27; Bernardes, J., Ayres-De-Campos, D., Costa-Pereira, A., Pereira-Leite, L., Garrido, A., Objective computerized fetal heart rate analysis (1998) Int. J. Gynecol. Obstet., 62 (2), pp. 141-147; Bernardes, J., Costa-Pereira, A., The effect of different sampling intervals on the measurement of intrapartum fetal heart rate variability (1997) Obstet. Gynecol., 90 (2), pp. 318-319; Bernardes, J., Garrido, A., Computerized fetal heart rate analysis in labour based on 2-s sampling. Can it proceed with confidence? (1995) Eur. J. Obstet. Gynecol. Reprod. Biol., 63 (1), pp. 105-107; Bernardes, J., Moura, C., Marques-De-Sá, J.P., Pereira-Leite, L., The Porto system for automated cardiotocographic signal analysis (1991) J. Perinat. Med., 19, pp. 61-65; Bernardes, J., Moura, C., Marques-De-Sá, J.P., Van Geijn, H.P., Pereira-Leite, L., The Porto system (1994) A Critical Appraisal of Fetal Surveillance, pp. 315-324; Boog, G., Analyse informatisée du rythme cardiaque fetal au cours de la grosssesse et de l'accouchement (2004) Encyclopédie Médico-Chirurgicale, 148; Boos, A., Jagger, M.H., Paret, G.W., Hausmann, J.W., A new, lightweight fetal telemetry system (1995) Hewlett-Packard J., pp. 82-93; Carter, M.C., Signal processing and display-cardiotocographs (1993) Br. J. Obstet. Gynaecol., 100, pp. 21-23; Chaffin, D.G., Barnard, J.M., Phernetton, T., Reed, K.L., Decreased approximate entropy of heart rate variability in the hypoxic ovine fetus (1998) J. Matern. Fetal Invest., 8, pp. 23-26; Chang, A., Sahota, D.S., Reed, N.N., James, D.K., Mohajer, M.P., Computerised fetal heart rate analysis in labour-effect of sampling rate (1995) Eur. J. Obstet. Gynecol. Reprod. Biol., 59 (2), pp. 125-129; Court, D.J., Parer, J.T., Experimental studies of fetal asphyxia and fetal heart rate interpretation (1984) Research in Perinatal Medicine, pp. 113-169; Dawes, G., Computerized fetal heart rate analysis (1994) A Critical Appraisal of Fetal Surveillance, pp. 311-314; Dawes, G.S., Moulden, M., Sheil, O., Redman, C.W.G., Approximate entropy, a statistic of regularity, applied to fetal heart rate data before and during labour (1992) Obstet. Gynecol., 80, pp. 763-768; Dawes, G.S., Moulden, M., Redman, C.W., Criteria for the design of fetal heart rate analysis systems (1990) Int. J. Biomed. Comput., 25 (4), pp. 287-294; Di Renzo, G.C., Montani, M., Fioriti, V., Clerici, G., Branconi, F., Pardini, A., Indraccolo, R., Cosmi, E.V., Fractal analysis: A new method for evaluating fetal heart rate variability (1996) J. Perinat. Med., 24, pp. 261-269; Echeverria, J.C., Hayes-Gill, B.R., Crowe, J.A., Woolfson, M.S., Croaker, G.D., Detrended fluctuation analysis: A suitable method for studying fetal heart rate variability? (2004) Physiol. Meas., 25 (3), pp. 763-774; Felgueiras, C., Marques-De-Sá, J.P., Bernardes, J., Gama, S., Fractal characterisation of fetal heart rate sequences (1998) Biomed. Eng., 36, pp. 197-201; Felgueiras, C.S., Marques-De-Sá, J.P., Bernardes, J., Gama, S., On the reconstruction of fetal heart rate sequences (1996) Actas Do 4° Congresso Português de Engenharia Biomédica-BioEng'96, pp. 61-vii65; Fukushima, T., Flores, C.A., Hon, E.H., Davidson Jr., E.C., Limitations of autocorrelation in fetal heart rate monitoring (1985) Am. J. Obstet. Gynecol., 153, pp. 685-692; Fusheng, Y., Bo, H., Qingyu, T., Approximate entropy and its application in biosignal analysis (1998) Nonlinear Biomedical Signal Processing-Volume II: Dynamical Analysis and Modelling, pp. 72-91; Gough, N.A., Fractal analysis of fetal heart rate variability (1993) Physiol. Meas., 14 (3), pp. 309-315; Hayes, M., (1996) Statistical Digital Signal Processing and Modelling; Hewlett-Packard, (1993) Hewlett-Packard Series 50 Service Manual, M1351A and 1353A; Hirsch, M., Karin, J., Akselrod, S., Heart rate variability in the fetus (1995) Heart Rate Variability, pp. 517-531; Lawson, G.W., Belcher, R., Dawes, G.S., Redman, C.W., A comparison of ultrasound (with autocorrelation) and direct electrocardiogram fetal heart rate detector systems (1983) Am. J. Obstet. Gynecol., 147, pp. 721-722; Li, X., Tang, D., Zhou, S., Zhou, G., Wang, C., Zhuang, Y., Wu, G., Shen, L., Redistribution of power spectrum of heart rate variability during acute umbilical artery embolism and hypoxemia in late-gestation fetal sheep (2004) Eur. J. Obstet. Gynecol. Reprod. Biol., 114 (2), pp. 137-143; Lunghi, F., Magenes, G., Pedrinazzi, L., Signorini, M.G., Detection of fetal distress through a support vector machine based on fetal heart rate parameters (2005) Comput. Cardiol., 32, pp. 247-250; Magenes, G., Signorini, M.G., Arduini, D., Classification of cardiotocographic records by neural networks (2000) IJCNN 2000: Proc. IEEE-INNS-ENNS Int. Joint Conf. on Neural Networks, pp. 637-641; Electronic fetal heart rate monitoring: Research guidelines for interpretation (1997) Am. J. Obstet. Gynecol., 177 (6), pp. 1385-1390; Nijhuis, I., Ten Hof, J., Development of fetal heart rate and behavior: Indirect measures to assess the fetal nervous system (1999) Eur. J. Obstet. Gynecol. Reprod. Biol., 87 (1), pp. 1-2; Oppenheimer, L.W., Lewinsky, R.M., Power spectral analysis of fetal heart rate (1994) Baillieres Clin. Obstet. Gynaecol., 8, pp. 643-661; Peters, C.H., Ten Broeke, E.D., Andriessen, P., Vermeulen, B., Berendsen, R.C., Wijn, P.F., Oei, S.G., Beat-to-beat detection of fetal heart rate: Doppler ultrasound cardiotocography compared to direct ECG cardiotocography in time and frequency domain (2004) Physiol. Meas., 25 (2), pp. 585-593; Pincus, S., Approximate entropy as a measure of system complexity (1991) Proc. Natl. Acad. Sci. USA, 88, pp. 2297-2301; Pincus, S., Approximate entropy (ApEn) as a complexity measure (1995) Chaos, 5 (1), pp. 110-117; Pincus, S., Viscarello, R., Approximate entropy: A regularity measure for fetal heart rate analysis (1992) Obstet. Gynecol., 79, pp. 249-255; Richman, J.S., Moorman, J.R., Physiological time-series analysis using approximate entropy and sample entropy (2000) Am. J. Physiol. Heart Circ. Physiol., 278, pp. 2039-H2049; Salamalekis, E., Thomopoulos, P., Giannaris, D., Salloum, I., Vasios, G., Prentza, A., Koutsouris, D., Computerised intrapartum diagnosis of fetal hypoxia based on fetal heart rate monitoring and fetal pulse oximetry recordings utilising wavelet analysis and neural networks (2002) BJOG, 109 (10), pp. 1137-1142; Signorini, M., Cerutti, S., Nonlinear properties of Cardiovascular Time Series (1999) Methodology and Clinical Applications of Blood Pressure and Heart Rate Analysis, pp. 73-89; Signorini, M.G., Magenes, G., Cerrutti, S., Arduini, D., Linear and nonlinear parameters for the analysis of fetal heart rate signal from cardiotacographic recordings (2003) IEEE Trans. Biomed. Eng., 50 (3), pp. 365-373; Suzuki, T., Okamura, K., Kimura, Y., Watanabe, T., Yaegashi, N., Murotsuki, J., Uehara, S., Yajima, A., Power spectral analysis of R-R interval variability before and during the sinusoidal heart rate pattern in fetal lambs (2000) Am. J. Obstet. Gynecol., 182 (5), pp. 1227-1232; Heart rate variability. Standards of measurement, physiological interpretation, and clinical use (1996) Eur. Heart J., 17, pp. 354-381; Wilcox, M.A., Wang, W., Sahota, D.S., Dawkins, R.R., Chung, T.K., Chang, A.M., The effect of different sampling intervals on the measurement of intrapartum fetal heart rate variability (1997) Obstet. Gynecol., 89 (4), pp. 577-580; Yum, M.K., Kim, K., Kim, J.H., Park, E.Y., A consistent abnormality in the average local smoothness of fetal heart rate in growth-restricted fetuses affected by severe pre-eclampsia (2004) Hypertens. Res., 27 (12), pp. 911-918
Keywords: abdomen; Algorithms; article; Cardiotocography; commercial phenomena; Confidence interval; controlled study; correlation coefficient; delivery; Diagnosis, Computer-Assisted; Electrocardiography; electrode; entropy; External and internal monitoring; Female; fetus electrocardiography; fetus monitoring; Foetal heart rate (FHR); Frequency domain analysis; Heart; Heart rate; human; intermethod comparison; intrapartum care; Linear and nonlinear analysis; Linear Models; mathematical computing; Nonlinear Dynamics; normal human; priority journal; Reproducibility of Results; sensitivity and specificity; sensor; Signal Processing, Computer-Assisted; Statistical significance; ultrasound; Variability

Linear and nonlinear fetal heart rate analysis of normal and acidemic fetuses in the minutes preceding delivery - Gonçalves, H.; Rocha, A.P.; Ayres-de-Campos, D.; Bernardes, J. (Medical and Biological Engineering and ComputingMed. Biol. Eng. Comput., 2006)
Linear and nonlinear fetal heart rate (FHR) indices, namely mean FHR, interval index (II), very low, low and high frequencies, approximate (ApEn) and sample entropy (SampEn), were computed, immediately before delivery, in the initial and final FHR tracing segments, from 48 normal, 10 mildly acidemic and 10 moderate-to-severely acidemic fetuses. Progression of labor was associated with a significant increase in linear frequency domain indices whereas nonlinear indices were significantly decreased. Moderate-to-severe fetal acidemia was associated with a significant decrease in nonlinear indices. The best discrimination between moderate-to-severe acidemic fetuses and the remaining cases was obtained combining II and ApEn(2,0.15), with a specificity of 71% and a sensitivity of 80%. These findings support the hypothesis of increased autonomic nervous system activity in the final minutes of labor and of decreased central nervous system activity, both in the final minutes of labor and in moderate-to-severe acidemic fetuses. © International Federation for Medical and Biological Engineering 2006.
Cited By (since 1996): 20Export Date: 21 November 2012Source: ScopusCODEN: MBECDdoi: 10.1007/s11517-006-0105-6PubMed ID: 16988896Language of Original Document: EnglishCorrespondence Address: Gonçalves, H.; Departamento de Matemática Aplicada, Faculdade de Ciências, Universidade do Porto, Rua do Campo Alegre - 687, 4169-007 Porto, Portugal; email: hernani.goncalves@fc.up.ptChemicals/CAS: AcidsReferences: ACOG technical bulletin. Fetal heart rate patterns: Monitoring, interpretation, and management (1995) Int J Gynecol Obstet, 51, pp. 65-74. , ACOG;Ayres-de-Campos, D., Bernardes, J., Costa-Pereira, A., Pereira-Leite, L., Inconsistencies in expert's classification of cardiotocograms and subsequent clinical decision (1999) Br J Obstet Gynecol, 106, pp. 1307-1310; Ayres-de-Campos, D., Bernardes, J., Garrido, A., de Sá, J.M., Pereira-Leite, L., Sisporto 2.0: A program for automated analysis of cardiotocograms (2000) J Mat Fet Med, 9, pp. 311-318; Bernardes, J., de Campos, D.A., Costa-Pereira, A., Pereira-Leite, L., Garrido, A., Objective computerized fetal heart rate analysis (1998) Int J Gynecol Obstet, 62, pp. 141-147; Bernardes, J., Costa-Pereira, A., de Campos, D.A., van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynecol Obstet, 57 (1), pp. 33-37; Bernardes, J., Moura, C., de Sá, J.P.M., Pereira-Leite, L., The porto system for automated cardiotocographic signal analysis (1991) J Perinat Med, 19, pp. 61-65; Boog, G., Analyse informatisTe du rythme cardiaque foetal au cours de la grossesse et de l'accouchement (2004) EncyclopTdie MTdico-Chirurgicale, 148, pp. 1-10. , (5-049-D-23); Carter, M.C., Signal processing and display - Cardiotocographs (1993) Br J Obstet Gynaecol, 100 (9), pp. 21-23; Chaffin, D.G., Barnard, J.M., Phernetton, T., Reed, K.L., Decreased approximate entropy of heart rate variability in the hypoxic ovine fetus (1998) J Matern Fetal Invest, 8, pp. 23-26; Chung, D.Y., Sim, Y.B., Park, K.T., Yi, S.H., Shin, J.C., Kim, S.P., Spectral analysis of fetal heart rate variability as a predictor of intrapartum fetal distress (2001) Int J Gynecol Obstet, 73, pp. 109-116; Colenbrander, G.J., van Geijn, H.P., Goovaerts, H.G., Acquisition of fetal heart rate signals (1994) A Critical Appraisal of Fetal Surveillance, pp. 203-210. , In: Geijn HPV, Copray FJA (eds) Elsevier Science, Amsterdam; Dawes, G.S., Moulden, M., Sheil, O., Redman, C.W.G., Approximate entropy, a statistic of regularity, applied to fetal heart rate data before and during labour (1992) Obstet Gynecol, 80 (5), pp. 763-768; Dudewicz, E., Mishra, S., (1988) Modern Mathematical Statistics, , Wiley, New York; Echeverrfa, J.C., Hayes-Gill, B.R., Crowe, J.A., Woolfson, M.S., Croaker, G.D.H., Detrended fluctuation analysis: A suitable method for studying fetal heart rate variability? (1990) Int J Biomed Comput, 25, pp. 287-294; Felgueiras, C., de Sá, J.P.M., Bernardes, J., Gama, S., Fractal characterisation of fetal heart rate sequences (1998) Biomed Eng, 36 (2), pp. 197-201; Fusheng, Y., Bo, H., Qingyu, T., Approximate entropy and its application in biosignal analysis (1998) Nonlinear Biomedical Signal Processing. Dynamical Analysis and Modelling, 2, pp. 72-91. , In: Akay M (ed) IEEE Press, New York; Gonçalves, H., Rocha, A.P., de Campos, D.A., Bernardes, J., Internal versus external intrapartum foetal heart rate monitoring: The effect on linear and nonlinear parameters (2006) Physiol Meas, 27, pp. 307-319; Gough, N.A., Fractal analysis of foetal heart rate variability (1993) Physiol Meas, 14 (3), pp. 309-315; Hayes, M., (1996) Statistical Digital Signal Processing and Modelling, , Wiley, New York; Hewlett-Packard, (1993) Hewlett-Packard Series 50 Service Manual, , M1351A and 1353A. Germany; King, T., Parer, J., The physiology of fetal heart rate patterns and perinatal asphyxia (2000) J Perinat Neonat Nurs, 14 (3), pp. 19-39; Li, X., Tang, D., Zhou, S., Zhou, G., Wang, C., Zhuang, Y., Wu, G., Shen, L., Redistribution of power spectrum of heart rate variability during acute umbilical artery embolism and hypoxemia in late-gestation fetal sheep (2004) Eur J Obstet Gynecol Reprod Biol, 114, pp. 137-143; Magenes, G., Signorini, M.G., Arduini, D., Classification of cardiotocographic records by neural networks (2000) Proceedings of the IEEE-INNS-ENNS International Joint Conference on Neural Networks,, 3, pp. 637-641. , In: IJCNN 2000; Martin, J.C.B., Electronic fetal monitoring: A brief summary of its development, problems and prospects (1998) Eur J Obstet Gynecol Reprod Biol, 78, pp. 133-140; Martinez, W.L., Martinez, A.R., (2002) Computational Statistics Handbook With MATLAB, , CRC Press, Boca Raton; Oppenheimer, L.W., Lewinsky, R.M., Power spectral analysis of fetal heart rate (1994) Baillieres Clin Obstet Gynaecol, 8 (3), pp. 643-661; Pincus, S., Approximate entropy as a measure of system complexity (1991) Proc Natl Acad Sci USA, 88, pp. 2297-2301; Pincus, S., Approximate entropy (apen) as a complexity measure (1995) Chaos, 5 (1), pp. 110-117; Pincus, S., Viscarello, R., Approximate entropy: A regularity measure for fetal heart rate analysis (1992) Obstet Gynecol, 79 (2), pp. 249-255; di Renzo, G.C., Montani, M., Fioriti, V., Clerici, G., Branconi, F., Pardini, A., Indraccolo, R., Cosmi, E.V., Fractal analysis: A new method for evaluating fetal heart rate variability (1996) J Perinat Med, 24 (3), pp. 261-269; Richman, J.S., Moorman, J.R., Physiological time-series analysis using approximate entropy and sample entropy (2000) Am J Physiol Heart Circ Physiol, 278, pp. H2039-H2049; Ripley, B.D., (1996) Pattern Recognition and Neural Networks, , Cambridge University Press, London; Rooth, G., Huch, A., Huch, R., FIGO news. Guidelines for the use of fetal monitoring (1987) Int J Gynecol Obstet, 25, p. 159; (2001) Evidence-Based Clinical Guideline Number 8. The Use of Electronic Fetal Monitoring, , Royal College of Obstetricians and Gynaecologists Royal College of Obstetricians and Gynaecologists, London; Salamalekis, E., Thomopoulos, P., Giannaris, D., Salloum, I., Vasios, G., Prentza, A., Koutsouris, D., Computerised intrapartum diagnosis of fetal hypoxia based on fetal heart rate monitoring and fetal pulse oximetry recordings utilising wavelet analysis and neural networks (2002) BJOG, 109 (10), pp. 1137-1142; Signorini, M.G., Cerutti, S., Nonlinear properties of cardiovascular time series (1999) Methodology and Clinical Applications of Blood Pressure and Heart Rate Analysis, pp. 73-89. , In: Di Rienzo M, Mancia G, Parati G, Pedotti A, Zanchetti A (eds) IOS Press, Amsterdam; Signorini, M.G., Magenes, G., Cerrutti, S., Arduini, D., Linear and nonlinear parameters for the analysis of fetal heart rate signal from cardiotacographic recordings (2003) IEEE Trans Biomed Eng, 50 (3), pp. 365-373; Siira, S.M., Ojala, T.H., Vahlberg, T.J., Jalonen, J.O., Valimaki, I.A., Rosen, K.G., Ekholm, E.M., Marked fetal acidosis and specific changes in power spectrum analysis of fetal heart rate variability recorded during the last hour of labour (2005) Br J Obstet Gynaecol, 112, pp. 418-423; Suzuki, T., Okamura, K., Kimura, Y., Watanabe, T., Murotsuki, N.Y.J., Uehara, S., Yajima, A., Power spectral analysis of R-R interval variability before and during the sinusoidal heart rate pattern in fetal lambs (2000) Am J Obstet Gynecol, 182, pp. 1227-1232; Heart rate variability. Standards of measurement, physiological interpretation, and clinical use. Task force of the european society of cardiology and the north american society of pacing and electrophysiology (1996) Eur Heart J, 17, pp. 354-381. , Task-Force; Teich, M.C., Lowen, S.B., Jost, B.M., Vibe-Rheymer, K., Heneghan, C., Heart rate variability: Measures and models (1998) Nonlinear Biomedical Signal Processing. Dynamic Analysis and Modeling, 2, pp. 159-213. , In: Akay M (ed) IEEE Press, New York; Yum, M.K., Kim, K., Kim, J.H., Park, E.Y., A consistent abnormality in the average local smoothness of fetal heart rate in growth-restricted fetuses affected by severe pre-eclampsia (2004) Hypertens Res, 27 (12), pp. 911-918
Keywords: acidemia; Acidosis; Acids; article; autonomic nervous system; Biological materials; Cardiology; Central nervous system; clinical article; controlled study; delivery; Delivery, Obstetric; Discriminant Analysis; disease severity; entropy; Fetal Diseases; Fetal heart rate; Fetal heart rate (FHR); Fetal monitoring; fetus; fetus heart rate; Frequency domain analysis; Heart Rate, Fetal; human; Humans; hypothesis; labor; Linear and nonlinear indices; linear system; Neurology; newborn; nonlinear system; Prenatal Care; Second stage of labor; sensitivity and specificity; Severity of Illness Index

A model for educational simulation of neonatal cardiovascular pathophysiology. - Sá Couto, C.D.; van Meurs, W.L.; Goodwin, J.A.; Andriessen, P. (Simulation in healthcare : journal of the Society for Simulation in HealthcareSimul Healthc, 2006)
Full-body patient simulators provide a technological basis for clinical education without risk to real patients. In a previous study, we described a model for educational simulation of infant cardiovascular physiology. Using essentially the same methodology, we derive a mathematical model for the cardiovascular system of a healthy 1-week-old neonate. Computer simulations of this model result in vital signs that are close to target hemodynamic variables. Simulated systemic arterial pressure waveform and left ventricular pressure-volume loop are realistic, and the system reacts appropriately to blood loss. We also adapt the model structure and change its parameters to reflect the congenital heart defects: patent ductus arteriosus, tetralogy of Fallot, complex coarctation of the aorta with patent foramen ovale, and transposition of the great arteries. Simulated vital signs are again close to target hemodynamic variables. The resulting model for neonatal cardiovascular pathophysiology is an essential step in attaining a full-body, model-driven neonatal acute care simulator.
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusPubMed ID: 19088566Language of Original Document: EnglishCorrespondence Address: Sá Couto, C.D.
Keywords: article; cardiovascular disease; Cardiovascular Diseases; cardiovascular function; Cardiovascular Physiological Phenomena; cardiovascular system; Computer simulation; congenital heart malformation; Education, Medical, Graduate; educational model; Heart Defects, Congenital; human; Humans; infant welfare; Infant, Newborn; medical education; methodology; Models, Educational; Models, Theoretical; newborn; theoretical model

Modular neural network task decomposition via entropic clustering - Santos, J.M.; Alexandre, L.A.; De Sá, J.M. (Proceedings - ISDA 2006: Sixth International Conference on Intelligent Systems Design and ApplicationsProc. ISDA Sixth Int. Conf. Intelligent Syst. Design Applic., 2006)
The use of monolithic neural networks (such as a multilayer perceptron) has some drawbacks: e.g. slow learning, weight coupling, the black box effect. These can be alleviated by the use of a modular neural network. The creation of a MNN has three steps: task decomposition, module creation and decision integration. In this paper we propose the use of an entropie clustering algorithm as a way of performing task decomposition. We present experiments on several real world classification problems that show the performance of this approach. © 2006 IEEE.
Conference code: 69992Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusArt. No.: 4021410doi: 10.1109/ISDA.2006.198Language of Original Document: EnglishCorrespondence Address: Santos, J.M.; Instituto Superior de Engenharia do Porto, Instituto de Engenharia Biomédica, Porto, Portugal; email: jms@isep.ipp.ptReferences: Santos, J.M., Marques de Sá, J., Alexandre, L.A., LEGClust - a clustering algorithm based on layered entropie subgraphs (2005) IEEE Transactions on Pattern Analysis and Machine Intelligence, , submitted;Bauer, E., Kohavi, R., An empirical comparison of voting classification algorithms: Bagging, boosting, and variants (1999) Machine Learning, 36 (1-2), pp. 105-139; Dietterich, T.G., An experimental comparison of three methods for constructing ensembles of decision trees: Bagging, boosting, and randomization (2000) Machine Learning, 40 (2), pp. 139-157; Kittler, J., Hatef, M., Duin, R.P.W., Matas, J., On combining classifiers (1998) IEEE Trans. Pattern Anal. Mach. Intell, 20 (3), pp. 226-239; Allwein, E.L., Schapire, R.E., Singer, Y., Reducing multiclass to binary: A unifying approach for margin classifiers (2000) Proc. 17th International Conf on Machine Learning, pp. 9-16. , Morgan Kaufmann, San Francisco, CA; Alexandre, L.A., Campilho, A.C., Kamel, M., Bounds for the average generalization error of the mixture of experts neural network (2004) LNCS, 3138, pp. 618-625. , 5th International Workshop on Statistical Techniques in Pattern Recognition; Jacobs, R., Jordan, M., Nowlan, S., Hinton, G., Adaptive mixtures of local experts (1991) Neural Computation, 3, pp. 79-87; Auda, G., Kamel, M., Modular neural network classifiers: A comparative study (1998) Intel. Robotic Systems, 21, pp. 117-129; Jordan, M., Jacobs, R., Hierarchical mixture of experts and the EM algorithm (1994) Neural Computation, 6, pp. 181-214; Jacobs, R., Peng, F., Tanner, M., A bayesian approach to model selection in hierarchical mixtures-of-experts architectures (1997) Neural Networks, 10 (2), pp. 231-241; Vilalta, R., Achari, M.K., Eick, C.F., Class decomposition via clustering: A new framework for lowvariance classifiers (2003) Third IEEE International Conference on Data Mining, pp. 673-676; Alexandre, L.A., Campilho, A.C., Kamel, M., A probabilistic model for the cooperative modular neural network (2003) LNCS, 2652, pp. 11-18. , Proceedings of the IbPRIA 2003; Ennaji, A., Ribert, A., Lecourtier, Y., From data topology to a modular classifier (2003) International Journal on Document Analysis and Recognition, 6 (1), pp. 1-9; Ng, A.Y., Jordan, M.I., Weiss, Y., On spectral clustering: Analysis and an algorithm (2001) Advances in Neural Information Processing Systems, 14; Bowman, A.W., Azzalini, A., (1997) Applied Smooting Techniques for Data Analysis, , London:Oxford University Press; Marques de Sá, J., (2003) Applied statistics using SPSS, STATISTICA andMATLAB, , Springer; Blake, C., Keogh, E., Merz, C., (1998) UCI repository of machine learning databases; Forina, M., Armanino, C., Eigenvector projection and simplified non-linear mapping of fatty acid content of Italian olive oils (1981) Ann. Chim. (Rome), 72, pp. 127-155
Keywords: Classification (of information); Clustering algorithms; Decision Theory; Entropic clustering; Learning systems; Modular neural network task decomposition; Monolithic neural networks; Neural networks; Weight coupling

A multiclassifier approach for lung nodule classification - Pereira, C.S.; Alexandre, L.A.; Mendonça, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2006)
The aim of this paper is to examine a multiclassifier approach to the classification of the lung nodules in X-ray chest radiographs. The approach investigated here is based on an image region-based classification whose output is the information of the presence or absence of a nodule in an image region. The classification was made, essentially, in two steps: firstly, a set of rotation invariant features was extracted from the responses of a multi-scale and multi-orientation filter bank; secondly, different classifiers (multi-layer perceptrons) are designed using different features sets and trained in different data. These classifiers are further combined in order to improve the classification performance. The obtained results are promising and can be used for reducing the false-positives nodules detected in a computer-aided diagnosis system. © Springer-Verlag Berlin Heidelberg 2006.
Conference code: 68310Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Pereira, C.S.; Instituto de Engenharia Biomédica, Rua Roberto Frias, 4200-465 Porto, Portugal; email: cpereira@estgl.ipv.ptReferences: Jemal, A., Murray, T., Ward, E., Samuels, A., Tiwari, R.C., Ghafoor, A., Feuer, E.J., Thun, M.J., (2005) Cancer Statistics, 2005, 55, pp. 10-30. , CA Cancer J Clin;Keserci, B., Yoshida, H., Computerized detection of pulmonary nodules in chest radiographs based on morphological features and wavelet snake model (2002) Medical Image Analysis, 6, pp. 431-447; Van Ginneken, B., Romeny, B.M.H., Viergever, M.A., Computer-aided diagnosis in chest radiography: A survey (2001) IEEE Transactions on Medical Imaging, 20 (12), pp. 1228-1241; Wei, J., Hagihara, Y., Shimizu, A., Kobatake, H., Optimal image feature set for detecting lung nodules on chest X-ray images (2002) CARS 2002; Van Ginneken, B., Katsuragawa, S., Ter Haar Romeny, B.M., Kunio, D., Viergever, M.A., Automatic detection of abnormalities in chest radiographs using local texture analysis (2002) IEEE Transactions on Medical Imaging, 21, pp. 139-149; Schilham, A.M.R., Van Ginneken, B., Loog, M., Multi-scale nodule detection in chest radiographs (2003) Lecture Notes in Computer Science, LNCS 2878, pp. 602-609; Shiraishi, J., Katsuragawa, S., Ikezoe, J., Matsumoto, T., Kobayashi, T., Matsu, K.-I.K., Matsui, M., Doi, K., Development of a digital image database for chest radiographs with and without a lung nodule: Receiver operating characteristic analysis of radiologists' detection of pulmonary nodules (2000) American Journal of Roentgenology, 174, pp. 71-74; Yoshida, H., Local contralateral subtraction based on bilateral symmetry of lung for reduction of false positives in computerized detection of pulmonary nodules (2004) IEEE Transactions on Biomedical Engineering, 51, pp. 778-789; Suzuki, K., Shiraishi, J., Abe, H., MacMahon, H., Doi, K., False-positive reduction in computer-aided diagnostic scheme for detecting nodules in chest radiographs by means of massive training artificial neural network (2005) Academic Radiology, 12, pp. 191-201; Randen, T., Husoy, J.H., Filtering for texture classification: A comparative study (1999) IEEE Transactions on Pattern Analysis and Machine Intelligence, 21 (4); Grigorescu, S.E., Petkov, N., Kruizinga, P., Comparison of texture features based on Gabor filters (2002) IEEE Transactions on Image Processing, 11 (10), pp. 195-203; Kumar, A., Pang, G.K.H., Defect detection in textured materials using Gabor filters (2002) IEEE Transactions on Industry Applications, 38 (2); Varma, M., Zisserman, A., Unifying statistical texture classification frameworks (2004) Image and Vision Computing, 22, pp. 1175-1183; Leung, T., Malik, J., Representing and recognizing the visual appearance of materials using three-dimensional textons (2001) International Journal of Computer Vision, 43, pp. 29-44; Alexandre, L.A., Campilho, A.C., Kamel, M., On combining classifiers using sum and product rules (2001) Pattern Recognition Letters, 22, pp. 1283-1289
Keywords: Biological organs; Classification (of information); Computer aided diagnosis; False-positives nodules; Medical imaging; Multi-orientation filter bank; Radiography; X rays; X-ray chest radiographs

New developments of the Z-EDM algorithm - Silva, L.M.; Marques de Sá, J.; Alexandre, L.A. (Proceedings - ISDA 2006: Sixth International Conference on Intelligent Systems Design and ApplicationsProc. ISDA Sixth Int. Conf. Intelligent Syst. Design Applic., 2006)
In this paper we address some open questions on the recently proposed Zero-Error Density Maximization algorithm for MLP training. We propose a new version of the cost function that solves a training problem encountered in previous work and prove that the use of a nonparametric density estimator preserves the optimal solution. Some experiments are reported comparing this cost function to the usual mean-square error and cross entropy cost junctions. © 2006 IEEE.
Conference code: 69992Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusArt. No.: 4021587doi: 10.1109/ISDA.2006.204Language of Original Document: EnglishCorrespondence Address: Silva, L.M.; INEB - Instituto de Engenharia Biomédica, Porto, Portugal; email: lmsilva@fe.up.ptReferences: Bishop, C., (1995) Neural Networks for Pattern Recognition, , Oxford University Press;Blake, C., Merz, C., (1998) UCI Repository of machine learning databases University of California, , http://www.ics.uci.edu/~mlearn/MLRepository.html, Irvine, Dept. of Information and Computer Sciences; Erdogmus, D., Principe, J.C., An Error-Entropy Minimization Algorithm for Supervised Training of Nonlinear Adaptive Systems (2002) IEEE Transactions on Signal Processing, 50 (7), pp. 1780-1786; Forina, M., Armanino, C., Eigenvector projection and simplified non-linear mapping of fatty acid content of Italian olive oils (1981) Ann. Chim. (Rome), 50, pp. 127-155; Marques de Sá, J., (2001) Pattern Recognition: Concepts, Methods and Applications, , Springer Verlag; J. Santos, L. Alexandre, and J. Marques de Sá. The Error Entropy Minimization Algorithm for Neural Network Classification. In Int. Conf. on Recent Advances in Soft Computing, Nottingham, United Kingdom, 2004Silva, L., Alexandre, L., Marques de Sá, J., Neural network classification: Maximizing zero-error density (2005) LNCS, 3686, pp. 127-135. , ICAPR 2005; Silva, L., Marques de Sá, J., Alexandre, L., Neural Network Classification using Shannon's Entropy (2005) European Symposium on Artificial Neural Networks; Silverman, B., (1986) Density Estimation for Statistics and Data Analysis, , Chapman & Hall
Keywords: Algorithms; Cost functions; Mean square error; MLP training; Nonparametric density estimators; Optimization; Personnel training; Problem solving; Zero-Error Density Maximization algorithm

The N-terminal half of the peroxisomal cycling receptor Pex5p is a natively unfolded domain - Carvalho, A.F.; Costa-Rodrigues, J.; Correia, I.; Costa Pessoa, J.; Faria, T.Q.; Martins, C.L.; Fransen, M.; Sá-Miranda, C.; Azevedo, J.E. (Journal of Molecular BiologyJ. Mol. Biol., 2006)
Targeting of most newly synthesised peroxisomal matrix proteins to the organelle requires Pex5p, the so-called PTS1 receptor. According to current models of peroxisomal biogenesis, Pex5p interacts with these proteins in the cytosol, transports them to the peroxisomal membrane and catalyses their translocation across the membrane. Presently, our knowledge on the structural details behind the interaction of Pex5p with the cargo proteins is reasonably complete. In contrast, information regarding the structure of the Pex5p N-terminal half (a region containing its peroxisomal targeting domain) is still limited. We have recently observed that the Stokes radius of this Pex5p domain is anomalously large, suggesting that this portion of the protein is either a structured elongated domain or that it adopts a low compactness conformation. Here, we address this issue using a combination of biophysical and biochemical approaches. Our results indicate that the N-terminal half of Pex5p is best described as a natively unfolded pre-molten globule-like domain. The implications of these findings on the mechanism of protein import into the peroxisome are discussed. © 2005 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 34Export Date: 21 November 2012Source: ScopusCODEN: JMOBAdoi: 10.1016/j.jmb.2005.12.002PubMed ID: 16403517Language of Original Document: EnglishCorrespondence Address: Azevedo, J.E.; Instituto de Biologia Molecular e Celular, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jazevedo@ibmc.up.ptChemicals/CAS: Amino Acids; peroxisome-targeting signal 1 receptor; Receptors, Cytoplasmic and NuclearReferences: Brown, L.A., Baker, A., Peroxisome biogenesis and the role of protein import (2003) J. Cell. Mol. Med., 7, pp. 388-400;Heiland, I., Erdmann, R., Biogenesis of peroxisomes. Topogenesis of the peroxisomal membrane and matrix proteins (2005) FEBS J., 272, pp. 2362-2372; Lazarow, P.B., Peroxisome biogenesis: Advances and conundrums (2003) Curr. Opin. Cell Biol., 15, pp. 489-497; Moyersoen, J., Choe, J., Fan, E., Hol, W.G., Michels, P.A., Biogenesis of peroxisomes and glycosomes: Trypanosomatid glycosome assembly is a promising new drug target (2004) FEMS Microbiol. Rev., 28, pp. 603-643; Weller, S., Gould, S.J., Valle, D., Peroxisome biogenesis disorders (2003) Annu. Rev. Genomics Hum. Genet., 4, pp. 165-211; Gould, S.J., Keller, G.A., Hosken, N., Wilkinson, J., Subramani, S., A conserved tripeptide sorts proteins to peroxisomes (1989) J. Cell Biol., 108, pp. 1657-1664; Klein, A.T., Barnett, P., Bottger, G., Konings, D., Tabak, H.F., Distel, B., Recognition of peroxisomal targeting signal type 1 by the import receptor Pex5p (2001) J. Biol. Chem., 276, pp. 15034-15041; Lametschwandtner, G., Brocard, C., Fransen, M., Van Veldhoven, P., Berger, J., Hartig, A., The difference in recognition of terminal tripeptides as peroxisomal targeting signal 1 between yeast and human is due to different affinities of their receptor Pex5p to the cognate signal and to residues adjacent to it (1998) J. Biol. Chem., 273, pp. 33635-33643; Brocard, C., Kragler, F., Simon, M.M., Schuster, T., Hartig, A., The tetratricopeptide repeat-domain of the PAS10 protein of Saccharomyces cerevisiae is essential for binding the peroxisomal targeting signal-SKL (1994) Biochem. Biophys. Res. Commun., 204, pp. 1016-1022; Dodt, G., Braverman, N., Wong, C., Moser, A., Moser, H.W., Watkins, P., Mutations in the PTS1 receptor gene, PXR1, define complementation group 2 of the peroxisome biogenesis disorders (1995) Nature Genet., 9, pp. 115-125; Fransen, M., Brees, C., Baumgart, E., Vanhooren, J.C., Baes, M., Mannaerts, G.P., Van Veldhoven, P.P., Identification and characterization of the putative human peroxisomal C-terminal targeting signal import receptor (1995) J. Biol. Chem., 270, pp. 7731-7736; Gatto Jr., G.J., Geisbrecht, B.V., Gould, S.J., Berg, J.M., A proposed model for the PEX5-peroxisomal targeting signal-1 recognition complex (2000) Proteins: Struct. Funct. Genet., 38, pp. 241-246; Otera, H., Setoguchi, K., Hamasaki, M., Kumashiro, T., Shimizu, N., Fujiki, Y., Peroxisomal targeting signal receptor Pex5p interacts with cargoes and import machinery components in a spatiotemporally differentiated manner: Conserved Pex5p WXXXF/Y motifs are critical for matrix protein import (2002) Mol. Cell. Biol., 22, pp. 1639-1655; Terlecky, S.R., Nuttley, W.M., McCollum, D., Sock, E., Subramani, S., The Pichia pastoris peroxisomal protein PAS8p is the receptor for the C-terminal tripeptide peroxisomal targeting signal (1995) EMBO J., 14, pp. 3627-3634; Gatto Jr., G.J., Geisbrecht, B.V., Gould, S.J., Berg, J.M., Peroxisomal targeting signal-1 recognition by the TPR domains of human PEX5 (2000) Nature Struct. Biol., 7, pp. 1091-1095; Agne, B., Meindl, N.M., Niederhoff, K., Einwachter, H., Rehling, P., Sickmann, A., Pex8p: An intraperoxisomal organizer of the peroxisomal import machinery (2003) Mol. Cell., 11, pp. 635-646; Albertini, M., Girzalsky, W., Veenhuis, M., Kunau, W.H., Pex12p of Saccharomyces cerevisiae is a component of a multi-protein complex essential for peroxisomal matrix protein import (2001) Eur. J. Cell Biol., 80, pp. 257-270; Reguenga, C., Oliveira, M.E., Gouveia, A.M., Sa-Miranda, C., Azevedo, J.E., Characterization of the mammalian peroxisomal import machinery: Pex2p. Pex5p, Pex12p, and Pex14p are subunits of the same protein assembly (2001) J. Biol. Chem., 276, pp. 29935-29942; Huhse, B., Rehling, P., Albertini, M., Blank, L., Meller, K., Kunau, W.-H., Pex17p of Saccharomyces cerevisiae is a novel peroxin and component of the peroxisomal protein translocation machinery (1998) J. Cell Biol., 140, pp. 49-60; Liu, H., Tan, X., Russell, K.A., Veenhuis, M., Cregg, J.M., PER3, a gene required for peroxisome biogenesis in Pichia pastoris, encodes a peroxisomal membrane protein involved in protein import (1995) J. Biol. Chem., 270, pp. 10940-10951; Rehling, P., Skaletz-Rorowski, A., Girzalsky, W., Voorn-Brouwer, T., Fransen, M.M., Distel, B., Pex8p, an intraperoxisomal peroxin of Saccharomyces cerevisiae required for protein transport into peroxisomes binds the PTS1 receptor pex5p (2000) J. Biol. Chem., 275, pp. 3593-3602; Smith, J.J., Szilard, R.K., Marelli, M., Rachubinski, R.A., The peroxin Pex17p of the yeast Yarrowia lipolytica is associated peripherally with the peroxisomal membrane and is required for the import of a subset of matrix proteins (1997) Mol. Cell. Biol., 17, pp. 2511-2520; Waterham, H.R., Titorenko, V.I., Haima, P., Cregg, J.M., Harder, W., Veenhuis, M., The Hansenula polymorpha PER1 gene is essential for peroxisome biogenesis and encodes a peroxisomal matrix protein with both carboxy- and amino-terminal targeting signals (1994) J. Cell Biol., 127, pp. 737-749; Costa-Rodrigues, J., Carvalho, A.F., Gouveia, A.M., Fransen, M., Sa-Miranda, C., Azevedo, J.E., The N terminus of the peroxisomal cycling receptor, Pex5p, is required for redirecting the peroxisome-associated peroxin back to the cytosol (2004) J. Biol. Chem., 279, pp. 46573-46579; Dodt, G., Gould, S.J., Multiple, P.E.X., Genes are required for proper subcellular distribution and stability of Pex5p, the PTS1 receptor: Evidence that PTS1 protein import is mediated by a cycling receptor (1996) J. Cell Biol., 135, pp. 1763-1774; Gouveia, A.M., Guimaraes, C.P., Oliveira, M.E., Reguenga, C., Sa-Miranda, C., Azevedo, J.E., Characterization of the peroxisomal cycling receptor, Pex5p, using a cell-free in vitro import system (2003) J. Biol. Chem., 278, pp. 226-232; Oliveira, M.E., Gouveia, A.M., Pinto, R.A., Sa-Miranda, C., Azevedo, J.E., The energetics of Pex5p-mediated peroxisomal protein import (2003) J. Biol. Chem., 278, pp. 39483-39488; Glover, J.R., Andrews, D.W., Rachubinski, R.A., Saccharomyces cerevisiae peroxisomal thiolase is imported as a dimer (1994) Proc. Natl Acad. Sci. USA, 91, pp. 10541-10545; McNew, J.A., Goodman, J.M., An oligomeric protein is imported into peroxisomes in vivo (1994) J. Cell Biol., 127, pp. 1245-1257; Stewart, M.Q., Esposito, R.D., Gowani, J., Goodman, J.M., Alcohol oxidase and dihydroxyacetone synthase, the abundant peroxisomal proteins of methylotrophic yeasts, assemble in different cellular compartments (2001) J. Cell Sci., 114, pp. 2863-2868; Walton, P.A., Hill, P.E., Subramani, S., Import of stably folded proteins into peroxisomes (1995) Mol. Biol. Cell, 6, pp. 675-683; Saidowsky, J., Dodt, G., Kirchberg, K., Wegner, A., Nastainczyk, W., Kunau, W.H., Schliebs, W., The di-aromatic pentapeptide repeats of the human peroxisome import receptor PEX5 are separate high affinity binding sites for the peroxisomal membrane protein PEX14 (2001) J. Biol. Chem., 276, pp. 34524-34529; Schliebs, W., Saidowsky, J., Agianian, B., Dodt, G., Herberg, F.W., Kunau, W.H., Recombinant human peroxisomal targeting signal receptor PEX5. Structural basis for interaction of PEX5 with PEX14 (1999) J. Biol. Chem., 274, pp. 5666-5673; Costa-Rodrigues, J., Carvalho, A.F., Fransen, M., Hambruch, E., Schliebs, W., Sa-Miranda, C., Azevedo, J.E., Pex5p, the peroxisomal cycling receptor, is a monomeric non-globular protein (2005) J. Biol. Chem., 280, pp. 24404-24411; Elgersma, Y., Elgersma-Hooisma, M., Wenzel, T., McCaffery, J.M., Farquhar, M.G., Subramani, S., A mobile PTS2 receptor for peroxisomal protein import in Pichia pastoris (1998) J. Cell Biol., 140, pp. 807-820; Rehling, P., Marzioch, M., Niesen, F., Wittke, E., Veenhuis, M., Kunau, W.H., The import receptor for the peroxisomal targeting signal 2 (PTS2) in Saccharomyces cerevisiae is encoded by the PAS7 gene (1996) EMBO J., 15, pp. 2901-2913; Zhang, J.W., Lazarow, P.B., Peb1p (Pas7p) is an intraperoxisomal receptor for the NH2-terminal, type 2, peroxisomal targeting sequence of thiolase: Peb1p itself is targeted to peroxisomes by an NH2-terminal peptide (1996) J. Cell Biol., 132, pp. 325-334; Dodt, G., Warren, D., Becker, E., Rehling, P., Gould, S.J., Domain mapping of human PEX5 reveals functional and structural similarities to Saccharomyces cerevisiae Pex18p and Pex21p (2001) J. Biol. Chem., 276, pp. 41769-41781; Einwachter, H., Sowinski, S., Kunau, W.H., Schliebs, W., Yarrowia lipolytica Pex20p Saccharomyces cerevisiae Pex18p/Pex21p and mammalian Pex5pL fulfil a common function in the early steps of the peroxisomal PTS2 import pathway (2001) EMBO Rep., 2, pp. 1035-1039; Matsumura, T., Otera, H., Fujiki, Y., Disruption of the interaction of the longer isoform of Pex5p, Pex5pL, with Pex7p abolishes peroxisome targeting signal type 2 protein import in mammals. Study with a novel Pex5-impaired Chinese hamster ovary cell mutant (2000) J. Biol. Chem., 275, pp. 21715-21721; Gouveia, A.M., Guimaraes, C.P., Oliveira, M.E., Sa-Miranda, C., Azevedo, J.E., Insertion of Pex5p into the peroxisomal membrane is cargo protein-dependent (2003) J. Biol. Chem., 278, pp. 4389-4392; De La Torre, J.G., Hydrodynamics of segmentally flexible macromolecules (1994) Eur. Biophys. J., 23, pp. 307-322; Denning, D.P., Uversky, V., Patel, S.S., Fink, A.L., Rexach, M., The Saccharomyces cerevisiae nucleoporin Nup2p is a natively unfolded protein (2002) J. Biol. Chem., 277, pp. 33447-33455; Permyakov, S.E., Millett, I.S., Doniach, S., Permyakov, E.A., Uversky, V.N., Natively unfolded C-terminal domain of caldesmon remains substantially unstructured after the effective binding to calmodulin (2003) Proteins: Struct. Funct. Genet., 53, pp. 855-862; Uversky, V.N., Natively unfolded proteins: A point where biology waits for physics (2002) Protein Sci., 11, pp. 739-756; Lydakis-Simantiris, N., Hutchison, R.S., Betts, S.D., Barry, B.A., Yocum, C.F., Manganese stabilizing protein of photosystem II is a thermostable, natively unfolded polypeptide (1999) Biochemistry, 38, pp. 404-414; Sreerama, N., Woody, R.W., Estimation of protein secondary structure from circular dichroism spectra: Comparison of CONTIN, SELCON, and CDSSTR methods with an expanded reference set (2000) Anal. Biochem., 287, pp. 252-260; Stanley, W.A., Sokolova, A., Brown, A., Clarke, D.T., Wilmanns, M., Svergun, D.I., Synergistic use of synchrotron radiation techniques for biological samples in solution: A case study on protein-ligand recognition by the peroxisomal import receptor Pex5p (2004) J. Synchrotron Radiat., 11, pp. 490-496; Oberg, K.A., Fink, A.L., A new attenuated total reflectance Fourier transform infrared spectroscopy method for the study of proteins in solution (1998) Anal. Biochem., 256, pp. 92-106; Navea, S., Tauler, R., De Juan, A., Application of the local regression method interval partial least-squares to the elucidation of protein secondary structure (2005) Anal. Biochem., 336, pp. 231-242; Obradovic, Z., Peng, K., Vucetic, S., Radijovac, P., Dunker, A.K., Exploiting heterogeneous sequence properties improves prediction of protein disorder (2006) Proteins, , In the press; Gould, S.J., Collins, C.S., Opinion: Peroxisomal-protein import: Is it really that complex? (2002) Nature Rev. Mol. Cell. Biol., 3, pp. 382-389; Shoemaker, B.A., Portman, J.J., Wolynes, P.G., Speeding molecular recognition by using the folding funnel: The fly-casting mechanism (2000) Proc. Natl Acad. Sci. USA, 97, pp. 8868-8873; Pontius, B.W., Close encounters: Why unstructured, polymeric domains can increase rates of specific macromolecular association (1993) Trends Biochem. Sci., 18, pp. 181-186; Tompa, P., Intrinsically unstructured proteins (2002) Trends Biochem. Sci., 27, pp. 527-533; Gouveia, A.M., Reguenga, C., Oliveira, M.E., Sa-Miranda, C., Azevedo, J.E., Characterization of peroxisomal Pex5p from rat liver. Pex5p in the Pex5p-Pex14p membrane complex is a transmembrane protein (2000) J. Biol. Chem., 275, pp. 32444-32451; Dammai, V., Subramani, S., The human peroxisomal targeting signal receptor, Pex5p, is translocated into the peroxisomal matrix and recycled to the cytosol (2001) Cell, 105, pp. 187-196; Imanaka, T., Small, G.M., Lazarow, P.B., Translocation of acyl-CoA oxidase into peroxisomes requires ATP hydrolysis but not a membrane potential (1987) J. Cell Biol., 105, pp. 2915-2922; Wendland, M., Subramani, S., Cytosol-dependent peroxisomal protein import in a permeabilized cell system (1993) J. Cell Biol., 120, pp. 675-685; Azevedo, J.E., Costa-Rodrigues, J., Guimaraes, C.P., Oliveira, M.E., Sa-Miranda, C., Protein translocation across the peroxisomal membrane (2004) Cell Biochem. Biophys., 41, pp. 451-468; Wang, D., Visser, N.V., Veenhuis, M., Van Der Klei, I.J., Physical interactions of the peroxisomal targeting signal 1 receptor pex5p, studied by fluorescence correlation spectroscopy (2003) J. Biol. Chem., 278, pp. 43340-43345; Oliveira, M.E., Reguenga, C., Gouveia, A.M., Guimaraes, C.P., Schliebs, W., Kunau, W.H., Mammalian Pex14p: Membrane topology and characterisation of the Pex14p-Pex14p interaction (2002) Biochim. Biophys. Acta, 1567, pp. 13-22; Fransen, M., Wylin, T., Brees, C., Mannaerts, G.P., Van Veldhoven, P.P., Human pex19p binds peroxisomal integral membrane proteins at regions distinct from their sorting sequences (2001) Mol. Cell. Biol., 21, pp. 4413-4424; Sreerama, N., Venyaminov, S.Y., Woody, R.W., Estimation of protein secondary structure from circular dichroism spectra: Inclusion of denatured proteins with native proteins in the analysis (2000) Anal. Biochem., 287, pp. 243-251; Vigano, C., Margolles, A., Van Veen, H.W., Konings, W.N., Ruysschaert, J.M., Secondary and tertiary structure changes of reconstituted LmrA induced by nucleotide binding or hydrolysis. a Fourier transform attenuated total reflection infrared spectroscopy and tryptophan fluorescence quenching analysis (2000) J. Biol. Chem., 275, pp. 10962-10967; Laurent, T.C., Killander, J., Theory of gel filtration + its experimental verification (1964) J. Chromatog., 14, pp. 217-230;
Keywords: Amino acids; amino terminal sequence; article; biogenesis; Calorimetry, Differential Scanning; cell membrane; cell receptor; Chromatography, Gel; circular dichroism; cytosol; differential scanning calorimetry; human; Humans; infrared spectroscopy; matrix protein; Natively unfolded; Peroxisomal protein import; peroxisome; Pex5p; priority journal; Protein conformation; protein degradation; protein domain; protein folding; protein interaction; protein Pex5p; protein structure; Protein Structure, Secondary; Protein Structure, Tertiary; protein transport; pts1 receptor; PTS1-receptor; Receptors, Cytoplasmic and Nuclear; Spectroscopy, Fourier Transform Infrared; unclassified drug

Three-dimensional culture of human osteoblastic cells in chitosan sponges: The effect of the degree of acetylation - Amaral, I.F.; Sampaio, P.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2006)
In this investigation, the effect of the degree of acetylation (DA) of chitosan on the behavior of human osteoblastic MG-63 cells cultured in three-dimensional chitosan matrices was assessed. Chitosan sponges with DAs in the range of 4 to 49% were prepared and characterized in terms of microstructure, porosity, and pore size. Collagen sponges were used as 3D control. Cell proliferation was determined using the MTT assay while the retention of the osteoblastic phenotype was monitored by assaying alkaline phosphatase activity. Cell morphology, cytoskeletal organization, and viability were assessed using different microscopy techniques. Chitosan sponges showed a similar microstructure regardless the DA, except for the highest DA used, where a more heterogeneous pore distribution was observed. In terms of cell proliferation, alkaline phosphatase activity and cell viability, cells cultured in chitosan scaffolds performed as well as in the 3D control regardless the DA, except for the highest DA used, where an inhibitory effect on cell proliferation was found. However, while in sponges with DAs ≤ 13% cells attached and spread displaying long cell filopodia and numerous cell-to-cell contacts, in sponges with higher DAs cells tended to remain spherical and grow into spheroid-like cellular aggregates. In the present study, the DA played a key role in determining the affinity of osteoblastic cells towards the substrates, possibly by influencing the nature of the initial adsorbed protein layer. © 2005 Wiley Periodicals, Inc.
Cited By (since 1996): 19Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30522PubMed ID: 16270345Language of Original Document: EnglishCorrespondence Address: Amaral, I.F.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: iamaral@ineb.up.ptChemicals/CAS: alkaline phosphatase, 9001-78-9; chitosan, 9012-76-4; collagen, 9007-34-5; Alkaline Phosphatase, EC 3.1.3.1; Chitosan, 9012-76-4; Collagen, 9007-34-5References: Bruder, S.P., Caplan, A.I., Bone regeneration through cellular engineering (2000) Principles of Tissue Engineering, pp. 683-696. , Lanza RP, Langer R, Vacanti J, editors. San Diego: Academic Press;Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 21, pp. 667-681; Khor, E., (2001) Chitin: Fulfilling a Biomaterials Promise, , Oxford, UK: Elsevier Science Ltd; Vandevord, P.J., Hwt, M., DeSilva, S.P., Mayton, L., Wu, B., Wooley, P.H., Evaluation of the biocompatibility of a chitosan scaffold in mice (2002) J Biomed Mater Res, 59, pp. 585-590; Tomihata, K., Ikada, Y., In vitro and in vivo degradation of films of chitin and its deacetylated derivatives (1997) Biomaterials, 18, pp. 567-575; Rao, S.B., Sharma, C.P., Sterilization of chitosan: Implications (1995) J Biomater Appl, 10, pp. 136-143; Muzzarelli, R.A.A., Zucchini, C., Ilari, P., Pugnaloni, A., Belmonte, M.M., Biagini, G., Castaldini, C., Osteoconductive properties of methylpyrrolidinone chitosan in an animal-model (1993) Biomaterials, 14, pp. 925-929; Lee, J.Y., Nam, S.H., Im, S.Y., Park, Y.J., Lee, Y.M., Seol, Y.J., Chung, C.P., Lee, S.J., Enhanced bone formation by controlled growth factor delivery from chitosan-based biomaterials (2002) J Control Release, 78, pp. 187-197; Zhao, F., Yin, Y.J., Lu, W.W., Leong, J.C., Zhang, W.J., Zhang, J.Y., Zhang, M.F., Yao, K.D., Preparation and histological evaluation of biomimetic three-dimensional hydroxyapatite/chitosan-gelatin network composite scaffolds (2002) Biomaterials, 23, pp. 3227-3234; Nettles, D.L., Elder, S.H., Gilbert, J.A., Potential use of chitosan as a cell scaffold material for cartilage tissue engineering (2002) Tissue Eng, 8, pp. 1009-1016; Zhang, Y., Zhang, M.Q., Calcium phosphate/chitosan composite scaffolds for controlled in vitro antibiotic drug release (2002) J Biomed Mater Res, 62, pp. 378-386; Prasitsilp, M., Jenwithisuk, R., Kongsuwan, K., Damrongchai, N., Watts, P., Cellular responses to chitosan in vitro: The importance of deacetylation (2000) J Mater Sci Mater Med, 11, pp. 773-778; Chatelet, C., Damour, O., Domard, A., Influence of the degree of acetylation on some biological properties of chitosan films (2001) Biomaterials, 22, pp. 261-268; Dhiman, H.K., Ray, A.R., Panda, A.K., Characterization and evaluation of chitosan matrix for in vitro growth of MCF-7 breast cancer cell lines (2004) Biomaterials, 25, pp. 5147-5154; Amaral, I.F., Lamghari, M., Sousa, S.R., Sampaio, P., Barbosa, M.A., Rat bone marrow stromal cells osteogenic differentiation and fibronectin adsorption on chitosan membranes: The effect of the degree of acetylation (2005) J Biomed Mater Res Part A, 75 A, pp. 387-397; Cukierman, E., Pankov, R., Stevens, D.R., Yamada, K.M., Taking cell-matrix adhesions to the third dimension (2001) Science, 294, pp. 1708-1712; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42, pp. 3569-3580; Mima, S., Miya, M., Iwamoto, R., Yoshikawa, S., Highly deacetylated chitosan and its properties (1983) J Appl Polym Sci, 28, pp. 1909-1917; Aiba, S., Studies on Chitosan: 1. Determination of the degree of N-acetylation of chitosan by ultraviolet spectrophotometry and gel-permeation chromatography (1986) Int J Biol Macromol, 8, pp. 173-176; Hirano, S., Ohe, Y., Ono, H., Selective N-acylation of chitosan (1976) Carbohydr Res, 47, pp. 315-320; Baxter, A., Dillon, M., Taylor, K.D.A., Roberts, G.A.F., Improved method for Ir determination of the degree of N-acetylation of chitosan (1992) Int J Biol Macromol, 14, pp. 166-169; Terbojevich, M., Cosani, A., Muzzarelli, R.A.A., Molecular parameters of chitosans depolymerized with the aid of papain (1996) Carbohydr Polym, 29, pp. 63-68; Zhang, R.Y., Ma, P.X., Poly(alpha-hydroxyl acids) hydroxyapatite porous composites for bone-tissue engineering. I. Preparation and morphology (1999) J Biomed Mater Res, 44, pp. 446-455; Mosmann, T., Rapid colorimetric assay for cellular growth and survival: Application to proliferation and cytotoxicity assays (1983) J Immunol Methods, 65, pp. 55-63; Ashton, B.A., Abdullah, F., Cave, J., Williamson, M., Sykes, B.C., Couch, M., Poser, J.W., Characterization of cells with high alkaline-phosphatase activity derived from human-bone and marrow - Preliminary assessment of their osteogenicity (1985) Bone, 6, pp. 313-319; Kurita, K., Controlled functionalization of the polysaccharide chitin (2001) Prog Polym Sci, 26, pp. 1921-1971; Wang, W., Bo, S.Q., Li, S.Q., Qin, W., Determination of the Mark-Houwink equation for chitosans with different degrees of deacetylation (1991) Int J Biol Macromol, 13, pp. 281-285; Roberts, G.A.F., (1992) Chitin Chemistry, , Houndmills: The Macmillan Press Ltd; Ueda, H., Hong, L., Yamamoto, M., Shigeno, K., Inoue, M., Toba, T., Yoshitani, M., Shimizu, Y., Use of collagen sponge incorporating transforming growth factor-beta 1 to promote bone repair in skull defects in rabbits (2002) Biomaterials, 23, pp. 1003-1010; Hanthamrongwit, M., Grant, M.H., Wilkinson, R., Confocal laser-scanning microscopy (Clsm) for the study of collagen sponge microstructure (1994) J Biomed Mater Res, 28, pp. 213-216; Zinger, O., Anselme, K., Denzer, A., Habersetzer, P., Wieland, M., Jeanfils, J., Hardouin, P., Landolt, D., Time-dependent morphology and adhesion of osteoblastic cells on titanium model surfaces featuring scale-resolved topography (2004) Biomaterials, 25, pp. 2695-2711; Eggli, P.S., Muller, W., Schenk, R.K., Porous hydroxyapatite and tricalcium phosphate cylinders with 2 different pore-size ranges implanted in the cancellous bone of rabbits - A comparative histomorphometric and histologic-study of bony ingrowth and implant substitution (1988) Clin Orthop, 232, pp. 127-138; Madihally, S.V., Matthew, H.W.T., Porous chitosan scaffolds for tissue engineering (1999) Biomaterials, 20, pp. 1133-1142; Madihally, S.V., Frattaroli, T.L., Matthew, H.W.T., (1999) In Vivo Colonization of Chitosan Based Porous Scaffolds, p. 172. , Providence, RI: Transactions from the 25th Annual Meeting of the Society for Biomaterials, Providence, RI; Zhang, Y., Zhang, M.Q., Synthesis and characterization of macroporous chitosan/calcium phosphate composite scaffolds for tissue engineering (2001) J Biomed Mater Res, 55, pp. 304-312; Chung, T.W., Yang, J., Akaike, T., Cho, K.Y., Nah, J.W., Kim, S.I., Cho, C.S., Preparation of alginate/galactosylated chitosan scaffold for hepatocyte attachment (2002) Biomaterials, 23, pp. 2827-2834; Masi, L., Franchi, A., Santucci, M., Danielli, D., Arganini, L., Giannone, V., Formigli, L., Beghe, F., Adhesion, growth, and matrix production by osteoblasts on collagen substrata (1992) Calcif Tissue Int, 51, pp. 202-212; Wiesmann, H.P., Nazer, N., Klatt, C., Szuwart, T., Meyer, U., Bone tissue engineering by primary osteoblast-like cells in a monolayer system and 3-dimensional collagen gel (2003) J Oral Maxillofac Surg, 61, pp. 1455-1462; Henriksen, I., Green, K.L., Smart, J.D., Smistad, G., Karlsen, J., Bioadhesion of hydrated chitosans: An in vitro and in vivo study (1996) Int J Pharmaceut, 145, pp. 231-240; Lebaron, R.G., Athanasiou, K.A., Extracellular matrix cell adhesion peptides: Functional applications in orthopedic materials (2000) Tissue Eng, 6, pp. 85-103; Cuy, J.L., Beckstead, B.L., Brown, C.D., Hoffman, A.S., Giachelli, C.M., Adhesive protein interactions with chitosan: Consequences for valve endothelial cell growth on tissue-engineering materials (2003) J Biomed Mater Res Part A, 67 A, pp. 538-547; Keselowsky, B.G., Collard, D.M., Garcia, A.J., Surface chemistry modulates fibronectin conformation and directs integrin binding and specificity to control cell adhesion (2003) J Biomed Mater Res Part A, 66 A, pp. 247-259; Webb, K., Hlady, V., Tresco, P.A., Relationships among cell attachment, spreading, cytoskeletal organization, and migration rate for anchorage-dependent cells on model surfaces (2000) J Biomed Mater Res, 49, pp. 362-368; Anselme, K., Bigerelle, M., Noel, B., Dufresne, E., Judas, D., Lost, A., Hardouin, P., Qualitative and quantitative study of human osteoblast adhesion on materials with various surface roughnesses (2000) J Biomed Mater Res, 49, pp. 155-166; Domard, A., Chitosan interactions (1997) Advances in Chitin Science, pp. 410-420. , Domard A, Roberts GAF, Varum KM, editors. Lyon, France: Jacques André Publisher;
Keywords: Acetylation; Aggregates; alkaline phosphatase; article; Bone Regeneration; bone tissue; Bone tissue engineering; Cell culture; Cell Culture Techniques; Cell filopodia; cell growth; cell proliferation; Cell Shape; cell structure; cell survival; cell viability; chitosan; Collagen; confocal microscopy; controlled study; Cytoskeletal organization; cytoskeleton; Degree of acetylation (DA); enzyme activity; gel permeation chromatography; human; human cell; Humans; infrared spectroscopy; Microstructure; morphology; osteoblast; Osteoblastic cells; Osteoblasts; Phosphatase activity; porosity; Proteins; Scaffold; Scaffolds; Scanning electron microscopy; Substrates; Tissue engineering

Titanium dental implants coated with Bonelike®: Clinical case report - Lobato, J.V.; Sooraj Hussain, N.; Botelho, C.M.; Maurício, A.C.; Lobato, J.M.; Lopes, M.A.; Afonso, A.; Ali, N.; Santos, J.D. (Thin Solid FilmsThin Solid Films, 2006)
The aim of the study was to evaluate the direct bone bonding and osteointegration of the commercial pure (cp Ti) implants coated with Bonelike® synthetic bone graft by plasma spraying. The Bonelike® coated implant was placed in the mandible of a 40-year-old patient and it was removed after a healing period of 3 months with a trephine of 6 mm diameter. The structure of the coating and new bone/implant interface of retrieved samples were evaluated using scanning electron microscopy (SEM) and histological analysis using light microscopy. In vivo microstructure observations of Bonelike® coated retrieved implants showed excellent bone remnants on its surface without any tissue and inflammatory signs observed. The reported Bonelike® coated (cp Ti) implants improved primary stability, which may increase the lifetime of the implant. Bonelike® coated dental implants proved to be highly bioactive with extensive new bone formation and strongly bonded to Bonelike® coating. © 2005 Elsevier B.V. All rights reserved.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: THSFAdoi: 10.1016/j.tsf.2005.12.151Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua Campo Alegre, 823, 4150-180 Porto, Portugal; email: jdsantos@fe.up.ptReferences: Murugan, R., Ramakrishna, S., (2005) Compos. Sci. Technol., 65, p. 2385;Boyle, W.J., Simonet, W.S., Lacey, D.L., (2003) Nature, 423, p. 337; Karabuda, C., Ozdemir, O., Tosun, T., Anil, A., Olgac, V., (2001) J. Periodontol., 72, p. 1436; Placko, H.E., Mishra, S., Weimer, J.J., Lucas, L.C., (2000) Int. J. Oral Maxillofac. Implants, 15, p. 355; Jung, Y.C., Han, C.H., Lee, I.S., Kim, H.E., (2001) Int. J. Oral Maxillofac. Implants, 16, p. 809; Kong, Y.M., Kim, D.H., Kim, H.E., Heo, S.J., Koak, J.Y., (2002) J. Biomed. Mater. Res., Part B Appl. Biomater., 63, p. 714; Schutz, R.W., Thomas, D.E., (1987) Metals Handbook. ed. 9, 13, p. 669. , Davis J.R. (Ed), American Society for Metals, Cleveland, OH; Tsui, Y.C., Doyle, C., Clyne, T.W., (1998) Biomaterials, 19, p. 2015; Lavos-Valereto, I.C., Wolynec, S., Deboni, M.C.Z., Konig Jr., B., (2001) J. Biomed. Mater. Res., Part B Appl. Biomater., 58, p. 727; Lacefield, W.R., (1993) An Introduction to Bioceramics, , Hench L.L., and Wilsion J. (Eds), World Scientific, Singapore; Golec, T.S., Krauser, J.T., (1992) Dent. Clin. North Am., 36, p. 39; Block, M.S., Kkent, J.N., (1992) Dent. Clin. North Am., 36, p. 27; Yukna, R.A., (1992) Dent. Clin. North Am., 36, p. 97; Baltag, I., Watanabe, K., Kusakari, H., Taoyuki, N., Miyakawa, O., Kobayashi, M., Ito, N., (2000) J. Biomed. Mater. Res., Part B Appl. Biomater., 53, p. 76; Wheeler, S.L., (1996) Int. J. Oral Maxillofac. Implants, 11, p. 340; Tsui, Y.C., Doyle, C., Clyne, T.W., (1998) Biomaterials, 19, p. 2031; (1981) Science and Medical Applications of Hydroxyapatite, , Conish H., Aoki H., and Sawai K. (Eds), Takyama Press Systems Centre Co., Tokyo; Santos, J.D., Knowles, J.C., Reis, R.L., Monteiro, F.J., Hastings, G.W., (1994) Biomaterials, 15, p. 5; Santos, J.D., Lakhan, J.J., Monteiro, F.J., (1995) Biomaterials, 16, p. 521; Lopes, M.A., Santos, J.D., Monteiro, F.J., Knowles, J.C., (1998) J. Biomed. Mater. Res., 39, p. 244; Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) Biomaterials, 20, p. 2085; Lopes, M.A., Silva, R.F., Monteiro, F.J., Santos, J.D., (1999) Biomaterials, 21, p. 749; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., (2000) Biomaterials, 21, p. 1165; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Oslen, I., (1998) J. Biomed. Mater. Res., 41, p. 649; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., (2001) J. Mater. Sci., Mater. Med., 12, p. 629; Ferraz, M.P., Monteiro, F.J., Serro, A.P., Saramago, B., Gibson, I.R., Santos, J.D., (2001) Biomaterials, 22, p. 3105; Silva, P.L., Santos, J.D., Monteiro, F.J., Knowles, J.C., (1998) Surf. Coat. Technol., 102, p. 191; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., (1999) J. Mater. Sci., Mater. Med., 10, p. 567; Lobato, J.V., Sooraj Hussain, N., Sousa, R.C., Maurício, A.C., Santos, J.D., (2005) Br. J. Oral Maxillofac. Surg., , (Communicated); Bränemark, P.I., Svensson, B., van Steenberghe, D., (1995) Clin. Oral Implants Res., 6 (4), p. 227; Strnad, Z., Strand, J., Povysil, C., Urban, K.K., (2000) Int. J. Oral Maxillofac. Implants, 15, p. 483; Ross, M.H., Romrell, L.J., Kaye, G.I., (1995) Histology, a Text and Atlas. ed. 3, , Williams & Wilkins, New York
Keywords: Bone; Bone Regeneration; Bone/implant interface; Bonelike® coatings; Clinical applications; Dental Implants; Dental prostheses; Hip prostheses; Medical applications; Optical microscopy; Plasma spraying

Biological behaviour of Bonelike® graft implanted in the tibia of humans - Gutierres, M.; Hussain, N.S.; Afonso, A.; Almeida, L.; Cabral, T.; Lopes, M.A.; Santos, J.D. (Key Engineering MaterialsKey Eng Mat, 2005)
This paper reports the ability of Bonelike® to regenerate bone defected areas when implanted in the tibia of 3 patients (average age of 59 years) during a high tibial osteotomy (HTO) to treat medial compartment osteoarthritis of the knee. Bonelike® is a synthetic bone graft designed to mimic the inorganic composition of bone using a patent process that consists of liquid sintering hydroxyapatite in the presence of CaO-P 2O 5 based glass. The preliminary clinical evaluation performed showed that an intimate contact between new formed bone and Bonelike® was established (67±10%), with no fibrous interface. Therefore, Bonelike® is a single-handedly viable osteoconductive synthetic grafting material as it has been demonstrated from the profiles of radiological, histological and scanning electron microscopy analyses for the six months implantation period.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Gutierres, M.; Faculdade de Medicina da Universidade do Porto, Hospital de São João, Largo Hernâni Monteiro, 4200 Porto, Portugal; email: m.gutierres@clix.ptReferences: Bauer, T.W., Muschler, G.F., Bone Graft Materials. An Overview of the Basic Science (2000) Clin orthop Rel. Res, 371, pp. 10-27;Perry, C.R., Bone Repair Techniques, Bone Graft and Bone Graft Substitutes (1999) Clin Orthop Rel Res, 360, pp. 71-86; Ilan, D.I., Ladd, A.L., Bone graft substitutes (2003) Operative Tech. in plastic and Reconstructive Surgery, 9 (4), pp. 151-160; Santos, J.D., Hastings, G.W., Knowles, J.C., Sintered Hydroxyapatite Compositions and Method for the Preparation Thereof European Patent WO 0068164Lopes, M.A., Glass reinforced hydroxyapatite composites: Structural, Physicochemical characterisation and Biological performance (1999), PhD thesis, FEUP, University of Porto, PortugalCoventry, M.B., Osteotomy of the upper portion of the tibia for degenerative arthritis of the knee: A preliminary report (1965) J. Bone Joint Surg.Am, 47, p. 984; Lopes, M.A., Santos, J.D., (2001) J.Biomed Mat Res, 54, pp. 463-469
Keywords: Biological behavior; Bone; Bonelike® graft; Clinical trials; histology; hydroxyapatite; Implants (surgical); Radiology; Scanning electron microscopy; Surgery; Synthetic grafting material

Bone substitutes: General concepts and "state of the art" - Gutierres, M.; Ascensão Lopes, M.; Sooraj Hussain, N.; Trigo Cabral, A.; Almeida, L.; Domingos Santos, J. (Substitutos ósseos: Conceitos gerais e estado actualArquivos de MedicinaArq. Med., 2005)
Bone grafts are nowadays the subject of extensive research worldwide, aimed at overcoming limitations associated with the use of autografts or bone banks to fill bone defects. Additionally, the use of osteogenic substances opens new perspectives in the treatment of fractures, pseudarthroses and vertebral arthrodeses. Due to the large amount of information available in the area of bone grafts, this paper aims not only to revise general concepts but also to summarize what has been published recently in the area of bone substitutes for bone regeneration. ©ArquiMed, 2006.
Keywords: Autografts; biomaterial; bone defect; bone demineralization; bone development; Bone graft; Bone growth factors; Bone morphogenetic protein; bone prosthesis; calcium phosphate; calcium sulfate; cortical bone; fibroblast growth factor; fracture; health care facility; health status; human; hydroxyapatite; platelet derived growth factor; pseudarthrosis; publication; review; somatomedin C derivative; spondylarthritis; transforming growth factor

Chemical modification of chitosan by phosphorylation: An XPS, FT-IR and SEM study - Amaral, I.F.; Granja, P.L.; Barbosa, M.A. (Journal of Biomaterials Science, Polymer EditionJ. Biomater. Sci. Polym. Ed., 2005)
In the present work, the surface of chitosan membranes was modified using a phosphorylation method carried out at room temperature. Phosphorylation may be of particular interest in materials for orthopaedic applications, due to the cation-exchange properties of phosphate functionalities. Phosphate groups chelate calcium ions, thus inducing the deposition of an apatite-like layer known to improve the osteoconduction of polymer-based implants. Additionally, the negatively charged phosphate functionalities, together with the positively charged amine groups from chitosan, are expected to provide chitosan with an amphoteric character, which may be useful as a combinatorial therapeutic strategy, by simultaneously allowing the immobilization of signalling molecules like growth factors. Phosphorylation was carried out at room temperature using the H 3 PO 4/Et 3 PO 4/P 2O 5/butanol method. Surface characterization was performed by XPS, ATR-FT-IR, and SEM. Cross-sections were analyzed by SEM fitted with EDS. The phosphate content increased with the reaction time, as shown by XPS and ATR-FT-IR, a P/N atomic ratio of 0.73 being obtained after 48 h of treatment. High-resolution XPS spectra regarding C 1s, O 1s, N 1s and P 2p are discussed. The introduction of a neutralization step led to a reduction of P content, which pointed out to the presence of phosphates ionically bound to protonated amines, in addition to phosphate esters. EDS analysis of cross-sections revealed a gradual P reduction up to 50% towards the inner part of the membrane. © VSP 2005.
Cited By (since 1996): 50Export Date: 21 November 2012Source: ScopusCODEN: JBSEEdoi: 10.1163/156856205774576736Language of Original Document: EnglishCorrespondence Address: Amaral, I.F.; Laboratório de Biomateriais, INEB - Instituto de Engenharia Biomédica, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: iamaral@ineb.up.ptChemicals/CAS: chitosan, 9012-76-4; phosphate, 14066-19-4, 14265-44-2; apatite, 64476-38-6; butanol, 35296-72-1, 71-36-3; calcium ion, 14127-61-8; Chitosan, 9012-76-4; PhosphatesReferences: Khor, E., (2001) Chitin: Fulfilling a Biomaterials Promise, , Elsevier Science, Oxford;Vande Vord, P.J., Matthew, H.W.T., DeSilva, S.P., Mayton, L., Wu, B., Wooley, P.H., (2002) J. Biomed. Mater. Res., 59, p. 585; Muzzarelli, R.A.A., Mattioli-Belmonte, M., Tietz, C., Biagini, R., Ferioli, G., Brunelli, M.A., Fini, M., Biagini, G., (1994) Biomaterials, 15, p. 1075; Lee, J.Y., Nam, S.H., Im, S.Y., Park, Y.J., Lee, Y.M., Seol, Y.J., Chung, C.P., Lee, S.J., (2002) J. Control. Rel., 78, p. 187; (2002) Chitosan in Pharmacy and Chemistry, p. 233. , R.A. A. Muzzarelli and C. Muzzarelli (Eds), in: Atec, Grottammare; Zhao, F., Yin, Y.J., Lu, W.W., Leong, J.C., Zhang, W.J., Zhang, J.Y., Zhang, M.F., Yao, K.D., (2002) Biomaterials, 23, p. 3227; Tanahashi, M., Matsuda, T., (1997) J. Biomed Mater. Res., 34, p. 305; Yokogawa, Y., Reyes, J.P., Mucalo, M.R., Toriyama, M., Kawamoto, Y., Suzuki, T., Nishizawa, K., Kamayama, T., (1997) J. Mater. Sci. Mater. Med., 8, p. 407; Varma, H.K., Yokogawa, Y., Espinosa, F.F., Kawamoto, Y., Nishizawa, K., Nagata, F., Kameyama, T., (1999) Biomaterials, 20, p. 879; Orban, J.M., Marra, K.G., Hollinger, J.O., (2002) Tissue Eng., 8, p. 529; Ilyina, A.V., Varlamov, V.P., Tikhonov, V.E., Yamskov, I.A., Davankov, V.A., (1994) Biotechnol. Appl. Biochem., 19, p. 199; Sugihara, J., Imamura, T., Yanase, T., Yamada, H., Imoto, T., (1982) J. Chromatogr., 229, p. 193; Kennedy, J.F., Cabral, J.M.S., (1983) Solid Phase Biochemistry: Analytical Synthetic Aspects, p. 253. , in: W. H. Schouten (Ed.) Wiley, New York, NY; Chatelet, C., Damour, O., Domard, A., (2001) Biomaterials, 22, p. 261; Granja, P.L., Pouysegu, L., Petraud, M., De Jeso, B., Baquey, C., Barbosa, M.A., (2001) J. Appl. Polym. Sci., 82, p. 3341; Fricain, J.C., Granja, P.L., Barbosa, A.M., de Jeso, B., Barthe, N., Baquey, C., (2002) Biomaterials, 23, p. 971; Sakairi, N., Shirai, A., Miyazaki, S., Tashiro, H., Tsuji, Y., Kawahara, H., Yoshida, T., Tokura, S., (1998) Kobunshi Ronbunshu, 55, p. 212; Sakaguchi, T., Horkoshi, T., Nakajima, A., (1981) Agricult. Biol. Chem., 45, p. 2191; Nishi, N., Ebina, A., Nishimura, S., Tsutsumi, A., Hasegawa, O., Tokura, S., (1986) Int. J. Biol. Macromol., 8, p. 311; Baxter, B., Dillon, M., Taylor, K.D.A., Roberts, G.A.F., (1992) Int. J. Biol. Macromol., 14, p. 166; Wang, W., Bo, S.Q., Li, S.Q., Qin, W., (1991) Int. J. Biol. Macromol., 13, p. 281; Aiba, S., (1986) Int. J. Biol. Macromol., 8, p. 173; Hirano, S., Ohe, Y., Ono, H., (1976) Carbohydr. Res., 47, p. 315; Shigemasa, Y., Matsuura, H., Sashiwa, H., Saimoto, H., (1996) Int. J. Biol. Macromol., 18, p. 237; Seah, M.P., (1990) Practical Surface Analysis, 1, p. 541. , D.in: Briggs and M. P. Seah (Eds) Wiley, Chichester; Sherwood, P.M.A., (1990) Practical Surface Analysis, 1, p. 555. , in: D. Briggs and M. P. Seah (Eds) Wiley, Chichester; Hudson, S.M., Smith, C., (1998) Bio-polymers from Renewable Resources, p. 96. , in: D. L. Kaplan (Ed.) Springer, Berlin; Shepherd, R., Reader, S., Falshaw, A., (1997) Glycoconj. J., 14, p. 535; Wang, X.H., Ma, J.B., Wang, Y.N., He, B.L., (2001) Biomaterials, 22, p. 2247; Lee, Y.M., Shin, E.M., (1991) J. Membr. Sci., 64, p. 145; Kim, S.S., Jeong, W.Y., Shin, B.C., Oh, S.Y., Kim, H.W., Rhee, J.M., (1998) J. Biomed. Mater. Res., 40, p. 401; Whistler, R.L., Towle, G.A., (1969) Arch. Biochem. Biophys., 135, p. 396; Gardner, S.D., Singamsetty, C.S.K., Booth, G.L., He, G., (1995) Carbon, 33, p. 587; Briggs, D., (1990) Practical Surface Analysis, 1, p. 437. , in: D. Briggs and M. P. Seah (Eds) Wiley, Chichester; Beamson, G.D.B., (1992) High Resolution XPS of Organic Polymers, , Wiley, Chichester; Ratner, B.D., Caster, D.G., (1997) Surface Analysis - The Principal Techniques, p. 43. , in: J. C. Vickerman (Ed.) Wiley, Chichester; Bourbigot, S., Lebras, M., Gengembre, L., Delobel, R., (1994) Appl. Surf. Sci., 81, p. 299; Kilpadi, D.V., Raikar, G.N., Liu, J., Lemons, J.E., Vohra, Y., Gregory, J.C., (1998) J. Biomed. Mater. Res., 40, p. 646; Landis, W.J., (1984) Vac. Technol., A2, p. 1108; Wagner, C.D., Naumkin, A.V., Kraut-Vass, A., Alisson, J.W., Powell, C.J., Rumble Jr., J.R., (2003) NIST-X-ray Photoelectron Spectroscopy Database 20 Version 3.4, , http://srdata.nist.gov/xps/, National Institute of Standards and Technology, Gaithersburg, MD Available online at; Quan, D.T., Le Bloa, A., Habib, H., Bonnaud, O., Meinnel, J., Quemerais, A., Marchand, R., (1989) Rev. Phys. Appl., 24, p. 545; Lindberg, B., Maripuu, R., Siegbahn, K., Larsson, R., Golander, C.G., Eriksson, J.C., (1983) J. Colloid Interf. Sci., 95, p. 308; Domard, A., (1997) Advances in Chitin Science, 2, p. 410. , in: A. Domard, G. Roberts and K. Vårum (Eds) Jacques André, Lyon; Granja, P.L., Pouysegu, L., Deffieux, D., Daude, G., De Jeso, B., Labrugere, C., Baquey, C., Barbosa, M.A., (2001) J. Appl. Polym. Sci., 82, p. 3354; Roeges, N.P.G., (1994) A Guide to the Complete Interpretation of Infrared Spectra of Organic Structures, , Wiley, Chichester; Pearson, F.G., Marchessault, R.H., Liang, C.Y., (1960) J. Polym. Sci., 43, p. 101; Roberts, G.A.F., (1992) Chitin Chemistry, , Macmillan, London; Kuptsov, A.H., Zhizhin, G.N., (1998) Handbook of Fourrier Transform Raman and Infrared Spectra of Polymers, , Elsevier, Amsterdam; Daasch, L.W., Smith, D.C., (1951) Anal. Chem., 23, p. 854; Bueno, W.A., (1990) Manual De Espectroscopia Vibracional, , McGraw-Hill, São Paulo; Nyquist, R.A., Craver, C.D., (1997) The Coblentz Society Desk Book of Infrared Spectra, , The Coblentz Society, French Village, MO; Hirano, S., Tobetto, K., Noishiki, Y., (1981) J. Biomed. Mater. Res., 15, p. 903
Keywords: Acetylation; amine; animal; Animals; Apatite; article; bone conduction; butanol; calcium ion; cation exchange; cephalopod; chelate; Chemical modification; chemistry; Chitin; chitosan; comparative study; controlled study; Decapodiformes; Fourier transform infrared spectroscopy; Fourier transform infrared spectroscopy (FT-IR); Growth factor; immobilization; Implants (surgical); infrared spectroscopy; isolation and purification; Microscopy, Electron, Scanning; molecular weight; organophosphate; phosphate; Phosphate groups; Phosphates; Phosphorylation; Phosphorylation method; Plastics applications; priority journal; reflectometry; room temperature; Scanning electron microscopy; SEM-EDS; signal transduction; spectrometry; Spectrometry, X-Ray Emission; Spectroscopy, Fourier Transform Infrared; Surface chemical reaction; Surface Properties; surface property; temperature; time; Time Factors; viscosity; X ray photoelectron spectroscopy; X-rayphotoelectron spectroscopy (XPS)

Feature extraction for classification of thin-layer chromatography images - Sousa, A.V.; Mendonça, A.M.; Campilho, A.; Aguiar, R.; Sá Miranda, C. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2005)
Thin-Layer Chromatography images are used to detect and identify the presence of specific oligosaccharides, expressed by the existence, at different positions, of bands in the gel image. ID gaussian deconvolution, commonly used for band detection, does not produce good results due to the large curvature observed in the bands. To overcome this uncertainty on the band position, we propose a novel feature extraction methodology that allows an accurate modeling of curved bands. The features are used to classify the data into two different classes, to differentiate normal from pathologic cases. The paper presents the developed methodology together with the analysis and discussion of the results. © Springer-Verlag Berlin Heidelberg 2005.
Conference code: 67124Cited By (since 1996): 2Export Date: 21 November 2012Source: Scopusdoi: 10.1007/11559573_118Language of Original Document: EnglishCorrespondence Address: Sousa, A.V.; Instituto de Engenharia Biomédica, Rua Roberto Frias, 4200-465 Porto, Portugal; email: ats@isep.ipp.ptReferences: Bajla, I., Holländer, I., Burg, K., Improvement of electrophoretic gel image analysis (2001) M. S.R, 1 (1);Ye, X., Suen, C., Cheriet, M., Wang, E., A recent development in image analysis of electrophoresis gels (1999) Vision Interface 99, , Canada; Shadle, S., Allen, D., Guo, H., Pogozelski, W., Bashkin, J., Tullius, T., Quantitative analysis of electrophoresis data: Novel curve fitting methodology and its application to the determination of aprotein-DNA binding constant (1997) Nucleic Acids Research, 25 (4); Sousa, A., Aguiar, R., Mendonça, A.M., Campilho, A., Automatic lane and band detection in images of thin layer chromatography (2004) Springer Lecture Notes on Computer Science, LNCS, 3212, pp. 372-380; Heijden, F., Duin, R., Ridder, D., Tax, D., (2004) Classification, Parameter Estimation and State Estimation, , John Wiley and Sons, England; Sewell, A., (1991) Urinary Oligosaccharides. Techniques in Diagnostic Human Biochemical Genetics, pp. 219-231. , Willey-Liss, Inc; Thomas, G., Disorders of Glycoprotein Degradation. α-Mahnosidosis, β-Mannosidosis, Fucosidosis and Sialidosis. Disorders of Glycoprotein Degradation, , Chap. 140; Durant, G., Seta, N., Protein glycosylation and diseases: Blood and urinary oligosaccharides as markers for diagnosis and therapeutic monitoring (2000) Clinical Chemistry, 46 (6), pp. 795-805; Marques De Sá, J., (2003) Applied Statistics Using SPSS, STATISTICA and MATLAD, , Springer Verlag
Keywords: Edge detection; Feature extraction; Image analysis; Image segmentation; Oligosaccharides; Thin layer chromatography; Thin-Layer Chromatography images

Inflammatory cell recruitment and adhesion to methyl-terminated self-assembled monolayers: Effect of implantation time - Barbosa, J.N.; Barbosa, M.A.; Águas, A.P. (Microscopy Research and TechniqueMicrosc. Res. Tech., 2005)
The contribution of methyl groups in implant-triggered inflammation was investigated in vivo using self-assembled monolayers (SAMs) of alkanethiols on gold. The CH 3-coated implants were inserted in an air-pouch cavity induced in BALB/c mice. The in situ inflammatory response was monitored 24, 48, and 72 hours later. Inflammatory cells recovered from the air pouches were counted and observed by light microscopy. The cellularity of the implant surfaces was defined by scanning electron microscopy (SEM). In comparison with gold implants, the CH 3-coated SAMs recruited a significantly higher number of inflammatory cells. Polymorphonuclear leukocytes (PMN) were more numerous than mononuclear cells (Mo) in the exudates recovered from the air pouches with CH 3-coated SAMs. The opposite PMN/Mo proportion was observed in air pouches of the two control groups (mice receiving gold implants or sham-operated animals). A low density of adherent cells was seen on CH 3-coated implants, with no significant quantitative differences during the time course of the study. In contrast, the gold-coated surfaces were covered with numerous cells during all of the 3 days of the inflammation. In conclusion, implants with CH 3 surfaces are likely to induce PMN-dominated local acute inflammation but these surfaces are not associated with a significant adherence of leukocytes to the implant. © 2005 Wiley-Liss, Inc.
Cited By (since 1996): 4Export Date: 21 November 2012Source: ScopusCODEN: MRTEEdoi: 10.1002/jemt.20141PubMed ID: 15816035Language of Original Document: EnglishCorrespondence Address: Barbosa, J.N.; INEB, Inst. de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: judite@ibmc.up.ptChemicals/CAS: gold, 7440-57-5; thiol derivative, 13940-21-1; Coated Materials, Biocompatible; Gold, 7440-57-5References: Anderson, J.M., Biological responses to materials (2001) Annu Rev Mater Res, 31, pp. 81-110;Babensee, J.E., Anderson, J.M., Mclntire, L.V., Mikos, A.G., Host response to tissue engineered devices (1998) Adv Drug Deliv Rev, 33, pp. 111-139; Barbosa, J.N., Barbosa, M.A., Águas, A.P., Inflammatory responses and cell adhesion to self-assembled monolayers of alkanethiolates on gold (2004) Biomaterials, 25, pp. 2557-2563; Castro, A.G., Esaguy, N., Macedo, P.M., Águas, A.P., Silva, M.T., Live but not heat-killed mycobacteria cause rapid chemotaxis of large numbers of eosinophils in vivo and are ingested by the attracted granulocytes (1991) Infect Immun, 59, pp. 3009-3014; Gelb, H., Schumacher, H.R., Cuckler, J., Ducheyne, P., Baker, D.G., In vivo inflammatory response to polymethylmethacrylate particulate debris: Effect of size, morphology, and surface area (1994) J Orthop Res, 12, pp. 83-92; Hooper, K.A., Nickolas, T.L., Yurkow, E.J., Kohn, J., Laskin, D., Characterization of the inflammatory response to biomaterials using a rodent air pouch model (2000) J Biomed Mater Res, 50, pp. 365-374; Hu, W., Eaton, J.W., Tang, L., Molecular basis of biomaterial-mediated foreign body reactions (2001) Blood, 98, pp. 1231-1238; Isaji, M., Momose, Y., Naito, J., Enhancement of inflammatory reactions in a non-immunological air pouch model in rats (1989) Br J Exp Pathol, 70, pp. 705-716; Källtorp, M., Oblogina, S., Jacobsson, S., Karlsson, A., Tengvall, P., Thomsen, P., In vivo cell recruitment, cytokine release and chemiluminescence response at gold, and thiol functionalized surfaces (1999) Biomaterials, 20, pp. 2123-2137; Kao, W.J., Evaluation of leukocyte adhesion on polyurethanes: The effects of shear stress and blood proteins (2000) Biomaterials, 21, pp. 2295-2303; Kao, W.J., Liu, Y., Gundloori, R., Li, J., Lee, D., Einerson, N., Burmania, J., Stevens, K., Engineering endogenous inflammatory cells as delivery vehicles (2002) J Control Release, 78, pp. 219-233; Lin, J., Chuang, W., Synthesis, surface characterization, and platelet reactivity evaluation for the self-assembled monolayer of alkanethiol with sulfonic acid functionality (2000) J Biomed Mater Res, 51, pp. 413-423; Lindblad, M., Lestelius, M., Johansson, A., Tengvall, P., Thomsen, P., Cell and soft tissue interactions with methyl- and hydroxyl-terminated alkane thiols on gols surfaces (1997) Biomaterials, 18, pp. 1059-1068; Margel, S., Vogler, E.A., Firment, L., Watt, T., Haynie, S., Sogah, D.Y., Peptide, protein, and cellular interactions with self-assembled monolayer model surfaces (1993) J Biomed Mater Res, 27, pp. 1463-1476; Martins, M.C.L., Naeemi, E., Ratner, B.D., Barbosa, M.A., Albumin adsorption on cibacron blue F3G-A immobilized onto oligo(ethylene glycol)-terminated self-assembled monolayers (2003) J Mater Sci Mater Med, 14, pp. 945-954; Mrksich, M., Using self-assembled monolayers to understand the biomaterials interface (1997) Curr Opin Colloid Int Sci, 2, pp. 83-88; Mrkisich, M., Tailored substrates for studies of attached cell culture (1998) Cell Mol Life Sci, 54, pp. 653-662; Mrksich, M., Whitesides, G.M., Interactions of SAMs with proteins (1996) Annu Rev Biophys Biomol Struct, 25, pp. 55-57; Pan, S., Castner, D.G., Ratner, B.D., Multitechnique surface characterization of derivatization efficiences for hydroxyl-terminated self-assembled monolayers (1998) Langmuir, 14, pp. 3545-3550; Prime, K.L., Whitesides, G.M., Self assembled organic monolayers: Model systems for studying the adsorption of proteins at surfaces (1991) Science, 252, pp. 1164-1167; Sedwick, A.D., Sin, Y.M., Edwards, J.C., Willoughby, D.A., Increased inflammatory reactivity in newly formed lining tissue (1983) J Pathol, 141, pp. 483-495; Tang, L., Eaton, J.W., Mechanisms of acute inflammatory response to biomaterials (1994) Cells and Materials, 4, pp. 429-436; Tang, L., Eaton, J.W., Inflammatory responses to biomaterials (1995) Am J Clin Pathol, 103, pp. 466-471; Tang, L., Ugarova, T.P., Plow, E.F., Eaton, J.W., Molecular determinants of acute inflammatory responses to biomaterials (1997) J Clin Invest, 97, pp. 1329-1334; Tang, L., Jennings, T.A., Eaton, J.W., Mast cells mediate acute inflammatory responses to implanted biomaterials (1998) Proc Natl Acad Sci, 95, pp. 8841-8846; Tang, L., Liu, L., Elwing, H.B., Complement activation and inflammation triggered by model biomaterial surfaces (1998) J Biomed Mater Res, 41, pp. 333-340; Tegoulia, V.A., Cooper, S.L., Leukocyte adhesion on model surfaces under flow: Effects of surface chemistry, protein adsorption, and shear rate (2000) J Biomed Mater Res, 50, pp. 291-301; Tomczok, J., Sliwa-Tomczok, W., Klein, C.L., Van Kooten, T.G., Kirkpatrick, C.J., Biomaterial-induced alterations of human neutrophils under fluid shear stress: Scanning electron microscopical study in vitro (1996) Biomaterials, 17, pp. 1359-1367; Ulman, A., Formation and structure of self-assembled monolayers (1996) Chem Rev, 96, pp. 1533-1554; Wooley, P.H., Mayton, L., Sud, S., Nasser, S., Synergistic inflammatory responses to metallic and polymeric particles in the murine air pouch model of aseptic loosening (1996) Arthritis Rheum, 39, pp. 175-183; Wooley, P.H., Morren, R., Andary, J., Sud, S., Yang, S., Mayton, L., Markel, D., Nasser, S., Inflammatory responses to orthopaedic biomaterials in the murine air pouch (2002) Biomaterials, 23, pp. 517-526; Yun, J.K., DeFife, K., Colton, E., Stack, S., Azeez, A., Cahalan, L., Verhoeven, M., Anderson, J.M., Human monocyte/macrophage adhesion and cytokine production on surface-modified poly (tetrafluoroethylene/hexafluoropropylene) polymers with and without protein preadsorption (1995) J Biomed Mater Res, 29, pp. 257-268
Keywords: Air-pouch model; animal experiment; animal model; Animalia; Animals; article; biomaterial; cell adhesion; Cell Count; cell density; cell surface; Cell-surface interactions; Coated Materials, Biocompatible; Contact angle; controlled study; gold; implantation; Implants, Experimental; Inflammation; inflammatory cell; Inflammatory responses; leukocyte adherence; Leukocytes; male; materials testing; methyl group; Mice; Microscopy, Electron, Scanning; mononuclear cell; mouse; neutrophil; nonhuman; priority journal; Scanning electron microscopy; Self-assembled monolayers; Surface Properties; thiol derivative; Time Factors

Neural network classification: Maximizing zero-error density - Silva, L.M.; Alexandre, L.A.; De Sá, J.M. (Lecture Notes in Computer ScienceLect. Notes Comput. Sci., 2005)
We propose a new cost function for neural network classification: the error density at the origin. This method provides a simple objective function that can be easily plugged in the usual backpropagation algorithm, giving a simple and efficient learning scheme. Experimental work shows the effectiveness and superiority of the proposed method when compared to the usual mean square error criteria in four well known datasets. © Springer-Verlag Berlin Heidelberg 2005.
Conference code: 65875Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Silva, L.M.; Instituto de Engenharia Biomédica, Lab. de Sinai e Imagem Biomédica, Campus da FEUP, Rua Dr. Roberto Frias, 4200 - 465 Porto, PortugalReferences: Erdogmus, D., Principe, J.C., An error-entropy minimization algorithm for supervised training of nonlinear adaptive systems (2002) IEEE Transactions on Signal Processing, 50 (7), pp. 1780-1786;Erdogmus, D., Principe, J., Generalized information potential criterion for adaptive system training (2002) IEEE Transactions on Neural Networks, 13 (5), pp. 1035~1044; Santos, J.M., Alexandre, L.A., Marques De Sá, J., The error entropy minimization algorithm for neural network classification (2004) Int. Conf. on Recent Advances in Soft Computing, , Nottingham, United Kingdom; Santos, J.M., Alexandre, L.A., De Sa, J.M., Optimization of the error entropy minimization algorithm for neural network classification (2004) Intelligent Engineering Systems Through Artificial Neural Networks, 14, pp. 81-86. , C. Dagli, A. Buczak, D. Enke, M. Embrechts, and O. Ersoy, editors, ASME Press Series; Silva, L.M., De Sa, J.M., Alexandre, L.A., Neural network classification using shannon's entropy (2005) European Symposium on Artificial Neural Networks; Jacobs, R., Jordan, M., Nowlan, S., Hinton, G., Adaptive mixtures of local experts (1991) Neural Computation, 3, pp. 79-87; Blake, C.L., Merz, C.J., (1998) UCI Repository of Machine Learning Databases, , http://www.ics.uci.edu/~mlearn/MLRepository.html, University of California, Irvine, Dept. of Information and Computer Sciences
Keywords: Algorithms; Backpropagation; Backpropagation algorithm; Classification (of information); Costs; Error analysis; Function evaluation; Learning systems; Mean square error; Neural network classification; Neural networks; Zero-error density

Neural networks trained with the EEM algorithm: Tuning the smoothing parameter - Santos, J.M.; Marques de Sá, J.; Alexandre, L.A. (WSEAS Transactions on SystemsWSEAS Trans. Syst., 2005)
The training of Neural Networks and particularly Multi-Layer Perceptrons (MLP's) is made by minimizing an error function usually known as "cost function". In our previous works, we apply the Error Entropy Minimization (EEM) algorithm in classification and its optimized version using, as cost function, the entropy of the errors between the outputs and the desired targets of the neural network. One of the difficulties in implementing the EEM algorithm is the choice of the smoothing parameter, also known as window size, in the Parzen Window probability density function estimation for the computation of the entropy and its gradient. We present here a formula yielding the value of the smoothing parameter, depending on the number of data samples and on the neural network output dimension. Several experiments with real data sets were made in order to show the validity of the proposed formula.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Santos, J.M.; Intituto de Engenharia Biomédica, Porto, Portugal; email: jms@isep.ipp.ptReferences: Erdogmus, D., Principe, J., "An Error-Entropy Minimization Algorithm for Supervised Training of Nonlinear Adaptive Systems" (2002) Trans. On Signal Processing, 50 (7), pp. 1780-1786;Santos, J.M., Alexandre, L.A., Marques de Sá, J., "The error entropy minimization algorithm for neural network classification" (2004) Proceedings of the 5th International Conference on Recent Advances in Soft Computing, pp. 92-97. , A. Lofti, Ed. Nottingham Trent University; Santos, J.M., Marques de Sá, J., Alexandre, L.A., Sereno, F., "Optimization of the error entropy minimization algorithm for neural network classification" (2004) Intelligent Engineering Systems Through Artificial Neural Networks, 14, pp. 81-86. , C.H. Dagli, A.L. Buczak, D.L. Enke, M.J. Embrechts, and O. Ersoy, Eds., ASME Press; Erdogmus, D., Principe, J., "Entropy Minimization Algorithm for Neural Networks" (2001) Proceedings of the Intl. Joint Conf. on Neural Networks, pp. 3003-3008; Xu, D., Princpe, J., "Training mlps layer-by-layer with the information potential" (1999) Intl. Joint Conf. on Neural Networks, pp. 1716-1720; Silverman, B.W., (1986) Density Estimation for Statistics and Data Analisys, 26. , Chapman & Hall; Bowman, A.W., Azzalini, A., (1997) Applied Smooting Techniques for Data Analysis, , London: Oxford University Press; Jacobs, R., Jordan, M., Nowlan, S., Hinton, G., "Adaptive mixtures of local experts" (1991) Neural Computation, pp. 79-87
Keywords: Cost function; entropy; Error entropy minimization (EEM) algorithm; Learning algorithms; Learning systems; Neural networks; Optimization; Parzen; Probability density function; Smoothing parameter

Polysaccharides as scaffolds for bone regeneration - Barbosa, M.A.; Granja, P.L.; Barrias, C.C.; Amaral, I.F. (ITBM-RBMITBM-RBM, 2005)
This review is concerned with the use of polysaccharides for bone regeneration. Cellulose, alginate and chitosan have been chosen as examples of the formidable potential of this class of materials. Many others could be cited but our experience and research interests dictated the choice. As in many areas of research we know how they started but we cannot see how and if they will end. Modification of cellulose was our entrance to the world of polysaccharides and a lot of what we know we owe to Charles Baquey, to whom we would like to express our immense gratitude. This chapter is dedicated to him, for his cooperation, unlimited enthusiasm and friendship. © 2005 Elsevier SAS. All rights reserved.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: ITBMFdoi: 10.1016/j.rbmret.2005.04.006Language of Original Document: EnglishCorrespondence Address: Barbosa, M.A.; INEB, Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: mbarbosa@ibmc.up.ptChemicals/CAS: alginic acid, 28961-37-7, 29894-36-8, 9005-32-7, 9005-38-3; arginylglycylaspartic acid, 99896-85-2; cellulose, 61991-22-8, 68073-05-2, 9004-34-6; chitosan, 9012-76-4References: Shogren, R.L., Bagley, E.B., Natural polymers as advanced materials: Some research needs and directions (1999) Biopolymers. Utilizing Nature's Advanced Materials, ACS Symposium Series 723, pp. 2-11. , S.H. Iman R.V. Greene B.R. Zaidi Oxford University Press Cary, USA;Kaplan, D.L., Introduction to polymers from renewable resources (1998) Biopolymers from Renewable Resources, pp. 1-29. , D.L. Kaplan Springer Verlag Berlin, Germany; Yannas, I.V., Natural materials (1996) Biomaterials Science. An Introduction to Materials in Medicine, pp. 84-94. , B.D. Ratner A.S. Hoffman F.J. Schoen J.E. Lemons Academic Press California, USA; Hon, D.-S., Cellulose and its derivatives: Structures, reactions, and medical uses (1996) Polysaccharides in Medicinal Applications, pp. 87-105. , S. Dumitriu Marcel Dekker New York, USA; Okajima, K., Role of molecular characteristics on some physiological properties of cellulose derivatives (1989) Cellulose: Structural and Functional Aspects, pp. 439-446. , J.F. Kennedy G.O. Phillips P.A. Williams Ellis Horwood Chichester, UK; Ikada, Y., Biomedical applications of cellulose membranes Cellulose: Structural and Functional Aspects, pp. 447-455; Miyamoto, T., Takahashi, S., Ito, H., Inagaki, H., Noishiki, Y., Tissue biocompatibility of cellulose and its derivatives (1989) J. Biomed. Mater. Res., 23, pp. 125-133; Hayashi, T., Biodegradable polymers for biomedical uses (1994) Prog. Polym. Sci., 19, pp. 663-702; Klemm, D., Philipp, B., Heinze, T., Heinze, U., Wagenknecht, W., (1998) Comprehensive Cellulose Chemistry, Vol 1, Fundamentals and Analytical Methods and Functionalization of Cellulose, Vol. 2, , Wiley-VCH Weinheim, Germany; Hon, D.-S., Cellulose and its derivatives: Structures, reactions, and medical uses (1996) Polysaccharides in Medicinal Applications, pp. 87-105. , S. Dumitriu Marcel Dekker New York, USA; Nevell, T.P., Zeronian, S.H., (1985) Cellulose Chemistry and Its Applications, , Ellis Horwood Chichester, UK; Pommier, J.C., Poustis, J., Baquey, C., Chauveaux, D., Biocompatible, hydrophilic material. Method of manufacture and uses of same. Fr Pat 8610331, 1986; Eur Pat 0256906 A1, 1987; US Pat 4904258, 1990Baquey, C., Chauveuax, D., Poustis, J., La cellulose: Un vieux mat́riau pour le developpement de biomat́riaux innovants (1992) Sci. Tech. Technol., 20, pp. 28-32; Barbí, C., Chauveaux, D., Baquey, C., Poustis, J., Pommier, J.C., Morlier, R., Évaluation des propriet́s mecaniques de mat́riaux cellulosiques et perspectives d'application originales de ces mat́riaux en chirurgie orthoṕdique (1987) Calcified Tissues and Biomaterials, pp. 319-325. , Proc BIOMAT 87 Congress Bordeaux, France; Barbí, C., Bareille, R., Harmand, M.-F., Baquey, C., Cellulosic materials for skeletal reparation: Mechanical, physical and biological in vitro behaviour (1989) Calcified Tissues and Biomaterials, , Proc BIOMAT 89 Congress Bordeaux, France; Brie, J., Lafage, M.H., Chauveaux, D., Gueroult, J.M., Poustis, J., Baquey, C., La cellulose macroporeuse: Un mat́riau potentiellement utilisable pour le comblement osseux (1992) Biomat́riaux et Organes Artificiels, , Proc BIOMAT 92 Congress Bordeaux, France; Poustis, J., Chauveaux, D., Baquey, C., (1992) Dynamic Testing of Cellulose in Orthopaedics Devices and Related Environments, p. 191. , 4th World Biomaterials Congr Berlin, Germany; Poustis, J., Baquey, C., Chauveaux, D., Mechanical properties of cellulose in orthopaedic devices and related environments (1994) Clin. Mater., 16, pp. 119-124; Chauveaux, D., Gueroult, J.-M., Barbí, C., Baquey, C., Cellulosic materials for skeletal reparation: Preliminary study of in vivo biocompatibility (1989) Calcified Tissues and Biomaterials, , Proc BIOMAT 89 Congress Bordeaux, France; Barbie, C., Chauveaux, D., Barthe, X., Baquey, C., Poustis, J., Biological behaviour of cellulosic materials after bone implantation: Preliminary results (1990) Clin. Mater., 5, pp. 251-258; Gross, U., Muller-Mai, C., Voigt, C., (1992) The Tissue Response on Cellulose Cylinders after Implantation in the Distal Femur of Rabbits, p. 192. , 4th World Biomaterials Congr Berlin, Germany; Baquey, C., Barbí, C., More, N., Rouais, F., Poustis, J., Chauveaux, D., (1992) In Vivo Study of the Biostability of a Cellulose Material, p. 365. , 4th World Biomaterials Congr Berlin, Germany; Mizusawa, Y., Burke, J.R., Prednisolone and cellulose phosphate treatment in idiopathic infantile hypercalcaemia with nephrocalcinosis (1996) J. Pediatr. Child Health, 32, pp. 350-352; Parfitt, A.M., Effect of cellulose phosphate on calcium and magnesium homeostasis: Studies in normal subjects and patients with latent hypoparathyroidism (1975) Clin. Sci. Mol. Med., 49, pp. 83-90; Pak, C.Y.C., Delea, C.S., Bartter, F.C., Successful treatment of recurrent nephrolithiasis (calcium stones) with cellulose phosphate (1974) N. Engl. J. Med., 290, pp. 175-180; Dowd, V., Yon, R.J., Heterogeneous binding of aldolase to phosphocellulose. Interpretation in terms of a "concerted cluster" model of multivalent affinity (1992) J. Chromatogr., 627, pp. 145-151; Sugihara, J., Imamura, T., Yanase, T., Separation of peptides by cellulose-phosphate chromatography for identification of a hemoglobin variant (1982) J. Chromatogr., 229, pp. 193-199; Granja, P.L., Pouyśgu, L., Ṕtraud, M., De J́so, B., Baquey, C., Barbosa, M.A., Cellulose phosphates as biomaterials. Synthesis and characterization of highly phosphorylated cellulose gels (2001) J. Appl. Polym. Sci., 82, pp. 3341-3353; Granja, P.L., Pouyśgu, L., Deffieux, D., Daud́, G., De J́so, B., Labrug̀re, C., Cellulose phosphates as biomaterials. Surface chemical modification of regenerated cellulose hydrogels (2001) J. Appl. Polym. Sci., 82, pp. 3354-3365; Granja, P.L., Pouyśgu, L., De J́so, B., Rouais, F., Baquey, C., Barbosa, M.A., Cellulose phosphates as biomaterials. Mineralization of chemically modified regenerated cellulose hydrogels (2001) J. Mater. Sci., 36, pp. 2163-2172; Granja, P.L., Ribeiro, C.C., De J́so, B., Baquey, C., Barbosa, M.A., Mineralization of regenerated cellulose hydrogels (2001) J. Mater. Sci. Mater. Med., 12, pp. 785-791; Granja, P.L., De J́so, B., Bareille, R., Rouais, F., Baquey, C., Barbosa, M.A., (2004) Cellulose Phosphates As Biomaterials. in Vitro Biocompatibility Studies; Granja, P.L., De J́so, B., Bareille, R., Rouais, F., Baquey, C., Barbosa, M.A., (2004) Mineralization of Regenerated Cellulose Hydrogels Induced by Human Osteoprogenitor Cells; Fricain, J.C., Granja, P.L., Barbosa, M.A., De J́so, B., Barthe, N., Baquey, C., Cellulose phosphates as biomaterials. in vivo biocompatibility studies (2001) Biomaterials, 23, pp. 971-980; Franz, G., Polysaccharides in pharmacy (1986) Adv. Polym. Sci., 76, pp. 1-30; Skoog, T., The use of periosteum and surgicel® for bone restoration in congenital clefts of the maxilla (1967) Scand. J. Plast. Reconstr. Surg., 1, pp. 113-130; Degenshein, G.A., Hurwitz, A., Ribacoff, S., Experience with regenerated oxidized cellulose (1963) N. Y. State J. Med., 63, pp. 2639-2643; Finn, M.D., Schow, S.R., Schneiderman, E.D., Osseous regeneration in the presence of four common hemostatic agents (1992) J. Oral Maxillofac. Surg., 50, pp. 608-612; Galgut, P.N., Oxidized cellulose mesh. I. Biodegradable membrane in periodontal surgery (1990) Biomaterials, 11, pp. 561-564; Matthew, I.R., Browne, R.M., Frame, J.W., Millar, B.G., Subperiosteal behaviour of alginate and cellulose wound dressing materials (1995) Biomaterials, 16, pp. 275-278; Galgut, P.N., Oxidized cellulose mesh. II. Using hydroxy-apatite bone grafting material in the treatment of intrabony deffects (1990) Biomaterials, 11, pp. 565-567; De Taillac, L.B., Fricain, J.C., Barthe, N., Brouillaud, B., Labrugere, C., Bareille, R., Validation du concept de materiaux hybrids a base de cellulose macroporeuse - Application a l'odontologie (2004) Les Cahiers de l'Adf, 1617, pp. 18-25; De Taillac, L.B., (2004), Ph.D. Thesis. University of Bordeaux 1. DecemberMartson, M., Viljanto, J., Hurme, T., Saukko, P., Biocompatibility of cellulose sponge with bone (1998) Eur. Surg. Res., 30, pp. 426-432; Martson, M., Viljanto, J., Hurme, T., Laippala, P., Saukko, P., Is cellulose sponge degradable or stable as implantation materials? An in vivo subcutaneous study in the rat (1999) Biomaterials, 20, pp. 1899-1995; Pajulo, O., Viljanto, J., Lonnberg, B., Hurme, T., Lonnqvist, K., Saukko, P., Viscose cellulose sponge as an implantable matrix: Changes in the structure increase the production of granulation tissue (1996) J. Biomed. Mater. Res., 32, pp. 439-446; De Taillac, L.B., Porte, M.C., Bareille, R., Amedee, J., Labrugere, C., Fortin, F., (2002) Development of a New Generation of Bone Substitute - Covalenet Immobilization of the Active Peptides onto Cellulose, , Society for Biomaterials Conference Florida, USA; De Taillac, L.B., Labrugere, C., Amedee, J., Bareille, R., Fricain, J.C., Fortin, F., (2002) Human Osteoblasts Interaction with Adhesion Peptides Grafted onto Cellulose, , 17th European Conference on Biomaterials Barcelona, Spain; De Taillac, L.B., Porte-Durrieu, M.C., Labrugere, C., Bareille, R., Aḿd́e, J., Baquey, C., Grafting of RGD peptides to cellulose to enhance human osteoprogenitor cells adhesion and proliferation (2004) Compos. Sci. Technol., 64, pp. 775-915; Gombotz, W.R., Wee, S.F., Protein release from alginate matrices (1998) Adv. Drug Deliv. Rev., 31, pp. 267-285; Smidsrod, O., Draget, K.I., Chemistry and physical properties of alginates (1996) Carbohydr. Eur., 14, pp. 6-13; Eiselt, P., Yeh, J., Latvala, R.K., Shea, L.D., Mooney, D.J., Porous carriers for biomedical applications based on alginate hydrogels (2000) Biomaterials, 21, pp. 1921-1927; Alsberg, V., Anderson, K., Albeiruti, A., Franceshi, R.T., Mooney, D.J., Cell interactive alginate hydrogels for bone tissue engineering (2001) J. Dent. Res., 80, pp. 2025-2029; Barrias, C.C., Granja, P.L., Meriem, L., Sá Miranda, M.C., Barbosa, M.A., Biological evaluation of calcium alginate microspheres as a vehicle for the localised delivery of a therapeutic enzyme (2005) J. Biomed. Mater Res.; Rowley, J.A., Madlambayan, G., Mooney, D.J., Alginate hydrogels as synthetic extracellular matrix materials (1999) Biomaterials, 20, pp. 45-53; Dalby, M.J., Di Silvio, L., Harper, E.J., Bonfield, W., Increasing hydroxyapatite incorporation into poly(methylmethacrylate) cement increases osteoblast adhesion and response (2002) Biomaterials, 23, pp. 569-576; Ribeiro, C.C., Barrias, C.C., Barbosa, M.A., Calcium phosphate-alginate microspheres as enzyme delivery matrices (2004) Biomaterials, 25, pp. 4363-4373; Barrias, C.C., Ribeiro, C.C., Sá Miranda, M.C., Barbosa, M.A., Effect of calcium phosphate addition to alginate microspheres: Modulation of enzyme release kinetics and improvement of osteoblastic cell adhesion (2005) Key Eng. Mater., 284-286, pp. 689-692; Khor, E., (2001) Chitin: Fulfilling a Biomaterials Promise. 1st Ed, , Elsevier Oxford, UK; Vandevord, P.J., Matthew, H.W.T., Desilva, S.P., Mayton, L., Wu, B., Wooley, P.H., Evaluation of the biocompatibility of a chitosan scaffold in mice (2002) J. Biomed. Mater. Res., 59, pp. 585-590; Roberts, G.A.F., (1992) Chitin Chemistry, , The Macmillan Press Houndmills; Domard, A., Chitosan interactions Advances in Chitin Science, pp. 410-420. , Domard A, Roberts GAF, Varum KM, editors. Lyon, France: Jacques André Publisher (1007); Tomihata, K., Ikada, Y., In vitro and in vivo degradation of films of chitin and its deacetylated derivatives (1997) Biomaterials, 18, pp. 567-575; Muzzarelli, R.A.A., Human enzymatic activities related to the therapeutic administration of chitin derivatives (1997) Cell. Mol. Life Sci., 53, pp. 131-140; Muzzarelli, R.A.A., Muzzarelli, C., Natural and artificial chitosan-inorganic composites, a mini-review (2002) Chitosan in Pharmacy and Chemistry: Atec Edizioni, pp. 233-244. , R.A.A. Muzzarelli C. Muzzarelli; Lee, J.Y., Nam, S.H., Im, S.Y., Park, Y.J., Lee, Y.M., Seol, Y.J., Chung, C.P., Lee, S.J., Enhanced bone formation by controlled growth factor delivery from chitosan-based biomaterials (2002) J. Control. Release, 78, pp. 187-197; Madihally, S.V., Matthew, H.W.T., Porous chitosan scaffolds for tissue engineering (1999) Biomaterials, 20, pp. 1133-1142; Nettles, D.L., Elder, S.H., Gilbert, J.A., Potential use of chitosan as a cell scaffold material for cartilage tissue engineering (2002) Tissue Eng., 8, pp. 1009-1016; Lahiji, A., Sohrabi, A., Hungerford, D.S., Frondoza, C.G., Chitosan supports the expression of extracellular matrix proteins in human osteoblasts and chondrocytes (2000) J. Biomed. Mater. Res., 51, pp. 586-595; Zhao, F., Yin, Y.J., Lu, W.W., Leong, J.C., Zhang, W.J., Zhang, J.Y., Preparation and histological evaluation of biomimetic three-dimensional hydroxyapatite/chitosan-gelatin network composite scaffolds (2002) Biomaterials, 23, pp. 3227-3234; Chatelet, C., Damour, O., Domard, A., Influence of the degree of acetylation on some biological properties of chitosan films (2001) Biomaterials, 22, pp. 261-268; Dhiman, H.K., Ray, A.R., Panda, A.K., Characterization and evaluation of chitosan matrix for in vitro growth of MCF-7 breast cancer cell lines (2004) Biomaterials, 25, pp. 5147-5154; Prasitsilp, M., Jenwithisuk, R., Kongsuwan, K., Damrongchai, N., Watts, P., Cellular responses to chitosan in vitro: The importance of deacetylation (2000) J. Mater. Sci. Mater. Med., 11, pp. 773-778; Amaral, I.F., Granja, P.L., Barbosa, M.A., In vitro mineralisation of chitosan membranes carrying phosphate functionalities (2004) Key Eng. Mater., 254-256, pp. 577-580
Keywords: Alginate; alginic acid; Amino Acid Sequence; arginylglycylaspartic acid; biomaterial; biotechnology; bone cell; bone prosthesis; Bone Regeneration; Cellulose; chitosan; enzyme degradation; polysaccharide; Polysaccharides; review; Tissue engineering

Rat bone marrow stromal cell osteogenic differentiation and fibronectin adsorption on chitosan membranes: The effect of the degree of acetylation - Amaral, I.F.; Lamghari, M.; Sousa, S.R.; Sampaio, P.; Barbosa, M.A. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2005)
Cell adhesion, migration, and proliferation of a few anchorage-dependent cells cultured on chitosan (Ch) matrices are influenced by the degree of N-acetylation (DA) of Ch. In the present work, we examined the influence of the DA on the attachment, spreading, proliferation, and osteogenic differentiation of rat bone marrow stromal cells (rBM-SCs). Ch membranes were characterized in terms of surface morphology, roughness, and wettability, and in terms of adsorption of an adhesive protein, fibronectin (Fn). Chs with DAs in the range of 4 to 49% were used. Among the Ch samples, the DA of 4% led to the highest Fn surface concentration, both from single protein solution and from diluted serum. Furthermore, the levels of Fn adsorbed from serum found for this DA were threefold higher than for the tissue culture polystyrene control, indicating that in the presence of competitive proteins Ch is more specific toward Fn adsorption than tissue culture polystyrene. rBMSCs cultured on Ch carrying a DA of 4% were able to spread, proliferate, and differentiate, reaching a higher level of osteogenic differentiation than on the control, despite the lower cell attachment observed for all Ch samples. Because the Ch sample with a DA of 4% showed the highest Fn adsorption from serum, we suggest that cell adhesion, spreading, and osteogenic differentiation of rBMSCs on Ch may be mediated by the adsorbed layer of Fn. © 2005 Wiley Periodicals, Inc.
Cited By (since 1996): 25Export Date: 21 November 2012Source: ScopusCODEN: JBMRCdoi: 10.1002/jbm.a.30436PubMed ID: 16092111Language of Original Document: EnglishCorrespondence Address: Amaral, I.F.; INEB-Instituto de Engenharia Biomédica, Laboratório de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: iamaral@ineb.up.ptChemicals/CAS: chitosan, 9012-76-4; fibronectin, 86088-83-7; polystyrene, 9003-53-6; Chitosan, 9012-76-4; Coated Materials, Biocompatible; FibronectinsReferences: VandeVord, P.J., Matthew, H.W.T., DeSilva, S.P., Mayton, L., Wu, B., Wooley, P.H., Evaluation of the biocompatibility of a chitosan scaffold in mice (2002) J Biomed Mater Res, 59 (3), pp. 585-590;Muzzarelli, R.A.A., Human enzymatic activities related to the therapeutic administration of chitin derivatives (1997) Cell Mol Life Sci, (53), pp. 131-140; Peluso, G., Petillo, O., Ranieri, M., Santin, M., Ambrosio, L., Calabro, D., Avallone, B., Balsamo, G., Chitosan-mediated stimulation of macrophage function (1994) Biomaterials, 15 (15), pp. 1215-1220; Muzzarelli, R.A.A., Mattiolibelmonte, M., Tietz, C., Biagini, R., Ferioli, G., Brunelli, M.A., Fini, M., Biagini, G., Stimulatory effect on bone-formation exerted by a modified chitosan (1994) Biomaterials, 15 (13), pp. 1075-1081; Lee, J.Y., Nam, S.H., Im, S.Y., Park, Y.J., Lee, Y.M., Seol, Y.J., Chung, C.P., Lee, S.J., Enhanced bone formation by controlled growth factor delivery from chitosan-based biomaterials (2002) J Controlled Release, 78 (1-3), pp. 187-197; Chupa, J.M., Foster, A.M., Sumner, S.R., Madihally, S.V., Matthew, H.W.T., Vascular cell responses to polysaccharide materials: In vitro and in vivo evaluations (2000) Biomaterials, 21 (22), pp. 2315-2322; Lahiji, A., Sohrabi, A., Hungerford, D.S., Frondoza, C.G., Chitosan supports the expression of extracellular matrix proteins in human osteoblasts and chondrocytes (2000) J Biomed Mater Res, 51 (4), pp. 586-595; Klokkevold, P.R., Vandemark, L., Kenney, E.B., Bernard, G.W., Osteogenesis enhanced by chitosan (poly-N-acetyl glucosaminoglycan) in vitro (1996) J Periodontol, 67 (11), pp. 1170-1175; Tomihata, K., Ikada, Y., In vitro and in vivo degradation of films of chitin and its deacetylated derivatives (1997) Biomaterials, 18 (7), pp. 567-575; Chatelet, C., Damour, O., Domard, A., Influence of the degree of acetylation on some biological properties of chitosan films (2001) Biomaterials, 22 (3), pp. 261-268; Dhiman, H.K., Ray, A.R., Panda, A.K., Characterization and evaluation of chitosan matrix for in vitro growth of MCF-7 breast cancer cell lines (2004) Biomaterials, 25 (21), pp. 5147-5154; Prasitsilp, M., Jenwithisuk, R., Kongsuwan, K., Damrongchai, N., Watts, P., Cellular responses to chitosan in vitro: The importance of deacetylation (2000) J Mater Sci Mater Med, 11 (12), pp. 773-778; Rainaldi, G., Filippini, P., Ferrante, A., Indovina, P.L., Santini, M.T., Fibronectin facilitates adhesion of K562 leukemic cells normally growing in suspension to cationic surfaces (2001) J Biomed Mater Res, 55 (1), pp. 104-113; Faucheux, N., Schweiss, R., Lutzow, K., Werner, C., Groth, T., Self-assembled monolayers with different terminating groups as model substrates for cell adhesion studies (2004) Biomaterials, 25 (14), pp. 2721-2730; Cuy, J.L., Beckstead, B.L., Brown, C.D., Hoffman, A.S., Giachelli, C.M., Adhesive protein interactions with chitosan: Consequences for valve endothelial cell growth on tissue-engineering materials (2003) J Biomed Mater Res, 67 A (2), pp. 538-547; Bumgardner, J.D., Wiser, R., Elder, S.H., Jouett, R., Yang, Y., Ong, J.L., Contact angle, protein adsorption and osteoblast precursor cell attachment to chitosan coatings bonded to titanium (2003) J Biomater Sci Polym Ed, 14 (12), pp. 1401-1409; Gong, H.P., Zhong, Y.H., Li, J.C., Gong, Y.D., Zhao, N.M., Zhang, X.F., Studies on nerve cell affinity of chitosan-derived materials (2000) J Biomed Mater Res, 52 (2), pp. 285-295; Benesch, J., Tengvall, P., Blood protein adsorption onto chitosan (2002) Biomaterials, 23 (12), pp. 2561-2568; Brugnerotto, J., Lizardi, J., Goycoolea, F.M., Arguelles-Monal, W., Desbrieres, J., Rinaudo, M., An infrared investigation in relation with chitin and chitosan characterization (2001) Polymer, 42 (8), pp. 3569-3580; Mima, S., Miya, M., Iwamoto, R., Yoshikawa, S., Highly deacetylated chitosan and its properties (1983) J Appl Polym Sci, 28 (6), pp. 1909-1917; Aiba, S., Studies on chitosan: 1. Determination of the degree of N-acetylation of chitosan by ultraviolet spectrophotometry and gel-permeation chromatography (1986) Int J Biol Macromol, 8 (3), pp. 173-176; Baxter, A., Dillon, M., Taylor, K.D.A., Roberts, G.A.F., Improved method for i.r. determination of the degree of N-acetylation of chitosan (1992) Int J Biol Macromol, 14 (3), pp. 166-169; Terbojevich, M., Cosani, A., Muzzarelli, R.A.A., Molecular parameters of chitosans depolymerized with the aid of papain (1996) Carbohydr Polym, 29 (1), pp. 63-68; Grundke, K., Bogumil, T., Werner, C., Janke, A., Poschel, K., Jacobasch, H.J., Liquid-fluid contact angle measurements on hydrophilic cellulosic materials (1996) Colloids Surf A, 116 (1-2), pp. 79-91; Slack, M., Properties of biological fluids (2004) Biomaterials Science: An Introduction to Materials in Medicine, pp. 813-817. , Ratner BD, Hoffman AS, Schoen FJ, Lemons JE, editors. Amsterdam: Elsevier; Du, Y.J., Cornelius, R.M., Brash, J.L., Measurement of protein adsorption to gold surface by radioiodination methods: Suppression of free iodide Sorption (2000) Colloids Surf B, 17 (1), pp. 59-67; (1993) Iodine-125, a Guide to Radioiodination Techniques, p. 64. , Little Chalfont, Buckinghamshire, UK: Amersham International; Sousa, S.R., Moradas-Ferreira, P., Saramago, B., Melo, L.V., Barbosa, M.A., Human serum albumin adsorption on TiO2 from single protein solutions and from plasma (2004) Langmuir, 20 (22), pp. 9745-9754; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone-formation in vitro by stromal cells obtained from bone-marrow of young-adult rats (1988) Cell Tissue Res, 254 (2), pp. 317-330; Ashton, B.A., Abdullah, F., Cave, J., Williamson, M., Sykes, B.C., Couch, M., Poser, J.W., Characterization of cells with high alkaline-phosphatase activity derived from human-bone and marrow: Preliminary assessment of their osteogenicity (1985) Bone, 6 (5), pp. 313-319; Huang, R.Y.M., Moon, G.Y., Pal, R., Chitosan/anionic surfactant complex membranes for the pervaporation separation of methanol/MTBE and characterization of the polymer/surfactant system (2001) J Membr Sei, 184 (1), pp. 1-15; Domke, J., Dannohl, S., Parak, W.J., Muller, O., Aicher, W.K., Radmacher, M., Substrate dependent differences in morphology and elasticity of living osteoblasts investigated by atomic force microscopy (2000) Colloids Surf B, 19 (4), pp. 367-379; Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 21 (7), pp. 667-681; Domard, A., Chitosan interactions (1997) Advances in Chitin Science, pp. 410-420. , Domard A, Roberts GAF, Varum KM, editors. Lyon, France: Jacques André Publisher; Smidsrod, O., Ottoy, M.H., Anthonsen, M.W., Varum, K.M., Solution properties of chitosan (1997) Advances in Chitin Science, pp. 402-409. , Domard A, Roberts GAF, Varum KM, editors. Lyon, France: Jacques André Publisher; Fee, M., Errington, N., Jumel, K., Ilium, L., Smith, A., Harding, S.E., Correlation of SEC/MALLS with ultracentrifuge and viscometric data for chitosans (2003) Eur Biophys J, 32, pp. 457-464; Keselowsky, B.G., Collard, D.M., Garcia, A.J., Surface chemistry modulates fibronectin conformation and directs integrin binding and specificity to control cell adhesion (2003) J Biomed Mater Res, 66 A (2), pp. 247-259; Andrade, J.D., Smith, L.M., Gregonis, D.E., The contact angle and interface energetics (1997) Physical Chemistry of Surfaces, pp. 249-292. , Adamson AW, Gast AP, editors. New York: John Wiley & Sons;; McFarland, C.D., Mayer, S., Scotchford, C., Dalton, B.A., Steele, J.G., Downes, S., Attachment of cultured human bone cells to novel polymers (1999) J Biomed Mater Res, 44 (1), pp. 1-11; Lebaron, R.G., Athanasiou, K.A., Extracellular matrix cell adhesion peptides: Functional applications in orthopedic materials (2000) Tissue Eng, 6 (2), pp. 85-103; Massia, S.P., Hubbell, J.A., An RGD spacing of 440 run is sufficient for integrin alpha-V-beta-3- mediated fibroblast spreading and 140 nm for focal contact and stress fiber formation (1991) J Cell Biol, 114 (5), pp. 1089-1100; Verrier, S., Fallu, S., Bareille, R., Jonczyk, A., Meyer, J., Dard, M., Amedee, J., Function of linear and cyclic RGD-containing peptides in osteoprogenitor cells adhesion process (2002) Biomaterials, 23 (2), pp. 585-596; Gronthos, S., Sirnmons, P.J., Graves, S.E., Robey, P.G., Integrin-mediated interactions between human bone marrow stromal precursor cells and the extracellular matrix (2001) Bone, 28 (2), pp. 174-181; Webb, K., Hlady, V., Tresco, P.A., Relationships among cell attachment, spreading, cytoskeletal organization, and migration rate for anchorage-dependent cells on model surfaces (2000) J Biomed Mater Res, 49 (3), pp. 362-368; Stein, G.S., Lian, J.B., Stein, J.L., Wijnen, A.J., Frenkel, B., Montecino, M., Mechanisms regulating osteoblast proliferation and differentiation (1996) Principles of Bone Biology, pp. 69-86. , Bilezikian JP, Raisz LG, Rodan GA, editors. San Diego: Academic Press; Aubin, J.E., Liu, F., The osteoblast lineage (1996) Principles of Bone Biology, pp. 51-67. , Bilezikian JP, Raisz LG, Rodan GA, editors. San Diego: Academic Press; Moursi, A.M., Globus, R.K., Damsky, C.H., Interactions between integrin receptors and fibronectin are required for calvarial osteoblast differentiation in vitro (1997) J Cell Sci, 110, pp. 2187-2196; Stephansson, S.N., Byers, B.A., Garcia, A.J., Enhanced expression of the osteoblastic phenotype on substrates that modulate fibronectin conformation and integrin receptor binding (2002) Biomaterials, 23 (12), pp. 2527-2534
Keywords: Acetylation; Adhesion; Adsorption; animal cell; Animals; article; artificial membrane; binding affinity; binding competition; Bone; bone development; bone marrow cell; Bone Marrow Cells; Bone marrow stomal cells; Bone marrow stromal cells; cell adhesion; cell anchorage; Cell culture; cell differentiation; Cell membranes; cell migration; cell proliferation; Cell Shape; cell spreading; chitosan; Coated Materials, Biocompatible; controlled study; cytoskeleton; Degree of acetylation; Fibronectin; Fibronectins; male; materials testing; morphology; nonhuman; polystyrene; Proteins; rat; Rats; Rats, Wistar; roughness; stroma cell; Stromal Cells; Surface Properties; surface property; Tissue culture; wettability

Automatic lane and band detection in images of thin layer chromatography - Sousa, A.V.; Aguiar, R.; Mendonca, A.M.; Campilho, A. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2004)
This work aims at developing an automatic method for the analysis of TLC images for measuring a set of features that can be used for the characterization of the distinctive patterns that result from the separation of oligosaccharides contained in human urine. This paper describes the methods developed for the automatic detection of the lanes contained in TLC images, and for the automatic separation of bands for each detected lane. The extraction of quantitative information related with each band was accomplished with two methods: the EM expectation-maximization and nonlinear least squares trustregion algorithms. The results of these methods, as well as additional quantitative information related with each band, are also presented. © Springer-Verlag 2004.
Cited By (since 1996): 7Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Sousa, A.V.; Institute de Engenharia Biomédica, Rua Roberto Prias, 4200-465 Porto, Portugal; email: ats@isep.ipp.ptReferences: Sewell, A., (1991) Urinary Oligosaccharides. Techniques in Diagnostic Human Biochemical Genetics, pp. 219-231. , Willey-Liss, Inc;Thomas, G., Disorders of Glycoprotein Degradation. α-Mannosidosis, β-Mannosidosis, Fucosidosis and Sialidosis, , Disorders of Glycoprotein Degradation (Chap. 140); Starr, C., Masada, R., Hague, C., Klock, J., Fluorophore-assisted Carbohydrate Electrophoresis in the Separation, Analysis, and Sequencing of Carbohydrates (1996) Journal of Chromatography A, 720, pp. 295-321; Klein, A., Lebreton, A., Lemoine, J., Périni, J., Roussel, P., Michalski, J., Identification of Urinary Oligosaccharides by Matrix-assisted Laser Desorption Ionization Time-of-flight Mass Spectrometry (1998) Clinical Chemistry, 44 (12), pp. 2422-2428; Dempster, A., Laird, N., Rubin, D., Maximum Likelihood from Incomplete Data via the em Algorithm (1977) Journal of the Royal Statistical Society, B, 39 (1), pp. 1-38; Schwedt, G., The Essential Guide to Analytical Chemistry, , John Wiley & Sons; Dennis, J., Nonlinear Least-squares, State of the Art in Numerical Analysis, , D. Jacobs Academic Press; Byrd, R., Schnabel, R., Shultz, G., Approximate Solution of the Trust Region Problem by Minimization over Two-Dimensional Subspaces (1988) Mathematical Programming, 40, pp. 247-263; Branch, M., Coleman, T., Li, Y., A Subspace, Interior, and Conjugate Gradient Method for Large-Scale Bound-Constrained Minimization Problems (1999) SIAM SISC, 21 (1), pp. 1-23; Nabney, I., Netlab Algorithms for Pattern Recognition (2003) Advances in Pattern Recognition, , Springer; Marques, J., Reconhecimento de Padrões, , Métodos Estatisticos e Neuronais, IST-Press; Machado, A., Campos, M., Siqueira, A., Carvalho, O., (1997) An Iterative Algorithm for Segmenting Lanes in Gel Electrophoresis Images;

Bonelike®/PLGA hybrid materials for bone regeneration: In vivo evaluation - Oliveira, J.M.; Kawai, T.; Lopes, M.A.; Ohtsuki, C.; Santos, J.D.; Afonso, A. (Materials Science ForumMater Sci Forum, 2004)
The biocompatibility and osteoconductive potential of Bonelike® and Bonelike®/PLGA hybrid materials were evaluated through subcutaneous and tibiae implantations for a 4 week period. Qualitative histology was performed to evaluate new bone formation and characterise bone-implant interface and results showed that Bonelike®/PLGA hybrid materials promote extensive bone growth. After the 4 week implantation period, Bonelike® resorption was recognized, which may be due to the presence of resorbable β and α-tricalcium phosphate phases.
Conference code: 63332Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: MSFOELanguage of Original Document: EnglishCorrespondence Address: Oliveira, J.M.; Inst. de Engenharia Biomédica, Lab. de Biomateriais, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jmolive@fe.up.ptReferences: Praemer, A., Furner, S., Rice, D.P., (1992) Am. Acad. Orthop. Surg., p. 1;Glowacki, J., Mulliken, J.B., (1985) Clin. Plast. Surg., 12, p. 233; Buck, B.E., Malinin, T.I., Brown, M.D., (1989) Clin. Orthop., 36, p. 129; Sepulveda, P., Bressiani, A.H., Bressiani, J.C., Mesenguer, L., König Jr., B., (2002) J. Biomed. Mater. Res. Vol., 62, p. 587; Glimcher, M.J., (1987) Instr. Course Lect., 36, p. 46; Yakamuro, T., Hench, L.L., Wilson, J., (1990) CRC Handbook of Bioactive Ceramics, 2, pp. 245-252; Klemm, K.W., (1993) Clin. Orthop. & Rel. Res., 295, pp. 63-76; Agrawal, C.M., Ray, R.B., (2001) J. Biomed. Mater. Res., 55, p. 141; Santos, J.D., Campbell, J.K., Winton, G.H., (2000), European Patent N° W00068164Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., (2001) J. Biomed. Mater. Res., 54, p. 463
Keywords: Bacteria; Biodegradation; Bone; Bonelike resorption; Bonelike®; Histological studies; histology; Hybrid materials; hydroxyapatite; In vivo; physiology; PLGA; Polymers; Surgery; Tissue

Bounds for the Average Generalization Error of the Mixture of Experts Neural Network - Alexandre, L.A.; Campilho, A.; Kamel, M. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2004)
In this paper we derive an upper bound for the average-case generalization error of the mixture of experts modular neural network, based on an average-case generalization error bound for an isolated neural network. By doing this we also generalize a previous bound for this architecture that was restricted to special problems. We also present a correction factor for the original average generalization error, that was empirically obtained, that yields more accurate error bounds for the 6 data sets used in the experiments. These experiments illustrate the validity of the derived error bound for the mixture of experts modular neural network and show how it can be used in practice. © Springer-Verlag 2004.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Alexandre, L.A.; Networks and Multimedia Group, IT, Covilhã, Portugal; email: lfbaa@di.ubi.ptReferences: Gu, H., Takahashi, H., Towards more practical average bounds on supervised learning (1996) IEEE Trans. Neural Networks, 7, pp. 953-968;Vapnik, V., (1999) The Nature of Statistical Learning Theory., , Springer; Haykin, S., (1999) Neural Networks: A Comprehensive Foundation, 2nd Edition., , Prentice Hall; Alexandre, L., Campilho, A., Kamel, M., Average error bound for the mixture of experts MNN architecture (2002) Proceedings of the 12th Portuguese Conference on Pattern Recognition, , Aveiro, Portugal; Jacobs, R., Jordan, M., Nowlan, S., Hinton, G., Adaptive mixtures of local experts (1991) Neural Computation, pp. 79-87; Auda, G., Kamel, M., Modular neural network classifiers: A comparative study (1998) J. Intel. Robotic Systems, pp. 117-129; Jordan, M., Jacobs, R., Hierarchical mixture of experts and the em algorithm (1994) Neural Computation, pp. 181-214; Jacobs, R., Peng, F., Tanner, M., A bayesian approach to model selection in hierarchical mixtures-of-experts architectures (1997) Neural Networks, 10, pp. 231-241; De Marques Sa, J., Pattern Recognition: Concepts (2001) Methods and Applications, , Springer; Blake, C., Keogh, E., Merz, C., (1998) UCI repository of machine learning databases, , http://www.ics.uci.edu/~mlearn/MLRepository.html; Gu, H., Takahashi, H., Estimating learning curves of concept learning (1997) Neural Networks, 10, pp. 1089-1102; Bishop, C., (1995) Neural Networks for Pattern Recognition., , Oxford University Press; Riedmiller, M., Braun, H., A direct adaptive method for faster backpropagation learning: The RPROP algorithm (1993) IEEE International Conference on Neural Networks, pp. 586-591. , San Francisco
Keywords: Generalization error bounds; Mixture of experts; Modular neural networks

CaO-P 2O 5 Glass-Hydroxyapatite Thin Films Obtained by Laser Ablation: Characterisation and In Vitro Bioactivity Evaluation - Ferraz, M.P.; Monteiro, F.J.; Gião, D.; Leon, B.; Gonzalez, P.; Liste, S.; Serra, J.; Arias, J.; Perez-Amor, M. (Key Engineering MaterialsKey Eng Mat, 2004)
Hydroxyapatite (HA) coatings have been applied to improve adhesion of non-cemented implants to host bone. Plasma spraying is the most common technique leading to thick calcium phosphate films (>120μm). Pulse laser deposition (PLD), is a possible alternative method to obtain thin (<10 μm), well adherent hydroxyapatite (HA) films. Similarly to synthetic HA, biological apatites contain Ca 2+, PO 4 3- and OH
Conference code: 62053Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Ferraz, M.P.; Inst. de Engenharia Biomédica, Laboratório de Biomateriais, Rua Campo Alegre 823, 4150-180 Porto, Portugal; email: mpferraz@ufp.ptReferences: Arias, J.L., (1997) J Mater. Sci. Mater. Med., 8, pp. 873-876;Peraire, C., (1997) 13 th European Conference on Biomaterials, p. 75. , Göteborg, Sweden, 4-7 Sept; Ferraz, M.P., Monteiro, F.J., Santos, J.D., (1999) J Biomed Mater Res, 45, p. 373; Ferraz, M.P., Fernandes, M.H., Trigo-Cabral, A., Santos, J.D., Monteiro, F.J., (1999) J. Mat Sci: Mat. Med, 10 (9), p. 567
Keywords: 2O; 5 glass; Adhesion; Bioactivity; Bone; Calcium Compounds; CaO-P; Coatings; Deposition; Energy dispersive spectroscopy; Homogeneous mixtures; Hydroxylapatite thin films; Implants (surgical); In vitro bioactivity; Laser ablation; Plasma spraying; Scanning electron microscopy; Thin films; X ray diffraction

"In vitro" bioactivity evaluation of CaO-P 2O 5 glass-hydroxylapatite thin coatings produced by pulsed laser deposition - Arias, J.L.; Liste, S.; González, P.; Serra, J.; León, B.; Ferraz, M.P.; Monteiro, F.J.; Giao, D.; Pérez-Amor, M. (Transactions - 7th World Biomaterials CongressTrans. World Biomater. Congr., 2004)
The synthesis of coatings based on hydroxyapatites (HA) and glass modified hydroxyapatite targets by pulsed laser deposition, was presented. It was observed that coatings produced from HA targets keep their crystallinity through all their thickness, while there is a loss of crystallinity towards the surface of the HA+1.5G coatings. On immersion in SBF for three days, the coatings produced from HA targets suffered a loss of crystallinity near the surfaces, while the crystallinity of the coatings produced from HA+1.5G targets increased. It was also observed that addition of 1.5wt% of CaO-P 2O 5 glasses to HA thin coatings produced by pulsed laser deposition leads to a significant structural change of the coating surface.
Conference code: 64310Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Arias, J.L.; Depto. de Física Aplicada, Universidade de Vigo, Lagoas-Marcosende 9, E-36200 Vigo, SpainReferences: Arias, J.L., (1997) J Mater Sci Mater Med, 8, p. 873;Ferraz, M.P., (1999) J Biomed Mater Res, 45, p. 373; Ferraz, M.P., (1999) J. Mat Sci Mat Med, 10, p. 567
Keywords: Apatites; Bioactivity; Calcium Compounds; Coatings; Crystalline materials; Crystalline phases; hydroxyapatite; Mixtures; Phosphorus Compounds; Pressure effects; Pulsed laser deposition; Scanning electron microscopy; Substrates; Thin coatings; X ray diffraction; X ray photoelectron spectroscopy

In Vitro Mineralisation of Human Bone Marrow Cells Cultured on Bonelike® - Costa, M.A.; Gutierres, M.; Almeida, L.; Lopes, M.A.; Santos, J.D.; Fernandes, M.H. (Key Engineering MaterialsKey Eng Mat, 2004)
Bonelike® is a CaO-P 2O 5 based glass-reinforced hydroxyapatite (HA) designed to mimic the inorganic composition of the bone tissue. This work evaluates the response of human bone marrow cells to Bonelike® concerning cell proliferation and osteoblast differentiation. HA was used as control material. Results showed that Bonelike® allowed the proliferation of bone marrow cells and their complete differentiation, as evidenced by the formation of cell-mediated mineralisation. In comparison with HA, Bonelike® had a positive effect on the expression of alkaline phosphatase and also on the formation of a mineralised matrix, two osteoblast markers.
Conference code: 62053Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Costa, M.A.; Inst. Cie. Blomed. de Abel Salazar, Universidade do Porto, Largo Abel Salazar, 4000 Porto, PortugalReferences: Santos, J.D., Campbell, J.K., Winston, G.H., European Patent N° WO0068164, 2000Lopes, M.A., Knowles, J.C., Santos, J.D., (2000) Biomaterials, 21, p. 1905;Lopes, M.A., Monteiro, F.J., Santos, J.D., (1999) J. Biomed. Mater. Res.:App. Biomater., 48, p. 734; Lopes, M.A., Knowles, J.C., Kuru, L., Santos, J.D., Monteiro, F.J., Olsen, I., (1998) J. Biomed. Mater. Res., 41, p. 649; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., (2000) Biomaterials, 21, p. 1165; Ferraz, M.P., Fernandes, M., Santos, J.D., Monteiro, F.J., (2001) J. Mat. Sci.: Mat. Med., 12, p. 629; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., (2001) J. Biomed. Mater. Res., 54, p. 463; Duarte, F., Santos, J.D., Afonso, A., Advanced Materials Forum, , in press; Coelho, M.J., Fernandes, M.H., (2000) Biomaterials, 21, p. 1095; Kleerekoper, M., (1996) Principles of Bone Biology, p. 1053. , Academic Press
Keywords: Bone; Bonelike®; Cell culture; cell proliferation; Composition; Grafts; Human bone marrow cells; hydroxyapatite; In vitro mineralisation; mineralization; Scanning electron microscopy; Sintering; X ray diffraction

In Vivo Behaviour of Bonelike®/PLGA Hybrid: Histological Analysis and Peripheral Quantitative Computed Tomography (pQ-CT) Evaluation - Oliveira, J.M.; Kawai, T.; Lopes, M.A.; Ohtsuki, C.; Santos, J.D.; Afonso, A. (Key Engineering MaterialsKey Eng Mat, 2004)
The present work consisted in assessing the in vivo biological behaviour of novel Bonelike®/PLGA hybrid materials through subcutaneous and tibiae implantations for a 4 week period using an animal model. No sign of inflammation was observed as a result of subcutaneous implantation, which reveals that these materials were well-tolerated by the soft tissues. pQ-CT analysis demonstrated that the implanted materials were highly osteointegrated in bone tissue. SEM analysis at bone defect area revealed that Bonelike® resorption occurred after 4 weeks of implantation. Although the osteoconductive properties of Bonelike® have been reported in literature, the present work allowed to demonstrate that the silane-coupling agent and the PLGA treatments do not significantly modify the biological performance of Bonelike®. This result is strongly encouraging since Bonelike®/PLGA hybrid materials are being developed for bone tissue healing/regeneration purposes with simultaneous delivery of therapeuthic molecules.
Conference code: 62053Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Oliveira, J.M.; Inst. de Engenharia Biomédica, Lab. de Biomaterials, Rua do Campo Alegre, 823, 4150-180 Porto, Portugal; email: jmoliv@fe.up.ptReferences: Solheim, E., Pinholt, E., Bang, G., (1992) Journal Neurosurgery, 76, pp. 275-279;Laurecin, C.T., Attawia, M.A., Lu, L.Q., Borden, M.D., Lu, H.H., Gorum, W.J., Lieberman, J.R., (2001) Biomaterials, 22, pp. 1271-1277; Nielsen, F.F., Karring, T., Gogolewski, S., (1992) Acta Orthop Scandinavica, 63, pp. 66-69; Jiang, G., Woo, B.H., Kang, F., Singh, J., Deluca, P.P., (2002) Journal of Controlled Release, 79, pp. 137-145; Duarte, F., Lopes, M.A., Santos, J.D., European Cells and Materials, , in press; Duarte, F., Afonso, A., Santos, J.D., Advanced Materials Forum, , in press; Oliveira, J.M., Lopes, M.A., Kawai, T., Ohtsuki, C., Santos, J.D., Afonso, A., Advanced Materials Forum, , in press; Santos, J.D., Campbell, J.K., Winton, G.H., European Patent N° W00068164 (2000)Oliveira, J.M., Miyazaki, T., Lopes, M.A., Ohtsuki, C., Santos, J.D., Biomaterials, , submitted
Keywords: Biodegradation; Bonelike®; Computerized tomography; Histological analysis; histology; hydroxyapatite; In vivo studies; Organic polymers; PLGA; pQ-CT; Silanes; Sintering; Synthetic polymers; Tibiae implantations; Tissue

Inflammatory responses and cell adhesion to self-assembled monolayers of alkanethiolates on gold - Barbosa, J.N.; Barbosa, M.A.A.; Águas, A.P. (BiomaterialsBiomaterials, 2004)
The acute inflammatory response and the adhesion of cells to self-assembled monolayers (SAMs) of well-defined surface chemistry was studied in vivo using a rodent air-pouch model of inflammation. SAMs with three different terminal functional groups (OH, COOH and CH 3) were implanted in subcutaneous air pouches induced in BALB/c mice. After 24h, inflammatory cells were recovered from the air pouches and the implants were removed and prepared for observation by scanning electron microscopy (SEM). The implants coated with OH and CH 3, were found to cause the highest recruitment of inflammatory cells into the subcutaneous pouches. Polymorphonuclear neutrophils (PMNs) leukocytes predominated over mononuclear cells in inflammatory exudates of SAMs-coated implants, the opposite being found in uncoated implants (controls). CH 3-coated implants induced the highest number of inflammatory cells and also the largest percentage of PMNs seen in the subcutaneous pouches. Control and OH-covered implants presented the higher densities of attached inflammatory cells detected by SEM. In contrast, the CH 3-coated implants showed a very low density of cells adherent to the implant surface. We conclude that the chemical nature and the degree of hydrophobicity of the surface of implants modulate both the local acute inflammatory reaction and the adhesion of leukocytes. © 2003 Elsevier Ltd. All rights reserved.
Cited By (since 1996): 34Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/j.biomaterials.2003.09.047PubMed ID: 14751741Language of Original Document: EnglishCorrespondence Address: Barbosa, J.N.; INEB - Inst. de Engenharia Biomedica, Laboratório de Biomaterials, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: judite@ibmc.up.ptChemicals/CAS: Gold, 7440-57-5; Sulfhydryl CompoundsReferences: Tang, L., Jiang, W., Welty, S.E., The participation of P- and E-selectins on biomaterial-mediated tissue responses (2002) J Biomed Mater Res, 62, pp. 471-477;Thomsen, P., Gretzer, C., Macrophage interactions with modified material surfaces (2001) Curr Opin Solid State Mater Sci, 5, pp. 163-176; Kao, W.J., Liu, Y., Gundloori, R., Li, J., Lee, D., Einerson, N., Burmania, J., Stevens, K., Engineering endogenous inflammatory cells as delivery vehicles (2002) J Control Release, 78, pp. 219-233; Anderson, J.M., Mechanisms of inflammation and infection with implanted devices (1993) Cardiovasc Pathol, 2, pp. 33S-41S; Anderson, J.M., Inflammatory response to implants (1988) ASAIO J, 11, pp. 101-107; Babensee, J.E., Anderson, J.M., McLntire, L.V., Mikos, A.G., Host response to tissue engineered devices (1998) Adv Drug Deliver Rev, 33, pp. 111-139; Mrksich, M., Whitesides, G.M., Interactions of SAMs with proteins (1996) Annu Rev Biophys Biomol Struct, 25, pp. 55-57; Ulman, A., Formation and structure of self-assembled monolayers (1996) Chem Rev, 96, pp. 1533-1554; Mrksich, M., Tailored substrates for studies of attached cell culture (1998) Cell Mol Life Sci, 54, pp. 653-662; Nuzzo, R.G., Allara, D.L., Adsorption of biofunctional organic dissulfides on gold surfaces (1983) J Am Chem Soc, 105, pp. 4481-4483; Pan, S., Castner, D.G., Ratner, B.D., Multitechnique surface characterization of derivatization efficiencies for hydroxyl-terminated self-assembled monolayers (1998) Langmuir, 14, pp. 3545-3550; Sedwick, A.D., Sin, Y.M., Edwards, J.C., Willoughby, D.A., Increased inflammatory reactivity in newly formed lining tissue (1983) J Pathol, 141, pp. 483-495; Castro, A.G., Esaguy, N., MacEdo, P.M., Águas, A.P., Silva, M.T., Live but not heat-killed mycobacteria cause rapid chemotaxis of large numbers of eosinophils in vivo and are ingested by the attracted granulocytes (1991) Infect Immun, 59, pp. 3009-3014; Isaji, M., Momose, Y., Naito, J., Enhancement of inflammatory reactions in a non-immunological air pouch model in rats (1989) Br J Exp Pathol, 70, pp. 705-716; Tegoulia, V.A., Cooper, S.L., Leukocyte adhesion on model surfaces under flow: Effects of surface chemistry, protein adsorption, and shear rate (2000) J Biomed Mater Res, 50, pp. 291-301; Lin, J., Chuang, W., Synthesis, surface characterization, and platelet reactivity evaluation for the self-assembled monolayer of alkanethiol with sulfonic acid functionality (2000) J Biomed Mater Res, 51, pp. 413-423; Hooper, K.A., Nickolas, T.L., Yurkow, E.J., Kohn, J., Laskin, D., Characterization of the inflammatory response to biomaterials using a rodent air pouch model (2000) J Biomed Mater Res, 50, pp. 365-374; Wooley, P.H., Morren, R., Andary, J., Sud, S., Yang, S., Mayton, L., Markel, D., Nasser, S., Inflammatory responses to orthopaedic biomaterials in the murine air pouch (2002) Biomaterials, 23, pp. 517-526; Gelb, H., Schumacher, H.R., Cuckler, J., Ducheyne, P., Baker, D.G., In vivo inflammatory response to polymethylmethacrylate particulate debris: Effect of size, morphology, and surface area (1994) J Orthop Res, 12, pp. 83-92; Wooley, P.H., Mayton, L., Sud, S., Nasser, S., Synergistic inflammatory responses to metallic and polymeric particles in the murine air pouch model of aseptic loosening (1996) Arthritis Rheum, 39, pp. 175-183; Moore, R., Beredjiklian, P., Rhoad, R., Theiss, S., Cuckler, J., Ducheyne, P., Baker, D.G., A comparison of the inflammatory potential of particulates derived from two composite materials (1997) J Biomed Mater Res, 34, pp. 137-147; Krause, T.J., Robertson, F.M., Greco, R.S., Measurement of intracellular hydrogen peroxide induced by biomaterials implanted in a rodent air pouch (1993) J Biomed Mater Res, 27, pp. 65-69; Yang, S., Ren, W., Park, Y., Sieving, A., Hsu, S., Nasser, S., Wooley, P.H., Diverse cellular and apoptotic responses to variant shapes of UHMWPE particles in a murine model of inflammation (2002) Biomaterials, 23, pp. 3535-3543; Lindblad, M., Lestelius, M., Johansson, A., Tengvall, P., Thomsen, P., Cell and soft tissue interactions with methyl- and hydroxyl-terminated alkanethiols on gold surfaces (1997) Biomaterials, 18, pp. 1059-1068; Tengvall, P., Askendal, A., Lundsröm, I., Complement activation by 3-mercapto-1,2-propanediol immobilized on gold surfaces (1996) Biomaterials, 17, pp. 1001-1007; Liu, L., Elwing, H., Complement activation on thiol-modified gold surfaces (1996) J Biomed Mater Res, 30, pp. 535-541; Tang, L., Liu, L., Elwing, H.B., Complement activation and inflammation triggered by model biomaterial surfaces (1998) J Biomed Mater Res, 41, pp. 333-340; Källtorp, M., Oblogina, S., Jacobsson, S., Karlsson, A., Tengvall, P., Thomsen, P., In vivo cell recruitment, cytokine release and chemiluminescence response at gold, and thiol functionalized surfaces (1999) Biomaterials, 20, pp. 2123-2137; Tang, L., Ugarova, T.P., Plow, E.F., Eaton, J.W., Molecular determinants of acute inflammatory responses to biomaterials (1997) J Clin Invest, 97, pp. 1329-1334; Hu, W., Eaton, J.W., Tang, L., Molecular basis of biomaterial-mediated foreign body reactions (2001) Blood, 98, pp. 1231-1238; Silver, J.H., Hergenrother, R.W., Lin, J., Lim, F., Lin, H., Okada, T., Chaudhury, M.K., Cooper, S.L., Surface and blood-contacting properties of alkylsiloxane monolayers supported on silicone rubber (1995) J Biomed Mater Res, 29, pp. 535-548; Werthén, M., Sellborn, A., Källtorp, M., Elwing, H., Thomsen, P., In vitro study of monocyte viability during the initial adhesion to albumin- and fibrinogen-coated surfaces (2001) Biomaterials, 22, pp. 827-832; Tang, L., Eaton, J.W., Fibrin(ogen) mediates acute inflammatory responses to biomaterials (1993) J Exp Med, 178, pp. 2147-2156; Liu, L., Elwing, H., Complement activation on solid surfaces as determined by C3 deposition and hemolytic consumption (1994) J Biomed Mater Res, 28, pp. 767-773; Tengvall, P., Askendal, A., Lundstrom, I., Complement activation by IgG immobilized on methylated silicon (1996) J Biomed Mater Res, 31, pp. 305-312; Källtorp, M., Askendal, A., Thomsen, P., Tengvall, P., Ellipsometric studies in vitro on kinetics of rat complement activation (1999) J Biomed Mater Res, 44, pp. 222-225; Barbosa, J.N., Barbosa, M.A., Águas, A.P., Adhesion of human leukocytes to biomaterials: An in vitro study using alkanethiolate monolayers with different chemically functionalized surfaces (2003) J Biomed Mater Res, 65, pp. 429-434
Keywords: Air-pouch model; alkane derivative; animal cell; animal experiment; animal model; Animals; article; Biomaterials; cell adhesion; Cell culture; cell density; cell surface; Cell-surface interactions; controlled study; exudate; gold; gold complex; hydrophobicity; implantation; Inflammation; Inflammatory responses; leukocyte; Leukocytes; male; material coating; Mice; Mice, Inbred BALB C; Microscopy, Electron, Scanning; mouse; neutrophil; nonhuman; polymorphonuclear cell; priority journal; Rodentia; Scanning electron microscopy; Self assembly; Self-assembled monolayers; Sulfhydryl Compounds; Surface chemistry; surface property

Mineralised membranes for bone regeneration - Mesquita, P.; Branco, R.; Afonso, A.; Vasconcelos, M.; Cavalheiro, J. (Key Engineering MaterialsKey Eng Mat, 2004)
Guided bone regeneration can be achieved using filling biomaterials and protective membranes. The aim of this work is to study a new membrane prepared from shrimp shells, without modification of the natural concave shape. The "in vitro" bioactivity was evaluated using a simulated body fluid prepared with substitution of calcium by strontium (SBR-Sr). The bioactivity behaviour was increased using a surface treatment with sodium silicate. The "in vitro" and "in vivo" tests allow to conclude that these membranes are bioactive and can induce bone growth on their surfaces.
Conference code: 62053Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Mesquita, P.; Inst. de Engenharia Biomédica, R. do Campo Alegre 823, 4150-180 Porto, PortugalReferences: Baron, M., Haas, R., Dörtbudak, O., Watzek, G., Experimentally induced peri-implantitis: A review (2000) Int J Oral Maxillofac Implants, 15, pp. 533-544;Hammerle, C.H., Jung, R.E., Feloutzis, A., A systematic review of the survival of implants in bone sites augmented with barrier membranes (guided bone regeneration) in partially edentulous patients (2002) J Clin. Periodontol., 29 (SUPPL. 3), pp. 226-231; Brunel, G., Brocard, D., Duffort, J.F., Jacquet, E., Justumus, P., Simonet, T., Benque, E., Bioabsorbable materials for guided bone regeneration prior to implant placement and 7-year followup: Report of 14 cases (2001) J Periodontol., 72 (2), pp. 257-264; Karapati, S., Hugson, A., Kugelberg, C.F., Healing following GTR treatment of bone defects distal to mandibular 2 nd molars after removal of impacted 3 rd molars (2000) J. Clin. Periodontol., 27, pp. 325-332; Simões, R., Fonseca, L., Vasconcelos, M., Afonso, A., Cavalheiro, J., Modified exoskeleton of shrimp for guided bone regeneration (2002) 17 th ESB, , Barcelona, Spain, September
Keywords: Biological membranes; biomaterial; Biomaterials; Bone; Bone Regeneration; Calcium; Ceramic materials; Deproteinization; Membrane; Mineralised membranes; Natural material; Optical microscopy; Shear strength; Sodium compounds; Strontium; Substitution reactions

Study of a Silicate Cement for Dental Applications - Pereira, S.; Cavalheiro, J.; Branco, R.; Afonso, A.; Vasconcelos, M. (Key Engineering MaterialsKey Eng Mat, 2004)
Dental cements have a wide field of applications in clinical practice. The use as a base material is a very important one in dentistry. The aim of this study is to assess some relevant properties of a silicate cement (SC) developed for dental applications, comparing it with two other cements already commercialised, a zinc phosphate cement De Trey Zinc Cement Improved® (DT) and ProRootMTA®(MTA). Their compressive strength, dimensional changes and weight variation in water after setting, according to ISO standards were compared. The mean compressive strength of DT, MTA and SC were, respectively, 134MPa, 31MPa and 46MPa. There were no statistically significant differences for the three tested cements at the various time intervals, in respect to their weight variation or dimensional changes. However, there was a little loss of weight for DT (0.15%) and for MTA (3%) and a gain of 3% for the SC. Regarding the dimensional changes, all materials undergo little expansion, more significant in the MTA and in the SC samples of 2,07% and 0,4%, respectively. The new Silicate Cement, presented enough compressive strength, low weight variation, very small dimensional changes and good adaptation to the surface of dental cavity. For these reasons this new cement could be a valuable proposal as a base material for dental applications.
Conference code: 62053Cited By (since 1996): 1Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Pereira, S.; Fac. de Medicina Dentária, Universidade do Porto, R. Dr. Manuel Pereira da Silva, 4200-393 Porto, PortugalReferences: Craig, R.G., Rovers, J.M., (2002) Restorative Dental Materials. 9th Ed., pp. 593-627. , St Louis: Mosby;Gladwin, M., Bagby, M., (2000) Clinical Aspects of Dental Materials. First Edition, pp. 81-92. , Philadelphia: Lippincott Williams & Wilkins; Leinfelder, K.F., Changing Restorative Traditions: The Use of Bases and Liners (1994) JADA, 125, pp. 65-67; Macchi, R.L., (2000) Mat. Dentales. 3 a Ed., pp. 129-135. , Buenos Aires: Edit. Médica P.americana S.A; Wise, D.L., (1995) Encyclopedic Handbook of Biomaterials and Bioengineering, pp. 1398-1411. , New York: Marcel Dekver; Gordan, V.V., Mjör, I.A., Hucke, R.D., Smith, G.E., Effect of Different Liner Treatments on Postoperative Sensivity of Amalgam Restorations (1999) Quintessence Int, 30, pp. 55-59; Me, M., Nakai, H., Effect of Immersion in Water on Linear Expansion and Strength of Three Base/Liner Materials (1995) Dent Mater, 14, pp. 70-77; Leevailoj, C., Cochran, M.A., Matis, B.A., Moore, B.K., Platt, J.A., Microleakage of Posterior Packable Resin Composites with and without Flowable Liners (2001) Oper Dent, 26, pp. 302-307; Weiner, R.S., Weiner, L.K., Kugel, G., Teaching the Use of Bases and Liners: A Survey of the North American Dental Schools (1996) JADA, 127, pp. 1640-1645; Pereira, S., Branco, R., Cavalheiro, J., Afonso, A., Vasconcelos, M., (2003) Sealing Ability of a New Dental Base Material, , Bioeng; (1991) Specification for Dental Water-based Cements, , ISO 9917 (F)
Keywords: Biocompatibility; Body fluids; Ceramic materials; ceramics; Compressive Strength; Dental cement; Dental cements; Dental prostheses; Dimensional stability; Precipitation (chemical); Scanning electron microscopy; Silicate cements; Silicates; Stainless steel; Weight variation

Adhesion of human leukocytes to biomaterials: An in vitro study using alkanethiolate monolayers with different chemically functionalized surfaces - Barbosa, J.N.; Barbosa, M.A.; Água, A.P. (Journal of Biomedical Materials Research - Part AJ. Biomed. Mater. Res. Part A, 2003)
The adhesion of human leukocytes to self-assembled monolayers of well-defined surface chemistry was investigated in vitro. Polymorphonuclear (PMN) and mononuclear leukocytes were isolated from human blood by centrifugation techniques. The effect on adhesion of cell activation produced by pre-incubation of leukocytes with phytohemagglutinin (PHA) and phorbol 12-myristate 13-acetate (PMA) was also studied. Gold substrates were modified by treatment with alkanethiols with three different terminal chemical groups: COOH, OH, and CH 3. After incubation with the two subpopulations of leukocytes, the monolayers were washed, treated with fixative, stained with a Giemsa method, and observed by light microscopy to quantify the number of attached leukocytes. Comparative quantification of the density of leukocyte adhesion to the three types of self-assembled monolayers was determined. The hydrophobic surface expressing CH 3 was found to be the one that induced the highest adhesion density of leukocytes, both of PMN and mononuclear cells. In vitro activation of both mononuclear and PMN leukocytes further increased cell adhesion to the chemically defined monolayers that were used. This enhancement was higher for PHA-activated than for PMA-stimulated mononuclear cells, whereas PMA treatment of neutrophils resulted in a higher rate of adhesion of these cells than PHA stimulation. © 2003 Wiley Periodicals, Inc.
Cited By (since 1996): 24Export Date: 21 November 2012Source: ScopusCODEN: JBMRCLanguage of Original Document: EnglishCorrespondence Address: Barbosa, J.N.; INEB-Inst. de Engenharia Biomedica, Laboratório de Biomateriais, Rua do Campo Alegre 823, 4150-180 Porto, Portugal; email: judite@ibmc.up.ptChemicals/CAS: gold, 7440-57-5; hydroxide, 14280-30-9; methane, 74-82-8; phorbol 12 acetate 13 myristate, 31365-46-5; phytohemagglutinin, 9008-97-3; phorbol 13 acetate 12 myristate, 16561-29-8; Biocompatible Materials; Gold, 7440-57-5; Phytohemagglutinins; Tetradecanoylphorbol Acetate, 16561-29-8References: Jones, D.A., Smith, C.W., McIntire, L.V., Leucocyte adhesion under flow conditions: Principles importante in tissue engineering (1996) Biomaterials, 17, pp. 337-347;Marchant, R.E., Cell adhesion and interactions with biomaterials (1984) J Adhes, 20, pp. 211-225; Tegoulia, V.A., Cooper, S.L., Leukocyte adhesion on model surfaces under flow: Effects of surface chemistry, protein adsorption, and shear rate (2000) J Biomed Mater Res, 50, pp. 291-301; Brunstedt, M.R., Anderson, J.M., Spilizewski, K.L., Marchant, R.E., Hiltner, A., In vivo leucocyte interactions on Pellethane surfaces (1990) Biomaterials, 11, pp. 370-378; Kao, W.J., Evaluation of leukocyte adhesion on polyurethanes: The effects of shear stress and blood proteins (2000) Biomaterials, 21, pp. 2295-2303; Lim, F., Cooper, S.L., Effect of sulphonate incorporation on in vitro leucocyte adhesion to polyuretanes (1995) Biomaterials, 16, pp. 457-466; Tomczok, J., Sliwa-Tomczok, W., Klein, C.L., Van Kooten, T.G., Kirkpatrick, C.J., Biomaterial-induced alterations of human neutrophils under fluid shear stress: Scanning electron microscopical study in vitro (1996) Biomaterials, 17, pp. 1359-1367; Yun, J.K., DeFife, K., Colton, E., Stack, S., Azeez, A., Cahalan, L., Verhoeven, M., Anderson, J.M., Human monocyte/macrophage adhesion and cytokine production on surface-modified poly(tetrafluoroethylene/hexafluoropropylene) polymers with and without protein preadsorption (1995) J Biomed Mater Res, 29, pp. 257-268; Mrksich, M., Whitesides, G.M., Interactions of SAMs with proteins (1996) Annu Rev Biophys Biomol Struct, 25, pp. 55-57; Ulman, A., Formation and structure of self-assembled monolayers (1996) Chem Rev, 96, pp. 1533-1554; Mrkisich, M., Tailored substrates for studies of attached cell culture (1998) Cell Mol Life Sci, 54, pp. 653-662; Kane, R.S., Takayama, S., Ostuni, E., Ingber, D.E., Whitesides, G.M., Patterning proteins and cells using soft lithography (1999) Biomaterials, 20, pp. 2363-2376; Mrksich, M., Using self-assembled monolayers to understand the biomaterials interface (1997) Curr Opin Colloid Int Sci, 2, pp. 83-88; Margel, S., Vogler, E.A., Firment, L., Watt, T., Haynie, S., Sogah, D.Y., Peptide, protein, and cellular interactions with self-assembled monolayer model surfaces (1993) J Biomed Mater Res, 27, pp. 1463-1476; Prime, K.L., Whitesides, G.M., Self assembled organic monolayers model systems for studying the adsorption of proteins at surfaces (1991) Science, 252, pp. 1164-1167; Lopez, G.P., Albers, M.W., Schreiber, S.L., Carroll, R., Peralta, E., Whitesides, G.M., Convenient methods for patterning the adhesion of mammalian cells to surfaces using self-assembled monolayers of alkane thiolates on gold (1993) J Am Chem Soc, 115, pp. 5877-5878; Shinghvi, R., Kumar, A., Lopez, G.P., Stephanopoulos, G.N., Wang, D.I.C., Whitesides, G.M., Ingber, D.E., Engineering cell shape and function (1994) Science, 264, pp. 696-698; Pan, S., Castner, D.G., Ratner, B.D., Multitechnique surface characterization of derivatization efficiencies for hydroxyl-terminated self-assembled monolayers (1998) Langmuir, 14, pp. 3545-3550; Lin, J., Chuang, W., Synthesis, surface characterization, and platelet reactivity evaluation for the self-assembled monolayer of alkanethiol with sulfonic acid functionality (2000) J Biomed Mater Res, 51, pp. 413-423; Lindblad, M., Lestelius, M., Johansson, A., Tengvall, P., Thomsen, P., Cell and soft tissue interactions with methyl- and hydroxyl-terminated alkane thiols on gold surfaces (1997) Biomaterials, 18, pp. 1059-1068; Baker, L.C., Davis, W.C., Autieri, J., Watach, M.J., Yamazaki, K., Litwak, P., Wagner, W.R., Flow cytometric assays to detect platelet activation and aggregation in device-implanted calves (1998) J Biomed Mater Res, 41, pp. 312-321; English, D., Andersen, B.R., Single-step separation of red blood cells. Granulocytes and mononuclear leukocytes on discontinuous density gradient of ficoll-hypaque (1974) J Immunol Methods, 5, pp. 249-253; Nygren, H., Hrustic, E., Karlsson, C., Öster, L., Respiratory burst response of peritoneal leukocytes adhering to titanium and stainless steel (2001) J Biomed Mater Res, 57, pp. 238-247; Gorbet, M.B., Yeo, E.L., Sefton, M.V., Flow cytometric study of in vitro neutrophil activation by biomaterials (1999) J Biomed Mater Res, 44, pp. 289-297; Källtrorp, M., Askendal, A., Thompsen, P., Tengvall, P., Inflammatory cell recruitment, distribution, and chemiluminescence response at IgG precoated- and thiol functionalized gold surfaces (1999) J Biomed Mater Res, 47, pp. 251-259; Mahiout, A., Courtney, J.M., Effect of dialyser membranes on extracellular and intracellular granulocyte and monocyte activation in ex vivo pyrogen-free conditions (1994) Biomaterials, 15, pp. 969-980; Davis, R.G., Goodman, S.B., Smith, R.L., Lerman, J.A., Williams III, R.J., The effects of bone cement powder on human adherent monocytes/ macrophages in vitro (1993) J Biomed Mater Res, 27, pp. 1039-1046; Gery, I., Gerhon, R.K., Waskman, B., Potentiation of the T lymphocyte response to mitogens. I. The responding cell (1972) J Exp Med, 136, pp. 128-134; Peters, S.P., Cerasoli Jr., F., Albertine, K.H., Gee, M.H., Berd, D., Ishihara, Y., "Autoregulation" of human neutrophil activation in vitro: Regulation of phorbol myristate acetate-induced neutrophil activation by cell density (1990) J Leukocyte Biol, 47, pp. 457-474; Esaguy, N., Águas, A.P., Vilanova, M., Silva, M.T., Activation of human neutrophils by phorbol ester decreases the cytoplasm compactness and the lactoferrin content of the granulocytes (1991) J Leukocyte Biol, 50, pp. 444-452; Collins, D.P., Cytokine and cytokine receptor expression as a biological indicator of immune activation: Important considerations in the development of in vitro model systems (2000) J Immunol Methods, 243, pp. 125-145; Ruoslahti, E., Integrin signaling and matrix assembly (1996) Tumor Biol, 17, pp. 117-128; Aoudjit, F., Vuori, K., Engagement of the α2β1 integrin inhibits Fas ligand expression and activation-induced cell death in T cells in a focal adhesion kinase-dependent manner (2000) Blood, 95, pp. 2044-2051; Lehr, H.A., Krombach, F., Munzing, S., Bodlaj, R., Glaubitt, S.I., Seiffge, D., Hubner, C., Messmer, K., In vitro effects of oxidized low density lipoprotein on CD11b/CD18 and L-selectin presentation on neutrophils and monocytes with relevance for the in vivo situation (1995) Am J Pathol, 146, pp. 218-227; Kansas, G.S., Tedder, T.F., Transmembrane signals generated through MHC class II, CD19, CD20, CD39, and CD40 antigens induce LFA-1-dependent adhesion in human B cells through a tyrosine kinase-dependent pathway (1991) J Immunol, 147, pp. 4094-4102; Damle, N.K., Eberhardt, C., Van Der Vieren, M., Direct interactions with primed CD4+ CD45R0+ memory T lymphocytes induces expression of endothelial leukocyte adhesion molecule-1 and vascular cell adhesion molecule-1 on the surface of vascular endothelial cells (1991) Eur J Immunol, 21, pp. 2915-2923; Murata, S., Tanaka, T., Miysaka, M., Lymphocyte binding to MAd-CAM-1 via α4β7 integrin activates a signal transduction pathway involving tyrosine phosphorylation of paxillin and p105 Cas-L (2002) Immunol Lett, 81, pp. 223-228; Roth, S.J., Carr, M.W., Rose, S.S., Springer, T.A., Characterization of transendothelial chemotaxis of T lymphocytes (1995) J Immunol Methods, 188, pp. 97-116; Aziz, K.E., Wakefield, D., In vivo and in vitro expression of adhesion molecules by peripheral blood lymphocytes from patients with primary Sjogren's syndrome: Culture-associated enhancement of LECAM-1 and CD4 (1995) Rheumatol Int, 15, pp. 69-74; Tengvall, P., Lundstrom, I., Liedberg, B., Protein adsorption studies on model organic surfaces: An ellipsometric and infrared spectroscopic approach (1998) Biomaterials, 19, pp. 407-422; Tidwell, C.D., Ertel, S.I., Ratner, B.D., Tarasevich, B.J., Atre, S., Allara, D.L., Endothelial cell growth and protein adsorption on terminally functionalised self-assembled monolayers of alkanethiols on gold (1997) Langmuir, 13, pp. 3404-3413; Tsai, M., Lin, J., Surface characterization and platelet adhesion studies of self-assembled monolayer with phosphonate ester and phosphonic acid functionalities (2001) J Biomed Mater Res, 55, pp. 554-565; Franco, M., Nealy, P.F., Campbell, S., Teixeira, A.I., Murphy, C.J., Adhesion and proliferation of corneal epithelial cells on self-assembled monolayers (2000) J Biomed Mater Res, 52, pp. 261-269; Scotchford, C.A., Gilmore, C.P., Cooper, E., Leggett, G.J., Downes, S., Protein adsorption and human osteoblast-like cell attachment and growth on alkylthiol on gold self-assembled monolayers (2002) J Biomed Mater Res, 59, pp. 84-99; Silin, V., Weetall, H., Vanderah, D.J., SPR studies of the non-specific adsorption kinetics of human IgG and BSA on gold surfaces modified by self-assembled monolayers (SAMs) (1997) J Colloid Interface Sci, 185, pp. 94-103
Keywords: alkane derivative; article; Biocompatible Materials; biomaterial; Biomaterials; Blood; carboxyl group; cell adhesion; cell interaction; cell isolation; cell subpopulation; cell surface; Cell-surface interactions; Cells; Centrifugation; controlled study; drug effect; Giemsa stain; gold; human; human cell; Humans; hydrophobicity; hydroxide; in vitro study; Incubation; lectin; Lectins; leukocyte; Leukocyte activation; leukocyte adherence; Leukocyte adhesion; Leukocytes; Leukocytes, Mononuclear; materials testing; methane; microscopy; Monolayers; mononuclear cell; neutrophil; Neutrophils; Optical microscopy; phorbol 12 acetate 13 myristate; phorbol 13 acetate 12 myristate; physiology; phytohemagglutinin; Phytohemagglutinins; polymorphonuclear cell; Self-assembled monolayers; Surface Properties; surface property; Tetradecanoylphorbol Acetate; thiolacid

Corrosion behaviour of commercially pure titanium shot blasted with different materials and sizes of shot particles for dental implant applications - Aparicio, C.; Javier Gil, F.; Fonseca, C.; Barbosa, M.; Planell, J.A. (BiomaterialsBiomaterials, 2003)
It is well known that the osseointegration of the commercially pure titanium (c.p. Ti) dental implant is improved when the metal is shot blasted in order to increase its surface roughness. This roughness is colonised by bone, which improves implant fixation. However, shot blasting also changes the chemical composition of the implant surface because some shot particles remain adhered on the metal. The c.p. Ti surfaces shot blasted with different materials and sizes of shot particles were tested in order to determine their topographical features (surface roughness, real surface area and the percentage of surface covered by the adhered shot particles) and electrochemical behaviour (open circuit potential, electrochemical impedance spectroscopy and cyclic polarisation). The results demonstrate that the increased surface area of the material because of the increasing surface roughness is not the only cause for differences found in the electrochemical behaviour and corrosion resistance of the blasted c.p. Ti. Among other possible causes, those differences may be attributed to the compressive residual surface stresses induced by shot blasting. All the materials tested have an adequate corrosion and electrochemical behaviour in terms of its possible use as dental implant material. © 2002 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 77Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(02)00314-9Language of Original Document: EnglishCorrespondence Address: Aparicio, C.; Res. Center in Biomed. Eng. (CREB), Department of Materials Science, Universitat Politecnica de Catalunya, Av. Diagonal 647, 08028 Barcelona, Spain; email: conrado.aparicio@upc.esChemicals/CAS: Dental Implants; Titanium, 7440-32-6References: Brånemark, P.I., Hansson, B.O., Adell, R., Breine, U., Lindström, J., Hallen, O., Öhman, A., Osseointegrated implants in the treatment of edentulous jaw experience from a 10-year period (1977) Scand J Reconstr Surg, 16 (SUPPL.), pp. 1-132;Lemons, J.E., Application of materials in medicine and dentistry. Dental implants (1996) Biomaterials Science: An Introduction to Materials in Medicine, pp. 308-318. , B.D. Ratner, A.S. Hoffman, F.J. Schoen, & J.E. Lemons. San Diego: Academic Press; Pourbaix, M., Electrochemical corrosion of metallic biomaterials (1984) Biomaterials, 5, pp. 122-134; Bardos, D.I., Titanium and titanium alloys (1990) Encyclopaedia of Medical and Dental Materials, pp. 360-365. , D. William. Oxford: Pergamon Press; Boyer, R., Welsh, G., Colling, E.W., (1994) Materials Properties Handbook: Titanium Alloys, pp. 181-219. , Ohio: ASM International; Kasemo, B., Lausmaa, J., Surface science aspects on inorganic biomaterials (1986) CRC Crit Rev Biocompatibilty, 4, pp. 335-380; Tengvall, P., Lundtröm, I., Physico-chemical considerations of titanium as a biomaterial (1992) Biomaterials, 9, pp. 115-134; Albrektsson, T., Brånemark, P.I., Hansson, B.O., Lindström, J., Osseointegrated titanium implants (1981) Acta Orthop Scand, 52, pp. 155-170; Thomas, K.A., Cook, S., An evaluation of variables influencing implant fixation by direct bone apposition (1985) J Biomed Mater Res, 19, pp. 875-901; Wennerberg, A., (1996) On Surface Roughness and Implant Incorporation, , Ph.D. thesis, Göteborg: University of Göteborg; Bowers, K.T., Keller, J.C., Randolph, B.A., Wick, D.G., Michaels, C.M., Optimization of surface micromorphology from enhanced osteoblast response in vitro (1992) Int J Oral Maxillofac Implants, 7, pp. 302-310; Groessner-Schereider, B., Tuan, R.S., Enhanced extracellular matrix production and mineralization by osteoblasts cultured on titanium surfaces in vitro (1992) J Cell Sci, 101, pp. 209-217; Schwartz, Z., Boyan, B.D., Underlaying mechanisms at the bone biomaterial interface (1994) J Cell Biochem, 56, pp. 340-347; Boyan, B.D., Hummert, T.W., Kieswetter, K., Schraub, D., Dean, D.D., Schwartz, Z., Effect of titanium surface characteristics on chondrocytes and osteoblasts in vitro (1995) Scanning Electron Microsc (Cells and Materials), 5, pp. 323-335; Martin, J.Y., Schwartz, Z., Hummert, T.W., Schraub, D.M., Simpson, J., Lankford, J., Dean, D.D., Boyan, B.D., Effect of titanium surface roughness on proliferation, differentiation and protein synthesis of human osteoblast-like cells (MG63) (1995) J Biomed Mater Res, 29, pp. 389-401; Ong, J.L., Prince, C.W., Raikar, G.N., Lucas, L.C., Effect of surface topography of titanium on surface chemistry and cellular response (1996) Implant Dent, 5, pp. 83-88; Deligianni, D.D., Katsal, N., Ladas, S., Sotiropoulou, D., Amedee, J., Missirlis, Y.F., Effect of surface roughness of the titanium alloy Ti-6Al-4V on human bone marrow cell response and on protein adsorption (2001) Biomaterials, 22, pp. 1241-1251; Schwartz, Z., Lohmann, C.H., Sisk, M., Cochran, D.L., Sylvia, V.L., Simpson, J., Dean, D.D., Boyan, B.D., Local factor production by MG63 ostoblast-like cells in response to surface roughness and 1,25-(OH) 2D 3 is mediated via protein kinase C- and protein kinase A-dependent pathways (2001) Biomaterials, 22, pp. 731-741; Predecki, P., Stephan, J.E., Auslander, B.A., Mooney, V.L., Kirkland, K., Kinetics of bone growth into cylindrical channels in aluminium oxide and titanium (1972) J Biomed Mater Res, 6, pp. 375-400; Buser, D., Schenk, R.K., Steinemann, S., Fiorelini, J.P., Fox, C.H., Stich, H., Influence of surface characteristics on bone integration of titanium implants. A histomorphometric study in miniature pigs (1991) J Biomed Mater Res, 25, pp. 889-902; Ericsson, I., Johansson, C., Bystedt, H., Norton, M.R., A histomorphometric evaluation of bone-to-implant contact on machined-prepared roughened titanium dental implants (1994) Clin Oral Implant Res, 5, pp. 202-206; Feighan, J.E., Goldberg, V.M., Davy, D., Parr, J.A., Stevenson, S., The influence of surface-blasting on the incorporation of titanium alloy implants in a rabit intramedullary model (1995) J Bone Jt Surg Am, 77, pp. 1380-1395; Wennerberg, A., Albrektsson, T., Andersson, B., An animal study of c.p. titanium screws with different surface topographies (1995) J Mater Sci: Mater Med, 6, pp. 302-309; Wong, M., Eulenberger, J., Schenk, R., Hunziker, E., Effect of surface topology on the osseointegration of implant materials in trabecular bone (1995) J Biomed Mater Res, 29, pp. 1567-1575; Wennerberg, A., Albrektsson, T., Johansson, C., Andersson, B., Experimental study of turned and grit-blasted screw-shaped implants with special emphasis on effects of blasting material and surface topography (1996) Biomaterials, 17, pp. 15-22; Cochran, D.L., Schenk, R.K., Lussi, A., Higginbottom, F.L., Buser, D., Bone response to unloaded and loaded titanium implants with a sandblasted and acid etched surface: A histometric study in the canine mandible (1998) J Biomed Mater Res, 40, pp. 1-11; Piatelli, A., Manzon, L., Scarano, A., Paolantonio, M., Piatelli, M., Histologic and histomorphometric analysis of the bone response to machined and sandblasted titanium implants: An experimental study in rabbits (1998) Int J Oral Maxillofac Implants, 13, pp. 805-810; Svehla, M., Morberg, P., Zicat, B., Bruce, W., Sonnabend, D., Walsh, W.R., Morphometric and mechanical evaluation of titanium implant integration: Comparison of five surface structures (2000) J Biomed Mater Res, 51, pp. 15-22; Gotfredsen, K., Nimb, L., Hjorting-Hansen, E., Jensen, J.S., Holmen, A., Histomorphometric and removal torque analysis for TiO 2-blasted titanium implants (1994) Clin Oral Implant Res, 5, pp. 202-206; Jones, F., Teeth and bones: Applications of surface science to dental materials and related biomaterials (2001) Surf Sci Rep, 42, pp. 75-205; Naji, A., Harnad, M.F., Cytocompatibility of two coating materials, amorphous alumina and silicon carbide, using human differentiated cell cultures (1991) Biomaterials, 12, pp. 690-694; Darvell, B.W., Samman, N., Luk, W.K., Clark, K.F., Tideman, H., Contamination of titanium casting by aluminium oxide blasting (1995) J Dent, 23, pp. 319-322; Placko, H.E., Mishra, S., Weimer, J.J., Lucas, L.C., Surface Characterization of titanium-based implant materials (2000) Int J Oral Maxillofac Implants, 15, pp. 355-363; Orsini, G., Assenza, B., Scarano, A., Piatelli, M., Piatelli, A., Surface analysis of machined versus sandblasted and acid-etched titanium implants (2000) Int J Oral Maxillofac Implants, 15, pp. 779-784; Gross, U., Strunz, V., The interface of various glasses and glass ceramics with a bony implantation bed (1985) J Biomed Mater Res, 19, pp. 251-271; Aparicio, C., Gil, F.J., Peraire, C., Padrós, A., Planell, J.A., Effect of size and material of the shot peening particles on adhesion and differentiation of osteoblast-like cell cultures on commercially pure titanium (1998) North Sea Biomaterials 1998 Proceedings, p. 137. , The Hague; Fontana, M.G., Green, N.D., (1978) Corrosion Engineering: Mc Graw Hill Series in Materials Science and Engineering, , USA: McGraw-Hill; Standard practice for laboratory immersion corrosion testing metals (1992) 1992 Annual Book of ASTM Standards, pp. 102-109. , vol. 03.02. Philadelphia: ASTM; Boukamp, B.A., (1989) Equivalent Circuit (EQUIVCRTPAS). User's Manual, , Enschede: University of Twente; Standard test method for conducting cyclic potentiodynamic polarization measurements for localized corrosion susceptibility of iron-nickel, or cobalt-based alloys (1992) 1992 Annual Book of ASTM Standards, pp. 231-235. , vol. 03.02. Philadelphia: ASTM; (1984) Norme FEPA des Grains de Corindon Electrofondu et de Carbure de Silicium Pour Abrasifs Agglomeres, , Paris: Fedération Européenne des Fabricants de Produits Abrasifs; Bohn, P., Qualitaty control of shot media by sieve analysis (1999) Shot Peener, 13, pp. 6-9; Mehelich, C.S., Van Kuiken, L., Woelfel, M.M., Shot peening (1995) ASM Metals Handbook. Vol. 5: Surface Engineering, 5, pp. 138-149. , USA: ASM International; Udupa, G., Singaperumal, M., Sirohi, R.S., Kothiyal, M.P., Characterization of surface topography by confocal microscopy: II. The micro and macro surface irregularities (2000) Meas Sci Technol, 11, pp. 315-329; Arnell, R.D., Davie, P.B., Halling, J., Whomes, T.L., (1991) Tribology: Principles and Design Applications, , London: Mac Millan; Udupa, G., Singaperumal, M., Sirohi, R.S., Kothiyal, M.P., Characterization of surface topography by confocal microscopy: I. Principles and the measurement system (2000) Meas Sci Technol, 11, pp. 305-314; Solar, R.J., Pollack, S.R., Korostoff, E., In vitro corrosion testing of titanium surgical implant alloys: An approach to understanding titanium release from implants (1979) J Biomed Mater Res, 13, pp. 217-250; Hoar, T.P., Mears, D.C., Corrosion resistant alloys in chloride solutions, materials for surgical implants (1966) Proc Royal Soc London Ser A, 294, pp. 486-510; Gonzalez, J.E.G., Mirza-Rosca, J.C., Study of the corrosion behaviour of titanium and some of its alloys for biomedical and dental implant applications (1999) J Electroanal Chem, 471, pp. 109-115; McDonald, J.R., (1987) Impedance Spectroscopy, , New York: Wiley; Aziz-Kerrzo, M., Conroy, K.G., Fenelson, A.M., Farrell, S.T., Breslin, C.B., Electrochemical studies on the stability and corrosion resistance of titanium-based implant materials (2001) Biomaterials, 22, pp. 1531-1539; Cai, Z., Nakajima, H., Woldu, M., Berglund, A., Bergman, M., Okabe, T., In vitro corrosion resistance of titanium made using different fabrication methods (1999) Biomaterials, 20, pp. 183-190; Kobayashi, M., Matsui, T., Murakami, Y., Mechanism of creation of compressive residual stresses by shot peening (1998) Int J Fatigue, 20, pp. 351-357; Prevey, P.S., X-ray diffraction characterization of residual stresses produced by shot peening (2001) Shot Peener, 15, pp. 4-8; Mueller, H.J., Greener, E.H., Polarization studies of surgical materials in Ringer's solution (1970) J Biomed Mater Res, 4, pp. 29-41; Speck, K.M., Fraker, A.C., Anodic polarization behavior of Ti-Ni and Ti-6Al-4V in simulated physiological solution (1980) J Dent Res, 59, pp. 1590-1595; Sousa, S.R., Barbosa, M.A., Corrosion resistance of titanium cp in saline physiological solutions with calcium phosphate and proteins (1993) Biomaterials, 14, pp. 287-294; Khan, M.A., Williams, R.L., Williams, D.F., In-vitro corrosion and wear of titanium alloys in the biological environment (1996) Biomaterials, 17, pp. 2117-2126; Ewers, G.J., Greener, E.H., The electrochemical activity of the oral cavity - A new approach (1985) J Oral Rehab, 12, pp. 469-476
Keywords: article; Blast finishing; chemical composition; chemistry; Corrosion; Dental implant; Dental Implants; Dental prostheses; Electric Potential; Electrochemical impedance spectroscopy; electrochemistry; impedance; materials testing; Particle Size; Polarization; priority journal; Shot blasting; Spectroscopy; stress; Surface roughness; Surface topography; Titanium; tooth implantation

Detection and validation of lung field contours on chest radiographs - Mendonça, A.M.; Alves Da Silva, J.; Campilho, A. (Proceedings of the IASTED International Conference on Biomedical EngineeringProc. IASTED Internat. Conf. Biomed. Eng., 2003)
The purpose of the research herein presented is the automatic detection of lung boundaries in posterior-anterior digital chest radiographs. The precise location of the two lungs is important in a computer-aided diagnosis system as it allows the reduction of the region under analysis, decreasing the computation time and facilitating data compression. Furthermore, it allows the delimitation of the search area, easing the selective tuning of the abnormalities detection algorithms. The results produced by the automatic method were validated by comparison with manual contours traced by an experienced radiologist. For this particular purpose, two programs with friendly interfaces were developed. The achieved comparison results demonstrate the good performance of the automatic method.
Conference code: 63063Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Mendonça, A.M.; INEB, Inst. de Engenharia Biomédica, Campus da FEUP, Rua Dr. Roberto Frias, s/n, 4200-465 Porto, Portugal; email: amendon@fe.up.ptReferences: Tsujii, O., Freedman, M., Mun, S., Automated segmentation of anatomic regions in chest radiographs using an adaptive-sized hybrid neural network (1998) Medical Physics, 25, pp. 998-1007;Armato III, S., Giger, M., MacMahon, H., Computerized detection of abnormal asymetry in digital lateral chest radiographs (1994) Medical Physics, 21, pp. 1761-1768; Armato III, S., Giger, M., Ashizawa, K., MacMahon, H., Automated lung segmentation in digital lateral chest radiographs (1998) Medical Physics, 25, pp. 1507-1520; Carrascal, F., Carreira, J., Souto, M., Automatic calculation of total lung capacity from automatically traced lung boundaries in posterior-anterior and lateral digital chest radiographs (1998) Medical Physics, 25, pp. 1118-1131; Ginneken, B., Romeny, B., Automatic segmentation of lung fields in chest radiographs (2000) Medical Physics, 27, pp. 2445-2455; Li, L., Zheng, Y., Kallergi, M., Clark, R., Improved method for automatic identification of lung regions on chest radiographs (2001) Academic Radiology, 8, pp. 629-638; Monteiro, M., Mendonça, A.M., Campilho, A., Lung field detection on chest radiographs (2002) Proceedings of VIIP02, IASTED International Conference on Visualization, Imaging and Image Processing, pp. 367-372. , J. Villanueva (ed): Spain Sponsors: IASTED
Keywords: Algorithms; automation; Biological organs; Chest radiographs; Computational time; Computer aided diagnosis; Computer-aided diagnosis; Data compression; Image analysis; Medical image processing; Medical imaging; Radiography; Regions of interest (ROI)

Development of foetal and neonatal simulators at the University of Porto - van Meurs, W.L.; Sá Couto, P.M.; Sá Couto, C.D.; Bernardes, J.F.; Ayres-de-Campos, D. (Medical Education, SupplementMed. Educ. Suppl., 2003)
Background: Human error can be expected to play a significant role in adverse outcomes in perinatal acute care. In acute care of the adult, simulator based training is recommended and used to improve patient safety. Aims: Our general goal is to develop model-driven foetal and neonatal educational simulators and curricula. The specific objectives of this paper are to introduce the reader to the perinatal acute care context and simulator design considerations, as well as to give initial results and describe ongoing developments. A brief description of adult simulators and simulation engines is followed by a more detailed description of a foetal distress simulator (FDS) and of models for a neonatal simulator developed at the University of Porto. Ongoing developments involve the modelling of foetal baroreflexes, the effect of uterine contractions, and an adapted method for estimating foetal heart rate variability parameters. Results: We present FDS simulation results reflecting the changes in oxygen supply to the foetus and the foetal heart rate in response to a reduction in uterine blood flow. We also present a structural diagram of a model for the educational simulation of congenital heart disease and preliminary simulation results reflecting a patent ductus arteriosus. Conclusion: We expect that, after initial clinical and educational validation, the presented models and simulators will play a role in simulator-based educational programmes contributing to increased perinatal safety.
Cited By (since 1996): 6Export Date: 21 November 2012Source: ScopusCODEN: MESECPubMed ID: 14641636Language of Original Document: EnglishCorrespondence Address: Van Meurs, W.L.; INEB - Inst. de Engenharia Biomedica, Lab. de Sinal e Imagem Biomedica, Edificio I-Poente, Rua Roberto Prias, s/n, 4200-465 Porto, Portugal; email: wvanmeurs@ineb.up.ptChemicals/CAS: oxygen, 7782-44-7References: Kohn, L.T., Corrigan, J.M., Donaldson, M.S., (2000) To Err Is Human, Building a Safer Health Care System, , Washington, DC: National Academic Press;Denson, J.S., Abrahamson, S., A computer-controlled patient simulator (1969) JAMA, 208, pp. 504-508; Gaba, D.M., DeAnda, A., A comprehensive anesthesia simulation environment. Re-creating the operating room for research and training (1988) Anesthesiology, 69, pp. 387-394; Good, M.L., Gravenstein, J.S., Anesthesia simulators and training devices (1989) Int Anesthesiol Clin, 27, pp. 161-168; Gaba, D., Howard, S., Fish, K., Smith, B., Sowb, Y., Simulation-based training in anesthesia crisis resource management (ACRM): A decade of experience (2001) Simulation Gaming, 32, pp. 175-193; Gordon, J.A., 'Practicing' medicine without risk: Students' and educators' responses to high-fidelity patient simulation (2001) Acad Med, 76, pp. 469-472; Ma, O., Simulation saves lives (2001) Newsletter of the American Society of Anesthesiologists, , Park Ridge: American Society of Anesthesiologists; October; Van Meurs, W.L., Good, M.L., Lampotang, S., Functional anatomy of full-scale patient simulators (1997) J Clin Monit, 13, pp. 317-324; Van Meurs, W.L., Nikkelen, E., Good, M.L., Pharmacokinetic-pharmacodynamic model for educational simulations (1998) IEEE Trans Biomed Eng, 45, pp. 582-590; Öhrn, M.A.K., Van Oostrom, J.H., Van Meurs, W.L., A comparison of traditional textbook and interactive computer learning of neuromuscular block (1997) Anesth Analg, 84, pp. 657-661; Euliano, T.Y., Caton, D., Van Meurs, W.L., Good, M.L., Modeling obstetric cardiovascular physiology on a full-scale patient simulator (1997) J Clin Monit, 13, pp. 293-297; Sá Couto, P.M., Van Meurs, W.L., Bernardes, J.F., Marques De Sá, J.P., Goodwin, J.A., Mathematical model for educational simulation of the oxygen delivery to the fetus (2002) Cont Eng Prac, 10, pp. 59-66; Sá Couto, P.M., Van Meurs, W.L., Bernardes, J.F., Marques De Sá, J.P., Goodwin, J.A., Combined model-driven and rule-based approach for educational simulation of fetal heart rate (2002) BIOSIGNAL 2002. Proceedings of the 16th Biennial International Conference of the European Association for Speech, Signal and Image Processing (EURASIP), 26-28 June 2002, Brno, Czech Republic, pp. 400-402. , Jan J, Kozumplík J, Provazník I, eds. Brno: Vutium Press; Itskovitz, J., LaGamma, E.F., Rudolph, A.M., Heart rate and blood pressure responses to umbilical cord compression in fetal lambs with special references to the mechanism of variable deceleration (1983) Am J Obstet Gynecol, 147, pp. 451-457; Lee, S.T., Hon, E.H., Fetal hemodynamic response to umbilical cord compression (1963) J Obstet Gynecol, 22, pp. 553-562; Goodlin, R.C., Lowe, E.W., A functional umbilical cord occlusion heart rate pattern - The significance of overshoot (1974) Obstet Gynecol, 43, pp. 22-30; Scheffs, J., Vasicka, A., Li, C., Solomon, N., Siler, W., Uterine blood flow during labor (1971) Obstet Gynecol, 38, pp. 15-24; Brotanek, V., Hendricks, C.H., Yoshida, T., Importance of changes in uterine blood flow in initiation of labor (1969) Am J Obstet Gynecol, 105, pp. 535-546; Butler, L.A., Longo, L.D., Power, G.G., Placental blood flows and oxygen transfer during uterine contractions: A mathematical model (1976) J Theor Biol, 61, pp. 81-95; Felgueiras, C., Marques De Sá, J.P., Bernardes, J., Gama, S., Classification of foetal heart rate sequences based on fractal features (1998) Med Biol Eng Comput, 36, pp. 197-201; Sá Couto, C.D., Van Meurs, W.L., Goodwin, J.A., Graphical and mathematical representation of congenital heart disease (2002) Proceedings of the SESAM Annual Meeting, 10-11 May 2002; Centro de Entrenamiento en Situaciones Críticas, Santander, Spain, p. 18; Beneken, J.E.W., (1965) A Mathematical Approach to Cardiovascular Function: The Uncontrolled Human System, , PhD dissertation. Utrecht, The Netherlands: Rijksuniversiteit Utrecht; Huikeshoven, F., Coleman, T.G., Jongsma, H.W., Mathematical model of the fetal cardiovascular system: The uncontrolled case (1980) Am J Physiol, 239, pp. R317-25; Klaus, M.H., Fanaroff, A.A., (2001) Care of the High-Risk Neonate, 5th Edn., , Philadelphia: WB Saunders
Keywords: article; audiovisual equipment; blackstarPatient simulation; clinical competence; Clinical competence/blackstarstandards/economics; competence; Curriculum; Education, Medical, Undergraduate; Education, medical, undergraduate/blackstarmethods; Equipment Safety; fetus distress; human; Humans; Manikins; medical education; model; oxygen; Patient Simulation; perinatal care; Perinatal care/ blackstarstandards/methods; Portugal; safety; simulator; training

A probabilistic model for the cooperative modular neural network - Alexandre, L.A.; Campilho, A.; Kamel, M. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics)Lect. Notes Comput. Sci., 2003)
This paper presents a model for the probability of correct classification for the Cooperative Modular Neural Network (CMNN). The model enables the estimation of the performance of the CMNN using parameters obtained from the data set. The performance estimates for the experiments presented are quite accurate (less than 1% relative difference). We compare the CMNN with a multi-layer perceptron with equal number of weights and conclude that the CMNN is preferred for complex problems. We also investigate the error introduced by one of the CMNN voting strategies. © Springer-Verlag Berlin Heidelberg 2003.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Alexandre, L.A.; Departamento de Informática, Universidade da Beira Interior, Covilhã, Portugal; email: lfbaa@di.ubi.ptReferences: Auda, G., Kamel, M., Modular neural network classifiers: A comparative study (1998) J. Intel. Robotic Systems, pp. 117-129;De Bollivier, M., Gallinari, P., Thiria, S., Cooperation of neural nets and task decomposition (1991) Int. Joint Conf. on Neural Networks, 2, pp. 573-576. , Seattle, USA; Jacobs, R., Jordan, M., Nowlan, S., Hinton, G., Adaptive mixtures of local experts (1991) Neural Computation, pp. 79-87; Jacobs, R., Peng, F., Tanner, M., A bayesian approach to model selection in hierarchical mixtures-of-experts architectures (1997) Neural Networks, 10, pp. 231-241; Wanas, N., Kamel, M., Auda, G., Karray, F., Feature-based decision aggregation in modular neural network classifiers (1999) Pattern Recognition Letters, 20, pp. 1353-1359; Alexandre, L., Campilho, A., Kamel, M., Combining independent and unbiased classifiers using weighted average (2000) Proceedings of the 15th International Conference on Pattern Recognition, 2, pp. 495-498. , Barcelona, Spain, IEEE Press; Alexandre, L., Campilho, A., Kamel, M., On combining classifiers using sum and product rules (2001) Pattern Recognition Letters, 22, pp. 1283-1289; Kittler, J., Hatef, M., Duin, R., Matas, J., On combining classifiers (1998) IEEE Trans. PAMI, 20, pp. 226-239; Auda, G., Kamel, M., CMNN: Cooperative modular neural networks for pattern recognition (1997) Pattern Recognition Letters, 18, pp. 1391-1398; Auda, G., Kamel, M., Raafat, H., Voting schemes for cooperative neural network classifiers (1995) IEEE Int. Conference on Neural Networks, 3, pp. 1240-1243. , Australia

Densification route and mechanical properties of Si 3N 4-bioglass biocomposites - Amaral, M.; Lopes, M.A.; Silva, R.F.; Santos, J.D. (BiomaterialsBiomaterials, 2002)
The processing route and the final microstructural and mechanical characteristics of a novel biomaterial composite are described. This new material is composed of 70 wt% Si 3N 4 ceramic phase and 30 wt% bioglass, the later performing as a liquid sintering aid system and simultaneously providing bioactivity characteristics to the composite. The conditions for fabrication of an almost fully dense material (∼98% of relative density) were pursued. Optimised parameters were 1350°C-40min-30 MPa by hot-pressing technique. The very fast densification rate of the process avoided the crystallisation of the bioglass intergranular phase and therefore its intrinsic properties were maintained. Also, the large amount of glassy phase assured the densification by liquid phase assisted grain rearrangement without Si 3N 4 phase transformation. The final mechanical properties of the Si 3N 4-bioglass were as follows: fracture toughness, K IC = 4.4 MPa m 1/2; Vickers hardness, H V = 10.3 GPa; Young's modulus, E = 197 GPa; bending strength, σ R = 383 MPa; Weibull modulus, m = 8.3. These values provide an attractive set of properties among other bioactive materials, namely by upgrading the main drawback of bioceramics and bioglasses for high-load medical applications, which is the lack of satisfactory fracture toughness. © 2001 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 33Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(01)00194-6PubMed ID: 11771704Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Secção de Materiais, Fac. Eng. da Univ. do Porto (FEUP), Universidade do Porto, Rua Roberto Frias, 4200-465 Porto Cedex, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: Biocompatible Materials; Bioglass; Ceramics; Composite Resins; Silicon Compounds; silicon nitride, 12033-89-5Tradenames: BioglassReferences: Kue, R., Sohrabi, A., Nagle, D., Frondonza, C., Hungerford, D., Enhanced proliferation and osteacalcin production by human osteablast-like cells on silicon nitride ceramic discs (1999) Biomaterials, 20, pp. 1195-1201;Howlett, C., McCartney, E., Ching, W., The effects of silicon nitride ceramic on rabbit skeletal cells and tissues (1989) Clin Orthop, 244, pp. 296-301; Hench, L.L., Biomaterials: A forecast for the future (1998) Biomaterials, 19, pp. 1419-1423; Radin, S., Ducheyne, P., Falaize, S., Hammond, A., In vitro transformation of bioactive glass granules into Ca-P shells (2000) J Biomed Mater Res, 49, pp. 264-272; Santos, J.D., Amaral, M., Oliveira, S.M., Lopes, M.A., Silva, R.F., Silicon Nitride-Bioglass®45S5 composite for biomedical applications (2001) Key Eng Mater, 192-195, pp. 589-592; Gazzara, C.P., Messier, D.R., Determination of phase content of Si 3N 4 by X-ray diffraction analysis (1997) Am Ceram Soc Bull, 56 (9), pp. 777-780; Niihara, K., Morena, R., Hasselman, D.P., Evaluation of K IC of brittle solids by the indentation method with low crack-to-indent ratios (1982) J Mater Sci Lett, 1, pp. 13-16; Standard test method for dynamic Young's modulus, shear modulus, and Poisson's ratio for advanced ceramics by impulse excitation of vibration; Kingery, W.D., Densification during sintering in the presence of a liquid phase. I. Theory (1959) J Appl Phys, 30 (3), pp. 301-306; Ziegler, G., Heinrich, J., Wötting, G., Review: Relationships between processing, microstructure and properties of dense and reaction-bonded silicon nitride (1987) J Mater Sci, 22, pp. 3041-3086; Filho, O.P., LaTorre, G.P., Hench, L.L., Effect of crystallization on apatite-layer formation of bioactive glass 45S5 (1996) J Biomed Mater Res, 30, pp. 509-514; Evans, A.G., Wilshaw, T.R., Quasi-static solid particle damage in brittle solids I. Observations, analysis and implications (1976) Acta Metall, 24, pp. 939-956; Yamamuro, T., Reconstruction of the iliac crest with bioactive glass-ceramic prostheses (1990) Handbook of Bioactive Ceramics, 1, pp. 335-342. , Yamamuro T, Hench LL, Wilson J, editors. Boca Raton: CRC Press; Hench, L.L., Bioceramics (1998) J Am Ceram Soc, 81, pp. 1705-1728; Ravaglioli, A., Krajewski, A., (1992) Bioceramics - materials, properties and applications, , London: Chapman & Hall; Kong, Y.M., Kim, S., Kim, H.E., Reinforcement of hydroxyapatite bioceramic by addition of ZrO 2 coated with Al 2O 3 (1999) J Am Ceram Soc, 82 (11), pp. 963-968; Ducheyne, P., Marcolongo, M., Schepers, E., Bioceramic composites (1993) An Introduction to Bioceramics. Advanced series in ceramics, 1, pp. 281-297. , Hench L, Wilson J, editors. Singapore: World Scientific. Chapter 15
Keywords: 3N; 4-bioglass composites; article; Bending strength; Biocompatible Materials; biomaterial; Biomaterial composites; Biomaterials; Ceramic materials; ceramics; Composite Resins; Crystallization; Densification; Densification behaviour; density; Elastic moduli; Fracture toughness; glass; hardness; heat; Hot pressing; Hot-pressing; Kinetics; Mechanical properties; phase transition; Phase transitions; priority journal; Si; Silicon compounds; silicon derivative; Sintering; strength; Stress, Mechanical; technique; Thermodynamics; Vickers hardness testing; X-Ray Diffraction; young modulus

Si 3N 4-bioglass composites stimulate the proliferation of MG63 osteoblast-like cells and support the osteogenic differentiation of human bone marrow cells - Amaral, M.; Costa, M.A.; Lopes, M.A.; Silva, R.F.; Santos, J.D.; Fernandes, M.H. (BiomaterialsBiomaterials, 2002)
The in vitro osteocompatibility of a novel Si 3N 4-bioglass composite (70-30% weight proportion) with improved mechanical properties (fracture toughness=4.4MPam 1/2; bending strength=383±47MPa) is reported. Immersion of the composite samples in culture medium (30min to 7 days) resulted in rapid protein adsorption to the surface and, also, dissolution of the intergranular phase of bioglass (time-dependent process) with the formation of different size cavities. "As-received" and pre-treated material samples presented a similar behaviour concerning the proliferation of MG63 osteoblast-like cells, evaluated during a 5-day culture period. Seeded materials showed a higher cell growth rate as compared to cultures performed on the standard plastic culture plates. To assess the osteogenic potential of the composite, "as-received" material samples were seeded with human bone marrow cells and cultured for 35 days in experimental conditions that favour the development of the osteoblastic phenotype. The cell adhesion process was similar to that observed in control cultures. Cells successfully adapted to the irregularities of the surface and were able to grow towards inside the cavities; in addition, osteogenic differentiation occurred with the formation of abundant cell-mediated mineralised deposits. Results suggest that this Si 3N 4-bioglass composite seems to be a promising candidate for high-stress medical applications. © 2002 Elsevier Science Ltd. All rights reserved.
Cited By (since 1996): 31Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(02)00249-1PubMed ID: 12361631Language of Original Document: EnglishCorrespondence Address: Fernandes, M.H.; Faculdade de Medicina Dentaria, Universidade do Porto, Rua Dr Manuel Pereira da Silva, 4200-393 Porto, Portugal; email: mhrf@portugalmail.ptChemicals/CAS: Alkaline Phosphatase, EC 3.1.3.1; Calcium, 7440-70-2; Phosphorus, 7723-14-0; Silicon Compounds; silicon nitride, 12033-89-5References: Amaral, M., Lopes, M.A., Silva, R.F., Santos, J.D., Densification route and mechanical properties of Si 3N 4-bioglass biocomposites (2002) Biomaterials, 23, pp. 857-862;Kue, R., Sahrabi, A., Nagle, D., Frondonza, C., Hungerford, D., Enhanced proliferation and osteocalcin production by human osteoblast-like cells on silicon nitride ceramic discs (1999) Biomaterials, 20, pp. 1195-1201; Howlett, C., McCartney, E., Ching, W., The effects of silicon nitride ceramic on rabbit skeletal cells and tissues (1989) Clin Orthop, 244, pp. 296-301; Hench, L.L., Biomaterials: A forecast for the future (1998) Biomaterials, 19, pp. 1419-1423; Radin, S., Ducheyne, P., Falaize, S., Hammond, A., In vitro transformation of bioactive glass granules into Ca-P shells (2000) J Biomed Mater Res, 49, pp. 264-272; Santos, J.D., Amaral, M., Oliveira, S.M., Lopes, M.A., Silva, R.F., Silicon Nitride - Bioglass ® 45S5 composite for biomedical applications (2001) Key Eng Mater, 192-195, pp. 589-592; Clover, J., Gowen, M., Are MG63 and HOS TE 85 human osteosarcoma cell lines representative models of the osteoblastic phenotype? (1994) Bone, 15, pp. 585-591; Maniatopoulos, C., Sodek, J., Melcher, A., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res, 254, pp. 317-330; Aronow, M.A., Gerstenfeld, L.C., Owen, T.A., Factors that promote progressive development of the osteoblastic phenotype in cultured fetal rat calvaria cells (1990) J Cell Phys, 43, pp. 213-221; Gundle, R., Joyner, C.J., Triffit, J.T., Human bone tissue formation in diffusion chamber culture in vivo by bone derived cells and marrow stromal fibroblastic cells (1995) Bone, 16, pp. 597-601; Stein, G.S., Lian, J.B., Stein, J.L., Van Wijnem, A.J., Frenkel, B., Montecino, M., Mechanisms regulating osteoblast proliferation and differentiation (1996) Principles of bone biology, pp. 69-86. , J.P. Bilizikian, L.G. Raisz, & G.A. Rodan. New York: Academic Press; Fernandes, M.H., Costa, M.A., Carvalho, G.S., Mineralization in serially passaged human alveolar bone cells (1997) J Mater Sci: Mater Med, 8, pp. 61-65; Coelho, M.J., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part II: Effect of ascorbic acid β-glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21, pp. 1095-1102; Costa, M.A., Fernandes, M.H., Long-term effects of parathyroid hormone, 1,25-dihydroxyvitamin D3 and dexamethasone on the cell growth and functional activity of human osteogenic alveolar bone cell cultures (2000) Pharmacol Res, 42, pp. 345-353; Coelho, M.J., Trigo Cabral, A., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part I: Osteoblastic differentiation of serially passaged human bone marrow cells cultured in α-MEM and in DMEM (2000) Biomaterials, 21, pp. 1087-1094; Aubin, J.E., Liu, F., The osteoblastic lineage (1996) Principles of bone biology, pp. 51-67. , J.P. Bilizikian, L.G. Raisz, & G.A. Rodan. New York: Academic Press; Ferraz, M.P., Monteiro, F.J., Santos, J.D., CaO-P 2O 5 glass hydroxyapatite double layer plasma sprayed coatings: In vitro bioactivity evatuation (1999) J Biomed Mater Res, 45, pp. 376-383; Kokubo, T., Ito, S., Huang, Z.T., Hayashi, T., Sakka, S., Ca, P-rich layer formed on high-strenght bioactive glass-ceramic A-W (1990) J Biomed Mater Res, 24, pp. 331-343; Daculsi, G., Legeros, R.Z., Heughebaert, M., Barbieux, I., Formation of carbonato-apatite crystals after implantation of calcium phosphate ceramics (1990) Calcif Tissue Int, 46 (1), pp. 20-27; Neo, M., Nakamura, T., Ohtsuki, C., Kokubo, T., Yamamuro, T., Apatite formation on three kinds of bioactive material at an early stage in vivo: A comparative study by transmission electron microscopy (1993) J Biomed Mater Res, 27, pp. 999-1006; Bagambisa, F.B., Joos, U., Schilli, W., Mechanisms and structure of the bond between bone and hydroxyapatite ceramics (1993) J Biomed Mater Res, 27, pp. 1047-1055; Bagambisa, F.B., Kappert, H.F., Schilli, W., Interfacial reactions of osteoblast to dental and implant materials (1994) J Oral Maxillofac Surg, 52, pp. 52-56; De Bruijn, J.D., Van Blitterswijk, C.A., Davies, J.E., Initial bone matrix formation at the hydroxyapatite interface (1995) J Biomed Mater Res, 29 (1), pp. 89-99; Hulshott, J.E.G., Van Kijk, K., De Ruijter, J.E., Rietveld, F.J.R., Ginsel, L.A., Jansen, J.A., Interfacial phenomena: An in vitro study of the effect of calcium phosphate (Ca-P) ceramic on bone formation (1998) J Biomed Mater Res, 40, pp. 464-474; De Santis, D., Guerriero, C., Nocini, P.F., Vangersbock, A., Richard, G., Gotte, P., Armato, U., Adult human bone cells from jaw bones cultured on plasma-sprayed or polished surfaces of titanium or hydroxyapatite discs (1996) J Mater Sci Mater Med, 7, pp. 21-28; Anselme, K., Sharrock, P., Hardouin, P., Dard, M., In vitro growth of human adult bone-derived cells on hydroxyapatite plasma-sprayed coatings (1997) J Biomed Mater Res, 34, pp. 247-259; Ferraz, M.P., Fernandes, M.H., Trigo Cabral, A., Santos, J.D., Monteiro, F.J., In vitro growth and differentiation of osteoblastic-like human bone marrow cells on a glass reinforced hydroxyapatite plasma-speayed coating (1999) J Mater Sci: Mater Med, 10, pp. 567-576; Ferraz, M.P., Knowles, J.C., Olsen, I., Monteiro, F.J., Santos, J.D., Flow cytometry analysis of the effects of pre-immersion on the biocompatibility of glass-reinforced hydroxyapatite plasma sprayed coatings (2000) Biomaterials, 21, pp. 813-820; Ferraz, M.P., Fernandes, M.H., Santos, J.D., Monteiro, F.J., HA and double-layer HA/CaO-P 2O 5 glass coatings: Influence of chemical composition on human bone marrow cells osteoblastic behaviour (2001) J Mater Sci: Mater Med, 7, pp. 628-638; Lopes, M.A., Knowles, J.C., Santos, J.D., Monteiro, F.J., Olsen, I., Direct and indirect effects of P 2O 5-glass reinforced hydroxyapatite composites on the growth and function of osteoblast-like cells (2000) Biomaterials, 21, pp. 1165-1172; Lopes, M.A., Santos, J.D., Monteiro, F.J., Ohtsuki, C., Osaka, A., Kaneko, S., Inoue, H., Push-out testing and histological evaluation of glass reinforced hydroxyapatite composites implanted in the tibia of rabbits (2001) J Biomed Mater Res, 54, pp. 463-469; Gwynn, I.A.P., Cell biology at interfaces (1994) J Mater Sci Mater Med, 5, pp. 357-360; Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 21, pp. 667-681; KirkPatrick, C.J., Wagner, M., Kohler, H., Bittinger, F., Otto, M., Klein, C.L., The cell and molecular biological approach to biomaterial research: A perspective (1997) J Mater Sci Mater Med, 8, pp. 131-141; Verrier, S., Bareille, R., Rovira, A., Dard, M., Amedee, J., Human osteoprogenitor responses to orthopaedic implant: Mechanism of cell attachment and cell adhesion (1996) J Mater Sci Mater Med, 7, pp. 46-51; Dee, K.C., Rueger, D.C., Andersen, T.T., Bizios, R., Conditions which promote mineralization at the bone-implant interface: A model for in vitro study (1996) Biomaterials, 17, pp. 209-215; Anseme, K., Bigerelle, M., Noel, B., Dufresne, E., Judas, D., Iost, A., Hardouin, P., Qualitative and quantitative study of human osteoblast adhesion on materials with various surface roughnesses (2000) J Biomed Mater Res, 49, pp. 155-166; Diniz, M.G., Soares, G.A., Coelho, M.J., Fernandes, M.H., Surface topography modulates the osteogenesis in human bone marrow cell cultures grown on titanium samples prepared by a combination of mechanical and acid treatments (2002) J Mater Sci: Mater Med, 13, pp. 421-432; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Initiation and progression of mineralization of bone nodules formed in vitro: The role of alkaline phosphatase and organic phosphate (1991) Bone Min, 14, pp. 27-40; Bellows, C.G., Heersche, J.N.M., Aubin, J.E., Inorganic phosphate added exogenously or released from β-glycerophosphate initiates mineralization of osteoid nodules in vitro (1992) Bone Min, 17, pp. 15-29
Keywords: 3N; 4-bioglass composite; Adhesion; Adsorption; alkaline phosphatase; article; Biocompatibility; Bioglass; Biomaterials; bone marrow cell; Bone Marrow Cells; Calcium; cell adhesion; Cell Culture Techniques; cell differentiation; Cell Division; cell growth; cell proliferation; composite material; controlled study; culture medium; Dissolution; glass; Growth kinetics; human; Human bone marrow cells; human cell; Humans; immersion; in vitro study; Mechanical properties; MG63 osteoblast-like cells; Microscopy, Electron, Scanning; osteoblast; Osteoblasts; Osteocompatibility; Osteogenic differentiation; phenotype; phosphorus; priority journal; Proteins; rigidity; Si; Silicon compounds; silicon derivative; surface property; tensile strength; Time Factors

Silicon and iron levels in tissues of animals treated with a "ferrimagnetic ceramic" with oncotherapeutic potential (anti-tumor) value - Almeida, T.; Soares, M.E.; Cavalheiro, J.; Bastos, M.D.L. (Journal of Trace Elements in Medicine and BiologyJ. Trace Elem. Med. Biol., 2002)
The stability in a biological environment of an injectable cement with oncotherapeutic potential - consisting of a glass powder of SiO 2 (35.6%), CaO (42.4%), P 2O 5 (17%), Na 2O (5%) and 30% of its weight of Fe 3O 4 dissolved in (NH 4) 2HPO 4 plus NH 4H 2PO 4 - was evaluated referring to the release of silicon and iron. The experimental model was the rat, and organs (liver, kidney, spleen, lung, heart, and brain) of the implanted and control animals were collected for quantification of these elements by electrothermal atomization atomic absorption spectrometry methods. In most of the analysed organs no significant difference in the contents of silicon and iron between the implanted and the control animals was found.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: JTEBFdoi: 10.1016/S0946-672X(02)80054-2PubMed ID: 12530589Language of Original Document: EnglishCorrespondence Address: Bastos, M.D.L.; Toxicology Department, Faculty of Pharmacy, University of Porto, Rua Aníbal Cunha 164, 4050 Porto, PortugalChemicals/CAS: calcium oxide, 1305-78-8; iron, 14093-02-8, 53858-86-9, 7439-89-6; phosphorus pentoxide, 1314-56-3; silicon dioxide, 10279-57-9, 14464-46-1, 14808-60-7, 15468-32-3, 60676-86-0, 7631-86-9; silicon, 7440-21-3; Biocompatible Materials; Ceramics; Iron, 7439-89-6; Silicon, 7440-21-3; Tissue ExtractsReferences: Rofstad, E.K., Brustad, T., Primary and secondary cell death in human melanoma xenografts following hyperthermic treatment (1986) Cancer Res., 46, pp. 355-361;Nishimura, Y., Shibamoto, Y., Jo, S., Akuta, K., Hiraoka, M., Takahashi, M., Abe, M., Relationship between heat-induced vascular damage and thermosensitivity in four mouse tumors (1988) Cancer Res., 48, pp. 7226-7230; Brown, S.L., Hunt, J.W., Hill, R.P., Differential thermal sensitivity of tumour and normal tissue microvascular response during hyperthermia (1992) Int. J. Hyperthermia, 8, pp. 501-514; Dudar, T.E., Jain, R.K., Differential response of normal and tumor microcirculation to hyperthermia (1984) Cancer Res., 44, pp. 605-612; Hill, S.A., Smith, K.A., Denekamp, J., Reduced thermal sensitivity of the vasculature in a slowly growing tumour (1989) Int. J. Hyperthermia, 5, pp. 359-370; Bicher, H.I., Hetzel, F.W., Sandhu, T.S., Frinak, S., Vaupel, P., O'Hara, M.D., O'Brien, T., Effects of Hyperthermia on normal and tumor microenvironment (1980) Radiology, 137, pp. 523-530; Song, C.W., Kang, M.S., Rhee, J.G., Levitt, S.H., The effect of hyperthermia on vascular function, pH, and cell survival (1980) Radiology, 137, pp. 795-803; Emami, B., Song, C.W., Physiological mechanisms in hyperthermia: A review (1984) Int. J. Radiation Oncology Biol. Phys., 10, pp. 289-295; Cavalheiro, J., Vasconcelos, M., Afonso, A., Branco, R., Ferrimagnetic and biocompatible cement for tumours thermotherapy (1996) Bioceramics, 9, pp. 243-246; Coury, A.J., Levy, R.J., McMillin, C.R., Pathak, Y., Ratner, B.D., Schoen, F.J., Williams, D.F., Williams, R.L., Degradation of materials in the biological environment (1996) Biomaterials Science, pp. 243-260. , Ratner BD, Hoffman AS, Schoen FJ, Lemons JE (Eds). Academic Press, San Diego; Williams, D.F., Williams, R.L., Degradative effects of the biological environment on metals and ceramics (1996) Biomaterials Science, pp. 260-267. , Ratner BD, Hoffman AS, Schoen FJ, Lemons JE (Eds). Academic Press, San Diego; Van Dyck, K., Robberecht, H., Van Cauwenbergh, R., Deelstra, H., Arnaud, J., Willemyns, L., Benijts, F., Uytterhoeven, M., Spectrometric determination of silicon in food and biological samples: An interlaboratory trial (2000) J. Anal. At. Spectrom., 15, pp. 735-741; Adler, A.J., Etzion, Z., Berlyne, G.M., Uptake, distribution, and excretion of 31silicon in normal rats (1986) Am. J. Physiol., 251, pp. E670-E673; Beattie, J.H., Avenell, A., Trace element nutrition and bone metabolism (1992) Nutrition Res. Rev., 5, pp. 167-188; Robinson, C.H., Lawler, M.R., Mineral elements (1982) Normal and Therapeutic Nutrition, 16 th Edition, pp. 131-160. , Robinson CH, Lawler MR (Eds). Macmillan Publishing Co., Inc., New York, Collier Macmillan Publishers, London; Sorond, F.A., Ratan, R.R., Ironing-out mechanisms of neuronal injury under hypoxic-ischemic conditions and potential role of iron chelators as neuroprotective agents (2000) Antioxid. Redox Signal, 2, pp. 421-436; Bonkovsky, H.L., Lambrecht, R.W., Iron-induced liver injury (2000) Clin. Liver Dis., 4, pp. 409-429; Bartfay, W.J., Bartfay, E., Iron-overload cardiomyopathy: Evidence for a free radical-mediated mechanism of injury and dysfunction in a murine model (2000) Biol. Res. Nurs., 2, pp. 49-59; Kang, J.L., Pack, I.S., Lee, H.S., Castranova, V., Enhancement of nuclear factor-KB activation and protein tyrosine phosphorylation by a tyrosine phosphatase inhibitor, pervanadate, involves reactive oxygen species in silica-stimulated macrophages (2000) Toxicology, 151, pp. 81-89
Keywords: animal model; animal tissue; Animalia; Animals; article; atomic absorption spectrometry; Biocompatible Materials; calcium oxide; cancer therapy; cement; ceramics; controlled study; experimental model; Ferrimagnetic ceramic; heat; Humans; implant; Iron; Magnetics; materials testing; Neoplasms; nonhuman; Oncotherapy; phosphorus pentoxide; powder; priority journal; Prostheses and Implants; rat; Rats; Reproducibility of Results; Silicon; silicon dioxide; tissue distribution; Tissue Extracts

Soluble silk-like organic matrix in the nacreous layer of the bivalve Pinctada maxima: A new insight in the biomineralization field - Pereira-Mouriès, L.; Almeida, M.-J.; Ribeiro, C.; Peduzzi, J.; Barthélemy, M.; Milet, C.; Lopez, E. (European Journal of BiochemistryEur. J. Biochem., 2002)
Nacre organic matrix has been conventionally classified as both 'water-soluble' and 'water-insoluble', based on its solubility in aqueous solutions after decalcification with acid or EDTA. Some characteristics (aspartic acid-rich, silk-fibroin-like content) were specifically attributed to either one or the other. The comparative study on the technique of extraction (extraction with water alone vs. demineralization with EDTA) presented here, seems to reveal that this generally accepted classification may need to be reconsidered. Actually, the nondecalcified soluble organic matrix, extracted in ultra-pure water, displays many of the characteristics of what until now has been called 'insoluble matrix'. We present the results obtained on this extract and on a conventional EDTA-soluble matrix, with various characterization methods: fractionation by size-exclusion and anion-exchange HPLC, amino acid analysis, glycosaminoglycan and calcium quantification, SDS/PAGE and FTIR spectroscopy. We propose that the model for the interlamellar matrix sheets of nacre given by Nakahara [In: Biomineralization and Biological Metal Accumulation, Westbroek, P. & deJong, E.W., eds, (1983) pp. 225-230. Reidel, Dordrecht, Holland] and Weiner and Traub [Phil. Trans. R. Soc. Lond. B (1984) 304, 425-434] may no longer be valid. The most recent model, proposed by Levi-Kalisman et al. [J. Struct. Biol. (2001) 135, 8-17], seemed to be more in accordance with our findings.
Cited By (since 1996): 58Export Date: 21 November 2012Source: ScopusCODEN: EJBCAdoi: 10.1046/j.1432-1033.2002.03203.xPubMed ID: 12383258Language of Original Document: EnglishCorrespondence Address: Lopez, E.; Lab. de Physiologie Gen. et Comparee, UMR CNRS 8572, Museum National d'Histoire Naturelle, 7 rue Cuvier, 75231 Paris Cedex 05, France; email: lopez@mnhn.frChemicals/CAS: Amino Acids; Calcium, 7440-70-2; Edetic Acid, 60-00-4; Extracellular Matrix Proteins; Glycosaminoglycans; Insect Proteins; SilkReferences: Crenshaw, M.A., The soluble matrix from Mercenaria mercenaria shell (1972) Biomineralization, 6, pp. 6-11;Krampitz, G., Engels, J., Cazaux, C., Biochemical studies on water-soluble proteins and related components of gastropod shells (1976) The Mechanisms of Mineralization in the Invertebrates and Plants, pp. 175-190. , Watabe, N. & Wilbur, K.M., eds. The Barush B.W. Library in Marine Science no. 5, The University of South Carolina Press, Columbia; Weiner, S., Traub, W., Lowenstam, H.A., Organic matrix in calcified exoskeletons (1983) Biomineralization and Biological Metal Accumulation, pp. 205-224. , Westbroek, P. & deJong, E.W., eds. Reidel, Dordrecht, Holland; Keith, J., Stockwell, D., Ball, D., Remillard, K., Kaplan, D., Thannhauser, T., Sherwood, R., Comparative analysis of macromolecules in mollusc shells (1993) Comp. Biochem. Physiol., 105 B, pp. 487-496; Levi-Kalisman, Y., Falini, G., Addadi, L., Weiner, S., Structure of the nacreous organic matrix of a bivalve mollusk shell examined in the hydrated state using cryo-TEM (2001) J. Struct. Biol., 135, pp. 8-17; Weiner, S., Hood, L., Soluble protein of the organic matrix of mollusk shells: A potential template for shell formation (1975) Science, 190, pp. 987-989; Weiner, S., Traub, W., Macromolecules in mollusc shells and their functions in biomineralization (1984) Phil. Trans. R. Soc. Lond. B, 304, pp. 425-434; Belcher, A.M., Wu, X.H., Christensen, R.J., Hansma, P.K., Stucky, G.D., Morse, D.E., Control of crystal phase switching and orientation by soluble mollusc-shell proteins (1996) Nature, 381, pp. 56-58; Kamat, S., Su, X., Ballarini, R., Heuer, A.H., Structural basis for the fracture toughness of the shell of the conch Strombus gigas (2000) Nature, 405, pp. 1036-1040; Hare, P.E., Amino acids in the proteins from aragonite and calcite in the shells of Mytilus californianus (1963) Science, 139, pp. 216-217; Hare, P.E., Abelson, P.H., Amino acid composition of some calcified proteins (1965) Carnegie Inst. Washington Year Book, 64, p. 223; Watabe, N., Shell (1984) Biology of the Integument, 1, pp. 448-485. , Invertebrates (Bereiterhahn, J., Matolsty, A.G. & Richards, K.S., eds). Springer-Verlag, Berlin; Mann, S., Molecular recognition in biomineralization (1988) Nature, 332, pp. 119-124; Kono, M., Hayashi, N., Samata, T., Molecular mechanism of the nacreous layer formation in Pinctada maxima (2000) Biochem. Biophys. Res. Commun., 269, pp. 213-218; Lopez, E., Berland, S., Le Faou, A., Nacre, osteogenic and osteoinductive properties (1994) Bull. Inst. Océan Monaco, 14, pp. 49-57; Lopez, E., Vidal, B., Berland, S., Camprasse, C., Camprasse, G., Silve, C., Demonstration of the capacity of nacre to induce bone formation by human osteoblasts maintained in vitro (1992) Tissue Cell, 24, pp. 667-679; Atlan, G., Balmain, N., Berland, S., Vidal, B., Lopez, E., Reconstruction of human maxillary defects with nacre powder: Histological evidence for bone regeneration (1997) C. R. Acad. Sci. Paris, Life Sci., 320, pp. 253-258; Atlan, G., Delattre, O., Berland, S., Le Faou, A., Nabias, G., Cot, D., Lopez, E., Interface between bone and nacre implants in sheep (1999) Biomaterials, 20, pp. 1017-1022; Lamghari, M., Almeida, M.J., Berland, S., Huet, H., Laurent, A., Milet, C., Lopez, E., Stimulation of bone marrow cells and bone formation by nacre: In vivo and in vitro studies (1999) Bone, 25 S, pp. 91S-94S; Almeida, M.J., Milet, C., Peduzzi, J., Pereira, L., Haigle, J., Barthélemy, M., Lopez, E., The effect of water-soluble matrix fraction extracted from the nacre of Pinctada maxima on the alkaline phosphatase activity of cultured fibroblasts (2000) J. Exp. Zool. (Mol. Dev. Evol.), 288, pp. 327-334; Almeida, M.J., Pereira, L., Milet, C., Haigle, J., Barbosa, M., Lopez, E., Comparative effects of nacre water-soluble matrix and dexamethasone on the alkaline phosphatase activity of MRC-5 fibroblasts (2001) J. Biomed. Mater. Res., 57, pp. 306-312; Lamghari, M., Berland, S., Laurent, A., Huet, H., Lopez, E., Bone reactions to nacre injected percutaneously into the vertebrae of sheep (2001) Biomaterials, 22, pp. 555-562; Lopez, E., Giraud, M., Le Faou, A., Berland, S., Gutierrez, J., (1995), Procédé de préparation de substances actives à partir de la nacre, produits obtenus, utiles comme médicaments. Patent CNRS no. FR. 9515650, 28/12/1995, WO 97/24133-10/07/97Wheeler, A.P., Rusenko, K.W., George, J.W., Sikes, S., Evaluation of calcium binding by molluscan shell organic matrix and its relevance to biomineralization (1987) Comp. Biochem. Physiol., 87 B, pp. 953-960; Cohen-Solal, L., Lian, J.B., Kossiva, D., Glimcher, M.J., The identification of O-phosphothreonine with soluble non-collagenous phosphoproteins of bone matrix (1978) FEBS Lett., 89, pp. 107-110; Cohen, S.A., Strydom, D.J., Amino acid analyses utilizing phenylisothiocyanate derivatives (1988) Anal. Biochem., 174, pp. 1-16; Hewitt, B.R., Spectrophotometric determination of protein in alkaline solution (1958) Nature, 187, p. 246; Whiteman, P., The quantitative determination of glycosaminoglycans in urine with Alcian blue 8GX (1973) Biochem. J., 131, pp. 351-357; Whiteman, P., The quantitative measurement of Alcian blue-glycosaminoglycan complexes (1973) Biochem. J., 131, pp. 343-350; Gold, E.W., A simple spectrophotometric method for estimating glycosaminoglycan concentrations (1979) Anal. Biochem., 99, pp. 183-188; Laemmli, U.K., Cleavage of structural proteins during the assembly of the head of bacteriophage T4 (1970) Nature, 227, pp. 680-685; Morrissey, J.H., Silver stain for proteins in polyacrylamide gels: A modified procedure with enhanced uniform sensitivity (1981) Anal. Biochem., 117, pp. 307-310; Wheeler, A.P., Rusenko, K.W., Sikes, S., Organic matrix from carbonate biomineral as a regulator of mineralization (1988) Chemical Aspects of Regulation of Mineralization, , (Sikes, C.S. & Wheeler, A.P., eds). University of South Alabama Publication Services, Mobile, Alabama; Weiner, S., Aspartic acid-rich proteins: Major components of the soluble organic matrix of mollusk shells (1979) Calcif. Tissue Int., 29, pp. 163-167; Wheeler, A.P., Rusenko, K.W., Swift, D.M., Sikes, S., Regulation of in vitro and in vivo CaCO 3 crystallization by fractions of oyster shell organic matrix (1988) Mar. Biol., 98, pp. 71-80; Halloran, B.A., Donachy, J.E., Characterization of organic matrix macromolecules from the shells of the antarctic scallop Adamussium colbecki (1995) Comp. Biochem. Physiol., 111 B, pp. 221-231; Scott, J.E., Quintarelli, G., Dellovo, M.C., The chemical and histochemical properties of Alcian blue staining (1964) Histochemie, 4, pp. 73-85; Nakamoto, K., (1986) IR and Raman Spectra of Inorganic and Coordination Compounds, , J. Wiley & Sons, New York; Samata, T., Krampitz, G.P., Calcium binding polypeptides in oyster shells (1982) Malacologia, 22, pp. 225-233; Roeges, N.P.G., (1998) A Guide to the Complete Interpretation of Infrared Spectra of Organic Structures, , J. Wiley & Sons, New York; Cariolou, M., Morse, D., Purification and characterization of calcium binding conchiolin shell peptides from the mollusc, Haliotis rufescens, as a function of development (1988) J. Comp. Physiol., 157 B, pp. 717-729; Krampitz, G.P., Structure of the organic matrix in mollusc shells and avian eggshells (1982) Biological Mineralization and Demineralization, pp. 219-232. , Nancollas, G.H., ed. Springer-Verlag, Berlin, Heidelberg, New York; Weiner, S., Addadi, L., Acidic macromolecules of mineralized tissues: The controllers of crystal formation (1991) Trends Biochem. Sci., 16, pp. 252-256; Marin, F., Pereira, L., Westbroek, P., Large-scale fractionation of molluscan shell matrix (2001) Protein Expr. Purif., 23, pp. 175-179; Balmain, J., Hannoyer, B., Lopez, E., Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction analyses of mineral and organic matrix during heating of mother of pearl (nacre) from the shell of the mollusc Pinctada maxima (1999) J. Biomed. Mater. Res. Appl. Mat., 48, p. 754; Marxen, J.C., Hammer, M., Gehrke, T., Becker, W., Carbohydrates of the organic shell matrix and the shell forming tissue of the snail Biomphalaria glabrata (Say) (1998) Biol. Bull., 194, pp. 231-240; Miyazawa, T., Blout, E.R., The infrared spectra of polypeptides in various conformations - Amide I and II bands (1961) J. Am. Chem. Soc., 83, pp. 712-719; Worms, D., Weiner, S., Mollusk shell organic matrix: Fourier transform infrared study of the acidic macromolecules (1986) J. Exp. Zool., 237, pp. 11-20; Weiner, S., Traub, W., X-ray diffraction study of the insoluble organic matrix of mollusk shells (1980) FEBS Lett., 111, pp. 311-316; Pereira-Mouriès, L., Almeida, M.J., Marin, F., Gay, M., Milet, C., Lopez, E., Soluble proteins of the nacre from the giant oyster Pinctada maxima with highly hydrophobic amino acids (2002) Biomineralization: Formation, Diversity, Evol. Appl., , in press; Nakahara, H., Kakei, M., Bevelander, G., Fine structure and amino acid composition of the organic 'envelope' in the prismatic layer of some bivalve shells (1980) Venus Jpn. J. Malacol., 39, pp. 167-177; Falini, G., Albeck, S., Weiner, S., Addadi, L., Control of aragonite or calcite polymorphism by mollusk shell macromolecules (1996) Science, 271, pp. 67-69; Simkiss, K., The organic matrix of the oyster shell (1965) Comp. Biochem. Physiol., 16, pp. 427-435; Golberg, M., Takagi, M., Dentine proteoglycans: Composition, ultrastructure, and functions (1993) Histochem. J., 25, pp. 781-806; Wilbur, K.M., Recent studies of invertebrate mineralization (1976) The Mechanisms of Mineralization in Invertebrates and Plants, pp. 79-108. , Watabe, N. & Wilbur, K.M., eds. The University of South Carolina Press, The Belle W. Baruch Library in Marine Science no. 5, Columbia; Addadi, L., Moradian, J., Shay, E., Maroudas, N.G., Weiner, S., A chemical model for the cooperation of sulfates and carboxylates in calcite crystal nucleation: Revelance to biomineralization (1987) Proc. Natl. Acad. Sci. USA, 84, pp. 2732-2736; Marxen, J.C., Becker, W., Calcium binding constituents of the organic shell matrix from the freshwater snail Biomphalaria glabrata (2000) Comp. Biochem. Physiol., 127 B, pp. 235-242; Tanaka, Y., Adams, D.H., Shaw, S., Proteoglycans on endothelial cells present adhesion-inducing cytokines to leukocytes (1993) Immunol. Today, 14, pp. 111-115; Jackson, R.L., Bush, S.J., Cardin, A.D., Glycosaminoglycans: Molecular properties, protein interactions, and role in physiological processes (1991) Physiol. Rev., 71, pp. 481-539; Nakahara, H., Calcification of gastropod nacre (1983) Biomineralization and Biological Metal Accumulation, pp. 225-230. , Westbroek, P. & deJong, E.W., eds. Reidel, Dordrecht, Holland; Zentz, F., Bédouet, L., Almeida, M.J., Milet, C., Lopez, E., Giraud, M., Characterization and quantification of chitosan extracted from nacre of the abalone Haliotis tuberculata and the oyster Pinctada maxima (2001) Mar. Biotechnol., 3, pp. 36-44; Alzieu, C., Thibaud, Y., Heral, M., Boutier, B., Evaluation des risques dus a l'emploi des peintures anti-sallissures dans les zones conchyoliques (1980) Rev. Trav. Inst. Pêches Marit., 44, pp. 301-348; Alzieu, C., Heral, M., Thibaud, Y., Dardignac, M.J., Feuillet, M., Influence des peintures anti-sallissures à base d'organostanniques sur la calcification de la coquille de l'huître Crassostrea gigas (1982) Rev. Trav. Inst. Pêches Marit., 45, pp. 101-116; Krampitz, G., Drolshagen, H., Deltreil, J.P., Soluble matrix components in malformed oyster shells (1983) Experientia, 39, pp. 1105-1106; Alzieu, C., Heral, M., Ecotoxicological effects of organotin coumpounds on oyster culture (1984) Ecotoxicological Testing for the Marine Environment, 2, pp. 187-196. , Persoone, G., Jaspers, E. & Claus, C., eds. State University Ghent and Inst. Mar. Sci. Res., Bredene, Belgium; Almeida, M.J., (1996) Crescimento em Ostras: Factores que Afectam a Formação e Estrutura da Concha, , PhD Thesis, Instituto de Ciências Biomédicas Abel Salazar, University of Porto, Portugal; Sudo, S., Fujikawa, T., Nagakura, T., Ohkubo, T., Sakaguchi, K., Tanaka, M., Nakashina, K., Takahashi, T., Structures of mollusc shell framework proteins (1997) Nature, 387, pp. 563-564; Shen, X., Belcher, A.M., Hansma, P.K., Stucky, G.D., Morse, D.E., Molecular cloning and characterization of Lustrin A, a matrix protein from shell and pearl nacre of Haliotis rufescens (1997) J. Biol. Chem., 272, pp. 32472-32481; Samata, T., Hayashi, N., Kono, M., Hasegawa, K., Horita, C., Akera, S., A new matrix protein family related to the nacreous layer formation of Pinctada fucata (1999) FEBS Lett., 462, pp. 225-229; Mann, S., Webb, J., Williams, R.J.P., (1989) Biomineralization: Chemical and Biochemical Perspectives, pp. 35-62. , VCH, Weinheim; Simkiss, K., Wilbur, K.M., (1989) Biomineralization - Cell Biology and Mineral Deposition, , Academic Press, San Diego; Sarashina, I., Endo, K., Primary structure of a soluble matrix protein of scallop shell: Implications for calcium carbonate biomineralization (1998) Am. Mineral., 83, pp. 1510-1515; Weiss, I., Kaufmann, S., Mann, K., Fritz, M., Purification and characterization of perlucin and perlustrin, two new proteins from the shell of the mollusc Haliotis laevigata (2000) Biochem. Biophys. Res. Commun., 267, pp. 17-21; Pereira-Mouriès, L., Milet, C., Almeida, M.J., Rousseau, M., Borzeix, S., Lopez, E., Biological effect of the water-soluble matrix extract of the nacre shell layer of Pinctada maxima on vertebrate cell proliferation and differentiation (2001) Proceedings of the 3rd International Satellite Symposium on the Comparative Endocrinology of Calcium Regulation, , http://www.sci.port.ac.uk/-cecr, Gay, C.V., Dacke, C.G., Dancks, J.A. & Cox, P.A., eds; Pereira-Mouriès, L., Almeida, M.J., Milet, C., Berland, S., Lopez, E., Bioactivity of nacre water-soluble organic matrix from the bivalve mollusk Pinctada maxima in three mammalian cell types: Fibroblasts, bone marrow stromal cells and osteoblasts (2002) Comp. Biochem. Physiol., 132, pp. 215-217
Keywords: amino acid analysis; Amino acids; Animals; anion exchange chromatography; article; Biochemistry; biomineralization; bivalve; Bivalvia; Calcium; Chemical Fractionation; Chromatography, High Pressure Liquid; controlled study; demineralization; edetic acid; EDTA-soluble matrix; Electrophoresis, Polyacrylamide Gel; Extracellular Matrix Proteins; extraction; fractionation; gel permeation chromatography; glycosaminoglycan; Glycosaminoglycans; High performance liquid chromatography; hydrophobicity; infrared spectroscopy; Insect Proteins; model; Nacre; nonhuman; Ostreidae; Pinctada; Pinctada maxima; polyacrylamide gel electrophoresis; priority journal; Silk; Silk-fibroin-like-proteins; Solubility; Spectroscopy, Fourier Transform Infrared; Undecalcified soluble matrix; Water

Wettability and surface charge of Si 3N 4-bioglass composites in contact with simulated physiological liquids - Amaral, M.; Lopes, M.A.; Santos, J.D.; Silva, R.F. (BiomaterialsBiomaterials, 2002)
Wettability and surface charge studies were performed on a novel Si 3N 4-30wt% bioglass biocomposite. Contact angle and surface tension variation with time were determined at 25°C, respectively, by the sessile and pendant drop techniques, for distinct testing liquids: water, diiodomethane, simulated body fluid (SBF) and bovine serum albumin (BSA) dissolved in SBF solution. This biocomposite revealed a hydrophilic character (θ=26.6±2.0°) and a surface tension value (66.6mJm
Cited By (since 1996): 18Export Date: 21 November 2012Source: ScopusCODEN: BIMADdoi: 10.1016/S0142-9612(02)00155-2Language of Original Document: EnglishCorrespondence Address: Santos, J.D.; Laboratório de Biomateriais, Inst. de Engenharia Biomedica (INEB), Rua do Campo Alegre, 823, 4150 Porto, Portugal; email: jdsantos@fe.up.ptChemicals/CAS: Serum Albumin, Bovine; Silicon Compounds; silicon nitride, 12033-89-5References: Von Recum, A.F., (1999) Handbook of biomaterials evaluation: scientific, technical, and clinical testing of implant materials, 2nd. ed., , Hemisphere Pub;Davies, J.E., The importance and measurement of surface charge species in cell behaviour at the biomaterial interface (1998) Surface characterisation of biomaterials, 6, pp. 219-234. , Ratner, editor. Progress in Biomedical Engineering. Amsterdam: Elsevier; Lampin, M., Warocquier-Clérout, R., Legris, C., Degrange, M., Sigot-Luizard, M.F., Correlation between substratum roughness and wettability, cell adhesion, and cell migration (1997) J Biomed Mater Res, 36, pp. 99-108; Dewez, J.L., Schneider, Y.J., Rouxhet, P.G., Coupled influence of substratum hydrophilicity and surfactant on epithelial cell adhesion (1996) J Biomed Mater Res, 30, pp. 373-383; Hallab, N.J., Bundy, K., O'Connor, R., Clark, R., Moses, R.L., Cell adhesion to biomaterials: Correlations between surface charge, surface roughness, adsorbed protein, and cell morphology (1995) J Long-Term Effects Med Implants, 3, pp. 209-231; Anselme, K., Osteoblast adhesion on biomaterials (2000) Biomaterials, 7, pp. 667-681; Garbassi, Morra, Occhiello, Polymer surfaces, from physics to technology, , Wiley & Sons, New York [Chapter 4]; Adamson, A.W., (1990) Physical chemistry of surfaces, , 5th ed, New York: Wiley; Correia, N.T., Ramos, J.M., Saramago, B., Calado, J., Estimation of the surface tension of a solid: Application to a liquid crystalline (1997) J Colloid Interface Sci, 189, pp. 361-369; Schrader, M.E., Young-Dupre Revisited (1995) Langmuir, 11, pp. 3585-3589; Nishizawa, K., Toriyama, M., Effects of the surface wettability and zeta potential of bioceramics on the adhesiveness of anchorage-dependent animal-cells (1993) J Ferment Bioeng, 6, pp. 435-437; Suzuki, T., Nishizawa, K., Yokogawa, Y., Kameyama, T., Time-dependent variation of the surface structure of bioceramics in tissue culture medium and the effect on adhesiveness of cells (1996) J Ferment Bioeng, 3, pp. 226-232; Parfitt, G.D., (1967) Principles of the colloidal state, , London: Royal Institute of Chemistry; Hench, L.L., Biomaterials: A forecast for the future (1998) Biomaterials, 19, pp. 1419-1423; Radin, S., Ducheyne, P., Falaize, S., Hammond, A., In vitro transformation of bioactive glass granules into Ca-P shells (2000) J Biomed Mater Res, 49, pp. 264-272; Amaral, M., Lopes, M.A., Silva, R.F., Santos, J.D., Densification route and mechanical properties of Si3N4-bioglass biocomposites (2002) Biomaterials, 23, pp. 857-862; Santos, J.D., Amaral, M., Oliveira, S.M., Lopes, M.A., Silva, R.F., Silicon nitride-bioglass ® composite for biomedical applications (2001) Key Eng Mater, 192-195, pp. 589-592; Krajewski, A., Piancastelli, A., Malavolti, R., Albumin adhesion on ceramics and correlation with their Z-potential (1998) Biomaterials, 19, pp. 637-641; Kokubo, T., Kushitani, H., Ohtsuki, C., Sakka, S., Chemical reaction of bioactive glass and glass-ceramics with a simulated body fluid (1992) J Mater Sci: Mater Med, 3, pp. 79-83; Vogler, E.A., Interfacial chemistry in biomaterials science (1993) Wettability, surfactant science series, 49, pp. 183-250. , Berg J.C., editor, Chapter 4; Lopes, M.A., Monteiro, F.J., Santos, J.D., Serro, A.P., Saramago, B., Hydrophobicity, surface tension, and zeta potential measurements of glass-reinforced hydroxyapatite composites (1999) J Biomed Mater Res, 45, pp. 370-375; Ferraz, M.P., Monteiro, F.J., Serro, A.P., Saramago, B., Gibson, I.R., Santos, J.D., Effect of chemical composition on hydrophobicity and zeta potential of plasma sprayed HA/CaO-P 2O 5 glass coatings (2001) Biomaterials, 22, pp. 3105-3112; Agathopoulos, S., Nikolopoulos, P., Wettability and interfacial interactions in bioceramic-body-liquid systems (1995) J Biomed Mater Res, 29, pp. 421-429; Agathopoulos, S., Nikolopoulos, P., Determination of the energy of the interactions between oxides and biological liquids (1995) Fourth Euro ceramics, 8, pp. 319-324. , A. Ravaglioli; Wang, L., Sigmund, W., Aldinger, F., Systematic approach for dispersion of silicon nitride powder in organic media: I, surface chemistry of the powder (2000) J Am Ceram Soc, 4, pp. 691-696; Galassi, C., Bertoni, F., Water-based Si 3N 4 suspensions: Part I effect of processing routes on the surface chemistry and particle interactions (2000) J Mater Res, 1, pp. 155-163; Haynes, C.A., Norde, W., Globular proteins at solid/liquid interfaces (1994) Colloids Surf B: Biointerfaces, 2, pp. 517-566
Keywords: 3N; 4-bioglass composites; Adsorption; aqueous solution; article; Biocomposites; Biomaterials; body fluid; Body fluids; Bovinae; bovine serum albumin; cation; Cattle; ceramics; chemistry; conformation; Conformations; Contact angle; electrochemistry; enthalpy; entropy; glass; Glass ceramics; Hydrogen-Ion Concentration; hydrophilicity; liquid; methyl iodide; methylene iodide; pH; Physiological models; priority journal; Serum Albumin; Serum Albumin, Bovine; Si; Silicon compounds; silicon derivative; Silicon nitride; simulation; Support, Non-U.S. Gov't; Surface charge; Surface chemistry; Surface Properties; surface property; Surface tension; temperature; time; unclassified drug; Water; wettability; Wetting; Zeta potential

On combining classifiers using sum and product rules - Alexandre, L.A.; Campilho, A.C.; Kamel, M. (Pattern Recognition LettersPattern Recogn. Lett., 2001)
This paper presents a comparative study of the performance of arithmetic and geometric means as rules to combine multiple classifiers. For problems with two classes, we prove that these combination rules are equivalent when using two classifiers and the sum of the estimates of the a posteriori probabilities is equal to one. We also prove that the case of a two class problem and a combination of two classifiers is the only one where such equivalence occurs. We present experiments illustrating the equivalence of the rules under the above mentioned assumptions. © 2001 Elsevier Science B.V. All rights reserved.
Cited By (since 1996): 51Export Date: 21 November 2012Source: Scopusdoi: 10.1016/S0167-8655(01)00073-3Language of Original Document: EnglishCorrespondence Address: Alexandre, L.A.; INEB-Inst. de Engenharia Biomedica, Rua Dr. Roberto Frias s/n, Porto 4200-465, Portugal; email: lfbaa@noe.ubi.ptReferences: Alexandre, L., Campilho, A., Kamel, M., Combining independent and unbiased classifiers using weighted average (2000) Proc. 15th Internat. Conf. on Pattern Recognition, 2. , IEEE Press, Barcelona, Spain;Bishop, C., (1995) Neural Networks for Pattern Recognition, , Oxford University Press, Oxford; Blake, C., Keogh, E., Merz, C., (1998) UCI Repository of Machine Learning Databases, , http://www.ics.uci.edu/~mlearn/MLRepository.html; Demuth, H., Beale, M., (1998) Neural Network Toolbox User's Guide, , The MathWorks, Inc; Hansen, L., Salamon, P., Neural network ensembles (1990) IEEE Trans. PAMI, 12 (10), pp. 993-1001; Hashem, S., Optimal linear combinations of neural networks (1997) Neural Networks, 10 (4), pp. 599-614; Kittler, J., Hatef, M., Duin, R., Combining classifiers (1996) Proc. Internat. Conf. on Pattern Recognition'96; Kittler, J., Hatef, M., Duin, R., Matas, J., On combining classifiers (1998) IEEE Trans. PAMI, 20 (3), pp. 226-239; Opitz, D., Maclin, R., Popular ensemble methods: An empirical study (1999) J. Artif. Intell. Res, 11, pp. 169-198; Richard, M., Lippmann, R., Neural network classifiers estimate Bayesian a posteriori probabilities (1991) Neural Comput, 3, pp. 461-483; Rogova, G., Combining the results of several neural network classifiers (1994) Neural Networks, 7 (5), pp. 777-781; Tax, D., Duin, R., Breukelen, M., Comparison between product and mean classifier combination rules (1997) Workshop on Statistical Techniques in Pattern Recognition, , Prague Czech Republic; Ueda, N., Optimal linear combination of neural networks for improving classification performance (2000) IEEE Trans. PAMI, 22 (2), pp. 207-215
Keywords: artificial neural network; Classification; Classifier fusion; Combinatorial mathematics; Combining classifiers; Equivalence classes; Estimation; K nearest-neighbours; Multiple classifiers; Neural networks; Pattern recognition; probability

Comparative effects of nacre water-soluble matrix and dexamethasone on the alkaline phosphatase activity of MRC-5 fibroblasts - Almeida, M.J.; Pereira, L.; Milet, C.; Haigle, J.; Barbosa, M.; Lopez, E. (Journal of Biomedical Materials ResearchJ. Biomed. Mater. Res., 2001)
In this study we demonstrate, for the first time, that dexamethasone and BMP-2 stimulated alkaline phosphatase (ALP) activity in MRC-5 fibroblasts, a cell line derived from human fetal lung. Previously we reported that the water-soluble matrix (WSM) of nacre obtained from the inner shell layer of the oyster Pinctada maxima, promoted an increase in ALP activity that was dose-dependent. In this work, we show that the effect of WSM is also time-dependent. As a comparison, the effect of WSM was also tested in bone marrow stromal cells because marrow and other bone surface-derived osteoblast stem cells have the inherent direct potential for osteogenesis. WSM promotes cell proliferation and ALP activity when tested with bone marrow cells in concentrations between 135 and 540 μg protein/mL. The effect of WSM on ALP activity of bone marrow stromal cells is similar to that obtained by dexamethasone. These results imply that MRC-5 fibroblasts respond to differentiating factors that promote osteoblastic phenotype in bone-derived cell cultures. © 2001 John Wiley & Sons, Inc.
Cited By (since 1996): 20Export Date: 21 November 2012Source: ScopusCODEN: JBMRBdoi: 10.1002/1097-4636(200111)57:2<306::AID-JBM1172>3.0.CO;2-HPubMed ID: 11484195Language of Original Document: EnglishCorrespondence Address: Lopez, E.; Lab. de Physiol. Gen. et Comparee, UMR CNRS 8572, Museum National d'Histoire Naturelle, 7 rue Cuvier, 75231 Paris Cedex 05, France; email: lopez@mnhn.frChemicals/CAS: Alkaline Phosphatase, EC 3.1.3.1; BMP2 protein, human; Bmp2 protein, rat; bone morphogenetic protein 2; Bone Morphogenetic Proteins; Dexamethasone, 50-02-2; Glucocorticoids; Transforming Growth Factor betaReferences: Lopez, E., Vidal, B., Berland, S., Camprasse, S., Camprasse, G., Silve, C., Demonstration of the capacity of nacre to induce bone formation by human osteoblasts maintained in vitro (1992) Tissue Cell, 24, pp. 667-679;Lopez, E., Berland, S., Le Faou, A., Nacre, osteogenic and osteoinductive properties (1994) Bull Inst Océan Monaco, 14, pp. 49-57; Silve, C., Lopez, E., Vidal, B., Smith, D.C., Camprasse, S., Camprasse, G., Couly, G., Nacre initiates biomineralization by human osteoblasts maintained in vitro (1992) Calcif Tissue Int, 51, pp. 363-369; Atlan, G., Balmain, N., Berland, S., Vidal, B., Lopez, E., Reconstruction of human maxillary defects with nacre powder: Histological evidence for bone regeneration (1997) C R Acad Sci III, 320, pp. 253-258; Atlan, G., Delattre, O., Berland, S., Le Faou, A., Nabias, G., Cot, D., Lopez, E., Interface between bone and nacre implants in sheep (1999) Biomaterials, 20, pp. 1017-1022; Lamghari, M., Almeida, M.J., Berland, S., Huet, H., Laurent, A., Milet, C., Lopez, E., Stimulation of bone marrow cells and bone formation by nacre: In vivo and in vitro studies (1999) Bone, 25 S, pp. 91S-94S; Westbroek, P., Marin, F., A marriage of bone and nacre (1998) Nature, 392, pp. 861-862; Le Faou, A., Berland, S., Lallier, F., Lopez, E., Osteoinductive effects induced by nacre implanted in subcutaneous pouches in rat (1995) Calcif Tissue Int, 56 A, p. 156; Le Faou, A., Berland, S., Lallier, F., Lopez, E., Local regulation of the osteoinductive process induced by nacre in connective tissues (1996) Ann Endoc, 57 (SUPPL. 4A), p. 75; Aubin, J.E., Liu, F., Malaval, L., Gupta, A.K., Osteoblast and chondroblast differentiation (1995) Bone, (SUPPL. 2), pp. S77-S83; Huggins, C.B., Urist, M.R., Dentin matrix transformation: Rapid induction of alkaline phosphatase and cartilage (1970) Science, 167, pp. 896-897; Reddi, A.H., Huggins, C.B., Biochemical sequences in the transformation of normal fibroblasts in adolescent rats (1972) Proc Natl Acad Sci USA, 69, pp. 1601-1605; Glowacki, J., Mulliken, J.B., Demineralized bone implants (1985) Clin Plast Surg, 12 (2), pp. 233-241; Katagiri, T., Yamaguchi, A., Ikeda, T., Yoshiki, S., Wozney, J.M., Rosen, V., Wang, E.A., Suda, T., The nonosteogenic mouse pluripotent cell line, C3H10T1/2, is induced to differentiate into osteobtastic cells by recombinant human bone morphogenetic protein-2 (1990) Biochem Biophys Res Commun, 172, pp. 295-299; McCulloch, C.A.G., Tenenbaum, H.C., Dexamethasone induces proliferation and terminal differentiation of osteogenic cells in tissue culture (1986) Anat Rec, 215, pp. 397-402; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., Physiological concentrations of glucocorticoids stimulate formation of bone nodules from isolated rat calvaria cells in vitro (1987) Endocrinology, 121, pp. 1985-1992; Bellows, C.G., Aubin, J.E., Determination of numbers of osteoprogenitors present in isolated fetal calvarial cells in vitro (1989) Dev Biol, 133, pp. 8-13; Bhargava, U., Bar-Lev, M., Bellows, C.G., Aubin, J.E., Ultrastructural analyses of bone nodules formed in vitro by isolated fetal rat calvaria cells (1988) Bone, 9, pp. 155-163; Wiren, K.M., Rodan, G.A., Dissociation between the effects of glucocorticosteroids on cell spreading and phenotypic expression (1985) The chemistry and biology of mineralized tissues, pp. 320-325. , Butler WT, editor. Birmingham, AL: EBSCO Media; Kasugai, S., Todescan, R., Nagata, T., Yao, K.-L., Butler, W.T., Sodek, J., Expression of bone matrix proteins associated with mineralized tissue formation by adult rat bone marrow cells in vitro: Inductive effects of dexamethasone on the osteoblastic phenotype (1991) J Cell Physiol, 147, pp. 111-120; Chen, T.L., Bates, R.L., Dudley, A., Hammonds, R.G., Amento, E.P., Bone morphogenetic protein-2b stimulation of growth and osteogenic phenotypes in rat osteobtast-like cells: Comparison with TGF-β1 (1991) J Bone Miner Res, 6, pp. 1387-1393; Hiraki, Y., Inoue, H., Shigeno, C., Sanma, Y., Bentz, H., Rosen, D.M., Asada, A., Suzuki, F., Bone morphogenetic proteins (BMP-2 and BMP-3) promote growth and expression of the differentiated phenotype of rabbit chondrocytes and osteoblastic MC3T3-E1 cells in vitro (1991) J Bone Miner Res, 6, pp. 1373-1385; Rosen, V., Thies, R.S., The BMP proteins in bone formation and repair (1992) Trends Genet, 8, pp. 97-102; Thies, R.S., Bauduy, M., Ashton, B.A., Kurtzberg, L., Wozney, J.M., Rosen, V., Recombinant human bone morphogenetic protein-2 induces osteoblastic differentiation in W-20-17 stromal cells (1992) Endocrinology, 130, pp. 1318-1324; Urist, M.R., Iwata, H., Ceccotti, P.L., Dorfman, R.L., Boyd, S.D., McDowell, R., Chien, C., Bone morphogenesis in implants of insoluble bone gelatin (1973) Proc Natl Acad Sci USA, 70, pp. 3511-3515; Almeida, M.J., Milet, C., Peduzzi, J., Pereira, L., Haigle, J., Barthélemy, M., Lopez, E., The effect of water-soluble matrix fraction extracted from the nacre of Pinctada maxima on the alkaline phosphatase activity of cultured fibroblasts (2000) J Exp Zool, 288, pp. 327-334; Maniatopoulos, C., Sodek, J., Melcher, A.H., Bone formation in vitro by stromal cells obtained from bone marrow of young adult rats (1988) Cell Tissue Res, 254, pp. 317-330; Owen, M., Marrow stromal stem cells (1988) J Cell Sci, (SUPPL. 10), pp. 63-76; Triffitt, J.T., Initiation and enhancement of bone formation (1987) Acta Orthop Scand, 58, pp. 673-684; Triffitt, J.T., The stem cell of the osteoblast (1996) Principles of bone biology, pp. 39-50. , Bilezikian JP, Raisz LG, Rodan GA, editors. New York: Academic Press; Wharton, S.A., Hipkiss, A.R., Degradation of peptides and proteins of different sizes by homogenates of human MRC5 lung fibroblasts (1985) FEBS Lett, 184 (2), pp. 249-253; Harada, K., Oida, S., Sasaki, S., Chondrogenesis and osteogenesis of bone marrow-derived cells by bone-inductive factor (1988) Bone, 9, pp. 177-183; Tucker, R.F., Shipley, G.D., Moses, H.L., Growth inhibitor from BSC-1 cells closely related to platelet type β transforming factor (1984) Science, 226, pp. 705-707; Noda, M., Rodan, G.A., Type-β transforming growth factor inhibits proliferation and expression of alkaline phosphatase in murine osteoblast-like cells (1986) Biochem Biophys Res Commun, 140, pp. 56-65; Tintut, Y., Parhami, F., Boström, K., Jackson, S., Demer, L., cAMP stimulates osteoblast-like differentiation of calcifying vascular cells (1998) J Biol Chem, 273, pp. 7547-7553; Rickard, D.J., Sullivan, T.A., Shenker, B.J., Leboy, P.S., Kazhdan, I., Induction of rapid osteoblast differentiation in rat bone marrow stromal cell cultures by dexamethasone and BMP-2 (1994) Dev Biol, 161, pp. 218-228; Coelho, M.J., Fernandes, M.H., Human bone cell cultures in biocompatibility testing. Part II. Effect of ascorbic acid, β-glycerophosphate and dexamethasone on osteoblastic differentiation (2000) Biomaterials, 21, pp. 1095-1102; Green, S., Chambon, P., A superfamily of potentially oncogenic hormone receptors (1986) Nature, 324, pp. 615-617; Grigoriadis, A.E., Heersche, J.N.M., Aubin, J.E., Differentiation of muscle, fat, cartilage and bone from progenitor cells present in a bone-derived clonal cell population: Effect of dexamethasone (1988) J Cell Biol, 106, pp. 2139-2151; Leboy, P.S., Beresford, J.N., Devlin, C., Owen, M.E., Dexamethasone induction of osteoblast mRNAs in rat marrow stromal cell cultures (1991) J Cell Physiol, 146, pp. 370-378; Guerriero V., Jr., Florini, J.R., Dexamethasone effects on myoblast proliferation and differentiation (1980) Endocrinology, 106, pp. 1198-1202; Maor, G., Silbermann, M., Supraphysiological concentrations of dexamethasone induce elevation of calcium uptake and depression of [ 3H]-thymidine incorporation into DNA in cartilage in vitro (1986) Calcif Tissue Int, 39, pp. 284-290; Urist, M.R., Bone morphogenetic protein in biology and medicine (1996) Bone morphogenetic proteins: Biology, biochemistry and reconstructive surgery, pp. 7-27. , Lindholm TS, editor. Austin, TX: RG Landes Company; Wozney, J.M., Rosen, V., Byrne, T., Celeste, A.J., Moutsatsos, I., Wang, E.A., Growth factor influencing bone development (1990) J Cell Sci, 97 (SUPPL. 13), pp. 149-156; Takuwa, Y., Ohse, C., Wang, E.A., Wozney, J.M., Yamashita, K., Bone morphogenetic protein-2 stimulates alkaline phosphatase activity and collagen synthesis in cultured osteoblastic cells, MC3T3 (1991) Biochem Biophys Res Commun, 174, pp. 96-101; Jortikka, L., Target cells and receptors for bone morphogenetic protein (1996) Bone morphogenetic proteins: Biology, biochemistry and reconstructive surgery, pp. 65-73. , Lindholm TS, editor. Austin, TX: RG Landes Company; Canalis, E., Centrella, M., Urist, M.R., Effect of partially purified bone morphogenetic protein on DNA synthesis and cell replication in calvarial and fibroblast cultures (1985) Clin Orthop, 198, pp. 289-294; Centrella, M., Casinghino, S., Kim, J., Pham, T., Rosen, V., Wozney, J., McCarthy, T.L., Independent changes in type I and type II receptors for transforming growth factor β induced by bone morphogenetic protein 2 parallel expression of the osteoblast phenotype (1995) Mol Cell Biol, 15, pp. 3273-3281; Vukicevic, S., Luyten, F.P., Redi, A.H., Stimulation of the expression of osteogenic and chondrogenic phenotypes in vitro by osteogenin (1989) Proc Natl Acad Sci USA, 86, pp. 8793-8797
Keywords: alkaline phosphatase; Animals; article; Biomedical engineering; BMP-2; Bone; bone development; bone marrow; Bone Marrow Cells; Bone morphogenetic proteins; Cell culture; Cell Line; cell proliferation; Cells; concentration response; dexamethasone; differentiation inducing factor; dose response; Dose-Response Relationship, Drug; enzyme activity; fibroblast; Fibroblasts; Glucocorticoids; human; human cell; Humans; male; MRC-5 fibroblasts; Nacre; natural product; osteoblast; Ostreidae; oyster; phenotype; Proteins; Pulmonary diseases; Rats; Rats, Wistar; Solubility; stroma cell; time; Time Factors; Transforming Growth Factor beta; unclassified drug; Water; Water-soluble matrix

Histological studies of double layer HA/CaO-P 2O 5 glass plasma sprayed coatings using Rabbit model - Ferraz, M.P.; Santos, J.D.; Afonso, A.; Vasconcelos, M.; Monteiro, F.J. (Key Engineering MaterialsKey Eng Mat, 2001)
The in vivo biological performance of a double layer HA/CaO-P 2O 5 glass and HA plasma sprayed coatings was assessed, using cylindrical implants that were placed in rabbits tibiae and histologically characterised after 2, 4, 8 and 16 weeks of implantation. For both types of coatings, long-term histological results indicated successful contact between implanted materials and bone, with organised new bone established at the interface. The main difference between the two coatings corresponded to the shorter implantation periods, where the composite coating induced faster osteointegration than HA coating. The faster formation of organised bone for composite coatings is discussed in terms of the presence of phase composition in the coatings structure.
Conference code: 57760Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Ferraz, M.P.; Instituto de Engenharia Biomedica, (INEB), Porto, PortugalReferences: Lacefield, W.R., (1988) Bioceramics: Material Characteristics Versus In Vivo Behaviour, pp. 72-80. , P. Ducheyne, J.E. Lemons. New York: New York Academy of Science Publishers;Klein, C.P.A.T., Wolke, J.G.C., De Blieck-Hogervorst, J.M.A., De Groot, K., (1994) J Biomed Mater Res, 28, pp. 961-967; Klein, C.P.A.T., Wolke, J.G.C., De Blieck-Hogervorst, J.M.A., De Groot, K., (1994) J Biomed Mater Res, 28, pp. 909-917; Burnie, J., Gilchrist, T., (1983) Ceramic in Surgery, pp. 169-176. , P. Vicenzini. Amsterdam: Elsevier Science Publishers; Ferraz, M.P., Fernandes, M.H., Trigo Cabrai, A., Santos, J.D., Monteiro, F.J., (1999) J Mater Sci Mater Med, 10 (9), pp. 567-576; Oonishi, H., Hench, L.L., Wilson, J., Sugihara, F., Tsuji, E., Kushitani, S., Iwak, H., (1999) J Biomed Mater Res, 44, pp. 31-43; Kitsugi, T., Nakamura, T., Oka, M., Senaha, Y., Got, T., (1996) J Biomed Mater Res, 30, pp. 261-269; Klein, C.P.A.T., Patka, P., Van Der Lubbe, H.B.M., Wolke, J.G.V., De Groot, K., (1991) J Biomed Mater Res, 25, pp. 53-65
Keywords: Bond strength (materials); Bone; Double layer coatings; hydroxyapatite; Implants (surgical); In vivo evaluation; Interfaces (materials); morphology; Phase composition; Phosphates; Plasma sprayed coatings; Rabbit model; Scanning electron microscopy; Sprayed coatings; X ray diffraction analysis

Silicon nitride - bioglass composite for biomedical applications - Santos, J.D.; Amaral, M.; Oliveira, S.M.; Lopes, M.A.; Silva, R.F. (Key Engineering MaterialsKey Eng Mat, 2001)
This study aimed at preparing novel highly toughened bioactive ceramic composite composed of Si 3N 4 matrix and Bioglass using a hot pressing technique. Densification rate, hardness and fracture toughness of this novel composite were assessed as well as in vitro bioactivity using a simulated body fluid (SBF). A fracture toughness of 5.2±0.3 MPa.m. 1/2 was achieved for fully densified samples, which complies with K 1c value reported for cortical bone. This novel composite, which can be used in high load medical applications, seems to overcome the drawback of low fracture toughness presented by most currently available bioactive ceramics.
Conference code: 57760Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: KEMAELanguage of Original Document: EnglishCorrespondence Address: Santos, J.D.; Universidade do Porto, Porto, PortugalReferences: Hench, L.L., Wilson, J., (1993) An Introduction to Bioceramics;(1995) Engineering Materials Handbook, Ceramics and Glasses, Asm International, 4, pp. 812-820; Fishman, G., Clare, A., Hench, L.L., (1995) Materials and Applications, 48; Niihara, K., Morena, R., Hasselman, D.P., (1982) J. Mater. Sci., 1, pp. 13-16; Hench, L.L., (1998) Bioceramics, J. Am. Ceram. Soc., 81 (7), pp. 1705-1728; Landis, W.J., Martin, J.R., (1984) J. Vac. Sci. Technol., A2, p. 1108
Keywords: Bioactive ceramic composite; Bioglass; Biomaterials; Body fluids; Bone; Ceramic matrix composites; cortical bone; Densification; Fracture toughness; Glass ceramics; Hot pressing; Medical applications; Silicon nitride; Simulated body fluid

Fetal heart rate baselines in twins: Interobserver agreement in antepartum estimation - Bernardes, J.; Costa-Pereira, A.; Calejo, L.; Ayres-de-Campos, D.; Patrício, B.; Pereira-Leite, L. (Journal of Reproductive Medicine for the Obstetrician and GynecologistJ. Reprod. Med. Obstet. Gynecol., 2000)
OBJECTIVE: To assess interobserver agreement in antepartum estimation of fetal heart rate (FHR) baselines in twins. STUDY DESIGN: Two residents and one specialist in obstetrics and gynecology, all with special interest in FHR monitoring, independently estimated baselines in 162 consecutive antepartum FHR tracings recorded in 24 twins. Tracings were obtained with a dual-channel fetal monitor for the simultaneous recording of both twins' heart rates. Baselines were estimated, as single values corresponding to the mean of the lowest stable FHR segment, in the absence of fetal movements and uterine contractions, within physiologic limits (110-150 beats per minute [bpm]). If these criteria were not met, the possibility of persistent bradycardia or tachycardia was considered, and if this was confirmed in a tracing with at least 40 minutes, a baseline < 110 or > 150 bpm was chosen. Interobserver agreement was assessed by the proportions of agreement (PA), kappa statistic (K) and intraclass correlation coefficient (ICCC), with 95% confidence intervals (CIs). RESULTS: Interobserver agreement was excellent, with a PA of 0.90 (95% CI: 0.89-0.91), K of 0.88 (95% CI: 0.84-0.92) and ICCC of 0.91 (95% CI: 0.88-0.94). CONCLUSION: Interobserver agreement in antepartum estimation of fetal heart rate baselines in twins was excellent with the baseline concept used in this study.
Cited By (since 1996): 2Export Date: 21 November 2012Source: ScopusCODEN: JRPMAPubMed ID: 10710739Language of Original Document: EnglishCorrespondence Address: Bernardes, J.; Depto. de Ginecologia e Obstetricia, Faculdade de Medicina do Porto, Al. Prof. Hernani Monteiro, 4200 Porto, Portugal; email: Jbernardes@mail.telepac.ptReferences: Sherman, S.J., Kovacs, B.W., Medearis, A.L., Nonstress test assessment of twins (1992) J Reprod Med, 37, pp. 804-808;Grant, J.M., The fetal heart rate is normal, isn't it?: Observer agreement of categorical assessments (1991) Lancet, 337, pp. 215-218; Cibils, L.A., On intrapartum fetal monitoring (1996) Am J Obstet Gynecol, 174, pp. 1382-1389; Bernardes, J., Costa-Pereira, A., Ayres-De-Campos, D., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynecol Obstet, 57, pp. 33-37; Bernardes, J., Costa-Pereira, A., Van Geijn, H.P., A more objective fetal heart rate baseline estimation (1996) Br J Obstet Gynaecol, 103, pp. 714-715; Bernardes, J., Ayres-De-Campos, D., Costa-Pereira, A., Objective computerized fetal heart rate analysis (1998) Int J Gynecol Obstet, 62, pp. 141-147; Bland, J.M., Altman, D.G., Statistical methods for assessing two methods of clinical measurement (1986) Lancet, 11, pp. 307-310; Armitage, P., Berry, G., (1994) Statistical Methods in Medical Research, pp. 273-276. , Oxford, Blackwell Science Ltd; Khan, K.S., Chien, P.F.W., Honest, M.R., Evaluating measurement variability of clinical investigations: The case of ultrasonic estimation of urinary bladder volume (1997) Br J Obstet Gynaecol, 104, pp. 1036-1043; Devoe, L.D., Carlton, E., Prescott, P., Neural network prediction of nonstress test results: How often should we perform nonstress tests? (1995) Am J Obstet Gynecol, 173, pp. 1128-1131; Bernardes, J., Ayres De Campos, D., Costa-Pereira, A., Baseline estimation in typical fetal heart rate patterns using different computerized methods (1997) Acta Obstet Gynecol Scand (Suppl), 76, p. 56;
Keywords: adult; article; clinical article; Electrocardiography; Female; Fetal heart rate; Fetal monitoring; fetus; fetus heart rate; fetus monitoring; Heart rate variability; Heart Rate, Fetal; human; Humans; Internship and Residency; observer variation; Obstetrics; Pregnancy; Prenatal Care; priority journal; Professional Competence; Twins

ECG noise filtering using wavelets with soft-thresholding methods - Agante Da Silva, P.M.G.; Marques De Sá, J.P. (Computers in CardiologyComput Cardiol, 1999)
In this paper we analyze algorithms for filtering white gaussian noise and 50 Hz power line noise from ECG signals. We used several wavelets to study their effect and efficiency in the filtering process. To deal with these different kinds of noises we used two distinct soft-thresholding techniques: the Donoho's statistical threshold estimator and a method developed by us. This last method exploits one of the wavelet processing main features: time-frequency relation. The de-noising methods led to good filtering results: noise reduction with only minor change of the ECG waveforms as confirmed by the high correlation values between the processed signal and the original one. These good results are due to a wavelet advantage over classical filtering - time-frequency relation - enabling the possibility of filtering noise in the same frequency band of the ECG signal with minimal interference.
Conference code: 56519Cited By (since 1996): 29Export Date: 21 November 2012Source: ScopusCODEN: COCADLanguage of Original Document: EnglishCorrespondence Address: Agante, P.M.; Inst Nacional de Engenharia, Biomedica, Oporto, PortugalReferences: Graps, A., An introduction to wavelets (1995) IEEE Computational Science and Engineering, 2 (2);Donoho, D.L., De-noising by soft-thresholding (1992) Symposium on Wavelet Theory, , Vanderbilt; Daubechies, I., The wavelet transform, time-frequency localization and signal analysis (1990) IEEE Transactions on Information Theory, 36 (5), pp. 961-1005; Chui, C.K., (1992) An Introduction to Wavelets, , Academic Press; Willems, J.L., CSE multilead atlas (1988) Common Standards for Quantitative Electrocardiography (European Concerted Action Project II.2.2), Div. Medical Informatics, , CSE Project Leader, Univ. Hosp. Gasthuisberg, Leuven; Coifman, R., Meyer, Y., Wickerhauser, V., Wavelet Analysis and Signal Processing, , ceres.math.yale.edu, Yale University, available by anonymous ftp at;
Keywords: Algorithms; Electrocardiography; Signal filtering and prediction; Signal interference; Wavelet denoising; White noise

Objective computerized fetal heart rate analysis - Bernardes, J.; Ayres-de-Campos, D.; Costa-Pereira, A.; Pereira-Leite, L.; Garrido, A. (International Journal of Gynecology and ObstetricsInt. J. Gynecol. Obstet., 1998)
Objective: To assess the validity of a computerized methodology for cardiotocogram analysis based on a recently described reproducible visual estimation of the baseline. Methods: Forty-two antepartum and 43 intrapartum cardiotocograms (CTGs) acquired by a personal computer were selected. Antepartum tracings were performed in the 48 h that preceded an elective cesarean section, and intrapartum tracings were performed until delivery. FHR baselines were estimated by an expert, according to an objective and reproducible methodology. Using these baselines, automated detection of accelerations and decelerations and estimation of variability was performed by the personal computer. A quantitative adaptation of the FIGO guidelines for fetal monitoring was used to classify tracings. Perinatal outcome was classified according to the Apgar score and umbilical arterial pH. Validity was then assessed by the proportions of agreement (PA), kappa statistic (κ), sensitivity and specificity, with 95% confidence intervals (95% CI). Cases showing a disagreement between CTG and perinatal classification were reviewed and an adjustment in baseline definition was tested. Results: The initial overall PA and κ between CTG and perinatal classification were, respectively, 0.79 (95% CI: 0.69-0.87) and 0.62 (95% CI: 0.41-0.83). The overall PA and κ, after baseline adjustment were, respectively, 0.89 (95% CI: 0.81-0.95) and 0.78 (95% CI: 0.58-0.98). Sensitivities and specificities ranged between 79% (95% CI: 60-92%) and 100% (95% CI: 95-100%). Conclusions: Good clinical prediction may be possible with an objective methodology for cardiotocogram analysis based on a recently described reproducible baseline estimation.
Cited By (since 1996): 23Export Date: 21 November 2012Source: ScopusCODEN: IJGOAdoi: 10.1016/S0020-7292(98)00079-4PubMed ID: 9749885Language of Original Document: EnglishCorrespondence Address: Bernardes, J.; Departmento Ginecologia Obstetricia, Faculdade Medicina-Hospital S. Joao, Porto, Portugal; email: sisporto@mail.telepac.ptReferences: Bernardes, J., Costa-Pereira, A., Ayres-De-Campos, D., Van Geijn, H.P., Pereira-Leite, L., Evaluation of interobserver agreement of cardiotocograms (1997) Int J Gynecol Obstet, 57 (1), pp. 33-37;Bernardes, J., Costa-Pereira, A., Van Geijn, H.P., Pereira-Leite, L., A more objective fetal heart rate baseline estimation (1996) Br J Obstet Gynaecol, 103, pp. 714-715; Grant, A., Principles for clinical evaluation of methods of perinatal monitoring (1984) J Perinat Med, 12, pp. 227-231; Bernardes, J., Moura, C., Marques-De-Sá, J.P., Pereira-Leite, L., Van Geijn, H.P., The Porto System (1994) A Critical Appraisal of Fetal Surveillance, pp. 315-324. , In: van Geijn HP, Copray FJA, editors. Amsterdam: Elsevier Science; Rooth, G., Huch, A., Huch, R., Guidelines for the use of fetal monitoring. FIGO news (1987) Int J Gynaecol Obstet, 25, pp. 159-167; Mohide, P., Grant, A., Evaluating diagnosis and screening during pregnancy and childbirth (1989) Effective Care in Pregnancy and Childbirth, pp. 66-80. , In: Chalmers I, Enkin M, Keirse M JNC, editors. Oxford University Press; Garcia-Romero, H., Garcia-Barrios, C., Ramos-Gutierrez, F.R., Effects of uncertain results on sensitivity and specificity of diagnostic tests (1996) Lancet, 348, pp. 1745-1746; Grant, J.M., The fetal heart rate is normal, isn't it?. Observer agreement of categorical assessments (1991) Lancet, 337, pp. 215-218; Guzman, E., Vintzileos, A., Martins, M., Benito, C., Houlihan, C., The efficacy of individual computer heart rate indices in detecting acidemia at birth in growth-restricted fetuses (1996) Obstet Gynecol, 87, pp. 969-974; Nielsen, P.V., Stigsby, B., Nickelsen, C., Nim, J., Computer assessment of the intrapartum cardiotocogram. II. The value of compared with visual assessment (1988) Acta Obstet Gynecol Scand, 67, pp. 461-464; Chung, T.K.H., Mohajer, M.P., Yang, Z.J., Chang, A.M.Z., Sahota, D.S., The prediction of fetal acidosis at birth by computerized analysis of intrapartum cardiotocography (1995) Br J Obstet Gynaecol, 102, pp. 454-460; Stigsby, B., Nielson, P.V., Nickelsen, C., Nim, J., Computer assessment of the intrapartum cardiotocogram. I. Methods of data reduction and diagnostic procedure (1988) Acta Obstet Gynecol Scand, 67, pp. 455-460
Keywords: Apgar score; arterial pH; article; Cardiotocography; cesarean section; computer analysis; Computerized analysis; Female; Fetal heart rate; fetus; fetus heart rate; fetus monitoring; Heart Rate, Fetal; human; Humans; Image Processing, Computer-Assisted; practice guideline; Predictive Value of Tests; Pregnancy; priority journal; umbilical artery; validity

Guided bone regeneration using osteopatite® granules and polytetrafluoroethylene membranes - Vasconcelos, M.; Afonso, A.; Branco, R.; Cavalheiro, J. (Journal of Materials Science: Materials in MedicineJ. Mater. Sci. Mater. Med., 1997)
Granules of a modified hydroxyapatite, Osteopatite®, were implanted in the right posterior tibiae of adult rabbits. We studied the extent of bone regeneration in bone holes. In the right tibiae, that were filled with granules of this biomaterial covered with a polytetrafluoroethylene (PTFE) membrane using, as a control, uncovered granules. In the left tibia, an empty hole was covered with PTFE membrane and a second hole was left empty to be used as a control. A histomorphometric study was carried out using light microscopy, four and eight weeks after the surgery. The covered granules presented a higher percentage of bone contact than the uncovered ones, and it was also possible to observe a better bone tissue organization, mainly produced by the immobilization action of the PTFE membrane. Empty bone defects covered with PTFE membranes, two months after implantation, presented large areas of Haversian bone and direct bone contact to the PTFE membrane.Granules of a modified hydroxyapatite, Osteopatite, were implanted in the right posterior tibiae of adult rabbits. We studied the extent of bone regeneration in bone holes. In the right tibiae, that were filled with granules of this biomaterial covered with a polytetrafluoroethylene (PTFE) membrane using, as a control, uncovered granules. In the left tibia, an empty hole was covered with PTFE membrane and a second hole was left empty to be used as a control. A histomorphometric study was carried out using light microscopy, four and eight weeks after the surgery. The covered granules presented a higher percentage of bone contact than the uncovered ones, and it was also possible to observe a better bone tissue organization, mainly produced by the immobilization action of the PTFE membrane. Empty bone defects covered with PTFE membranes, two months after implantation, presented large areas of Haversian bone and direct bone contact to the PTFE membrane.
Cited By (since 1996): 3Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1023/A:1018533217238Language of Original Document: EnglishCorrespondence Address: Vasconcelos, M.; Faculty of Dental Medicine, University of Porto, Rua Dr. Roberto Frias, 4200 Porto, PortugalTradenames: OsteopatiteReferences: Cavalheiro, J., Branco, R., Vasconcelos, M., (1991) Proceedings of the 4th International Conference on Bioceramics, p. 205. , edited by W. Bonfield, G. W. Hastings and K. E. Tanner, London, UK Butterworth-Heinemann, Oxford;Cavalheiro, J., Vasconcelos, M., Afonso, A., Peres, F., Branco, R., (1994) Stoma, 30, p. 15; Dahlin, C., Lekholm, U., Becker, W., Becker, B., Higuchi, K., Callens, A., Steenberghe, D., (1995) Int. J. Oral Maxillofac. Implants, 3, p. 312; Aughtun, M., Doz, P., Yildirim, M., Spiekermann, H., Biesterfeld, S., (1995) Int. J. Oral Maxillofac. Implants, 4, p. 421; Simion, M., Scarano, A., Gionso, L., Piattelli, A., (1995) Int. J. Oral Maxillofac. Implants, 3, p. 312; Afonso, A., Santos, J.D., Vasconcelos, M., Branco, R., Cavalheiro, J., (1996) J. Mater. Sci: Mater. Med., 7, p. 507; Jovanovic, S.A., Schenk, R.K., Orsini, M., Kenney, E.B., (1995) Int. J. Oral Maxillofac. Implants, 1, p. 27; Sander, L., Karring, T., (1995) J. Clin. Periodontol., 22, p. 295; Grevstad, H.J., Leknes, K.N., (1993) J. Clin. Periodontol., 20, p. 193; Piattelli, A., Scarano, A., Russo, P., Matarasso, S., (1996) Biomaterials, 17, p. 791
Keywords: animal experiment; Animalia; biomaterial; Bone; bone defect; Bone Regeneration; conference paper; controlled study; haversian canal; hydroxyapatite; Implants (surgical); microscopy; nonhuman; Optical microscopy; Oryctolagus cuniculus; Phosphate minerals; politef; Polymeric membranes; Polytetrafluoroethylenes; priority journal; rabbit; tibia

Structure development and control of injection-molded hydroxylapatite-reinforced starch/EVOH composites - Reis, R.L.; Cunha, A.M.; Allan, P.S.; Bevis, M.J. (Advances in Polymer TechnologyAdv Polym Technol, 1997)
This article reports on the development of novel composites of starch-based polymers reinforced with hydroxylapatite (HA). Two different grades of blends of starch and ethylene vinyl alcohol copolymers were reinforced with up to 30% (wt) of sintered and nonsintered HA. The initial compounding stage was carried out either in a rotating drum or by twin-screw extrusion (TSE). Compounds were injection molded using both conventional molding and a shear-controlled orientation in injection molding (Scorim) technique. It was possible to obtain composites with very good mechanical properties, approaching those of cortical bone. The best results were achieved for 30% sintered HA composites processed by TSE and Scorim, due to the in situ formation of HA fibers, and the development of molecular orientation and more compact microstructures in the moldings. This was confirmed by SEM analysis of the fracture surfaces, x-ray diffraction, and Raman spectroscopy. The biodegradability of the composites was also assessed and was found to be faster than that of the matrix. © 1997 John Wiley & Sons, Inc.
Cited By (since 1996): 53Export Date: 21 November 2012Source: ScopusCODEN: APTYDLanguage of Original Document: EnglishCorrespondence Address: Reis, R.L.; Dept. of Metallurgical Engineering, Faculty of Engineering, University of Porto, Rua dos Bragas, 4099 Porto Codex, PortugalReferences: Hayashi, T., (1994) Prog. Polym. Sci., 19, p. 663;Rokkanen, P.U., (1991) Ann. Med., 23, p. 109; Knowles, J.C., Hastings, G.W., (1992) J. Mater. Sci. Mater. Med., 3, p. 352; Adriano, K.P., Pohjonen, T., Tormalla, P., (1994) J. Appl. Biomater., 5, p. 133; Daniels, A.U., Andriano, K.P., Smutz, W.P., Chang, M.K.O., Heller, J., (1994) J. Appl. Biomater., 5, p. 51; Bastioli, C., Bellotti, V., Del Guidice, L., Gilli, G., (1993) J. Environ. Polym. Degrad., 1, p. 181; Griffin, G.J.L., (1994) Polym. Degrad. Stabil., 45, p. 241; Stepto, R.F.T., Tomka, I., (1987) Chimia, 41, p. 76; Bhattarcharya, M., Vaidya, U.R., Zhang, D., Narayan, R., (1995) J. Appl. Polym. Sci., 57, p. 539; Reis, R.L., Cunha, A.M., (1995) J. Mater. Sci. Mater. Med., 6, p. 786; Reis, R.L., Cunha, A.M., Allan, P.S., Bevis, M.J., (1996) J. Polym. Adv. Technol., 7, p. 784; Wang, M., Bonfield, W., Hench, L.L., (1995) Bioceramics 8, p. 383. , J. Wilson and L. L. Hench (Eds). Butterworth-Heinemann, New York; Verheyen, C.C.P.M., Wijn, J.R., Van Blitterswijk, C.A., De Groot, K., (1992) J. Biomedd. Mater. Res., 26, p. 1277; Verheyen, C.C.P.M., Klein, C.P.A.T., De Blieck-Hogervorst, J.M.A., Wolke, J.G.C., Van Blitterswijk, C.A., De Groot, K., (1993) J. Mater. Sci. Mater. Med., 4, p. 58; Higashi, S., Yamamuro, T., Nakamura, T., Ikada, Y., Hyon, S.H., Jamshidi, K., (1986) Biomaterials, 7, p. 183; Knowles, J.C., Hastings, G.W., (1993) J. Mater. Sci. Mater. Med., 4, p. 102; Oréfice, R.L., La Torre, G.P., West, J.K., Hench, L.L., (1995) Bioceramics 8, p. 409. , J. Wilson, and L. L. Hench (Eds)., Butterworth-Heinemann, New York; Allan, P.S., Bevis, M.J., British Patent 2170-140-B (1987)Allan, P.S., Bevis, M.J., (1987) Plast. Rubber Proc. Appl., 7, p. 3; Allan, P.S., Bevis, M.J., (1990) Comp. Manuf., 2, p. 79; Bastioli, C., Bellotti, V., Rallis, A., (1994) Rheol. Acta, 33, p. 307; Reis, R.L., Mendes, S.C., Cunha, A.M., Bevis, M.J., (1997) Polym. Int, 43, p. 347
Keywords: Biodegradation; Composition effects; Compounding (chemical); Copolymers; Extrusion molding; hydroxyapatite; Injection molding; Microstructure; Molecular orientation; Phosphate minerals; Polymer blends; Polyvinyl alcohols; Reinforced plastics; Rotating drum extrusion; Starch; Twin screw extrusion

Amino acid and metal content of Crassostrea gigas shell infested by Polydora sp. in the prismatic layer insoluble matrix and blister membrane - Almeida, M.J.; Moura, G.; MacHado, J.; Coimbra, J.; Vilarinho, L.; Ribeiro, C.; Soares-Da-Silva, P. (Aquatic Living ResourcesAquatic Living Resour., 1996)
The spionid polychaete Polydora sp. can live and reproduce inside the oysters' shell, excavating a U-shaped burrow the central portion of which is filled with detritus and particles of dissolved shell. The oyster responds by secreting an organic layer, confining the worm, and later covering it with calcitostracum. This process creates a characteristic "mud blister". Crassostrea gigas were analysed for the organic matrix amino acid content and 14 metals of the whole shell of normal oysters and severely Polydora infested ones. Amino acid, DOPA and FT-Raman analyses were also performed on isolated membranes from the characteristic mud blister and on prismatic layer insoluble matrix (PLIM) of infested oysters, with the aim of detecting any differences between the two organic matrices. Membranes and PLIM composition differ from whole normal shell organic matrix by having lower aspartate and glycine and higher levels of virtually all hydrophobic amino acids, especially alanine. There are no significant differences between membranes and PLIM in the ratio of charged to non-polar amino acids, respectively 0.54 and 0.59. L-DOPA content is also similar in the two matrices with 0.45 (±0.18) and 0.57 (±0.30) ng.mg
Cited By (since 1996): 5Export Date: 21 November 2012Source: ScopusCODEN: ALREELanguage of Original Document: EnglishCorrespondence Address: Almeida, M.J.; Laboratório de Fisiologia Aplicada, Instituto de Ciências Biomédicas Abel Salazar, 4050 Porto, PortugalReferences: Allen, J.A., Manganese deposition on the shell of living molluscs (1960) Nature, 185, pp. 336-337;Beedham, G.E., Repair of the shell in species of Anodonta (1965) Proc. Zool. Soc. London, 145, pp. 107-125; Boggess, R.K., Martin, R.B., Copper chelation by DOPA, epinephrine and other catechols (1975) J. Am. Soc. Chem., 97, pp. 3076-3081; Brown, C.H., (1975) Structural Materials in Animals, , Wiley, New York; Bubel, A., An electron microscope study of periostracum repair in Mytilus edulis (1973) Mar. Biol., 20, pp. 235-244; Carriker, M.R., Swann, C.P., Prezant, R.S., Counts, C.L., Chemical elements in the aragonitic and calcitic microstructural groups of shell of the oyster Crassostrea virginica: A proton probe study (1991) Mar. Biol., 109, pp. 289-297; Catherine, M., Blateau, D., Mazurié, J., Le Bec, C., (1990) Anomalies des Coquilles D'huîtres Creuses Crassostrea Gigas Observées sur le Littoral Français en Mai-juin 1989, Dues au ver Polydora et aux Peintures Antisalissures., pp. 13-14. , Rapp. Int. Dir. Ressources Vivantes, IFREMER Nantes; Degens, E.T., Spencer, D.W., Parker, R.H., Paleobiochemistry of Molluscan shell proteins (1967) Comp. Biochem. Physiol., 79, pp. 553-579; Dorsett, D.A., The behavior of Polydora ciliata (Johnst.). Tube building and burrowing (1961) J. Mar. Biol. Assoc. U.K., 41, pp. 577-590; Felix, C.C., Sealy, R.C., Electron spin resonance characterization of radicals from 3-4-dihydroxyphenylalanine: Semiquinone anions and their metal chelates (1981) J. Am. Chem. Soc., 103, pp. 2831-2835; Galstoff, P.S., The American oyster Crassostrea virginica (Gmelin) (1964) Fish. Bull. U.S., p. 64; Gergely, A., Kiss, T., Coordination chemistry of L-DOPA and related ligands (1979) Met. Ions Biol. Syst., 9, pp. 143-172; Haigler, S., Boring mechanism of Polydora websteri inhabiting Crassostrea virginica (1969) Am. Zool., 9, pp. 821-828; Jones, G.M., Saleuddin, A.S.M., Cellular mechanisms of periostracum formation in Physa spp. (Mollusca: Pulmonata) (1978) Can. J. Zool., 56, pp. 2299-2311; Kawaguchi, T., Watabe, N., The organic matrices of the shell of the American oyster Crassostrea virginica Gmelin (1993) J. Exp. Mar. Biol. Ecol., 170, pp. 11-28; Kawaguti, S., Ikemoto, N., Electron microscopy on the mantle of a bivalve Musculus senhousia, during regeneration of shell (1962) Biol. J. Okayama Univ., 8, pp. 31-42; Krampitz, G., Drolshagen, H., Hotta, S., Simultaneous binding of calcium and bicarbonate by conchiolin of oyster shells (1983) Experiemia, 39, pp. 1104-1105; Laukner, G., Diseases of Mollusca: Bivalvia (1983) Diseases of Marine Animals, Vol. II, Bivalvia to Scaphopoda, 2, pp. 477-978. , Biologische Anstalt Helgoland, O. Kinne ed. Hamburg; Levitt, M., A simplified representation of protein conformation for rapid simulation of protein folding (1976) J. Mol. Biol., 104, pp. 59-108; Linderstrom-Lang, K., Duspiva, F., Studies in enzymatic histochemistry. XVI. the digestion of keratin by larvae of clothes moth (Tineola biselliela Humm.) (1936) C. R. Trav. Lab. Carlsberg, Ser. Chim., 21, pp. 1-82; Lowry, O.H., Rosebrough, N.J., Farr, A.L., Randall, R.J., Protein determination with the Folin phenol reagent (1951) J. Biol. Chem., 193, pp. 265-275; Martius, K.V., Schwarzhans, K.E., Preparation of the Mn (II) complex with 3,4-dihydroxyphenylalanine (DOPA) (1978) Z Naturforsch., 33 B, p. 124; Meenaakshi, V.R., Hare, P.E., Watabe, N., Wilbur, K.M., The chemical composition of the periostracum of the molluscan shell (1969) Comp. Biochem. Physiol., 29, pp. 611-620; Nozaki, Y., Tanford, C., The solubility of amino acids and two glycyl peptides in aqueous ethanol and dioxane solutions (1971) J. Biol. Chem., 246, pp. 2211-2217; Saleuddin, A.S.M., Petit, H.P., The mode of formation and the structure of the periostracum (1983) The Mollusca, 4, pp. 199-234. , K. M. Wilbur ed. Academic Press, New York; Sato-Okoshi, W., Okoshi, K., Microstructure of scallop and oyster shells infested with boring Polydora (1993) Nippon Suisan Gakkaishi, 59, pp. 1243-1247; Segar, D.A., Collins, J.D., Riley, J.P., The distribution of the major and some minor elements in marine animals. Part II (1971) Molluscs. J. Mar. Biol. Assoc. U.K., 51, pp. 131-136; Swinehart, J.H., Smith, K.W., Iron and manganese deposition in the periostraca of several bivalve molluscs (1979) Biol. Bull., 156, pp. 369-381; Travis, D.F., Gonsalves, M., Comparative ultrastructure and organization of the prismatic region of two bivalves and its possible relation to the chemical mechanism of boring (1969) Am. Zool., 9, pp. 635-661; Tsujii, T., An electron microscopic study of the mantle epithelial cells of Anodonta sp. during shell regeneration (1976) The Mechanisms of Mineralization in the Invertebrates and Plants, pp. 339-353. , N. Watabe, K. M. Wilbur eds. Univ. South Carolina Press, Columbia; Vovelle, J., Sclérotisation et minéralisation des structures squellettiques chez les Mollusques (1974) Haliotis, 2, pp. 133-165; Waite, J.H., Evidence for the mode of sclerotization in a molluscan periostracum (1977) Comp. Biochem. Physiol., 58 B, pp. 157-162; Waite, J.H., Quinone-tanned scleroproteins (1983) The Mollusca, 1, pp. 467-504. , K. M. Wilbur ed. Academic Press, New York; Waite, J.H., Andersen, S.O., 3,4-dihydroxyphenyl-alanine in an insoluble shell protein of Mytilus edulis (1978) Biochem. Biophys. Acta, 541, pp. 107-114; Wheeler, A.P., Rusenko, K.W., Swift, D.M., Sikes, C.S., Regulation of in vitro and in vivo CaCO 3 crystallization by fractions of oyster shell organic matrix (1988) Mar. Biol., 98, pp. 71-80; Zottoli, R.A., Carriker, M.R., Burrow morphology, tube formation and microarchitecture of shell dissolution by the spionid polychaete Polydora websteri (1974) Mar. Biol., 27, pp. 307-316
Keywords: Amino acids; Crassostrea gigas; Metals; Polydora sp.; Shell organic matrix

Effects of Co-Cr corrosion products and corresponding separate metal ions on human osteoblast-like cell cultures - Tomás, H.; Carvalho, G.S.; Fernandes, M.H.; Freire, A.P.; Abrantes, L.M. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
The cytocompatibility of the degradation products of a Co-Cr orthopaedic alloy was investigated with particular focus on the dose-effect of an electrochemically dissolved alloy extract and of the corresponding separate metal ions on human osteogenic bone marrow derived cells. The extract solution contained 15ppm of Co and 8ppm of Cr as analysed by atomic absorption spectroscopy. Stock salt solutions of CoCl 2·6H 2O, CrCl 3·6H 2O and Na 2CrO 4 at corresponding concentrations were also prepared. Several dilutions of the above metallic solutions were tested for a period of 21 days on cells (third subculture) cultured in α-minimal essential medium containing foetal bovine serum and supplemented with antibiotics, dexamethasone ascorbic acid and β-glycerophosphate. The osteoblast response to the presence of metal ions was evaluated by several biochemical parameters: cell viability (MTT reduction by intracellular enzymes), alkaline phosphatase activity (an osteoblast marker) and protein production (both intracellular and extracellular). Co-Cr corrosion products showed opposite effects to their respective metal salts only on day 1. With time the different metal solutions presented a similar pattern of inhibition. These results suggest that impaired bone formation in vitro can occur in the presence of Co-Cr corrosion products. The cytocompatibility of the degradation products of a Co-Cr orthopaedic alloy was investigated with particular focus on the dose-effect of an electrochemically dissolved alloy extract and of the corresponding separate metal ions on human osteogenic bone marrow derived cells. The extract solution contained 15 ppm of Co and 8 ppm of Cr as analyzed by atomic absorption spectroscopy. Stock salt solutions of COCl 2·6H 2O, CrCl 3·6H 2O and Na 2CrO 4 at corresponding concentrations were also prepared. Several dilutions of the above metallic solutions were tested for a period of 21 days on cells (third subculture) cultured in α-minimal essential medium containing foetal bovine serum and supplemented with antibiotics, dexamethasone ascorbic acid and β-glycerophosphate. The osteoblast response to the presence of metal ions was evaluated by several biochemical parameters: cell viability (MTT reduction by intracellular enzymes), alkaline phosphatase activity (an osteoblast marker) and protein production (both intracellular and extracellular). Co-Cr corrosion products showed opposite effects to their respective metal salts only on day 1. With time the different metal solutions presented a similar pattern of inhibition. These results suggest that impaired bone formation in vitro can occur in the presence of Co-Cr corrosion products.
Cited By (since 1996): 22Export Date: 21 November 2012Source: ScopusCODEN: JSMMELanguage of Original Document: EnglishCorrespondence Address: Tomas, H.; Faculdade de Ciencias, Universidade de Lisboa, Campo Grande, C1, Piso 5, 1700 Lisboa, PortugalReferences: Pohler, O.E.M., (1983) Biomaterials in Reconstructive Surgery, p. 158. , C. V. Mosby, St. Louis;Black, J., Oppenheiner, P., Morris, R.O.M., Peduto, A.M., Clark, C.C., (1987) J. Biomed. Mater. Res., 21, p. 1213; Sunderman Jr., F.W., Hopfer, S.M., Swift, T., Rezuke, W.N., Ziebka, L., Highman, P., Edwards, B., Gossling, H.R., (1989) J. Orthop. Res., 7, p. 307; Traisnel, M., Maguer, D., Hildebrand, H.F., (1990) Clin. Mater., 5, p. 309; Moore Jr., R.M., Hamburger, S., Jeng, L.J., Hamilton, P.M., (1991) J. Appl. Biomater., 2, p. 127; Henning, E.F., Raithel, H.J., Schaller, K.H., Dòhler, J.R., (1992) J. Trace Elem. Electrolytes Health Dis., 6, p. 239; Brown, S.A., Zhang, K., Merritt, K., Payer, J.H., (1993) J. Biomed. Mater. Res., 27, p. 1007; Albore-Saavedra, J., Vuitch, F., Delgado, R., Wiley, E., Hagler, H., (1994) Amer. Surg. Pathol., 18, p. 83; Buechel, F.F., Drucker, D., Jasty, M., Jiranek, W., Harris, W., (1994) Clin. Orthop. Related Res., 298, p. 202; De Bruijn, J.D., (1993), p. 9. , PhD thesis, LeidenNasser, S., Campbell, P.A., Kilgus, D., Kossovsky, N., Amstutz, H.C., (1990) Clin. Orthop., 261, p. 171; Revell, P.A., Weightman, B., Freeman, M.A.R., Roberts, B.V., (1978) Arch. Orthop. Trauma Surg., 91, p. 167; Vilamitjana-Amedee, J., Bareille, R., Rouais, F., Caplan, A.I., Harmand, M.F., (1993) In Vitro Cell. Dev. Biol., 29 A, p. 699; Bizios, R., (1994) Biotechnol. Bioeng., 43, p. 582; Pizzoferrato, A., Ciapetti, G., Stea, S., Cenni, E., Arciola, C.R., Granchi, D., Savarino, L., (1994) Clin. Mater., 15, p. 173; Tomás, H., Freire, A.P., Abrantes, L.M., (1994) J. Mater. Sci. Mater. Med., 5, p. 446; Lowry, O.H., Rosebrough, N.J., Farr, A.L., Randall, R.J., (1951) J. Biol. Chem., 193, p. 256; Maniatopoulos, C., Sodek, J., Melcher, A.H., (1988) Cell Tissue Res., 254, p. 317; Berridge, M.V., Tan, A.S., (1993) Arch. Biochem. Biophys., 303, p. 474; Ciapetti, G., Cenni, E., Pratelli, L., Pizzoferrato, A., (1993) Biomaterials, 14, p. 359; Martin, A., Clynes, M., (1993) Cytotechnology, 11, p. 49; Carvalho, G.S., Castanheira, M., Diogo, I., Abreu, A.M., Sousa, J.P., Loon, J.A., Van Blitterswijk, C.A., J. Mater. Sci. Mater. Med., , in press; Gotoh, Y., Hiraiwa, K., Nagayama, M., (1990) Bone and Mineral, 8, p. 239; Bellows, C.G., Aubin, J.E., Heersche, J.N.M., (1991) Bone and Mineral, 14, p. 27
Keywords: Absorption spectroscopy; article; Atomic spectroscopy; Biocompatibility; Bone; Cell culture; Chromium alloys; Cobalt alloys; Corrosion; Corrosion resistance; Cytocompatibility; Enzyme inhibition; human; human cell; Human osteoblasts; Implants (surgical); Orthopaedic alloys; ossification; osteoblast; priority journal; surface property

Fracture toughness of hydroxyapatite reinforced with P 2O 5-CaO glasses containing Na 2O, K 2O and MgO - Silva, P.L.; Santos, J.D.; Knowles, J.C.; Silva, R.F.; Monteiro, F.J. (Transactions of the Annual Meeting of the Society for Biomaterials in conjunction with the International Biomaterials SymposiumTrans Annu Meet Soc Biomater Int Biomater Symp, 1996)
Calcium phosphate materials are widely used in biomedical applications but their poor strength and brittleness limit their use in load bearing applications. To improve their mechanical properties, hydroxyapatite (HA) ceramics were reinforced with P 2O 5-CaO based glasses with additions of Na 2+, Mg 2+ and K + oxides. A composite chemical composition that approaches the inorganic part of bone chemical composition was obtained using HA with calcium phosphate-based glasses. Fracture toughness was significantly enhanced by glass additions, and the decrease in fracture toughness at 1300 and 1350 °C was attributed to grain growth since it significantly increased with sintering temperature.
Conference code: 45651Export Date: 21 November 2012Source: ScopusCODEN: TAMSELanguage of Original Document: EnglishCorrespondence Address: Silva, P.L.; INEB, Porto, Portugal
Keywords: Biomaterials; Bone; Composition effects; Fracture toughness; glass; Grain growth; hardness; Hydroxyapatites; Lime; Magnesia; Phosphate minerals; Potassium compounds; Sodium compounds; Thermal effects

Granules of osteoapatite and glass-reinforced hydroxyapatite implanted in rabbit tibiae - Afonso, A.; Santos, J.D.; Vasconcelos, M.; Branco, R.; Cavalheiro, J. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
Granules of a modified hydroxyapatite, glass-reinforced hydroxyapatite composite and commercial hydroxyapatite were implanted in rabbit tibiae. Histological studies were carried out after 1 and 2 months implantation periods using light and fluorescence microscopy. A much higher percentage of bone contact was developed for both the glass-reinforced hydroxyapatite composite and the modified hydroxyapatite when compared to commercial hydroxyapatite (89-91% versus 66%) after 2 months implantation. The mechanism of bone formation and growth around implants is discussed in terms of the influence of elements incorporated into these novel materials which are commonly found in bone tissues, such as Na, K and Mg, and the presence of a soluble β-tricalcium phosphate phase in the microstructure of the composite.
Cited By (since 1996): 16Export Date: 21 November 2012Source: ScopusCODEN: JSMMELanguage of Original Document: EnglishCorrespondence Address: Afonso, A.; Faculty of Dental Medicine, University of Porto, Rua Dr Roberto Frias, 4200 Porto, PortugalChemicals/CAS: calcium phosphate, 10103-46-5, 13767-12-9, 14358-97-5, 7758-87-4; hydroxyapatite, 1306-06-5, 51198-94-8; magnesium, 7439-95-4; potassium, 7440-09-7; sodium, 7440-23-5References: Ravaglioli, A., Krajewski, A., (1992) Bioceramics-materials, Properties and Applications, p. 100. , Chapman & Hall, London;Cranin, A.N., Ronen, E., Puntoff, R.S.H., Tobim, G., Dibeling, J.B., (1988) J. Biomed. Mater. Res., 22, p. 1165; De Groot, K., Klein, C.P.A.T., (1990) "Handbook of Bioactive Ceramics", Vol. II-Calcium Phosphate and Hydroxylapatite Ceramics, 2, p. 3. , edited by T. Yamamuro CRC Press, Boston; Hollinger, J.O., Schmitz, J.P., Mizgala, J.W., Hassler, C., (1989) J. Biomed. Mater. Res., 23, p. 17; Cavalheiro, J., Branco, R., Vasconcelos, M., (1991) Proceedings of the 4th International Conference on Bioceramics, p. 205. , edited by W. Bonfield, G. W. Hastings and K. E. Tanner, London, UK Butterworth-Heinemann, Oxford; Santos, J.D., Reis, R.L., Knowles, J.C., Monteiro, F.J., Hastings, G.W., (1994) Biomaterials, 15, p. 5; Nery, E.B., Legeros, R.Z., Lynch, K.L., Kalbleisch, J., (1988) J. Dent. Res., 67, p. 178; Ellinger, R.F., Nery, E.B., Lynch, K.L., (1986) Int. J. Period. Restor. Dent., 3, p. 223; Legeros, R.Z., Daculsi, G., (1990) "Handbook of Bioactive Ceramics", Vol. II-Calcium Phosphate and Hydroxylapatite Ceramics, 2, p. 17. , edited by T. Yamamuro CRC Press, Boston
Keywords: animal experiment; animal tissue; article; Bone; Bone formation; bone growth; Calcium Compounds; calcium phosphate; Composite materials; Fiber reinforced materials; glass; Glass fibers; Glass reinforced hydroxyapatite; Granular materials; histology; hydroxyapatite; implant; Implants (surgical); Magnesium; Microstructure; Modified hydroxyapatite; nonhuman; Optical microscopy; ossification; Osteoapatite; Oxides; Phosphates; Physiological models; potassium; priority journal; rabbit; Rabbit tibiae; Sodium; tibia; X ray diffraction analysis

Histological evaluation of two bioactive cements - Vasconcelos, M.; Afonso, A.; Branco, R.; Planell, J.; Driessens, F.; Cavalheiro, J. (Transactions of the Annual Meeting of the Society for Biomaterials in conjunction with the International Biomaterials SymposiumTrans Annu Meet Soc Biomater Int Biomater Symp, 1996)
Two bioactive bone cements were compared with poly(methylmethacrylate) (PMMA) cement. Cement A was prepared from precipitated hydroxyapatite and tricalcium phosphate, using an aqueous solution of Na 2HPO 4. Cement B was prepared by crushing a bioactive glass composed of SiO 2, CaO, P 2O 5 and Na 2O. The powder was mixed with NH 4H 2PO 4/(NH 4) 2 PO 4 aqueous solution buffered at pH = 7.4. The bioactive cements exhibited different in vivo behaviors but both performed better than PMMA cement.
Conference code: 45651Export Date: 21 November 2012Source: ScopusCODEN: TAMSELanguage of Original Document: EnglishCorrespondence Address: Vasconcelos, M.; INEB-Inst Eng. Biomedica, Porto, Portugal
Keywords: Bioactive bone cements; bone cement; glass; hydroxyapatite; Ion exchange; Lime; pH; Phosphate minerals; Polymethyl methacrylates; Silica; Sodium compounds; Solutions; Sorption; Tricalcium phosphate

Inhibition and stimulation of enzymatic activities of human fibroblasts by corrosion products and metal salts - Carvalho, G.S.; Castanheira, M.; Diogo, I.; Abreu, A.M.; Sousa, J.P.; Loon, J.A.; Van Blitterswijk, C.A. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1996)
Fibroblasts from normal human skin were cultured for a period of 21 days in the absence or in the presence of metal ions. The effects of stainless steel (SS) corrosion products were compared to the effects of iron, chromium and nickel ions used either separately (Fe, Cr, or Ni solutions) or combined (Fe+Cr+Ni solution). At several periods of time (4, 7, 14 and 21 days) the cell cultures were analysed for the following parameters: (a) metal ion accumulation by atomic absorption spectrometry; (b) cell morphology and viability by the neutral red assay; (c) cell proliferation by DNA assessment, and enzyme activity by both (d) MTT reduction and (e) acid phosphatase activity. Results showed that SS-corrosion products and the corresponding metal ions combined at the same concentrations, Fe+Cr+Ni solution, had opposite effects on fibroblast cultures. In fact, SS-corrosion products caused no apparent effects on cell morphology nor on cell proliferation whereas Fe+Cr+Ni solution stimulated both neutral red uptake and cell proliferation. The enzymatic assays showed that SS-corrosion products caused inhibition of both MTT reduction and acid phosphatase activity in contrast to Fe+Cr+Ni solution which stimulated their activity. Furthermore, in all biological parameters studied, a strong association was observed between the effects of Fe+Cr+Ni solution and Cr alone, suggesting that Cr was the metal ion mostly involved in the stimulatory effects of the combined solution.Fibroblasts from normal human skin were cultured for 21 days in the absence, or presence, of metal ions. The effects of stainless steel (SS) corrosion products were compared to the effects of iron, chromium, and nickel ions used either separately or combined. At different periods of time, the cell cultures were analyzed for the following parameters: metal ion accumulation by atomic absorption spectrometry; cell morphology and viability by the neutral red assay; cell proliferation by DNA assessment; and enzyme activity by both MTT reduction and acid phosphatase activity. Results show that SS-corrosion products and the corresponding metal ions combined at the same concentrations, Fe+Cr+Ni solution, have opposite effects on fibroblast cultures.
Cited By (since 1996): 9Export Date: 21 November 2012Source: ScopusCODEN: JSMMELanguage of Original Document: EnglishCorrespondence Address: Carvalho, G.S.; INEB-Instituto Engenharia Biomedica, Portugal Universidade do Minho, Praca Coronel Pacheco, 1, 4000 Porto, PortugalChemicals/CAS: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide, 298-93-1; acid phosphatase, 9001-77-8, 9025-88-1; chromium, 16065-83-1, 7440-47-3; DNA, 9007-49-2; iron, 14093-02-8, 53858-86-9, 7439-89-6; neutral red, 553-24-2; nickel, 7440-02-0; stainless steel, 12597-68-1References: Pohler, O.E.M., (1983) Biomaterials in Reconstructive Surgery, p. 158. , C.V. Mosby, St. Louis;Galante, J.O., Lemons, J., Spector, M., Wilson Jr., P.D., Wright, T.M., (1991) J. Orthop. Res., 9, p. 760; Henning, E.F., Raithel, H.J., Schaller, K.H., Döhler, J.R., (1992) J. Trace Elem. Electrolytes Health Dis., 6, p. 239; Maloney, W.J., Smith, R.L., Castro, F., Schurman, J., (1993) J. Bone Joint Surg., 75 A, p. 835; Jorgensen, T.J., Munno, F., Mitchell, T.G., Hungerford, D., (1983) Clin. Orthop., 176, p. 124; Jones, L.C., Hungerford, D.S., (1987) Trans Orthop. Res. Soc., 32, p. 317; Stulberg, B.N., Watson, J.T., Shull, S.L., Merritt, K., Crowe, T.D., Stulberg, S.D., Guidry, C.H., (1987) Trans Orthop. Res. Soc., 33, p. 314; Sunderman Jr., F.W., Hopfer, S.M., Swift, T., Rezuke, W.N., Ziebka, L., Highman, P., Edwards, B., Gossling, H.R., (1989) J. Orthop. Res., 7, p. 307; Merritt, K., Brown, S.A., Sharkey, N.A., (1984) J. Biomed. Mater. Res., 18, p. 991; Brown, S.A., Farnsworth, L.J., Merritt, K., Crowe, T.D., (1988) Biomed. Mater. Res., 22, p. 321; Merritt, K., Crowe, T.D., Brown, S.A., (1989) J. Biomed. Mater. Res., 23, p. 845; Merritt, K., Margevicius, R.W., Brown, S.A., (1992) J. Biomed. Mater. Res., 26, p. 1503; Brown, S.A., Zhang, K., Merritt, K., Payer, J.H., (1993) J. Biomed. Mater. Res., 27, p. 1007; Pereira, M.L., Silva, A., Tracana, R., Carvalho, G.S., (1994) Cytobios, 77, p. 73; Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci. Mater. Med., 6, p. 523; Tracana, R.B., Pereira, M.L., Abreu, A.M., Sousa, J.P., Carvalho, G.S., (1995) J. Mater. Sci. Mater. Med., 6, p. 56; Bravo, I., Sousa, S.R., Carvalho, G.S., Barbosa, M., (1992) Advances in Biomaterials, p. 7. , edited by P. J. Doherty et al. Elsevier, Amsterdam; Vrouwenvelder, W.C.A., Groot, C.G., DeGroot, K., (1993) J. Biomed. Mater. Res., 27, p. 465; Ciapetti, G., Cenni, E., Pratelli, L., Pizzoferrato, A., (1993) Biomaterials, 14, p. 359; Martin, A., Clynes, M., (1991) In Vitro Cell. Dev. Biol., 27 A, p. 183; Borenfreund, E., Puerner, J.A., (1983) J. Tissue Culture Methods, 9, p. 7; Hansen, M.B., Nielsen, S.E., Berg, K., (1989) J. Immunol. Methods, 119, p. 203; Rosdy, M., Grisoni, B., Claus, L.C., (1991) Biomaterials, 12, p. 511; Van Sliedregt, A., Radder, A.M., De Groot, K., Van Blitterswijk, C.A., (1992) J. Mater. Sci. Mater. Med., 3, p. 365; Caughman, W.F., Caughman, G.B., Shiflett, R.A., Rueggeberg, F., Schuster, G.S., (1991) Biomaterials, 12, p. 737; Carvalho, G.S., Bravo, I., (1993) J. Mater. Sci. Mater. Med., 4, p. 366; Harmand, M.F., Bordenave, L., Bareille, R., Naji, A., Jeandot, R., Rouais, F., Ducassou, D., (1991) J. Biomater. Sci. Polymer Edn., 2, p. 67; Katz, A., Feldman, M., Eisenbach, L., (1992) J. Immunol. Methods, 149, p. 117; Naji, A., Harmand, M.F., (1990) J. Biomed. Mater. Res., 24, p. 861; Mosmann, T., (1983) J. Immunol. Methods, 65, p. 55; Berridge, M.V., Tan, S., (1993) Arch. Biochem. Biophys., 303, p. 474
Keywords: 3 (4,5 dimethyl 2 thiazolyl) 2,5 diphenyltetrazolium bromide; Absorption spectroscopy; Acid phosphatase; article; atomic absorption spectrometry; Atomic spectroscopy; Bioassay; Cell culture; Cell morphology; cell proliferation; cell structure; cell viability; Chromium; controlled study; Corrosion; Corrosion products; cytology; DNA; Enzymatic assays; Enzyme Activation; enzyme activity; Enzyme inhibition; fibroblast; human; human cell; Ions; Iron; metal; Metal ion accumulation; Metal salts; Metals; neutral red; Nickel; priority journal; Salts; Skin; skin fibroblast; Stainless steel; Steel corrosion

Mechanical behavior of injection-molded starch-based polymers - Reis, R.L.; Cunha, A.M.; Allan, P.S.; Bevis, M.J. (Polymers for Advanced TechnologiesPolym. Adv. Technol., 1996)
This work evaluates the mechanical performance of injection-molded starch-based copolymers, 60/40 (mol/ mol) starch/poly(ethylene vinyl alcohol), and the possibility of improving material properties through deliberately induced anisotropy during processing. Different types of samples were produced by conventional and shear-controlled injection molding (Scorim) and tested under tensile and impact loading. The behavior of three distinct grades is discussed in terms of the respective fracture morphology (evaluated by scanning electron microscopy). A comparison is made between the behavior of conventional and Scorim samples. The results show that the mechanical properties of the materials used were significantly improved by the employment of the Scorim process. The stiffness values of the conventional moldings were doubled, without reducing the ductility of the polymer. The impact data showed a material sensitivity, and consequent loss of properties, to the localized shear imposed to the melt during processing. This situation is attributed to very narrow mold gates (in the case of pingated systems) and leads to much reduced impact performance.
Cited By (since 1996): 58Export Date: 21 November 2012Source: ScopusLanguage of Original Document: EnglishCorrespondence Address: Reis, R.L.; Dept. of Metallurgical Engineering, FEUP, Rua dos Bragas, 4099 Porto Codex, PortugalReferences: Rokkanen, P.U., (1991) Ann. Med., 23, p. 109;Danniels, A.U., Adriano, K.P., Smutz, W.P., Chang, M.K.O., Heller, J., (1994) J. Appl. Biomater., 5, p. 51; Baumgart, F.W., Perren, S.M., (1994) Clinical and Laboratory Performance of Bone Plates, p. 42. , J. P. Harvey and R. F. Games, eds., ASTM STP1217, Philadelphia; Knowles, J.C., Hastings, G.W., (1992) J. Mater. Sci.: Mater. Med., 3, p. 352; Knowles, J.C., Hastings, G.W., (1993) J. Mater. Sci.: Mater. Med., 4, p. 102; Bastioli, C., Bellotti, V., Del Guidice, L., Gilli, G., (1993) J. Environ. Polym. Degr., 1, p. 181; Yoshida, Y., Uemura, T., (1994) Biodegradable Plastics and Polymers, p. 443. , Y. Doi and K. Fukuda, eds, Elsevier Science, Tokyo; Bastioli, C., Bellotti, V., Camia, M., Del Giudice, L., Rallis, A., (1994) Biodegradable Plastics and Polymers, p. 200. , Y. Doi and K. Fukuda, eds, Elsevier Science, Tokyo; Allan, P.S., Bevis, M.J., British Patent 2170-140-BAllan, P.S., Bevis, M.J., (1987) Plast. Rubb. Proc. Appl., 7, p. 3; Allan, P.S., Bevis, M.J., (1990) Comp. Manufac., 2, p. 79; Reis, R.L., Cunha, A.M., (1995) J. Mater. Sci.: Mater. Med., 6, p. 786; Bastioli, C., Belloti, V., Rallis, A., (1994) Rheological Acta, 33, p. 307
Keywords: Anisotropy; Biomaterials; Copolymers; differential scanning calorimetry; Ductility; fracture; Impact performance; Impact testing; Injection molding; Mechanical performance; Melting temperature; morphology; Narrow mold gates; performance; Scanning electron microscopy; Scorim; Scorim process; Starch-based polymers; Starched based polymers; Stiffness; Tensile testing

Electrochemical and surface modifications on N +-ion implanted Ti-6A1-4V immersed in HBSS - Leitão, E.; Sa, C.; Silva, R.A.; Barbosa, M.A.; Ali, H. (Corrosion ScienceCorros. Sci., 1995)
The effect of nitrogen-ion implantation on the electrochemical behaviour of Ti-6Al-4V in a simulated physiological solution (HBSS-Hank's balanced salt solution) was studied by open-circuit potential versus time and cyclic polarization techniques, with the aim of characterizing better the surface prior to biological testing and to choose the most appropriate nitrogen-ion fluence. Three fluences (10 15, 10 16 and 10 17 ions/cm 2) were used. The 10 16 ions/cm 2 N + fluence produced the lowest corrosion rate under passive conditions. The highest fluence originated a large increase in the corrosion rate and inhibited the formation of a calcium- and phosphate-rich layer on the electrode surface. © 1995.
Cited By (since 1996): 37Export Date: 21 November 2012Source: ScopusCODEN: CRRSALanguage of Original Document: EnglishCorrespondence Address: Leitão, E.; INEB-Instituto de Engenharia Biomédica, Praca do Coronel Pacheco, 1, 4050 Porto, Portugal
Keywords: Biological testing; Characterization; Corrosion; Corrosion rate; Cyclic polarization technique; Electrochemical behaviour; electrochemistry; Hank balanced salt solution; Ion implantation; materials testing; Nitrogen ion implanted titanium aluminum vanadium alloy; Nitrogen-ion fluence; Open circuit potential; Passivation; Polarization; Simulated physiological solution; Solutions; Surface modification; Surface treatment; Titanium alloys

Stainless steel corrosion products cause alterations on mouse spleen cellular populations - Tracana, R.B.; Pereira, M.L.; Abreu, A.M.; Sousa, J.P.; Carvalho, G.S. (Journal of Materials Science: Materials in MedicineJ. MATER. SCI. MATER. MED., 1995)
Stainless steel is a metallic biomaterial commonly used in orthopaedic surgery. In this study we looked at the effects of stainless steel corrosion products on spleen, in order to evaluate their potential immunotoxicological effects. For this purpose stainless steel, type AISI 316L, was electrochemically dissolved in a physiological salt solution. The final solution, containing 490 μg/ml Fe, 224 μg/ml Cr and 150 μg/ml Ni, was injected subcutaneously in mice. After several periods of time (4, 10 and 14 days) spleens were removed and analysed for: (a) their contents in Fe, Cr and Ni, (b) histological alterations, (c) enumeration of cellular populations. Results showed that stainless steel corrosion products accumulated in spleen, caused histological alterations, and induced changes in cellular populations. When compared to chromium and nickel, iron was the metal ion preferentially accumulated in spleen. The increase of the multinucleated giant cell population was accompanied by depletion of lymphocyte populations. This study indicates that stainless steel corrosion products can spread systemically and accumulate in spleen inducing histological and cellular alterations which may give rise to immunotoxicological consequences.Stainless steel is a metallic biomaterial commonly used in orthopaedic surgery. In this study we looked at the effects of stainless steel corrosion products on spleen, in order to evaluate their potential immunotoxicological effects. For this purpose stainless steel, type AISI 316L, was electrochemically dissolved in a physiological salt solution. The final solution, containing 490 μg/ml Fe, 224 μg/ml Cr and 150 μg/ml Ni, was injected subcutaneously in mice. After several periods of time (4, 10 and 14 days) spleens were removed and analysed for: (a) their contents in Fe, Cr and Ni, (b) histological alterations, (c) enumeration of cellular populations. Results showed that stainless steel corrosion products accumulated in spleen, caused histological alterations, and induced changes in cellular populations. When compared to chromium and nickel, iron was the metal ion preferentially accumulated in spleen. The increase of the multinucleated giant cell population was accompanied by depletion of lymphocyte populations. This study indicates that stainless steel corrosion products can spread systematically and accumulate in spleen inducing histological and cellular alterations which may give rise to immunotoxicological consequences.
Cited By (since 1996): 19Export Date: 21 November 2012Source: ScopusCODEN: JSMMEdoi: 10.1007/BF00121249Language of Original Document: EnglishCorrespondence Address: Tracana, R.B.; Natl. Inst. Biomedical Engineering, INEB, Praca Coronel Pacheco 1, 4000 Porto, Portugal
Keywords: animal cell; animal experiment; animal tissue; Animalia; article; Biocompatibility; biomaterial; cell population; Cells; Chromium; Chronoamperometry; controlled study; Corrosion; Corrosion products; Dissolution; electrochemistry; giant cell; histology; immunology; immunotoxicity; Immunotoxicological effects; Ions; Iron; Lymphocyte; lymphocyte subpopulation; male; mouse; Nickel; nonhuman; orthopedic surgery; priority journal; sodium chloride; Spleen; spleen cell; Stainless steel; Steel corrosion; subcutaneous drug administration; toxicity